Quantitative proteomic analysis of Sulfolobus solfataricus membrane proteins. - Pham, T. K.; Sierocinski, P.; van der Oost, J.; Wright, P. C. (J Proteome Res, 2010)
A quantitative proteomic analysis of the membrane of the archaeon Sulfolobus solfataricus P2 using iTRAQ was successfully demonstrated in this technical note. The estimated number of membrane proteins of this organism is 883 (predicted based on Gravy score), corresponding to 30% of the total number of proteins. Using a modified iTRAQ protocol for membrane protein analysis, of the 284 proteins detected, 246 proteins were identified as membrane proteins, while using an original iTRAQ protocol, 147 proteins were detected with only 133 proteins being identified as membrane proteins. Furthermore, 97.2% of proteins identified in the modified protocol contained more than 2 distinct peptides compared to the original workflow. The successful application of this modified protocol offers a potential technique for quantitatively analyzing membrane-associated proteomes of organisms in the archaeal kingdom. The combination of 3 different iTRAQ experiments resulted in the detection of 395 proteins (>or=2 distinct peptides) of which 373 had predicted membrane properties. Approximately 20% of the quantified proteins were observed to exhibit >or=1.5-fold differential expression at temperatures well below the optimum for growth.
Keywords: Archaeal Proteins/*chemistry; Membrane Proteins/*chemistry; *Proteomics; Sulfolobus solfataricus/*chemistry

Genome-scale reconstruction and analysis of the Pseudomonas putida KT2440 metabolic network facilitates applications in biotechnology. - Puchalka, J.; Oberhardt, M. A.; Godinho, M.; Bielecka, A.; Regenhardt, D.; Timmis, K. N.; Papin, J. A.; Martins dos Santos, V. A. (PLoS Comput Biol, 2008)
A cornerstone of biotechnology is the use of microorganisms for the efficient production of chemicals and the elimination of harmful waste. Pseudomonas putida is an archetype of such microbes due to its metabolic versatility, stress resistance, amenability to genetic modifications, and vast potential for environmental and industrial applications. To address both the elucidation of the metabolic wiring in P. putida and its uses in biocatalysis, in particular for the production of non-growth-related biochemicals, we developed and present here a genome-scale constraint-based model of the metabolism of P. putida KT2440. Network reconstruction and flux balance analysis (FBA) enabled definition of the structure of the metabolic network, identification of knowledge gaps, and pin-pointing of essential metabolic functions, facilitating thereby the refinement of gene annotations. FBA and flux variability analysis were used to analyze the properties, potential, and limits of the model. These analyses allowed identification, under various conditions, of key features of metabolism such as growth yield, resource distribution, network robustness, and gene essentiality. The model was validated with data from continuous cell cultures, high-throughput phenotyping data, (13)C-measurement of internal flux distributions, and specifically generated knock-out mutants. Auxotrophy was correctly predicted in 75% of the cases. These systematic analyses revealed that the metabolic network structure is the main factor determining the accuracy of predictions, whereas biomass composition has negligible influence. Finally, we drew on the model to devise metabolic engineering strategies to improve production of polyhydroxyalkanoates, a class of biotechnologically useful compounds whose synthesis is not coupled to cell survival. The solidly validated model yields valuable insights into genotype-phenotype relationships and provides a sound framework to explore this versatile bacterium and to capitalize on its vast biotechnological potential.
Keywords: Biocatalysis; Biomass; Biotechnology/*methods; Databases, Genetic; Genome, Bacterial/*physiology; Genomics/methods; Metabolic Networks and Pathways/*physiology; *Models, Biological; Mutagenesis, Site-Directed; Polyhydroxyalkanoates/biosynthesis; Pseudomonas putida/*genetics/growth & development/*metabolism; Systems Biology/methods

Functional analysis of new transporters involved in stress tolerance inPseudomonas putidaDOT-T1E - García, Vanina; Godoy, Patricia; Daniels, Craig; Hurtado, Ana; Ramos, Juan; Segura, Ana (2009)
Pseudomonas putida DOT-T1E is a highly solvent-tolerant strain. Although the main mechanism that confers solvent tolerance to the strain is the TtgGHI efflux pump, a number of other proteins are also involved in the response to toluene. Previous proteomic and transcriptomic analysis carried out in our lab with P. putida DOT-T1E, and the solvent-sensitive strain, P. putida KT2440, revealed several transporters that were induced in the presence of toluene. We prepared five mutants of the corresponding genes in P. putida DOT-T1E and analysed their phenotypes with respect to solvent tolerance, stress endurance and growth with different carbon, nitrogen and sulfur sources. The data clearly demonstrated that two transporters (Ttg2ABC and TtgK) are involved in multidrug resistance and toluene tolerance, whereas another (homologous to PP0219 of P. putida KT2440) is a sulfate/sulfite transporter. No clear function could be assigned to the other two transporters. Of the transporters shown to be involved in toluene tolerance, one (ttg2ABC) belongs to the ATP-Binding Cassette (ABC) family, and is involved in multidrug resistance in P. putida DOT-T1E, while the other belongs to the Major Facilitator Superfamily and exhibits homology to a putative transporter of the Bcr/CflA family that has not previously been reported to be involved in toluene tolerance.

Identification and characterization of the PhhR regulon inPseudomonas putida - Herrera, M. Carmen; Duque, Estrella; RodrÃguez-Herva, JosÃ© J.; FernÃ¡ndez-Escamilla, Ana M.; Ramos, Juan (2010)
Pseudomonas putida is a soil microorganism that utilizes aromatic amino acids present in root exudates as a nitrogen source. We have previously shown that the PhhR transcriptional regulator induces phhAB genes encoding a phenylalanine hydroxylase. In this study we show, using microarray assays and promoter fusions, that PhhR is a global regulator responsible for the activation of genes essential for phenylalanine degradation, phenylalanine homeostasis and other genes of unknown function. Recently, it has been shown that phenylalanine catabolism occurs through more than one pathway. One of these possible pathways involves the metabolism of phenylalanine via tyrosine, p-hydroxyphenylpyruvate, and homogentisate. We identified two genes within this pathway that encode an acyl-CoA transferase involved in the metabolism of acetoacetate. All genes in this pathway were induced in response to phenylalanine in a PhhR-proficient background. The second potential degradative pathway involves the degradation of phenylalanine to produce phenylpyruvate, which seems to be degraded via phenylacetyl-CoA. A number of mutants in the paa genes encoding phenylacetyl-CoA degradation enzymes fail to grow on phenylpyruvate or phenylacetate, further supporting the existence of this second pathway. We found that the PhhR regulon also includes genes involved in the biosynthesis of aromatic amino acids that are repressed in the presence of phenylalanine, suggesting the possibility of feedback at the transcriptional level. In addition, we found that PhhR modulates the level of expression of the broad-substrate-specificity MexEF/OprN efflux pump. Expression from this pump is under the control of mexT gene product because phenylalanine-dependent transcription from the mexE promoter does not occur in a mexT mutant background. These results place PhhR as an important regulator in the control of bacterial responses to aromatic amino acids.

Metabolic modeling and analysis of the metabolic switch in Streptomyces coelicolor - Alam, M. Tauqeer; Merlo, Maria Elena; (stream), The STREAM Consortium; Hodgson, David; Wellington, Elizabeth; Takano, Eriko; Breitling, Rainer (BMC Genomics, 2010)
Background The transition from exponential to stationary phase in Streptomyces coelicolor is accompanied by a major metabolic switch and results in a strong activation of secondary metabolism. Here we have explored the underlying reorganization of the metabolome by combining computational predictions based on constraint-based modeling and detailed transcriptomics time course observations. Results We reconstructed the stoichiometric matrix of S. coelicolor, including the major antibiotic biosynthesis pathways, and performed flux balance analysis to predict flux changes that occur when the cell switches from biomass to antibiotic production. We defined the model input based on observed fermenter culture data and used a dynamically varying objective function to represent the metabolic switch. The predicted fluxes of many genes show highly significant correlation to the time series of the corresponding gene expression data. Individual mispredictions identify novel links between antibiotic production and primary metabolism. Conclusion Our results show the usefulness of constraint-based modeling for providing a detailed interpretation of time course gene expression data. Other Sections▼

The dynamic architecture of the metabolic switch in Streptomyces coelicolor. - Nieselt, K.; Battke, F.; Herbig, A.; Bruheim, P.; Wentzel, A.; Jakobsen, O. M.; Sletta, H.; Alam, M. T.; Merlo, M. E.; Moore, J.; Omara, W. A.; Morrissey, E. R.; et al. (BMC Genomics, 2010)
BACKGROUND: During the lifetime of a fermenter culture, the soil bacterium S. coelicolor undergoes a major metabolic switch from exponential growth to antibiotic production. We have studied gene expression patterns during this switch, using a specifically designed Affymetrix genechip and a high-resolution time-series of fermenter-grown samples. RESULTS: Surprisingly, we find that the metabolic switch actually consists of multiple finely orchestrated switching events. Strongly coherent clusters of genes show drastic changes in gene expression already many hours before the classically defined transition phase where the switch from primary to secondary metabolism was expected. The main switch in gene expression takes only 2 hours, and changes in antibiotic biosynthesis genes are delayed relative to the metabolic rearrangements. Furthermore, global variation in morphogenesis genes indicates an involvement of cell differentiation pathways in the decision phase leading up to the commitment to antibiotic biosynthesis. CONCLUSIONS: Our study provides the first detailed insights into the complex sequence of early regulatory events during and preceding the major metabolic switch in S. coelicolor, which will form the starting point for future attempts at engineering antibiotic production in a biotechnological setting.
Keywords: Anti-Bacterial Agents/biosynthesis; Cluster Analysis; Fermentation; *Gene Expression Profiling; Gene Expression Regulation, Bacterial; Genes, Bacterial; Multigene Family; RNA, Bacterial/genetics; Streptomyces coelicolor/*genetics/growth & development/*metabolism

A bistable gene switch for antibiotic biosynthesis: the butyrolactone regulon in Streptomyces coelicolor. - Mehra, S.; Charaniya, S.; Takano, E.; Hu, W. S. (PLoS One, 2008)
Many microorganisms, including bacteria of the class Streptomycetes, produce various secondary metabolites including antibiotics to gain a competitive advantage in their natural habitat. The production of these compounds is highly coordinated in a population to expedite accumulation to an effective concentration. Furthermore, as antibiotics are often toxic even to their producers, a coordinated production allows microbes to first arm themselves with a defense mechanism to resist their own antibiotics before production commences. One possible mechanism of coordination among individuals is through the production of signaling molecules. The gamma-butyrolactone system in Streptomyces coelicolor is a model of such a signaling system for secondary metabolite production. The accumulation of these signaling molecules triggers antibiotic production in the population. A pair of repressor-amplifier proteins encoded by scbA and scbR mediates the production and action of one particular gamma-butyrolactone, SCB1. Based on the proposed interactions of scbA and scbR, a mathematical model was constructed and used to explore the ability of this system to act as a robust genetic switch. Stability analysis shows that the butyrolactone system exhibits bistability and, in response to a threshold SCB1 concentration, can switch from an OFF state to an ON state corresponding to the activation of genes in the cryptic type I polyketide synthase gene cluster, which are responsible for production of the hypothetical polyketide. The switching time is inversely related to the inducer concentration above the threshold, such that short pulses of low inducer concentration cannot switch on the system, suggesting its possible role in noise filtering. In contrast, secondary metabolite production can be triggered rapidly in a population of cells producing the butyrolactone signal due to the presence of an amplification loop in the system. S. coelicolor was perturbed experimentally by varying concentrations of SCB1, and the model simulations match the experimental data well. Deciphering the complexity of this butyrolactone switch will provide valuable insights into how robust and efficient systems can be designed using "simple" two-protein networks.
Keywords: 4-Butyrolactone/*chemistry; Anti-Bacterial Agents/*chemistry; Bacterial Physiological Phenomena; Bacterial Proteins/genetics; Biochemistry/methods; Computer Simulation; *Gene Expression Regulation, Bacterial; Genes, Bacterial; Models, Genetic; Models, Theoretical; Regulon; Streptomyces coelicolor/*genetics; Time Factors

Chapter 6. Regulation of antibiotic production by bacterial hormones. - Hsiao, N. H.; Gottelt, M.; Takano, E. (Methods Enzymol, 2009)
Antibiotic production is regulated by numerous signals, including the so-called bacterial hormones found in antibiotic producing organisms such as Streptomyces. These signals, the gamma-butyrolactones, are produced in very small quantities, which has hindered their structural elucidation and made it difficult to assess whether they are being produced. In this chapter, we describe a rapid small-scale extraction method from either solid or liquid cultures in scales of one plate or 50 ml of medium. Also described is a bioassay to detect the gamma-butyrolactones by determining either the production of pigmented antibiotic of Streptomyces coelicolor or kanamycin resistant growth on addition of the gamma-butyrolactones. We also describe some insights into the identification of the gamma-butyrolactone receptor and its targets and also the gel retardation conditions with three differently labeled probes.
Keywords: 4-Butyrolactone/*biosynthesis/pharmacology; Electrophoretic Mobility Shift Assay; Gene Expression Regulation, Bacterial/drug effects/genetics; Kanamycin/pharmacology; Receptors, GABA-A/genetics/metabolism; Streptomyces/drug effects/genetics/*metabolism

New surveyor tools for charting microbial metabolic maps. - Breitling, R.; Vitkup, D.; Barrett, M. P. (Nat Rev Microbiol, 2008)
The computational reconstruction and analysis of cellular models of microbial metabolism is one of the great success stories of systems biology. The extent and quality of metabolic network reconstructions is, however, limited by the current state of biochemical knowledge. Can experimental high-throughput data be used to improve and expand network reconstructions to include unexplored areas of metabolism? Recent advances in experimental technology and analytical methods bring this aim an important step closer to realization. Data integration will play a particularly important part in exploiting the new experimental opportunities.
Keywords: Animals; Arabidopsis/metabolism; Computational Biology/*methods; *Genomics; Gram-Negative Bacteria/*metabolism; Mass Spectrometry/*methods; *Metabolic Networks and Pathways; Methanosarcina/*metabolism; Trypanosoma/*metabolism

MetaNetter: inference and visualization of high-resolution metabolomic networks. - Jourdan, F.; Breitling, R.; Barrett, M. P.; Gilbert, D. (Bioinformatics, 2008)
SUMMARY: We present a Cytoscape plugin for the inference and visualization of networks from high-resolution mass spectrometry metabolomic data. The software also provides access to basic topological analysis. This open source, multi-platform software has been successfully used to interpret metabolomic experiments and will enable others using filtered, high mass accuracy mass spectrometric data sets to build and analyse networks. AVAILABILITY: http://compbio.dcs.gla.ac.uk/fabien/abinitio/abinitio.html
Keywords: Computer Simulation; Gene Expression Profiling/*methods; *Models, Biological; Protein Interaction Mapping/*methods; Proteome/*metabolism; Reproducibility of Results; Sensitivity and Specificity; Signal Transduction/*physiology; *Software; *User-Computer Interface

Probabilistic assignment of formulas to mass peaks in metabolomics experiments. - Rogers, S.; Scheltema, R. A.; Girolami, M.; Breitling, R. (Bioinformatics, 2009)
MOTIVATION: High-accuracy mass spectrometry is a popular technology for high-throughput measurements of cellular metabolites (metabolomics). One of the major challenges is the correct identification of the observed mass peaks, including the assignment of their empirical formula, based on the measured mass. RESULTS: We propose a novel probabilistic method for the assignment of empirical formulas to mass peaks in high-throughput metabolomics mass spectrometry measurements. The method incorporates information about possible biochemical transformations between the empirical formulas to assign higher probability to formulas that could be created from other metabolites in the sample. In a series of experiments, we show that the method performs well and provides greater insight than assignments based on mass alone. In addition, we extend the model to incorporate isotope information to achieve even more reliable formula identification. AVAILABILITY: A supplementary document, Matlab code, data and further information are available from http://www.dcs.gla.ac.uk/inference/metsamp.
Keywords: Computer Simulation; Mass Spectrometry/*methods; Metabolomics/*methods; Proteome/metabolism

Increasing the mass accuracy of high-resolution LC-MS data using background ions: a case study on the LTQ-Orbitrap. - Scheltema, R. A.; Kamleh, A.; Wildridge, D.; Ebikeme, C.; Watson, D. G.; Barrett, M. P.; Jansen, R. C.; Breitling, R. (Proteomics, 2008)
With the advent of a new generation of high-resolution mass spectrometers, the fields of proteomics and metabolomics have gained powerful new tools. In this paper, we demonstrate a novel computational method that improves the mass accuracy of the LTQ-Orbitrap mass spectrometer from an initial +/- 1-2 ppm, obtained by the standard software, to an absolute median of 0.21 ppm (SD 0.21 ppm). With the increased mass accuracy it becomes much easier to match mass chromatograms in replicates and different sample types, even if compounds are detected at very low intensities. The proposed method exploits the ubiquitous presence of background ions in LC-MS profiles for accurate alignment and internal mass calibration, making it applicable for all types of MS equipment. The accuracy of this approach will facilitate many downstream systems biology applications, including mass-based molecule identification, ab initio metabolic network reconstruction, and untargeted metabolomics in general.
Keywords: Chromatography, Liquid/*methods; Computational Biology/*methods; Ions; Mass Spectrometry/*methods; Metabolome; Metabolomics/*methods; Proteome; Proteomics/*methods; Sensitivity and Specificity; Software

Phosphate-dependent regulation of the low- and high-affinity transport systems in the model actinomycete Streptomyces coelicolor. - Santos-Beneit, F.; Rodriguez-Garcia, A.; Franco-Dominguez, E.; Martin, J. F. (Microbiology (Reading), 2008)
The transport of inorganic phosphate (P(i)) is essential for the growth of all organisms. The metabolism of soil-dwelling Streptomyces species, and their ability to produce antibiotics and other secondary metabolites, are strongly influenced by the availability of phosphate. The transcriptional regulation of the SCO4138 and SCO1845 genes of Streptomyces coelicolor was studied. These genes encode the two putative low-affinity P(i) transporters PitH1 and PitH2, respectively. Expression of these genes and that of the high-affinity transport system pstSCAB follows a sequential pattern in response to phosphate deprivation, as shown by coupling their promoters to a luciferase reporter gene. Expression of pitH2, but not that of pap-pitH1 (a bicistronic transcript), is dependent upon the response regulator PhoP. PhoP binds to specific sequences consisting of direct repeats of 11 nt in the promoter of pitH2, but does not bind to the pap-pitH1 promoter, which lacks these direct repeats for PhoP recognition. The transcription start point of the pitH2 promoter was identified by primer extension analyses, and the structure of the regulatory sequences in the PhoP-protected DNA region was established. It consists of four central direct repeats flanked by two other less conserved repeats. A model for PhoP regulation of this promoter is proposed based on the four promoter DNA-PhoP complexes detected by electrophoretic mobility shift assays and footprinting studies.
Keywords: Bacterial Proteins/genetics/*metabolism; Base Sequence; Binding Sites; Biological Transport; *Gene Expression Regulation, Bacterial; Molecular Sequence Data; Phosphate Transport Proteins/genetics/*metabolism; Phosphates/*metabolism; Promoter Regions, Genetic; Streptomyces coelicolor/genetics/*metabolism; Transcription, Genetic

Phosphate control over nitrogen metabolism in Streptomyces coelicolor: direct and indirect negative control of glnR, glnA, glnII and amtB expression by the response regulator PhoP. - Rodriguez-Garcia, A.; Sola-Landa, A.; Apel, K.; Santos-Beneit, F.; Martin, J. F. (Nucleic Acids Res, 2009)
Bacterial growth requires equilibrated concentration of C, N and P sources. This work shows a phosphate control over the nitrogen metabolism in the model actinomycete Streptomyces coelicolor. Phosphate control of metabolism in Streptomyces is exerted by the two component system PhoR-PhoP. The response regulator PhoP binds to well-known PHO boxes composed of direct repeat units (DRus). PhoP binds to the glnR promoter, encoding the major nitrogen regulator as shown by EMSA studies, but not to the glnRII promoter under identical experimental conditions. PhoP also binds to the promoters of glnA and glnII encoding two glutamine synthetases, and to the promoter of the amtB-glnK-glnD operon, encoding an ammonium transporter and two putative nitrogen sensing/regulatory proteins. Footprinting analyses revealed that the PhoP-binding sequence overlaps the GlnR boxes in both glnA and glnII. 'Information theory' quantitative analyses of base conservation allowed us to establish the structure of the PhoP-binding regions in the glnR, glnA, glnII and amtB genes. Expression studies using luxAB as reporter showed that PhoP represses the above mentioned nitrogen metabolism genes. A mutant deleted in PhoP showed increased expression of the nitrogen metabolism genes. The possible conservation of phosphate control over nitrogen metabolism in other microorganisms is discussed.
Keywords: Bacterial Proteins/genetics/*metabolism; Binding Sites; Cation Transport Proteins/genetics; *Gene Expression Regulation, Bacterial; Glutamate-Ammonia Ligase/genetics; Nitrogen/*metabolism; Operator Regions, Genetic; Operon; Phosphates/metabolism; Promoter Regions, Genetic; Repressor Proteins/*metabolism; Streptomyces coelicolor/*genetics/*metabolism; Trans-Activators/genetics/metabolism; Transcription, Genetic

The roles of the nitrate reductase NarGHJI, the nitrite reductase NirBD and the response regulator GlnR in nitrate assimilation of Mycobacterium tuberculosis. - Malm, S.; Tiffert, Y.; Micklinghoff, J.; Schultze, S.; Joost, I.; Weber, I.; Horst, S.; Ackermann, B.; Schmidt, M.; Wohlleben, W.; Ehlers, S.; Geffers, R.; et al. (Microbiology (Reading), 2009)
Mycobacterium tuberculosis can utilize various nutrients including nitrate as a source of nitrogen. Assimilation of nitrate requires the reduction of nitrate via nitrite to ammonium, which is then incorporated into metabolic pathways. This study was undertaken to define the molecular mechanism of nitrate assimilation in M. tuberculosis. Homologues to a narGHJI-encoded nitrate reductase and a nirBD-encoded nitrite reductase have been found on the chromosome of M. tuberculosis. Previous studies have implied a role for NarGHJI in nitrate respiration rather than nitrate assimilation. Here, we show that a narG mutant of M. tuberculosis failed to grow on nitrate. A nirB mutant of M. tuberculosis failed to grow on both nitrate and nitrite. Mutant strains of Mycobacterium smegmatis mc(2)155 that are unable to grow on nitrate were isolated. The mutants were rescued by screening a cosmid library from M. tuberculosis, and a gene with homology to the response regulator gene glnR of Streptomyces coelicolor was identified. A DeltaglnR mutant of M. tuberculosis was generated, which also failed to grow on nitrate, but regained its ability to utilize nitrate when nirBD was expressed from a plasmid, suggesting a role of GlnR in regulating nirBD expression. A specific binding site for GlnR within the nirB promoter was identified and confirmed by electrophoretic mobility shift assay using purified recombinant GlnR. Semiquantitative reverse transcription PCR, as well as microarray analysis, demonstrated upregulation of nirBD expression in response to GlnR under nitrogen-limiting conditions. In summary, we conclude that NarGHJI and NirBD of M. tuberculosis mediate the assimilatory reduction of nitrate and nitrite, respectively, and that GlnR acts as a transcriptional activator of nirBD.
Keywords: Bacterial Proteins/genetics/*metabolism; Culture Media; *Gene Expression Regulation, Bacterial; Humans; Molecular Sequence Data; Mutation; Mycobacterium tuberculosis/enzymology/genetics/*growth & development; Nitrate Reductase/genetics/*metabolism; Nitrates/*metabolism; Nitrite Reductases/genetics/*metabolism; Nitrites/metabolism; Oligonucleotide Array Sequence Analysis; Reverse Transcriptase Polymerase Chain Reaction; Sequence Analysis, DNA

The Streptomyces coelicolor GlnR regulon: identification of new GlnR targets and evidence for a central role of GlnR in nitrogen metabolism in actinomycetes. - Tiffert, Y.; Supra, P.; Wurm, R.; Wohlleben, W.; Wagner, R.; Reuther, J. (Mol Microbiol, 2008)
Streptomyces coelicolor GlnR is a global regulator that controls genes involved in nitrogen metabolism. By genomic screening 10 new GlnR targets were identified, including enzymes for ammonium assimilation (glnII, gdhA), nitrite reduction (nirB), urea cleavage (ureA) and a number of biochemically uncharacterized proteins (SCO0255, SCO0888, SCO2195, SCO2400, SCO2404, SCO7155). For the GlnR regulon, a GlnR binding site which comprises the sequence gTnAc-n(6)-GaAAc-n(6)-GtnAC-n(6)-GAAAc-n(6) has been found. Reverse transcription analysis of S. coelicolor and the S. coelicolor glnR mutant revealed that GlnR activates or represses the expression of its target genes. Furthermore, glnR expression itself was shown to be nitrogen-dependent. Physiological studies of S. coelicolor and the S. coelicolor glnR mutant with ammonium and nitrate as the sole nitrogen source revealed that GlnR is not only involved in ammonium assimilation but also in ammonium supply. blast analysis demonstrated that GlnR-homologous proteins are present in different actinomycetes containing the glnA gene with the conserved GlnR binding site. By DNA binding studies, it was furthermore demonstrated that S. coelicolor GlnR is able to interact with these glnA upstream regions. We therefore suggest that GlnR-mediated regulation is not restricted to Streptomyces but constitutes a regulon conserved in many actinomycetes.
Keywords: Amino Acid Sequence; Bacterial Proteins/genetics/*metabolism; Base Sequence; DNA-Binding Proteins/genetics/*metabolism; Gene Expression Regulation, Bacterial; Genes, Bacterial; Molecular Sequence Data; Nitrogen/*metabolism; Regulon/*genetics; Streptomyces coelicolor/genetics/*metabolism; Trans-Activators/genetics/*metabolism

Antibiotic resistance in the environment, with particular reference to MRSA. - Gaze, W.; O'Neill, C.; Wellington, E.; Hawkey, P. (Adv Appl Microbiol, 2008)
Keywords: Animals; Animals, Domestic/microbiology; Cattle; Dogs; Drug Resistance, Bacterial/*genetics; *Environmental Microbiology; *Gene Transfer, Horizontal; Humans; Methicillin Resistance/*genetics; Sewage/microbiology; Soil Microbiology; Staphylococcal Infections/microbiology; Staphylococcus aureus/*drug effects/genetics

Prevalence of sulfonamide resistance genes in bacterial isolates from manured agricultural soils and pig slurry in the United Kingdom. - Byrne-Bailey, K. G.; Gaze, W. H.; Kay, P.; Boxall, A. B.; Hawkey, P. M.; Wellington, E. M. (Antimicrob Agents Chemother, 2009)
The prevalences of three sulfonamide resistance genes, sul1, sul2, and sul3 and sulfachloropyridazine (SCP) resistance were determined in bacteria isolated from manured agricultural clay soils and slurry samples in the United Kingdom over a 2-year period. Slurry from tylosin-fed pigs amended with SCP and oxytetracycline was used for manuring. Isolates positive for sul genes were further screened for the presence of class 1 and 2 integrons. Phenotypic resistance to SCP was significantly higher in isolates from pig slurry and postapplication soil than in those from preapplication soil. Of 531 isolates, 23% carried sul1, 18% sul2, and 9% sul3 only. Two percent of isolates contained all three sul genes. Class 1 and class 2 integrons were identified in 5% and 11.7%, respectively, of sul-positive isolates. In previous reports, sul1 was linked to class 1 integrons, but in this study only 8% of sul1-positive isolates carried the intI1 gene. Sulfonamide-resistant pathogens, including Shigella flexneri, Aerococcus spp., and Acinetobacter baumannii, were identified in slurry-amended soil and soil leachate, suggesting a potential environmental reservoir. Sulfonamide resistance in Psychrobacter, Enterococcus, and Bacillus spp. is reported for the first time, and this study also provides the first description of the genotypes sul1, sul2, and sul3 outside the Enterobacteriaceae and in the soil environment.
Keywords: Animals; Anti-Bacterial Agents/*pharmacology; Colony Count, Microbial; Conjugation, Genetic; DNA, Bacterial/genetics/isolation & purification; Drug Resistance, Bacterial/*genetics; Integrons/genetics; Manure/*microbiology; Microbial Sensitivity Tests; Oxytetracycline/pharmacology; RNA, Ribosomal/genetics; Sewage/*microbiology; *Soil Microbiology; Sulfonamides/*pharmacology; Swine; Tylosin/pharmacology; United Kingdom

An approach to pathway reconstruction using whole genome metabolic models and sensitive sequence searching. - Saqi, M.; Dobson, R. J.; Kraben, P.; Hodgson, D. A.; Wild, D. L. (J Integr Bioinform, 2009)
Metabolic models have the potential to impact on genome annotation and on the interpretation of gene expression and other high throughput genome data. The genome of Streptomyces coelicolor genome has been sequenced and some 30% of the open reading frames (ORFs) lack any functional annotation. A recently constructed metabolic network model for S. coelicolor highlights biochemical functions which should exist to make the metabolic model complete and consistent. These include 205 reactions for which no ORF is associated. Here we combine protein functional predictions for the unannotated open reading frames in the genome with \'missing but expected\' functions inferred from the metabolic model. The approach allows function predictions to be evaluated in the context of the biochemical pathway reconstruction, and feed back iteratively into the metabolic model. We describe the approach and discuss a few illustrative examples.
Keywords: Amino Acid Sequence; Bacterial Proteins/genetics/metabolism; Computational Biology/*methods; *Genome, Fungal; Metabolic Networks and Pathways/*genetics; Molecular Sequence Data; Open Reading Frames; Streptomyces coelicolor/*genetics/metabolism

Annotation and merging of SBML models with semanticSBML. - Krause, F.; Uhlendorf, J.; Lubitz, T.; Schulz, M.; Klipp, E.; Liebermeister, W. (Bioinformatics, 2010)
SUMMARY: Systems Biology Markup Language (SBML) is the leading exchange format for mathematical models in Systems Biology. Semantic annotations link model elements with external knowledge via unique database identifiers and ontology terms, enabling software to check and process models by their biochemical meaning. Such information is essential for model merging, one of the key steps towards the construction of large kinetic models. SemanticSBML is a tool that helps users to check and edit MIRIAM annotations and SBO terms in SBML models. Using a large collection of biochemical names and database identifiers, it supports modellers in finding the right annotations and in merging existing models. Initially, an element matching is derived from the MIRIAM annotations and conflicting element attributes are categorized and highlighted. Conflicts can then be resolved automatically or manually, allowing the user to control the merging process in detail. AVAILABILITY: SemanticSBML comes as a free software written in Python and released under the GPL 3. A Debian package, a source package for other Linux distributions, a Windows installer and an online version of semanticSBML with limited functionality are available at http://www.semanticsbml.org. A preinstalled version can be found on the Linux live DVD SB.OS, available at http://www.sbos.eu. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Computational Biology/*methods; Database Management Systems; Databases, Factual; Semantics; *Software; Systems Biology/*methods

Lack of main K+ uptake systems in Saccharomyces cerevisiae cells affects yeast performance in both potassium-sufficient and potassium-limiting conditions. - Navarrete, C.; Petrezselyova, S.; Barreto, L.; Martinez, J. L.; Zahradka, J.; Arino, J.; Sychrova, H.; Ramos, J. (FEMS Yeast Res, 2010)
A new YNB medium containing very low concentrations of alkali metal cations has been developed to carry out experiments to study potassium homoeostasis. Physiological characterization of Saccharomyces cerevisiae BY4741 strain and the corresponding mutant lacking the main potassium uptake systems (trk1 trk2) under potassium nonlimiting and limiting concentrations was performed, and novel important differences between both strains were found. At nonlimiting concentrations of KCl, the two strains had a comparable cell size and potassium content. Nevertheless, mutants were hyperpolarized, had lower pH and extruded fewer protons compared with the BY4741 strain. Upon transfer to K(+)-limiting conditions, cells of both strains became hyperpolarized and their cell volume and K(+) content diminished; however, the decrease was more relevant in BY4741. In low potassium, trk1 trk2 cells were not able to accomplish the cell cycle to the same extent as in BY4741. Moreover, K(+) limitation triggered a high-affinity K(+)/Rb(+) uptake process only in BY4741, with the highest affinity being reached as soon as 30 min after transfer to potassium-limiting conditions. By establishing basic cellular parameters under standard growth conditions, this work aims to establish a basis for the investigation of potassium homoeostasis at the system level.
Keywords: Cation Transport Proteins/genetics/*metabolism; Cell Cycle; Cell Membrane/physiology; Culture Media/chemistry; Cytoplasm/chemistry; *Gene Deletion; Hydrogen-Ion Concentration; Membrane Potentials/physiology; Potassium/*metabolism; Rubidium/metabolism; Saccharomyces cerevisiae/cytology/genetics/metabolism/*physiology; Saccharomyces cerevisiae Proteins/genetics/*metabolism

Regulation of Trk-dependent potassium transport by the calcineurin pathway involves the Hal5 kinase. - Casado, C.; Yenush, L.; Melero, C.; Ruiz Mdel, C.; Serrano, R.; Perez-Valle, J.; Arino, J.; Ramos, J. (FEBS Lett, 2010)
The phosphatase calcineurin and the kinases Hal4/Hal5 regulate high-affinity potassium uptake in Saccharomyces cerevisiae through the Trk1 transporter. We demonstrate that calcineurin is necessary for high-affinity potassium uptake even in the absence of Na(+) stress. HAL5 expression is induced in response to stress in a calcineurin-dependent manner through a newly identified functional CDRE (nt -195/-189). Lack of calcineurin decreases Hal5 protein levels, although with little effect on Trk1 amounts. However, the growth defect of cnb1 cells at K(+)-limiting conditions can be rescued in part by overexpression of HAL5, and this mutation further aggravates the potassium requirements of a hal4 strain. This suggests that the control exerted by calcineurin on Hal5 expression may be biologically relevant for Trk1 regulation.
Keywords: Biological Transport/genetics; Calcineurin/*metabolism; Ion Transport/genetics; Ions/metabolism; Membrane Transport Proteins/*metabolism; Mutation; Potassium/*metabolism; Protein Kinases/*metabolism; Saccharomyces cerevisiae/*metabolism; Saccharomyces cerevisiae Proteins/*metabolism

Alkali metal cation transport and homeostasis in yeasts. - Arino, J.; Ramos, J.; Sychrova, H. (Microbiol Mol Biol Rev, 2010)
The maintenance of appropriate intracellular concentrations of alkali metal cations, principally K(+) and Na(+), is of utmost importance for living cells, since they determine cell volume, intracellular pH, and potential across the plasma membrane, among other important cellular parameters. Yeasts have developed a number of strategies to adapt to large variations in the concentrations of these cations in the environment, basically by controlling transport processes. Plasma membrane high-affinity K(+) transporters allow intracellular accumulation of this cation even when it is scarce in the environment. Exposure to high concentrations of Na(+) can be tolerated due to the existence of an Na(+), K(+)-ATPase and an Na(+), K(+)/H(+)-antiporter, which contribute to the potassium balance as well. Cations can also be sequestered through various antiporters into intracellular organelles, such as the vacuole. Although some uncertainties still persist, the nature of the major structural components responsible for alkali metal cation fluxes across yeast membranes has been defined within the last 20 years. In contrast, the regulatory components and their interactions are, in many cases, still unclear. Conserved signaling pathways (e.g., calcineurin and HOG) are known to participate in the regulation of influx and efflux processes at the plasma membrane level, even though the molecular details are obscure. Similarly, very little is known about the regulation of organellar transport and homeostasis of alkali metal cations. The aim of this review is to provide a comprehensive and up-to-date vision of the mechanisms responsible for alkali metal cation transport and their regulation in the model yeast Saccharomyces cerevisiae and to establish, when possible, comparisons with other yeasts and higher plants.
Keywords: Adenosine Triphosphatases/metabolism; *Homeostasis; Ion Transport; Metals, Alkali/*metabolism; Plants/metabolism; Signal Transduction; Yeasts/*physiology

Graphical analysis and experimental evaluation of Saccharomyces cerevisiae PTRK1|2 and PBMH1|2 promoter region. - Gerber, S.; Hasenbrink, G.; Hendriksen, W.; Van Heusden, P.; Ludwig, J.; Klipp, E.; Lichtenberg-Frate, H. (Genome Inform, 2010)
We designed a simple graphical presentation for the results of a transcription factor (TF) pattern matching analysis. The TF analysis algorithm utilized known sequence signature motifs from several databases. The graphical presentation enabled a quick overview of potential TF binding sites, their frequency and spacing on both DNA strands and thus straight forward identification of promising candidates for further experimental investigations. The developed tool was applied on in total four Saccharomyces cerevisiae gene promoter regions. The selected differentially expressed genes belong to functionally different families and encode duplicate functions, TRK1 and TRK2 as ion transporters and BMH1 and BMH2 as multiple regulators. Output evaluation revealed a number of TFs with promising differences in the promoter regions of each gene pair. Experimental investigations were performed by using corresponding TF yeast mutants for either phenotypic analysis of ion transport mediated growth or expression analysis of BMH1,2 genes. Upon phenotypic testing one TF mutant exhibited severely impaired growth under non-permissive conditions. This TF, Mot3p was identified as of most abundant potential binding sites and distinctive patterns among the TRK promoter regions.
Keywords: 14-3-3 Proteins/*genetics/metabolism; Base Sequence; Binding Sites; Cation Transport Proteins/*genetics/metabolism; Computational Biology; Computer Graphics; DNA, Fungal/genetics/metabolism; Gene Expression Regulation, Fungal; Molecular Sequence Data; Mutation/genetics; Phenotype; Promoter Regions, Genetic/*genetics; Saccharomyces cerevisiae/*genetics/metabolism; Saccharomyces cerevisiae Proteins/*genetics/metabolism; Sequence Homology, Nucleic Acid; Transcription Factors/*genetics/metabolism

Ref2, a regulatory subunit of the yeast protein phosphatase 1, is a novel component of cation homoeostasis. - Ferrer-Dalmau, J.; Gonzalez, A.; Platara, M.; Navarrete, C.; Martinez, J. L.; Barreto, L.; Ramos, J.; Arino, J.; Casamayor, A. (Biochem J, 2010)
Maintenance of cation homoeostasis is a key process for any living organism. Specific mutations in Glc7, the essential catalytic subunit of yeast protein phosphatase 1, result in salt and alkaline pH sensitivity, suggesting a role for this protein in cation homoeostasis. We screened a collection of Glc7 regulatory subunit mutants for altered tolerance to diverse cations (sodium, lithium and calcium) and alkaline pH. Among 18 candidates, only deletion of REF2 (RNA end formation 2) yielded increased sensitivity to these conditions, as well as to diverse organic toxic cations. The Ref2F374A mutation, which renders it unable to bind Glc7, did not rescue the salt-related phenotypes of the ref2 strain, suggesting that Ref2 function in cation homoeostasis is mediated by Glc7. The ref2 deletion mutant displays a marked decrease in lithium efflux, which can be explained by the inability of these cells to fully induce the Na+-ATPase ENA1 gene. The effect of lack of Ref2 is additive to that of blockage of the calcineurin pathway and might disrupt multiple mechanisms controlling ENA1 expression. ref2 cells display a striking defect in vacuolar morphogenesis, which probably accounts for the increased calcium levels observed under standard growth conditions and the strong calcium sensitivity of this mutant. Remarkably, the evidence collected indicates that the role of Ref2 in cation homoeostasis may be unrelated to its previously identified function in the formation of mRNA via the APT (for associated with Pta1) complex.
Keywords: Adaptation, Physiological/drug effects; Amino Acid Sequence; Calcineurin/genetics/metabolism; Calcium/metabolism; Calcium Chloride/pharmacology; Cations/*metabolism; *Homeostasis; Hydrogen-Ion Concentration; Ion Transport; Lithium/metabolism; Lithium Chloride/pharmacology; Mutation; Protein Phosphatase 1/genetics/*metabolism; RNA-Binding Proteins/genetics/*metabolism; Saccharomyces cerevisiae/drug effects/genetics/metabolism; Saccharomyces cerevisiae Proteins/genetics/*metabolism; Sodium/metabolism; Sodium Chloride/pharmacology; Sodium-Potassium-Exchanging ATPase/genetics/metabolism

14-3-3 Proteins: insights from genome-wide studies in yeast. - van Heusden, G. P. (Genomics, 2009)
14-3-3 proteins form a family of highly conserved, acidic, dimeric proteins. These proteins have been identified in all eukaryotic species investigated, often in multiple isoforms, up to 13 in the plant Arabidopsis thaliana. Hundreds of proteins, from diverse eukaryotic organisms, implicated in numerous cellular processes, have been identified as binding partners of 14-3-3 proteins. Therefore, the major activity of 14-3-3 proteins seems to be its ability to bind other intracellular proteins. Binding to 14-3-3 proteins may result in a conformational change of the protein required for its full activity or for inhibition of its activity, in interaction between two binding partners or in a different subcellular localization. Most of these interactions take place after phosphorylation of the binding partners. These observations suggest a major role of 14-3-3 proteins in regulatory networks. Here, the information on 14-3-3 proteins gathered from several genome- and proteome-wide studies in the yeast Saccharomyces cerevisiae is reviewed. In particular, the protein kinases responsible for the phosphorylation of 14-3-3 binding partners, phosphorylation of 14-3-3 proteins themselves, the transcriptional regulation of the 14-3-3 genes, and the role of 14-3-3 proteins in transcription are addressed. These large scale studies may help understand the function of 14-3-3 proteins at a cellular level rather than at the level of a single process.
Keywords: *14-3-3 Proteins/chemistry/genetics/metabolism; Amino Acid Sequence; *Gene Expression Regulation, Fungal; Genome, Fungal/genetics; Molecular Sequence Data; Phosphorylation; Saccharomyces cerevisiae/genetics/*metabolism; *Saccharomyces cerevisiae Proteins/chemistry/genetics/metabolism; Transcription, Genetic

Novel components of an active mitochondrial K(+)/H(+) exchange. - Zotova, L.; Aleschko, M.; Sponder, G.; Baumgartner, R.; Reipert, S.; Prinz, M.; Schweyen, R. J.; Nowikovsky, K. (J Biol Chem, 2010)
Defects of the mitochondrial K(+)/H(+) exchanger (KHE) result in increased matrix K(+) content, swelling, and autophagic decay of the organelle. We have previously identified the yeast Mdm38 and its human homologue LETM1, the candidate gene for seizures in Wolf-Hirschhorn syndrome, as essential components of the KHE. In a genome-wide screen for multicopy suppressors of the pet(-) (reduced growth on nonfermentable substrate) phenotype of mdm38Delta mutants, we now characterized the mitochondrial carriers PIC2 and MRS3 as moderate suppressors and MRS7 and YDL183c as strong suppressors. Like Mdm38p, Mrs7p and Ydl183cp are mitochondrial inner membrane proteins and constituents of approximately 500-kDa protein complexes. Triple mutant strains (mdm38Delta mrs7Delta ydl183cDelta) exhibit a remarkably stronger pet(-) phenotype than mdm38Delta and a general growth reduction. They totally lack KHE activity, show a dramatic drop of mitochondrial membrane potential, and heavy fragmentation of mitochondria and vacuoles. Nigericin, an ionophore with KHE activity, fully restores growth of the triple mutant, indicating that loss of KHE activity is the underlying cause of its phenotype. Mdm38p or overexpression of Mrs7p, Ydl183cp, or LETM1 in the triple mutant rescues growth and KHE activity. A LETM1 human homologue, HCCR-1/LETMD1, described as an oncogene, partially suppresses the yeast triple mutant phenotype. Based on these results, we propose that Ydl183p and the Mdm38p homologues Mrs7p, LETM1, and HCCR-1 are involved in the formation of an active KHE system.
Keywords: Chromatography, Affinity; Gene Deletion; Genome, Fungal; Humans; Hydrogen/*metabolism; Immunoprecipitation; Membrane Potential, Mitochondrial; Membrane Proteins/genetics/*metabolism; Mitochondria/*metabolism; Mitochondrial Proteins/genetics/*metabolism; Mutation/genetics; Potassium/*metabolism; Saccharomyces cerevisiae/genetics/*metabolism; Saccharomyces cerevisiae Proteins/genetics/*metabolism; Sodium-Hydrogen Exchangers/*physiology; Suppression, Genetic

SemanticSBML: a tool for annotating, checking, and merging of biochemical models in SBML format - Liebermeister, Wolfram; Krause, Falko; Uhlendorf, Jannis; Lubitz, Timo; Klipp, Edda (Nature Precedings, 2009)
Semantic annotations in SBML (systems biology markup language) enable computer programs to check and process biochemical models based on their biochemical meaning. Annotations are an important prerequisite for model merging, which would be a major step towards the construction of large-scale cell models. The software tool semanticSBML allows users to check and edit MIRIAM annotations and SBO terms, the most common forms of annotation in SBML models. It uses a large collection of biochemical names and database identifiers to support modellers in finding the right annotations. Annotated SBML models can also be built from lists of chemical reactions. In model merging, semanticSBML suggests a preliminary merged model based on MIRIAM annotations in the original models. This model provides a starting point for manually aligning the elements of all input models. To resolve conflicting element properties, conflicts are highlighted and categorised. The user can navigate through the models, change the matching of model elements, check the conflicts between them and decide how they should be resolved. Alternatively, the software can resolve all conflicts automatically, selecting each time the attribute value from the input model with highest priority. URL: http://www.semanticsbml.org/

Saccharomyces cerevisiae BY4741 and W303-1A laboratory strains differ in salt tolerance (Fungal Biology, 2010)
Saccharomyces cerevisiae yeast cells serve as a model to elucidate the bases of salt tolerance and potassium homeostasis regulation in eukaryotic cells. In this study, we show that two widely used laboratory strains, BY4741 and W303-1A, differ not only in cell size and volume but also in their relative plasma-membrane potential (estimated with a potentiometric fluorescent dye diS-C3(3) and as Hygromycin B sensitivity) and tolerance to alkali-metal cations. W303-1A cells and their mutant derivatives lacking either uptake (trk1 trk2) or efflux (nha1) systems for alkali-metal cations are more tolerant to toxic sodium and lithium cations but also more sensitive to higher external concentrations of potassium than BY4741 cells and their mutants. Moreover, our results suggest that though the two strains do not differ in the total potassium content, the regulation of intracellular potassium homeostasis is probably not the same in BY4741 and W303-1A cells.

Storing and annotating of kinetic data. - Rojas, I.; Golebiewski, M.; Kania, R.; Krebs, O.; Mir, S.; Weidemann, A.; Wittig, U. (In Silico Biol, 2007)
This paper briefly describes the SABIO-RK database model for the storage of reaction kinetics information and the guidelines followed within the SABIO-RK project to annotate the kinetic data. Such annotations support the definition of cross links to other related databases and augment the semantics of the data stored in the database.
Keywords: Animals; *Databases, Protein; Enzymes/*chemistry; Humans; Kinetics; *Software; Vocabulary, Controlled

Mathematical modelling of the sporulation-initiation network in Bacillus subtilis revealing the dual role of the putative quorum-sensing signal molecule PhrA. - Jabbari, S.; Heap, J. T.; King, J. R. (Bull Math Biol, 2011)
Bacillus subtilis cells may opt to forgo normal cell division and instead form spores if subjected to certain environmental stimuli, for example nutrient deficiency or extreme temperature. The resulting spores are extremely resilient and can survive for extensive periods of time, importantly under particularly harsh conditions such as those mentioned above. The sporulation process is highly time and energy consuming and essentially irreversible. The bacteria must therefore ensure that this route is only undertaken under appropriate circumstances. The gene regulation network governing sporulation initiation accordingly incorporates a variety of signals and is of significant complexity. We present a model of this network that includes four of these signals: nutrient levels, DNA damage, the products of the competence genes, and cell population size. Our results can be summarised as follows: (i) the model displays the correct phenotypic behaviour in response to these signals; (ii) a basal level of sda expression may prevent sporulation in the presence of nutrients; (iii) sporulation is more likely to occur in a large population of cells than in a small one; (iv) finally, and of most interest, PhrA can act simultaneously as a quorum-sensing signal and as a timing mechanism, delaying sporulation when the cell has damaged DNA, possibly thereby allowing the cell time to repair its DNA before forming a spore.
Keywords: Bacillus subtilis/genetics/growth & development/*physiology; Bacterial Proteins/genetics/physiology; DNA Damage; DNA Repair; DNA, Bacterial/genetics/metabolism; Gene Regulatory Networks; Genes, Bacterial; Mathematical Concepts; *Models, Biological; Quorum Sensing/genetics/*physiology; Signal Transduction; Spores, Bacterial/physiology

Mathematical modelling of the agr operon in Staphylococcus aureus. - Jabbari, S.; King, J. R.; Koerber, A. J.; Williams, P. (J Math Biol, 2010)
Staphylococcus aureus is a pathogenic bacterium that utilises quorum sensing (QS), a cell-to-cell signalling mechanism, to enhance its ability to cause disease. QS allows the bacteria to monitor their surroundings and the size of their population, and S. aureus makes use of this to regulate the production of virulence factors. Here we describe a mathematical model of this QS system and perform a detailed time-dependent asymptotic analysis in order to clarify the roles of the distinct interactions that make up the QS process, demonstrating which reactions dominate the behaviour of the system at various timepoints. We couple this analysis with numerical simulations and are thus able to gain insight into how a large population of S. aureus shifts from a relatively harmless state to a highly virulent one, focussing on the need for the three distinct phases which form the feedback loop of this particular QS system.
Keywords: Bacterial Proteins/genetics; Computer Simulation; *Models, Genetic; Operon/*genetics; Peptides, Cyclic; Protein Kinases/genetics; Quorum Sensing/*genetics; Staphylococcal Infections/microbiology; Staphylococcus aureus/genetics/*pathogenicity; Virulence Factors/genetics

A mathematical investigation of the effects of inhibitor therapy on three putative phosphorylation cascades governing the two-component system of the agr operon. - Jabbari, S.; King, J. R.; Williams, P. (Math Biosci, 2010)
Two-component systems (TCSs) are widely employed by bacteria to sense specific external signals and conduct an appropriate response via a phosphorylation cascade within the cell. The TCS of the agr operon in the bacterium Staphylococcus aureus forms part of a regulatory process termed quorum sensing, a cell-to-cell communication mechanism used to assess population density. Since S. aureus manipulates this "knowledge" in order to co-ordinate production of its armoury of exotoxin virulence factors required to promote infection, it is important to understand fully how this process works. We present three models of the agr operon, each incorporating a different phosphorylation cascade for the TCS since the precise nature of the cascade is not fully understood. Using numerical and asymptotic techniques we examine the effects of inhibitor therapy, a novel approach to controlling bacterial infection through the attenuation of virulence, on each of these three cascades. We present results which, if evaluated against appropriate experimental data, provide insights into the potential effectiveness of such therapy. Moreover, the TCS models presented here are of broad relevance given that TCSs are widely conserved throughout the bacterial kingdom.
Keywords: Bacterial Proteins/antagonists & inhibitors/genetics/*metabolism; *Models, Biological; Operon; Phosphorylation; Quorum Sensing/*physiology; Staphylococcus aureus/genetics/metabolism/*physiology; Trans-Activators/antagonists & inhibitors/genetics/*metabolism

SensSB: a software toolbox for the development and sensitivity analysis of systems biology models. - Rodriguez-Fernandez, M.; Banga, J. R. (Bioinformatics, 2010)
SUMMARY: SensSB (Sensitivity Analysis for Systems Biology) is an easy to use, MATLAB-based software toolbox, which integrates several local and global sensitivity methods that can be applied to a wide variety of biological models. In addition to addressing the sensitivity analysis problem, SensSB aims to cover all the steps involved during the modeling process. The main features of SensSB are: (i) derivative and variance-based global sensitivity analysis, (ii) pseudo-global identifiability analysis, (iii) optimal experimental design (OED) based on global sensitivities, (iv) robust parameter estimation, (v) local sensitivity and identifiability analysis, (vi) confidence intervals of the estimated parameters and (vii) OED based on the Fisher Information Matrix (FIM). SensSB is also able to import models in the Systems Biology Mark-up Language (SBML) format. Several examples from simple analytical functions to more complex biological pathways have been implemented and can be downloaded together with the toolbox. The importance of using sensitivity analysis techniques for identifying unessential parameters and designing new experiments is quantified by increased identifiability metrics of the models and decreased confidence intervals of the estimated parameters. AVAILABILITY: SensSB is a software toolbox freely downloadable from http://www.iim.csic.es/ approximately gingproc/SensSB.html. The web site also contains several examples and an extensive documentation. CONTACT: mrodriguez@iim.csic.es SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Internet; *Models, Biological; Programming Languages; *Software; Systems Biology/*methods

Cross-talk between two global regulators in Streptomyces: PhoP and AfsR interact in the control of afsS, pstS and phoRP transcription. - Santos-Beneit, F.; Rodriguez-Garcia, A.; Sola-Landa, A.; Martin, J. F. (Mol Microbiol, 2009)
The regulatory proteins AfsR and PhoP control expression of the biosynthesis of actinorhodin and undecylprodigiosin in Streptomyces coelicolor. Electrophoretic mobility shift assays showed that PhoP(DBD) does not bind directly to the actII-ORF4, redD and atrA promoters, but it binds to the afsS promoter, in a region overlapping with the AfsR operator. DNase I footprinting studies revealed a PhoP protected region of 26 nt (PHO box; two direct repeats of 11 nt) that overlaps with the AfsR binding sequence. Binding experiments indicated a competition between AfsR and PhoP; increasing concentrations of PhoP(DBD) resulted in the disappearance of the AfsR-DNA complex. Expression studies using the reporter luxAB gene coupled to afsS promoter showed that PhoP downregulates afsS expression probably by a competition with the AfsR activator. Interestingly, AfsR binds to other PhoP-regulated promoters including those of pstS (a component of the phosphate transport system) and phoRP (encoding the two component system itself). Analysis of the AfsR-protected sequences in each of these promoters allowed us to distinguish the AfsR binding sequence from the overlapping PHO box. The reciprocal regulation of the phoRP promoter by AfsR and of afsS by PhoP suggests a fine interplay of these regulators on the control of secondary metabolism.
Keywords: Bacterial Proteins/genetics/*metabolism; Base Sequence; Binding Sites; DNA Footprinting; DNA-Binding Proteins/genetics/*metabolism; Electrophoretic Mobility Shift Assay; Gene Expression Regulation, Bacterial; Molecular Sequence Data; Promoter Regions, Genetic; Streptomyces coelicolor/*genetics/metabolism; Transcription Factors/genetics/*metabolism; Transcription, Genetic

Computer controlled automated assay for comprehensive studies of enzyme kinetic parameters. - Bonowski, F.; Kitanovic, A.; Ruoff, P.; Holzwarth, J.; Kitanovic, I.; Bui, V. N.; Lederer, E.; Wolfl, S. (PLoS One, 2010)
Stability and biological activity of proteins is highly dependent on their physicochemical environment. The development of realistic models of biological systems necessitates quantitative information on the response to changes of external conditions like pH, salinity and concentrations of substrates and allosteric modulators. Changes in just a few variable parameters rapidly lead to large numbers of experimental conditions, which go beyond the experimental capacity of most research groups. We implemented a computer-aided experimenting framework ("robot lab assistant") that allows us to parameterize abstract, human-readable descriptions of micro-plate based experiments with variable parameters and execute them on a conventional 8 channel liquid handling robot fitted with a sensitive plate reader. A set of newly developed R-packages translates the instructions into machine commands, executes them, collects the data and processes it without user-interaction. By combining script-driven experimental planning, execution and data-analysis, our system can react to experimental outcomes autonomously, allowing outcome-based iterative experimental strategies. The framework was applied in a response-surface model based iterative optimization of buffer conditions and investigation of substrate, allosteric effector, pH and salt dependent activity profiles of pyruvate kinase (PYK). A diprotic model of enzyme kinetics was used to model the combined effects of changing pH and substrate concentrations. The 8 parameters of the model could be estimated from a single two-hour experiment using nonlinear least-squares regression. The model with the estimated parameters successfully predicted pH and PEP dependence of initial reaction rates, while the PEP concentration dependent shift of optimal pH could only be reproduced with a set of manually tweaked parameters. Differences between model-predictions and experimental observations at low pH suggest additional protonation-sites at the enzyme or substrates critical for enzymatic activity. The developed framework is a powerful tool to investigate enzyme reaction specifics and explore biological system behaviour in a wide range of experimental conditions.
Keywords: Automation/*methods; Buffers; *Computer Simulation; Enzyme Assays/*methods; Fructosediphosphates/metabolism; Hydrogen-Ion Concentration; Kinetics; *Models, Molecular; Phosphoenolpyruvate/metabolism; Pyruvate Kinase/metabolism; Substrate Specificity; Surface Properties

Systems biology: the elements and principles of life. - Westerhoff, H. V.; Winder, C.; Messiha, H.; Simeonidis, E.; Adamczyk, M.; Verma, M.; Bruggeman, F. J.; Dunn, W. (FEBS Lett, 2009)
Systems Biology has a mission that puts it at odds with traditional paradigms of physics and molecular biology, such as the simplicity requested by Occam's razor and minimum energy/maximal efficiency. By referring to biochemical experiments on control and regulation, and on flux balancing in yeast, we show that these paradigms are inapt. Systems Biology does not quite converge with biology either: Although it certainly requires accurate 'stamp collecting', it discovers quantitative laws. Systems Biology is a science of its own, discovering own fundamental principles, some of which we identify here.
Keywords: Biochemistry; Genome; *Life; Physics; *Systems Biology; *Thermodynamics; Yeasts/genetics/physiology

Construction and characterization of three lactate dehydrogenase-negative Enterococcus faecalis V583 mutants. - Jonsson, M.; Saleihan, Z.; Nes, I. F.; Holo, H. (Appl Environ Microbiol, 2009)
The roles of the two ldh genes of Enterococcus faecalis were studied using knockout mutants. Deletion of ldh-1 causes a metabolic shift from homolactic fermentation to ethanol, formate, and acetoin production, with a high level of formate production even under aerobic conditions. Ldh-2 plays only a minor role in lactate production.
Keywords: Acetoin/metabolism; Aerobiosis; Bacterial Proteins/*genetics; Enterococcus faecalis/*enzymology/*genetics; Ethanol/metabolism; Formates/metabolism; *Gene Knockout Techniques; L-Lactate Dehydrogenase/*deficiency; Lactates/metabolism; Metabolic Networks and Pathways; Models, Biological

How mathematical modelling elucidates signalling in B. subtilis (2010)
Appropriate stimulus perception, signal processing and transduction ensure optimal adaptation of bacteria to environmental challenges. In the Gram-positive model bacterium Bacillus subtilis signalling networks and molecular interactions therein are well-studied, making this species a suitable candidate for the application of mathematical modelling. Here, we review systems biology approaches, focusing on chemotaxis, sporulation, σB-dependent general stress response and competence. Processes like chemotaxis and Z-ring assembly depend critically on the subcellular localization of proteins. Environmental response strategies, including sporulation and competence, are characterized by phenotypic heterogeneity in isogenic cultures. The examples of mathematical modelling also include investigations that have demonstrated how operon structure and signalling dynamics are intricately interwoven to establish optimal responses. Our review illustrates that these interdisciplinary approaches offer new insights into the response of B. subtilis to environmental challenges. These case studies reveal modelling as a tool to increase the understanding of complex systems, to help formulating hypotheses and to guide the design of more directed experiments that test predictions.

The silicon trypanosome. - Bakker, B. M.; Krauth-Siegel, R. L.; Clayton, C.; Matthews, K.; Girolami, M.; Westerhoff, H. V.; Michels, P. A.; Breitling, R.; Barrett, M. P. (Parasitology, 2010)
African trypanosomes have emerged as promising unicellular model organisms for the next generation of systems biology. They offer unique advantages, due to their relative simplicity, the availability of all standard genomics techniques and a long history of quantitative research. Reproducible cultivation methods exist for morphologically and physiologically distinct life-cycle stages. The genome has been sequenced, and microarrays, RNA-interference and high-accuracy metabolomics are available. Furthermore, the availability of extensive kinetic data on all glycolytic enzymes has led to the early development of a complete, experiment-based dynamic model of an important biochemical pathway. Here we describe the achievements of trypanosome systems biology so far and outline the necessary steps towards the ambitious aim of creating a 'Silicon Trypanosome', a comprehensive, experiment-based, multi-scale mathematical model of trypanosome physiology. We expect that, in the long run, the quantitative modelling enabled by the Silicon Trypanosome will play a key role in selecting the most suitable targets for developing new anti-parasite drugs.
Keywords: Parasitology/*methods/*trends; *Systems Biology/methods/trends; Trypanosoma/*genetics/*metabolism

Metabolomic systems biology of trypanosomes. - Barrett, M. P.; Bakker, B. M.; Breitling, R. (Parasitology, 2010)
Metabolomics analysis, which aims at the systematic identification and quantification of all metabolites in biological systems, is emerging as a powerful new tool to identify biomarkers of disease, report on cellular responses to environmental perturbation, and to identify the targets of drugs. Here we discuss recent developments in metabolomic analysis, from the perspective of trypanosome research, highlighting remaining challenges and the most promising areas for future research.
Keywords: Genome, Protozoan; *Metabolome; Metabolomics/methods; Models, Genetic; Trypanosomiasis/genetics/*metabolism

Penicillin-binding protein folding is dependent on the PrsA peptidyl-prolyl cis-trans isomerase in Bacillus subtilis. - Hyyrylainen, H. L.; Marciniak, B. C.; Dahncke, K.; Pietiainen, M.; Courtin, P.; Vitikainen, M.; Seppala, R.; Otto, A.; Becher, D.; Chapot-Chartier, M. P.; Kuipers, O. P.; Kontinen, V. P. (Mol Microbiol, 2010)
Summary The PrsA protein is a membrane-anchored peptidyl-prolyl cis-trans isomerase in Bacillus subtilis and most other Gram-positive bacteria. It catalyses the post-translocational folding of exported proteins and is essential for normal growth of B. subtilis. We studied the mechanism behind this indispensability. We could construct a viable prsA null mutant in the presence of a high concentration of magnesium. Various changes in cell morphology in the absence of PrsA suggested that PrsA is involved in the biosynthesis of the cylindrical lateral wall. Consistently, four penicillin-binding proteins (PBP2a, PBP2b, PBP3 and PBP4) were unstable in the absence of PrsA, while muropeptide analysis revealed a 2% decrease in the peptidoglycan cross-linkage index. Misfolded PBP2a was detected in PrsA-depleted cells, indicating that PrsA is required for the folding of this PBP either directly or indirectly. Furthermore, strongly increased uniform staining of cell wall with a fluorescent vancomycin was observed in the absence of PrsA. We also demonstrated that PrsA is a dimeric or oligomeric protein which is localized at distinct spots organized in a helical pattern along the cell membrane. These results suggest that PrsA is essential for normal growth most probably as PBP folding is dependent on this PPIase.
Keywords: Bacillus subtilis/cytology/*enzymology/*metabolism; Bacterial Proteins/genetics/*metabolism; Cell Membrane/chemistry; Cell Wall/chemistry/metabolism; Gene Deletion; Genes, Bacterial; Genes, Essential; Lipoproteins/genetics/*metabolism; Magnesium/metabolism; Membrane Proteins/genetics/*metabolism; Penicillin-Binding Proteins/*metabolism; Peptidoglycan/analysis; Peptidylprolyl Isomerase/genetics/*metabolism; *Protein Folding; Protein Multimerization

ClpP modulates the activity of the Bacillus subtilis stress response transcription factor, sigmaB. - Reeves, A.; Gerth, U.; Volker, U.; Haldenwang, W. G. (J Bacteriol, 2007)
The general stress regulon of Bacillus subtilis is controlled by the activity state of sigmaB, a transcription factor that is switched on following exposure to either physical or nutritional stress. ClpP is the proteolytic component of an ATP-dependent protease that is essential for the proper regulation of multiple adaptive responses in B. subtilis. Among the proteins whose abundance increases in ClpP- B. subtilis are several known to depend on sigmaB for their expression. In the current work we examine the relationship of ClpP to the activity of sigmaB. The data reveal that the loss of ClpP in otherwise wild-type B. subtilis results in a small increase in sigmaB activity during growth and a marked enhancement of sigmaB activity following its induction by either physical or nutritional stress. It appears to be the persistence of sigmaB's activity rather than its induction that is principally affected by the loss of ClpP. sigmaB-dependent reporter gene activity rose in parallel in ClpP+ and ClpP- B. subtilis strains but failed to display its normal transience in the ClpP- strain. The putative ClpP targets are likely to be stress generated and novel. Enhanced sigmaB activity in ClpP- B. subtilis was triggered by physical stress but not by the induced synthesis of the physical stress pathway's positive regulator (RsbT). In addition, Western blot analyses failed to detect differences in the levels of the principal known sigmaB regulators in ClpP+ and ClpP- B. subtilis strains. The data suggest a model in which ClpP facilitates the turnover of stress-generated factors, which persist in ClpP's absence to stimulate ongoing sigmaB activity.
Keywords: *Adaptation, Physiological; Artificial Gene Fusion; Bacillus subtilis/*physiology; Bacterial Proteins/*metabolism; Endopeptidase Clp/genetics/*physiology; Gene Deletion; Gene Expression Regulation, Bacterial/*physiology; Genes, Reporter; Models, Biological; Mutagenesis, Insertional; Sigma Factor/*metabolism; beta-Galactosidase/biosynthesis/genetics

The MarR-type repressor MhqR (YkvE) regulates multiple dioxygenases/glyoxalases and an azoreductase which confer resistance to 2-methylhydroquinone and catechol in Bacillus subtilis. - Towe, S.; Leelakriangsak, M.; Kobayashi, K.; Van Duy, N.; Hecker, M.; Zuber, P.; Antelmann, H. (Mol Microbiol, 2007)
Catechol and 2-methylhydroquinone (2-MHQ) cause the induction of the thiol-specific stress response and four dioxygenases/glyoxalases in Bacillus subtilis. Using transcription factor arrays, the MarR-type regulator YkvE was identified as a repressor of the dioxygenase/glyoxalase-encoding mhqE gene. Transcriptional and proteome analyses of the DeltaykvE mutant revealed the upregulation of ykcA (mhqA), ydfNOP (mhqNOP), yodED (mhqED) and yvaB (azoR2) encoding multiple dioxygenases/glyoxalases, oxidoreductases and an azoreductase. Primer extension experiments identified sigma(A)-type promoter sequences upstream of mhqA, mhqNOP, mhqED and azoR2 from which transcription is elevated after thiol stress. DNase I footprinting analysis showed that YkvE protects a primary imperfect inverted repeat with the consensus sequence of tATCTcgaAtTCgAGATaaaa in the azoR2, mhqE and mhqN promoter regions. Analysis of mhqE-promoter-bgaB fusions confirmed the significance of YkvE binding to this operator in vivo. Adjacent secondary repeats were protected by YkvE in the azoR2 and mhqN promoter regions consistent with multiple DNA-protein binding complexes. DNA-binding activity of YkvE was not directly affected by thiol-reactive compounds in vitro. Mutational analyses showed that MhqA, MhqO and AzoR2 confer resistance to 2-MHQ. Moreover, the DeltaykvE mutant displayed a 2-MHQ and catechol resistant phenotype. YkvE was renamed as MhqR controlling a 2-MHQ and catechol-resistance regulon of B. subtilis.
Keywords: Anti-Bacterial Agents/metabolism/pharmacology; Bacillus subtilis/*physiology; Bacterial Proteins/genetics/physiology; Binding Sites/genetics; Catechols/metabolism/*pharmacology; DNA Footprinting; DNA, Bacterial/metabolism; Dioxygenases/*biosynthesis; Drug Resistance, Bacterial/*physiology; Electrophoretic Mobility Shift Assay; Gene Deletion; Gene Expression Regulation, Bacterial/*physiology; Hydroquinones/metabolism/*pharmacology; Mutagenesis, Insertional; NADH, NADPH Oxidoreductases/*biosynthesis; Nitroreductases; Oligonucleotide Array Sequence Analysis; Promoter Regions, Genetic; Protein Binding; Proteome/analysis; Repressor Proteins/genetics/*physiology

Regulation of quinone detoxification by the thiol stress sensing DUF24/MarR-like repressor, YodB in Bacillus subtilis. - Leelakriangsak, M.; Huyen, N. T.; Towe, S.; van Duy, N.; Becher, D.; Hecker, M.; Antelmann, H.; Zuber, P. (Mol Microbiol, 2008)
Recently, we showed that the MarR-type repressor YkvE (MhqR) regulates multiple dioxygenases/glyoxalases, oxidoreductases and the azoreductase encoding yvaB (azoR2) gene in response to thiol-specific stress conditions, such as diamide, catechol and 2-methylhydroquinone (MHQ). Here we report on the regulation of the yocJ (azoR1) gene encoding another azoreductase by the novel DUF24/MarR-type repressor, YodB after exposure to thiol-reactive compounds. DNA binding activity of YodB is directly inhibited by thiol-reactive compounds in vitro. Mass spectrometry identified YodB-Cys-S-adducts that are formed upon exposure of YodB to MHQ and catechol in vitro. This confirms that catechol and MHQ are auto-oxidized to toxic ortho- and para-benzoquinones which act like diamide as thiol-reactive electrophiles. Mutational analyses further showed that the conserved Cys6 residue of YodB is required for optimal repression in vivo and in vitro while substitution of all three Cys residues of YodB affects induction of azoR1 transcription. Finally, phenotype analyses revealed that both azoreductases, AzoR1 and AzoR2 confer resistance to catechol, MHQ, 1,4-benzoquinone and diamide. Thus, both azoreductases that are controlled by different regulatory mechanisms have common functions in quinone and azo-compound reduction to protect cells against the thiol reactivity of electrophiles.
Keywords: Bacillus subtilis/drug effects/*genetics/metabolism; Bacterial Proteins/chemistry/genetics/*metabolism; Catechols/metabolism; Cysteine/metabolism; DNA Footprinting; DNA-Binding Proteins/chemistry/*genetics/metabolism; Diamide/metabolism; Gene Expression Regulation, Bacterial; Hydrogen Peroxide/metabolism; Hydroquinones/metabolism; Mass Spectrometry; Models, Molecular; NADH, NADPH Oxidoreductases/drug effects/*genetics; Nitroreductases; Oligonucleotide Array Sequence Analysis; Oxidative Stress; Promoter Regions, Genetic; Proteomics; Quinones/*metabolism; Repressor Proteins/chemistry/*genetics/metabolism; Sulfhydryl Compounds/*metabolism; Transcription, Genetic; Up-Regulation

Proteomic signatures uncover thiol-specific electrophile resistance mechanisms in Bacillus subtilis. - Antelmann, H.; Hecker, M.; Zuber, P. (Expert Rev Proteomics, 2008)
Proteomic and transcriptomics signatures are powerful tools for visualizing global changes in gene expression in bacterial cells after exposure to stress, starvation or toxic compounds. Based on the global expression profile and the dissection into specific regulons, this knowledge can be used to predict the mode of action for novel antimicrobial compounds. This review summarizes our recent progress of proteomic signatures in the model bacterium for low-GC Gram-positive bacteria Bacillus subtilis in response to the antimicrobial compounds phenol, catechol, salicylic acid, 2-methylhydroquinone (2-MHQ) and 6-brom-2-vinyl-chroman-4-on (chromanon). Catechol, 2-MHQ and diamide displayed a common mode of action, as revealed by the induction of the thiol-specific oxidative stress response. In addition, multiple dioxygenases/glyoxalases, azoreductases and nitroreductases were induced by thiol-reactive compounds that are regulated by two novel thiol-specific regulators, YodB and MhqR (YkvE), both of which contribute to electrophile resistance in B. subtilis. These novel thiol-stress-responsive mechanisms are highly conserved among Gram-positive bacteria and are thought to have evolved to detoxify quinone-like electrophiles.
Keywords: Bacillus subtilis/*drug effects/enzymology/genetics; Bacterial Proteins/biosynthesis/genetics/*physiology; Catechols/pharmacology; Cell Wall/drug effects; Chromones/pharmacology; Diamide/pharmacology; Drug Resistance, Bacterial/*physiology; Electrophoresis, Gel, Two-Dimensional; Enzyme Induction/drug effects; Gene Expression Regulation, Bacterial/drug effects; Gram-Positive Bacteria/drug effects/enzymology; Hydroquinones/pharmacology; Nitrofurantoin/pharmacology; Oxidative Stress/drug effects; Phenol/pharmacology; *Proteomics/methods; Quinones/*pharmacology; Regulon/drug effects; Salicylic Acid/pharmacology; Sulfhydryl Compounds/*pharmacology

The twin-arginine translocation (Tat) systems from Bacillus subtilis display a conserved mode of complex organization and similar substrate recognition requirements. - Barnett, J. P.; van der Ploeg, R.; Eijlander, R. T.; Nenninger, A.; Mendel, S.; Rozeboom, R.; Kuipers, O. P.; van Dijl, J. M.; Robinson, C. (FEBS J, 2009)
The twin arginine translocation (Tat) system transports folded proteins across the bacterial plasma membrane. In Gram-negative bacteria, membrane-bound TatABC subunits are all essential for activity, whereas Gram-positive bacteria usually contain only TatAC subunits. In Bacillus subtilis, two TatAC-type systems, TatAdCd and TatAyCy, operate in parallel with different substrate specificities. Here, we show that they recognize similar signal peptide determinants. Both systems translocate green fluorescent protein fused to three distinct Escherichia coli Tat signal peptides, namely DmsA, AmiA and MdoD, and mutagenesis of the DmsA signal peptide confirmed that both Tat pathways recognize similar targeting determinants within Tat signals. Although another E. coli Tat substrate, trimethylamine N-oxide reductase, was translocated by TatAdCd but not by TatAyCy, we conclude that these systems are not predisposed to recognize only specific Tat signal peptides, as suggested by their narrow substrate specificities in B. subtilis. We also analysed complexes involved in the second Tat pathway in B. subtilis, TatAyCy. This revealed a discrete TatAyCy complex together with a separate, homogeneous, approximately 200 kDa TatAy complex. The latter complex differs significantly from the corresponding E. coli TatA complexes, pointing to major structural differences between Tat complexes from Gram-negative and Gram-positive organisms. Like TatAd, TatAy is also detectable in the form of massive cytosolic complexes.
Keywords: Adenosine Triphosphate/metabolism; Bacillus subtilis/*genetics/*metabolism; Bacterial Proteins/metabolism; Cell Membrane/*metabolism; Conserved Sequence; Escherichia coli/genetics/metabolism; Gene Products, tat/*metabolism; Genes, Reporter; Gram-Negative Bacteria/metabolism; Oxidoreductases, N-Demethylating/metabolism; Protein Transport; Substrate Specificity

Glutamate metabolism in Bacillus subtilis: gene expression and enzyme activities evolved to avoid futile cycles and to allow rapid responses to perturbations of the system. - Commichau, F. M.; Gunka, K.; Landmann, J. J.; Stulke, J. (J Bacteriol, 2008)
Glutamate is a central metabolite in all organisms since it provides the link between carbon and nitrogen metabolism. In Bacillus subtilis, glutamate is synthesized exclusively by the glutamate synthase, and it can be degraded by the glutamate dehydrogenase. In B. subtilis, the major glutamate dehydrogenase RocG is expressed only in the presence of arginine, and the bacteria are unable to utilize glutamate as the only carbon source. In addition to rocG, a second cryptic gene (gudB) encodes an inactive glutamate dehydrogenase. Mutations in rocG result in the rapid accumulation of gudB1 suppressor mutations that code for an active enzyme. In this work, we analyzed the physiological significance of this constellation of genes and enzymes involved in glutamate metabolism. We found that the weak expression of rocG in the absence of the inducer arginine is limiting for glutamate utilization. Moreover, we addressed the potential ability of the active glutamate dehydrogenases of B. subtilis to synthesize glutamate. Both RocG and GudB1 were unable to catalyze the anabolic reaction, most probably because of their very high K(m) values for ammonium. In contrast, the Escherichia coli glutamate dehydrogenase is able to produce glutamate even in the background of a B. subtilis cell. B. subtilis responds to any mutation that interferes with glutamate metabolism with the rapid accumulation of extragenic or intragenic suppressor mutations, bringing the glutamate supply into balance. Similarly, with the presence of a cryptic gene, the system can flexibly respond to changes in the external glutamate supply by the selection of mutations.
Keywords: Bacillus subtilis/*enzymology/genetics/*metabolism; Gene Expression Regulation, Bacterial/*physiology; Glutamate Dehydrogenase/isolation & purification/*metabolism; Glutamic Acid/*metabolism; Operon/genetics; *Substrate Cycling

Monitoring of changes in the membrane proteome during stationary phase adaptation of Bacillus subtilis using in vivo labeling techniques. - Dreisbach, A.; Otto, A.; Becher, D.; Hammer, E.; Teumer, A.; Gouw, J. W.; Hecker, M.; Volker, U. (Proteomics, 2008)
Bacillus subtilis has been developed as a model system for physiological proteomics. However, thus far these studies have mainly been limited to cytoplasmic, extracellular, and cell-wall attached proteins. Although being certainly important for cell physiology, the membrane protein fraction has not been studied in comparable depth due to inaccessibility by traditional 2-DE-based workflows and limitations in reliable quantification. In this study, we now compare the potential of stable isotope labeling with amino acids (SILAC) and (14)N/(15)N-labeling for the analysis of bacterial membrane fractions in physiology-driven proteomic studies. Using adaptation of B. subtilis to amino acid (lysine) and glucose starvation as proof of principle scenarios, we show that both approaches provide similarly valuable data for the quantification of bacterial membrane proteins. Even if labeling with stable amino acids allows a more straightforward analysis of data, the (14)N/(15)N-labeling has some advantages in general such as labeling of all amino acids and thereby increasing the number of peptides for quantification. Both, SILAC as well as (14)N/(15)N-labeling are compatible with 2-DE, 2-D LC-MS/MS, and GeLC-MS/MS and thus will allow comprehensive simultaneous interrogation of cytoplasmic and enriched membrane proteomes.
Keywords: Adaptation, Physiological; Bacillus subtilis/growth & development/*metabolism; Bacterial Proteins/*analysis/metabolism; Chromatography, Liquid; Electrophoresis, Gel, Two-Dimensional; Gene Expression Regulation, Bacterial; Isotope Labeling/methods; Membrane Proteins/*analysis/metabolism; Proteomics/*methods

How quantitative measures unravel design principles in multi-stage phosphorylation cascades. - Frey, S.; Millat, T.; Hohmann, S.; Wolkenhauer, O. (J Theor Biol, 2008)
We investigate design principles of linear multi-stage phosphorylation cascades by using quantitative measures for signaling time, signal duration and signal amplitude. We compare alternative pathway structures by varying the number of phosphorylations and the length of the cascade. We show that a model for a weakly activated pathway does not reflect the biological context well, unless it is restricted to certain parameter combinations. Focusing therefore on a more general model, we compare alternative structures with respect to a multivariate optimization criterion. We test the hypothesis that the structure of a linear multi-stage phosphorylation cascade is the result of an optimization process aiming for a fast response, defined by the minimum of the product of signaling time and signal duration. It is then shown that certain pathway structures minimize this criterion. Several popular models of MAPK cascades form the basis of our study. These models represent different levels of approximation, which we compare and discuss with respect to the quantitative measures.
Keywords: Animals; Cells/*metabolism; Enzyme Activation; MAP Kinase Signaling System/*physiology; Mitogen-Activated Protein Kinase Phosphatases/*metabolism; Mitogen-Activated Protein Kinases/*metabolism; Models, Biological; *Numerical Analysis, Computer-Assisted; Phosphorylation

Carbon catabolite repression in bacteria: many ways to make the most out of nutrients. - Gorke, B.; Stulke, J. (Nat Rev Microbiol, 2008)
Most bacteria can selectively use substrates from a mixture of different carbon sources. The presence of preferred carbon sources prevents the expression, and often also the activity, of catabolic systems that enable the use of secondary substrates. This regulation, called carbon catabolite repression (CCR), can be achieved by different regulatory mechanisms, including transcription activation and repression and control of translation by an RNA-binding protein, in different bacteria. Moreover, CCR regulates the expression of virulence factors in many pathogenic bacteria. In this Review, we discuss the most recent findings on the different mechanisms that have evolved to allow bacteria to use carbon sources in a hierarchical manner.
Keywords: Bacteria/enzymology/genetics/*metabolism; Bacterial Proteins/genetics/*metabolism; Carbon/*metabolism; *Enzyme Repression; Gene Expression Regulation, Bacterial; Transcription, Genetic

Gel-based proteomics of Gram-positive bacteria: a powerful tool to address physiological questions. - Hecker, M.; Antelmann, H.; Buttner, K.; Bernhardt, J. (Proteomics, 2008)
In this review, we demonstrate the power of gel-based proteomics to address physiological questions of bacteria. Although gel-based proteomics covers a subpopulation of proteins only, fundamental issues of a bacterial cell such as almost all metabolic pathways or the main signatures of stress and starvation responses can be analyzed. The analysis of the synthesis pattern of single proteins, e.g., in response to environmental changes, requires gel-based proteomics because only this technique can compare protein synthesis and amount in the same 2-D gel. Moreover, highly sophisticated software packages facilitate the analysis of the regulation of the main metabolic enzymes or the stress/starvation responses, PTMs, protein damage/repair, and degradation and finally protein secretion mechanisms at a proteome-wide scale. The challenge of proteomics whose panorama view shows events never seen before is to select the most interesting issues for detailed follow up studies. This "road map of proteomics" from proteome data via new hypothesis and finally novel molecular mechanisms should lead to exciting information on bacterial physiology. However, many proteins escape detection by gel-based procedures, such as membrane or low abundance proteins. The smart combination of gel-free and gel-based approaches is the "state of the art" for physiological proteomics of bacteria.
Keywords: Bacterial Proteins/analysis; Electrophoresis, Gel, Two-Dimensional; Gram-Positive Bacteria/cytology/*physiology; Protein Processing, Post-Translational; Proteomics/*methods; Stress, Physiological

Localization of general and regulatory proteolysis in Bacillus subtilis cells. - Kirstein, J.; Strahl, H.; Moliere, N.; Hamoen, L. W.; Turgay, K. (Mol Microbiol, 2008)
Protein degradation mediated by ATP-dependent proteases, such as Hsp100/Clp and related AAA+ proteins, plays an important role in cellular protein homeostasis, protein quality control and the regulation of, e.g. heat shock adaptation and other cellular differentiation processes. ClpCP with its adaptor proteins and other related proteases, such as ClpXP or ClpEP of Bacillus subtilis, are involved in general and regulatory proteolysis. To determine if proteolysis occurs at specific locations in B. subtilis cells, we analysed the subcellular distribution of the Clp system together with adaptor and general and regulatory substrate proteins, under different environmental conditions. We can demonstrate that the ATPase and the proteolytic subunit of the Clp proteases, as well as the adaptor or substrate proteins, form visible foci, representing active protease clusters localized to the polar and to the mid-cell region. These clusters could represent a compartmentalized place for protein degradation positioned at the pole close to where most of the cellular protein biosynthesis and also protein quality control are taking place, thereby spatially separating protein synthesis and degradation.
Keywords: Adenosine Triphosphatases/genetics/*metabolism; Bacillus subtilis/cytology/*enzymology/genetics; Bacterial Proteins/genetics/*metabolism; Cell Division; Endopeptidase Clp/genetics/*metabolism; Heat-Shock Proteins/genetics/*metabolism; Heat-Shock Response; Microscopy, Fluorescence; Recombinant Fusion Proteins/genetics/metabolism; Time Factors

Interchangeable modules in bacterial thiol-disulfide exchange pathways. - Kouwen, T. R.; van Dijl, J. M. (Trends Microbiol, 2009)
Thiol-disulfide oxidoreductases (TDORs) catalyze thiol-disulfide exchange reactions that are crucial for protein activity and stability. Specifically, they can function as thiol oxidases, disulfide reductases or disulfide isomerases. The generally established view is that particular TDORs act unidirectionally within a fixed cascade of specific, sequentially arranged reactions. However, recent studies on both Gram-negative and Gram-positive bacteria imply that this view needs to be expanded, at least for thiol-disulfide exchanges in proteins that are exported from the cytoplasm. Here, we present our opinion that various TDORs can function as interchangeable modules in different thiol-disulfide exchange pathways. Such TDOR modules, thus, fulfil important functions in generating the diversity in activity and specificity that is needed in productive extracytoplasmic thiol-disulfide exchange.
Keywords: Bacillus subtilis/enzymology/genetics/*metabolism; Bacterial Proteins/chemistry/genetics/metabolism; Disulfides/chemistry/*metabolism; Escherichia coli/enzymology/genetics/*metabolism; Escherichia coli Proteins/chemistry/genetics/metabolism; Membrane Proteins/chemistry/genetics/metabolism; Models, Molecular; Oxidation-Reduction; Protein Disulfide Reductase (Glutathione)/chemistry/genetics/*metabolism; Protein Disulfide-Isomerases/chemistry/genetics/metabolism; Sulfhydryl Compounds/chemistry/*metabolism

Modulation of thiol-disulfide oxidoreductases for increased production of disulfide-bond-containing proteins in Bacillus subtilis. - Kouwen, T. R.; Dubois, J. Y.; Freudl, R.; Quax, W. J.; van Dijl, J. M. (Appl Environ Microbiol, 2008)
Disulfide bonds are important for the correct folding, structural integrity, and activity of many biotechnologically relevant proteins. For synthesis and subsequent secretion of these proteins in bacteria, such as the well-known "cell factory" Bacillus subtilis, it is often the correct formation of disulfide bonds that is the greatest bottleneck. Degradation of inefficiently or incorrectly oxidized proteins and the requirement for costly and time-consuming reduction and oxidation steps in the downstream processing of the proteins still are major limitations for full exploitation of B. subtilis for biopharmaceutical production. Therefore, the present study was aimed at developing a novel in vivo strategy for improved production of secreted disulfide-bond-containing proteins. Three approaches were tested: depletion of the major cytoplasmic reductase TrxA; introduction of the heterologous oxidase DsbA from Staphylococcus carnosus; and addition of redox-active compounds to the growth medium. As shown using the disulfide-bond-containing molecule Escherichia coli PhoA as a model protein, combined use of these three approaches resulted in secretion of amounts of active PhoA that were approximately 3.5-fold larger than the amounts secreted by the parental strain B. subtilis 168. Our findings indicate that Bacillus strains with improved oxidizing properties can be engineered for biotechnological production of heterologous high-value proteins containing disulfide bonds.
Keywords: Alkaline Phosphatase/biosynthesis; Bacillus subtilis/*enzymology/*genetics; Bacterial Proteins/*genetics/*metabolism; Biotechnology/methods; Culture Media/chemistry; Escherichia coli Proteins/biosynthesis; Oxidation-Reduction; Protein Disulfide Reductase (Glutathione)/*genetics/*metabolism; Recombinant Proteins/genetics/metabolism; Staphylococcus/enzymology/genetics

The role of dynamic stimulation pattern in the analysis of bistable intracellular networks. - Millat, T.; Sreenath, S. N.; Soebiyanto, R. P.; Avva, J.; Cho, K. H.; Wolkenhauer, O. (Biosystems, 2008)
Bistable systems play an important role in the functioning of living cells. Depending on the strength of the necessary positive feedback one can distinguish between (irreversible) "one-way switch" or (reversible) "toggle-switch" type behavior. Besides the well- established steady-state properties, some important characteristics of bistable systems arise from an analysis of their dynamics. We demonstrate that a supercritical stimulus amplitude is not sufficient to move the system from the lower (off-state) to the higher branch (on-state) for either a step or a pulse input. A switching surface is identified for the system as a function of the initial condition, input pulse amplitude and duration (a supercritical signal). We introduce the concept of bounded autonomy for single level systems with a pulse input. Towards this end, we investigate and characterize the role of the duration of the stimulus. Furthermore we show, that a minimal signal power is also necessary to change the steady state of the bistable system. This limiting signal power is independent of the applied stimulus and is determined only by systems parameters. These results are relevant for the design of experiments, where it is often difficult to create a defined pattern for the stimulus. Furthermore, intracellular processes, like receptor internalization, do manipulate the level of stimulus such that level and duration of the stimulus is conducive to characteristic behavior.
Keywords: *Cell Communication; *Computer Simulation; *Models, Biological

Carbon catabolite repression in Bacillus subtilis: quantitative analysis of repression exerted by different carbon sources. - Singh, K. D.; Schmalisch, M. H.; Stulke, J.; Gorke, B. (J Bacteriol, 2008)
In many bacteria glucose is the preferred carbon source and represses the utilization of secondary substrates. In Bacillus subtilis, this carbon catabolite repression (CCR) is achieved by the global transcription regulator CcpA, whose activity is triggered by the availability of its phosphorylated cofactors, HPr(Ser46-P) and Crh(Ser46-P). Phosphorylation of these proteins is catalyzed by the metabolite-controlled kinase HPrK/P. Recent studies have focused on glucose as a repressing substrate. Here, we show that many carbohydrates cause CCR. The substrates form a hierarchy in their ability to exert repression via the CcpA-mediated CCR pathway. Of the two cofactors, HPr is sufficient for complete CCR. In contrast, Crh cannot substitute for HPr on substrates that cause a strong repression. Determination of the phosphorylation state of HPr in vivo revealed a correlation between the strength of repression and the degree of phosphorylation of HPr at Ser46. Sugars transported by the phosphotransferase system (PTS) cause the strongest repression. However, the phosphorylation state of HPr at its His15 residue and PTS transport activity have no impact on the global CCR mechanism, which is a major difference compared to the mechanism operative in Escherichia coli. Our data suggest that the hierarchy in CCR exerted by the different substrates is exclusively determined by the activity of HPrK/P.
Keywords: Bacillus subtilis/genetics/*metabolism; Bacterial Proteins/genetics/*metabolism; Blotting, Western; Carbon/*metabolism; DNA-Binding Proteins/genetics/*metabolism; Electrophoresis, Polyacrylamide Gel; Fructosediphosphates/metabolism; Gene Expression Regulation, Bacterial; Operon; Phosphoenolpyruvate Sugar Phosphotransferase System/genetics/metabolism; Phosphorylation; Repressor Proteins/genetics/*metabolism; Xylans/metabolism; Xylosidases/genetics/metabolism

The Spx paralogue MgsR (YqgZ) controls a subregulon within the general stress response of Bacillus subtilis. - Reder, A.; Hoper, D.; Weinberg, C.; Gerth, U.; Fraunholz, M.; Hecker, M. (Mol Microbiol, 2008)
The alternative sigma factor sigma(B) of Bacillus subtilis is responsible for the induction of the large general stress regulon comprising approximately 150-200 genes. YqgZ, a member of the sigma(B) regulon, resembles the global regulator Spx of the diamide stress regulon in B. subtilis. In this work we conducted a comprehensive transcriptome and proteome analysis of the B. subtilis wild-type 168 and its isogenic DeltasigB and DeltayqgZ mutants following exposure to 4% (v/v) ethanol stress, which led to the characterization of a 'subregulon' within the general stress response that is regulated by YqgZ. Activation and induction of sigma(B) are necessary but not sufficient for a full expression of all general stress genes. Expression of 53 genes was found to be positively regulated and the expression of 18 genes was negatively affected by YqgZ. The identification of the negatively regulated group represents a so far uncharacterized regulatory phenomenon observed in the DeltasigB mutant background that can now be attributed to the function of YqgZ. Due to the strict sigma(B)-dependent expression of YqgZ it was renamed to MgsR (modulator of the general stress response).
Keywords: Amino Acid Sequence; Amino Acid Substitution; Bacillus subtilis/chemistry/drug effects/genetics/*physiology; Bacterial Proteins/chemistry/genetics/*metabolism; Electrophoresis, Gel, Two-Dimensional; Ethanol/pharmacology; Gene Expression Profiling; *Gene Expression Regulation, Bacterial/drug effects; Molecular Sequence Data; Oxidative Stress/drug effects; *Regulon; Repressor Proteins/chemistry/genetics/*metabolism; Sequence Alignment; Sigma Factor/genetics/metabolism

Genetic or chemical protease inhibition causes significant changes in the Bacillus subtilis exoproteome. - Westers, L.; Westers, H.; Zanen, G.; Antelmann, H.; Hecker, M.; Noone, D.; Devine, K. M.; van Dijl, J. M.; Quax, W. J. (Proteomics, 2008)
Bacillus subtilis is a prolific producer of enzymes and biopharmaceuticals. However, the susceptibility of heterologous proteins to degradation by (extracellular) proteases is a major limitation for use of B. subtilis as a protein cell factory. An increase in protein production levels has previously been achieved by using either protease-deficient strains or addition of protease inhibitors to B. subtilis cultures. Notably, the effects of genetic and chemical inhibition of proteases have thus far not been compared in a systematic way. In the present studies, we therefore compared the exoproteomes of cells in which extracellular proteases were genetically or chemically inactivated. The results show substantial differences in the relative abundance of various extracellular proteins. Furthermore, a comparison of the effects of genetic and/or chemical protease inhibition on the stress response triggered by (over) production of secreted proteins showed that chemical protease inhibition provoked a genuine secretion stress response. From a physiological point of view, this suggests that the deletion of protease genes is a better way to prevent product degradation than the use of protease inhibitors. Importantly however, studies with human interleukin-3 show that chemical protease inhibition can result in improved production of protease-sensitive secreted proteins even in mutant strains lacking eight extracellular proteases.
Keywords: Bacillus subtilis/*enzymology/*genetics; Bacterial Proteins/genetics/*metabolism; Endopeptidases/metabolism; Gene Expression Regulation, Bacterial; Periplasmic Proteins/genetics/*metabolism; Protease Inhibitors/*metabolism; Proteome/*analysis; Proteomics/methods

Towards the development of Bacillus subtilis as a cell factory for membrane proteins and protein complexes. - Zweers, J. C.; Barak, I.; Becher, D.; Driessen, A. J.; Hecker, M.; Kontinen, V. P.; Saller, M. J.; Vavrova, L.; van Dijl, J. M. (Microb Cell Fact, 2008)
BACKGROUND: The Gram-positive bacterium Bacillus subtilis is an important producer of high quality industrial enzymes and a few eukaryotic proteins. Most of these proteins are secreted into the growth medium, but successful examples of cytoplasmic protein production are also known. Therefore, one may anticipate that the high protein production potential of B. subtilis can be exploited for protein complexes and membrane proteins to facilitate their functional and structural analysis. The high quality of proteins produced with B. subtilis results from the action of cellular quality control systems that efficiently remove misfolded or incompletely synthesized proteins. Paradoxically, cellular quality control systems also represent bottlenecks for the production of various heterologous proteins at significant concentrations. CONCLUSION: While inactivation of quality control systems has the potential to improve protein production yields, this could be achieved at the expense of product quality. Mechanisms underlying degradation of secretory proteins are nowadays well understood and often controllable. It will therefore be a major challenge for future research to identify and modulate quality control systems of B. subtilis that limit the production of high quality protein complexes and membrane proteins, and to enhance those systems that facilitate assembly of these proteins.

Immunity to the bacteriocin sublancin 168 Is determined by the SunI (YolF) protein of Bacillus subtilis. - Dubois, J. Y.; Kouwen, T. R.; Schurich, A. K.; Reis, C. R.; Ensing, H. T.; Trip, E. N.; Zweers, J. C.; van Dijl, J. M. (Antimicrob Agents Chemother, 2009)
Bacillus subtilis strain 168 produces the extremely stable lantibiotic sublancin 168, which has a broad spectrum of bactericidal activity. Both sublancin 168 production and producer immunity are determined by the SPbeta prophage. While the sunA and sunT genes for sublancin 168 production have been known for several years, the genetic basis for sublancin 168 producer immunity has remained elusive. Therefore, the present studies were aimed at identifying an SPbeta gene(s) for sublancin 168 immunity. By systematic deletion analysis, we were able to pinpoint one gene, named yolF, as the sublancin 168 producer immunity gene. Growth inhibition assays performed using plates and liquid cultures revealed that YolF is both required and sufficient for sublancin 168 immunity even when heterologously produced in the sublancin-sensitive bacterium Staphylococcus aureus. Accordingly, we propose to rename yolF to sunI (for sublancin immunity). Subcellular localization studies indicate that the SunI protein is anchored to the membrane with a single N-terminal membrane-spanning domain that has an N(out)-C(in) topology. Thus, the bulk of the protein faces the cytoplasm of B. subtilis. This topology has not yet been reported for known bacteriocin producer immunity proteins, which implies that SunI belongs to a novel class of bacteriocin antagonists.
Keywords: Bacillus subtilis/drug effects/*genetics; Bacteriocins/*pharmacology; Blotting, Western; Culture Media; Cytoplasm/drug effects/metabolism; DNA, Bacterial/genetics; Drug Resistance, Bacterial/*genetics; Electrophoresis, Polyacrylamide Gel; Genes, Bacterial/*genetics/*physiology; Glycopeptides; Microbial Sensitivity Tests; Peptides/*pharmacology; Plasmids; Prophages/genetics; Staphylococcus aureus/drug effects

Genome-wide responses to carbonyl electrophiles in Bacillus subtilis: control of the thiol-dependent formaldehyde dehydrogenase AdhA and cysteine proteinase YraA by the MerR-family regulator YraB (AdhR). - Nguyen, T. T.; Eiamphungporn, W.; Mader, U.; Liebeke, M.; Lalk, M.; Hecker, M.; Helmann, J. D.; Antelmann, H. (Mol Microbiol, 2009)
Quinones and alpha,beta-unsaturated carbonyls are naturally occurring electrophiles that target cysteine residues via thiol-(S)-alkylation. We analysed the global expression profile of Bacillus subtilis to the toxic carbonyls methylglyoxal (MG) and formaldehyde (FA). Both carbonyl compounds cause a stress response characteristic for thiol-reactive electrophiles as revealed by the induction of the Spx, CtsR, CymR, PerR, ArsR, CzrA, CsoR and SigmaD regulons. MG and FA triggered also a SOS response which indicates DNA damage. Protection against FA is mediated by both the hxlAB operon, encoding the ribulose monophosphate pathway for FA fixation, and a thiol-dependent formaldehyde dehydrogenase (AdhA) and DJ-1/PfpI-family cysteine proteinase (YraA). The adhA-yraA operon and the yraC gene, encoding a gamma-carboxymuconolactone decarboxylase, are positively regulated by the MerR-family regulator, YraB(AdhR). AdhR binds specifically to its target promoters which contain a 7-4-7 inverted repeat (CTTAAAG-N4-CTTTAAG) between the -35 and -10 elements. Activation of adhA-yraA transcription by AdhR requires the conserved Cys52 residue in vivo. We speculate that AdhR is redox-regulated via thiol-(S)-alkylation by aldehydes and that AdhA and YraA are specifically involved in reduction of aldehydes and degradation or repair of damaged thiol-containing proteins respectively.
Keywords: Aldehyde Oxidoreductases/genetics/*metabolism; Bacillus subtilis/drug effects/*enzymology/genetics; Bacterial Proteins/genetics/*metabolism; Cluster Analysis; Cysteine Endopeptidases/genetics/*metabolism; Formaldehyde/pharmacology; Gene Expression Profiling; Gene Expression Regulation, Bacterial; Genes, Bacterial; Mutation; Oligonucleotide Array Sequence Analysis; Operon; Promoter Regions, Genetic; Proteome/metabolism; Pyruvaldehyde/pharmacology; RNA, Bacterial/genetics; Regulon; Transcription, Genetic

Overflow of a hyper-produced secretory protein from the Bacillus Sec pathway into the Tat pathway for protein secretion as revealed by proteogenomics. - Kouwen, T. R.; van der Ploeg, R.; Antelmann, H.; Hecker, M.; Homuth, G.; Mader, U.; van Dijl, J. M. (Proteomics, 2009)
Bacteria secrete numerous proteins into their environment for growth and survival under complex and ever-changing conditions. The highly different characteristics of secreted proteins pose major challenges to the cellular protein export machinery and, accordingly, different pathways have evolved. While the main secretion (Sec) pathway transports proteins in an unfolded state, the twin-arginine translocation (Tat) pathway transports folded proteins. To date, these pathways were believed to act in strictly independent ways. Here, we have employed proteogenomics to investigate the secretion mechanism of the esterase LipA of Bacillus subtilis, using a serendipitously obtained hyper-producing strain. While LipA is secreted Sec-dependently under standard conditions, hyper-produced LipA is secreted predominantly Tat-dependently via an unprecedented overflow mechanism. Two previously identified B. subtilis Tat substrates, PhoD and YwbN, require each a distinct Tat translocase for secretion. In contrast, hyper-produced LipA is transported by both Tat translocases of B. subtilis, showing that they have distinct but overlapping specificities. The identified overflow secretion mechanism for LipA focuses interest on the possibility that secretion pathway choice can be determined by environmental and intracellular conditions. This may provide an explanation for the previous observation that many Sec-dependently transported proteins have potential twin-arginine signal peptides for export via the Tat pathway.
Keywords: Bacillus subtilis/genetics/*metabolism; Bacterial Proteins/genetics/*metabolism; Cloning, Molecular; Electrophoresis, Gel, Two-Dimensional; Genomics/methods; Membrane Transport Proteins/genetics/*metabolism; Protein Transport/genetics/physiology; Proteomics/methods; Secretory Pathway/genetics/*physiology

MscL of Bacillus subtilis prevents selective release of cytoplasmic proteins in a hypotonic environment. - Kouwen, T. R.; Antelmann, H.; van der Ploeg, R.; Denham, E. L.; Hecker, M.; van Dijl, J. M. (Proteomics, 2009)
Bacillus subtilis serves as an excellent model to study protein secretion at a proteomic scale. Most of the extracellular proteins are exported from the cytoplasm via the secretory (Sec) pathway. Despite extensive studies, the secretion mechanisms of about 25% of the extracellular proteins are unknown. This suggests that B. subtilis makes use of alternative mechanisms to release proteins into its environment. In search for novel pathways, which contribute to biogenesis of the B. subtilis exoproteome, we investigated a possible role of the large conductance mechanosensitive channel protein MscL. We compared protein secretion by MscL deficient and proficient B. subtilis cells. MscL did not contribute to secretion under standard growth conditions. Unexpectedly, we discovered that under hypo-osmotic shock conditions specific, normally cytoplasmic proteins were released by mscL mutant cells. This protein release was selective since not all cytoplasmic proteins were equally well released. We established that this protein release by mscL mutant cells cannot be attributed to cell death or lysis. The presence of MscL, therefore, seems to prevent the specific release of cytoplasmic proteins by B. subtilis during hypo-osmotic shock. Our unprecedented findings imply that an unidentified system for selective release of cytoplasmic proteins is active in B. subtilis.
Keywords: Apoptosis; Bacillus subtilis/genetics/*metabolism; Bacterial Proteins/genetics/*metabolism; Electrophoresis, Gel, Two-Dimensional; Ion Channels/genetics/*metabolism; Mechanotransduction, Cellular/genetics/*physiology; Microbial Viability; Microscopy, Fluorescence; Mutation; Osmotic Pressure/physiology; Proteomics; Secretory Pathway/genetics/physiology; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization

In vitro phosphorylation of key metabolic enzymes from Bacillus subtilis: PrkC phosphorylates enzymes from different branches of basic metabolism. - Pietack, N.; Becher, D.; Schmidl, S. R.; Saier, M. H.; Hecker, M.; Commichau, F. M.; Stulke, J. (J Mol Microbiol Biotechnol, 2010)
Phosphorylation is an important mechanism of protein modification. In the Gram-positive soil bacterium Bacillus subtilis, about 5% of all proteins are subject to phosphorylation, and a significant portion of these proteins is phosphorylated on serine or threonine residues. We were interested in the regulation of the basic metabolism in B. subtilis. Many enzymes of the central metabolic pathways are phosphorylated in this organism. In an attempt to identify the responsible protein kinase(s), we identified four candidate kinases, among them the previously studied kinase PrkC. We observed that PrkC is indeed able to phosphorylate several metabolic enzymes in vitro. Determination of the phosphorylation sites revealed a remarkable preference of PrkC for threonine residues. Moreover, PrkC often used several phosphorylation sites in one protein. This feature of PrkC-dependent protein phosphorylation resembles the multiple phosphorylations often observed in eukaryotic proteins. The HPr protein of the phosphotransferase system is one of the proteins phosphorylated by PrkC, and PrkC phosphorylates a site (Ser-12) that has recently been found to be phosphorylated in vivo. The agreement between in vivo and in vitro phosphorylation of HPr on Ser-12 suggests that our in vitro observations reflect the events that take place in the cell.
Keywords: Bacillus subtilis/*enzymology; Bacterial Proteins/*isolation & purification/*metabolism; Phosphoenolpyruvate Sugar Phosphotransferase System/isolation & purification/metabolism; Phosphorylation; Protein Kinase C/isolation & purification/metabolism; *Protein Processing, Post-Translational; Serine/metabolism; Threonine/metabolism

MINOMICS: visualizing prokaryote transcriptomics and proteomics data in a genomic context. - Brouwer, R. W.; van Hijum, S. A.; Kuipers, O. P. (Bioinformatics, 2009)
We have developed MINOMICS, a tool that allows facile and in-depth visualization of prokaryotic transcriptomic and proteomic data in conjunction with genomics data. MINOMICS generates interactive linear genome maps in which multiple experimental datasets are displayed together with operon, regulatory motif, transcriptional promoter and transcriptional terminator information. AVAILABILITY: MINOMICS is freely accessible at http://www.minomics.nl
Keywords: Computational Biology/*methods; *Gene Expression Profiling; Genome/*genetics; Internet; Prokaryotic Cells/*metabolism; *Proteomics; *Software

Novel activities of glycolytic enzymes in Bacillus subtilis: interactions with essential proteins involved in mRNA processing. - Commichau, F. M.; Rothe, F. M.; Herzberg, C.; Wagner, E.; Hellwig, D.; Lehnik-Habrink, M.; Hammer, E.; Volker, U.; Stulke, J. (Mol Cell Proteomics, 2009)
Glycolysis is one of the most important metabolic pathways in heterotrophic organisms. Several genes encoding glycolytic enzymes are essential in many bacteria even under conditions when neither glycolytic nor gluconeogenic activities are required. In this study, a screening for in vivo interaction partners of glycolytic enzymes of the soil bacterium Bacillus subtilis was used to provide a rationale for essentiality of glycolytic enzymes. Glycolytic enzymes proved to be in close contact with several other proteins, among them a high proportion of essential proteins. Among these essential interaction partners, other glycolytic enzymes were most prominent. Two-hybrid studies confirmed interactions of phosphofructokinase with phosphoglyceromutase and enolase. Such a complex of glycolytic enzymes might allow direct substrate channeling of glycolytic intermediates. Moreover we found associations of glycolytic enzymes with several proteins known or suspected to be involved in RNA processing and degradation. One of these proteins, Rny (YmdA), which has so far not been functionally characterized, is required for the processing of the mRNA of the glycolytic gapA operon. Two-hybrid analyses confirmed the interactions between the glycolytic enzymes phosphofructokinase and enolase and the enzymes involved in RNA processing, RNase J1, Rny, and polynucleotide phosphorylase. Moreover RNase J1 interacts with its homologue RNase J2. We suggest that this complex of mRNA processing and glycolytic enzymes is the B. subtilis equivalent of the RNA degradosome. Our findings suggest that the functional interaction of glycolytic enzymes with essential proteins may be the reason why they are indispensable.
Keywords: Bacillus subtilis/*enzymology; Base Sequence; Blotting, Northern; DNA Primers; Electrophoresis, Polyacrylamide Gel; Glycolysis; Phosphofructokinases/*metabolism; Phosphoglycerate Mutase/*metabolism; Phosphopyruvate Hydratase/*metabolism; Polymerase Chain Reaction; *RNA Processing, Post-Transcriptional; RNA, Messenger/genetics/*metabolism; Two-Hybrid System Techniques

Heterochronic phosphorelay gene expression as a source of heterogeneity in Bacillus subtilis spore formation. - de Jong, I. G.; Veening, J. W.; Kuipers, O. P. (J Bacteriol, 2010)
In response to limiting nutrient sources and cell density signals, Bacillus subtilis can differentiate and form highly resistant endospores. Initiation of spore development is governed by the master regulator Spo0A, which is activated by phosphorylation via a multicomponent phosphorelay. Interestingly, only part of a clonal population will enter this developmental pathway, a phenomenon known as sporulation bistability or sporulation heterogeneity. How sporulation heterogeneity is established is largely unknown. To investigate the origins of sporulation heterogeneity, we constructed promoter-green fluorescent protein (GFP) fusions to the main phosphorelay genes and perturbed their expression levels. Using time-lapse fluorescence microscopy and flow cytometry, we showed that expression of the phosphorelay genes is distributed in a unimodal manner. However, single-cell trajectories revealed that phosphorelay gene expression is highly dynamic or "heterochronic" between individual cells and that stochasticity of phosphorelay gene transcription might be an important regulatory mechanism for sporulation heterogeneity. Furthermore, we showed that artificial induction or depletion of the phosphorelay phosphate flow results in loss of sporulation heterogeneity. Our data suggest that sporulation heterogeneity originates from highly dynamic and variable gene activity of the phosphorelay components, resulting in large cell-to-cell variability with regard to phosphate input into the system. These transcriptional and posttranslational differences in phosphorelay activity appear to be sufficient to generate a heterogeneous sporulation signal without the need of the positive-feedback loop established by the sigma factor SigH.
Keywords: Bacillus subtilis/genetics/growth & development/*physiology; Bacterial Proteins/genetics/metabolism; Flow Cytometry; Gene Expression Regulation, Bacterial/genetics/*physiology; Microscopy, Fluorescence; Models, Biological; Phosphoprotein Phosphatases/genetics/metabolism; Protein Kinases/genetics/metabolism; Spores, Bacterial/genetics/*growth & development; Transcription Factors/genetics/metabolism

A community-curated consensual annotation that is continuously updated: the Bacillus subtilis centred wiki SubtiWiki. - Florez, L. A.; Roppel, S. F.; Schmeisky, A. G.; Lammers, C. R.; Stulke, J. (Database (Oxford), 2009)
Bacillus subtilis is the model organism for Gram-positive bacteria, with a large amount of publications on all aspects of its biology. To facilitate genome annotation and the collection of comprehensive information on B. subtilis, we created SubtiWiki as a community-oriented annotation tool for information retrieval and continuous maintenance. The wiki is focused on the needs and requirements of scientists doing experimental work. This has implications for the design of the interface and for the layout of the individual pages. The pages can be accessed primarily by the gene designations. All pages have a similar flexible structure and provide links to related gene pages in SubtiWiki or to information in the World Wide Web. Each page gives comprehensive information on the gene, the encoded protein or RNA as well as information related to the current investigation of the gene/protein. The wiki has been seeded with information from key publications and from the most relevant general and B. subtilis-specific databases. We think that SubtiWiki might serve as an example for other scientific wikis that are devoted to the genes and proteins of one organism.Database URL: The wiki can be accessed at http://subtiwiki.uni-goettingen.de/

The large mechanosensitive channel MscL determines bacterial susceptibility to the bacteriocin sublancin 168. - Kouwen, T. R.; Trip, E. N.; Denham, E. L.; Sibbald, M. J.; Dubois, J. Y.; van Dijl, J. M. (Antimicrob Agents Chemother, 2009)
Bacillus subtilis strain 168 produces the extremely stable and broad-spectrum lantibiotic sublancin 168. Known sublancin 168-susceptible organisms include important pathogens, such as Staphylococcus aureus. Nevertheless, since its discovery, the mode of action of sublancin 168 has remained elusive. The present studies were, therefore, aimed at the identification of cellular determinants for bacterial susceptibility toward sublancin 168. Growth inhibition and competition assays on plates and in liquid cultures revealed that sublancin 168-mediated growth inhibition of susceptible B. subtilis and S. aureus cells is affected by the NaCl concentration in the growth medium. Added NaCl did not influence the production, activity, or stability of sublancin 168 but, instead, lowered the susceptibility of sensitive cells toward this lantibiotic. Importantly, the susceptibility of B. subtilis and S. aureus cells toward sublancin 168 was shown to depend on the presence of the large mechanosensitive channel of conductance MscL. In contrast, MscL was not involved in susceptibility toward the bacteriocin nisin or Pep5. Taken together, our unprecedented results demonstrate that MscL is a critical and specific determinant in bacterial sublancin 168 susceptibility that may serve either as a direct target for this lantibiotic or as a gate of entry to the cytoplasm.
Keywords: Bacillus subtilis/*drug effects; Bacterial Proteins/*physiology; Bacteriocins/*pharmacology; Glycopeptides; Mechanotransduction, Cellular/*physiology; Microbial Sensitivity Tests; Peptides/*pharmacology; Sodium Chloride/pharmacology; Staphylococcus aureus/*drug effects

Applications of thiol-disulfide oxidoreductases for optimized in vivo production of functionally active proteins in Bacillus. - Kouwen, T. R.; van Dijl, J. M. (Appl Microbiol Biotechnol, 2009)
Bacillus subtilis is a well-established cellular factory for proteins and fine chemicals. In particular, the direct secretion of proteinaceous products into the growth medium greatly facilitates their downstream processing, which is an important advantage of B. subtilis over other biotechnological production hosts, such as Escherichia coli. The application spectrum of B. subtilis is, however, often confined to proteins from Bacillus or closely related species. One of the major reasons for this (current) limitation is the inefficient formation of disulfide bonds, which are found in many, especially eukaryotic, proteins. Future exploitation of B. subtilis to fulfill the ever-growing demand for pharmaceutical and other high-value proteins will therefore depend on overcoming this particular hurdle. Recently, promising advances in this area have been achieved, which focus attention on the need to modulate the cellular levels and activity of thiol-disulfide oxidoreductases (TDORs). These TDORs are enzymes that control the cleavage or formation of disulfide bonds. This review will discuss readily applicable approaches for TDOR modulation and aims to provide leads for further improvement of the Bacillus cell factory for production of disulfide bond-containing proteins.
Keywords: Bacillus subtilis/*enzymology/*metabolism; Bacterial Proteins/*metabolism; Protein Disulfide Reductase (Glutathione)/*metabolism

Contributions of the pre- and pro-regions of a Staphylococcus hyicus lipase to secretion of a heterologous protein by Bacillus subtilis. - Kouwen, T. R.; Nielsen, A. K.; Denham, E. L.; Dubois, J. Y.; Dorenbos, R.; Rasmussen, M. D.; Quax, W. J.; Freudl, R.; van Dijl, J. M. (Appl Environ Microbiol, 2010)
Bacillus subtilis is a well-established cell factory for efficient secretion of many biotechnologically relevant enzymes that are naturally produced by it or related organisms. However, the use of B. subtilis as a host for production of heterologous secretory proteins can be complicated by problems related to inefficient translocation of the foreign proteins across the plasma membrane or to inefficient release of the exported proteins from the cell surface into the surrounding medium. Therefore, there is a clear need for tools that allow more efficient membrane targeting, translocation, and release during the production of these proteins. In the present study, we investigated the contributions of the pre (pre(lip)) and pro (pro(lip)) sequences of a Staphylococcus hyicus lipase to secretion of a heterologous protein, the alkaline phosphatase PhoA of Escherichia coli, by B. subtilis. The results indicate that the presence of the pro(lip)-peptide, in combination with the lipase signal peptide (pre(lip)), contributes significantly to the efficient secretion of PhoA by B. subtilis and that pre(lip) directs PhoA secretion more efficiently than the authentic signal peptide of PhoA. Genome-wide transcriptional analyses of the host cell responses indicate that, under the conditions tested, no known secretion or membrane-cell wall stress responses were provoked by the production of PhoA with any of the pre- and pro-region sequences used. Our data underscore the view that the pre-pro signals of the S. hyicus lipase are very useful tools for secretion of heterologous proteins in B. subtilis.
Keywords: ATP-Binding Cassette Transporters/genetics/metabolism; Adenosine Triphosphatases/genetics/metabolism; Alkaline Phosphatase/genetics/*metabolism; Amino Acid Sequence; Bacillus subtilis/genetics/*metabolism; Bacterial Proteins/chemistry/genetics; Biotechnology/methods; Cell Membrane/genetics/metabolism; Cloning, Molecular; Endopeptidase Clp/genetics/metabolism; Escherichia coli Proteins/genetics/*metabolism; Lipase/*chemistry/genetics; Protein Folding; Protein Sorting Signals/genetics; Protein Transport/genetics; Recombinant Fusion Proteins/genetics/metabolism; Serine Endopeptidases/genetics/metabolism; Staphylococcus/*enzymology/genetics/metabolism; alpha-Amylases/metabolism

Connecting parts with processes: SubtiWiki and SubtiPathways integrate gene and pathway annotation for Bacillus subtilis. - Lammers, C. R.; Florez, L. A.; Schmeisky, A. G.; Roppel, S. F.; Mader, U.; Hamoen, L.; Stulke, J. (Microbiology (Reading), 2010)
Bacillus subtilis is the model organism for a large group of Gram-positive bacteria, the Firmicutes. Several online databases have been established over time to manage its genetic and metabolic information, but they differ greatly in their rate of update and their focus on B. subtilis. Therefore, a European systems biology consortium called for an integrated solution that empowers its users to enrich online content. To meet this goal we created SubtiWiki and SubtiPathways, two complementary online tools for gene and pathway information on B. subtilis 168. SubtiWiki (http://subtiwiki.uni-goettingen.de/ ) is a scientific wiki for all genes of B. subtilis and their protein or RNA products. Each gene page contains a summary of the most important information; sections on the gene, its product and expression; sections concerning biological materials and laboratories; and a list of references. SubtiWiki has been seeded with key content and can be extended by any researcher after a simple registration, thus keeping it always up to date. As a complement, SubtiPathways (http://subtipathways.uni-goettingen.de/) is an online tool for navigation of the metabolism of B. subtilis and its regulation. Each SubtiPathways diagram presents a metabolic pathway with its participating enzymes, together with the regulatory mechanisms that act on their expression and activity, in an intuitive interface that is based on Google Maps. Together, SubtiWiki and SubtiPathways provide an integrated view of the processes that make up B. subtilis and its components, making it the most comprehensive web resource for B. subtilis researchers.
Keywords: Bacillus subtilis/*genetics; *Database Management Systems; Databases, Genetic; Genes, Bacterial; *Software; User-Computer Interface

A rapid microwave-assisted derivatization of bacterial metabolome samples for gas chromatography/mass spectrometry analysis. - Liebeke, M.; Wunder, A.; Lalk, M. (Anal Biochem, 2010)
Analysis of metabolome samples by gas chromatography/mass spectrometry requires a comprehensive derivatization method to afford quantitative and qualitative information of a complex biological sample. Here we describe an extremely time-effective microwave-assisted protocol for the commonly used methoxyamine and N-methyl-N-trimethylsilylfluoracetamide silylation method of primary metabolites. Our studies show that microwave irradiation can decrease the sample preparation time from approximately 120 min to 6 min without loss of either qualitative or quantitative information for the tested synthetic metabolite mixtures and microbial-derived metabolome samples collected from Bacillus subtilis and Staphylococcus aureus. Comparisons of metabolic fingerprints and selected metabolites show no noticeable differences compared with the commonly used heating block methods.
Keywords: Bacillus subtilis/*metabolism; Gas Chromatography-Mass Spectrometry/economics/*methods; *Metabolome; Metabolomics/economics/*methods; Microwaves; Staphylococcus aureus/*metabolism; Time Factors

Diamide triggers mainly S Thiolations in the cytoplasmic proteomes of Bacillus subtilis and Staphylococcus aureus. - Pother, D. C.; Liebeke, M.; Hochgrafe, F.; Antelmann, H.; Becher, D.; Lalk, M.; Lindequist, U.; Borovok, I.; Cohen, G.; Aharonowitz, Y.; Hecker, M. (J Bacteriol, 2009)
Glutathione constitutes a key player in the thiol redox buffer in many organisms. However, the gram-positive bacteria Bacillus subtilis and Staphylococcus aureus lack this low-molecular-weight thiol. Recently, we identified S-cysteinylated proteins in B. subtilis after treatment of cells with the disulfide-generating electrophile diamide. S cysteinylation is thought to protect protein thiols against irreversible oxidation to sulfinic and sulfonic acids. Here we show that S thiolation occurs also in S. aureus proteins after exposure to diamide. We further analyzed the formation of inter- and intramolecular disulfide bonds in cytoplasmic proteins using diagonal nonreducing/reducing sodium dodecyl sulfate gel electrophoresis. However, only a few proteins were identified that form inter- or intramolecular disulfide bonds under control and diamide stress conditions in B. subtilis and S. aureus. Depletion of the cysteine pool was concomitantly measured in B. subtilis using a metabolomics approach. Thus, the majority of reversible thiol modifications that were previously detected by two-dimensional gel fluorescence-based thiol modification assay are most likely based on S thiolations. Finally, we found that a glutathione-producing B. subtilis strain which expresses the Listeria monocytogenes gshF gene did not show enhanced oxidative stress resistance compared to the wild type.
Keywords: Bacillus subtilis/*drug effects/*metabolism; Bacterial Proteins/*metabolism; Cytoplasm/metabolism; Diamide/*metabolism; Oxidative Stress; Protein Processing, Post-Translational; Staphylococcus aureus/*drug effects/*metabolism; Stress, Physiological; Sulfhydryl Compounds/*metabolism

Mechanisms and evolution of control logic in prokaryotic transcriptional regulation. - van Hijum, S. A.; Medema, M. H.; Kuipers, O. P. (Microbiol Mol Biol Rev, 2009)
A major part of organismal complexity and versatility of prokaryotes resides in their ability to fine-tune gene expression to adequately respond to internal and external stimuli. Evolution has been very innovative in creating intricate mechanisms by which different regulatory signals operate and interact at promoters to drive gene expression. The regulation of target gene expression by transcription factors (TFs) is governed by control logic brought about by the interaction of regulators with TF binding sites (TFBSs) in cis-regulatory regions. A factor that in large part determines the strength of the response of a target to a given TF is motif stringency, the extent to which the TFBS fits the optimal TFBS sequence for a given TF. Advances in high-throughput technologies and computational genomics allow reconstruction of transcriptional regulatory networks in silico. To optimize the prediction of transcriptional regulatory networks, i.e., to separate direct regulation from indirect regulation, a thorough understanding of the control logic underlying the regulation of gene expression is required. This review summarizes the state of the art of the elements that determine the functionality of TFBSs by focusing on the molecular biological mechanisms and evolutionary origins of cis-regulatory regions.
Keywords: *Bacteria/genetics/metabolism; Computational Biology; DNA, Bacterial/genetics/metabolism; Evolution, Molecular; *Gene Expression Regulation, Bacterial; Genome, Bacterial; Promoter Regions, Genetic; Transcription Factors/metabolism; *Transcriptional Activation

Protein transport across and into cell membranes in bacteria and archaea. - Yuan, J.; Zweers, J. C.; van Dijl, J. M.; Dalbey, R. E. (Cell Mol Life Sci, 2010)
In the three domains of life, the Sec, YidC/Oxa1, and Tat translocases play important roles in protein translocation across membranes and membrane protein insertion. While extensive studies have been performed on the endoplasmic reticular and Escherichia coli systems, far fewer studies have been done on archaea, other Gram-negative bacteria, and Gram-positive bacteria. Interestingly, work carried out to date has shown that there are differences in the protein transport systems in terms of the number of translocase components and, in some cases, the translocation mechanisms and energy sources that drive translocation. In this review, we will describe the different systems employed to translocate and insert proteins across or into the cytoplasmic membrane of archaea and bacteria.
Keywords: Adenosine Triphosphatases/chemistry/*metabolism; Archaea/*enzymology; Archaeal Proteins/chemistry/*metabolism; Bacteria/*enzymology; Bacterial Proteins/chemistry/*metabolism; Cell Membrane/*metabolism; Membrane Transport Proteins/chemistry/*metabolism; Protein Transport; SEC Translocation Channels; SecA Proteins

Stress-responsive systems set specific limits to the overproduction of membrane proteins in Bacillus subtilis. - Zweers, J. C.; Wiegert, T.; van Dijl, J. M. (Appl Environ Microbiol, 2009)
Essential membrane proteins are generally recognized as relevant potential drug targets due to their exposed localization in the cell envelope. Unfortunately, high-level production of membrane proteins for functional and structural analyses is often problematic. This is mainly due to their high overall hydrophobicity. To develop new concepts for membrane protein overproduction, we investigated whether the biogenesis of overproduced membrane proteins is affected by stress response-related proteolytic systems in the membrane. For this purpose, the well-established expression host Bacillus subtilis was used to overproduce eight essential membrane proteins from B. subtilis and Staphylococcus aureus. The results show that the sigma(W) regulon (responding to cell envelope perturbations) and the CssRS two-component regulatory system (responding to unfolded exported proteins) set critical limits to membrane protein production in large quantities. The identified sigW or cssRS mutant B. subtilis strains with significantly improved capacity for membrane protein production are interesting candidate expression hosts for fundamental research and biotechnological applications. Importantly, our results pinpoint the interdependent expression and function of membrane-associated proteases as key parameters in bacterial membrane protein production.
Keywords: Bacillus subtilis/*genetics/*metabolism; Bacterial Proteins/*biosynthesis/genetics/metabolism; Gene Deletion; *Gene Expression; *Gene Expression Regulation, Bacterial; Membrane Proteins/*biosynthesis; Models, Biological; Protein Kinases/genetics/metabolism; Sigma Factor/genetics/metabolism; Signal Transduction; *Stress, Physiological; Transcription Factors/genetics/metabolism

Functional dissection of a trigger enzyme: mutations of the bacillus subtilis glutamate dehydrogenase RocG that affect differentially its catalytic activity and regulatory properties. - Gunka, K.; Newman, J. A.; Commichau, F. M.; Herzberg, C.; Rodrigues, C.; Hewitt, L.; Lewis, R. J.; Stulke, J. (J Mol Biol, 2010)
Any signal transduction requires communication between a sensory component and an effector. Some enzymes engage in signal perception and transduction, as well as in catalysis, and these proteins are known as "trigger" enzymes. In this report, we detail the trigger properties of RocG, the glutamate dehydrogenase of Bacillus subtilis. RocG not only deaminates the key metabolite glutamate to form alpha-ketoglutarate but also interacts directly with GltC, a LysR-type transcription factor that regulates glutamate biosynthesis from alpha-ketoglutarate, thus linking the two metabolic pathways. We have isolated mutants of RocG that separate the two functions. Several mutations resulted in permanent inactivation of GltC as long as a source of glutamate was present. These RocG proteins have lost their ability to catabolize glutamate due to a strongly reduced affinity for glutamate. The second class of mutants is exemplified by the replacement of aspartate residue 122 by asparagine. This mutant protein has retained enzymatic activity but has lost the ability to control the activity of GltC. Crystal structures of glutamate dehydrogenases that permit a molecular explanation of the properties of the various mutants are presented. Specifically, we may propose that D122N replacement affects the surface of RocG. Our data provide evidence for a correlation between the enzymatic activity of RocG and its ability to inactivate GltC, and thus give insights into the mechanism that couples the enzymatic activity of a trigger enzyme to its regulatory function.
Keywords: Bacillus subtilis/chemistry/*enzymology/genetics/*physiology; Bacterial Proteins/chemistry/genetics/*metabolism; Crystallography, X-Ray; DNA Mutational Analysis; Glutamate Dehydrogenase/chemistry/genetics/*metabolism; Glutamic Acid/*metabolism; Ketoglutaric Acids/metabolism; Models, Biological; Models, Molecular; *Mutation, Missense; Protein Structure, Tertiary; Repressor Proteins/metabolism; *Signal Transduction; Trans-Activators/metabolism

Physiological proteomics and stress/starvation responses in Bacillus subtilis and Staphylococcus aureus. - Hecker, M.; Reder, A.; Fuchs, S.; Pagels, M.; Engelmann, S. (Res Microbiol, 2009)
Gel-based proteomics is a useful approach for visualizing the responses of bacteria to stress and starvation stimuli. In order to face stress/starvation, bacteria have developed very complicated gene expression networks. A proteomic view of stress/starvation responses, however, is only a starting point which should promote follow-up studies aimed at the comprehensive description of single regulons, their signal transduction pathways on the one hand, and their adaptive functions on the other, and finally their integration into complex gene expression networks. This "road map of physiological proteomics" will be demonstrated for the general stress regulon controlled by sigma(B) in Bacillus subtilis and the oxygen starvation response with Rex as a master regulator in Staphylococcus aureus.
Keywords: Bacillus subtilis/*physiology; Bacterial Proteins/physiology; Gene Expression Regulation, Bacterial; Gene Regulatory Networks; Metabolic Networks and Pathways; *Proteomics; Sigma Factor/physiology; Signal Transduction; Staphylococcus aureus/*physiology; *Stress, Physiological

TFInfer: a tool for probabilistic inference of transcription factor activities. - Asif, H. M.; Rolfe, M. D.; Green, J.; Lawrence, N. D.; Rattray, M.; Sanguinetti, G. (Bioinformatics, 2010)
SUMMARY: TFInfer is a novel open access, standalone tool for genome-wide inference of transcription factor activities from gene expression data. Based on an earlier MATLAB version, the software has now been extended in a number of ways. It has been significantly optimised in terms of performance, and it was given novel functionality, by allowing the user to model both time series and data from multiple independent conditions. With a full documentation and intuitive graphical user interface, together with an in-built data base of yeast and Escherichia coli transcription factors, the software does not require any mathematical or computational expertise to be used effectively. AVAILABILITY: http://homepages.inf.ed.ac.uk/gsanguin/TFInfer.html CONTACT: gsanguin@staffmail.ed.ac.uk SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Computational Biology; Databases, Factual; Escherichia coli/metabolism; Gene Expression; *Models, Statistical; *Software; Transcription Factors/*chemistry/metabolism; Yeasts/metabolism

Integration of sensitivity and bifurcation analysis to detect critical processes in a model combining signalling and cell population dynamics - Nikolov, S.; Lai, X.; Liebal, Ulf; Wolkenhauer, Olaf; Vera, J. (Int. J. of Systems Sc., 2010)
In this article we present and test a strategy to integrate, in a sequential manner, sensitivity analysis, bifurcation analysis and predictive simulations. Our strategy uses some of these methods in a coordinated way such that information, generated in one step, feeds into the definition of further analyses and helps refining the structure of the mathematical model. The aim of the method is to help in the designing of more informative predictive simulations, which focus on critical model parameters and the biological effects of their modulation. We tested our methodology with a multilevel model, accounting for the effect of erythropoietin (Epo)-mediated JAK2-STAT5 signalling in erythropoiesis. Our analysis revealed that time-delays associated with the proliferation-differentiation process are critical to induce pathological sustained oscillations, whereas the modulation of time-delays related to intracellular signalling and hypoxia-controlled physiological dynamics is not enough to induce self-oscillations in the system. Furthermore, our results suggest that the system is able to compensate (through the physiological-level feedback loop on hypoxia) the partial impairment of intracellular signalling processes (downregulation or overexpression of Epo receptor complex and STAT5), but cannot control impairment in some critical physiological-level processes, which provoke the emergence of pathological oscillations.

Dynamics of receptor and protein transducer homodimerisation - Vera, Julio; Millat, Thomas; Kolch, Walter; Wolkenhauer, Olaf (BMC Syst Biol, 2008)
Background Signalling pathways are complex systems in which not only simple monomeric molecules interact, but also more complex structures that include constitutive or induced protein assemblies. In particular, the hetero-and homo-dimerisation of proteins is a commonly encountered motif in signalling pathways. Several authors have suggested in recent times that dimerisation relates to a series of physical and biological outcomes used by the cell in the regulation of signal transduction.

Ein Beitrag zu einer Theorie lebender Zellen (A Contribution towards a Theory of Living Cells) - Wolkenhauer, Olaf; Hofmeyr, Jan-Hendrik S. (at - Automatisierungstechnik, 2008)
The following article describes systems biology as a merger of systems theory with cell biology. The role of modelling in the description of living cells is discussed. As an example, an abstract multiple-level model of a cell is developed. It is shown that a level of elementary cellular processes, realising cell functions, and a coordination-level are sufficient to create a system that is closed with respect to efficient causation. This form of self-organisation is thereby considered as basic criterion by which living systems, such as cells and organisms, are distinguished from machines and computers. Die causal closure of the cell is possible through the definition of the cell model as a cartesian closed category. It follows the conclusion that computer simulations of differential equations may be able to reproduce cellular processes but not this aspect of causal closure. The article ends with a discussion about the role of systems theory in the life sciences.

A proteomic and transcriptional view of acidogenic and solventogenic steady-state cells of Clostridium acetobutylicum in a chemostat culture - Janssen, Holger; Döring, Christina; Ehrenreich, Armin; Voigt, Birgit; Hecker, Michael; Bahl, Hubert; Fischer, Ralf-Jörg (Appl Microbiol Biotechnol, 2010)
The complex changes in the life cycle of Clostridium acetobutylicum, a promising biofuel producer, are not well understood. During exponential growth, sugars are fermented to acetate and butyrate, and in the transition phase, the metabolism switches to the production of the solvents acetone and butanol accompanied by the initiation of endospore formation. Using phosphate-limited chemostat cultures at pH 5.7, C. acetobutylicum was kept at a steady state of acidogenic metabolism, whereas at pH 4.5, the cells showed stable solvent production without sporulation. Novel proteome reference maps of cytosolic proteins from both acidogenesis and solventogenesis with a high degree of reproducibility were generated. Yielding a 21% coverage, 15 protein spots were specifically assigned to the acidogenic phase, and 29 protein spots exhibited a significantly higher abundance in the solventogenic phase. Besides well-known metabolic proteins, unexpected proteins were also identified. Among these, the two proteins CAP0036 and CAP0037 of unknown function were found as major striking indicator proteins in acidogenic cells. Proteome data were confirmed by genome-wide DNA microarray analyses of the identical cultures. Thus, a first systematic study of acidogenic and solventogenic chemostat cultures is presented, and similarities as well as differences to previous studies of batch cultures are discussed.

Physical interactions between tricarboxylic acid cycle enzymes in Bacillus subtilis: evidence for a metabolon. - Meyer, F. M.; Gerwig, J.; Hammer, E.; Herzberg, C.; Commichau, F. M.; Volker, U.; Stulke, J. (Metab Eng, 2011)
The majority of all proteins of a living cell is active in complexes rather than in an isolated way. These protein-protein interactions are of high relevance for many biological functions. In addition to many well established protein complexes an increasing number of protein-protein interactions, which form rather transient complexes has recently been discovered. The formation of such complexes seems to be a common feature especially for metabolic pathways. In the Gram-positive model organism Bacillus subtilis, we identified a protein complex of three citric acid cycle enzymes. This complex consists of the citrate synthase, the isocitrate dehydrogenase, and the malate dehydrogenase. Moreover, fumarase and aconitase interact with malate dehydrogenase and with each other. These five enzymes catalyze sequential reaction of the TCA cycle. Thus, this interaction might be important for a direct transfer of intermediates of the TCA cycle and thus for elevated metabolic fluxes via substrate channeling. In addition, we discovered a link between the TCA cycle and gluconeogenesis through a flexible interaction of two proteins: the association between the malate dehydrogenase and phosphoenolpyruvate carboxykinase is directly controlled by the metabolic flux. The phosphoenolpyruvate carboxykinase links the TCA cycle with gluconeogenesis and is essential for B. subtilis growing on gluconeogenic carbon sources. Only under gluconeogenic growth conditions an interaction of these two proteins is detectable and disappears under glycolytic growth conditions.
Keywords: Bacillus subtilis/*enzymology; Bacterial Proteins/*metabolism; Citric Acid Cycle/*physiology; Metabolome/*physiology; *Models, Biological; Multienzyme Complexes/*metabolism; Protein Interaction Mapping; Signal Transduction/*physiology

A mathematical analysis of nuclear intensity dynamics for Mig1-GFP under consideration of bleaching effects and background noise in Saccharomyces cerevisiae - Frey, Simone; Sott, Kristin; Smedh, Maria; Millat, Thomas; Dahl, Peter; Wolkenhauer, Olaf; Goksör, Mattias (Mol. BioSyst., 2011)
Fluorescence microscopy is an imaging technique that provides insights into signal transduction pathways through the generation of quantitative data, such as the spatiotemporal distribution of GFP-tagged proteins in signaling pathways. The data acquired are, however, usually a composition of both the GFP-tagged proteins of interest and of an autofluorescent background, which both undergo photobleaching during imaging. We here present a mathematical model based on ordinary differential equations that successfully describes the shuttling of intracellular Mig1-GFP under changing environmental conditions regarding glucose concentration. Our analysis separates the different bleaching rates of Mig1-GFP and background, and the background-to-Mig1-GFP ratio. By applying our model to experimental data, we can thus extract the Mig1-GFP signal from the overall acquired signal and investigate the influence of kinase and phosphatase on Mig1. We found a stronger regulation of Mig1 through its kinase than through its phosphatase when controlled by the glucose concentration, with a constant (de)phosphorylation rate independent of the glucose concentration. By replacing the term for decreasing excited Mig1-GFP concentration with a constant, we were able to reconstruct the dynamics of Mig1-GFP, as it would occur without bleaching and background noise. Our model effectively demonstrates how data, acquired with an optical microscope, can be processed and used for a systems biology analysis of signal transduction pathways.

Characterization of three lactic acid bacteria and their isogenic ldh deletion mutants shows optimization for YATP (cell mass produced per mole of ATP) at their physiological pHs. - Fiedler, T.; Bekker, M.; Jonsson, M.; Mehmeti, I.; Pritzschke, A.; Siemens, N.; Nes, I.; Hugenholtz, J.; Kreikemeyer, B. (Appl Environ Microbiol, 2011)
Several lactic acid bacteria use homolactic acid fermentation for generation of ATP. Here we studied the role of the lactate dehydrogenase enzyme on the general physiology of the three homolactic acid bacteria Lactococcus lactis, Enterococcus faecalis, and Streptococcus pyogenes. Of note, deletion of the ldh genes hardly affected the growth rate in chemically defined medium under microaerophilic conditions. However, the growth rate was affected in rich medium. Furthermore, deletion of ldh affected the ability for utilization of various substrates as a carbon source. A switch to mixed acid fermentation was observed during glucose-limited continuous growth and was dependent on the growth rate for S. pyogenes and on the pH for E. faecalis. In S. pyogenes and L. lactis, a change in pH resulted in a clear change in Y(ATP) (cell mass produced per mole of ATP). The pH that showed the highest Y(ATP) corresponded to the pH of the natural habitat of the organisms.
Keywords: Adenosine Triphosphate/*metabolism; Biomass; Carbon/metabolism; Culture Media/chemistry; Enterococcus faecalis/*enzymology/genetics/growth & development/metabolism; Hydrogen-Ion Concentration; L-Lactate Dehydrogenase/*deficiency; Lactic Acid/*metabolism; Lactococcus lactis/*enzymology/genetics/growth & development/metabolism; *Sequence Deletion; Streptococcus pyogenes/*enzymology/genetics/growth & development/metabolism

A systems biology approach to investigate the effect of pH-induced gene regulation on solvent production by Clostridium acetobutylicum in continuous culture (BMC Syst Biol, 2011)
Background: Clostridium acetobutylicum is an anaerobic bacterium which is known for its solvent-producing capabilities, namely regarding the bulk chemicals acetone and butanol, the latter being a highly efficient biofuel. For butanol production by C. acetobutylicum to be optimized and exploited on an industrial scale, the effect of pH-induced gene regulation on solvent production by C. acetobutylicum in continuous culture must be understood as fully as possible.

Modeling of cellular processes: methods, data, and requirements. - Millat, T.; Wolkenhauer, O.; Fischer, R. J.; Bahl, H. (Methods Mol Biol, 2011)
Systems biology is a comprehensive quantitative analysis how the components of a biological system interact over time which requires an interdisciplinary team of investigators. System-theoretic methods are applied to investigate the system's behavior. Using known information about the considered system, a conceptual model is defined. It is transferred in a mathematical model that can be simulated (analytically or numerically) and analyzed using system-theoretic tools. Finally, simulation results are compared with experimental data. However, assumptions, approximations, and requirements to available experimental data are crucial ingredients of this systems biology workflow. Consequently, the modeling of cellular processes creates special demands on the design of experiments: the quality, the amount, and the completeness of data. The relation between models and data is discussed in this chapter. Thereby, we focus on the requirements on experimental data from the perspective of systems biology projects.
Keywords: Cells/*metabolism; Computer Simulation; *Databases as Topic; Enzymes/metabolism; Hydrogen-Ion Concentration; Kinetics; *Models, Biological; Molecular Dynamics Simulation; Stochastic Processes; Systems Biology/*methods

Transcript profiling and inference of Escherichia coli K-12 ArcA activity across the range of physiologically relevant oxygen concentrations. - Rolfe, M. D.; Ter Beek, A.; Graham, A. I.; Trotter, E. W.; Asif, H. M.; Sanguinetti, G.; de Mattos, J. T.; Poole, R. K.; Green, J. (J Biol Chem, 2011)
Oxygen availability is the major determinant of the metabolic modes adopted by Escherichia coli. Although much is known about E. coli gene expression and metabolism under fully aerobic and anaerobic conditions, the intermediate oxygen tensions that are encountered in natural niches are understudied. Here, for the first time, the transcript profiles of E. coli K-12 across the physiologically significant range of oxygen availabilities are described. These suggested a progressive switch to aerobic respiratory metabolism and a remodeling of the cell envelope as oxygen availability increased. The transcriptional responses were consistent with changes in the abundance of cytochrome bd and bo' and the outer membrane protein OmpW. The observed transcript and protein profiles result from changes in the activities of regulators that respond to oxygen itself or to metabolic and environmental signals that are sensitive to oxygen availability (aerobiosis). A probabilistic model (TFInfer) was used to predict the activity of the indirect oxygen-sensing two-component system ArcBA across the aerobiosis range. The model implied that the activity of the regulator ArcA correlated with aerobiosis but not with the redox state of the ubiquinone pool, challenging the idea that ArcA activity is inhibited by oxidized ubiquinone. The amount of phosphorylated ArcA correlated with the predicted ArcA activities and with aerobiosis, suggesting that fermentation product-mediated inhibition of ArcB phosphatase activity is the dominant mechanism for regulating ArcA activity under the conditions used here.
Keywords: Aerobiosis/physiology; Anaerobiosis/physiology; Bacterial Outer Membrane Proteins/genetics/*metabolism; Cytochrome b Group/genetics/metabolism; Cytochromes/genetics/metabolism; Electron Transport Chain Complex Proteins/genetics/metabolism; Escherichia coli K12/genetics/*metabolism; Escherichia coli Proteins/genetics/*metabolism; Membrane Proteins/genetics/metabolism; *Models, Biological; Oxidoreductases/genetics/metabolism; Oxygen/*metabolism; Phosphorylation/physiology; Protein Kinases/genetics/metabolism; Repressor Proteins/genetics/*metabolism; Transcription, Genetic/*physiology; Ubiquinone/genetics/metabolism

Insights into Streptococcus pyogenes pathogenesis from transcriptome studies. - Fiedler, T.; Sugareva, V.; Patenge, N.; Kreikemeyer, B. (Future Microbiol, 2010)
Streptococcus pyogenes (group A Streptococcus [GAS]) is a major human pathogen, causing diseases ranging from mild superficial infections of the skin and pharyngeal mucosal membrane, up to severe systemic and invasive diseases and autoimmune sequelae. The capability of GAS to cause this wide variety of infections is due to the expression of a large set of virulence factors, their concerted transcriptional regulation, and bacterial adaptation mechanisms to various host niches, which we are now beginning to understand on a molecular level. The addition of -omics technologies for GAS pathogenesis investigation, on top of traditional molecular methods, led to fast progress in understanding GAS pathogenesis mechanisms. This article focuses on differential transcriptional analysis performed on the bacterial side as well as on the host cell side. The microarray studies discussed provide new insight into the following five topics: gene-expression patterns under infection-relevant conditions, gene-expression patterns in mutant strains compared with wild-type strains, emergence of exceptionally fit GAS clones, gene-expression patterns of eukaryotic target and immune cells in response to GAS infection, and mechanisms underlying shifts from a pharyngeal to invasive GAS lifestyle.
Keywords: *Gene Expression Profiling; *Gene Expression Regulation, Bacterial; Humans; Streptococcus pyogenes/*pathogenicity; Virulence Factors/*biosynthesis

Stepwise mechanism for transcription fidelity. - Yuzenkova, Y.; Bochkareva, A.; Tadigotla, V. R.; Roghanian, M.; Zorov, S.; Severinov, K.; Zenkin, N. (BMC Biol, 2010)
BACKGROUND: Transcription is the first step of gene expression and is characterized by a high fidelity of RNA synthesis. During transcription, the RNA polymerase active centre discriminates against not just non-complementary ribo NTP substrates but also against complementary 2'- and 3'-deoxy NTPs. A flexible domain of the RNA polymerase active centre, the Trigger Loop, was shown to play an important role in this process, but the mechanisms of this participation remained elusive. RESULTS: Here we show that transcription fidelity is achieved through a multi-step process. The initial binding in the active centre is the major discrimination step for some non-complementary substrates, although for the rest of misincorporation events discrimination at this step is very poor. During the second step, non-complementary and 2'-deoxy NTPs are discriminated against based on differences in reaction transition state stabilization and partly in general base catalysis, for correct versus non-correct substrates. This step is determined by two residues of the Trigger Loop that participate in catalysis. In the following step, non-complementary and 2'-deoxy NTPs are actively removed from the active centre through a rearrangement of the Trigger Loop. The only step of discrimination against 3'-deoxy substrates, distinct from the ones above, is based on failure to orient the Trigger Loop catalytic residues in the absence of 3'OH. CONCLUSIONS: We demonstrate that fidelity of transcription by multi-subunit RNA polymerases is achieved through a stepwise process. We show that individual steps contribute differently to discrimination against various erroneous substrates. We define the mechanisms and contributions of each of these steps to the overall fidelity of transcription.
Keywords: DNA/*metabolism; DNA-Directed RNA Polymerases/*metabolism; Kinetics; *Models, Molecular; Nucleotides/metabolism; Transcription, Genetic/*physiology

Gene position within a long transcript as a determinant for stochastic switching in bacteria. - Veening, J. W.; Kuipers, O. P. (Mol Microbiol, 2010)
How cultures of genetically identical cells bifurcate into distinct phenotypic subpopulations under uniform growth conditions is an important question in developmental biology of relevance even to relatively simple developmental systems, such as spore formation in bacteria. A growing Bacillus subtilis culture consists of either cells that are motile and can swim or cells that are non-motile and are chained together. In this issue of Molecular Microbiology, Cozy and Kearns show that the probability of a cell to become motile depends on the position of the sigD gene within the long (27 kb) motility operon. sigD encodes the alternative sigma factor sigma(D) that, together with RNA polymerase, drives expression of genes required for cell separation and the assembly of flagella. sigD is the penultimate gene of the B. subtilis motility operon and, in the control strain approximately, 70% of the cells are motile. When sigD was moved upstream within the operon, a larger fraction of cells became motile (up to 100%). This study highlights that the position of a gene within an operon can have a large impact on the control of gene expression. Furthermore, it suggests that RNA polymerase processivity or mRNA turnover can play important roles as sources of noise in bacterial development, and that gene position might be an unrecognized and possibly widespread mechanism to regulate phenotypic variation.
Keywords: Bacillus subtilis/genetics/*physiology; Bacterial Proteins/biosynthesis/*genetics; *Gene Expression Regulation, Bacterial; *Gene Order; Locomotion; Operon; Sigma Factor/biosynthesis/*genetics; Transcription, Genetic

DnaA and ORC: more than DNA replication initiators. - Scholefield, G.; Veening, J. W.; Murray, H. (Trends Cell Biol, 2011)
Mutations in DNA replication initiator genes in both prokaryotes and eukaryotes lead to a pleiotropic array of phenotypes, including defects in chromosome segregation, cytokinesis, cell cycle regulation and gene expression. For years, it was not clear whether these diverse effects were indirect consequences of perturbed DNA replication, or whether they indicated that DNA replication initiator proteins had roles beyond their activity in initiating DNA synthesis. Recent work from a range of organisms has demonstrated that DNA replication initiator proteins play direct roles in many cellular processes, often functioning to coordinate the initiation of DNA replication with essential cell-cycle activities. The aim of this review is to highlight these new findings, focusing on the pathways and mechanisms utilized by DNA replication initiator proteins to carry out a diverse array of cellular functions.
Keywords: Animals; Bacterial Proteins/*metabolism; Cell Cycle; DNA/*metabolism; *DNA Replication; DNA-Binding Proteins/*metabolism; Humans; Origin Recognition Complex/*metabolism

Transformation of environmental Bacillus subtilis isolates by transiently inducing genetic competence. - Nijland, R.; Burgess, J. G.; Errington, J.; Veening, J. W. (PLoS One, 2010)
Domesticated laboratory strains of Bacillus subtilis readily take up and integrate exogenous DNA. In contrast, "wild" ancestors or Bacillus strains recently isolated from the environment can only be genetically modified by phage transduction, electroporation or protoplast transformation. Such methods are laborious, have a variable yield or cannot efficiently be used to alter chromosomal DNA. A major disadvantage of using laboratory strains is that they have often lost, or do not display ecologically relevant physiologies such as the ability to form biofilms. Here we present a method that allows genetic transformation by natural competence in several environmental isolates of B. subtilis. Competence in these strains was established by expressing the B. subtilis competence transcription factor ComK from an IPTG-inducible promoter construct present on an unstable plasmid. This transiently activates expression of the genes required for DNA uptake and recombination in the host strain. After transformation, the comK encoding plasmid is lost easily because of its intrinsic instability and the transformed strain returns to its wild state. Using this method, we have successfully generated mutants and introduced foreign DNA into a number of environmental isolates and also B. subtilis strain NCIB3610, which is widely used to study biofilm formation. Application of the same method to strains of B. licheniformis was unsuccessful. The efficient and rapid approach described here may facilitate genetic studies in a wider array of environmental B. subtilis strains.
Keywords: Bacillus subtilis/*genetics/metabolism; Bacterial Proteins/*genetics/metabolism; Biofilms; DNA, Bacterial/genetics; Environmental Microbiology; Flow Cytometry/methods; Gene Expression Regulation, Bacterial; Genetic Techniques; Green Fluorescent Proteins/metabolism; Models, Genetic; Plasmids/metabolism; Promoter Regions, Genetic; Species Specificity; Transcription Factors/*genetics/metabolism

Cellular localization of choline-utilization proteins in Streptococcus pneumoniae using novel fluorescent reporter systems. - Eberhardt, A.; Wu, L. J.; Errington, J.; Vollmer, W.; Veening, J. W. (Mol Microbiol, 2009)
The molecular mechanisms underlying cell growth, cell division and pathogenesis in Streptococcus pneumoniae are still not fully understood. Single-cell methodologies are potentially of great value to investigate S. pneumoniae cell biology. Here, we report the construction of novel plasmids for single and double cross-over integration of functional fusions to the gene encoding a fast folding variant of the green fluorescent protein (GFP) into the S. pneumoniae chromosome. We have also established a zinc-inducible system for the fine control of gfp-fusion gene expression and for protein depletion experiments in S. pneumoniae. Using this novel single cell toolkit, we have examined the cellular localization of the proteins involved in the essential process of choline decoration of S. pneumoniae teichoic acid. GFP fusions to LicA and LicC, enzymes involved in the activation of choline, showed a cytoplasmic distribution, as predicted from their primary sequences. A GFP fusion to the choline importer protein LicB showed clear membrane localization. GFP fusions to LicD1 and LicD2, enzymes responsible for loading of teichoic acid subunits with choline, are also membrane-associated, even though both proteins lack any obvious membrane spanning domain. These results indicate that the decoration of teichoic acid by the LicD enzymes is a membrane-associated process presumably occurring at lipid-linked teichoic acid precursors.
Keywords: Bacterial Proteins/*metabolism; Choline/*metabolism; Cloning, Molecular; Cytoplasm/metabolism; DNA, Bacterial/genetics; Gene Expression Regulation, Bacterial; Genes, Reporter; Green Fluorescent Proteins/*metabolism; Membrane Proteins/metabolism; Microscopy, Fluorescence; Plasmids; Streptococcus pneumoniae/*enzymology/genetics; Teichoic Acids/metabolism

A mechanism for cell cycle regulation of sporulation initiation in Bacillus subtilis. - Veening, J. W.; Murray, H.; Errington, J. (Genes Dev, 2009)
Coordination of DNA replication with cellular development is a crucial problem in most living organisms. Bacillus subtilis cells switch from vegetative growth to sporulation when starved. Sporulation normally occurs in cells that have stopped replicating DNA and have two completed chromosomes: one destined for the prespore and the other for the mother cell. It has long been recognized that there is a sensitive period in the cell cycle during which the initiation of spore development can be triggered, presumably to allow for the generation of exactly two complete chromosomes. However, the mechanism responsible for this has remained unclear. Here we show that the sda gene, previously identified as a checkpoint factor preventing sporulation in response to DNA damage, exerts cell cycle control over the initiation of sporulation. Expression of sda occurs in a pulsatile manner, with a burst of expression each cell cycle at the onset of DNA replication. Up-regulation of the intrinsically unstable Sda protein, which is dependent on the active form of the DNA replication initiator protein, DnaA, transiently inhibits the initiation of sporulation. This regulation avoids the generation of spore formers with replicating chromosomes, which would result in diploid or polyploid spores that we show have reduced viability.
Keywords: Bacillus subtilis/cytology/genetics/*growth & development/*metabolism; Bacterial Proteins/metabolism; Cell Cycle/physiology; Chromosomes, Bacterial; DNA Replication/physiology; DNA-Binding Proteins/metabolism; *Gene Expression Regulation, Bacterial; Phosphoprotein Phosphatases/metabolism; Serine Endopeptidases/metabolism; Spores, Bacterial/*growth & development; Trans-Activators/metabolism

Controlled interplay between trigger loop and Gre factor in the RNA polymerase active centre. - Roghanian, M.; Yuzenkova, Y.; Zenkin, N. (Nucleic Acids Res, 2011)
The highly processive transcription by multi-subunit RNA polymerases (RNAP) can be interrupted by misincorporation or backtracking events that may stall transcription or lead to erroneous transcripts. Backtracked/misincorporated complexes can be resolved via hydrolysis of the transcript. Here, we show that, in response to misincorporation and/or backtracking, the catalytic domain of RNAP active centre, the trigger loop (TL), is substituted by transcription factor Gre. This substitution turns off the intrinsic TL-dependent hydrolytic activity of RNAP active centre, and exchanges it to a far more efficient Gre-dependent mechanism of RNA hydrolysis. Replacement of the TL by Gre factor occurs only in backtracked/misincorporated complexes, and not in correctly elongating complexes. This controlled switching of RNAP activities allows the processivity of elongation to be unaffected by the hydrolytic activity of Gre, while ensuring efficient proofreading of transcription and resolution of backtracked complexes.
Keywords: Catalytic Domain; DNA-Directed RNA Polymerases/*chemistry/*metabolism; Hydrolysis; Models, Molecular; Transcription Factors/*metabolism; *Transcription, Genetic

Transcriptome, proteome, and metabolite analyses of a lactate dehydrogenase-negative mutant of Enterococcus faecalis V583. - Mehmeti, I.; Jonsson, M.; Fergestad, E. M.; Mathiesen, G.; Nes, I. F.; Holo, H. (Appl Environ Microbiol, 2011)
A constructed lactate dehydrogenase (LDH)-negative mutant of Enterococcus faecalis V583 grows at the same rate as the wild type but ferments glucose to ethanol, formate, and acetoin. Microarray analysis showed that LDH deficiency had profound transcriptional effects: 43 genes in the mutant were found to be upregulated, and 45 were found to be downregulated. Most of the upregulated genes encode enzymes of energy metabolism or transport. By two-dimensional (2D) gel analysis, 45 differentially expressed proteins were identified. A comparison of transcriptomic and proteomic data suggested that for several proteins the level of expression is regulated beyond the level of transcription. Pyruvate catabolic genes, including the truncated ldh gene, showed highly increased transcription in the mutant. These genes, along with a number of other differentially expressed genes, are preceded by sequences with homology to binding sites for the global redox-sensing repressor, Rex, of Staphylococcus aureus. The data indicate that the genes are transcriptionally regulated by the NADH/NAD ratio and that this ratio plays an important role in the regulatory network controlling energy metabolism in E. faecalis.
Keywords: Acetoin/metabolism; Electrophoresis, Gel, Two-Dimensional; Enterococcus faecalis/chemistry/*enzymology/genetics/metabolism; Fermentation; Formates/metabolism; *Gene Expression Profiling; Gene Expression Regulation, Bacterial; Glucose/metabolism; L-Lactate Dehydrogenase/*deficiency; *Metabolome; Microarray Analysis; NAD/metabolism; Proteome/*analysis

Central role of the RNA polymerase trigger loop in intrinsic RNA hydrolysis. - Yuzenkova, Y.; Zenkin, N. (Proc Natl Acad Sci U S A, 2010)
The active center of RNA polymerase can hydrolyze phosphodiester bonds in nascent RNA, a reaction thought to be important for proofreading of transcription. The reaction proceeds via a general two Mg(2+) mechanism and is assisted by the 3' end nucleotide of the transcript. Here, by using Thermus aquaticus RNA polymerase, we show that the reaction also requires the flexible domain of the active center, the trigger loop (TL). We show that the invariant histidine (beta' His1242) of the TL is essential for hydrolysis/proofreading and participates in the reaction in two distinct ways: by positioning the 3' end nucleotide of the transcript that assists catalysis and/or by directly participating in the reaction as a general base. We also show that participation of the beta' His1242 of the TL in phosphodiester bond hydrolysis does not depend on the extent of elongation complex backtracking. We obtained similar results with Escherichia coli RNA polymerase, indicating that the function of the TL in phosphodiester bond hydrolysis is conserved among bacteria.
Keywords: Amino Acid Substitution; Catalytic Domain; DNA-Directed RNA Polymerases/*chemistry/genetics/*metabolism; Enzyme Stability; Escherichia coli/enzymology/genetics; Hydrolysis; Kinetics; Macromolecular Substances; Models, Molecular; Mutagenesis, Site-Directed; RNA, Bacterial/genetics/*metabolism; Recombinant Proteins/chemistry/genetics/metabolism; Thermus/enzymology/genetics

Significance analysis and statistical mechanics: an application to clustering. - Luksza, M.; Lassig, M.; Berg, J. (Phys Rev Lett, 2010)
This Letter addresses the statistical significance of structures in random data: given a set of vectors and a measure of mutual similarity, how likely is it that a subset of these vectors forms a cluster with enhanced similarity among its elements? The computation of this cluster p value for randomly distributed vectors is mapped onto a well-defined problem of statistical mechanics. We solve this problem analytically, establishing a connection between the physics of quenched disorder and multiple-testing statistics in clustering and related problems. In an application to gene expression data, we find a remarkable link between the statistical significance of a cluster and the functional relationships between its genes.

Structures of carbon catabolite protein A-(HPr-Ser46-P) bound to diverse catabolite response element sites reveal the basis for high-affinity binding to degenerate DNA operators. - Schumacher, M. A.; Sprehe, M.; Bartholomae, M.; Hillen, W.; Brennan, R. G. (Nucleic Acids Res, 2011)
In Gram-positive bacteria, carbon catabolite protein A (CcpA) is the master regulator of carbon catabolite control, which ensures optimal energy usage under diverse conditions. Unlike other LacI-GalR proteins, CcpA is activated for DNA binding by first forming a complex with the phosphoprotein HPr-Ser46-P. Bacillus subtilis CcpA functions as both a transcription repressor and activator and binds to more than 50 operators called catabolite response elements (cres). These sites are highly degenerate with the consensus, WTGNNARCGNWWWCAW. How CcpA-(HPr-Ser46-P) binds such diverse sequences is unclear. To gain insight into this question, we solved the structures of the CcpA-(HPr-Ser46-P) complex bound to three different operators, the synthetic (syn) cre, ackA2 cre and gntR-down cre. Strikingly, the structures show that the CcpA-bound operators display different bend angles, ranging from 31 degrees to 56 degrees . These differences are accommodated by a flexible linkage between the CcpA helix-turn-helix-loop-helix motif and hinge helices, which allows independent docking of these DNA-binding modules. This flexibility coupled with an abundance of non-polar residues capable of non-specific nucleobase interactions permits CcpA-(HPr-Ser46-P) to bind diverse operators. Indeed, biochemical data show that CcpA-(HPr-Ser46-P) binds the three cre sites with similar affinities. Thus, the data reveal properties that license this protein to function as a global transcription regulator.
Keywords: Bacillus subtilis/genetics; Bacterial Proteins/*chemistry; Base Sequence; Binding Sites; Consensus Sequence; Crystallography, X-Ray; DNA, Bacterial/chemistry; DNA-Binding Proteins/*chemistry; Models, Molecular; *Operator Regions, Genetic; Phosphoproteins/*chemistry; Protein Binding; Response Elements; Transcription Factors/*chemistry

"Hot standards" for the thermoacidophilic archaeon Sulfolobus solfataricus. - Zaparty, M.; Esser, D.; Gertig, S.; Haferkamp, P.; Kouril, T.; Manica, A.; Pham, T. K.; Reimann, J.; Schreiber, K.; Sierocinski, P.; Teichmann, D.; van Wolferen, M.; et al. (Extremophiles, 2010)
Within the archaea, the thermoacidophilic crenarchaeote Sulfolobus solfataricus has become an important model organism for physiology and biochemistry, comparative and functional genomics, as well as, more recently also for systems biology approaches. Within the Sulfolobus Systems Biology ("SulfoSYS")-project the effect of changing growth temperatures on a metabolic network is investigated at the systems level by integrating genomic, transcriptomic, proteomic, metabolomic and enzymatic information for production of a silicon cell-model. The network under investigation is the central carbohydrate metabolism. The generation of high-quality quantitative data, which is critical for the investigation of biological systems and the successful integration of the different datasets, derived for example from high-throughput approaches (e.g., transcriptome or proteome analyses), requires the application and compliance of uniform standard protocols, e.g., for growth and handling of the organism as well as the "-omics" approaches. Here, we report on the establishment and implementation of standard operating procedures for the different wet-lab and in silico techniques that are applied within the SulfoSYS-project and that we believe can be useful for future projects on Sulfolobus or (hyper)thermophiles in general. Beside established techniques, it includes new methodologies like strain surveillance, the improved identification of membrane proteins and the application of crenarchaeal metabolomics.
Keywords: Genomics/*methods/*standards; Sulfolobus solfataricus/*genetics

Recombination between ccrC genes in a type V (5C2&5) staphylococcal cassette chromosome mec (SCCmec) of Staphylococcus aureus ST398 leads to conversion from methicillin resistance to methicillin susceptibility in vivo. - Chlebowicz, M. A.; Nganou, K.; Kozytska, S.; Arends, J. P.; Engelmann, S.; Grundmann, H.; Ohlsen, K.; van Dijl, J. M.; Buist, G. (Antimicrob Agents Chemother, 2010)
Various types of the staphylococcal cassette chromosome mec (SCCmec) are known to confer methicillin resistance on the human pathogen Staphylococcus aureus. Such cassettes are not always stably maintained. The present studies were aimed at identifying the mechanism underlying the in vivo conversion of methicillin-resistant S. aureus (MRSA) to methicillin-susceptible S. aureus (MSSA) derivatives as encountered in two patients suffering from pneumonia and an umbilicus infection, respectively. All MRSA and MSSA isolates identified belong to multilocus sequence type (MLST) 398, have spa type t034, and are Panton-Valentine leukocidin positive. Sequencing of 27,616 nucleotides from the chromosomal SCCmec insertion site in orfX to the hsdR gene for a restriction enzyme revealed a type V (5C2&5) SCCmec. Sequence comparisons show that parts of the cassette are highly similar to sequences within SCCmec elements from coagulase-negative staphylococci, indicating a possible common origin. The cassette investigated contains ccrC-carrying units on either side of its class C2b mec gene complex. In vivo loss of the mec gene complex was caused by recombination between the recombinase genes ccrC1 allele 8 and ccrC1 allele 10. In vitro, the SCCmec was very stable, and low-frequency MRSA-to-MSSA conversion was only observed when MRSA isolates were cultivated at 41 degrees C for prolonged periods of time. In this case also, loss of the mec complex was due to ccrC gene recombination. Interestingly, the MRSA and MSSA isolates studied displayed no detectable differences in competitive growth and virulence, suggesting that the presence of the intact type V (5C2&5) SCCmec has no negative bearing on staphylococcal fitness under the conditions used.
Keywords: Animals; Anti-Bacterial Agents/pharmacology; Bacterial Proteins/*genetics; Blotting, Southern; Electrophoresis, Gel, Pulsed-Field; Female; Methicillin/*pharmacology; Methicillin Resistance/*genetics; Mice; Mice, Inbred BALB C; Microbial Sensitivity Tests; Recombinases/*genetics; Recombination, Genetic/genetics/*physiology; Staphylococcal Infections/drug therapy/microbiology; Staphylococcus aureus/*drug effects/genetics/growth & development/*pathogenicity; Virulence/genetics

Requirement of the agr locus for colony spreading of Staphylococcus aureus. - Tsompanidou, E.; Sibbald, M. J.; Chlebowicz, M. A.; Dreisbach, A.; Back, J. W.; van Dijl, J. M.; Buist, G.; Denham, E. L. (J Bacteriol, 2011)
The important human pathogen Staphylococcus aureus is known to spread on soft agar plates. Here, we show that colony spreading of S. aureus involves the agr quorum-sensing system. This finding can be related to the agr-dependent expression of biosurfactants, such as phenol-soluble modulins, suggesting a connection between spreading motility and virulence.
Keywords: Bacterial Proteins/genetics/*metabolism; Gene Expression Regulation, Bacterial/*physiology; Mutation; Quorum Sensing/physiology; Staphylococcus aureus/genetics/growth & development/*metabolism; Surface-Active Agents/metabolism; Trans-Activators/genetics/*metabolism

Staphylococcal PknB as the first prokaryotic representative of the proline-directed kinases. - Miller, M.; Donat, S.; Rakette, S.; Stehle, T.; Kouwen, T. R.; Diks, S. H.; Dreisbach, A.; Reilman, E.; Gronau, K.; Becher, D.; Peppelenbosch, M. P.; van Dijl, J. M.; et al. (PLoS One, 2010)
In eukaryotic cell types, virtually all cellular processes are under control of proline-directed kinases and especially MAP kinases. Serine/threonine kinases in general were originally considered as a eukaryote-specific enzyme family. However, recent studies have revealed that orthologues of eukaryotic serine/threonine kinases exist in bacteria. Moreover, various pathogenic species, such as Yersinia and Mycobacterium, require serine/threonine kinases for successful invasion of human host cells. The substrates targeted by bacterial serine/threonine kinases have remained largely unknown. Here we report that the serine/threonine kinase PknB from the important pathogen Staphylococcus aureus is released into the external milieu, which opens up the possibility that PknB does not only phosphorylate bacterial proteins but also proteins of the human host. To identify possible human targets of purified PknB, we studied in vitro phosphorylation of peptide microarrays and detected 68 possible human targets for phosphorylation. These results show that PknB is a proline-directed kinase with MAP kinase-like enzymatic activity. As the potential cellular targets for PknB are involved in apoptosis, immune responses, transport, and metabolism, PknB secretion may help the bacterium to evade intracellular killing and facilitate its growth. In apparent agreement with this notion, phosphorylation of the host-cell response coordinating transcription factor ATF-2 by PknB was confirmed by mass spectrometry. Taken together, our results identify PknB as the first prokaryotic representative of the proline-directed kinase/MAP kinase family of enzymes.
Keywords: Activating Transcription Factor 2/metabolism; Amino Acid Sequence; Bacterial Proteins/genetics/*metabolism; Binding Sites; Blotting, Western; Humans; MAP Kinase Kinase 4/metabolism; Mass Spectrometry; Mutation; Peptides/metabolism; Phosphorylation; Proline/*metabolism; Protein Array Analysis; Protein Serine-Threonine Kinases/genetics/*metabolism; Staphylococcus aureus/*enzymology/genetics; p38 Mitogen-Activated Protein Kinases/metabolism

Integrative responses to high pH stress in S. cerevisiae. - Arino, J. (OMICS, 2010)
The budding yeast Saccharomyces cerevisiae grows far better at acidic than at neutral or alkaline pH. Consequently, even a modest alkalinization of the medium represents a stressful situation for this yeast. In the past few years, data generated by a combination of genome-wide techniques has demonstrated that adaptive responses of S. cerevisiae to high pH stress involves extensive gene remodeling as a result of the fast activation of a number of stress-related signaling pathways, such as the Rim101, the Wsc1-Pkc1-Slt2 MAP kinase, and the calcium-activated calcineurin pathways. Alkalinization of the environment also disturbs nutrient homeostasis, as deduced from its impact on iron/copper, phosphate, and glucose uptake/utilization pathways. In this review we will examine these responses, their possible interactions, and the role that they play in tolerance to high pH stress.
Keywords: Calcineurin/genetics/metabolism; Gene Expression Regulation, Fungal; Homeostasis; *Hydrogen-Ion Concentration; Saccharomyces cerevisiae/*physiology; Saccharomyces cerevisiae Proteins/genetics/metabolism; Signal Transduction/physiology; *Stress, Physiological

Alkali-metal-cation influx and efflux systems in nonconventional yeast species. - Ramos, J.; Arino, J.; Sychrova, H. (FEMS Microbiol Lett, 2011)
To maintain optimal intracellular concentrations of alkali-metal-cations, yeast cells use a series of influx and efflux systems. Nonconventional yeast species have at least three different types of efficient transporters that ensure potassium uptake and accumulation in cells. Most of them have Trk uniporters and Hak K(+)-H(+) symporters and a few yeast species also have the rare K(+) (Na(+))-uptake ATPase Acu. To eliminate surplus potassium or toxic sodium cations, various yeast species use highly conserved Nha Na(+) (K(+))/H(+) antiporters and Na(+) (K(+))-efflux Ena ATPases. The potassium-specific yeast Tok1 channel is also highly conserved among various yeast species and its activity is important for the regulation of plasma membrane potential.
Keywords: Alkalies/*metabolism; Biological Transport, Active; Cations/*metabolism; Fungal Proteins/*metabolism; Membrane Transport Proteins/*metabolism; Metals/*metabolism; Yeasts/*metabolism

Molecular sieving properties of the cytoplasm of Escherichia coli and consequences of osmotic stress - Mika, Jacek; Van Den Bogaart, Geert; Veenhoff, Liesbeth; Krasnikov, Victor; Poolman, Bert (2010)
We determined the diffusion coefficients (D) of (macro)molecules of different sizes (from ∼0.5 to 600 kDa) in the cytoplasm of live Escherichia coli cells under normal osmotic conditions and osmotic upshift. D values decreased with increasing molecular weight of the molecules. Upon osmotic upshift, the decrease in D of NBD-glucose was much smaller than that of macromolecules. Barriers for diffusion were found in osmotically challenged cells only for GFP and larger proteins. These barriers are likely formed by the nucleoid and crowding of the cytoplasm. The cytoplasm of E. coli appears as a meshwork allowing the free passage of small molecules while restricting the diffusion of bigger ones.

Macromolecule diffusion and confinement in prokaryotic cells. - Mika, J. T.; Poolman, B. (Curr Opin Biotechnol, 2011)
We review recent observations on the mobility of macromolecules and their spatial organization in live bacterial cells. We outline the major fluorescence microscopy-based methods to determine the mobility and thus the diffusion coefficients (D) of molecules, which is not trivial in small cells. The extremely high macromolecule crowding of prokaryotes is used to rationalize the reported lower diffusion coefficients as compared to eukaryotes, and we speculate on the nature of the barriers for diffusion observed for proteins (and mRNAs) in vivo. Building on in vitro experiments and modeling studies, we evaluate the size dependence of diffusion coefficients for macromolecules in vivo, in case of both water-soluble and integral membrane proteins. We comment on the possibilities of anomalous diffusion and provide examples where the macromolecule mobility may be limiting biological processes.
Keywords: 3T3 Cells; Animals; Cell Compartmentation/physiology; Cell Membrane/*metabolism; *Diffusion; Humans; Kinetics; Mice; Microscopy, Fluorescence; *Models, Biological; Prokaryotic Cells/*metabolism; Proteins/metabolism; RNA, Messenger/metabolism

Protein mobility and diffusive barriers in Escherichia coli: consequences of osmotic stress. - van den Bogaart, G.; Hermans, N.; Krasnikov, V.; Poolman, B. (Mol Microbiol, 2007)
The effect of osmotic stress on the intracellular diffusion of proteins in Escherichia coli was studied, using a pulsed version of fluorescence recovery after photo-bleaching, pulsed-FRAP. This method employs sequences of laser pulses which only partly bleach the fluorophores in a cell. Because the cell size and geometry are taken into account, pulsed-FRAP enables to measure diffusion in very small cells of different shapes. We found that upon an osmotic upshock from 0.15 to 0.6 Osm, imposed by NaCl or sorbitol, the apparent intracellular diffusion (D) of mobile green fluorescent protein (GFP) decreased from 3.2 to 0.4 microm(2) s(-1), whereas the membrane permeable glycerol had no effect. Exposing E. coli cells to higher osmolalities (> 0.6 Osm) led to compartmentalization of the GFP into discrete pools, from where the GFP could not escape. Although free diffusion through the cell was hindered, the mobility of GFP in these pools was still relatively high (D approximately 0.4 microm(2) s(-1)). The presence of osmoprotectants restored the effect of osmotic stress on the protein mobility and apparent compartmentalization. Also, lowering the osmolality from 0.6 Osm back to 0.15 Osm restored the mobility of GFP. The implications of these findings in terms of heterogeneities and diffusive barriers inside the cell are discussed.
Keywords: Diffusion; Escherichia coli/*metabolism; Escherichia coli Proteins/*chemistry/metabolism; Fluorescence Recovery After Photobleaching/*methods; Green Fluorescent Proteins/chemistry/metabolism; Models, Biological; Osmolar Concentration; Osmotic Pressure; Protein Transport

The role of biomacromolecular crowding, ionic strength, and physicochemical gradients in the complexities of life's emergence. - Spitzer, J.; Poolman, B. (Microbiol Mol Biol Rev, 2009)
We have developed a general scenario of prebiotic physicochemical evolution during the Earth's Hadean eon and reviewed the relevant literature. We suggest that prebiotic chemical evolution started in microspaces with membranous walls, where external temperature and osmotic gradients were coupled to free-energy gradients of potential chemical reactions. The key feature of this scenario is the onset of an emergent evolutionary transition within the microspaces that is described by the model of complex vectorial chemistry. This transition occurs at average macromolecular crowding of 20 to 30% of the cell volume, when the ranges of action of stabilizing colloidal forces (screened electrostatic forces, hydration, and excluded volume forces) become commensurate. Under these conditions, the macromolecules divide the interior of microspaces into dynamically crowded macromolecular regions and topologically complementary electrolyte pools. Small ions and ionic metabolites are transported vectorially between the electrolyte pools and through the (semiconducting) electrolyte pathways of the crowded macromolecular regions from their high electrochemical potential (where they are biochemically produced) to their lower electrochemical potential (where they are consumed). We suggest a sequence of tentative transitions between major evolutionary periods during the Hadean eon as follows: (i) the early water world, (ii) the appearance of land masses, (iii) the pre-RNA world, (iv) the onset of complex vectorial chemistry, and (v) the RNA world and evolution toward Darwinian thresholds. We stress the importance of high ionic strength of the Hadean ocean (short Debye's lengths) and screened electrostatic interactions that enabled the onset of the vectorial structure of the cytoplasm and the possibility of life's emergence.
Keywords: Animals; Cytoplasm/metabolism; Electrochemistry; Electrolytes/metabolism; Evolution, Chemical; Humans; Macromolecular Substances/*chemistry/metabolism; *Origin of Life; Osmolar Concentration; Proton-Motive Force; RNA/metabolism; Seawater; Water Microbiology

Structural basis for the enhanced activity of cyclic antimicrobial peptides: the case of BPC194. - Mika, J. T.; Moiset, G.; Cirac, A. D.; Feliu, L.; Bardaji, E.; Planas, M.; Sengupta, D.; Marrink, S. J.; Poolman, B. (Biochim Biophys Acta, 2011)
We report the molecular basis for the differences in activity of cyclic and linear antimicrobial peptides. We iteratively performed atomistic molecular dynamics simulations and biophysical measurements to probe the interaction of a cyclic antimicrobial peptide and its inactive linear analogue with model membranes. We establish that, relative to the linear peptide, the cyclic one binds stronger to negatively charged membranes. We show that only the cyclic peptide folds at the membrane interface and adopts a beta-sheet structure characterised by two turns. Subsequently, the cyclic peptide penetrates deeper into the bilayer while the linear peptide remains essentially at the surface. Finally, based on our comparative study, we propose a model characterising the mode of action of cyclic antimicrobial peptides. The results provide a chemical rationale for enhanced activity in certain cyclic antimicrobial peptides and can be used as a guideline for design of novel antimicrobial peptides.
Keywords: Antimicrobial Cationic Peptides/*chemistry/pharmacology; Biophysics/methods; Cell Membrane/metabolism; Circular Dichroism; Computer Simulation; Dose-Response Relationship, Drug; Lipids/chemistry; Liposomes/*chemistry; Membranes, Artificial; Molecular Conformation; Peptides/chemistry; Peptides, Cyclic/*chemistry/pharmacology; Permeability; Protein Binding; Protein Folding; Protein Structure, Secondary; Time Factors

The molecular basis for antimicrobial activity of pore-forming cyclic peptides. - Cirac, A. D.; Moiset, G.; Mika, J. T.; Kocer, A.; Salvador, P.; Poolman, B.; Marrink, S. J.; Sengupta, D. (Biophys J, 2011)
The mechanism of action of antimicrobial peptides is, to our knowledge, still poorly understood. To probe the biophysical characteristics that confer activity, we present here a molecular-dynamics and biophysical study of a cyclic antimicrobial peptide and its inactive linear analog. In the simulations, the cyclic peptide caused large perturbations in the bilayer and cooperatively opened a disordered toroidal pore, 1-2 nm in diameter. Electrophysiology measurements confirm discrete poration events of comparable size. We also show that lysine residues aligning parallel to each other in the cyclic but not linear peptide are crucial for function. By employing dual-color fluorescence burst analysis, we show that both peptides are able to fuse/aggregate liposomes but only the cyclic peptide is able to porate them. The results provide detailed insight on the molecular basis of activity of cyclic antimicrobial peptides.
Keywords: Amino Acid Sequence; Anti-Infective Agents/*chemistry/*pharmacology; Computational Biology; Electrophysiological Phenomena/drug effects; Fluorescence; Lipid Bilayers/chemistry; Liposomes/chemistry; Molecular Sequence Data; Peptides, Cyclic/*chemistry/*pharmacology; Phosphatidylglycerols/chemistry; Porosity/drug effects; Protein Structure, Secondary; Structure-Activity Relationship

SMC is recruited to oriC by ParB and promotes chromosome segregation in Streptococcus pneumoniae. - Minnen, A.; Attaiech, L.; Thon, M.; Gruber, S.; Veening, J. W. (Mol Microbiol, 2011)
Segregation of replicated chromosomes is an essential process in all organisms. How bacteria, such as the oval-shaped human pathogen Streptococcus pneumoniae, efficiently segregate their chromosomes is poorly understood. Here we show that the pneumococcal homologue of the DNA-binding protein ParB recruits S. pneumoniae condensin (SMC) to centromere-like DNA sequences (parS) that are located near the origin of replication, in a similar fashion as was shown for the rod-shaped model bacterium Bacillus subtilis. In contrast to B. subtilis, smc is not essential in S. pneumoniae, and Deltasmc cells do not show an increased sensitivity to gyrase inhibitors or high temperatures. However, deletion of smc and/or parB results in a mild chromosome segregation defect. Our results show that S. pneumoniae contains a functional chromosome segregation machine that promotes efficient chromosome segregation by recruitment of SMC via ParB. Intriguingly, the data indicate that other, as of yet unknown mechanisms, are at play to ensure proper chromosome segregation in this organism.
Keywords: Bacterial Proteins/genetics/*metabolism; Cell Cycle Proteins/genetics/*metabolism; *Chromosome Segregation; Chromosomes, Bacterial/*metabolism; DNA-Binding Proteins/*metabolism; Gene Deletion; *Origin Recognition Complex; Protein Binding; Streptococcus pneumoniae/*enzymology/genetics/growth & development/*metabolism

Live Cell Imaging of Bacillus subtilis and Streptococcus pneumoniae using Automated Time-lapse Microscopy. - de Jong, I. G.; Beilharz, K.; Kuipers, O. P.; Veening, J. W. (J Vis Exp, 2011)
During the last few years scientists became increasingly aware that average data obtained from microbial population based experiments are not representative of the behavior, status or phenotype of single cells. Due to this new insight the number of single cell studies rises continuously (for recent reviews see (1,2,3)). However, many of the single cell techniques applied do not allow monitoring the development and behavior of one specific single cell in time (e.g. flow cytometry or standard microscopy). Here, we provide a detailed description of a microscopy method used in several recent studies (4, 5, 6, 7), which allows following and recording (fluorescence of) individual bacterial cells of Bacillus subtilis and Streptococcus pneumoniae through growth and division for many generations. The resulting movies can be used to construct phylogenetic lineage trees by tracing back the history of a single cell within a population that originated from one common ancestor. This time-lapse fluorescence microscopy method cannot only be used to investigate growth, division and differentiation of individual cells, but also to analyze the effect of cell history and ancestry on specific cellular behavior. Furthermore, time-lapse microscopy is ideally suited to examine gene expression dynamics and protein localization during the bacterial cell cycle. The method explains how to prepare the bacterial cells and construct the microscope slide to enable the outgrowth of single cells into a microcolony. In short, single cells are spotted on a semi-solid surface consisting of growth medium supplemented with agarose on which they grow and divide under a fluorescence microscope within a temperature controlled environmental chamber. Images are captured at specific intervals and are later analyzed using the open source software ImageJ.
Keywords: Bacillus subtilis/*cytology; Bacteriological Techniques/*methods; Microscopy, Fluorescence/*methods; Streptococcus pneumoniae/*cytology

Growth rate-dependent control in Enterococcus faecalis: effects on the transcriptome and proteome, and strong regulation of lactate dehydrogenase. - Mehmeti, I.; Faergestad, E. M.; Bekker, M.; Snipen, L.; Nes, I. F.; Holo, H. (Appl Environ Microbiol, 2012)
Enterococcus faecalis V583 was grown in a glucose-limited chemostat at three different growth rates (0.05, 0.15, and 0.4 h(-)(1)). The fermentation pattern changed with growth rate, from a mostly homolactic profile at a high growth rate to a fermentation dominated by formate, acetate, and ethanol production at a low growth rate. A number of amino acids were consumed at the lower growth rates but not by fast-growing cells. The change in metabolic profile was caused mainly by decreased flux through lactate dehydrogenase. The transcription of ldh-1, encoding the principal lactate dehydrogenase, showed very strong growth rate dependence and differed by three orders of magnitude between the highest and the lowest growth rates. Despite the increase in ldh-1 transcript, the content of the Ldh-1 protein was the same under all conditions. Using microarrays and quantitative PCR, the levels of 227 gene transcripts were found to be affected by the growth rate, and 56 differentially expressed proteins were found by proteomic analyses. Few genes or proteins showed a growth rate-dependent increase or decrease in expression across the whole range of conditions, and many showed a maximum or minimum at the middle growth rate (i.e., 0.15 h(-)(1)). For many gene products, a discrepancy between transcriptomic and proteomic data were seen, indicating posttranscriptional regulation of expression.
Keywords: Bacterial Proteins/*metabolism; Cell Culture Techniques; Enterococcus faecalis/*enzymology/genetics/growth & development; Gene Expression Profiling; Gene Expression Regulation; Isoenzymes/genetics/metabolism; L-Lactate Dehydrogenase/genetics/*metabolism; Metabolome/*physiology; Oligonucleotide Array Sequence Analysis; Polymerase Chain Reaction; Proteome/*metabolism; Proteomics; RNA, Bacterial/analysis; Transcriptome/*physiology

A new basal promoter element recognized by RNA polymerase core enzyme. - Yuzenkova, Y.; Tadigotla, V. R.; Severinov, K.; Zenkin, N. (EMBO J, 2011)
Bacterial promoters are recognized by RNA polymerase (RNAP) sigma subunit, which specifically interacts with the -10 and -35 promoter elements. Here, we provide evidence that the beta' zipper, an evolutionarily conserved loop of the largest subunit of RNAP core, interacts with promoter spacer, a DNA segment that separates the -10 and -35 promoter elements, and facilitates the formation of stable closed promoter complex. Depending on the spacer sequence, the proposed interaction of the beta' zipper with the spacer can also facilitate open promoter complex formation and even substitute for interactions of the sigma subunit with the -35 element. These results suggest that there exists a novel class of promoters that rely on interaction of the beta' zipper with promoter spacer, along with or instead of interactions of sigma subunit with the -35 element, for their activity. Finally, our data suggest that sequence-dependent interactions of the beta' zipper with DNA can contribute to promoter-proximal sigma-dependent RNAP pausing, a recently recognized important step of transcription control.
Keywords: *Binding Sites; DNA-Directed RNA Polymerases/*metabolism; *Promoter Regions, Genetic; Protein Binding; Thermus/*enzymology/genetics/metabolism

Factor-independent transcription pausing caused by recognition of the RNA-DNA hybrid sequence. - Bochkareva, A.; Yuzenkova, Y.; Tadigotla, V. R.; Zenkin, N. (EMBO J, 2012)
Pausing of transcription is an important step of regulation of gene expression in bacteria and eukaryotes. Here we uncover a factor-independent mechanism of transcription pausing, which is determined by the ability of the elongating RNA polymerase to recognize the sequence of the RNA-DNA hybrid. We show that, independently of thermodynamic stability of the elongation complex, RNA polymerase directly 'senses' the shape and/or identity of base pairs of the RNA-DNA hybrid. Recognition of the RNA-DNA hybrid sequence delays translocation by RNA polymerase, and thus slows down the nucleotide addition cycle through 'in pathway' mechanism. We show that this phenomenon is conserved among bacterial and eukaryotic RNA polymerases, and is involved in regulatory pauses, such as a pause regulating the production of virulence factors in some bacteria and a pause regulating transcription/replication of HIV-1. The results indicate that recognition of RNA-DNA hybrid sequence by multi-subunit RNA polymerases is involved in transcription regulation and may determine the overall rate of transcription elongation.
Keywords: Bacteria/pathogenicity; Base Sequence; Biocatalysis; DNA/*chemistry; DNA-Directed RNA Polymerases/metabolism; HIV-1/pathogenicity; Molecular Sequence Data; *Nucleic Acid Hybridization; RNA/*chemistry; *Transcription, Genetic; Virulence

In vitro experimental system for analysis of transcription-translation coupling. - Castro-Roa, D.; Zenkin, N. (Nucleic Acids Res, 2012)
Transcription and translation are coupled in bacteria, meaning that translation takes place co-transcriptionally. During transcription-translation, both machineries mutually affect each others' functions, which is important for regulation of gene expression. Analysis of interactions between RNA polymerase (RNAP) and the ribosome, however, are limited due to the lack of an in vitro experimental system. Here, we report the development of an in vitro transcription coupled to translation system assembled from purified components. The system allows controlled stepwise transcription and simultaneous stepwise translation of the nascent RNA, and permits investigation of the interactions of RNAP with the ribosome, as well as the effects of translation on transcription and transcription on translation. As an example of usage of this experimental system, we uncover complex effects of transcription-translation coupling on pausing of transcription.
Keywords: DNA-Directed RNA Polymerases/metabolism; Promoter Regions, Genetic; *Protein Biosynthesis; Ribosomal Proteins/isolation & purification/metabolism; Ribosomes/metabolism; Templates, Genetic; *Transcription, Genetic

Nonlinear fitness landscape of a molecular pathway. - Perfeito, L.; Ghozzi, S.; Berg, J.; Schnetz, K.; Lassig, M. (PLoS Genet, 2011)
Genes are regulated because their expression involves a fitness cost to the organism. The production of proteins by transcription and translation is a well-known cost factor, but the enzymatic activity of the proteins produced can also reduce fitness, depending on the internal state and the environment of the cell. Here, we map the fitness costs of a key metabolic network, the lactose utilization pathway in Escherichia coli. We measure the growth of several regulatory lac operon mutants in different environments inducing expression of the lac genes. We find a strikingly nonlinear fitness landscape, which depends on the production rate and on the activity rate of the lac proteins. A simple fitness model of the lac pathway, based on elementary biophysical processes, predicts the growth rate of all observed strains. The nonlinearity of fitness is explained by a feedback loop: production and activity of the lac proteins reduce growth, but growth also affects the density of these molecules. This nonlinearity has important consequences for molecular function and evolution. It generates a cliff in the fitness landscape, beyond which populations cannot maintain growth. In viable populations, there is an expression barrier of the lac genes, which cannot be exceeded in any stationary growth process. Furthermore, the nonlinearity determines how the fitness of operon mutants depends on the inducer environment. We argue that fitness nonlinearities, expression barriers, and gene-environment interactions are generic features of fitness landscapes for metabolic pathways, and we discuss their implications for the evolution of regulation.
Keywords: Biological Evolution; Environment; Escherichia coli/genetics/metabolism; Escherichia coli Proteins/genetics/metabolism; Gene Expression Regulation, Bacterial; *Genetic Fitness; Genotype; Lac Operon/physiology; Metabolic Networks and Pathways/*genetics; Phenotype

Dynamic Modelling under Uncertainty: The Case of Trypanosoma brucei Energy Metabolism (PLoS Comput Biol, 2012)
Kinetic models of metabolism require detailed knowledge of kinetic parameters. However, due to measurement errors or lack of data this knowledge is often uncertain. The model of glycolysis in the parasitic protozoan Trypanosoma brucei is a particularly well analysed example of a quantitative metabolic model, but so far it has been studied with a fixed set of parameters only. Here we evaluate the effect of parameter uncertainty. In order to define probability distributions for each parameter, information about the experimental sources and confidence intervals for all parameters were collected. We created a wiki-based website dedicated to the detailed documentation of this information: the SilicoTryp wiki (http://silicotryp.ibls.gla.ac.uk/wiki/Gl​ycolysis). Using information collected in the wiki, we then assigned probability distributions to all parameters of the model. This allowed us to sample sets of alternative models, accurately representing our degree of uncertainty. Some properties of the model, such as the repartition of the glycolytic flux between the glycerol and pyruvate producing branches, are robust to these uncertainties. However, our analysis also allowed us to identify fragilities of the model leading to the accumulation of 3-phosphoglycerate and/or pyruvate. The analysis of the control coefficients revealed the importance of taking into account the uncertainties about the parameters, as the ranking of the reactions can be greatly affected. This work will now form the basis for a comprehensive Bayesian analysis and extension of the model considering alternative topologies.

Role of phosphate in the central metabolism of two lactic acid bacteria--a comparative systems biology approach. - Levering, J.; Musters, M. W.; Bekker, M.; Bellomo, D.; Fiedler, T.; de Vos, W. M.; Hugenholtz, J.; Kreikemeyer, B.; Kummer, U.; Teusink, B. (FEBS J, 2012)
Lactic acid-producing bacteria survive in distinct environments, but show common metabolic characteristics. Here we studied the dynamic interactions of the central metabolism in Lactococcus lactis, extensively used as a starter culture in the dairy industry, and Streptococcus pyogenes, a human pathogen. Glucose-pulse experiments and enzymatic measurements were performed to parameterize kinetic models of glycolysis. Significant improvements were made to existing kinetic models for L. lactis, which subsequently accelerated the development of the first kinetic model of S. pyogenes glycolysis. The models revealed an important role for extracellular phosphate in the regulation of central metabolism and the efficient use of glucose. Thus, phosphate, which is rarely taken into account as an independent species in models of central metabolism, should be considered more thoroughly in the analysis of metabolic systems in the future. Insufficient phosphate supply can lead to a strong inhibition of glycolysis at high glucose concentrations in both species, but this was more severe in S. pyogenes. S. pyogenes is more efficient at converting glucose to ATP, showing a higher tendency towards heterofermentative energy metabolism than L. lactis. Our comparative systems biology approach revealed that the glycolysis of L. lactis and S. pyogenes have similar characteristics, but are adapted to their individual natural habitats with respect to phosphate regulation.
Keywords: Energy Metabolism/*physiology; Fermentation; Glucose/metabolism; Glycolysis/physiology; Humans; Lactic Acid/*metabolism; Lactococcus lactis/*metabolism; Models, Theoretical; Phosphates/*metabolism; Streptococcus pyogenes/*metabolism; Systems Biology/*methods

Simplified absolute metabolite quantification by gas chromatography–isotope dilution mass spectrometry on the basis of commercially available source material - Vielhauer, Oliver; Zakhartsev, Maksim; Horn, Thomas; Takors, Ralf; Reuss, Matthias (Journal of Chromatography B, 2011)
In the field of metabolomics, GC–MS has rather established itself as a tool for semi-quantitative strategies like metabolic fingerprinting or metabolic profiling. Absolute quantification of intra- or extracellular metabolites is nowadays mostly accomplished by application of diverse LC–MS techniques. Only few groups have so far adopted GC–MS technology for this exceptionally challenging task. Besides numerous and deeply investigated problems related to sample generation, the pronounced matrix effects in biological samples have led to the almost mandatory application of isotope dilution mass spectrometry (IDMS) for the accurate determination of absolute metabolite concentrations. Nevertheless, access to stable isotope labeled internal standards (ILIS), which are in many cases commercially unavailable, is quite laborious and very expensive. Here we present an improved and simplified gas chromatography–isotope dilution mass spectrometry (GC–IDMS) protocol for the absolute determination of intra- and extracellular metabolite levels. Commercially available 13C-labeled algal cells were used as a convenient source for the preparation of internal standards. Advantages as well as limitations of the described method are discussed.

RightField: embedding ontology annotation in spreadsheets. - Wolstencroft, K.; Owen, S.; Horridge, M.; Krebs, O.; Mueller, W.; Snoep, J. L.; du Preez, F.; Goble, C. (Bioinformatics, 2011)
MOTIVATION: In the Life Sciences, guidelines, checklists and ontologies describing what metadata is required for the interpretation and reuse of experimental data are emerging. Data producers, however, may have little experience in the use of such standards and require tools to support this form of data annotation. RESULTS: RightField is an open source application that provides a mechanism for embedding ontology annotation support for Life Science data in Excel spreadsheets. Individual cells, columns or rows can be restricted to particular ranges of allowed classes or instances from chosen ontologies. The RightField-enabled spreadsheet presents selected ontology terms to the users as a simple drop-down list, enabling scientists to consistently annotate their data. The result is 'semantic annotation by stealth', with an annotation process that is less error-prone, more efficient, and more consistent with community standards. AVAILABILITY AND IMPLEMENTATION: RightField is open source under a BSD license and freely available from http://www.rightfield.org.uk
Keywords: Abstracting and Indexing; Classification/methods; Information Management/*methods; *Software; User-Computer Interface

Populous: a tool for building OWL ontologies from templates. - Jupp, S.; Horridge, M.; Iannone, L.; Klein, J.; Owen, S.; Schanstra, J.; Wolstencroft, K.; Stevens, R. (BMC Bioinformatics, 2012)
BACKGROUND: Ontologies are being developed for the life sciences to standardise the way we describe and interpret the wealth of data currently being generated. As more ontology based applications begin to emerge, tools are required that enable domain experts to contribute their knowledge to the growing pool of ontologies. There are many barriers that prevent domain experts engaging in the ontology development process and novel tools are needed to break down these barriers to engage a wider community of scientists. RESULTS: We present Populous, a tool for gathering content with which to construct an ontology. Domain experts need to add content, that is often repetitive in its form, but without having to tackle the underlying ontological representation. Populous presents users with a table based form in which columns are constrained to take values from particular ontologies. Populated tables are mapped to patterns that can then be used to automatically generate the ontology's content. These forms can be exported as spreadsheets, providing an interface that is much more familiar to many biologists. CONCLUSIONS: Populous's contribution is in the knowledge gathering stage of ontology development; it separates knowledge gathering from the conceptualisation and axiomatisation, as well as separating the user from the standard ontology authoring environments. Populous is by no means a replacement for standard ontology editing tools, but instead provides a useful platform for engaging a wider community of scientists in the mass production of ontology content.
Keywords: *Biological Ontologies; Computational Biology/*methods; Databases, Factual; Semantics; Software; User-Computer Interface

Toward interoperable bioscience data. - Sansone, S. A.; Rocca-Serra, P.; Field, D.; Maguire, E.; Taylor, C.; Hofmann, O.; Fang, H.; Neumann, S.; Tong, W.; Amaral-Zettler, L.; Begley, K.; Booth, T.; et al. (Nat Genet, 2012)
To make full use of research data, the bioscience community needs to adopt technologies and reward mechanisms that support interoperability and promote the growth of an open 'data commoning' culture. Here we describe the prerequisites for data commoning and present an established and growing ecosystem of solutions using the shared 'Investigation-Study-Assay' framework to support that vision.
Keywords: Biomedical Research/*standards; Information Storage and Retrieval/*standards

Genome-wide gene expression analysis of the switch between acidogenesis and solventogenesis in continuous cultures of Clostridium acetobutylicum. - Grimmler, C.; Janssen, H.; Krausse, D.; Fischer, R. J.; Bahl, H.; Durre, P.; Liebl, W.; Ehrenreich, A. (J Mol Microbiol Biotechnol, 2011)
Clostridium acetobutylicum is able to switch from acidogenic growth to solventogenic growth. We used phosphate-limited continuous cultures that established acidogenic growth at pH 5.8 and solventogenic growth at pH 4.5. These cultures allowed a detailed transcriptomic study of the switch from acidogenesis to solventogenesis that is not superimposed by sporulation and other growth phase-dependent parameters. These experiments led to new insights into the physiological role of several genes involved in solvent formation. The adc gene for acetone decarboxylase is upregulated well before the rest of the sol locus during the switch, and pyruvate decarboxylase is induced exclusively for the period of this switch. The aldehyde-alcohol dehydrogenase gene adhE1 located in the sol operon is regulated antagonistically to the paralog adhE2 that is expressed during acidogenic conditions. A similar antagonistic pattern can be seen with the two paralogs of thiolase genes, thlA and thlB. Interestingly, the genes coding for the putative cellulosome in C. acetobutylicum are exclusively transcribed throughout solventogenic growth. The genes for stress response are only induced during the shift but not in the course of solventogenesis when butanol is present in the culture. Finally, the data clearly indicate that solventogenesis is independent from sporulation.
Keywords: Alcohol Dehydrogenase/metabolism; Butanols/metabolism; Carboxylic Acids/*metabolism; Cellulosomes/metabolism; Clostridium acetobutylicum/*genetics/*metabolism; Culture Media/chemistry; *Gene Expression Profiling; *Gene Expression Regulation, Bacterial; Hydrogen-Ion Concentration; Metabolic Networks and Pathways/genetics; Microarray Analysis; Pyruvate Decarboxylase/metabolism; Solvents/*metabolism

Miniaturized device for agitating a high-density yeast suspension that is suitable for in vivo nuclear magnetic resonance applications - Zakhartsev, Maksim; Bock, Christian (Analytical Biochemistry, 2010)
In vivo nuclear magnetic resonance (NMR) monitoring requires a high-density cell suspension, where cell precipitation should be avoided. We have designed a miniaturized cell agitator that fits entirely into an 8-mm NMR probe but that, being mounted into the instrument, is situated outside of the sensitive area. The device consists of two glass tubes connected in a way that, when gas flow is blown through them, creates influx of cell suspension into the device that returns through apertures. This flow creates continuous circular vortex of the cell suspension in the whole sample volume, whereas there are no moving mechanical parts or gas bubbles crossing the instrument’s sensitive area. The gas flow controls conditions of the cell suspension and removes volatile waste metabolites.

Characterization of E. coli MG1655 and frdA and sdhC mutants at various aerobiosis levels - Steinsiek, Sonja; Frixel, S.; Stagge, Stefan; Bettenbrock, Katja (Journal of Biotechnology, 2011)

A transcriptional study of acidogenic chemostat cells of Clostridium acetobutylicum–cellular behavior in adaptation to n-butanol - Schwarz, Katrin; Kuit, Wouter; Grimmler, Christina; Ehrenreich, Armin; Kengen, Servé (Journal of Biotechnology, 2012)
To gain more insight into the butanol stress response of Clostridium acetobutylicum the transcriptional response of a steady state acidogenic culture to different levels of n-butanol (0.25-1%) was investigated. No effect was observed on the fermentation pattern and expression of typical solvent genes (aad, ctfA/B, adc, bdhA/B, ptb, buk). Elevated levels of butanol mainly affected class I heat-shock genes (hrcA, grpE, dnaK, dnaJ, groES, groEL, hsp90), which were upregulated in a dose- and time-dependent manner, and genes encoding proteins involved in the membrane composition (fab and fad or glycerophospholipid related genes) and various ABC-transporters of unknown specificity. Interestingly, fab and fad genes were embedded in a large, entirely repressed cluster (CAC1988-CAC2019), which inter alia encoded an iron-specific ABC-transporter and molybdenum-cofactor synthesis proteins. Of the glycerophospholipid metabolism, the glycerol-3-phosphate dehydrogenase (glpA) gene was highly upregulated, whereas a glycerophosphodiester ABC-transporter (ugpAEBC) and a phosphodiesterase (ugpC) were repressed. On the megaplasmid, only a few genes showed differential expression, e.g. a rare lipoprotein (CAP0058, repressed) and a membrane protein (CAP0102, upregulated) gene. Observed transcriptional responses suggest that C. acetobutylicum reacts to butanol stress by induction of the general stress response and changing its cell envelope and transporter composition, but leaving the central catabolism unaffected.

Integrated Sampling Procedure for Metabolome Analysis - Schaub, Jochen; Schiesling, Carola; Reuss, Matthias; Dauner, Michael (Biotechnol Progress, 2006)

Condition-dependent transcriptome reveals high-level regulatory architecture in Bacillus subtilis. - Nicolas, P.; Mader, U.; Dervyn, E.; Rochat, T.; Leduc, A.; Pigeonneau, N.; Bidnenko, E.; Marchadier, E.; Hoebeke, M.; Aymerich, S.; Becher, D.; Bisicchia, P.; et al. (Science, 2012)
Bacteria adapt to environmental stimuli by adjusting their transcriptomes in a complex manner, the full potential of which has yet to be established for any individual bacterial species. Here, we report the transcriptomes of Bacillus subtilis exposed to a wide range of environmental and nutritional conditions that the organism might encounter in nature. We comprehensively mapped transcription units (TUs) and grouped 2935 promoters into regulons controlled by various RNA polymerase sigma factors, accounting for ~66% of the observed variance in transcriptional activity. This global classification of promoters and detailed description of TUs revealed that a large proportion of the detected antisense RNAs arose from potentially spurious transcription initiation by alternative sigma factors and from imperfect control of transcription termination.
Keywords: Adaptation, Physiological; Algorithms; Bacillus subtilis/*genetics/*physiology; Binding Sites; Gene Expression Profiling; *Gene Expression Regulation, Bacterial; Gene Regulatory Networks; Oligonucleotide Array Sequence Analysis; *Promoter Regions, Genetic; RNA, Antisense/genetics/metabolism; RNA, Bacterial/genetics/metabolism; RNA, Messenger/genetics/metabolism; Regulon; Sigma Factor/metabolism; Terminator Regions, Genetic; *Transcription, Genetic; *Transcriptome

Proteolysis of beta-galactosidase following SigmaB activation in Bacillus subtilis - Liebal, Ulf; Sappa, Praveen kumar; Millat, Thomas; Steil, Leif; Homuth, Georg; Voelker, Uwe; Wolkenhauer, Olaf (Mol. BioSyst., 2012)
In Bacillus subtilis the σB mediated general stress response provides protection against various environmental and energy related stress conditions. To better understand the general stress response, we need to explore the mechanism by which the components interact. Here, we performed experiments in B. subtilis wild type and mutant strains to test and validate a mathematical model of the dynamics of σB activity. In the mutant strain BSA115, σB transcription is inducible by the addition of IPTG and negative control of σB activity by the anti-sigma factor RsbW is absent. In contrast to our expectations of a continuous β-galactosidase activity from a ctc::lacZ fusion, we observed a transient activity in the mutant. To explain this experimental finding, we constructed mathematical models reflecting different hypotheses regarding the regulation of σB and β-galactosidase dynamics. Only the model assuming instability of either ctc::lacZ mRNA or β-galactosidase protein is able to reproduce the experiments in silico. Subsequent Northern blot experiments revealed stable high-level ctc::lacZ mRNA concentrations after the induction of the σB response. Therefore, we conclude that protein instability following σB activation is the most likely explanation for the experimental observations. Our results thus support the idea that B. subtilis increases the cytoplasmic proteolytic degradation to adapt the proteome in face of environmental challenges following activation of the general stress response. The findings also have practical implications for the analysis of stress response dynamics using lacZ reporter gene fusions, a frequently used strategy for the σB response.

T-box-mediated control of the anabolic proline biosynthetic genes of Bacillus subtilis. - Brill, J.; Hoffmann, T.; Putzer, H.; Bremer, E. (Microbiology (Reading), 2011)
Bacillus subtilis possesses interlinked routes for the synthesis of proline. The ProJ-ProA-ProH route is responsible for the production of proline as an osmoprotectant, and the ProB-ProA-ProI route provides proline for protein synthesis. We show here that the transcription of the anabolic proBA and proI genes is controlled in response to proline limitation via a T-box-mediated termination/antitermination regulatory mechanism, a tRNA-responsive riboswitch. Primer extension analysis revealed mRNA leader transcripts of 270 and 269 nt for the proBA and proI genes, respectively, both of which are synthesized from SigA-type promoters. These leader transcripts are predicted to fold into two mutually exclusive secondary mRNA structures, forming either a terminator or an antiterminator configuration. Northern blot analysis allowed the detection of both the leader and the full-length proBA and proI transcripts. Assessment of the level of the proBA transcripts revealed that the amount of the full-length mRNA species strongly increased in proline-starved cultures. Genetic studies with a proB-treA operon fusion reporter strain demonstrated that proBA transcription is sensitively tied to proline availability and is derepressed as soon as cellular starvation for proline sets in. Both the proBA and the proI leader sequences contain a CCU proline-specific specifier codon prone to interact with the corresponding uncharged proline-specific tRNA. By replacing the CCU proline specifier codon in the proBA T-box leader with UUC, a codon recognized by a Phe-specific tRNA, we were able to synthetically re-engineer the proline-specific control of proBA transcription to a control that was responsive to starvation for phenylalanine.
Keywords: Bacillus subtilis/*genetics/*metabolism; *Biosynthetic Pathways; Blotting, Northern; *Gene Expression Regulation, Bacterial; Nucleic Acid Conformation; Phenylalanine/metabolism; Proline/*metabolism; Promoter Regions, Genetic; RNA, Messenger/chemistry/metabolism; RNA, Transfer/metabolism; Recombination, Genetic; *Riboswitch; Terminator Regions, Genetic; Transcription, Genetic

Trigger enzymes: bifunctional proteins active in metabolism and in controlling gene expression. - Commichau, F. M.; Stulke, J. (Mol Microbiol, 2008)
All regulatory processes require components that sense the environmental or metabolic conditions of the cell, and sophisticated sensory proteins have been studied in great detail. During the last few years, it turned out that enzymes can control gene expression in response to the availability of their substrates. Here, we review four different mechanisms by which these enzymes interfere with regulation in bacteria. First, some enzymes have acquired a DNA-binding domain and act as direct transcription repressors by binding DNA in the absence of their substrates. A second class is represented by aconitase, which can bind iron responsive elements in the absence of iron to control the expression of genes involved in iron homoeostasis. The third class of these enzymes is sugar permeases of the phosphotransferase system that control the activity of transcription regulators by phosphorylating them in the absence of the specific substrate. Finally, a fourth class of regulatory enzymes controls the activity of transcription factors by inhibitory protein-protein interactions. We suggest that the enzymes that are active in the control of gene expression should be designated as trigger enzymes. An analysis of the occurrence of trigger enzymes suggests that the duplication and subsequent functional specialization is a major pattern in their evolution.
Keywords: Bacteria/*enzymology/genetics/metabolism; Bacterial Proteins/*metabolism; Enzymes/*metabolism; *Gene Expression Regulation, Bacterial; Metabolic Networks and Pathways; Phosphorylation; Repressor Proteins/metabolism; Signal Transduction; Transcription Factors/*metabolism

Signal Transduction by Trigger Enzymes: Bifunctional Enzymes and Transporters Controlling Gene Expression - Commichau, Fabian M.; Stlke, Jrg (Bacterial Signaling, 2009)

Bet hedging or not? A guide to proper classification of microbial survival strategies. - de Jong, I. G.; Haccou, P.; Kuipers, O. P. (Bioessays, 2011)
Bacteria have developed an impressive ability to survive and propagate in highly diverse and changing environments by evolving phenotypic heterogeneity. Phenotypic heterogeneity ensures that a subpopulation is well prepared for environmental changes. The expression bet hedging is commonly (but often incorrectly) used by molecular biologists to describe any observed phenotypic heterogeneity. In evolutionary biology, however, bet hedging denotes a risk-spreading strategy displayed by isogenic populations that evolved in unpredictably changing environments. Opposed to other survival strategies, bet hedging evolves because the selection environment changes and favours different phenotypes at different times. Consequently, in bet hedging populations all phenotypes perform differently well at any time, depending on the selection pressures present. Moreover, bet hedging is the only strategy in which temporal variance of offspring numbers per individual is minimized. Our paper aims to provide a guide for the correct use of the term bet hedging in molecular biology.
Keywords: *Bacterial Physiological Phenomena; *Biological Evolution; Environment; Genetic Association Studies; *Microbial Viability; Phenotype; *Selection, Genetic

Functional analysis of the sortase YhcS in Bacillus subtilis. - Fasehee, H.; Westers, H.; Bolhuis, A.; Antelmann, H.; Hecker, M.; Quax, W. J.; Mirlohi, A. F.; van Dijl, J. M.; Ahmadian, G. (Proteomics, 2011)
Sortases of Gram-positive bacteria catalyze the covalent C-terminal anchoring of proteins to the cell wall. Bacillus subtilis, a well-known host organism for protein production, contains two putative sortases named YhcS and YwpE. The present studies were aimed at investigating the possible sortase function of these proteins in B. subtilis. Proteomics analyses revealed that sortase-mutant cells released elevated levels of the putative sortase substrate YfkN into the culture medium upon phosphate starvation. The results indicate that YfkN required sortase activity of YhcS for retention in the cell wall. To analyze sortase function in more detail, we focused attention on the potential sortase substrate YhcR, which is co-expressed with the sortase YhcS. Our results showed that the sortase recognition and cell-wall-anchoring motif of YhcR is functional when fused to the Bacillus pumilus chitinase ChiS, a readily detectable reporter protein that is normally secreted. The ChiS fusion protein is displayed at the cell wall surface when YhcS is co-expressed. In the absence of YhcS, or when no cell-wall-anchoring motif is fused to ChiS, the ChiS accumulates predominately in the culture medium. Taken together, these novel findings show that B. subtilis has a functional sortase for anchoring proteins to the cell wall.
Keywords: Amino Acid Sequence; Aminoacyltransferases/genetics/*metabolism; Bacillus subtilis/*enzymology/genetics; Bacterial Proteins/genetics/*metabolism; Cell Wall/enzymology/*metabolism; Chitinases/metabolism; Cysteine Endopeptidases/genetics/*metabolism; Molecular Sequence Data; Mutation; Phosphates/metabolism

SPABBATS: A pathway-discovery method based on Boolean satisfiability that facilitates the characterization of suppressor mutants. - Florez, L. A.; Gunka, K.; Polania, R.; Tholen, S.; Stulke, J. (BMC Syst Biol, 2011)
BACKGROUND: Several computational methods exist to suggest rational genetic interventions that improve the productivity of industrial strains. Nonetheless, these methods are less effective to predict possible genetic responses of the strain after the intervention. This problem requires a better understanding of potential alternative metabolic and regulatory pathways able to counteract the targeted intervention. RESULTS: Here we present SPABBATS, an algorithm based on Boolean satisfiability (SAT) that computes alternative metabolic pathways between input and output species in a reconstructed network. The pathways can be constructed iteratively in order of increasing complexity. SPABBATS allows the accumulation of intermediates in the pathways, which permits discovering pathways missed by most traditional pathway analysis methods. In addition, we provide a proof of concept experiment for the validity of the algorithm. We deleted the genes for the glutamate dehydrogenases of the Gram-positive bacterium Bacillus subtilis and isolated suppressor mutant strains able to grow on glutamate as single carbon source. Our SAT approach proposed candidate alternative pathways which were decisive to pinpoint the exact mutation of the suppressor strain. CONCLUSIONS: SPABBATS is the first application of SAT techniques to metabolic problems. It is particularly useful for the characterization of metabolic suppressor mutants and can be used in a synthetic biology setting to design new pathways with specific input-output requirements.
Keywords: *Algorithms; Bacillus subtilis/cytology/genetics/metabolism; Cell Survival; Computational Biology/*methods; Glutamate Dehydrogenase/metabolism; Glutamic Acid/metabolism; *Logic; Metabolic Networks and Pathways/*genetics; Reproducibility of Results; *Suppression, Genetic

CellPublisher: a web platform for the intuitive visualization and sharing of metabolic, signalling and regulatory pathways. - Florez, L. A.; Lammers, C. R.; Michna, R.; Stulke, J. (Bioinformatics, 2010)
SUMMARY: Systems biology relies increasingly on collaborations between several groups with different expertise. Therefore, the systems biology community is adopting standards that allow effective communication of concepts, as well as transmission and processing of pathway information. The Systems Biology Graphical Notation (SBGN) is a graphical language for biological pathways that has both a biological as well as a computational meaning. The program CellDesigner allows the codification of biological phenomena in an SBGN compliant form. CellPublisher is a web server that allows the conversion of CellDesigner files to web-based navigatable diagrams based on the user interface of Google maps. Thus, CellPublisher complements CellDesigner by facilitating the understanding of complex diagrams and by providing the possibility to share any CellDesigner diagram online with collaborators and get their feedback. Due to the intuitive interface of the online diagrams, CellPublisher serves as a basis for discovery of novel properties of the modelled networks. AVAILABILITY: The freely available web server and the documentation can be accessed at: http://cellpublisher.gobics.de/. The source code and the offline version for Microsoft Windows are freely available at http://sourceforge.net/projects/cellpublisher/. CONTACT: jstuelk@gwdg.de SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Computational Biology; Gene Expression Regulation; Internet; *Metabolic Networks and Pathways; Models, Biological; *Signal Transduction; *Software; Systems Biology/*methods

Metabolic fluxes and beyond-systems biology understanding and engineering of microbial metabolism. - Kohlstedt, M.; Becker, J.; Wittmann, C. (Appl Microbiol Biotechnol, 2010)
The recent years have seen tremendous progress towards the understanding of microbial metabolism on a higher level of the entire functional system. Hereby, huge achievements including the sequencing of complete genomes and efficient post-genomic approaches provide the basis for a new, fascinating era of research-analysis of metabolic and regulatory properties on a global scale. Metabolic flux (fluxome) analysis displays the first systems oriented approach to unravel the physiology of microorganisms since it combines experimental data with metabolic network models and allows determining absolute fluxes through larger networks of central carbon metabolism. Hereby, fluxes are of central importance for systems level understanding because they fundamentally represent the cellular phenotype as integrated output of the cellular components, i.e. genes, transcripts, proteins, and metabolites. A currently emerging and promising area of research in systems biology and systems metabolic engineering is therefore the integration of fluxome data in multi-omics studies to unravel the multiple layers of control that superimpose the flux network and enable its optimal operation under different environmental conditions.
Keywords: Biocatalysis; Biochemical Phenomena; Biotechnology/*methods; Computational Biology/methods; Energy Metabolism; Genetic Engineering/*methods; Industrial Microbiology/*methods; Metabolic Networks and Pathways; Metabolism; *Models, Biological; Oxidation-Reduction; Protein Engineering/methods; Systems Biology/*methods

Carbon source control of the phosphorylation state of the Bacillus subtilis carbon-flux regulator Crh in vivo. - Landmann, J. J.; Werner, S.; Hillen, W.; Stulke, J.; Gorke, B. (FEMS Microbiol Lett, 2012)
Bacillus subtilis possesses carbon-flux regulating histidine protein (Crh), a paralog of the histidine protein (HPr) of the phosphotransferase system (PTS). Like HPr, Crh becomes (de)phosphorylated in vitro at residue Ser46 by the metabolite-controlled HPr kinase/phosphorylase HPrK/P. Depending on its phosphorylation state, Crh exerts regulatory functions in connection with carbohydrate metabolism. So far, knowledge on phosphorylation of Crh in vivo has been limited and derived from indirect evidence. Here, we studied the dynamics of Crh phosphorylation directly by non-denaturing gel electrophoresis followed by Western analysis. The results confirm that HPrK/P is the single kinase catalyzing phosphorylation of Crh in vivo. Accordingly, phosphorylation of Crh is triggered by the carbon source as observed previously for HPr, but with some differences. Phosphorylation of both proteins occurred during exponential growth and disappeared upon exhaustion of the carbon source. During exponential growth, ~80% of the Crh molecules were phosphorylated when cells utilized a preferred carbon source. The reverse distribution, i.e. around 20% of Crh molecules phosphorylated, was obtained upon utilization of less favorable substrates. This clear-cut classification of the substrates into two groups has not previously been observed for HPr(Ser)~P formation. The likely reason for this difference is the additional PTS-dependent phosphorylation of HPr at His15, which limits accumulation of HPr(Ser)~P.
Keywords: Bacillus subtilis/genetics/*metabolism; Bacterial Proteins/genetics/*metabolism; Carbon/metabolism; *Carbon Cycle; Gene Expression Regulation, Bacterial; Phosphoproteins/genetics/*metabolism; Phosphorylation

CcpA forms complexes with CodY and RpoA in Bacillus subtilis. - Wunsche, A.; Hammer, E.; Bartholomae, M.; Volker, U.; Burkovski, A.; Seidel, G.; Hillen, W. (FEBS J, 2012)
The Bacillus subtilis catabolite control protein A (CcpA) is a global transcriptional regulator that is controlled by interactions with the phosphoproteins histidine-containing protein (HPr)Ser46P and the catabolite responsive HPr (Crh)Ser46P and with low molecular weight effectors, depending on the availability of preferred carbon sources such as glucose. Distinct point mutations in CcpA abolish the regulation of some but not all target genes, suggesting additional interactions of CcpA. Therefore, in vivo crosslinking and MS were applied to identify CcpA complexes active in repression and activation. To compensate for an excess of promoters only repressed by CcpA, this experiment was accomplished with cells using multiple copies of the activated ackA promoter. Among the identified proteins HPr, RNA polymerase subunits and the global regulator transcriptional pleiotropic repressor (CodY) were observed. Bacterial two-hybrid assays combining each RNA polymerase subunit with CcpA localized CcpA binding at the alpha-subunit of the RNA polymerase (RpoA). In vivo crosslinking combined with immunoblot analyses revealed CcpA-RpoA complexes in cultures with or without glucose, whereas CcpA-HPr and CcpA-CodY complexes occurred only or predominantly in cultures with glucose. Surface plasmon resonance analyses confirmed the binding of CcpA to the N-terminal domain (alphaNTD) and C-terminal domain (alphaCTD) of RpoA, as well as to CodY. Furthermore, interactions of CodY with the alphaNTD and the alphaCTD were detected by surface plasmon resonance. The K(D) values of complexes of CcpA or CodY with the alphaNTD or the alphaCTD are in the range 5-8 mum. CcpA and CodY form a loose complex with a K(D) of 60 mum. These data were combined to propose a model for a transcription initiation complex at the ackA promoter.
Keywords: Bacillus subtilis/genetics/*metabolism; Bacterial Proteins/genetics/*metabolism; Immunoblotting; Protein Binding; Transcription Factors/genetics/metabolism

RNase Y in Bacillus subtilis: a Natively disordered protein that is the functional equivalent of RNase E from Escherichia coli. - Lehnik-Habrink, M.; Newman, J.; Rothe, F. M.; Solovyova, A. S.; Rodrigues, C.; Herzberg, C.; Commichau, F. M.; Lewis, R. J.; Stulke, J. (J Bacteriol, 2011)
The control of mRNA stability is an important component of regulation in bacteria. Processing and degradation of mRNAs are initiated by an endonucleolytic attack, and the cleavage products are processively degraded by exoribonucleases. In many bacteria, these RNases, as well as RNA helicases and other proteins, are organized in a protein complex called the RNA degradosome. In Escherichia coli, the RNA degradosome is assembled around the essential endoribonuclease E. In Bacillus subtilis, the recently discovered essential endoribonuclease RNase Y is involved in the initiation of RNA degradation. Moreover, RNase Y interacts with other RNases, the RNA helicase CshA, and the glycolytic enzymes enolase and phosphofructokinase in a degradosome-like complex. In this work, we have studied the domain organization of RNase Y and the contribution of the domains to protein-protein interactions. We provide evidence for the physical interaction between RNase Y and the degradosome partners in vivo. We present experimental and bioinformatic data which indicate that the RNase Y contains significant regions of intrinsic disorder and discuss the possible functional implications of this finding. The localization of RNase Y in the membrane is essential both for the viability of B. subtilis and for all interactions that involve RNase Y. The results presented in this study provide novel evidence for the idea that RNase Y is the functional equivalent of RNase E, even though the two enzymes do not share any sequence similarity.
Keywords: Amino Acid Sequence; Bacillus subtilis/*enzymology; Bacterial Proteins/*chemistry/genetics/*metabolism; Computational Biology; Endoribonucleases/*chemistry/genetics/*metabolism; Escherichia coli/enzymology; Molecular Sequence Data; Multienzyme Complexes/metabolism; Polyribonucleotide Nucleotidyltransferase/metabolism; Protein Binding/genetics; Protein Structure, Tertiary; RNA Helicases/metabolism; Sequence Homology, Amino Acid; Two-Hybrid System Techniques

RNA processing in Bacillus subtilis: identification of targets of the essential RNase Y. - Lehnik-Habrink, M.; Schaffer, M.; Mader, U.; Diethmaier, C.; Herzberg, C.; Stulke, J. (Mol Microbiol, 2011)
RNA processing and degradation is initiated by endonucleolytic cleavage of the target RNAs. In many bacteria, this activity is performed by RNase E which is not present in Bacillus subtilis and other Gram-positive bacteria. Recently, the essential endoribonuclease RNase Y has been discovered in B. subtilis. This RNase is involved in the degradation of bulk mRNA suggesting a major role in RNA metabolism. However, only a few targets of RNase Y have been identified so far. In order to assess the global impact of RNase Y, we compared the transcriptomes in response to the expression level of RNase Y. Our results demonstrate that processing by RNase Y results in accumulation of about 550 mRNAs. Some of these targets were substantially stabilized by RNase Y depletion, resulting in half-lives in the range of an hour. Moreover, about 350 mRNAs were less abundant when RNase Y was depleted among them the mRNAs of the operons required for biofilm formation. Interestingly, overexpression of RNase Y was sufficient to induce biofilm formation. The results presented in this work emphasize the importance of RNase Y as the global acting endoribonuclease for B. subtilis.
Keywords: Bacillus subtilis/*enzymology/*metabolism; Gene Expression Profiling; *Gene Expression Regulation, Bacterial; *RNA Processing, Post-Transcriptional; RNA Stability; Ribonucleases/*metabolism; Substrate Specificity

A metabolomics and proteomics study of the adaptation of Staphylococcus aureus to glucose starvation. - Liebeke, M.; Dorries, K.; Zuhlke, D.; Bernhardt, J.; Fuchs, S.; Pane-Farre, J.; Engelmann, S.; Volker, U.; Bode, R.; Dandekar, T.; Lindequist, U.; Hecker, M.; et al. (Mol Biosyst, 2011)
As a versatile pathogen Staphylococcus aureus can cause various disease patterns, which are influenced by strain specific virulence factor repertoires but also by S. aureus physiological adaptation capacity. Here, we present metabolomic descriptions of S. aureus central metabolic pathways and demonstrate the potential for combined metabolomics- and proteomics-based approaches for the basic research of this important pathogen. This study provides a time-resolved picture of more than 500 proteins and 94 metabolites during the transition from exponential growth to glucose starvation. Under glucose excess, cells exhibited higher levels of proteins involved in glycolysis and protein-synthesis, whereas entry into the stationary phase triggered an increase of enzymes of TCC and gluconeogenesis. These alterations in levels of metabolic enzymes were paralleled by more pronounced changes in the concentrations of associated metabolites, in particular, intermediates of the glycolysis and several amino acids.
Keywords: *Adaptation, Physiological; Cluster Analysis; Culture Media, Conditioned/chemistry; Glucose/*metabolism; Intracellular Space/metabolism; Metabolic Networks and Pathways; *Metabolomics; *Proteomics; Staphylococcus aureus/growth & development/metabolism/*physiology

Depletion of thiol-containing proteins in response to quinones in Bacillus subtilis. - Liebeke, M.; Pother, D. C.; van Duy, N.; Albrecht, D.; Becher, D.; Hochgrafe, F.; Lalk, M.; Hecker, M.; Antelmann, H. (Mol Microbiol, 2008)
Quinones are highly toxic naturally occurring thiol-reactive compounds. We have previously described novel pathways for quinone detoxification in the Gram-positive bacterium Bacillus subtilis. In this study, we have investigated the extent of irreversible and reversible thiol modifications caused in vivo by electrophilic quinones. Exposure to toxic benzoquinone (BQ) concentrations leads to depletion of numerous Cys-rich cytoplasmic proteins in the proteome of B. subtilis. Mass spectrometry and immunoblot analyses demonstrated that these BQ-depleted proteins represent irreversibly damaged BQ aggregates that escape the two-dimensional gel separation. This enabled us to quantify the depletion of thiol-containing proteins which are the in vivo targets for thiol-(S)-alkylation by toxic quinone compounds. Metabolomic approaches confirmed that protein depletion is accompanied by depletion of the low-molecular-weight (LMW) thiol cysteine. Finally, no increased formation of disulphide bonds was detected in the thiol-redox proteome in response to sublethal quinone concentrations. The glyceraldehyde-3-phosphate dehydrogenase (GapA) was identified as the only new target for reversible thiol modifications after exposure to toxic quinones. Together our data show that the thiol-(S)-alkylation reaction with protein and non-protein thiols is the in vivo mechanism for thiol depletion and quinone toxicity in B. subtilis and most likely also in other bacteria.
Keywords: Anti-Bacterial Agents/*pharmacology; Bacillus subtilis/*drug effects; Bacterial Proteins/*metabolism; Blotting, Western; Cysteine/metabolism; Cytoplasm/chemistry; Electrophoresis, Gel, Two-Dimensional; Glyceraldehyde-3-Phosphate Dehydrogenases/metabolism; Mass Spectrometry; Metabolic Networks and Pathways; Proteome/analysis; Quinones/*pharmacology; Sulfhydryl Compounds/*metabolism

Environmental salinity determines the specificity and need for Tat-dependent secretion of the YwbN protein in Bacillus subtilis. - van der Ploeg, R.; Mader, U.; Homuth, G.; Schaffer, M.; Denham, E. L.; Monteferrante, C. G.; Miethke, M.; Marahiel, M. A.; Harwood, C. R.; Winter, T.; Hecker, M.; Antelmann, H.; et al. (PLoS One, 2011)
Twin-arginine protein translocation (Tat) pathways are required for transport of folded proteins across bacterial, archaeal and chloroplast membranes. Recent studies indicate that Tat has evolved into a mainstream pathway for protein secretion in certain halophilic archaea, which thrive in highly saline environments. Here, we investigated the effects of environmental salinity on Tat-dependent protein secretion by the Gram-positive soil bacterium Bacillus subtilis, which encounters widely differing salt concentrations in its natural habitats. The results show that environmental salinity determines the specificity and need for Tat-dependent secretion of the Dyp-type peroxidase YwbN in B. subtilis. Under high salinity growth conditions, at least three Tat translocase subunits, namely TatAd, TatAy and TatCy, are involved in the secretion of YwbN. Yet, a significant level of Tat-independent YwbN secretion is also observed under these conditions. When B. subtilis is grown in medium with 1% NaCl or without NaCl, the secretion of YwbN depends strictly on the previously described "minimal Tat translocase" consisting of the TatAy and TatCy subunits. Notably, in medium without NaCl, both tatAyCy and ywbN mutants display significantly reduced exponential growth rates and severe cell lysis. This is due to a critical role of secreted YwbN in the acquisition of iron under these conditions. Taken together, our findings show that environmental conditions, such as salinity, can determine the specificity and need for the secretion of a bacterial Tat substrate.
Keywords: Bacillus subtilis/genetics/growth & development/*metabolism; Bacterial Proteins/genetics/*metabolism; Blotting, Northern; *Environment; Gene Expression Regulation, Bacterial; Genetic Complementation Test; Iron/metabolism; Membrane Transport Proteins/*metabolism; Phenotype; Plasmids/genetics; *Salinity; Transcription, Genetic

Comprehensive identification and quantification of microbial transcriptomes by genome-wide unbiased methods. - Mader, U.; Nicolas, P.; Richard, H.; Bessieres, P.; Aymerich, S. (Curr Opin Biotechnol, 2011)
Genomic tiling array transcriptomics and RNA-seq are two powerful and rapidly developing approaches for unbiased transcriptome analysis. Providing comprehensive identification and quantification of transcripts with an unprecedented resolution, they are leading to major breakthroughs in systems biology. Here we review each step of the analysis from library preparation to the interpretation of the data, with particular attention paid to the possible sources of artifacts. Methodological requirements and statistical frameworks are often similar in both the approaches despite differences in the nature of the data. Tiling array analysis does not require rRNA depletion and benefits from a more mature computational workflow, whereas RNA-Seq has a clear lead in terms of background noise and dynamic range with a considerable potential for evolution with the improvements of sequencing technologies. Being independent of prior sequence knowledge, RNA-seq will boost metatranscriptomics and evolutionary transcriptomics applications.
Keywords: Animals; Artifacts; Bacteria; Gene Expression Profiling/*methods; Gene Library; Genetics, Microbial/*methods; Genome; Genome-Wide Association Study; Humans; Mice; Oligonucleotide Array Sequence Analysis/*methods; RNA/*genetics; Saccharomyces cerevisiae; Sequence Analysis, RNA; Systems Biology

SubtiWiki--a comprehensive community resource for the model organism Bacillus subtilis. - Mader, U.; Schmeisky, A. G.; Florez, L. A.; Stulke, J. (Nucleic Acids Res, 2012)
In the post-genomic era, most components of a cell are known and they can be quantified by large-scale functional genomics approaches. However, genome annotation is the bottleneck that hampers our understanding of living cells and organisms. Up-to-date functional annotation is of special importance for model organisms that provide a frame of reference for studies with other relevant organisms. We have generated a Wiki-type database for the Gram-positive model bacterium Bacillus subtilis, SubtiWiki (http://subtiwiki.uni-goettingen.de/). This Wiki is centered around the individual genes and gene products of B. subtilis and provides information on each aspect of gene function and expression as well as protein activity and its control. SubtiWiki is accompanied by two companion databases SubtiPathways and SubtInteract that provide graphical representations of B. subtilis metabolism and its regulation and of protein-protein interactions, respectively. The diagrams of both databases are easily navigatable using the popular Google maps API, and they are extensively linked with the SubtiWiki gene pages. Moreover, each gene/gene product was assigned to one or more functional categories and transcription factor regulons. Pages for the specific categories and regulons provide a rapid overview of functionally related genes/proteins. Today, SubtiWiki can be regarded as one of the most complete inventories of knowledge on a living organism in one single resource.
Keywords: Bacillus subtilis/*genetics/metabolism; Bacterial Proteins/genetics; *Databases, Genetic; Genes, Bacterial; Internet; Models, Biological; Molecular Sequence Annotation; Protein Interaction Mapping; Regulon; Transcription Factors/metabolism

Dissection of the network of interactions that links RNA processing with glycolysis in the Bacillus subtilis degradosome. - Newman, J. A.; Hewitt, L.; Rodrigues, C.; Solovyova, A. S.; Harwood, C. R.; Lewis, R. J. (J Mol Biol, 2012)
The RNA degradosome is a multiprotein macromolecular complex that is involved in the degradation of messenger RNA in bacteria. The composition of this complex has been found to display a high degree of evolutionary divergence, which may reflect the adaptation of species to different environments. Recently, a degradosome-like complex identified in Bacillus subtilis was found to be distinct from those found in proteobacteria, the degradosomes of which are assembled around the unstructured C-terminus of ribonuclease E, a protein not present in B. subtilis. In this report, we have investigated in vitro the binary interactions between degradosome components and have characterized interactions between glycolytic enzymes, RNA-degrading enzymes, and those that appear to link these two cellular processes. The crystal structures of the glycolytic enzymes phosphofructokinase and enolase are presented and discussed in relation to their roles in the mediation of complex protein assemblies. Taken together, these data provide valuable insights into the structure and dynamics of the RNA degradosome, a fascinating and complex macromolecular assembly that links RNA degradation with central carbon metabolism.
Keywords: Bacillus subtilis/*enzymology/*genetics/*metabolism; Crystallography, X-Ray/methods; Endoribonucleases/*chemistry/genetics/*metabolism; Escherichia coli/enzymology/metabolism; Glycolysis/physiology; Models, Molecular; Multienzyme Complexes/*chemistry/genetics/*metabolism; Phosphofructokinases/chemistry/metabolism; Phosphopyruvate Hydratase/chemistry/metabolism; Polyribonucleotide Nucleotidyltransferase/*chemistry/genetics/*metabolism; Protein Interaction Maps/physiology; RNA Helicases/*chemistry/genetics/*metabolism; RNA Stability/physiology; RNA, Messenger/genetics/*metabolism; Ribonucleases/metabolism

Cellular Adjustments of Bacillus subtilis and Other Bacilli to Fluctuating Salinities - Pittelkow, Marco; Bremer, Erhard (Halophiles and Hypersaline Environments, 2011)

The role of the 5'-3' exoribonuclease XRNA in transcriptome-wide mRNA degradation. - Manful, T.; Fadda, A.; Clayton, C. (RNA, 2011)
The steady-state level of each mRNA in a cell is a balance between synthesis and degradation. Here, we use high-throughput RNA sequencing (RNASeq) to determine the relationship between mRNA degradation and mRNA abundance on a transcriptome-wide scale. The model organism used was the bloodstream form of Trypanosoma brucei, a protist that lacks regulation of RNA polymerase II initiation. The mRNA half-lives varied over two orders of magnitude, with a median half-life of 13 min for total (rRNA-depleted) mRNA. Data for poly(A)+ RNA yielded shorter half-lives than for total RNA, indicating that removal of the poly(A) tail was usually the first step in degradation. Depletion of the major 5'-3' exoribonuclease, XRNA, resulted in the stabilization of most mRNAs with half-lives under 30 min. Thus, on a transcriptome-wide scale, degradation of most mRNAs is initiated by deadenylation. Trypanosome mRNA levels are strongly influenced by gene copy number and mRNA half-life: Very abundant mRNAs that are required throughout the life-cycle may be encoded by multicopy genes and have intermediate-to-long half-lives; those encoding ribosomal proteins, with one to two gene copies, are exceptionally stable. Developmentally regulated transcripts with a lower abundance in the bloodstream forms than the procyclic forms had half-lives around the median, whereas those with a higher abundance in the bloodstream forms than the procyclic forms, such as those encoding glycolytic enzymes, had longer half-lives.
Keywords: Exoribonucleases/*metabolism; Open Reading Frames; *RNA Stability; RNA, Messenger/*metabolism; RNA, Protozoan/*metabolism; Transcriptome; Trypanosoma brucei brucei/*enzymology/genetics

SABIO-RK--database for biochemical reaction kinetics. - Wittig, U.; Kania, R.; Golebiewski, M.; Rey, M.; Shi, L.; Jong, L.; Algaa, E.; Weidemann, A.; Sauer-Danzwith, H.; Mir, S.; Krebs, O.; Bittkowski, M.; et al. (Nucleic Acids Res, 2012)
SABIO-RK (http://sabio.h-its.org/) is a web-accessible database storing comprehensive information about biochemical reactions and their kinetic properties. SABIO-RK offers standardized data manually extracted from the literature and data directly submitted from lab experiments. The database content includes kinetic parameters in relation to biochemical reactions and their biological sources with no restriction on any particular set of organisms. Additionally, kinetic rate laws and corresponding equations as well as experimental conditions are represented. All the data are manually curated and annotated by biological experts, supported by automated consistency checks. SABIO-RK can be accessed via web-based user interfaces or automatically via web services that allow direct data access by other tools. Both interfaces support the export of the data together with its annotations in SBML (Systems Biology Markup Language), e.g. for import in modelling tools.
Keywords: *Biochemical Phenomena; *Databases, Factual; Enzymes/metabolism; Internet; Kinetics; User-Computer Interface

My data are your data - Marx, Vivien (Nat Biotechnol, 2012)
Encouraging more broad and inclusive data sharing in today's world will involve concerted community efforts to overcome technical barriers and human foibles. Vivien Marx investigates.

From steady-state to synchronized yeast glycolytic oscillations II: model validation. - du Preez, F. B.; van Niekerk, D. D.; Snoep, J. L. (FEBS J, 2012)
In an accompanying paper [du Preez et al., (2012) FEBS J279, 2810-2822], we adapt an existing kinetic model for steady-state yeast glycolysis to simulate limit-cycle oscillations. Here we validate the model by testing its capacity to simulate a wide range of experiments on dynamics of yeast glycolysis. In addition to its description of the oscillations of glycolytic intermediates in intact cells and the rapid synchronization observed when mixing out-of-phase oscillatory cell populations (see accompanying paper), the model was able to predict the Hopf bifurcation diagram with glucose as the bifurcation parameter (and one of the bifurcation points with cyanide as the bifurcation parameter), the glucose- and acetaldehyde-driven forced oscillations, glucose and acetaldehyde quenching, and cell-free extract oscillations (including complex oscillations and mixed-mode oscillations). Thus, the model was compliant, at least qualitatively, with the majority of available experimental data for glycolytic oscillations in yeast. To our knowledge, this is the first time that a model for yeast glycolysis has been tested against such a wide variety of independent data sets. DATABASE: The mathematical models described here have been submitted to the JWS Online Cellular Systems Modelling Database and can be accessed at http://jjj.biochem.sun.ac.za/database/dupreez/index.html.
Keywords: Acetaldehyde/metabolism; Adenosine Triphosphate/metabolism; Cell-Free System/physiology; Cyanides/pharmacology; Glucose/metabolism; *Glycolysis/drug effects; Kinetics; *Models, Biological; NAD/metabolism; Saccharomyces cerevisiae/drug effects/*metabolism; Systems Biology

From steady-state to synchronized yeast glycolytic oscillations I: model construction. - du Preez, F. B.; van Niekerk, D. D.; Kooi, B.; Rohwer, J. M.; Snoep, J. L. (FEBS J, 2012)
An existing detailed kinetic model for the steady-state behavior of yeast glycolysis was tested for its ability to simulate dynamic behavior. Using a small subset of experimental data, the original model was adapted by adjusting its parameter values in three optimization steps. Only small adaptations to the original model were required for realistic simulation of experimental data for limit-cycle oscillations. The greatest changes were required for parameter values for the phosphofructokinase reaction. The importance of ATP for the oscillatory mechanism and NAD(H) for inter-and intra-cellular communications and synchronization was evident in the optimization steps and simulation experiments. In an accompanying paper [du Preez F et al. (2012) FEBS J279, 2823-2836], we validate the model for a wide variety of experiments on oscillatory yeast cells. The results are important for re-use of detailed kinetic models in modular modeling approaches and for approaches such as that used in the Silicon Cell initiative. DATABASE: The mathematical models described here have been submitted to the JWS Online Cellular Systems Modelling Database and can be accessed at http://jjj.biochem.sun.ac.za/database/dupreez/index.html.
Keywords: Acetaldehyde/metabolism; Adenosine Triphosphatases/metabolism; Cell Communication/physiology; Computer Simulation; Databases, Factual; *Glycolysis; Kinetics; Metabolic Networks and Pathways; *Models, Biological; NAD/metabolism; Phosphofructokinases/metabolism; Saccharomyces cerevisiae/*metabolism; Systems Biology

Systems analysis of transcription factor activities in environments with stable and dynamic oxygen concentrations. - Rolfe, M. D.; Ocone, A.; Stapleton, M. R.; Hall, S.; Trotter, E. W.; Poole, R. K.; Sanguinetti, G.; Green, J. (Open Biol, 2012)
Understanding gene regulation requires knowledge of changes in transcription factor (TF) activities. Simultaneous direct measurement of numerous TF activities is currently impossible. Nevertheless, statistical approaches to infer TF activities have yielded non-trivial and verifiable predictions for individual TFs. Here, global statistical modelling identifies changes in TF activities from transcript profiles of Escherichia coli growing in stable (fixed oxygen availabilities) and dynamic (changing oxygen availability) environments. A core oxygen-responsive TF network, supplemented by additional TFs acting under specific conditions, was identified. The activities of the cytoplasmic oxygen-responsive TF, FNR, and the membrane-bound terminal oxidases implied that, even on the scale of the bacterial cell, spatial effects significantly influence oxygen-sensing. Several transcripts exhibited asymmetrical patterns of abundance in aerobic to anaerobic and anaerobic to aerobic transitions. One of these transcripts, ndh, encodes a major component of the aerobic respiratory chain and is regulated by oxygen-responsive TFs ArcA and FNR. Kinetic modelling indicated that ArcA and FNR behaviour could not explain the ndh transcript profile, leading to the identification of another TF, PdhR, as the source of the asymmetry. Thus, this approach illustrates how systematic examination of regulatory responses in stable and dynamic environments yields new mechanistic insights into adaptive processes.
Keywords: Aerobiosis/physiology; Anaerobiosis/physiology; Bacterial Outer Membrane Proteins/*metabolism; Escherichia coli/*metabolism; Escherichia coli Proteins/*metabolism; Iron-Sulfur Proteins/*metabolism; Kinetics; *Models, Biological; Oxygen/*metabolism/pharmacology; Repressor Proteins/*metabolism

‘Domino’ systems biology and the ‘A’ of ATP (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2012)
We develop a strategic ‘domino’ approach that starts with one key feature of cell function and the main process providing for it, and then adds additional processes and components only as necessary to explain provoked experimental observations. The approach is here applied to the energy metabolism of yeast in a glucose limited chemostat, subjected to a sudden increase in glucose. The puzzles addressed include (i) the lack of increase in ATP upon glucose addition, (ii) the lack of increase in ADP when ATP is hydrolyzed, and (iii) the rapid disappearance of the ‘A’ (adenine) moiety of ATP. Neither the incorporation of nucleotides into new biomass, nor steady de novo synthesis of AMP explains. Cycling of the ‘A’ moiety accelerates when the cell's energy state is endangered, another essential domino among the seven required for understanding of the experimental observations. This new domino analysis shows how strategic experimental design and observations in tandem with theory and modeling may identify and resolve important paradoxes. It also highlights the hitherto unexpected role of the ‘A’ component of ATP.

Stealthy annotation of experimental biology by spreadsheets - Wolstencroft, Katy; Owen, Stuart; Horridge, Matthew; Jupp, Simon; Krebs, Olga; Snoep, Jacky; du Preez, Franco; Müller, Wolfgang; Stevens, Robert; Goble, Carole (Concurrency and Computation: Practice and Experience, 2013)
The increase in volume and complexity of biological data has led to increased requirements to reuse that data. Consistent and accurate metadata is essential for this task, creating new challenges in semantic data annotation and in the constriction of terminologies and ontologies used for annotation. The BioSharing community are developing standards and terminologies for annotation, which have been adopted across bioinformatics, but the real challenge is to make these standards accessible to laboratory scientists. Widespread adoption requires the provision of tools to assist scientists whilst reducing the complexities of working with semantics. This paper describes unobtrusive ‘stealthy’ methods for collecting standards compliant, semantically annotated data and for contributing to ontologies used for those annotations. Spreadsheets are ubiquitous in laboratory data management. Our spreadsheet-based RightField tool enables scientists to structure information and select ontology terms for annotation within spreadsheets, producing high quality, consistent data without changing common working practices. Furthermore, our Populous spreadsheet tool proves effective for gathering domain knowledge in the form of Web Ontology Language (OWL) ontologies. Such a corpus of structured and semantically enriched knowledge can be extracted in Resource Description Framework (RDF), providing further means for searching across the content and contributing to Open Linked Data (http://linkeddata.org/)

Hypothesis: emergence of translation as a result of RNA helicase evolution. - Zenkin, N. (J Mol Evol, 2012)
The origin of translation and the genetic code is one of the major mysteries of evolution. The advantage of templated protein synthesis could have been achieved only when the translation apparatus had already become very complex. This means that the translation machinery, as we know it today, must have evolved towards some different essential function that subsequently sub-functionalised into templated protein synthesis. The hypothesis presented here proposes that translation originated as the result of evolution of a primordial RNA helicase, which has been essential for preventing dying out of the RNA organism in sterile double-stranded form. This hypothesis emerges because modern ribosome possesses RNA helicase activity that likely dates back to the RNA world. I hypothesise that codon-anticodon interactions of tRNAs with mRNA evolved as a mechanism used by RNA helicase, the predecessor of ribosomes, to melt RNA duplexes. In this scenario, peptide bond formation emerged to drive unidirectional movement of the helicase via a molecular ratchet mechanism powered by Brownian motion. I propose that protein synthesis appeared as a side product of helicase activity. The first templates for protein synthesis were functional RNAs (ribozymes) that were unwound by the helicase, and the first synthesised proteins were of random or non-sense sequence. I further suggest that genetic code emerged to avoid this randomness. The initial genetic code thus emerged as an assignment of amino acids to codons according to the sequences of the pre-existing RNAs to take advantage of the side products of RNA helicase function.
Keywords: Aminoacylation; Animals; *Evolution, Molecular; Humans; *Models, Genetic; Nucleic Acid Conformation; Protein Biosynthesis/*genetics; RNA/genetics/metabolism; RNA Helicases/*genetics

Single cell analysis of gene expression patterns during carbon starvation in Bacillus subtilis reveals large phenotypic variation. - de Jong, I. G.; Veening, J. W.; Kuipers, O. P. (Environ Microbiol, 2012)
How cells dynamically respond to fluctuating environmental conditions depends on the architecture and noise of the underlying genetic circuits. Most work characterizing stress pathways in the model bacterium Bacillus subtilis has been performed on bulk cultures using ensemble assays. However, investigating the single cell response to stress is important since noise might generate significant phenotypic heterogeneity. Here, we study the stress response to carbon source starvation and compare both population and single cell data. Using a top-down approach, we investigate the transcriptional dynamics of various stress-related genes of B. subtilis in response to carbon source starvation and to increased cell density. Our data reveal that most of the tested gene-regulatory networks respond highly heterogeneously to starvation and cells show a large degree of variation in gene expression. The level of highly dynamic diversification within B. subtilis populations under changing environments reflects the necessity to study cells at the single cell level.
Keywords: Bacillus subtilis/*genetics/*metabolism; Biotransformation/genetics; Carbon/*metabolism; *Gene Expression Regulation, Bacterial; Genetic Heterogeneity; Phenotype; Single-Cell Analysis; Stress, Physiological/*genetics

GraphAlignment: Bayesian pairwise alignment of biological networks. - Kolar, M.; Meier, J.; Mustonen, V.; Lassig, M.; Berg, J. (BMC Syst Biol, 2012)
BACKGROUND: With increased experimental availability and accuracy of bio-molecular networks, tools for their comparative and evolutionary analysis are needed. A key component for such studies is the alignment of networks. RESULTS: We introduce the Bioconductor package GraphAlignment for pairwise alignment of bio-molecular networks. The alignment incorporates information both from network vertices and network edges and is based on an explicit evolutionary model, allowing inference of all scoring parameters directly from empirical data. We compare the performance of our algorithm to an alternative algorithm, Graemlin 2.0.On simulated data, GraphAlignment outperforms Graemlin 2.0 in several benchmarks except for computational complexity. When there is little or no noise in the data, GraphAlignment is slower than Graemlin 2.0. It is faster than Graemlin 2.0 when processing noisy data containing spurious vertex associations. Its typical case complexity grows approximately as O(N2.6).On empirical bacterial protein-protein interaction networks (PIN) and gene co-expression networks, GraphAlignment outperforms Graemlin 2.0 with respect to coverage and specificity, albeit by a small margin. On large eukaryotic PIN, Graemlin 2.0 outperforms GraphAlignment. CONCLUSIONS: The GraphAlignment algorithm is robust to spurious vertex associations, correctly resolves paralogs, and shows very good performance in identification of homologous vertices defined by high vertex and/or interaction similarity. The simplicity and generality of GraphAlignment edge scoring makes the algorithm an appropriate choice for global alignment of networks.
Keywords: *Algorithms; Bayes Theorem; Computational Biology/*methods; *Computer Graphics

Glucose Transport in Escherichia coli Mutant Strains with Defects in Sugar Transport Systems (Journal of Bacteriology, 2012)
In Escherichia coli several systems are known to transport glucose into the cytoplasm. The main glucose uptake system under batch conditions is the glucose phosphoenolpyruvate:carbohydrate phosphotransferase system (glucose-PTS), but also the mannose-PTS, as well as the galactose and maltose transporters can translocate glucose. Mutant strains which lack the EIIBC protein of the glucose-PTS have been previously investigated because their lower rate of acetate formation offers advantages in industrial applications. Nevertheless, a systematic study to analyze the impact of the different glucose uptake systems has not been undertaken. Specifically, how the bacteria cope with the deletion of the major glucose uptake system and which alternative transporters react to compensate for this deficit has not been studied in detail. Therefore, a series of mutant strains were analyzed in aerobic and anaerobic batch cultures, as well as in glucose limited continuous cultivations. Deletion of EIIBC, disturbs glucose transport severely. cAMP-CRP levels rise, induction of the mgl-operon occurs. Nevertheless mgl transcription is not essential, as deletion of this transporter did not affect growth rate; the activities of the remaining transporters seems to be sufficient by induction of the galactose and maltose transporters. Despite the strong up-regulation of mgl under glucose limitations, deletion of this transport-system did not lead to further changes.

Malate-mediated carbon catabolite repression in Bacillus subtilis involves the HPrK/CcpA pathway. - Meyer, F. M.; Jules, M.; Mehne, F. M.; Le Coq, D.; Landmann, J. J.; Gorke, B.; Aymerich, S.; Stulke, J. (J Bacteriol, 2011)
Most organisms can choose their preferred carbon source from a mixture of nutrients. This process is called carbon catabolite repression. The Gram-positive bacterium Bacillus subtilis uses glucose as the preferred source of carbon and energy. Glucose-mediated catabolite repression is caused by binding of the CcpA transcription factor to the promoter regions of catabolic operons. CcpA binds DNA upon interaction with its cofactors HPr(Ser-P) and Crh(Ser-P). The formation of the cofactors is catalyzed by the metabolite-activated HPr kinase/phosphorylase. Recently, it has been shown that malate is a second preferred carbon source for B. subtilis that also causes catabolite repression. In this work, we addressed the mechanism by which malate causes catabolite repression. Genetic analyses revealed that malate-dependent catabolite repression requires CcpA and its cofactors. Moreover, we demonstrate that HPr(Ser-P) is present in malate-grown cells and that CcpA and HPr interact in vivo in the presence of glucose or malate but not in the absence of a repressing carbon source. The formation of the cofactor HPr(Ser-P) could be attributed to the concentrations of ATP and fructose 1,6-bisphosphate in cells growing with malate. Both metabolites are available at concentrations that are sufficient to stimulate HPr kinase activity. The adaptation of cells to environmental changes requires dynamic metabolic and regulatory adjustments. The repression strength of target promoters was similar to that observed in steady-state growth conditions, although it took somewhat longer to reach the second steady-state of expression when cells were shifted to malate.
Keywords: Bacillus subtilis/genetics/*metabolism; Bacterial Proteins/genetics/*metabolism; *Catabolite Repression; Gene Expression Regulation, Bacterial; Malates/*metabolism; Protein Binding; Protein Serine-Threonine Kinases/genetics/*metabolism; Repressor Proteins/genetics/*metabolism

A high-frequency mutation in Bacillus subtilis: requirements for the decryptification of the gudB glutamate dehydrogenase gene. - Gunka, K.; Tholen, S.; Gerwig, J.; Herzberg, C.; Stulke, J.; Commichau, F. M. (J Bacteriol, 2012)
Common laboratory strains of Bacillus subtilis encode two glutamate dehydrogenases: the enzymatically active protein RocG and the cryptic enzyme GudB that is inactive due to a duplication of three amino acids in its active center. The inactivation of the rocG gene results in poor growth of the bacteria on complex media due to the accumulation of toxic intermediates. Therefore, rocG mutants readily acquire suppressor mutations that decryptify the gudB gene. This decryptification occurs by a precise deletion of one part of the 9-bp direct repeat that causes the amino acid duplication. This mutation occurs at the extremely high frequency of 10(-4). Mutations affecting the integrity of the direct repeat result in a strong reduction of the mutation frequency; however, the actual sequence of the repeat is not essential. The mutation frequency of gudB was not affected by the position of the gene on the chromosome. When the direct repeat was placed in the completely different context of an artificial promoter, the precise deletion of one part of the repeat was also observed, but the mutation frequency was reduced by 3 orders of magnitude. Thus, transcription of the gudB gene seems to be essential for the high frequency of the appearance of the gudB1 mutation. This idea is supported by the finding that the transcription-repair coupling factor Mfd is required for the decryptification of gudB. The Mfd-mediated coupling of transcription to mutagenesis might be a built-in precaution that facilitates the accumulation of mutations preferentially in transcribed genes.
Keywords: Bacillus subtilis/*enzymology/*genetics; Bacterial Proteins/genetics/*metabolism; DNA, Bacterial/genetics; Glutamate Dehydrogenase/genetics/*metabolism; *Mutation; *Pseudogenes; Repetitive Sequences, Nucleic Acid; Suppression, Genetic; Transcription Factors/genetics/*metabolism; Transcription, Genetic

Malate metabolism in Bacillus subtilis: distinct roles for three classes of malate-oxidizing enzymes. - Meyer, F. M.; Stulke, J. (FEMS Microbiol Lett, 2013)
The Gram-positive soil bacterium Bacillus subtilis uses glucose and malate as the preferred carbon sources. In the presence of either glucose or malate, the expression of genes and operons for the utilization of secondary carbon sources is subject to carbon catabolite repression. While glucose is a preferred substrate in many organisms from bacteria to man, the factors that contribute to the preference for malate have so far remained elusive. In this work, we have studied the contribution of the different malate-metabolizing enzymes in B. subtilis, and we have elucidated their distinct functions. The malate dehydrogenase and the phosphoenolpyruvate carboxykinase are both essential for malate utilization; they introduce malate into gluconeogenesis. The NADPH-generating malic enzyme YtsJ is important to establish the cellular pools of NADPH for anabolic reactions. Finally, the NADH-generating malic enzymes MaeA, MalS, and MleA are involved in keeping the ATP levels high. Together, this unique array of distinct activities makes malate a preferred carbon source for B. subtilis.
Keywords: Adenosine Triphosphate/metabolism; Bacillus subtilis/*enzymology/genetics/metabolism; Bacterial Proteins/genetics/*metabolism; Gluconeogenesis; Malate Dehydrogenase/genetics/*metabolism; Malates/*metabolism; Mutation; Phosphoenolpyruvate Carboxykinase (ATP)/genetics/*metabolism

RNA degradation in Bacillus subtilis: an interplay of essential endo- and exoribonucleases. - Lehnik-Habrink, M.; Lewis, R. J.; Mader, U.; Stulke, J. (Mol Microbiol, 2012)
RNA processing and degradation are key processes in the control of transcript accumulation and thus in the control of gene expression. In Escherichia coli, the underlying mechanisms and components of RNA decay are well characterized. By contrast, Gram-positive bacteria do not possess several important players of E. coli RNA degradation, most notably the essential enzyme RNase E. Recent research on the model Gram-positive organism, Bacillus subtilis, has identified the essential RNases J1 and Y as crucial enzymes in RNA degradation. While RNase J1 is the first bacterial exoribonuclease with 5'-to-3' processivity, RNase Y is the founding member of a novel class of endoribonucleases. Both RNase J1 and RNase Y have a broad impact on the stability of B. subtilis mRNAs; a depletion of either enzyme affects more than 25% of all mRNAs. RNases J1 and Y as well as RNase J2, the polynucleotide phosphorylase PNPase, the RNA helicase CshA and the glycolytic enzymes enolase and phosphofructokinase have been proposed to form a complex, the RNA degradosome of B. subtilis. This review presents a model, based on recent published data, of RNA degradation in B. subtilis. Degradation is initiated by RNase Y-dependent endonucleolytic cleavage, followed by processive exoribonucleolysis of the generated fragments both in 3'-to-5' and in 5'-to-3' directions. The implications of these findings for pathogenic Gram-positive bacteria are also discussed.
Keywords: Bacillus subtilis/*enzymology/*metabolism; Endoribonucleases/*metabolism; Exoribonucleases/*metabolism; Models, Biological; Models, Molecular; RNA/*metabolism; *RNA Stability

High- and low-affinity cre boxes for CcpA binding in Bacillus subtilis revealed by genome-wide analysis. - Marciniak, B. C.; Pabijaniak, M.; de Jong, A.; Duhring, R.; Seidel, G.; Hillen, W.; Kuipers, O. P. (BMC Genomics, 2012)
BACKGROUND: In Bacillus subtilis and its relatives carbon catabolite control, a mechanism enabling to reach maximal efficiency of carbon and energy sources metabolism, is achieved by the global regulator CcpA (carbon catabolite protein A). CcpA in a complex with HPr-Ser-P (seryl-phosphorylated form of histidine-containing protein, HPr) binds to operator sites called catabolite responsive elements, cre. Depending on the cre box position relative to the promoter, the CcpA/HPr-Ser-P complex can either act as a positive or a negative regulator. The cre boxes are highly degenerate semi-palindromes with a lowly conserved consensus sequence. So far, studies aimed at revealing how CcpA can bind such diverse sites were focused on the analysis of single cre boxes. In this study, a genome-wide analysis of cre sites was performed in order to identify differences in cre sequence and position, which determine their binding affinity. RESULTS: The transcriptomes of B. subtilis cultures with three different CcpA expression levels were compared. The higher the amount of CcpA in the cells, the more operons possessing cre sites were differentially regulated. The cre boxes that mediated regulation at low CcpA levels were designated as strong (high affinity) and those which responded only to high amounts of CcpA, as weak (low affinity). Differences in the sequence and position in relation to the transcription start site between strong and weak cre boxes were revealed. CONCLUSIONS: Certain residues at specific positions in the cre box as well as, to a certain extent, a more palindromic nature of cre sequences and the location of cre in close vicinity to the transcription start site contribute to the strength of CcpA-dependent regulation. The main factors contributing to cre regulatory efficiencies, enabling subtle differential control of various subregulons of the CcpA regulon, are identified.
Keywords: Bacillus subtilis/genetics/*metabolism; Bacterial Proteins/*metabolism; Binding Sites; Gene Expression Regulation, Bacterial; Genome, Bacterial/*genetics; Genome-Wide Association Study

Novel twin-arginine translocation pathway-dependent phenotypes of Bacillus subtilis unveiled by quantitative proteomics. - Goosens, V. J.; Otto, A.; Glasner, C.; Monteferrante, C. C.; van der Ploeg, R.; Hecker, M.; Becher, D.; van Dijl, J. M. (J Proteome Res, 2013)
The twin-arginine translocation (Tat) pathway is known to translocate fully folded proteins across bacterial, archaeal, and organellar membranes. To date, the mechanisms involved in processing, proofreading, and quality control of Tat substrates have remained largely elusive. Bacillus subtilis is an industrially relevant Gram-positive model bacterium. The Tat pathway in B. subtilis differs from that of other well-studied organisms in that it is composed of two complexes operating in parallel. To obtain a better understanding of this pathway in B. subtilis and to identify Tat-associated proteins, the B. subtilis 'Tat proteome' was investigated by quantitative proteomics. Metabolically labeled proteins from cytoplasmic, membrane, and extracellular fractions were analyzed by LC-MS/MS. Changes in the amounts of identified peptides allowed for quantitative comparisons of their abundance in tat mutant strains. The observed differences were suggestive of indirect or direct protein-protein relationships. The rich data set generated was then approached in hypothesis-driving and hypothesis-driven manners. The hypothesis-driving approach led to the identification of a novel delayed biofilm phenotype of certain tat mutant strains, whereas the hypothesis-driven approach identified the membrane protein QcrA as a new Tat substrate of B. subtilis. Thus, our quantitative proteomics analyses have unveiled novel Tat pathway-dependent phenotypes in Bacillus.
Keywords: Arginine/*chemistry; Bacillus subtilis/*metabolism; Biofilms/growth & development; Cell Membrane/metabolism; Chromatography, Liquid; Cytoplasm/metabolism; Extracellular Space/metabolism; Membrane Transport Proteins/*isolation & purification/metabolism; Phenotype; Protein Transport; Proteomics; Tandem Mass Spectrometry

DEAD-Box RNA helicases in Bacillus subtilis have multiple functions and act independently from each other. - Lehnik-Habrink, M.; Rempeters, L.; Kovacs, A. T.; Wrede, C.; Baierlein, C.; Krebber, H.; Kuipers, O. P.; Stulke, J. (J Bacteriol, 2013)
DEAD-box RNA helicases play important roles in remodeling RNA molecules and in facilitating a variety of RNA-protein interactions that are key to many essential cellular processes. In spite of the importance of RNA, our knowledge about RNA helicases is limited. In this study, we investigated the role of the four DEAD-box RNA helicases in the Gram-positive model organism Bacillus subtilis. A strain deleted of all RNA helicases is able to grow at 37 degrees C but not at lower temperatures. The deletion of cshA, cshB, or yfmL in particular leads to cold-sensitive phenotypes. Moreover, these mutant strains exhibit unique defects in ribosome biogenesis, suggesting distinct functions for the individual enzymes in this process. Based on protein accumulation, severity of the cold-sensitive phenotype, and the interaction with components of the RNA degradosome, CshA is the major RNA helicase of B. subtilis. To unravel the functions of CshA in addition to ribosome biogenesis, we conducted microarray analysis and identified the ysbAB and frlBONMD mRNAs as targets that are strongly affected by the deletion of the cshA gene. Our findings suggest that the different helicases make distinct contributions to the physiology of B. subtilis. Ribosome biogenesis and RNA degradation are two of their major tasks in B. subtilis.
Keywords: Bacillus subtilis/*enzymology/genetics/*metabolism; Bacterial Proteins/genetics/*metabolism; DEAD-box RNA Helicases/genetics/*metabolism; Gene Deletion; Gene Expression Regulation, Bacterial/*physiology; Gene Expression Regulation, Enzymologic/*physiology; Protein Binding; RNA Stability; RNA, Messenger/genetics/metabolism; Ribosomes/metabolism; Temperature

Osmotic control of opuA expression in Bacillus subtilis and its modulation in response to intracellular glycine betaine and proline pools. - Hoffmann, T.; Wensing, A.; Brosius, M.; Steil, L.; Volker, U.; Bremer, E. (J Bacteriol, 2013)
Glycine betaine is an effective osmoprotectant for Bacillus subtilis. Its import into osmotically stressed cells led to the buildup of large pools, whose size was sensitively determined by the degree of the osmotic stress imposed. The amassing of glycine betaine caused repression of the formation of an osmostress-adaptive pool of proline, the only osmoprotectant that B. subtilis can synthesize de novo. The ABC transporter OpuA is the main glycine betaine uptake system of B. subtilis. Expression of opuA was upregulated in response to both sudden and sustained increases in the external osmolarity. Nonionic osmolytes exerted a stronger inducing effect on transcription than ionic osmolytes, and this was reflected in the development of corresponding OpuA-mediated glycine betaine pools. Primer extension analysis and site-directed mutagenesis pinpointed the osmotically controlled opuA promoter. Deviations from the consensus sequence of SigA-type promoters serve to keep the transcriptional activity of the opuA promoter low in the absence of osmotic stress. opuA expression was downregulated in a finely tuned manner in response to increases in the intracellular glycine betaine pool, regardless of whether this osmoprotectant was imported or was newly synthesized from choline. Such an effect was also exerted by carnitine, an effective osmoprotectant for B. subtilis that is not a substrate for the OpuA transporter. opuA expression was upregulated in a B. subtilis mutant that was unable to synthesize proline in response to osmotic stress. Collectively, our data suggest that the intracellular solute pool is a key determinant for the osmotic control of opuA expression.
Keywords: ATP-Binding Cassette Transporters/genetics/*metabolism; Bacillus subtilis/classification/drug effects/*metabolism; Bacterial Proteins/genetics/*metabolism; Betaine/metabolism/*pharmacology; Escherichia coli/genetics/metabolism; Gene Expression Regulation, Bacterial/*physiology; Multigene Family; Mutagenesis, Site-Directed; Osmolar Concentration; Osmotic Pressure; Plasmids; Proline/metabolism/*pharmacology; Sodium Chloride

A mathematical modelling approach to assessing the reliability of biomarkers of glutathione metabolism. - Geenen, S.; du Preez, F. B.; Reed, M.; Nijhout, H. F.; Kenna, J. G.; Wilson, I. D.; Westerhoff, H. V.; Snoep, J. L. (Eur J Pharm Sci, 2012)
One of the main pathways for the detoxification of reactive metabolites in the liver involves glutathione conjugation. Metabolic profiling studies have shown paradoxical responses in glutathione-related biochemical pathways. One of these is the increase in 5-oxoproline and ophthalmic acid concentrations with increased dosage of paracetamol. Experimental studies have thus far failed to resolve these paradoxes and the robustness of how these proposed biomarkers correlate with liver glutathione levels has been questioned. To better understand how these biomarkers behave in the glutathione system a kinetic model of this pathway was made. By using metabolic control analysis and by simulating biomarker levels under a variety of conditions, we found that 5-oxoproline and ophthalmic acid concentrations may not only depend on the glutathione but also on the methionine status of the cell. We show that neither of the two potential biomarkers are reliable on their own since they need additional information about the methionine status of the system to relate them uniquely to intracellular glutathione concentration. However, when both biomarkers are measured simultaneously a direct inference of the glutathione concentration can be made, irrespective of the methionine concentration in the system.
Keywords: Acetaminophen/metabolism/toxicity; Animals; Biomarkers/metabolism; *Computer Simulation; Glutathione/*metabolism; Humans; Inactivation, Metabolic; Liver/drug effects/*metabolism; Methionine/metabolism; *Models, Biological; Oligopeptides/metabolism; Pyrrolidonecarboxylic Acid/metabolism; Reproducibility of Results; *Systems Biology

Emergence of the silicon human and network targeting drugs. - Kolodkin, A.; Boogerd, F. C.; Plant, N.; Bruggeman, F. J.; Goncharuk, V.; Lunshof, J.; Moreno-Sanchez, R.; Yilmaz, N.; Bakker, B. M.; Snoep, J. L.; Balling, R.; Westerhoff, H. V. (Eur J Pharm Sci, 2012)
The development of disease may be characterized as a pathological shift of homeostasis; the main goal of contemporary drug treatment is, therefore, to return the pathological homeostasis back to the normal physiological range. From the view point of systems biology, homeostasis emerges from the interactions within the network of biomolecules (e.g. DNA, mRNA, proteins), and, hence, understanding how drugs impact upon the entire network should improve their efficacy at returning the network (body) to physiological homeostasis. Large, mechanism-based computer models, such as the anticipated human whole body models (silicon or virtual human), may help in the development of such network-targeting drugs. Using the philosophical concept of weak and strong emergence, we shall here take a more general look at the paradigm of network-targeting drugs, and propose our approaches to scale the strength of strong emergence. We apply these approaches to several biological examples and demonstrate their utility to reveal principles of bio-modeling. We discuss this in the perspective of building the silicon human.
Keywords: *Computer Simulation; *Drug Design; Gene Expression Regulation/drug effects; Homeostasis; Humans; *Models, Biological; *Molecular Targeted Therapy; Signal Transduction/*drug effects; *Systems Biology; Systems Integration; User-Computer Interface

Reproducible computational biology experiments with SED-ML--the Simulation Experiment Description Markup Language. - Waltemath, D.; Adams, R.; Bergmann, F. T.; Hucka, M.; Kolpakov, F.; Miller, A. K.; Moraru, I. I.; Nickerson, D.; Sahle, S.; Snoep, J. L.; Le Novere, N. (BMC Syst Biol, 2011)
BACKGROUND: The increasing use of computational simulation experiments to inform modern biological research creates new challenges to annotate, archive, share and reproduce such experiments. The recently published Minimum Information About a Simulation Experiment (MIASE) proposes a minimal set of information that should be provided to allow the reproduction of simulation experiments among users and software tools. RESULTS: In this article, we present the Simulation Experiment Description Markup Language (SED-ML). SED-ML encodes in a computer-readable exchange format the information required by MIASE to enable reproduction of simulation experiments. It has been developed as a community project and it is defined in a detailed technical specification and additionally provides an XML schema. The version of SED-ML described in this publication is Level 1 Version 1. It covers the description of the most frequent type of simulation experiments in the area, namely time course simulations. SED-ML documents specify which models to use in an experiment, modifications to apply on the models before using them, which simulation procedures to run on each model, what analysis results to output, and how the results should be presented. These descriptions are independent of the underlying model implementation. SED-ML is a software-independent format for encoding the description of simulation experiments; it is not specific to particular simulation tools. Here, we demonstrate that with the growing software support for SED-ML we can effectively exchange executable simulation descriptions. CONCLUSIONS: With SED-ML, software can exchange simulation experiment descriptions, enabling the validation and reuse of simulation experiments in different tools. Authors of papers reporting simulation experiments can make their simulation protocols available for other scientists to reproduce the results. Because SED-ML is agnostic about exact modeling language(s) used, experiments covering models from different fields of research can be accurately described and combined.
Keywords: Computational Biology/*methods; *Computer Simulation; *Programming Languages; Reproducibility of Results; *Software

Osmotically controlled synthesis of the compatible solute proline is critical for cellular defense of Bacillus subtilis against high osmolarity. - Brill, J.; Hoffmann, T.; Bleisteiner, M.; Bremer, E. (J Bacteriol, 2011)
Bacillus subtilis is known to accumulate large amounts of the compatible solute proline via de novo synthesis as a stress protectant when it faces high-salinity environments. We elucidated the genetic determinants required for the osmoadaptive proline production from the precursor glutamate. This proline biosynthesis route relies on the proJ-encoded gamma-glutamyl kinase, the proA-encoded gamma-glutamyl phosphate reductase, and the proH-encoded Delta1-pyrroline-5-caboxylate reductase. Disruption of the proHJ operon abolished osmoadaptive proline production and strongly impaired the ability of B. subtilis to cope with high-osmolarity growth conditions. Disruption of the proA gene also abolished osmoadaptive proline biosynthesis but caused, in contrast to the disruption of proHJ, proline auxotrophy. Northern blot analysis demonstrated that the transcription of the proHJ operon is osmotically inducible, whereas that of the proBA operon is not. Reporter gene fusion studies showed that proHJ expression is rapidly induced upon an osmotic upshift. Increased expression is maintained as long as the osmotic stimulus persists and is sensitively linked to the prevalent osmolarity of the growth medium. Primer extension analysis revealed the osmotically controlled proHJ promoter, a promoter that resembles typical SigA-type promoters of B. subtilis. Deletion analysis of the proHJ promoter region identified a 126-bp DNA segment carrying all sequences required in cis for osmoregulated transcription. Our data disclose the presence of ProA-interlinked anabolic and osmoadaptive proline biosynthetic routes in B. subtilis and demonstrate that the synthesis of the compatible solute proline is a central facet of the cellular defense to high-osmolarity surroundings for this soil bacterium.
Keywords: Bacillus subtilis/genetics/*metabolism; Bacterial Proteins/genetics/metabolism; Blotting, Northern; Chromatography, High Pressure Liquid; Gene Expression Regulation, Bacterial/genetics/physiology; Magnetic Resonance Spectroscopy; *Osmolar Concentration; Proline/*biosynthesis; Promoter Regions, Genetic/genetics

Synthesis, release, and recapture of compatible solute proline by osmotically stressed Bacillus subtilis cells. - Hoffmann, T.; von Blohn, C.; Stanek, A.; Moses, S.; Barzantny, H.; Bremer, E. (Appl Environ Microbiol, 2012)
Bacillus subtilis synthesizes large amounts of the compatible solute proline as a cellular defense against high osmolarity to ensure a physiologically appropriate level of hydration of the cytoplasm and turgor. It also imports proline for this purpose via the osmotically inducible OpuE transport system. Unexpectedly, an opuE mutant was at a strong growth disadvantage in high-salinity minimal media lacking proline. Appreciable amounts of proline were detected in the culture supernatant of the opuE mutant strain, and they rose concomitantly with increases in the external salinity. We found that the intracellular proline pool of severely salinity-stressed cells of the opuE mutant was considerably lower than that of its opuE(+) parent strain. This loss of proline into the medium and the resulting decrease in the intracellular proline content provide a rational explanation for the observed salt-sensitive growth phenotype of cells lacking OpuE. None of the known MscL- and MscS-type mechanosensitive channels of B. subtilis participated in the release of proline under permanently imposed high-salinity growth conditions. The data reported here show that the OpuE transporter not only possesses the previously reported role for the scavenging of exogenously provided proline as an osmoprotectant but also functions as a physiologically highly important recapturing device for proline that is synthesized de novo and subsequently released by salt-stressed B. subtilis cells. The wider implications of our findings for the retention of compatible solutes by osmotically challenged microorganisms and the roles of uptake systems for compatible solutes are considered.
Keywords: Bacillus subtilis/genetics/growth & development/*metabolism/*physiology; Bacterial Proteins/genetics; Biological Transport; Culture Media/chemistry; Gene Deletion; Models, Biological; *Osmotic Pressure; Proline/*metabolism; Salinity

Osmoprotection of Bacillus subtilis through Import and Proteolysis of Proline-Containing Peptides - Zaprasis, Adrienne; Brill, J.; Thuring, M.; Wunsche, G.; Heun, M.; Barzantny, H.; Hoffmann, Tamara; Bremer, Erhard (Applied and Environmental Microbiology, 2012)

Modelling complex biological systems using an agent-based approach. - Holcombe, M.; Adra, S.; Bicak, M.; Chin, S.; Coakley, S.; Graham, A. I.; Green, J.; Greenough, C.; Jackson, D.; Kiran, M.; MacNeil, S.; Maleki-Dizaji, A.; et al. (Integr Biol (Camb), 2012)
Many of the complex systems found in biology are comprised of numerous components, where interactions between individual agents result in the emergence of structures and function, typically in a highly dynamic manner. Often these entities have limited lifetimes but their interactions both with each other and their environment can have profound biological consequences. We will demonstrate how modelling these entities, and their interactions, can lead to a new approach to experimental biology bringing new insights and a deeper understanding of biological systems.
Keywords: Animals; *Models, Biological; Software; Systems Biology/*methods

The O2 sensitivity of the transcription factor FNR is controlled by Ser24 modulating the kinetics of [4Fe-4S] to [2Fe-2S] conversion. - Jervis, A. J.; Crack, J. C.; White, G.; Artymiuk, P. J.; Cheesman, M. R.; Thomson, A. J.; Le Brun, N. E.; Green, J. (Proc Natl Acad Sci U S A, 2009)
Fumarate and nitrate reduction regulatory (FNR) proteins are bacterial transcription factors that coordinate the switch between aerobic and anaerobic metabolism. In the absence of O(2), FNR binds a [4Fe-4S](2+) cluster (ligated by Cys-20, 23, 29, 122) promoting the formation of a transcriptionally active dimer. In the presence of O(2), FNR is converted into a monomeric, non-DNA-binding form containing a [2Fe-2S](2+) cluster. The reaction of the [4Fe-4S](2+) cluster with O(2) has been shown to proceed via a 2-step process, an O(2)-dependent 1-electron oxidation to yield a [3Fe-4S](+) intermediate with release of 1 Fe(2+) ion, followed by spontaneous rearrangement to the [2Fe-2S](2+) form with release of 1 Fe(3+) and 2 S(2-) ions. Here, we show that replacement of Ser-24 by Arg, His, Phe, Trp, or Tyr enhances aerobic activity of FNR in vivo. The FNR-S24F protein incorporates a [4Fe-4S](2+) cluster with spectroscopic properties similar to those of FNR. However, the substitution enhances the stability of the [4Fe-4S](2+) cluster in the presence of O(2). Kinetic analysis shows that both steps 1 and 2 are slower for FNR-S24F than for FNR. A molecular model suggests that step 1 of the FNR-S24F iron-sulfur cluster reaction with O(2) is inhibited by shielding of the iron ligand Cys-23, suggesting that Cys-23 or the cluster iron bound to it is a primary site of O(2) interaction. These data lead to a simple model of the FNR switch with physiological implications for the ability of FNR proteins to operate over different ranges of in vivo O(2) concentrations.
Keywords: Aerobiosis; Amino Acid Sequence; Amino Acid Substitution; Escherichia coli/*metabolism; Escherichia coli Proteins/chemistry/*metabolism; Iron-Sulfur Proteins/chemistry/*metabolism; Kinetics; Ligands; Models, Molecular; Molecular Sequence Data; Oxygen/*metabolism; Phenylalanine/genetics; Protein Stability; Serine/*metabolism; Spectrophotometry, Ultraviolet; Structure-Activity Relationship; Transcription Factors/chemistry/*metabolism

Bacterial sensors of oxygen. - Green, J.; Crack, J. C.; Thomson, A. J.; LeBrun, N. E. (Curr Opin Microbiol, 2009)
The concentration of molecular oxygen (O(2)) began to increase in the Earth's atmosphere approximately two billion years ago. Its presence posed a threat to anaerobes but also offered opportunities for improved energy conservation via aerobic respiration. The ability to sense environmental O(2) thus became, and remains, important for many bacteria, both for protection and switching between anaerobic and aerobic respiration. Utilizing an iron-sulfur cluster as the sensor of O(2) exploits the ability of O(2) to oxidize the iron-sulfur cluster, ultimately resulting in cluster disassembly. When utilizing heme as the sensor, the capacity of O(2) to form a reversible Fe-O(2) bond or alternatively the oxidation of the heme iron atom itself is used to detect O(2) and switch regulators between active and inactive forms.
Keywords: *Bacterial Physiological Phenomena; Bacterial Proteins/*physiology; Escherichia coli Proteins/physiology; Hemeproteins/*physiology; Histidine Kinase; Iron-Sulfur Proteins/*physiology; Oxygen/*metabolism

Uncoupling of substrate-level phosphorylation in Escherichia coli during glucose-limited growth. - Sharma, P.; Hellingwerf, K. J.; de Mattos, M. J.; Bekker, M. (Appl Environ Microbiol, 2012)
The respiratory chain of Escherichia coli contains three different cytochrome oxidases. Whereas the cytochrome bo oxidase and the cytochrome bd-I oxidase are well characterized and have been shown to contribute to proton translocation, physiological data suggested a nonelectrogenic functioning of the cytochrome bd-II oxidase. Recently, however, this view was challenged by an in vitro biochemical analysis that showed that the activity of cytochrome bd-II oxidase does contribute to proton translocation with an H(+)/e(-) stoichiometry of 1. Here, we propose that this apparent discrepancy is due to the activities of two alternative catabolic pathways: the pyruvate oxidase pathway for acetate production and a pathway with methylglyoxal as an intermediate for the production of lactate. The ATP yields of these pathways are lower than those of the pathways that have so far always been assumed to catalyze the main catabolic flux under energy-limited growth conditions (i.e., pyruvate dehydrogenase and lactate dehydrogenase). Inclusion of these alternative pathways in the flux analysis of growing E. coli strains for the calculation of the catabolic ATP synthesis rate indicates an electrogenic function of the cytochrome bd-II oxidase, compatible with an H(+)/e(-) ratio of 1. This analysis shows for the first time the extent of bypassing of substrate-level phosphorylation in E. coli under energy-limited growth conditions.
Keywords: Adenosine Triphosphate/metabolism; *Energy Metabolism; Escherichia coli/growth & development/*metabolism; Glucose/*metabolism; Metabolic Networks and Pathways; Phosphorylation

On the function of the various quinone species in Escherichia coli - Sharma, Poonam; Teixeira de Mattos, Joost; Hellingwerf, Klaas J.; Bekker, Martijn (2012)
The respiratory chain of Escherichia coli contains three quinones. Menaquinone and demethylmenaquinone have low midpoint potentials and are involved in anaerobic respiration, while ubiquinone, which has a high midpoint potential, is involved in aerobic and nitrate respiration. Here, we report that demethylmenaquinone plays a role not only in trimethylaminooxide-, dimethylsulfoxide- and fumarate-dependent respiration, but also in aerobic respiration. Furthermore, we demonstrate that demethylmenaquinone serves as an electron acceptor for oxidation of succinate to fumarate, and that all three quinol oxidases of E. coli accept electrons from this naphtoquinone derivative.

Simulations of stressosome activation emphasize allosteric interactions between RsbR and RsbT - Liebal, Ulf; Millat, Thomas; Marles-Wright, Jon; Lewis, Rick; Wolkenhauer, Olaf (BMC Syst Biol, 2013)
Background The stressosome is a bacterial signalling complex that responds to environmental changes by initiating a protein partner switching cascade, which leads to the release of the alternative sigma factor, sigmaB. Stress perception increases the phosphorylation of the stressosome sensor protein, RsbR, and the scaffold protein, RsbS, by the protein kinase RsbT. Subsequent dissociation of RsbT from the stressosome activates the sigmaB cascade. However, the sequence of physical events that occur in the stressosome during signal transduction is insufficiently understood.

Integrative modelling of pH-dependent enzyme activity and transcriptomic regulation of the acetone-butanol-ethanol fermentation of Clostridium acetobutylicum in continuous culture (Microbial Biotechnology, 2013)
In a continuous culture under phosphate limitation the metabolism of Clostridium acetobutylicum depends on the external pH level. By comparing seven steady-state conditions between pH 5.7 and pH 4.5 we show that the switch from acidogenesis to solventogenesis occurs between pH 5.3 and pH 5.0 with an intermediate state at pH 5.1. Here, an integrative study is presented investigating how a changing external pH level affects the clostridial acetone–butanol–ethanol (ABE) fermentation pathway. This is of particular interest as the biotechnological production of n-butanol as biofuel has recently returned into the focus of industrial applications. One prerequisite is the furthering of the knowledge of the factors determining the solvent production and their integrative regulations. We have mathematically analysed the influence of pH-dependent specific enzyme activities of branch points of the metabolism on the product formation. This kinetic regulation was compared with transcriptomic regulation regarding gene transcription and the proteomic profile. Furthermore, both regulatory mechanisms were combined yielding a detailed projection of their individual and joint effects on the product formation. The resulting model represents an important platform for future developments of industrial butanol production based on C. acetobutylicum.

A shift in the dominant phenotype governs the pH-induced metabolic switch of Clostridium acetobutylicumin phosphate-limited continuous cultures. - Millat, T.; Janssen, H.; Thorn, G. J.; King, J. R.; Bahl, H.; Fischer, R. J.; Wolkenhauer, O. (Appl Microbiol Biotechnol, 2013)
In response to changing extracellular pH levels, phosphate-limited continuous cultures of Clostridium acetobutylicum reversibly switches its metabolism from the dominant formation of acids to the prevalent production of solvents. Previous experimental and theoretical studies have revealed that this pH-induced metabolic switch involves a rearrangement of the intracellular transcriptomic, proteomic and metabolomic composition of the clostridial cells. However, the influence of the population dynamics on the observations reported has so far been neglected. Here, we present a method for linking the pH shift, clostridial growth and the acetone-butanol-ethanol fermentation metabolic network systematically into a model which combines the dynamics of the external pH and optical density with a metabolic model. Furthermore, the recently found antagonistic expression pattern of the aldehyde/alcohol dehydrogenases AdhE1/2 and pH-dependent enzyme activities have been included into this combined model. Our model predictions reveal that the pH-induced metabolic shift under these experimental conditions is governed by a phenotypic switch of predominantly acidogenic subpopulation towards a predominantly solventogenic subpopulation. This model-driven explanation of the pH-induced shift from acidogenesis to solventogenesis by population dynamics casts an entirely new light on the clostridial response to changing pH levels. Moreover, the results presented here underline that pH-dependent growth and pH-dependent specific enzymatic activity play a crucial role in this adaptation. In particular, the behaviour of AdhE1 and AdhE2 seems to be the key factor for the product formation of the two phenotypes, their pH-dependent growth, and thus, the pH-induced metabolic switch in C. acetobutylicum.
Keywords: Acetone/metabolism; Acids/metabolism; Butanols/metabolism; Clostridium acetobutylicum/chemistry/growth & development/*metabolism; Culture Media/*chemistry/metabolism; Ethanol/metabolism; Gene Expression Regulation, Bacterial; Hydrogen-Ion Concentration; Phenotype; Phosphates/*metabolism

Regulation of the Activity of Lactate Dehydrogenases from Four Lactic Acid Bacteria - Feldman-Salit, Anna; Hering, Silvio; Messiha, H.; Veith, Nadine; Cojocaru, Vlad; Sieg, Antje; Westerhoff, Hans V.; Kreikemeyer, Bernd; Wade, Rebecca; Fiedler, Tomas (Journal of Biological Chemistry, 2013)

Dissecting the catalytic mechanism of Trypanosoma brucei trypanothione synthetase by kinetic analysis and computational modeling. - Leroux, A. E.; Haanstra, J. R.; Bakker, B. M.; Krauth-Siegel, R. L. (J Biol Chem, 2013)
In pathogenic trypanosomes, trypanothione synthetase (TryS) catalyzes the synthesis of both glutathionylspermidine (Gsp) and trypanothione (bis(glutathionyl)spermidine (T(SH)2)). Here we present a thorough kinetic analysis of Trypanosoma brucei TryS in a newly developed phosphate buffer system at pH 7.0 and 37 degrees C, mimicking the physiological environment of the enzyme in the cytosol of bloodstream parasites. Under these conditions, TryS displays Km values for GSH, ATP, spermidine, and Gsp of 34, 18, 687, and 32 mum, respectively, as well as Ki values for GSH and T(SH)2 of 1 mm and 360 mum, respectively. As Gsp hydrolysis has a Km value of 5.6 mm, the in vivo amidase activity is probably negligible. To obtain deeper insight in the molecular mechanism of TryS, we have formulated alternative kinetic models, with elementary reaction steps represented by linear kinetic equations. The model parameters were fitted to the extensive matrix of steady-state data obtained for different substrate/product combinations under the in vivo-like conditions. The best model describes the full kinetic profile and is able to predict time course data that were not used for fitting. This system's biology approach to enzyme kinetics led us to conclude that (i) TryS follows a ter-reactant mechanism, (ii) the intermediate Gsp dissociates from the enzyme between the two catalytic steps, and (iii) T(SH)2 inhibits the enzyme by remaining bound at its product site and, as does the inhibitory GSH, by binding to the activated enzyme complex. The newly detected concerted substrate and product inhibition suggests that TryS activity is tightly regulated.
Keywords: Adenosine Triphosphatases/metabolism; Amide Synthases/antagonists & inhibitors/*metabolism; Amidohydrolases/metabolism; *Biocatalysis; Buffers; *Computer Simulation; Cytosol/metabolism; Enzyme Assays; Glutathione/analogs & derivatives/chemistry/metabolism; Hydrogen-Ion Concentration; Hydrolysis; Kinetics; *Models, Molecular; Spermidine/analogs & derivatives/chemistry/metabolism; Substrate Specificity; Temperature; Time Factors; Trypanosoma brucei brucei/*enzymology

Kinetic characterization of arginine deiminase and carbamate kinase from Streptococcus pyogenes M49 (Protein Expression and Purification, 2013)
Streptococcus pyogenes (group A Streptococcus, GAS) is an important human pathogen causing mild superficial infections of skin and mucous membranes, but also life-threatening systemic diseases. S. pyogenes and other prokaryotic organisms use the arginine deiminase system (ADS) for survival in acidic environments. In this study, the arginine deiminase (AD), and carbamate kinase (CK) from S. pyogenes M49 strain 591 were heterologously expressed in E. coli DH5α, purified, and kinetically characterized. AD and CK from S. pyogenes M49 share high amino acid sequence similarity with the respective enzymes from Lactococcus lactis subsp. lactis IL1403 (45.6% and 53.5% identical amino acids) and Enterococcus faecalis V583 (66.8% and 66.8% identical amino acids). We found that the arginine deiminase of S. pyogenes is not allosterically regulated by the intermediates and products of the arginine degradation (E. g, ATP, citrulline, carbamoyl phosphate). The Km and Vmax values for arginine were 1.13±0.12 mM (mean ± SD) and 1.51±0.07 μmol/min/mg protein. The carbamate kinase is inhibited by ATP but unaffected by arginine and citrulline. The Km and Vmax values for ADP were 0.72±0.08 mM and 1.10±0.10 μmol/min/mg protein and the Km for carbamoyl phosphate was 0.65±0.07 mM. The optimum pH and temperature for both enzymes were 6.5 and 37°C, respectively.

Organism-Adapted Specificity of the Allosteric Regulation of Pyruvate Kinase in Lactic Acid Bacteria (PLoS Comput Biol, 2013)

Intermediate instability at high temperature leads to low pathway efficiency for an in vitro reconstituted system of gluconeogenesis in Sulfolobus solfataricus. - Kouril, T.; Esser, D.; Kort, J.; Westerhoff, H. V.; Siebers, B.; Snoep, J. L. (FEBS J, 2013)
Four enzymes of the gluconeogenic pathway in Sulfolobus solfataricus were purified and kinetically characterized. The enzymes were reconstituted in vitro to quantify the contribution of temperature instability of the pathway intermediates to carbon loss from the system. The reconstituted system, consisting of phosphoglycerate kinase, glyceraldehyde 3-phosphate dehydrogenase, triose phosphate isomerase and the fructose 1,6-bisphosphate aldolase/phosphatase, maintained a constant consumption rate of 3-phosphoglycerate and production of fructose 6-phosphate over a 1-h period. Cofactors ATP and NADPH were regenerated via pyruvate kinase and glucose dehydrogenase. A mathematical model was constructed on the basis of the kinetics of the purified enzymes and the measured half-life times of the pathway intermediates. The model quantitatively predicted the system fluxes and metabolite concentrations. Relative enzyme concentrations were chosen such that half the carbon in the system was lost due to degradation of the thermolabile intermediates dihydroxyacetone phosphate, glyceraldehyde 3-phosphate and 1,3-bisphosphoglycerate, indicating that intermediate instability at high temperature can significantly affect pathway efficiency.
Keywords: Archaeal Proteins/genetics/*metabolism; Dihydroxyacetone Phosphate/metabolism; Diphosphoglyceric Acids/metabolism; Enzyme Stability; Escherichia coli/genetics/metabolism; Fructose-Bisphosphate Aldolase/genetics/*metabolism; Fructosephosphates/biosynthesis; Gluconeogenesis/genetics; Glyceraldehyde 3-Phosphate/metabolism; Glyceraldehyde-3-Phosphate Dehydrogenases/genetics/*metabolism; Glyceric Acids/metabolism; Half-Life; Hot Temperature; Kinetics; *Models, Statistical; Phosphoglycerate Kinase/genetics/*metabolism; Recombinant Proteins/genetics/metabolism; Sulfolobus solfataricus/chemistry/*enzymology/genetics; Thermodynamics; Triose-Phosphate Isomerase/genetics/*metabolism

Semantic Data and Models Sharing in Systems Biology: The Just Enough Results Model and the SEEK Platform (Advanced Information Systems Engineering, 2013)
Research in Systems Biology involves integrating data and knowledge about the dynamic processes in biological systems in order to understand and model them. Semantic web technologies should be ideal for exploring the complex networks of genes, proteins and metabolites that interact, but much of this data is not natively available to the semantic web. Data is typically collected and stored with free-text annotations in spreadsheets, many of which do not conform to existing metadata standards and are often not publically released. Along with initiatives to promote more data sharing, one of the main challenges is therefore to semantically annotate and extract this data so that it is available to the research community. Data annotation and curation are expensive and undervalued tasks that have enormous benefits to the discipline as a whole, but fewer benefits to the individual data producers. By embedding semantic annotation into spreadsheets, however, and automatically extracting this data into RDF at the time of repository submission, the process of producing standards-compliant data, that is available for semantic web querying, can be achieved without adding additional overheads to laboratory data management. This paper describes these strategies in the context of semantic data management in the SEEK. The SEEK is a web-based resource for sharing and exchanging Systems Biology data and models that is underpinned by the JERM ontology (Just Enough Results Model), which describes the relationships between data, models, protocols and experiments. The SEEK was originally developed for SysMO, a large European Systems Biology consortium studying micro-organisms, but it has since had widespread adoption across European Systems Biology.

The silicon trypanosome: a test case of iterative model extension in systems biology. - Achcar, F.; Fadda, A.; Haanstra, J. R.; Kerkhoven, E. J.; Kim, D. H.; Leroux, A. E.; Papamarkou, T.; Rojas, F.; Bakker, B. M.; Barrett, M. P.; Clayton, C.; Girolami, M.; et al. (Adv Microb Physiol, 2014)
The African trypanosome, Trypanosoma brucei, is a unicellular parasite causing African Trypanosomiasis (sleeping sickness in humans and nagana in animals). Due to some of its unique properties, it has emerged as a popular model organism in systems biology. A predictive quantitative model of glycolysis in the bloodstream form of the parasite has been constructed and updated several times. The Silicon Trypanosome is a project that brings together modellers and experimentalists to improve and extend this core model with new pathways and additional levels of regulation. These new extensions and analyses use computational methods that explicitly take different levels of uncertainty into account. During this project, numerous tools and techniques have been developed for this purpose, which can now be used for a wide range of different studies in systems biology.
Keywords: Animals; Glycolysis; Humans; Protozoan Proteins/genetics/metabolism; *Systems Biology; Trypanosoma brucei brucei/genetics/*metabolism; Trypanosomiasis, African/*parasitology

Kinase activity of ArcB from Escherichia coli is subject to regulation by both ubiquinone and demethylmenaquinone. - Sharma, P.; Stagge, S.; Bekker, M.; Bettenbrock, K.; Hellingwerf, K. J. (PLoS One, 2013)
Expression of the catabolic network in Escherichia coli is predominantly regulated, via oxygen availability, by the two-component system ArcBA. It has been shown that the kinase activity of ArcB is controlled by the redox state of two critical pairs of cysteines in dimers of the ArcB sensory kinase. Among the cellular components that control the redox state of these cysteines of ArcB are the quinones from the cytoplasmic membrane of the cell, which function in 'respiratory' electron transfer. This study is an effort to understand how the redox state of the quinone pool(s) is sensed by the cell via the ArcB kinase. We report the relationship between growth, quinone content, ubiquinone redox state, the level of ArcA phosphorylation, and the level of ArcA-dependent gene expression, in a number of mutants of E. coli with specific alterations in their set of quinones, under a range of physiological conditions. Our results provide experimental evidence for a previously formulated hypothesis that not only ubiquinone, but also demethylmenaquinone, can inactivate kinase activity of ArcB. Also, in a mutant strain that only contains demethylmenaquinone, the extent of ArcA phosphorylation can be modulated by the oxygen supply rate, which shows that demethylmenaquinone can also inactivate ArcB in its oxidized form. Furthermore, in batch cultures of a strain that contains ubiquinone as its only quinone species, we observed that the ArcA phosphorylation level closely followed the redox state of the ubiquinone/ubiquinol pool, much more strictly than it does in the wild type strain. Therefore, at low rates of oxygen supply in the wild type strain, the activity of ArcB may be inhibited by demethylmenaquinone, in spite of the fact that the ubiquinones are present in the ubiquinol form.
Keywords: Escherichia coli; Escherichia coli Proteins/genetics/*metabolism; *Gene Expression Regulation, Bacterial; Membrane Proteins/genetics/*metabolism; Oxidation-Reduction; Phosphorylation; Protein Kinases/genetics/*metabolism; Signal Transduction/genetics; Ubiquinone/genetics/*metabolism; Vitamin K 2/*analogs & derivatives/metabolism

Towards a systems level understanding of the oxygen response of Escherichia coli. - Bettenbrock, K.; Bai, H.; Ederer, M.; Green, J.; Hellingwerf, K. J.; Holcombe, M.; Kunz, S.; Rolfe, M. D.; Sanguinetti, G.; Sawodny, O.; Sharma, P.; Steinsiek, S.; et al. (Adv Microb Physiol, 2014)
Escherichia coli is a facultatively anaerobic bacterium. With glucose if no external electron acceptors are available, ATP is produced by substrate level phosphorylation. The intracellular redox balance is maintained by mixed-acid fermentation, that is, the production and excretion of several organic acids. When oxygen is available, E. coli switches to aerobic respiration to achieve redox balance and optimal energy conservation by proton translocation linked to electron transfer. The switch between fermentative and aerobic respiratory growth is driven by extensive changes in gene expression and protein synthesis, resulting in global changes in metabolic fluxes and metabolite concentrations. This oxygen response is determined by the interaction of global and local genetic regulatory mechanisms, as well as by enzymatic regulation. The response is affected by basic physical constraints such as diffusion, thermodynamics and the requirement for a balance of carbon, electrons and energy (predominantly the proton motive force and the ATP pool). A comprehensive systems level understanding of the oxygen response of E. coli requires the integrated interpretation of experimental data that are pertinent to the multiple levels of organization that mediate the response. In the pan-European venture, Systems Biology of Microorganisms (SysMO) and specifically within the project Systems Understanding of Microbial Oxygen Metabolism (SUMO), regulator activities, gene expression, metabolite levels and metabolic flux datasets were obtained using a standardized and reproducible chemostat-based experimental system. These different types and qualities of data were integrated using mathematical models. The approach described here has revealed a much more detailed picture of the aerobic-anaerobic response, especially for the environmentally critical microaerobic range that is located between unlimited oxygen availability and anaerobiosis.
Keywords: Adenosine Triphosphate/metabolism; Aerobiosis; Escherichia coli/genetics/*metabolism; Escherichia coli Proteins/genetics/metabolism; Gene Expression Regulation, Bacterial; Oxygen/*metabolism; *Systems Biology

Benchmarking various green fluorescent protein variants in Bacillus subtilis, Streptococcus pneumoniae, and Lactococcus lactis for live cell imaging. - Overkamp, W.; Beilharz, K.; Detert Oude Weme, R.; Solopova, A.; Karsens, H.; Kovacs, A.; Kok, J.; Kuipers, O. P.; Veening, J. W. (Appl Environ Microbiol, 2013)
Green fluorescent protein (GFP) offers efficient ways of visualizing promoter activity and protein localization in vivo, and many different variants are currently available to study bacterial cell biology. Which of these variants is best suited for a certain bacterial strain, goal, or experimental condition is not clear. Here, we have designed and constructed two "superfolder" GFPs with codon adaptation specifically for Bacillus subtilis and Streptococcus pneumoniae and have benchmarked them against five other previously available variants of GFP in B. subtilis, S. pneumoniae, and Lactococcus lactis, using promoter-gfp fusions. Surprisingly, the best-performing GFP under our experimental conditions in B. subtilis was the one codon optimized for S. pneumoniae and vice versa. The data and tools described in this study will be useful for cell biology studies in low-GC-rich Gram-positive bacteria.
Keywords: Bacillus subtilis/*chemistry/genetics/metabolism; *Benchmarking; DNA, Bacterial/chemistry/genetics; Green Fluorescent Proteins/*analysis/genetics; Lactococcus lactis/*chemistry/genetics/metabolism; Microscopy, Fluorescence/*methods; Molecular Sequence Data; Sequence Analysis, DNA; Staining and Labeling/*methods; Streptococcus pneumoniae/*chemistry/genetics/metabolism

The metabolic response of P. putida KT2442 producing high levels of polyhydroxyalkanoate under single- and multiple-nutrient-limited growth: highlights from a multi-level omics approach. - Poblete-Castro, I.; Escapa, I. F.; Jager, C.; Puchalka, J.; Lam, C. M.; Schomburg, D.; Prieto, M. A.; Martins dos Santos, V. A. (Microb Cell Fact, 2012)
BACKGROUND: Pseudomonas putida KT2442 is a natural producer of polyhydroxyalkanoates (PHAs), which can substitute petroleum-based non-renewable plastics and form the basis for the production of tailor-made biopolymers. However, despite the substantial body of work on PHA production by P. putida strains, it is not yet clear how the bacterium re-arranges its whole metabolism when it senses the limitation of nitrogen and the excess of fatty acids as carbon source, to result in a large accumulation of PHAs within the cell. In the present study we investigated the metabolic response of KT2442 using a systems biology approach to highlight the differences between single- and multiple-nutrient-limited growth in chemostat cultures. RESULTS: We found that 26, 62, and 81% of the cell dry weight consist of PHA under conditions of carbon, dual, and nitrogen limitation, respectively. Under nitrogen limitation a specific PHA production rate of 0.43 (g.(g.h)-1) was obtained. The residual biomass was not constant for dual- and strict nitrogen-limiting growth, showing a different feature in comparison to other P. putida strains. Dual limitation resulted in patterns of gene expression, protein level, and metabolite concentrations that substantially differ from those observed under exclusive carbon or nitrogen limitation. The most pronounced differences were found in the energy metabolism, fatty acid metabolism, as well as stress proteins and enzymes belonging to the transport system. CONCLUSION: This is the first study where the interrelationship between nutrient limitations and PHA synthesis has been investigated under well-controlled conditions using a system level approach. The knowledge generated will be of great assistance for the development of bioprocesses and further metabolic engineering work in this versatile organism to both enhance and diversify the industrial production of PHAs.
Keywords: Biomass; Carbon/metabolism; Energy Metabolism; Fatty Acids/metabolism; *Gene Expression Regulation, Bacterial; Metabolomics; Nitrogen/metabolism; Polyhydroxyalkanoates/*biosynthesis; Proteomics; Pseudomonas putida/growth & development/*metabolism; Transcriptome

Pseudomonas putida KT2440 genome update by cDNA sequencing and microarray transcriptomics. - Frank, S.; Klockgether, J.; Hagendorf, P.; Geffers, R.; Schock, U.; Pohl, T.; Davenport, C. F.; Tummler, B. (Environ Microbiol, 2011)
Pseudomonas putida KT2440 is a completely sequenced biosafety strain that has retained its capability to survive and function in the environment. The global mRNA expression profiles of the KT2440 strain grown at 10 degrees C and 30 degrees C were determined by deep cDNA sequencing to refine the genome annotation. Transcriptome sequencing identified 36 yet unknown small non-coding RNAs, 143 novel ORFs in 106 intergenic regions, 42 unclassified genes and eight highly expressed leaderless mRNA transcripts. The genome coordinates of eight genes and the organization of 57 operons were corrected. No overrepresented sequence motifs were detected in the 5'-untranslated regions. The 50 most highly expressed genes made up 60% of the total mRNA pool. Comparison of cDNA sequencing, Affymetrix and Progenika microarray data from the same mRNA preparation revealed a higher sensitivity and specificity of cDNA sequencing, a relatively poor correlation between the normalized cDNA reads and microarray signal intensities, and a systematic signal-dependent bias of microarrays in the detection of differentially regulated genes. The study demonstrates the power of next-generation cDNA sequencing for the quantitation of mRNA transcripts and the refinement of bacterial genome annotation.
Keywords: DNA, Bacterial/genetics; DNA, Complementary/genetics; *Gene Expression Profiling; *Genome, Bacterial; Molecular Sequence Annotation; Oligonucleotide Array Sequence Analysis; Open Reading Frames; Pseudomonas putida/*genetics; RNA, Small Untranslated/genetics; Sensitivity and Specificity; Sequence Analysis, DNA/methods; Untranslated Regions

Systems Biology of Monovalent Cation Homeostasis in Yeast - Ariño, Joaquin; Aydar, Ebru; Drulhe, Samuel; Ganser, Daniel; Jorrin, Jesus; Kahm, Matthias; Krause, Falko; Petrezselyova, Silvia; Yenush, Lynne; Zimmermannová, Olga; van Heusden, G. Paul H.; Kschischo, Maik; et al. (Advances in Microbial Systems Biology, 2014)
Maintenance of monovalent cation homeostasis (mainly K(+) and Na(+)) is vital for cell survival, and cation toxicity is at the basis of a myriad of relevant phenomena, such as salt stress in crops and diverse human diseases. Full understanding of the importance of monovalent cations in the biology of the cell can only be achieved from a systemic perspective. Translucent is a multinational project developed within the context of the SysMO (System Biology of Microorganisms) initiative and focussed in the study of cation homeostasis using the well-known yeast Saccharomyces cerevisiae as a model. The present review summarize how the combination of biochemical, genetic, genomic and computational approaches has boosted our knowledge in this field, providing the basis for a more comprehensive and coherent vision of the role of monovalent cations in the biology of the cell.

Handling uncertainty in dynamic models: the pentose phosphate pathway in Trypanosoma brucei. - Kerkhoven, E. J.; Achcar, F.; Alibu, V. P.; Burchmore, R. J.; Gilbert, I. H.; Trybilo, M.; Driessen, N. N.; Gilbert, D.; Breitling, R.; Bakker, B. M.; Barrett, M. P. (PLoS Comput Biol, 2013)
Dynamic models of metabolism can be useful in identifying potential drug targets, especially in unicellular organisms. A model of glycolysis in the causative agent of human African trypanosomiasis, Trypanosoma brucei, has already shown the utility of this approach. Here we add the pentose phosphate pathway (PPP) of T. brucei to the glycolytic model. The PPP is localized to both the cytosol and the glycosome and adding it to the glycolytic model without further adjustments leads to a draining of the essential bound-phosphate moiety within the glycosome. This phosphate "leak" must be resolved for the model to be a reasonable representation of parasite physiology. Two main types of theoretical solution to the problem could be identified: (i) including additional enzymatic reactions in the glycosome, or (ii) adding a mechanism to transfer bound phosphates between cytosol and glycosome. One example of the first type of solution would be the presence of a glycosomal ribokinase to regenerate ATP from ribose 5-phosphate and ADP. Experimental characterization of ribokinase in T. brucei showed that very low enzyme levels are sufficient for parasite survival, indicating that other mechanisms are required in controlling the phosphate leak. Examples of the second type would involve the presence of an ATP:ADP exchanger or recently described permeability pores in the glycosomal membrane, although the current absence of identified genes encoding such molecules impedes experimental testing by genetic manipulation. Confronted with this uncertainty, we present a modeling strategy that identifies robust predictions in the context of incomplete system characterization. We illustrate this strategy by exploring the mechanism underlying the essential function of one of the PPP enzymes, and validate it by confirming the model predictions experimentally.
Keywords: Animals; Glucose/metabolism; Glycolysis; *Models, Biological; *Pentose Phosphate Pathway; RNA Interference; Trypanosoma brucei brucei/*metabolism; *Uncertainty

Naphthoquinone derivatives exert their antitrypanosomal activity via a multi-target mechanism. - Pieretti, S.; Haanstra, J. R.; Mazet, M.; Perozzo, R.; Bergamini, C.; Prati, F.; Fato, R.; Lenaz, G.; Capranico, G.; Brun, R.; Bakker, B. M.; Michels, P. A.; et al. (PLoS Negl Trop Dis, 2013)
BACKGROUND AND METHODOLOGY: Recently, we reported on a new class of naphthoquinone derivatives showing a promising anti-trypanosomatid profile in cell-based experiments. The lead of this series (B6, 2-phenoxy-1,4-naphthoquinone) showed an ED(50) of 80 nM against Trypanosoma brucei rhodesiense, and a selectivity index of 74 with respect to mammalian cells. A multitarget profile for this compound is easily conceivable, because quinones, as natural products, serve plants as potent defense chemicals with an intrinsic multifunctional mechanism of action. To disclose such a multitarget profile of B6, we exploited a chemical proteomics approach. PRINCIPAL FINDINGS: A functionalized congener of B6 was immobilized on a solid matrix and used to isolate target proteins from Trypanosoma brucei lysates. Mass analysis delivered two enzymes, i.e. glycosomal glycerol kinase and glycosomal glyceraldehyde-3-phosphate dehydrogenase, as potential molecular targets for B6. Both enzymes were recombinantly expressed and purified, and used for chemical validation. Indeed, B6 was able to inhibit both enzymes with IC(50) values in the micromolar range. The multifunctional profile was further characterized in experiments using permeabilized Trypanosoma brucei cells and mitochondrial cell fractions. It turned out that B6 was also able to generate oxygen radicals, a mechanism that may additionally contribute to its observed potent trypanocidal activity. CONCLUSIONS AND SIGNIFICANCE: Overall, B6 showed a multitarget mechanism of action, which provides a molecular explanation of its promising anti-trypanosomatid activity. Furthermore, the forward chemical genetics approach here applied may be viable in the molecular characterization of novel multitarget ligands.
Keywords: Antiprotozoal Agents/*pharmacology; Enzyme Inhibitors/pharmacology; Glyceraldehyde-3-Phosphate Dehydrogenases/antagonists & inhibitors/isolation & purification; Glycerol Kinase/antagonists & inhibitors/isolation & purification; Inhibitory Concentration 50; Mass Spectrometry; Naphthoquinones/*pharmacology; Proteome/analysis; Protozoan Proteins/analysis; Reactive Oxygen Species/metabolism/toxicity; Trypanosoma brucei rhodesiense/chemistry/*drug effects

Proliferating bloodstream-form Trypanosoma brucei use a negligible part of consumed glucose for anabolic processes. - Haanstra, J. R.; van Tuijl, A.; van Dam, J.; van Winden, W.; Tielens, A. G.; van Hellemond, J. J.; Bakker, B. M. (Int J Parasitol, 2012)
Our quantitative knowledge of carbon fluxes in the long slender bloodstream form (BSF) Trypanosoma brucei is mainly based on non-proliferating parasites, isolated from laboratory animals and kept in buffers. In this paper we present a carbon balance for exponentially growing bloodstream form trypanosomes. The cells grew with a doubling time of 5.3h, contained 46 mu mol of carbon (10(8) cells)(-1) and had a glucose consumption flux of 160 nmol min(-1) (10(8) cells)(-1). The molar ratio of pyruvate excreted versus glucose consumed was 2.1. Furthermore, analysis of the (13)C label distribution in pyruvate in (13)C-glucose incubations of exponentially growing trypanosomes showed that glucose was the sole substrate for pyruvate production. We conclude that the glucose metabolised in glycolysis was hardly, if at all, used for biosynthetic processes. Carbon flux through glycolysis in exponentially growing trypanosomes was 10 times higher than the incorporation of carbon into biomass. This biosynthetic carbon is derived from other precursors present in the nutrient rich growth medium. Furthermore, we found that the glycolytic flux was unaltered when the culture went into stationary phase, suggesting that most of the ATP produced in glycolysis is used for processes other than growth.
Keywords: Adenosine Triphosphate/metabolism; Biomass; Blood/*parasitology; Carbon Isotopes/metabolism; Culture Media/chemistry; *Energy Metabolism; Glucose/*metabolism; Glycolysis; Isotope Labeling/methods; Pyruvic Acid/metabolism; Time Factors; Trypanosoma brucei brucei/chemistry/*growth & development/*metabolism

Control of transcription elongation by GreA determines rate of gene expression in Streptococcus pneumoniae. - Yuzenkova, Y.; Gamba, P.; Herber, M.; Attaiech, L.; Shafeeq, S.; Kuipers, O. P.; Klumpp, S.; Zenkin, N.; Veening, J. W. (Nucleic Acids Res, 2014)
Transcription by RNA polymerase may be interrupted by pauses caused by backtracking or misincorporation that can be resolved by the conserved bacterial Gre-factors. However, the consequences of such pausing in the living cell remain obscure. Here, we developed molecular biology and transcriptome sequencing tools in the human pathogen Streptococcus pneumoniae and provide evidence that transcription elongation is rate-limiting on highly expressed genes. Our results suggest that transcription elongation may be a highly regulated step of gene expression in S. pneumoniae. Regulation is accomplished via long-living elongation pauses and their resolution by elongation factor GreA. Interestingly, mathematical modeling indicates that long-living pauses cause queuing of RNA polymerases, which results in 'transcription traffic jams' on the gene and thus blocks its expression. Together, our results suggest that long-living pauses and RNA polymerase queues caused by them are a major problem on highly expressed genes and are detrimental for cell viability. The major and possibly sole function of GreA in S. pneumoniae is to prevent formation of backtracked elongation complexes.
Keywords: Bacterial Proteins/*physiology; *Gene Expression Regulation, Bacterial; Models, Genetic; Promoter Regions, Genetic; Streptococcus pneumoniae/cytology/*genetics/growth & development/metabolism; *Transcription Elongation, Genetic; Transcription Initiation, Genetic; Transcriptional Elongation Factors/*physiology

Transcriptome-wide analysis of trypanosome mRNA decay reveals complex degradation kinetics and suggests a role for co-transcriptional degradation in determining mRNA levels. - Fadda, A.; Ryten, M.; Droll, D.; Rojas, F.; Farber, V.; Haanstra, J. R.; Merce, C.; Bakker, B. M.; Matthews, K.; Clayton, C. (Mol Microbiol, 2014)
African trypanosomes are an excellent system for quantitative modelling of post-transcriptional mRNA control. Transcription is constitutive and polycistronic; individual mRNAs are excised by trans splicing and polyadenylation. We here measure mRNA decay kinetics in two life cycle stages, bloodstream and procyclic forms, by transcription inhibition and RNASeq. Messenger RNAs with short half-lives tend to show initial fast degradation, followed by a slower phase; they are often stabilized by depletion of the 5'-3' exoribonuclease XRNA. Many longer-lived mRNAs show initial slow degradation followed by rapid destruction: we suggest that the slow phase reflects gradual deadenylation. Developmentally regulated mRNAs often show regulated decay, and switch their decay pattern. Rates of mRNA decay are good predictors of steady state levels for short mRNAs, but mRNAs longer than 3 kb show unexpectedly low abundances. Modelling shows that variations in splicing and polyadenylation rates can contribute to steady-state mRNA levels, but this is completely dependent on competition between processing and co-transcriptional mRNA precursor destruction.
Keywords: *Gene Expression Profiling; *Gene Expression Regulation; High-Throughput Nucleotide Sequencing; *RNA Stability; Trypanosoma/*genetics

What makes the lac-pathway switch: identifying the fluctuations that trigger phenotype switching in gene regulatory systems. - Bhogale, P. M.; Sorg, R. A.; Veening, J. W.; Berg, J. (Nucleic Acids Res, 2014)
Multistable gene regulatory systems sustain different levels of gene expression under identical external conditions. Such multistability is used to encode phenotypic states in processes including nutrient uptake and persistence in bacteria, fate selection in viral infection, cell-cycle control and development. Stochastic switching between different phenotypes can occur as the result of random fluctuations in molecular copy numbers of mRNA and proteins arising in transcription, translation, transport and binding. However, which component of a pathway triggers such a transition is generally not known. By linking single-cell experiments on the lactose-uptake pathway in E. coli to molecular simulations, we devise a general method to pinpoint the particular fluctuation driving phenotype switching and apply this method to the transition between the uninduced and induced states of the lac-genes. We find that the transition to the induced state is not caused only by the single event of lac-repressor unbinding, but depends crucially on the time period over which the repressor remains unbound from the lac-operon. We confirm this notion in strains with a high expression level of the lac-repressor (leading to shorter periods over which the lac-operon remains unbound), which show a reduced switching rate. Our techniques apply to multistable gene regulatory systems in general and allow to identify the molecular mechanisms behind stochastic transitions in gene regulatory circuits.
Keywords: Escherichia coli/genetics/metabolism; Escherichia coli Proteins/*metabolism; *Gene Expression Regulation, Bacterial; Gene Regulatory Networks; *Lac Operon; Lac Repressors/*metabolism; Lactose/metabolism; Phenotype

A mathematical model of metabolism and regulation provides a systems-level view of how Escherichia coli responds to oxygen. - Ederer, M.; Steinsiek, S.; Stagge, S.; Rolfe, M. D.; Ter Beek, A.; Knies, D.; Teixeira de Mattos, M. J.; Sauter, T.; Green, J.; Poole, R. K.; Bettenbrock, K.; Sawodny, O. (Front Microbiol, 2014)
The efficient redesign of bacteria for biotechnological purposes, such as biofuel production, waste disposal or specific biocatalytic functions, requires a quantitative systems-level understanding of energy supply, carbon, and redox metabolism. The measurement of transcript levels, metabolite concentrations and metabolic fluxes per se gives an incomplete picture. An appreciation of the interdependencies between the different measurement values is essential for systems-level understanding. Mathematical modeling has the potential to provide a coherent and quantitative description of the interplay between gene expression, metabolite concentrations, and metabolic fluxes. Escherichia coli undergoes major adaptations in central metabolism when the availability of oxygen changes. Thus, an integrated description of the oxygen response provides a benchmark of our understanding of carbon, energy, and redox metabolism. We present the first comprehensive model of the central metabolism of E. coli that describes steady-state metabolism at different levels of oxygen availability. Variables of the model are metabolite concentrations, gene expression levels, transcription factor activities, metabolic fluxes, and biomass concentration. We analyze the model with respect to the production capabilities of central metabolism of E. coli. In particular, we predict how precursor and biomass concentration are affected by product formation.

Agent-based modeling of oxygen-responsive transcription factors in Escherichia coli. - Bai, H.; Rolfe, M. D.; Jia, W.; Coakley, S.; Poole, R. K.; Green, J.; Holcombe, M. (PLoS Comput Biol, 2014)
In the presence of oxygen (O2) the model bacterium Escherichia coli is able to conserve energy by aerobic respiration. Two major terminal oxidases are involved in this process - Cyo has a relatively low affinity for O2 but is able to pump protons and hence is energetically efficient; Cyd has a high affinity for O2 but does not pump protons. When E. coli encounters environments with different O2 availabilities, the expression of the genes encoding the alternative terminal oxidases, the cydAB and cyoABCDE operons, are regulated by two O2-responsive transcription factors, ArcA (an indirect O2 sensor) and FNR (a direct O2 sensor). It has been suggested that O2-consumption by the terminal oxidases located at the cytoplasmic membrane significantly affects the activities of ArcA and FNR in the bacterial nucleoid. In this study, an agent-based modeling approach has been taken to spatially simulate the uptake and consumption of O2 by E. coli and the consequent modulation of ArcA and FNR activities based on experimental data obtained from highly controlled chemostat cultures. The molecules of O2, transcription factors and terminal oxidases are treated as individual agents and their behaviors and interactions are imitated in a simulated 3-D E. coli cell. The model implies that there are two barriers that dampen the response of FNR to O2, i.e. consumption of O2 at the membrane by the terminal oxidases and reaction of O2 with cytoplasmic FNR. Analysis of FNR variants suggested that the monomer-dimer transition is the key step in FNR-mediated repression of gene expression.
Keywords: Escherichia coli/genetics/*metabolism; Genes, Bacterial; Operon; Oxygen/*metabolism; Transcription Factors/*metabolism

Evolution, dynamics and specialized functions of glycosomes in metabolism and development of trypanosomatids - Szöör, Balázs; Haanstra, Jurgen; Gualdrón-López, Melisa; Michels, Paul AM (Current Opinion in Microbiology, 2014)
Kinetoplastea such as trypanosomatid parasites contain specialized peroxisomes that uniquely contain enzymes of the glycolytic pathway and other parts of intermediary metabolism and hence are called glycosomes. Their specific enzyme content can vary strongly, quantitatively and qualitatively, between different species and during the parasites’ life cycle. The correct sequestering of enzymes has great importance for the regulation of the trypanosomatids’ metabolism and can, dependent on environmental conditions, even be essential. Glycosomes also play a pivotal role in life-cycle regulation of Trypanosoma brucei, as the translocation of a protein phosphatase from the cytosol forms part of a crucial developmental control switch. Many glycosomal proteins are differentially phosphorylated in different life-cycle stages, possibly indicative for unique forms of activity regulation, whereas many kinetic activity regulation mechanisms common for glycolytic enzymes are absent in these organisms. Glycosome turnover occurs by autophagic degradation of redundant organelles and assembly of new ones. This may provide the trypanosomatids with a manner to rapidly and efficiently adapt their metabolism to the sudden, major nutritional changes often encountered during the life cycle. This could also have helped facilitating successful adaptation of kinetoplastids, at multiple occasions during evolution, to their parasitic life style.

Meeting report from the fourth meeting of the Computational Modeling in Biology Network (COMBINE) - Waltemath, Dagmar; Bergmann, Frank T.; Chaouiya, Claudine; Czauderna, Tobias; Gleeson, Padraig; Goble, Carole; Golebiewski, Martin; Hucka, Michael; Juty, Nick; Krebs, Olga; Le Novère, Nicolas; Mi, Huaiyu; et al. (Standards in Genomic Sciences, 2014)
The Computational Modeling in Biology Network (COMBINE) is an initiative to coordinate the development of community standards and formats in computational systems biology and related fields. This report summarizes the topics and activities of the fourth edition of the annual COMBINE meeting, held in Paris during September 16-20 2013, and attended by a total of 96 people. This edition pioneered a first day devoted to modeling approaches in biology, which attracted a broad audience of scientists thanks to a panel of renowned speakers. During subsequent days, discussions were held on many subjects including the introduction of new features in the various COMBINE standards, new software tools that use the standards, and outreach efforts. Significant emphasis went into work on extensions of the SBML format, and also into community-building. This year’s edition once again demonstrated that the COMBINE community is thriving, and still manages to help coordinate activities between different standards in computational systems biology.

Using a genome-scale metabolic model of Enterococcus faecalis V583 to assess amino acid uptake and its impact on central metabolism. - Veith, N.; Solheim, M.; van Grinsven, K. W.; Olivier, B. G.; Levering, J.; Grosseholz, R.; Hugenholtz, J.; Holo, H.; Nes, I.; Teusink, B.; Kummer, U. (Appl Environ Microbiol, 2015)
Increasing antibiotic resistance in pathogenic bacteria necessitates the development of new medication strategies. Interfering with the metabolic network of the pathogen can provide novel drug targets but simultaneously requires a deeper and more detailed organism-specific understanding of the metabolism, which is often surprisingly sparse. In light of this, we reconstructed a genome-scale metabolic model of the pathogen Enterococcus faecalis V583. The manually curated metabolic network comprises 642 metabolites and 706 reactions. We experimentally determined metabolic profiles of E. faecalis grown in chemically defined medium in an anaerobic chemostat setup at different dilution rates and calculated the net uptake and product fluxes to constrain the model. We computed growth-associated energy and maintenance parameters and studied flux distributions through the metabolic network. Amino acid auxotrophies were identified experimentally for model validation and revealed seven essential amino acids. In addition, the important metabolic hub of glutamine/glutamate was altered by constructing a glutamine synthetase knockout mutant. The metabolic profile showed a slight shift in the fermentation pattern toward ethanol production and increased uptake rates of multiple amino acids, especially l-glutamine and l-glutamate. The model was used to understand the altered flux distributions in the mutant and provided an explanation for the experimentally observed redirection of the metabolic flux. We further highlighted the importance of gene-regulatory effects on the redirection of the metabolic fluxes upon perturbation. The genome-scale metabolic model presented here includes gene-protein-reaction associations, allowing a further use for biotechnological applications, for studying essential genes, proteins, or reactions, and the search for novel drug targets.
Keywords: Amino Acids/*metabolism; *Computer Simulation; Energy Metabolism; Enterococcus faecalis/*genetics/growth & development/*metabolism; Metabolic Flux Analysis; Metabolic Networks and Pathways/*genetics; Models, Biological

RobOKoD: microbial strain design for (over)production of target compounds. - Stanford, N. J.; Millard, P.; Swainston, N. (Front Cell Dev Biol, 2015)
Sustainable production of target compounds such as biofuels and high-value chemicals for pharmaceutical, agrochemical, and chemical industries is becoming an increasing priority given their current dependency upon diminishing petrochemical resources. Designing these strains is difficult, with current methods focusing primarily on knocking-out genes, dismissing other vital steps of strain design including the overexpression and dampening of genes. The design predictions from current methods also do not translate well-into successful strains in the laboratory. Here, we introduce RobOKoD (Robust, Overexpression, Knockout and Dampening), a method for predicting strain designs for overproduction of targets. The method uses flux variability analysis to profile each reaction within the system under differing production percentages of target-compound and biomass. Using these profiles, reactions are identified as potential knockout, overexpression, or dampening targets. The identified reactions are ranked according to their suitability, providing flexibility in strain design for users. The software was tested by designing a butanol-producing Escherichia coli strain, and was compared against the popular OptKnock and RobustKnock methods. RobOKoD shows favorable design predictions, when predictions from these methods are compared to a successful butanol-producing experimentally-validated strain. Overall RobOKoD provides users with rankings of predicted beneficial genetic interventions with which to support optimized strain design.

Modelling reveals novel roles of two parallel signalling pathways and homeostatic feedbacks in yeast. - Schaber, J.; Baltanas, R.; Bush, A.; Klipp, E.; Colman-Lerner, A. (Mol Syst Biol, 2012)
The high osmolarity glycerol (HOG) pathway in yeast serves as a prototype signalling system for eukaryotes. We used an unprecedented amount of data to parameterise 192 models capturing different hypotheses about molecular mechanisms underlying osmo-adaptation and selected a best approximating model. This model implied novel mechanisms regulating osmo-adaptation in yeast. The model suggested that (i) the main mechanism for osmo-adaptation is a fast and transient non-transcriptional Hog1-mediated activation of glycerol production, (ii) the transcriptional response serves to maintain an increased steady-state glycerol production with low steady-state Hog1 activity, and (iii) fast negative feedbacks of activated Hog1 on upstream signalling branches serves to stabilise adaptation response. The best approximating model also indicated that homoeostatic adaptive systems with two parallel redundant signalling branches show a more robust and faster response than single-branch systems. We corroborated this notion to a large extent by dedicated measurements of volume recovery in single cells. Our study also demonstrates that systematically testing a model ensemble against data has the potential to achieve a better and unbiased understanding of molecular mechanisms.
Keywords: Adaptation, Physiological; Chromosomal Proteins, Non-Histone/metabolism; Computer Simulation; DNA-Binding Proteins/metabolism; *Feedback, Physiological; Glycerol/metabolism; *Homeostasis; Intracellular Space/metabolism; Mitogen-Activated Protein Kinases/antagonists & inhibitors/metabolism; *Models, Biological; Mutation/genetics; Osmotic Pressure; Phosphorylation; Saccharomyces cerevisiae/genetics/*metabolism; Saccharomyces cerevisiae Proteins/antagonists & inhibitors/metabolism; *Signal Transduction; Stress, Physiological; Transcription, Genetic

Identification of HNRNPK as regulator of hepatitis C virus particle production. - Poenisch, M.; Metz, P.; Blankenburg, H.; Ruggieri, A.; Lee, J. Y.; Rupp, D.; Rebhan, I.; Diederich, K.; Kaderali, L.; Domingues, F. S.; Albrecht, M.; Lohmann, V.; et al. (PLoS Pathog, 2015)
Hepatitis C virus (HCV) is a major cause of chronic liver disease affecting around 130 million people worldwide. While great progress has been made to define the principle steps of the viral life cycle, detailed knowledge how HCV interacts with its host cells is still limited. To overcome this limitation we conducted a comprehensive whole-virus RNA interference-based screen and identified 40 host dependency and 16 host restriction factors involved in HCV entry/replication or assembly/release. Of these factors, heterogeneous nuclear ribonucleoprotein K (HNRNPK) was found to suppress HCV particle production without affecting viral RNA replication. This suppression of virus production was specific to HCV, independent from assembly competence and genotype, and not found with the related Dengue virus. By using a knock-down rescue approach we identified the domains within HNRNPK required for suppression of HCV particle production. Importantly, HNRNPK was found to interact specifically with HCV RNA and this interaction was impaired by mutations that also reduced the ability to suppress HCV particle production. Finally, we found that in HCV-infected cells, subcellular distribution of HNRNPK was altered; the protein was recruited to sites in close proximity of lipid droplets and colocalized with core protein as well as HCV plus-strand RNA, which was not the case with HNRNPK variants unable to suppress HCV virion formation. These results suggest that HNRNPK might determine efficiency of HCV particle production by limiting the availability of viral RNA for incorporation into virions. This study adds a new function to HNRNPK that acts as central hub in the replication cycle of multiple other viruses.
Keywords: Cells, Cultured; HEK293 Cells; Hepacivirus/drug effects/*physiology; Heterogeneous-Nuclear Ribonucleoprotein K; Humans; Protein Binding; RNA Interference; RNA, Small Interfering/pharmacology; RNA, Viral/metabolism; Ribonucleoproteins/antagonists & inhibitors/*physiology; Virion/drug effects/*physiology; Virus Assembly/drug effects/*genetics; Virus Replication/drug effects/genetics

Construction and validation of a detailed kinetic model of glycolysis in Plasmodium falciparum - Penkler, Gerald; du Toit, Francois; Adams, Waldo; Rautenbach, Marina; Palm, Daniel C.; van Niekerk, Dawie; Snoep, Jacky (FEBS J, 2015)
The enzymes in the Embden–Meyerhof–Parnas pathway of Plasmodium falciparum trophozoites were kinetically characterized and their integrated activities analyzed in a mathematical model. For validation of the model, we compared model predictions for steady-state fluxes and metabolite concentrations of the hexose phosphates with experimental values for intact parasites. The model, which is completely based on kinetic parameters that were measured for the individual enzymes, gives an accurate prediction of the steady-state fluxes and intermediate concentrations. This is the first detailed kinetic model for glucose metabolism in P. falciparum, one of the most prolific malaria-causing protozoa, and the high predictive power of the model makes it a strong tool for future drug target identification studies. The modelling workflow is transparent and reproducible, and completely documented in the SEEK platform, where all experimental data and model files are available for download.

Recruitment and activation of a lipid kinase by hepatitis C virus NS5A is essential for integrity of the membranous replication compartment. - Reiss, S.; Rebhan, I.; Backes, P.; Romero-Brey, I.; Erfle, H.; Matula, P.; Kaderali, L.; Poenisch, M.; Blankenburg, H.; Hiet, M. S.; Longerich, T.; Diehl, S.; et al. (Cell Host Microbe, 2011)
Hepatitis C virus (HCV) is a major causative agent of chronic liver disease in humans. To gain insight into host factor requirements for HCV replication, we performed a siRNA screen of the human kinome and identified 13 different kinases, including phosphatidylinositol-4 kinase III alpha (PI4KIIIalpha), as being required for HCV replication. Consistent with elevated levels of the PI4KIIIalpha product phosphatidylinositol-4-phosphate (PI4P) detected in HCV-infected cultured hepatocytes and liver tissue from chronic hepatitis C patients, the enzymatic activity of PI4KIIIalpha was critical for HCV replication. Viral nonstructural protein 5A (NS5A) was found to interact with PI4KIIIalpha and stimulate its kinase activity. The absence of PI4KIIIalpha activity induced a dramatic change in the ultrastructural morphology of the membranous HCV replication complex. Our analysis suggests that the direct activation of a lipid kinase by HCV NS5A contributes critically to the integrity of the membranous viral replication complex.
Keywords: Cell Line; Gene Knockdown Techniques; Hepacivirus/*physiology; Hepatocytes/chemistry/enzymology/virology; *Host-Pathogen Interactions; Humans; Liver/chemistry/enzymology/virology; Minor Histocompatibility Antigens; Models, Biological; Phosphatidylinositol Phosphates/metabolism; Phosphotransferases (Alcohol Group Acceptor)/*metabolism; Protein Binding; RNA, Small Interfering/genetics/metabolism; Viral Nonstructural Proteins/*metabolism; *Virus Replication

Metabolic efficiency in yeast Saccharomyces cerevisiae in relation to temperature dependent growth and biomass yield - Zakhartsev, Maksim; Yang, Xuelian; Reuss, Matthias; Pörtner, Hans Otto (Journal of Thermal Biology, 2015)
Canonized view on temperature effects on growth rate of microorganisms is based on assumption of protein denaturation, which is not confirmed experimentally so far. We develop an alternative concept, which is based on view that limits of thermal tolerance are based on imbalance of cellular energy allocation. Therefore, we investigated growth suppression of yeast Saccharomyces cerevisiae in the supraoptimal temperature range (30–40 °C), i.e. above optimal temperature (Topt). The maximal specific growth rate (μmax) of biomass, its concentration and yield on glucose (Yx/glc) were measured across the whole thermal window (5–40 °C) of the yeast in batch anaerobic growth on glucose. Specific rate of glucose consumption, specific rate of glucose consumption for maintenance (mglc), true biomass yield on glucose (View the MathML source), fractional conservation of substrate carbon in product and ATP yield on glucose (Yatp/glc) were estimated from the experimental data. There was a negative linear relationship between ATP, ADP and AMP concentrations and specific growth rate at any growth conditions, whilst the energy charge was always high (~0.83). There were two temperature regions where mglc differed 12-fold, which points to the existence of a ‘low’ (within 5–31 °C) and a ‘high’ (within 33–40 °C) metabolic mode regarding maintenance requirements. The rise from the low to high mode occurred at 31–32 °C in step-wise manner and it was accompanied with onset of suppression of μmax. High mglc at supraoptimal temperatures indicates a significant reduction of scope for growth, due to high maintenance cost. Analysis of temperature dependencies of product formation efficiency and Yatp/glc revealed that the efficiency of energy metabolism approaches its lower limit at 26–31 °C. This limit is reflected in the predetermined combination of View the MathML source, elemental biomass composition and degree of reduction of the growth substrate. Approaching the limit implies a reduction of the safety margin of metabolic efficiency. We hypothesize that a temperature increase above Topt (e.g. >31 °C) triggers both an increment in mglc and suppression of μmax, which together contribute to an upshift of Yatp/glc from the lower limit and thus compensate for the loss of the safety margin. This trade-off allows adding 10 more degrees to Topt and extends the thermal window up to 40 °C, sustaining survival and reproduction in supraoptimal temperatures. Deeper understanding of the limits of thermal tolerance can be practically exploited in biotechnological applications.

Fast sampling for quantitative microbial metabolomics: new aspects on cold methanol quenching: metabolite co-precipitation - Zakhartsev, Maksim; Vielhauer, Oliver; Horn, Thomas; Yang, Xuelian; Reuss, Matthias (Metabolomics, 2015)
The intra- and extracellular concentrations of 16 metabolites were measured in chemostat (D = 0.1 h−1) anaerobic cultures of the yeast Saccharomyces cerevisiae CEN.PK-113-7D growing on minimal medium. Two independent sampling workflows were employed: (i) conventional cold methanol quenching and (ii) a differential approach. Metabolites were quantified in different sample fractions (total, extracellular, quenching supernatant, methanol/water extract and pellet) in order to derive their mass balance. The differential method in combination with absolute metabolite quantification by gas-chromatography with isotope dilution mass spectrometry (GC–IDMS) was used as a benchmark to assess quality of the cold methanol quenching procedure. Quantitative comparison of metabolite concentrations in all fractions collected by different quenching techniques indicates asystematic loss of the total mass of various metabolites in course of the cold methanol quenching. Pellet resulting from the cold methanol quenching besides biomass contains considerable amounts of precipitated inorganic salts from the fermentation media. Quantitative analysis has revealed significant co-precipitation of polar extracellular metabolites together with these salts. This phenomenon is especially significant for metabolites with large extracellular mass-fraction. We report that the co-precipitation is a hitherto neglected phenomenon and concluded that its degree strongly linked to culturing conditions (i.e. media composition) and chemical properties of the particular metabolite. Thus, intracellular metabolite levels measured from samples collected by cold methanol quenching might be uncertain and variably biased due to corruption by described phenomena.

Ribosome and transcript copy numbers, polysome occupancy and enzyme dynamics in Arabidopsis - Piques, Maria; Schulze, Waltraud X; Höhne, Melanie; Usadel, Björn; Gibon, Yves; Rohwer, Johann; Stitt, Mark (Mol Syst Biol, 2009)
Plants are exposed to continual changes in the environment. The daily alternation between light and darkness results in massive recurring changes in the carbon budget, and leads to widespread changes in transcript levels. These diurnal changes are superimposed on slower changes in the environment. Quantitative molecular information about the numbers of ribosomes, of transcripts for 35 enzymes in central metabolism and their loading into polysomes is used to estimate translation rates in Arabidopsis rosettes, and explore the consequences for important sub-processes in plant growth. Translation rates for individual enzyme are compared with their abundance in the rosette to predict which enzymes are subject to rapid turnover every day, and which are synthesized at rates that would allow only slow adjustments to sustained changes of the environment, or resemble those needed to support the observed rate of growth. Global translation rates are used to estimate the energy costs of protein synthesis and relate them to the plant carbon budget, in particular the rates of starch degradation and respiration at night.

QIIME allows analysis of high-throughput community sequencing data. - Caporaso, J. G.; Kuczynski, J.; Stombaugh, J.; Bittinger, K.; Bushman, F. D.; Costello, E. K.; Fierer, N.; Pena, A. G.; Goodrich, J. K.; Gordon, J. I.; Huttley, G. A.; Kelley, S. T.; et al. (Nat Methods, 2010)
Keywords: Animals; Feces/microbiology; Humans; Mice; RNA, Ribosomal, 16S/*genetics; Sequence Analysis, RNA/*methods; *Software; Twins, Dizygotic/genetics; Twins, Monozygotic/genetics

Division of labor by dual feedback regulators controls JAK2/STAT5 signaling over broad ligand range - Bachmann, J.; Raue, A.; Schilling, Marcel; Böhm, Martin; Kreutz, C.; Kaschek, D.; Busch, H.; Gretz, N.; Lehmann, W. D.; Timmer, Jens; Klingmüller, Ursula (Molecular Systems Biology, 2011)
Cellular signal transduction is governed by multiple feedback mechanisms to elicit robust cellular decisions. The specific contributions of individual feedback regulators, however, remain unclear. Based on extensive time-resolved data sets in primary erythroid progenitor cells, we established a dynamic pathway model to dissect the roles of the two transcriptional negative feedback regulators of the suppressor of cytokine signaling (SOCS) family, CIS and SOCS3, in JAK2/STAT5 signaling. Facilitated by the model, we calculated the STAT5 response for experimentally unobservable Epo concentrations and provide a quantitative link between cell survival and the integrated response of STAT5 in the nucleus. Model predictions show that the two feedbacks CIS and SOCS3 are most effective at different ligand concentration ranges due to their distinct inhibitory mechanisms. This divided function of dual feedback regulation enables control of STAT5 responses for Epo concentrations that can vary 1000-fold in vivo. Our modeling approach reveals dose-dependent feedback control as key property to regulate STAT5-mediated survival decisions over a broad range of ligand concentrations.

Minimum information about a microarray experiment (MIAME)-toward standards for microarray data. - Brazma, A.; Hingamp, P.; Quackenbush, J.; Sherlock, G.; Spellman, P.; Stoeckert, C.; Aach, J.; Ansorge, W.; Ball, C. A.; Causton, H. C.; Gaasterland, T.; Glenisson, P.; et al. (Nat Genet, 2001)
Microarray analysis has become a widely used tool for the generation of gene expression data on a genomic scale. Although many significant results have been derived from microarray studies, one limitation has been the lack of standards for presenting and exchanging such data. Here we present a proposal, the Minimum Information About a Microarray Experiment (MIAME), that describes the minimum information required to ensure that microarray data can be easily interpreted and that results derived from its analysis can be independently verified. The ultimate goal of this work is to establish a standard for recording and reporting microarray-based gene expression data, which will in turn facilitate the establishment of databases and public repositories and enable the development of data analysis tools. With respect to MIAME, we concentrate on defining the content and structure of the necessary information rather than the technical format for capturing it.
Keywords: *Computational Biology; Gene Expression Profiling/methods; Oligonucleotide Array Sequence Analysis/*standards

Design principles of nuclear receptor signaling: how complex networking improves signal transduction - Kolodkin, Alexey N; Bruggeman, Frank J; Plant, Nick; Moné, Martijn J; Bakker, Barbara M; Campbell, Moray J; van Leeuwen, Johannes P T M; Carlberg, Carsten; Snoep, Jacky; Westerhoff, Hans V (Mol Syst Biol, 2010)
The topology of nuclear receptor (NR) signaling is captured in a systems biological graphical notation. This enables us to identify a number of ‘design’ aspects of the topology of these networks that might appear unnecessarily complex or even functionally paradoxical. In realistic kinetic models of increasing complexity, calculations show how these features correspond to potentially important design principles, e.g.: (i) cytosolic ‘nuclear’ receptor may shuttle signal molecules to the nucleus, (ii) the active export of NRs may ensure that there is sufficient receptor protein to capture ligand at the cytoplasmic membrane, (iii) a three conveyor belts design dissipating GTP-free energy, greatly aids response, (iv) the active export of importins may prevent sequestration of NRs by importins in the nucleus and (v) the unspecific nature of the nuclear pore may ensure signal-flux robustness. In addition, the models developed are suitable for implementation in specific cases of NR-mediated signaling, to predict individual receptor functions and differential sensitivity toward physiological and pharmacological ligands.

Modeling the cell division cycle: cdc2 and cyclin interactions. - Tyson, J. J. (Proc Natl Acad Sci U S A, 1991)
The proteins cdc2 and cyclin form a heterodimer (maturation promoting factor) that controls the major events of the cell cycle. A mathematical model for the interactions of cdc2 and cyclin is constructed. Simulation and analysis of the model show that the control system can operate in three modes: as a steady state with high maturation promoting factor activity, as a spontaneous oscillator, or as an excitable switch. We associate the steady state with metaphase arrest in unfertilized eggs, the spontaneous oscillations with rapid division cycles in early embryos, and the excitable switch with growth-controlled division cycles typical of nonembryonic cells.
Keywords: Animals; CDC2 Protein Kinase/*metabolism; *Cell Division; Cyclins/*metabolism; Kinetics; Mathematics; Maturation-Promoting Factor/physiology; Mitosis; *Models, Biological

An allosteric model of calmodulin explains differential activation of PP2B and CaMKII. - Stefan, M. I.; Edelstein, S. J.; Le Novere, N. (Proc Natl Acad Sci U S A, 2008)
Calmodulin plays a vital role in mediating bidirectional synaptic plasticity by activating either calcium/calmodulin-dependent protein kinase II (CaMKII) or protein phosphatase 2B (PP2B) at different calcium concentrations. We propose an allosteric model for calmodulin activation, in which binding to calcium facilitates the transition between a low-affinity [tense (T)] and a high-affinity [relaxed (R)] state. The four calcium-binding sites are assumed to be nonidentical. The model is consistent with previously reported experimental data for calcium binding to calmodulin. It also accounts for known properties of calmodulin that have been difficult to model so far, including the activity of nonsaturated forms of calmodulin (we predict the existence of open conformations in the absence of calcium), an increase in calcium affinity once calmodulin is bound to a target, and the differential activation of CaMKII and PP2B depending on calcium concentration.
Keywords: Allosteric Regulation; Calcineurin/*metabolism; Calcium/*metabolism; Calcium-Calmodulin-Dependent Protein Kinase Type 2/*metabolism; Calmodulin/*chemistry/*metabolism; Computer Simulation; Enzyme Activation/genetics; Kinetics; *Models, Molecular; Protein Binding; Synapses/*metabolism

The Atlantic salmon genome provides insights into rediploidization. - Lien, S.; Koop, B. F.; Sandve, S. R.; Miller, J. R.; Kent, M. P.; Nome, T.; Hvidsten, T. R.; Leong, J. S.; Minkley, D. R.; Zimin, A.; Grammes, F.; Grove, H.; et al. (Nature, 2016)
The whole-genome duplication 80 million years ago of the common ancestor of salmonids (salmonid-specific fourth vertebrate whole-genome duplication, Ss4R) provides unique opportunities to learn about the evolutionary fate of a duplicated vertebrate genome in 70 extant lineages. Here we present a high-quality genome assembly for Atlantic salmon (Salmo salar), and show that large genomic reorganizations, coinciding with bursts of transposon-mediated repeat expansions, were crucial for the post-Ss4R rediploidization process. Comparisons of duplicate gene expression patterns across a wide range of tissues with orthologous genes from a pre-Ss4R outgroup unexpectedly demonstrate far more instances of neofunctionalization than subfunctionalization. Surprisingly, we find that genes that were retained as duplicates after the teleost-specific whole-genome duplication 320 million years ago were not more likely to be retained after the Ss4R, and that the duplicate retention was not influenced to a great extent by the nature of the predicted protein interactions of the gene products. Finally, we demonstrate that the Atlantic salmon assembly can serve as a reference sequence for the study of other salmonids for a range of purposes.
Keywords: Animals; DNA Transposable Elements/genetics; *Diploidy; *Evolution, Molecular; Female; Gene Duplication/*genetics; Genes, Duplicate/*genetics; Genome/*genetics; Genomics; Male; Models, Genetic; Mutagenesis/genetics; Phylogeny; Reference Standards; Salmo salar/classification/*genetics; Sequence Homology

Molecular biological correlation of fluorine-18 fluorodeoxyglucose uptake in esophageal squamous cell carcinoma. - Hirose, Y.; Kaida, H.; Kawahara, A.; Matono, S.; Tanaka, T.; Kurata, S.; Kage, M.; Ishibashi, M.; Abe, T. (Nucl Med Commun, 2016)
OBJECTIVE: The aim of this study was to assess the relationship between fluorine-18 fluorodeoxyglucose (F-FDG) uptake and molecular biological markers in esophageal squamous cell carcinoma (ESCC) patients. METHODS: Our patient population included 51 patients who underwent F-FDG PET/computed tomography before surgery. Excised tumor tissue was analyzed immunohistochemically using monoclonal antibodies for glucose transporter-1 (GLUT-1), GLUT-3, CD34 [microvessel density (MVD) marker], CD68 (macrophage marker), and CD163 (tumor-associated macrophage marker). The relationships among pathological factors [pathological T stage (p-T stage), pathological lymph node status (p-N status), pathological stage (p-stage), and pathological tumor length], the maximum standardized uptake value (SUVmax), and these molecular biological markers were evaluated using Spearman's rank test and the Kruskal-Wallis test. RESULTS: GLUT-1, GLUT-3, CD34, and CD163 significantly correlated with SUVmax (r=0.547, P<0.001 for GLUT-1; r=0.569, P<0.001 for GLUT-3; r=0.463, P=0.001 for CD34, r=0.455, P=0.001 for CD163), whereas SUVmax, GLUT-1, GLUT-3, CD34, and CD163 significantly correlated with p-T stage (r=0.552, P<0.001 for SUVmax, r=0.307, P=0.03 for GLUT-1, r=0.349, P=0.013 for GLUT-3, r=0.313, P=0.027 for CD34, r=0.526 for CD163, P<0.001), but not with p-N status. CD68 levels showed no significant correlation with SUVmax, p-T stage, p-stage, or p-N status. CONCLUSION: SUVmax, GLUT-1 expression, GLUT-3 expression, MVD, and TAMs show a relationship with the tumor stage and extent of ESCC. GLUT-1, GLUT-3, MVD, and TAMs are associated with the mechanism of F-FDG uptake in ESCC.
Keywords: Adult; Aged; Aged, 80 and over; Biological Transport; Biomarkers, Tumor/metabolism; Carcinoma, Squamous Cell/*metabolism/pathology; Esophageal Neoplasms/*metabolism/pathology; Esophageal Squamous Cell Carcinoma; Female; Fluorodeoxyglucose F18/*metabolism; Glucose Transporter Type 1/metabolism; Humans; Male; Middle Aged; Neoplasm Staging; Retrospective Studies

Transcriptomic analysis reveals how a lack of potassium ions increases Sulfolobus acidocaldarius sensitivity to pH changes - Buetti-Dinh, Antoine; Dethlefsen, Olga; Friedman, Ran; Dopson, Mark (2016)

Positive cooperative binding of calcium to bovine brain calmodulin - Crouch, Thomas H.; Klee, Claude B. (Biochemistry, 1980)

Search and clustering orders of magnitude faster than BLAST. - Edgar, R. C. (Bioinformatics, 2010)
MOTIVATION: Biological sequence data is accumulating rapidly, motivating the development of improved high-throughput methods for sequence classification. RESULTS: UBLAST and USEARCH are new algorithms enabling sensitive local and global search of large sequence databases at exceptionally high speeds. They are often orders of magnitude faster than BLAST in practical applications, though sensitivity to distant protein relationships is lower. UCLUST is a new clustering method that exploits USEARCH to assign sequences to clusters. UCLUST offers several advantages over the widely used program CD-HIT, including higher speed, lower memory use, improved sensitivity, clustering at lower identities and classification of much larger datasets. AVAILABILITY: Binaries are available at no charge for non-commercial use at http://www.drive5.com/usearch.
Keywords: *Algorithms; Cluster Analysis; Computational Biology/*methods; Databases, Protein; Proteins/chemistry; Sequence Alignment/*methods; Sequence Analysis, Protein/*methods

UPARSE: highly accurate OTU sequences from microbial amplicon reads. - Edgar, R. C. (Nat Methods, 2013)
Amplified marker-gene sequences can be used to understand microbial community structure, but they suffer from a high level of sequencing and amplification artifacts. The UPARSE pipeline reports operational taxonomic unit (OTU) sequences with </=1% incorrect bases in artificial microbial community tests, compared with >3% incorrect bases commonly reported by other methods. The improved accuracy results in far fewer OTUs, consistently closer to the expected number of species in a community.
Keywords: Algorithms; Databases, Genetic; Humans; Metagenomics; Microbiota/*genetics; *Phylogeny; RNA, Ribosomal, 16S/*genetics; Research Design; Sensitivity and Specificity; Software

cy3sabiork: A Cytoscape app for visualizing kinetic data from SABIO-RK - König, Matthias (F1000Res, 2016)
Kinetic data of biochemical reactions are essential for the creation of kinetic models of biochemical networks. One of the main resources of such information is SABIO-RK, a curated database for kinetic data of biochemical reactions and their related information. Despite the importance for computational modelling there has been no simple solution to visualize the kinetic data from SABIO-RK. In this work, I present cy3sabiork, an app for querying and visualization of kinetic data from SABIO-RK in Cytoscape. The kinetic information is accessible via a combination of graph structure and annotations of nodes, with provided information consisting of: (I) reaction details, enzyme and organism; (II) kinetic law, formula, parameters; (III) experimental conditions; (IV) publication; (V) additional annotations. cy3sabiork creates an intuitive visualization of kinetic entries in form of a species-reaction-kinetics graph, which reflects the reaction-centered approach of SABIO-RK. Kinetic entries can be imported in SBML format from either the SABIO-RK web interface or via web service queries. The app allows for easy comparison of kinetic data, visual inspection of the elements involved in the kinetic record and simple access to the annotation information of the kinetic record. I applied cy3sabiork in the computational modelling of galactose metabolism in the human liver.

Targeting glycolysis in the malaria parasite Plasmodium falciparum - van Niekerk, Dawie; Penkler, Gerald P.; du Toit, Francois; Snoep, Jacky (FEBS J, 2016)
Glycolysis is the main pathway for ATP production in the malaria parasite Plasmodium falciparum and essential for its survival. Following a sensitivity analysis of a detailed kinetic model for glycolysis in the parasite, the glucose transport reaction was identified as the step whose activity needed to be inhibited to the least extent to result in a 50% reduction in glycolytic flux. In a subsequent inhibitor titration with cytochalasin B, we confirmed the model analysis experimentally and measured a flux control coefficient of 0.3 for the glucose transporter. In addition to the glucose transporter, the glucokinase and phosphofructokinase had high flux control coefficients, while for the ATPase a small negative flux control coefficient was predicted. In a broader comparative analysis of glycolytic models, we identified a weakness in the P. falciparum pathway design with respect to stability towards perturbations in the ATP demand.

Quantitative analysis of drug effects at the whole-body level: a case study for glucose metabolism in malaria patients - Snoep, Jacky; Green, Kathleen; Eicher, J.; Palm, D. C.; Penkler, G.; du Toit, F.; Walters, N.; Burger, R.; Westerhoff, H. V.; van Niekerk, Dawie (Biochemical Society Transactions, 2015)
We propose a hierarchical modelling approach to construct models for disease states at the whole-body level. Such models can simulate effects of drug-induced inhibition of reaction steps on the whole-body physiology. We illustrate the approach for glucose metabolism in malaria patients, by merging two detailed kinetic models for glucose metabolism in the parasite Plasmodium falciparum and the human red blood cell with a coarse-grained model for whole-body glucose metabolism. In addition we use a genome-scale metabolic model for the parasite to predict amino acid production profiles by the malaria parasite that can be used as a complex biomarker.

Simplified absolute metabolite quantification by gas chromatography–isotope dilution mass spectrometry on the basis of commercially available source material - Vielhauer, Oliver; Zakhartsev, Maksim; Horn, Thomas; Takors, Ralf; Reuss, Matthias (Journal of Chromatography B, 2011)

Search for a minimal set of parameters by assessing the total optimisation potential for a dynamic model of a biochemical network - Stalidzans, Egils; Mozga, Ivars; Sulins, Jurijs; Zikmanis, Peteris (IEEE/ACM Trans. Comput. Biol. and Bioinf., 2016)
Selecting an efficient small set of adjustable parameters to improve metabolic features of an organism is important for a reduction of implementation costs and risks of unpredicted side effects. In practice, to avoid the analysis of a huge combinatorial space for the possible sets of adjustable parameters, experience-, and intuition-based subsets of parameters are often chosen, possibly leaving some interesting counter-intuitive combinations of parameters unrevealed. The combinatorial scan of possible adjustable parameter combinations at the model optimization level is possible; however, the number of analyzed combinations is still limited. The total optimization potential (TOP) approach is proposed to assess the full potential for increasing the value of the objective function by optimizing all possible adjustable parameters. This seemingly unpractical combination of adjustable parameters allows assessing the maximum attainable value of the objective function and stopping the combinatorial space scanning when the desired fraction of TOP is reached and any further increase in the number of adjustable parameters cannot bring any reasonable improvement. The relation between the number of adjustable parameters and the reachable fraction of TOP is a valuable guideline in choosing a rational solution for industrial implementation. The TOP approach is demonstrated on the basis of two case studies.

Disentangling the Complexity of HGF Signaling by Combining Qualitative and Quantitative Modeling. - D'Alessandro, L. A.; Samaga, R.; Maiwald, T.; Rho, S. H.; Bonefas, S.; Raue, A.; Iwamoto, N.; Kienast, A.; Waldow, K.; Meyer, R.; Schilling, M.; Timmer, J.; et al. (PLoS Comput Biol, 2015)
Signaling pathways are characterized by crosstalk, feedback and feedforward mechanisms giving rise to highly complex and cell-context specific signaling networks. Dissecting the underlying relations is crucial to predict the impact of targeted perturbations. However, a major challenge in identifying cell-context specific signaling networks is the enormous number of potentially possible interactions. Here, we report a novel hybrid mathematical modeling strategy to systematically unravel hepatocyte growth factor (HGF) stimulated phosphoinositide-3-kinase (PI3K) and mitogen activated protein kinase (MAPK) signaling, which critically contribute to liver regeneration. By combining time-resolved quantitative experimental data generated in primary mouse hepatocytes with interaction graph and ordinary differential equation modeling, we identify and experimentally validate a network structure that represents the experimental data best and indicates specific crosstalk mechanisms. Whereas the identified network is robust against single perturbations, combinatorial inhibition strategies are predicted that result in strong reduction of Akt and ERK activation. Thus, by capitalizing on the advantages of the two modeling approaches, we reduce the high combinatorial complexity and identify cell-context specific signaling networks.
Keywords: Animals; Cells, Cultured; Computer Simulation; Hepatocyte Growth Factor/*metabolism; Hepatocytes/*metabolism; Liver Regeneration/*physiology; MAP Kinase Signaling System/*physiology; Mice; *Models, Biological; Phosphatidylinositol 3-Kinases/*metabolism; Proto-Oncogene Proteins c-akt/metabolism

Evaluation of GMP-compliant culture media for in vitro expansion of human bone marrow mesenchymal stromal cells. - Wuchter, P.; Vetter, M.; Saffrich, R.; Diehlmann, A.; Bieback, K.; Ho, A. D.; Horn, P. (Exp Hematol, 2016)
Mesenchymal stromal cells (MSCs) from human bone marrow serve as a resource for cell-based therapies in regenerative medicine. Clinical applications require standardized protocols according to good manufacturing practice (GMP) guidelines. Donor variability as well as the intrinsic heterogeneity of MSC populations must be taken into consideration. The composition of the culture medium is a key factor in successful MSC expansion. The aim of this study was to comparatively assess the efficiency of xeno-free human platelet lysate (HPL)-based cell expansion with two commercially available media-StemPro MSC SFM CTS (for human ex vivo tissue and cell culture processing applications) and MSCGM (non-GMP-compliant, for research only)-in an academic setting as the first optimization step toward GMP-compliant manufacturing. We report the feasibility of MSC expansion up to the yielded cell number with all three media. MSCs exhibited the typical fibroblastoid morphology, with distinct differences in cell size depending on the medium. The differentiation capacity and characteristic immunophenotype were confirmed for all MSC populations. Proliferation was highest using StemPro MSC SFM CTS, whereas HPL medium was more cost-effective and its composition could be adjusted individually according to the respective needs. In summary, we present a comprehensive evaluation of GMP-compatible culture media for MSC expansion. Both StemPro and HPL medium proved to be suitable for clinical application and allowed sufficient cell proliferation. Specific differences were observed and should be considered according to the intended use. This study provides a detailed cost analysis and tools that may be helpful for the establishment of GMP-compliant MSC expansion.
Keywords: Cell Culture Techniques/economics/methods/*standards; Cell Differentiation; Cell Proliferation; Cell Separation; Coculture Techniques; Culture Media/*standards; *Guideline Adherence; Humans; Immunophenotyping; Mesenchymal Stem Cells/*cytology

Context-specific flow through the MEK/ERK module produces cell- and ligand-specific patterns of ERK single and double phosphorylation. - Iwamoto, N.; D'Alessandro, L. A.; Depner, S.; Hahn, B.; Kramer, B. A.; Lucarelli, P.; Vlasov, A.; Stepath, M.; Bohm, M. E.; Deharde, D.; Damm, G.; Seehofer, D.; et al. (Sci Signal, 2016)
The same pathway, such as the mitogen-activated protein kinase (MAPK) pathway, can produce different cellular responses, depending on stimulus or cell type. We examined the phosphorylation dynamics of the MAPK kinase MEK and its targets extracellular signal-regulated kinase 1 and 2 (ERK1/2) in primary hepatocytes and the transformed keratinocyte cell line HaCaT A5 exposed to either hepatocyte growth factor or interleukin-6. By combining quantitative mass spectrometry with dynamic modeling, we elucidated network structures for the reversible threonine and tyrosine phosphorylation of ERK in both cell types. In addition to differences in the phosphorylation and dephosphorylation reactions, the HaCaT network model required two feedback mechanisms, which, as the experimental data suggested, involved the induction of the dual-specificity phosphatase DUSP6 and the scaffold paxillin. We assayed and modeled the accumulation of the double-phosphorylated and active form of ERK1/2, as well as the dynamics of the changes in the monophosphorylated forms of ERK1/2. Modeling the differences in the dynamics of the changes in the distributions of the phosphorylated forms of ERK1/2 suggested that different amounts of MEK activity triggered context-specific responses, with primary hepatocytes favoring the formation of double-phosphorylated ERK1/2 and HaCaT A5 cells that produce both the threonine-phosphorylated and the double-phosphorylated form. These differences in phosphorylation distributions explained the threshold, sensitivity, and saturation of the ERK response. We extended the findings of differential ERK phosphorylation profiles to five additional cultured cell systems and matched liver tumor and normal tissue, which revealed context-specific patterns of the various forms of phosphorylated ERK.
Keywords: Cell Line, Transformed; Dual Specificity Phosphatase 6/genetics/metabolism; Humans; MAP Kinase Kinase Kinases/genetics/*metabolism; MAP Kinase Signaling System/*physiology; Mitogen-Activated Protein Kinase 1/genetics/*metabolism; Mitogen-Activated Protein Kinase 3/genetics/*metabolism; *Models, Biological; Phosphorylation/physiology

Microcavity arrays as an in vitro model system of the bone marrow niche for hematopoietic stem cells. - Wuchter, P.; Saffrich, R.; Giselbrecht, S.; Nies, C.; Lorig, H.; Kolb, S.; Ho, A. D.; Gottwald, E. (Cell Tissue Res, 2016)
In previous studies human mesenchymal stromal cells (MSCs) maintained the "stemness" of human hematopoietic progenitor cells (HPCs) through direct cell-cell contact in two-dimensional co-culture systems. We establish a three-dimensional (3D) co-culture system based on a custom-made chip, the 3(D)-KITChip, as an in vitro model system of the human hematopoietic stem cell niche. This array of up to 625 microcavities, with 300 mum size in each orientation, was inserted into a microfluidic bioreactor. The microcavities of the 3(D)-KITChip were inoculated with human bone marrow MSCs together with umbilical cord blood HPCs. MSCs used the microcavities as a scaffold to build a complex 3D mesh. HPCs were distributed three-dimensionally inside this MSC network and formed ss-catenin- and N-cadherin-based intercellular junctions to the surrounding MSCs. Using RT(2)-PCR and western blots, we demonstrate that a proportion of HPCs maintained the expression of CD34 throughout a culture period of 14 days. In colony-forming unit assays, the hematopoietic stem cell plasticity remained similar after 14 days of bioreactor co-culture, whereas monolayer co-cultures showed increasing signs of HPC differentiation and loss of stemness. These data support the notion that the 3D microenvironment created within the microcavity array preserves vital stem cell functions of HPCs more efficiently than conventional co-culture systems.
Keywords: Antigens, CD/metabolism; Bioreactors; Blotting, Western; Bone Marrow Cells/*cytology; Cell Count; Cell Culture Techniques/*instrumentation/*methods; Cell Separation; Coculture Techniques; Colony-Forming Units Assay; Fluorescent Antibody Technique; Hematopoietic Stem Cells/*cytology; Humans; Mesenchymal Stem Cells/cytology; *Models, Biological; Real-Time Polymerase Chain Reaction; *Stem Cell Niche

Data2Dynamics: a modeling environment tailored to parameter estimation in dynamical systems. - Raue, A.; Steiert, B.; Schelker, M.; Kreutz, C.; Maiwald, T.; Hass, H.; Vanlier, J.; Tonsing, C.; Adlung, L.; Engesser, R.; Mader, W.; Heinemann, T.; et al. (Bioinformatics, 2015)
Modeling of dynamical systems using ordinary differential equations is a popular approach in the field of systems biology. Two of the most critical steps in this approach are to construct dynamical models of biochemical reaction networks for large datasets and complex experimental conditions and to perform efficient and reliable parameter estimation for model fitting. We present a modeling environment for MATLAB that pioneers these challenges. The numerically expensive parts of the calculations such as the solving of the differential equations and of the associated sensitivity system are parallelized and automatically compiled into efficient C code. A variety of parameter estimation algorithms as well as frequentist and Bayesian methods for uncertainty analysis have been implemented and used on a range of applications that lead to publications. AVAILABILITY AND IMPLEMENTATION: The Data2Dynamics modeling environment is MATLAB based, open source and freely available at http://www.data2dynamics.org. CONTACT: andreas.raue@fdm.uni-freiburg.de SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Algorithms; Bayes Theorem; *Models, Biological; *Software; Systems Biology/*methods

Identification of isoform-specific dynamics in phosphorylation-dependent STAT5 dimerization by quantitative mass spectrometry and mathematical modeling. - Boehm, M. E.; Adlung, L.; Schilling, M.; Roth, S.; Klingmuller, U.; Lehmann, W. D. (J Proteome Res, 2014)
STAT5A and STAT5B are important transcription factors that dimerize and transduce activation signals of cytokine receptors directly to the nucleus. A typical cytokine that mediates STAT5 activation is erythropoietin (Epo). Differential functions of STAT5A and STAT5B have been reported. However, the extent to which phosphorylated STAT5A and STAT5B (pSTAT5A, pSTAT5B) form homo- or heterodimers is not understood, nor is how this might influence the signal transmission to the nucleus. To study this, we designed a concept to investigate the isoform-specific dimerization behavior of pSTAT5A and pSTAT5B that comprises isoform-specific immunoprecipitation (IP), measurement of the degree of phosphorylation, and isoform ratio determination between STAT5A and STAT5B. For the main analytical method, we employed quantitative label-free and -based mass spectrometry. For the cellular model system, we used Epo receptor (EpoR)-expressing BaF3 cells (BaF3-EpoR) stimulated with Epo. Three hypotheses of dimer formation between pSTAT5A and pSTAT5B were used to explain the analytical results by a static mathematical model: formation of (i) homodimers only, (ii) heterodimers only, and (iii) random formation of homo- and heterodimers. The best agreement between experimental data and model simulations was found for the last case. Dynamics of cytoplasmic STAT5 dimerization could be explained by distinct nuclear import rates and individual nuclear retention for homo- and heterodimers of phosphorylated STAT5.
Keywords: Algorithms; Amino Acid Sequence; Animals; Cell Line; Cell Nucleus/metabolism; Chromatography, Liquid; Cytoplasm/metabolism; Erythropoietin/pharmacology; Immunoblotting; Kinetics; Mass Spectrometry/*methods; Mice; *Models, Theoretical; Molecular Sequence Data; Phosphorylation; *Protein Multimerization; Protein Transport/drug effects; Receptors, Erythropoietin/genetics/metabolism; STAT5 Transcription Factor/*chemistry/genetics/metabolism; Sequence Homology, Amino Acid

Mesenchymal stromal cells inhibit proliferation of virus-specific CD8(+) T cells. - Malcherek, G.; Jin, N.; Huckelhoven, A. G.; Mani, J.; Wang, L.; Gern, U.; Diehlmann, A.; Wuchter, P.; Schmitt, A.; Chen, B.; Ho, A. D.; Schmitt, M. (Leukemia, 2014)
Mesenchymal stromal cells (MSCs) possess broad immunomodulatory capacities that are currently investigated for potential clinical application in treating autoimmune disorders. Third-party MSCs suppress alloantigen-induced proliferation of peripheral blood mononuclear cells providing the rationale for clinical use in graft-versus-host disease (GvHD). We confirmed that MSCs strongly inhibited proliferation of CD8(+) T cells in a mixed lymphocyte reaction. However, MSCs also suppressed proliferation of T cells specifically recognizing cytomegalovirus (CMV) and influenza virus. Inhibition was dose dependent, but independent of the culture medium. MSCs inhibited proliferation of specific CD8(+) T cells and the release of IFN-gamma by specific CD8(+) T cells for immunodominant HLA-A2- and HLA-B7- restricted antigen epitopes derived from CMV phosphoprotein 65 and influenza matrix protein. This is in contrast to a recently reported scenario where MSCs exert differential effects on alloantigen and virus-specific T cells potentially having an impact on surveillance and prophylaxis of patients treated by MSCs.
Keywords: CD8-Positive T-Lymphocytes/*immunology/*metabolism; Epitopes, T-Lymphocyte/immunology; Humans; Immunodominant Epitopes/immunology; Interferon-gamma/biosynthesis; Isoantigens/immunology; Lymphocyte Activation/immunology; Mesenchymal Stem Cells/*metabolism; Phosphoproteins/immunology; T-Cell Antigen Receptor Specificity/*immunology; Viral Matrix Proteins/immunology; Viruses/*immunology

Standardization of Good Manufacturing Practice-compliant production of bone marrow-derived human mesenchymal stromal cells for immunotherapeutic applications. - Wuchter, P.; Bieback, K.; Schrezenmeier, H.; Bornhauser, M.; Muller, L. P.; Bonig, H.; Wagner, W.; Meisel, R.; Pavel, P.; Tonn, T.; Lang, P.; Muller, I.; et al. (Cytotherapy, 2015)
BACKGROUND AIMS: Human mesenchymal stem or stromal cells (MSCs) represent a potential resource not only for regenerative medicine but also for immunomodulatory cell therapies. The application of different MSC culture protocols has significantly hampered the comparability of experimental and clinical data from different laboratories and has posed a major obstacle for multicenter clinical trials. Manufacturing of cell products for clinical application in the European Community must be conducted in compliance with Good Manufacturing Practice and requires a manufacturing license. In Germany, the Paul-Ehrlich-Institut as the Federal Authority for Vaccines and Biomedicines is critically involved in the approval process. METHODS: This report summarizes a consensus meeting between researchers, clinicians and regulatory experts on standard quality requirements for MSC production. RESULTS: The strategy for quality control testing depends on the product's cell composition, the manufacturing process and the indication and target patient population. Important quality criteria in this sense are, among others, the immunophenotype of the cells, composition of the culture medium and the risk for malignant transformation, as well as aging and the immunosuppressive potential of the manufactured MSCs. CONCLUSIONS: This position paper intends to provide relevant information to interested parties regarding these criteria to foster the development of scientifically valid and harmonized quality standards and to support approval of MSC-based investigational medicinal products.
Keywords: Bone Marrow; Cell Culture Techniques/standards; Culture Media; Germany; *Guideline Adherence; Humans; Immunophenotyping; Immunotherapy, Adoptive/*methods; Mesenchymal Stem Cell Transplantation/methods; Mesenchymal Stem Cells/*cytology; Quality Control; Regenerative Medicine/methods

Differences between healthy hematopoietic progenitors and leukemia cells with respect to CD44 mediated rolling versus adherence behavior on hyaluronic acid coated surfaces. - Hanke, M.; Hoffmann, I.; Christophis, C.; Schubert, M.; Hoang, V. T.; Zepeda-Moreno, A.; Baran, N.; Eckstein, V.; Wuchter, P.; Rosenhahn, A.; Ho, A. D. (Biomaterials, 2014)
We previously demonstrated that leukemia cell lines expressing CD44 and hematopoietic progenitor cells (HPC) from umbilical cord blood (CB) showed rolling on hyaluronic acid (HA)-coated surfaces under physiological shear stress. In the present study, we quantitatively assessed the interaction of HPC derived from CB, mobilized peripheral blood (mPB) and bone marrow (BM) from healthy donors, as well as primary leukemia blasts from PB and BM of patients with acute myeloid leukemia (AML) with HA. We have demonstrated that HPC derived from healthy donors showed relative homogeneous rolling and adhesion to HA. In contrast, highly diverse behavioral patterns were found for leukemia blasts under identical conditions. The monoclonal CD44 antibody (clone BU52) abrogated the shear stress-induced rolling of HPC and leukemia blasts, confirming the significance of CD44 in this context. On the other hand, the immobile adhesion of leukemia blasts to the HA-coated surface was, in some cases, not or incompletely inhibited by BU52. The latter property was associated with non-responsiveness to induction chemotherapy and subsequently poor clinical outcome.
Keywords: Antibodies, Monoclonal/immunology; Case-Control Studies; *Cell Adhesion; Cell Line, Tumor; Flow Cytometry; Hematopoietic Stem Cells/*cytology/immunology; Humans; Hyaluronan Receptors/*immunology; Hyaluronic Acid/*metabolism; Leukemia/*pathology; Leukocyte Rolling; Microfluidics; Surface Properties

Functional potentials of human hematopoietic progenitor cells are maintained by mesenchymal stromal cells and not impaired by plerixafor. - Ludwig, A.; Saffrich, R.; Eckstein, V.; Bruckner, T.; Wagner, W.; Ho, A. D.; Wuchter, P. (Cytotherapy, 2014)
BACKGROUND AIMS: Mesenchymal stromal cells (MSCs) resemble an essential component of the bone marrow niche for maintenance of stemness of hematopoietic progenitor cells (HPCs). Perturbation of the C-X-C chemokine receptor type 4 (CXCR4)/stromal cell-derived factor-1alpha (SDF-1alpha) axis by plerixafor (AMD3100) mobilizes HPCs from their niche; however, little is known about how plerixafor affects interaction of HPCs and MSCs in vitro. METHODS: We monitored cell division kinetics, surface expression of CD34 and CXCR4, migration behavior and colony-forming frequency of HPCs on co-culture with MSCs either with or without exposure to plerixafor. RESULTS: Co-culture with MSCs significantly accelerated cell division kinetics of HPCs. Despite this, the proportion of CD34(+) cells was significantly increased on co-culture, whereas the expression of CXCR4 was reduced. In addition, co-culture with MSCs led to significantly higher colony-forming capacity and enhanced migration rate of HPCs compared with mono-culture conditions. The composition of MSC sub-populations-and conversely their hematopoiesis supportive functions-may be influenced by culture conditions. We compared the stromal function of MSCs isolated with three different culture media. Overall, the supporting potentials of these MSC preparations were quite similar. Perturbation by the CXCR4-antagonist plerixafor reduced the cell division kinetics of HPCs on co-culture with MSCs. However, the progenitor cell potential of the HPCs as reflected by colony-forming capacity was not affected by plerixafor. CONCLUSIONS: These results support the notion that the CXCR4/SDF-1alpha axis is critical for HPC-MSC interaction with regard to migration, adhesion and regulation of proliferation but not for maintenance of primitive progenitor cells.
Keywords: Antigens, CD34/biosynthesis; Benzylamines; Bone Marrow Cells/cytology/drug effects; Cell Adhesion/drug effects; Cell Movement/drug effects; Chemokine CXCL12/biosynthesis; Cyclams; Gene Expression Regulation/drug effects; Hematopoiesis/drug effects; Hematopoietic Stem Cells/*cytology/drug effects; Heterocyclic Compounds/*administration & dosage; Humans; Mesenchymal Stem Cells/cytology/*drug effects; Receptors, CXCR4/antagonists & inhibitors/biosynthesis

[Mesenchymal stroma cells (MSCs) for the treatment of rheumatic disease]. - Schmitt, M.; Muller, L. P.; Keysser, G.; Lorenz, H. M.; Ho, A. D.; Wuchter, P. (Dtsch Med Wochenschr, 2013)
Keywords: Evidence-Based Medicine; Humans; Mesenchymal Stem Cell Transplantation/*methods/*trends; Rheumatic Diseases/*diagnosis/*surgery; Stromal Cells/transplantation; Treatment Outcome

Covering a broad dynamic range: information processing at the erythropoietin receptor. - Becker, V.; Schilling, M.; Bachmann, J.; Baumann, U.; Raue, A.; Maiwald, T.; Timmer, J.; Klingmuller, U. (Science, 2010)
Cell surface receptors convert extracellular cues into receptor activation, thereby triggering intracellular signaling networks and controlling cellular decisions. A major unresolved issue is the identification of receptor properties that critically determine processing of ligand-encoded information. We show by mathematical modeling of quantitative data and experimental validation that rapid ligand depletion and replenishment of the cell surface receptor are characteristic features of the erythropoietin (Epo) receptor (EpoR). The amount of Epo-EpoR complexes and EpoR activation integrated over time corresponds linearly to ligand input; this process is carried out over a broad range of ligand concentrations. This relation depends solely on EpoR turnover independent of ligand binding, which suggests an essential role of large intracellular receptor pools. These receptor properties enable the system to cope with basal and acute demand in the hematopoietic system.
Keywords: Animals; Cell Line; Cell Membrane/*metabolism; Computer Simulation; Endocytosis; Epoetin Alfa; Erythropoietin/metabolism/pharmacology; Kinetics; Ligands; Mice; Models, Biological; Protein Binding; Receptors, Erythropoietin/*metabolism; Recombinant Proteins; Signal Transduction

A systems biology approach reveals major metabolic changes in the thermoacidophilic archaeon Sulfolobus solfataricus in response to the carbon source L-fucose versus D-glucose. - Wolf, J.; Stark, H.; Fafenrot, K.; Albersmeier, A.; Pham, T. K.; Muller, K. B.; Meyer, B. H.; Hoffmann, L.; Shen, L.; Albaum, S. P.; Kouril, T.; Schmidt-Hohagen, K.; et al. (Mol Microbiol, 2016)
Archaea are characterised by a complex metabolism with many unique enzymes that differ from their bacterial and eukaryotic counterparts. The thermoacidophilic archaeon Sulfolobus solfataricus is known for its metabolic versatility and is able to utilize a great variety of different carbon sources. However, the underlying degradation pathways and their regulation are often unknown. In this work, the growth on different carbon sources was analysed, using an integrated systems biology approach. The comparison of growth on L-fucose and D-glucose allows first insights into the genome-wide changes in response to the two carbon sources and revealed a new pathway for L-fucose degradation in S. solfataricus. During growth on L-fucose major changes in the central carbon metabolic network, as well as an increased activity of the glyoxylate bypass and the 3-hydroxypropionate/4-hydroxybutyrate cycle were observed. Within the newly discovered pathway for L-fucose degradation the following key reactions were identified: (i) L-fucose oxidation to L-fuconate via a dehydrogenase, (ii) dehydration to 2-keto-3-deoxy-L-fuconate via dehydratase, (iii) 2-keto-3-deoxy-L-fuconate cleavage to pyruvate and L-lactaldehyde via aldolase and (iv) L-lactaldehyde conversion to L-lactate via aldehyde dehydrogenase. This pathway as well as L-fucose transport shows interesting overlaps to the D-arabinose pathway, representing another example for pathway promiscuity in Sulfolobus species.
Keywords: Amino Acid Sequence; Carbon/metabolism; Fucose/*metabolism; Glucose/*metabolism; Hydro-Lyases/metabolism; Metabolic Networks and Pathways; Metabolomics/methods; Proteome; Pyruvic Acid/metabolism; Sulfolobus solfataricus/genetics/*metabolism; Systems Biology/methods; Transcriptome

Computational processing and error reduction strategies for standardized quantitative data in biological networks. - Schilling, M.; Maiwald, T.; Bohl, S.; Kollmann, M.; Kreutz, C.; Timmer, J.; Klingmuller, U. (FEBS J, 2005)
High-quality quantitative data generated under standardized conditions is critical for understanding dynamic cellular processes. We report strategies for error reduction, and algorithms for automated data processing and for establishing the widely used techniques of immunoprecipitation and immunoblotting as highly precise methods for the quantification of protein levels and modifications. To determine the stoichiometry of cellular components and to ensure comparability of experiments, relative signals are converted to absolute values. A major source for errors in blotting techniques are inhomogeneities of the gel and the transfer procedure leading to correlated errors. These correlations are prevented by randomized gel loading, which significantly reduces standard deviations. Further error reduction is achieved by using housekeeping proteins as normalizers or by adding purified proteins in immunoprecipitations as calibrators in combination with criteria-based normalization. Additionally, we developed a computational tool for automated normalization, validation and integration of data derived from multiple immunoblots. In this way, large sets of quantitative data for dynamic pathway modeling can be generated, enabling the identification of systems properties and the prediction of targets for efficient intervention.
Keywords: Algorithms; Computational Biology/methods/*standards; Electronic Data Processing; Immunoblotting; Immunologic Techniques; Immunoprecipitation; Proteins/analysis; Reference Standards

Excemplify: a flexible template based solution, parsing and managing data in spreadsheets for experimentalists. - Shi, L.; Jong, L.; Wittig, U.; Lucarelli, P.; Stepath, M.; Mueller, S.; D'Alessandro, L. A.; Klingmuller, U.; Muller, W. (J Integr Bioinform, 2013)
In systems biology, quantitative experimental data is the basis of building mathematical models. In most of the cases, they are stored in Excel files and hosted locally. To have a public database for collecting, retrieving and citing experimental raw data as well as experimental conditions is important for both experimentalists and modelers. However, the great effort needed in the data handling procedure and in the data submission procedure becomes the crucial limitation for experimentalists to contribute to a database, thereby impeding the database to deliver its benefit. Moreover, manual copy and paste operations which are commonly used in those procedures increase the chance of making mistakes. Excemplify, a web-based application, proposes a flexible and adaptable template-based solution to solve these problems. Comparing to the normal template based uploading approach, which is supported by some public databases, rather than predefining a format that is potentiall impractical, Excemplify allows users to create their own experiment-specific content templates in different experiment stages and to build corresponding knowledge bases for parsing. Utilizing the embedded knowledge of used templates, Excemplify is able to parse experimental data from the initial setup stage and generate following stages spreadsheets automatically. The proposed solution standardizes the flows of data traveling according to the standard procedures of applying the experiment, cuts down the amount of manual effort and reduces the chance of mistakes caused by manual data handling. In addition, it maintains the context of meta-data from the initial preparation manuscript and improves the data consistency. It interoperates and complements RightField and SEEK as well.
Keywords: Animals; *Database Management Systems; Knowledge Management; Mice; *Software; *Systems Biology

Hedgehog signaling is a potent regulator of liver lipid metabolism and reveals a GLI-code associated with steatosis - Matz-Soja, Madlen; Rennert, Christiane; Schönefeld, Kristin; Aleithe, Susanne; Boettger, Jan; Schmidt-Heck, Wolfgang; Weiss, Thomas S; Hovhannisyan, Amalya; Zellmer, Sebastian; Klöting, Nora; Schulz, Angela; Kratzsch, Jürgen; et al. (2016)
Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease in industrialized countries and is increasing in prevalence. The pathomechanisms, however, are poorly understood. This study assessed the unexpected role of the Hedgehog pathway in adult liver lipid metabolism. Using transgenic mice with conditional hepatocyte-specific deletion of Smoothened in adult mice, we showed that hepatocellular inhibition of Hedgehog signaling leads to steatosis by altering the abundance of the transcription factors GLI1 and GLI3. This steatotic 'Gli-code' caused the modulation of a complex network of lipogenic transcription factors and enzymes, including SREBP1 and PNPLA3, as demonstrated by microarray analysis and siRNA experiments and could be confirmed in other steatotic mouse models as well as in steatotic human livers. Conversely, activation of the Hedgehog pathway reversed the "Gli-code" and mitigated hepatic steatosis. Collectively, our results reveal that dysfunctions in the Hedgehog pathway play an important role in hepatic steatosis and beyond.

Cause and cure of sloppiness in ordinary differential equation models - Tönsing, Christian; Timmer, Jens; Kreutz, Clemens (Phys. Rev. E, 2014)
Data-based mathematical modeling of biochemical reaction networks, e.g., by nonlinear ordinary differential equation (ODE) models, has been successfully applied. In this context, parameter estimation and uncertainty analysis is a major task in order to assess the quality of the description of the system by the model. Recently, a broadened eigenvalue spectrum of the Hessian matrix of the objective function covering orders of magnitudes was observed and has been termed as sloppiness. In this work, we investigate the origin of sloppiness from structures in the sensitivity matrix arising from the properties of the model topology and the experimental design. Furthermore, we present strategies using optimal experimental design methods in order to circumvent the sloppiness issue and present nonsloppy designs for a benchmark model.

Engineering Streptomyces coelicolor for heterologous expression of secondary metabolite gene clusters - Gomez-Escribano, Juan Pablo; Bibb, Mervyn J. (2011)
We have constructed derivatives of Streptomyces coelicolor M145 as hosts for the heterologous expression of secondary metabolite gene clusters. To remove potentially competitive sinks of carbon and nitrogen, and to provide a host devoid of antibiotic activity, we deleted four endogenous secondary metabolite gene clusters from S. coelicolor M145--those for actinorhodin, prodiginine, CPK and CDA biosynthesis. We then introduced point mutations into rpoB and rpsL to pleiotropically increase the level of secondary metabolite production. Introduction of the native actinorhodin gene cluster and of gene clusters for the heterologous production of chloramphenicol and congocidine revealed dramatic increases in antibiotic production compared with the parental strain. In addition to lacking antibacterial activity, the engineered strains possess relatively simple extracellular metabolite profiles. When combined with liquid chromatography and mass spectrometry, we believe that these genetically engineered strains will markedly facilitate the discovery of new compounds by heterologous expression of cloned gene clusters, particularly the numerous cryptic secondary metabolic gene clusters that are prevalent within actinomycete genome sequences.

The FAIR Guiding Principles for scientific data management and stewardship. - Wilkinson, M. D.; Dumontier, M.; Aalbersberg, I. J.; Appleton, G.; Axton, M.; Baak, A.; Blomberg, N.; Boiten, J. W.; da Silva Santos, L. B.; Bourne, P. E.; Bouwman, J.; Brookes, A. J.; et al. (Sci Data, 2016)
There is an urgent need to improve the infrastructure supporting the reuse of scholarly data. A diverse set of stakeholders-representing academia, industry, funding agencies, and scholarly publishers-have come together to design and jointly endorse a concise and measureable set of principles that we refer to as the FAIR Data Principles. The intent is that these may act as a guideline for those wishing to enhance the reusability of their data holdings. Distinct from peer initiatives that focus on the human scholar, the FAIR Principles put specific emphasis on enhancing the ability of machines to automatically find and use the data, in addition to supporting its reuse by individuals. This Comment is the first formal publication of the FAIR Principles, and includes the rationale behind them, and some exemplar implementations in the community.
Keywords: *Data Collection; *Data Curation; Database Management Systems; Guidelines as Topic; Reproducibility of Results; *Research Design

A technical platform for generating reproducible expression data from Streptomyces coelicolor batch cultivations. - Battke, F.; Herbig, A.; Wentzel, A.; Jakobsen, O. M.; Bonin, M.; Hodgson, D. A.; Wohlleben, W.; Ellingsen, T. E.; Nieselt, K. (Adv Exp Med Biol, 2011)
Streptomyces coelicolor, the model species of the genus Streptomyces, presents a complex life cycle of successive morphological and biochemical changes involving the formation of substrate and aerial mycelium, sporulation and the production of antibiotics. The switch from primary to secondary metabolism can be triggered by nutrient starvation and is of particular interest as some of the secondary metabolites produced by related Streptomycetes are commercially relevant. To understand these events on a molecular basis, a reliable technical platform encompassing reproducible fermentation as well as generation of coherent transcriptomic data is required. Here, we investigate the technical basis of a previous study as reported by Nieselt et al. (BMC Genomics 11:10, 2010) in more detail, based on the same samples and focusing on the validation of the custom-designed microarray as well as on the reproducibility of the data generated from biological replicates. We show that the protocols developed result in highly coherent transcriptomic measurements. Furthermore, we use the data to predict chromosomal gene clusters, extending previously known clusters as well as predicting interesting new clusters with consistent functional annotations.
Keywords: Bacteriological Techniques; Fermentation; Gene Expression Profiling/*statistics & numerical data; Genes, Bacterial; Multigene Family; Oligonucleotide Array Sequence Analysis/*statistics & numerical data; Reproducibility of Results; Software; Streptomyces coelicolor/*genetics/growth & development/*metabolism

Extracting regulator activity profiles by integration of de novo motifs and expression data: characterizing key regulators of nutrient depletion responses in Streptomyces coelicolor. - Iqbal, M.; Mast, Y.; Amin, R.; Hodgson, D. A.; Wohlleben, W.; Burroughs, N. J. (Nucleic Acids Res, 2012)
Determining transcriptional regulator activities is a major focus of systems biology, providing key insight into regulatory mechanisms and co-regulators. For organisms such as Escherichia coli, transcriptional regulator binding site data can be integrated with expression data to infer transcriptional regulator activities. However, for most organisms there is only sparse data on their transcriptional regulators, while their associated binding motifs are largely unknown. Here, we address the challenge of inferring activities of unknown regulators by generating de novo (binding) motifs and integrating with expression data. We identify a number of key regulators active in the metabolic switch, including PhoP with its associated directed repeat PHO box, candidate motifs for two SARPs, a CRP family regulator, an iron response regulator and that for LexA. Experimental validation for some of our predictions was obtained using gel-shift assays. Our analysis is applicable to any organism for which there is a reasonable amount of complementary expression data and for which motifs (either over represented or evolutionary conserved) can be identified in the genome.
Keywords: Bacterial Proteins/metabolism; Binding Sites; Gene Expression Profiling; Gene Regulatory Networks; Genomics/methods; Glutamic Acid/metabolism; Nucleotide Motifs; Phosphates/metabolism; Streptomyces coelicolor/*genetics/metabolism; Transcription Factors/*metabolism; *Transcriptome

Metabolic switches and adaptations deduced from the proteomes of Streptomyces coelicolor wild type and phoP mutant grown in batch culture. - Thomas, L.; Hodgson, D. A.; Wentzel, A.; Nieselt, K.; Ellingsen, T. E.; Moore, J.; Morrissey, E. R.; Legaie, R.; Wohlleben, W.; Rodriguez-Garcia, A.; Martin, J. F.; Burroughs, N. J.; et al. (Mol Cell Proteomics, 2012)
Bacteria in the genus Streptomyces are soil-dwelling oligotrophs and important producers of secondary metabolites. Previously, we showed that global messenger RNA expression was subject to a series of metabolic and regulatory switches during the lifetime of a fermentor batch culture of Streptomyces coelicolor M145. Here we analyze the proteome from eight time points from the same fermentor culture and, because phosphate availability is an important regulator of secondary metabolite production, compare this to the proteome of a similar time course from an S. coelicolor mutant, INB201 (DeltaphoP), defective in the control of phosphate utilization. The proteomes provide a detailed view of enzymes involved in central carbon and nitrogen metabolism. Trends in protein expression over the time courses were deduced from a protein abundance index, which also revealed the importance of stress pathway proteins in both cultures. As expected, the DeltaphoP mutant was deficient in expression of PhoP-dependent genes, and several putatively compensatory metabolic and regulatory pathways for phosphate scavenging were detected. Notably there is a succession of switches that coordinately induce the production of enzymes for five different secondary metabolite biosynthesis pathways over the course of the batch cultures.
Keywords: *Acclimatization; Bacterial Proteins/*genetics/*metabolism; Batch Cell Culture Techniques; Biomarkers/metabolism; Cells, Cultured; Chromatography, Liquid; Gene Expression Profiling; Gene Expression Regulation, Bacterial; Mutation/*genetics; Oligonucleotide Array Sequence Analysis; Phosphates/*metabolism; Proteome/analysis; Proteomics; RNA, Bacterial/genetics; RNA, Messenger/genetics; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Streptomyces coelicolor/growth & development/*metabolism

The PII protein GlnK is a pleiotropic regulator for morphological differentiation and secondary metabolism in Streptomyces coelicolor. - Waldvogel, E.; Herbig, A.; Battke, F.; Amin, R.; Nentwich, M.; Nieselt, K.; Ellingsen, T. E.; Wentzel, A.; Hodgson, D. A.; Wohlleben, W.; Mast, Y. (Appl Microbiol Biotechnol, 2011)
GlnK is an important nitrogen sensor protein in Streptomyces coelicolor. Deletion of glnK results in a medium-dependent failure of aerial mycelium and spore formation and loss of antibiotic production. Thus, GlnK is not only a regulator of nitrogen metabolism but also of morphological differentiation and secondary metabolite production. Through a comparative transcriptomic approach between the S. coelicolor wild-type and a S. coelicolor glnK mutant strain, 142 genes were identified that are differentially regulated in both strains. Among these are genes of the ram and rag operon, which are involved in S. coelicolor morphogenesis, as well as genes involved in gas vesicle biosynthesis and ectoine biosynthesis. Surprisingly, no relevant nitrogen genes were found to be differentially regulated, revealing that GlnK is not an important nitrogen sensor under the tested conditions.
Keywords: Bacterial Proteins/genetics/*metabolism; *Gene Expression Regulation, Bacterial; *Genes, Regulator; Molecular Sequence Data; Nitrogen/metabolism; Operon; PII Nitrogen Regulatory Proteins/genetics/*metabolism; Streptomyces coelicolor/genetics/*growth & development/*metabolism

Optimized submerged batch fermentation strategy for systems scale studies of metabolic switching in Streptomyces coelicolor A3(2). - Wentzel, A.; Bruheim, P.; Overby, A.; Jakobsen, O. M.; Sletta, H.; Omara, W. A.; Hodgson, D. A.; Ellingsen, T. E. (BMC Syst Biol, 2012)
BACKGROUND: Systems biology approaches to study metabolic switching in Streptomyces coelicolor A3(2) depend on cultivation conditions ensuring high reproducibility and distinct phases of culture growth and secondary metabolite production. In addition, biomass concentrations must be sufficiently high to allow for extensive time-series sampling before occurrence of a given nutrient depletion for transition triggering. The present study describes for the first time the development of a dedicated optimized submerged batch fermentation strategy as the basis for highly time-resolved systems biology studies of metabolic switching in S. coelicolor A3(2). RESULTS: By a step-wise approach, cultivation conditions and two fully defined cultivation media were developed and evaluated using strain M145 of S. coelicolor A3(2), providing a high degree of cultivation reproducibility and enabling reliable studies of the effect of phosphate depletion and L-glutamate depletion on the metabolic transition to antibiotic production phase. Interestingly, both of the two carbon sources provided, D-glucose and L-glutamate, were found to be necessary in order to maintain high growth rates and prevent secondary metabolite production before nutrient depletion. Comparative analysis of batch cultivations with (i) both L-glutamate and D-glucose in excess, (ii) L-glutamate depletion and D-glucose in excess, (iii) L-glutamate as the sole source of carbon and (iv) D-glucose as the sole source of carbon, reveal a complex interplay of the two carbon sources in the bacterium's central carbon metabolism. CONCLUSIONS: The present study presents for the first time a dedicated cultivation strategy fulfilling the requirements for systems biology studies of metabolic switching in S. coelicolor A3(2). Key results from labelling and cultivation experiments on either or both of the two carbon sources provided indicate that in the presence of D-glucose, L-glutamate was the preferred carbon source, while D-glucose alone appeared incapable of maintaining culture growth, likely due to a metabolic bottleneck at the oxidation of pyruvate to acetyl-CoA.
Keywords: Anti-Bacterial Agents/biosynthesis; Biomass; Carbon/metabolism; Culture Media/chemistry; *Fermentation; Glucose/metabolism; Glutamic Acid/metabolism; *Immersion; Oxygen/metabolism; Streptomyces coelicolor/growth & development/*metabolism; Systems Biology/*methods; Trace Elements/metabolism

Intracellular Metabolite Pool Changes in Response to Nutrient Depletion Induced Metabolic Switching in Streptomyces coelicolor. - Wentzel, A.; Sletta, H.; Ellingsen, T. E.; Bruheim, P. (Metabolites, 2012)
A metabolite profiling study of the antibiotic producing bacterium Streptomyces coelicolor A3(2) has been performed. The aim of this study was to monitor intracellular metabolite pool changes occurring as strains of S. coelicolor react to nutrient depletion with metabolic re-modeling, so-called metabolic switching, and transition from growth to secondary metabolite production phase. Two different culture media were applied, providing depletion of the key nutrients phosphate and L-glutamate, respectively, as the triggers for metabolic switching. Targeted GC-MS and LC-MS methods were employed to quantify important primary metabolite groups like amino acids, organic acids, sugar phosphates and other phosphorylated metabolites, and nucleotides in time-course samples withdrawn from fully-controlled batch fermentations. A general decline, starting already in the early growth phase, was observed for nucleotide pools and phosphorylated metabolite pools for both the phosphate and glutamate limited cultures. The change in amino acid and organic acid pools were more scattered, especially in the phosphate limited situation while a general decrease in amino acid and non-amino organic acid pools was observed in the L-glutamate limited situation. A phoP deletion mutant showed basically the same metabolite pool changes as the wild-type strain M145 when cultivated on phosphate limited medium. This implies that the inactivation of the phoP gene has only little effect on the detected metabolite levels in the cell. The energy charge was found to be relatively constant during growth, transition and secondary metabolite production phase. The results of this study and the employed targeted metabolite profiling methodology are directly relevant for the evaluation of precursor metabolite and energy supply for both natural and heterologous production of secondary metabolites in S. coelicolor.

FAIRDOMHub: a repository and collaboration environment for sharing systems biology research. - Wolstencroft, K.; Krebs, O.; Snoep, J. L.; Stanford, N. J.; Bacall, F.; Golebiewski, M.; Kuzyakiv, R.; Nguyen, Q.; Owen, S.; Soiland-Reyes, S.; Straszewski, J.; van Niekerk, D. D.; et al. (Nucleic Acids Res, 2017)
The FAIRDOMHub is a repository for publishing FAIR (Findable, Accessible, Interoperable and Reusable) Data, Operating procedures and Models (https://fairdomhub.org/) for the Systems Biology community. It is a web-accessible repository for storing and sharing systems biology research assets. It enables researchers to organize, share and publish data, models and protocols, interlink them in the context of the systems biology investigations that produced them, and to interrogate them via API interfaces. By using the FAIRDOMHub, researchers can achieve more effective exchange with geographically distributed collaborators during projects, ensure results are sustained and preserved and generate reproducible publications that adhere to the FAIR guiding principles of data stewardship.
Keywords: Carbon/metabolism; Data Curation; *Databases, Factual; Information Dissemination; Metabolic Networks and Pathways; Research; Systems Biology/*methods

Identification of Cell Type-Specific Differences in Erythropoietin Receptor Signaling in Primary Erythroid and Lung Cancer Cells. - Merkle, R.; Steiert, B.; Salopiata, F.; Depner, S.; Raue, A.; Iwamoto, N.; Schelker, M.; Hass, H.; Wasch, M.; Bohm, M. E.; Mucke, O.; Lipka, D. B.; et al. (PLoS Comput Biol, 2016)
Lung cancer, with its most prevalent form non-small-cell lung carcinoma (NSCLC), is one of the leading causes of cancer-related deaths worldwide, and is commonly treated with chemotherapeutic drugs such as cisplatin. Lung cancer patients frequently suffer from chemotherapy-induced anemia, which can be treated with erythropoietin (EPO). However, studies have indicated that EPO not only promotes erythropoiesis in hematopoietic cells, but may also enhance survival of NSCLC cells. Here, we verified that the NSCLC cell line H838 expresses functional erythropoietin receptors (EPOR) and that treatment with EPO reduces cisplatin-induced apoptosis. To pinpoint differences in EPO-induced survival signaling in erythroid progenitor cells (CFU-E, colony forming unit-erythroid) and H838 cells, we combined mathematical modeling with a method for feature selection, the L1 regularization. Utilizing an example model and simulated data, we demonstrated that this approach enables the accurate identification and quantification of cell type-specific parameters. We applied our strategy to quantitative time-resolved data of EPO-induced JAK/STAT signaling generated by quantitative immunoblotting, mass spectrometry and quantitative real-time PCR (qRT-PCR) in CFU-E and H838 cells as well as H838 cells overexpressing human EPOR (H838-HA-hEPOR). The established parsimonious mathematical model was able to simultaneously describe the data sets of CFU-E, H838 and H838-HA-hEPOR cells. Seven cell type-specific parameters were identified that included for example parameters for nuclear translocation of STAT5 and target gene induction. Cell type-specific differences in target gene induction were experimentally validated by qRT-PCR experiments. The systematic identification of pathway differences and sensitivities of EPOR signaling in CFU-E and H838 cells revealed potential targets for intervention to selectively inhibit EPO-induced signaling in the tumor cells but leave the responses in erythroid progenitor cells unaffected. Thus, the proposed modeling strategy can be employed as a general procedure to identify cell type-specific parameters and to recommend treatment strategies for the selective targeting of specific cell types.
Keywords: Carcinoma, Non-Small-Cell Lung/genetics/*metabolism; Cell Line, Tumor; Computational Biology; Erythroid Cells/cytology/*metabolism; Humans; Lung Neoplasms/genetics/*metabolism; *Receptors, Erythropoietin/analysis/classification/genetics/metabolism; Signal Transduction/*physiology

The Human Physiome: how standards, software and innovative service infrastructures are providing the building blocks to make it achievable. - Nickerson, D.; Atalag, K.; de Bono, B.; Geiger, J.; Goble, C.; Hollmann, S.; Lonien, J.; Muller, W.; Regierer, B.; Stanford, N. J.; Golebiewski, M.; Hunter, P. (Interface Focus, 2016)
Reconstructing and understanding the Human Physiome virtually is a complex mathematical problem, and a highly demanding computational challenge. Mathematical models spanning from the molecular level through to whole populations of individuals must be integrated, then personalized. This requires interoperability with multiple disparate and geographically separated data sources, and myriad computational software tools. Extracting and producing knowledge from such sources, even when the databases and software are readily available, is a challenging task. Despite the difficulties, researchers must frequently perform these tasks so that available knowledge can be continually integrated into the common framework required to realize the Human Physiome. Software and infrastructures that support the communities that generate these, together with their underlying standards to format, describe and interlink the corresponding data and computer models, are pivotal to the Human Physiome being realized. They provide the foundations for integrating, exchanging and re-using data and models efficiently, and correctly, while also supporting the dissemination of growing knowledge in these forms. In this paper, we explore the standards, software tooling, repositories and infrastructures that support this work, and detail what makes them vital to realizing the Human Physiome.

L1 regularization facilitates detection of cell type-specific parameters in dynamical systems. - Steiert, B.; Timmer, J.; Kreutz, C. (Bioinformatics, 2016)
MOTIVATION: A major goal of drug development is to selectively target certain cell types. Cellular decisions influenced by drugs are often dependent on the dynamic processing of information. Selective responses can be achieved by differences between the involved cell types at levels of receptor, signaling, gene regulation or further downstream. Therefore, a systematic approach to detect and quantify cell type-specific parameters in dynamical systems becomes necessary. RESULTS: Here, we demonstrate that a combination of nonlinear modeling with L1 regularization is capable of detecting cell type-specific parameters. To adapt the least-squares numerical optimization routine to L1 regularization, sub-gradient strategies as well as truncation of proposed optimization steps were implemented. Likelihood-ratio tests were used to determine the optimal regularization strength resulting in a sparse solution in terms of a minimal number of cell type-specific parameters that is in agreement with the data. By applying our implementation to a realistic dynamical benchmark model of the DREAM6 challenge we were able to recover parameter differences with an accuracy of 78%. Within the subset of detected differences, 91% were in agreement with their true value. Furthermore, we found that the results could be improved using the profile likelihood. In conclusion, the approach constitutes a general method to infer an overarching model with a minimum number of individual parameters for the particular models. AVAILABILITY AND IMPLEMENTATION: A MATLAB implementation is provided within the freely available, open-source modeling environment Data2Dynamics. Source code for all examples is provided online at http://www.data2dynamics.org/ CONTACT: bernhard.steiert@fdm.uni-freiburg.de.
Keywords: Algorithms; Cells/*classification; *Drug Delivery Systems; Least-Squares Analysis; *Nonlinear Dynamics; Probability; Programming Languages; Signal Transduction

Driving the Model to Its Limit: Profile Likelihood Based Model Reduction. - Maiwald, T.; Hass, H.; Steiert, B.; Vanlier, J.; Engesser, R.; Raue, A.; Kipkeew, F.; Bock, H. H.; Kaschek, D.; Kreutz, C.; Timmer, J. (PLoS One, 2016)
In systems biology, one of the major tasks is to tailor model complexity to information content of the data. A useful model should describe the data and produce well-determined parameter estimates and predictions. Too small of a model will not be able to describe the data whereas a model which is too large tends to overfit measurement errors and does not provide precise predictions. Typically, the model is modified and tuned to fit the data, which often results in an oversized model. To restore the balance between model complexity and available measurements, either new data has to be gathered or the model has to be reduced. In this manuscript, we present a data-based method for reducing non-linear models. The profile likelihood is utilised to assess parameter identifiability and designate likely candidates for reduction. Parameter dependencies are analysed along profiles, providing context-dependent suggestions for the type of reduction. We discriminate four distinct scenarios, each associated with a specific model reduction strategy. Iterating the presented procedure eventually results in an identifiable model, which is capable of generating precise and testable predictions. Source code for all toy examples is provided within the freely available, open-source modelling environment Data2Dynamics based on MATLAB available at http://www.data2dynamics.org/, as well as the R packages dMod/cOde available at https://github.com/dkaschek/. Moreover, the concept is generally applicable and can readily be used with any software capable of calculating the profile likelihood.
Keywords: Algorithms; *Computer Simulation; *Models, Biological; Nonlinear Dynamics; *Software; Systems Biology/*methods

Protein abundance of AKT and ERK pathway components governs cell type-specific regulation of proliferation. - Adlung, L.; Kar, S.; Wagner, M. C.; She, B.; Chakraborty, S.; Bao, J.; Lattermann, S.; Boerries, M.; Busch, H.; Wuchter, P.; Ho, A. D.; Timmer, J.; et al. (Mol Syst Biol, 2017)
Signaling through the AKT and ERK pathways controls cell proliferation. However, the integrated regulation of this multistep process, involving signal processing, cell growth and cell cycle progression, is poorly understood. Here, we study different hematopoietic cell types, in which AKT and ERK signaling is triggered by erythropoietin (Epo). Although these cell types share the molecular network topology for pro-proliferative Epo signaling, they exhibit distinct proliferative responses. Iterating quantitative experiments and mathematical modeling, we identify two molecular sources for cell type-specific proliferation. First, cell type-specific protein abundance patterns cause differential signal flow along the AKT and ERK pathways. Second, downstream regulators of both pathways have differential effects on proliferation, suggesting that protein synthesis is rate-limiting for faster cycling cells while slower cell cycles are controlled at the G1-S progression. The integrated mathematical model of Epo-driven proliferation explains cell type-specific effects of targeted AKT and ERK inhibitors and faithfully predicts, based on the protein abundance, anti-proliferative effects of inhibitors in primary human erythroid progenitor cells. Our findings suggest that the effectiveness of targeted cancer therapy might become predictable from protein abundance.
Keywords: Animals; Apoptosis; Cell Cycle; Cell Proliferation; Cells, Cultured; Erythroid Cells/*cytology/metabolism; Erythropoietin/*metabolism; Humans; *MAP Kinase Signaling System; Mice; Models, Theoretical; Proto-Oncogene Proteins c-akt/*metabolism

Defining the robust behaviour of the plant clock gene circuit with absolute RNA timeseries and open infrastructure. - Flis, A.; Fernandez, A. P.; Zielinski, T.; Mengin, V.; Sulpice, R.; Stratford, K.; Hume, A.; Pokhilko, A.; Southern, M. M.; Seaton, D. D.; McWatters, H. G.; Stitt, M.; et al. (Open Biol, 2015)
Our understanding of the complex, transcriptional feedback loops in the circadian clock mechanism has depended upon quantitative, timeseries data from disparate sources. We measure clock gene RNA profiles in Arabidopsis thaliana seedlings, grown with or without exogenous sucrose, or in soil-grown plants and in wild-type and mutant backgrounds. The RNA profiles were strikingly robust across the experimental conditions, so current mathematical models are likely to be broadly applicable in leaf tissue. In addition to providing reference data, unexpected behaviours included co-expression of PRR9 and ELF4, and regulation of PRR5 by GI. Absolute RNA quantification revealed low levels of PRR9 transcripts (peak approx. 50 copies cell(-1)) compared with other clock genes, and threefold higher levels of LHY RNA (more than 1500 copies cell(-1)) than of its close relative CCA1. The data are disseminated from BioDare, an online repository for focused timeseries data, which is expected to benefit mechanistic modelling. One data subset successfully constrained clock gene expression in a complex model, using publicly available software on parallel computers, without expert tuning or programming. We outline the empirical and mathematical justification for data aggregation in understanding highly interconnected, dynamic networks such as the clock, and the observed design constraints on the resources required to make this approach widely accessible.
Keywords: Arabidopsis/genetics/metabolism/*physiology; Arabidopsis Proteins/biosynthesis/genetics/metabolism; Biological Clocks/genetics; CLOCK Proteins/*genetics; Circadian Rhythm/genetics; DNA-Binding Proteins/genetics; Databases, Genetic; Feedback, Physiological; Gene Expression Profiling; Gene Expression Regulation, Plant/genetics; Gene Regulatory Networks/genetics; RNA, Messenger/genetics; Sucrose/metabolism; Transcription Factors/biosynthesis/genetics/metabolism

The circadian clock regulates the photoperiodic response of hypocotyl elongation through a coincidence mechanism in Arabidopsis thaliana. - Niwa, Y.; Yamashino, T.; Mizuno, T. (Plant Cell Physiol, 2009)
The plant circadian clock generates rhythms with a period close to 24 h, and it controls a wide range of physiological and developmental oscillations in habitats under natural light/dark cycles. Among clock-controlled developmental events, the best characterized is the photoperiodic control of flowering time in Arabidopsis thaliana. Recently, it was also reported that the clock regulates a daily and rhythmic elongation of hypocotyls. Here, we report that the promotion of hypocotyl elongation is in fact dependent on changes in photoperiods in such a way that an accelerated hypocotyl elongation occurs especially under short-day conditions. In this regard, we provide genetic evidence to show that the circadian clock regulates the photoperiodic (or seasonal) elongation of hypocotyls by modulating the expression profiles of the PIF4 and PIF5 genes encoding phytochrome-interacting bHLH (basic helix-loop-helix) factors, in such a manner that certain short-day conditions are necessary to enhance the expression of these genes during the night-time. In other words, long-day conditions are insufficient to open the clock-gate for triggering the expression of PIF4 and PIF5 during the night-time. Based on these and other results, the photoperiodic control of hypocotyl elongation is best explained by the accumulation of PIF4 and PIF5 during the night-time of short days, due to coincidence between the internal (circadian rhythm) and external (photoperiod) time cues. This mechanism is a mirror image of the photoperiod-dependent promotion of flowering in that plants should experience long-day conditions to initiate flowering promptly. Both of these clock-mediated coincidence mechanisms may coordinately confer ecological fitness to plants growing in natural habitats with varied photoperiods.
Keywords: Arabidopsis/genetics/*growth & development/metabolism; Arabidopsis Proteins/genetics/metabolism; Basic Helix-Loop-Helix Transcription Factors/genetics/metabolism; *Circadian Rhythm; Gene Expression Regulation, Plant; Hypocotyl/genetics/*growth & development; *Photoperiod; Plants, Genetically Modified/genetics/growth & development/metabolism; RNA, Plant/genetics

Arabidopsis clock-associated pseudo-response regulators PRR9, PRR7 and PRR5 coordinately and positively regulate flowering time through the canonical CONSTANS-dependent photoperiodic pathway. - Nakamichi, N.; Kita, M.; Niinuma, K.; Ito, S.; Yamashino, T.; Mizoguchi, T.; Mizuno, T. (Plant Cell Physiol, 2007)
Photoperiodism allows organisms to measure daylength, or external photoperiod, and to anticipate coming seasons. Daylength measurement requires the integration of light signal and temporal information by the circadian clock. In the long-day plant Arabidopsis thaliana, CONSTANS (CO) plays a crucial role in integrating the circadian rhythm and environmental light signals into the photoperiodic flowering pathway. Nevertheless, the molecular mechanism by which the circadian clock modulates the cyclic expression profile of CO is poorly understood. Here, we first showed that the clock-associated genes PSEUDO-RESPONSE REGULATOR (PRR) PRR9, PRR7 and PRR5 are involved in activation of CO expression during the daytime. Then, extensive genetic studies using CIRCADIAN CLOCK-ASSOCIATED1 (CCA1)/LATE ELONGATED HYPOCOTYL (LHY) double mutants (cca1/lhy) and prr7/prr5 were conducted. The results suggested that PRR genes act coordinately in a manner parallel with and antagonistic to CCA/LHY, upstream of the canonical CO-FLOWERING LOCUS T (FT) photoperiodic flowering pathway. Finally, we provided evidence to propose a model, in which CCA1/LHY repress CO through GIGANTEA (GI), while PRR9, PRR7 and PRR5 activate CO predominantly by repressing CYCLING DOF FACTOR1 (CDF1) encoding a DNA-binding transcriptional repressor.
Keywords: Arabidopsis/genetics/growth & development/*metabolism; Arabidopsis Proteins/genetics/*metabolism; Circadian Rhythm; DNA-Binding Proteins/*metabolism; Flowers/*physiology; Gene Expression Regulation, Plant; Mutation; *Photoperiod; RNA, Plant; Repressor Proteins; Time Factors; Transcription Factors/genetics/*metabolism

Liver transcriptome analysis of Atlantic cod (Gadus morhua) exposed to PCB 153 indicates effects on cell cycle regulation and lipid metabolism. - Yadetie, F.; Karlsen, O. A.; Eide, M.; Hogstrand, C.; Goksoyr, A. (BMC Genomics, 2014)
BACKGROUND: Polychlorinated biphenyls (PCBs) are persistent organic pollutants (POPs) with harmful effects in animals and humans. Although PCB 153 is one of the most abundant among PCBs detected in animal tissues, its mechanism of toxicity is not well understood. Only few studies have been conducted to explore genes and pathways affected by PCB 153 by using high throughput transcriptomics approaches. To obtain better insights into toxicity mechanisms, we treated juvenile Atlantic cod (Gadus morhua) with PCB 153 (0.5, 2 and 8 mg/kg body weight) for 2 weeks and performed gene expression analysis in the liver using oligonucleotide arrays. RESULTS: Whole-genome gene expression analysis detected about 160 differentially regulated genes. Functional enrichment, interactome, network and gene set enrichment analysis of the differentially regulated genes suggested that pathways associated with cell cycle, lipid metabolism, immune response, apoptosis and stress response were among the top significantly enriched. Particularly, genes coding for proteins in DNA replication/cell cycle pathways and enzymes of lipid biosynthesis were up-regulated suggesting increased cell proliferation and lipogenesis, respectively. CONCLUSIONS: PCB 153 appears to activate cell proliferation and lipogenic genes in cod liver. Transcriptional up-regulation of marker genes for lipid biosynthesis resembles lipogenic effects previously reported for persistent organic pollutants (POPs) and other environmental chemicals. Our results provide new insights into mechanisms of PCB 153 induced toxicity.
Keywords: Animals; Cell Cycle/*drug effects; Cluster Analysis; Computational Biology; Gadus morhua/*genetics/*metabolism; Gene Expression Profiling; Gene Expression Regulation; Gene Regulatory Networks; Lipid Metabolism/*drug effects; Liver/*drug effects/*metabolism; Molecular Sequence Annotation; Polychlorinated Biphenyls/*pharmacology; Signal Transduction; *Transcriptome

Global transcriptome analysis of Atlantic cod (Gadus morhua) liver after in vivo methylmercury exposure suggests effects on energy metabolism pathways. - Yadetie, F.; Karlsen, O. A.; Lanzen, A.; Berg, K.; Olsvik, P.; Hogstrand, C.; Goksoyr, A. (Aquat Toxicol, 2013)
Methylmercury (MeHg) is a widely distributed contaminant polluting many aquatic environments, with health risks to humans exposed mainly through consumption of seafood. The mechanisms of toxicity of MeHg are not completely understood. In order to map the range of molecular targets and gain better insights into the mechanisms of toxicity, we prepared Atlantic cod (Gadus morhua) 135k oligonucleotide arrays and performed global analysis of transcriptional changes in the liver of fish treated with MeHg (0.5 and 2 mg/kg of body weight) for 14 days. Inferring from the observed transcriptional changes, the main pathways significantly affected by the treatment were energy metabolism, oxidative stress response, immune response and cytoskeleton remodeling. Consistent with known effects of MeHg, many transcripts for genes in oxidative stress pathways such as glutathione metabolism and Nrf2 regulation of oxidative stress response were differentially regulated. Among the differentially regulated genes, there were disproportionate numbers of genes coding for enzymes involved in metabolism of amino acids, fatty acids and glucose. In particular, many genes coding for enzymes of fatty acid beta-oxidation were up-regulated. The coordinated effects observed on many transcripts coding for enzymes of energy pathways may suggest disruption of nutrient metabolism by MeHg. Many transcripts for genes coding for enzymes in the synthetic pathways of sulphur containing amino acids were also up-regulated, suggesting adaptive responses to MeHg toxicity. By this toxicogenomics approach, we were also able to identify many potential biomarker candidate genes for monitoring environmental MeHg pollution. These results based on changes on transcript levels, however, need to be confirmed by other methods such as proteomics.
Keywords: Animals; Energy Metabolism/*drug effects; Fish Proteins/genetics; *Gadus morhua/genetics/metabolism; Gene Expression Profiling; Gene Expression Regulation/*drug effects; Liver/*drug effects; Methylmercury Compounds/*toxicity; Oxidative Stress/drug effects; Water Pollutants, Chemical/*toxicity

Quantitative analyses of the hepatic proteome of methylmercury-exposed Atlantic cod (Gadus morhua) suggest oxidative stress-mediated effects on cellular energy metabolism. - Yadetie, F.; Bjorneklett, S.; Garberg, H. K.; Oveland, E.; Berven, F.; Goksoyr, A.; Karlsen, O. A. (BMC Genomics, 2016)
BACKGROUND: Methylmecury (MeHg) is a widely distributed environmental pollutant with considerable risk to both human health and wildlife. To gain better insight into the underlying mechanisms of MeHg-mediated toxicity, we have used label-free quantitative mass spectrometry to analyze the liver proteome of Atlantic cod (Gadus morhua) exposed in vivo to MeHg (0, 0.5, 2 mg/kg body weight) for 2 weeks. RESULTS: Out of a toltal of 1143 proteins quantified, 125 proteins were differentially regulated between MeHg-treated samples and controls. Using various bioinformatics tools, we performed gene ontology, pathway and network enrichment analysis, which indicated that proteins and pathways mainly related to energy metabolism, antioxidant defense, cytoskeleton remodeling, and protein synthesis were regulated in the hepatic proteome after MeHg exposure. Comparison with previous gene expression data strengthened these results, and further supported that MeHg predominantly affects many energy metabolism pathways, presumably through its strong induction of oxidative stress. Some enzymes known to have functionally important oxidation-sensitive cysteine residues in other animals are among the differentially regulated proteins, suggesting their modulations by MeHg-induced oxidative stress. Integrated analysis of the proteomics dataset combined with previous gene expression dataset showed a more pronounced effect of MeHg on amino acid, glucose and fatty acid metabolic pathways, and suggested possible interactions of the cellular energy metabolism and antioxidant defense pathways. CONCLUSIONS: MeHg disrupts mainly redox homeostasis and energy generating metabolic pathways in cod liver. The energy pathways appear to be modulated through MeHg-induced oxidative stress, possibly mediated by oxidation sensitive enzymes.
Keywords: Animals; Biomarkers; Computational Biology/methods; Energy Metabolism/*drug effects; Gadus morhua/genetics/*metabolism; Gene Expression Profiling/methods; Gene Ontology; Liver/*drug effects/*metabolism; Methylmercury Compounds/*toxicity; Oxidative Stress/*drug effects; Protein Interaction Mapping; Protein Interaction Maps; *Proteome; *Proteomics/methods

Quantitative proteomics analysis reveals perturbation of lipid metabolic pathways in the liver of Atlantic cod (Gadus morhua) treated with PCB 153 - Karlsen, Fekadu Yadetie, Eystein Oveland, Anne Døskeland, Frode Berven Anders Goksøyr, Odd André (Aquatic Toxicology, 2017)
PCB 153 is one of the most abundant PCB congeners detected in biological samples. It is a persistent compound that is still present in the environment despite the ban on production and use of PCBs in the late 1970s. It has strong tendencies to bioaccumulate and biomagnify in biota, and studies have suggested that it is an endocrine and metabolic disruptor. In order to study mechanisms of toxicity, we exposed Atlantic cod (Gadus morhua) to various doses of PCB 153 (0, 0.5, 2 and 8 mg/kg body weight) for two weeks and examined the effects on expression of liver proteins using label-free quantitative proteomics. Label-free liquid chromatography-mass spectrometry analysis of the liver proteome resulted in the quantification of 1272 proteins, of which 78 proteins were differentially regulated in the PCB 153-treated dose groups compared to the control group. Functional enrichment analysis showed that pathways significantly affected are related to the lipid metabolism, cytoskeletal remodeling, cell cycle and cell adhesion. Importantly, the main effects appear to be on lipid metabolism, with up-regulation of enzymes in the de novo fatty acid synthesis pathway, consistent with previous transcriptomics results. Increased plasma triglyceride levels were also observed in the PCB 153 treated fish, in agreement with the induction of the lipogenic genes and proteins. The results suggest that PCB 153 perturbs lipid metabolism in the Atlantic cod liver. Elevated levels of lipogenic enzymes and plasma triglycerides further suggest increased synthesis of fatty acids and triglycerides.

Regulatory principles and experimental approaches to the circadian control of starch turnover. - Seaton, D. D.; Ebenhoh, O.; Millar, A. J.; Pokhilko, A. (J R Soc Interface, 2014)
In many plants, starch is synthesized during the day and degraded during the night to avoid carbohydrate starvation in darkness. The circadian clock participates in a dynamic adjustment of starch turnover to changing environmental condition through unknown mechanisms. We used mathematical modelling to explore the possible scenarios for the control of starch turnover by the molecular components of the plant circadian clock. Several classes of plausible models were capable of describing the starch dynamics observed in a range of clock mutant plants and light conditions, including discriminating circadian protocols. Three example models of these classes are studied in detail, differing in several important ways. First, the clock components directly responsible for regulating starch degradation are different in each model. Second, the intermediate species in the pathway may play either an activating or inhibiting role on starch degradation. Third, the system may include a light-dependent interaction between the clock and downstream processes. Finally, the clock may be involved in the regulation of starch synthesis. We discuss the differences among the models' predictions for diel starch profiles and the properties of the circadian regulators. These suggest additional experiments to elucidate the pathway structure, avoid confounding results and identify the molecular components involved.
Keywords: Arabidopsis/*metabolism; Arabidopsis Proteins/metabolism; Biological Clocks; *Carbohydrate Metabolism; *Circadian Rhythm; Computer Simulation; Feedback, Physiological; Gene Expression Regulation, Plant; Kinetics; Light; Models, Theoretical; Mutation; Photoperiod; Signal Transduction; Starch/*metabolism; Systems Biology

Linked circadian outputs control elongation growth and flowering in response to photoperiod and temperature. - Seaton, D. D.; Smith, R. W.; Song, Y. H.; MacGregor, D. R.; Stewart, K.; Steel, G.; Foreman, J.; Penfield, S.; Imaizumi, T.; Millar, A. J.; Halliday, K. J. (Mol Syst Biol, 2015)
Clock-regulated pathways coordinate the response of many developmental processes to changes in photoperiod and temperature. We model two of the best-understood clock output pathways in Arabidopsis, which control key regulators of flowering and elongation growth. In flowering, the model predicted regulatory links from the clock to cycling DOF factor 1 (CDF1) and flavin-binding, KELCH repeat, F-box 1 (FKF1) transcription. Physical interaction data support these links, which create threefold feed-forward motifs from two clock components to the floral regulator FT. In hypocotyl growth, the model described clock-regulated transcription of phytochrome-interacting factor 4 and 5 (PIF4, PIF5), interacting with post-translational regulation of PIF proteins by phytochrome B (phyB) and other light-activated pathways. The model predicted bimodal and end-of-day PIF activity profiles that are observed across hundreds of PIF-regulated target genes. In the response to temperature, warmth-enhanced PIF4 activity explained the observed hypocotyl growth dynamics but additional, temperature-dependent regulators were implicated in the flowering response. Integrating these two pathways with the clock model highlights the molecular mechanisms that coordinate plant development across changing conditions.
Keywords: Arabidopsis/*genetics/physiology; Arabidopsis Proteins/genetics/metabolism; Basic Helix-Loop-Helix Transcription Factors/genetics/metabolism; Circadian Clocks/genetics; *Circadian Rhythm; Databases, Genetic; Flowers/*physiology; Gene Expression Regulation, Plant; Hypocotyl/*growth & development; Light; *Photoperiod; Phytochrome B/genetics/metabolism; RNA, Messenger/genetics/metabolism; RNA, Plant/genetics/*isolation & purification; Repressor Proteins/genetics/metabolism; Signal Transduction; *Temperature; Transcription Factors/genetics/metabolism

Multiscale digital Arabidopsis predicts individual organ and whole-organism growth. - Chew, Y. H.; Wenden, B.; Flis, A.; Mengin, V.; Taylor, J.; Davey, C. L.; Tindal, C.; Thomas, H.; Ougham, H. J.; de Reffye, P.; Stitt, M.; Williams, M.; et al. (Proc Natl Acad Sci U S A, 2014)
Understanding how dynamic molecular networks affect whole-organism physiology, analogous to mapping genotype to phenotype, remains a key challenge in biology. Quantitative models that represent processes at multiple scales and link understanding from several research domains can help to tackle this problem. Such integrated models are more common in crop science and ecophysiology than in the research communities that elucidate molecular networks. Several laboratories have modeled particular aspects of growth in Arabidopsis thaliana, but it was unclear whether these existing models could productively be combined. We test this approach by constructing a multiscale model of Arabidopsis rosette growth. Four existing models were integrated with minimal parameter modification (leaf water content and one flowering parameter used measured data). The resulting framework model links genetic regulation and biochemical dynamics to events at the organ and whole-plant levels, helping to understand the combined effects of endogenous and environmental regulators on Arabidopsis growth. The framework model was validated and tested with metabolic, physiological, and biomass data from two laboratories, for five photoperiods, three accessions, and a transgenic line, highlighting the plasticity of plant growth strategies. The model was extended to include stochastic development. Model simulations gave insight into the developmental control of leaf production and provided a quantitative explanation for the pleiotropic developmental phenotype caused by overexpression of miR156, which was an open question. Modular, multiscale models, assembling knowledge from systems biology to ecophysiology, will help to understand and to engineer plant behavior from the genome to the field.
Keywords: Arabidopsis/genetics/*growth & development/metabolism; Carbon/metabolism; Computer Simulation; Ecosystem; Genes, Plant; Metabolic Networks and Pathways; *Models, Biological; Phenotype; Photoperiod; Photosynthesis; Plant Leaves/growth & development; Plants, Genetically Modified; Starch/metabolism; Stochastic Processes; Systems Biology

Metabolic model of central carbon and energy metabolisms of growing Arabidopsis thaliana in relation to sucrose translocation - Zakhartsev, Maksim; Medvedeva, Irina; Orlov, Yuriy; Akberdin, Ilya; Krebs, Olga; Schulze, Waltraud (BMC Plant Biology, 2016)
Sucrose translocation between plant tissues is crucial for growth, development and reproduction of plants. Systemic analysis of these metabolic and underlying regulatory processes allow a detailed understanding of carbon distribution within the plant and the formation of associated phenotypic traits. Sucrose translocation from ‘source’ tissues (e.g. mesophyll) to ‘sink’ tissues (e.g. root) is tightly bound to the proton gradient across the membranes. The plant sucrose transporters are grouped into efflux exporters (SWEET family) and proton-symport importers (SUC, STP families). To better understand regulation of sucrose export from source tissues and sucrose import into sink tissues, there is a need for a metabolic model that takes in account the tissue organisation of Arabidopsis thaliana with corresponding metabolic specificities of respective tissues in terms of sucrose and proton production/utilization. An ability of the model to operate under different light modes (‘light’ and ‘dark’) and correspondingly in different energy producing modes is particularly important in understanding regulatory modules.

Formation of xylitol and xylitol-5-phosphate and its impact on growth of d-xylose-utilizing Corynebacterium glutamicum strains. - Radek, A.; Muller, M. F.; Gatgens, J.; Eggeling, L.; Krumbach, K.; Marienhagen, J.; Noack, S. (J Biotechnol, 2016)
Wild-type Corynebacterium glutamicum has no endogenous metabolic activity for utilizing the lignocellulosic pentose d-xylose for cell growth. Therefore, two different engineering approaches have been pursued resulting in platform strains harbouring a functional version of either the Isomerase (ISO) or the Weimberg (WMB) pathway for d-xylose assimilation. In a previous study we found for C. glutamicum WMB by-product formation of xylitol during growth on d-xylose and speculated that the observed lower growth rates are due to the growth inhibiting effect of this compound. Based on a detailed phenotyping of the ISO, WMB and the wild-type strain of C. glutamicum, we here show that this organism has a natural capability to synthesize xylitol from d-xylose under aerobic cultivation conditions. We furthermore observed the intracellular accumulation of xylitol-5-phosphate as a result of the intracellular phosphorylation of xylitol, which was particularly pronounced in the C. glutamicum ISO strain. Interestingly, low amounts of supplemented xylitol strongly inhibit growth of this strain on d-xylose, d-glucose and d-arabitol. These findings demonstrate that xylitol is a suitable substrate of the endogenous xylulokinase (XK, encoded by xylB) and its overexpression in the ISO strain leads to a significant phosphorylation of xylitol in C. glutamicum. Therefore, in order to circumvent cytotoxicity by xylitol-5-phosphate, the WMB pathway represents an interesting alternative route for engineering C. glutamicum towards efficient d-xylose utilization.
Keywords: Bacterial Proteins/metabolism; Corynebacterium glutamicum/*metabolism; Intracellular Space/chemistry/metabolism; Metabolic Engineering/methods; Metabolic Networks and Pathways; Pentosephosphates/*metabolism; Phosphotransferases (Alcohol Group Acceptor)/metabolism; Xylitol/*metabolism; Xylose/*metabolism

Engineering of Corynebacterium glutamicum for minimized carbon loss during utilization of D-xylose containing substrates. - Radek, A.; Krumbach, K.; Gatgens, J.; Wendisch, V. F.; Wiechert, W.; Bott, M.; Noack, S.; Marienhagen, J. (J Biotechnol, 2014)
Biomass-derived d-xylose represents an economically interesting substrate for the sustainable microbial production of value-added compounds. The industrially important platform organism Corynebacterium glutamicum has already been engineered to grow on this pentose as sole carbon and energy source. However, all currently described C. glutamicum strains utilize d-xylose via the commonly known isomerase pathway that leads to a significant carbon loss in the form of CO2, in particular, when aiming for the synthesis of alpha-ketoglutarate and its derivatives (e.g. l-glutamate). Driven by the motivation to engineer a more carbon-efficient C. glutamicum strain, we functionally integrated the Weimberg pathway from Caulobacter crescentus in C. glutamicum. This five-step pathway, encoded by the xylXABCD-operon, enabled a recombinant C. glutamicum strain to utilize d-xylose in d-xylose/d-glucose mixtures. Interestingly, this strain exhibited a tri-phasic growth behavior and transiently accumulated d-xylonate during d-xylose utilization in the second growth phase. However, this intermediate of the implemented oxidative pathway was re-consumed in the third growth phase leading to more biomass formation. Furthermore, C. glutamicum pEKEx3-xylXABCDCc was also able to grow on d-xylose as sole carbon and energy source with a maximum growth rate of mumax=0.07+/-0.01h(-1). These results render C. glutamicum pEKEx3-xylXABCDCc a promising starting point for the engineering of efficient production strains, exhibiting only minimal carbon loss on d-xylose containing substrates.
Keywords: Biomass; Carbon/metabolism; Carbon Dioxide/metabolism; Corynebacterium glutamicum/growth & development/*metabolism; Glucose/metabolism; Ketoglutaric Acids/*metabolism; Metabolome; Xylose/*metabolism

Spontaneous spatiotemporal waves of gene expression from biological clocks in the leaf. - Wenden, B.; Toner, D. L.; Hodge, S. K.; Grima, R.; Millar, A. J. (Proc Natl Acad Sci U S A, 2012)
The circadian clocks that drive daily rhythms in animals are tightly coupled among the cells of some tissues. The coupling profoundly affects cellular rhythmicity and is central to contemporary understanding of circadian physiology and behavior. In contrast, studies of the clock in plant cells have largely ignored intercellular coupling, which is reported to be very weak or absent. We used luciferase reporter gene imaging to monitor circadian rhythms in leaves of Arabidopsis thaliana plants, achieving resolution close to the cellular level. Leaves grown without environmental cycles for up to 3 wk reproducibly showed spatiotemporal waves of gene expression consistent with intercellular coupling, using several reporter genes. Within individual leaves, different regions differed in phase by up to 17 h. A broad range of patterns was observed among leaves, rather than a common spatial distribution of circadian properties. Leaves exposed to light-dark cycles always had fully synchronized rhythms, which could desynchronize rapidly. After 4 d in constant light, some leaves were as desynchronized as leaves grown without any rhythmic input. Applying light-dark cycles to such a leaf resulted in full synchronization within 2-4 d. Thus, the rhythms of all cells were coupled to external light-dark cycles far more strongly than the cellular clocks were coupled to each other. Spontaneous desynchronization under constant conditions was limited, consistent with weak intercellular coupling among heterogeneous clocks. Both the weakness of coupling and the heterogeneity among cells are relevant to interpret molecular studies and to understand the physiological functions of the plant circadian clock.
Keywords: Arabidopsis/physiology; Circadian Rhythm; *Gene Expression Regulation, Plant; Plant Leaves/*genetics/physiology

Specifications of Standards in Systems and Synthetic Biology: Status and Developments in 2016. - Schreiber, F.; Bader, G. D.; Gleeson, P.; Golebiewski, M.; Hucka, M.; Le Novere, N.; Myers, C.; Nickerson, D.; Sommer, B.; Walthemath, D. (J Integr Bioinform, 2016)
Standards are essential to the advancement of science and technology. In systems and synthetic biology, numerous standards and associated tools have been developed over the last 16 years. This special issue of the Journal of Integrative Bioinformatics aims to support the exchange, distribution and archiving of these standards, as well as to provide centralised and easily citable access to them.
Keywords: Synthetic Biology/methods/organization & administration/*standards

SABIO-RK, von Daten in der Publikation zur Suchlösung für Spezialisten - Müller, Wolfgang; Bittkowski, Meik; Golebiewski, Martin; Kania, Renate; Rey, Maja; Weidemann, Andreas; Wittig, Ulrike (Datenbank-Spektrum, 2017)

A model of yeast glycolysis based on a consistent kinetic characterisation of all its enzymes. - Smallbone, K.; Messiha, H. L.; Carroll, K. M.; Winder, C. L.; Malys, N.; Dunn, W. B.; Murabito, E.; Swainston, N.; Dada, J. O.; Khan, F.; Pir, P.; Simeonidis, E.; et al. (FEBS Lett, 2013)
We present an experimental and computational pipeline for the generation of kinetic models of metabolism, and demonstrate its application to glycolysis in Saccharomyces cerevisiae. Starting from an approximate mathematical model, we employ a "cycle of knowledge" strategy, identifying the steps with most control over flux. Kinetic parameters of the individual isoenzymes within these steps are measured experimentally under a standardised set of conditions. Experimental strategies are applied to establish a set of in vivo concentrations for isoenzymes and metabolites. The data are integrated into a mathematical model that is used to predict a new set of metabolite concentrations and reevaluate the control properties of the system. This bottom-up modelling study reveals that control over the metabolic network most directly involved in yeast glycolysis is more widely distributed than previously thought.
Keywords: Computer Simulation; *Glycolysis; Isoenzymes/chemistry; Kinetics; Metabolic Networks and Pathways; *Models, Biological; Saccharomyces cerevisiae/*enzymology/metabolism; Saccharomyces cerevisiae Proteins/*chemistry; Systems Biology

RightField: Scientific Knowledge Acquisition by Stealth through Ontology-Enabled Spreadsheets - Wolstencroft, Katy; Owen, Stuart; Horridge, Matthew; Müller, Wolfgang; Bacall, Finn; Snoep, Jacky; du Preez, Franco; Nguyen, Quyen; Krebs, Olga; Goble, Carole (Knowledge Engineering and Knowledge Management, 2012)
RightField is a Java application that provides a mechanism for embedding ontology annotation support for scientific data in Microsoft Excel or Open Office spreadsheets. The result is semantic annotation by stealth, with an annotation process that is less error-prone, more efficient, and more consistent with community standards. By automatically generating RDF statements for each cell a rich, Linked Data querying environment allows scientists to search their data and other Linked Data resources interchangeably, and caters for queries across heterogeneous spreadsheets. RightField has been developed for Systems Biologists but has since adopted more widely. It is open source (BSD license) and freely available from http://www.rightfield.org.uk

Comparison of 432 Pseudomonas strains through integration of genomic, functional, metabolic and expression data. - Koehorst, J. J.; van Dam, J. C.; van Heck, R. G.; Saccenti, E.; Dos Santos, V. A.; Suarez-Diez, M.; Schaap, P. J. (Sci Rep, 2016)
Pseudomonas is a highly versatile genus containing species that can be harmful to humans and plants while others are widely used for bioengineering and bioremediation. We analysed 432 sequenced Pseudomonas strains by integrating results from a large scale functional comparison using protein domains with data from six metabolic models, nearly a thousand transcriptome measurements and four large scale transposon mutagenesis experiments. Through heterogeneous data integration we linked gene essentiality, persistence and expression variability. The pan-genome of Pseudomonas is closed indicating a limited role of horizontal gene transfer in the evolutionary history of this genus. A large fraction of essential genes are highly persistent, still non essential genes represent a considerable fraction of the core-genome. Our results emphasize the power of integrating large scale comparative functional genomics with heterogeneous data for exploring bacterial diversity and versatility.
Keywords: *Computational Biology/methods; *Energy Metabolism; *Gene Expression Regulation, Bacterial; *Genome, Bacterial; *Genomics/methods; Humans; Molecular Sequence Annotation; Phylogeny; Pseudomonas/classification/*genetics/*metabolism; Workflow

Reconciliation of Genome-Scale Metabolic Reconstructions for Comparative Systems Analysis - Oberhardt, Matthew A.; Puchałka, Jacek; Martins dos Santos, Vitor; Papin, Jason A. (PLoS Comput Biol, 2011)

Engineering an anaerobic metabolic regime in Pseudomonas putida KT2440 for the anoxic biodegradation of 1,3-dichloroprop-1-ene - Nikel, Pablo I.; de Lorenzo, Victor (Metabolic Engineering, 2013)

In silico genome-scale metabolic analysis of Pseudomonas putida KT2440 for polyhydroxyalkanoate synthesis, degradation of aromatics and anaerobic survival - Sohn, Seung Bum; Kim, Tae Yong; Park, Jong Myoung; Lee, Sang Yup (Biotechnology Journal, 2010)

Dissecting the energy metabolism in Mycoplasma pneumoniae through genome-scale metabolic modeling. - Wodke, J. A.; Puchalka, J.; Lluch-Senar, M.; Marcos, J.; Yus, E.; Godinho, M.; Gutierrez-Gallego, R.; dos Santos, V. A.; Serrano, L.; Klipp, E.; Maier, T. (Mol Syst Biol, 2013)
Mycoplasma pneumoniae, a threatening pathogen with a minimal genome, is a model organism for bacterial systems biology for which substantial experimental information is available. With the goal of understanding the complex interactions underlying its metabolism, we analyzed and characterized the metabolic network of M. pneumoniae in great detail, integrating data from different omics analyses under a range of conditions into a constraint-based model backbone. Iterating model predictions, hypothesis generation, experimental testing, and model refinement, we accurately curated the network and quantitatively explored the energy metabolism. In contrast to other bacteria, M. pneumoniae uses most of its energy for maintenance tasks instead of growth. We show that in highly linear networks the prediction of flux distributions for different growth times allows analysis of time-dependent changes, albeit using a static model. By performing an in silico knock-out study as well as analyzing flux distributions in single and double mutant phenotypes, we demonstrated that the model accurately represents the metabolism of M. pneumoniae. The experimentally validated model provides a solid basis for understanding its metabolic regulatory mechanisms.
Keywords: Computer Simulation; Energy Metabolism/*genetics; *Gene Expression Regulation, Bacterial; *Genome, Bacterial; Metabolic Networks and Pathways/genetics; Models, Biological; Mutation; Mycoplasma pneumoniae/*genetics/*metabolism

Large-scale metabolome analysis and quantitative integration with genomics and proteomics data in Mycoplasma pneumoniae. - Maier, T.; Marcos, J.; Wodke, J. A.; Paetzold, B.; Liebeke, M.; Gutierrez-Gallego, R.; Serrano, L. (Mol Biosyst, 2013)
Systems metabolomics, the identification and quantification of cellular metabolites and their integration with genomics and proteomics data, promises valuable functional insights into cellular biology. However, technical constraints, sample complexity issues and the lack of suitable complementary quantitative data sets prevented accomplishing such studies in the past. Here, we present an integrative metabolomics study of the genome-reduced bacterium Mycoplasma pneumoniae. We experimentally analysed its metabolome using a cross-platform approach. We explain intracellular metabolite homeostasis by quantitatively integrating our results with the cellular inventory of proteins, DNA and other macromolecules, as well as with available building blocks from the growth medium. We calculated in vivo catalytic parameters of glycolytic enzymes, making use of measured reaction velocities, as well as enzyme and metabolite pool sizes. A quantitative, inter-species comparison of absolute and relative metabolite abundances indicated that metabolic pathways are regulated as functional units, thereby simplifying adaptive responses. Our analysis demonstrates the potential for new scientific insight by integrating different types of large-scale experimental data from a single biological source.
Keywords: Amino Acids/metabolism; *Genomics/methods; Glycolysis; Metabolome; *Metabolomics/methods; Mycoplasma pneumoniae/*genetics/*metabolism; Proteome; *Proteomics/methods

Digitoxin metabolism by rat liver microsomes. - Schmoldt, A.; Benthe, H. F.; Haberland, G. (Biochem Pharmacol, 1975)
Keywords: Animals; Chromatography, Thin Layer; Digitoxigenin/metabolism; Digitoxin/*metabolism; Hydroxylation; In Vitro Techniques; Male; Microsomes, Liver/*metabolism; NADP/metabolism; Rats; Time Factors

Oxidative Stickland reactions in an obligate aerobic organism - amino acid catabolism in the Crenarchaeon Sulfolobus solfataricus - Stark, Helge; Wolf, Jacqueline; Albersmeier, Andreas; Pham, Trong Khoa; Hofmann, Julia D.; Siebers, Bettina; Kalinowski, Jörn; Wright, Phil; Neumann-Schaal, Meina; Schomburg, Dietmar (FEBS J, 2017)
The thermoacidophilic Crenarchaeon Sulfolobus solfataricus is a model organism for archaeal adaptation to extreme environments and renowned for its ability to degrade a broad variety of substrates. It has been well characterised concerning the utilisation of numerous carbohydrates as carbon source. However, its amino acid metabolism, especially the degradation of single amino acids, is not as well understood. In this work, we performed metabolic modelling as well as metabolome, transcriptome and proteome analysis on cells grown on caseinhydrolysate as carbon source in order to draw a comprehensive picture of amino acid metabolism in S. solfataricus P2. We found that 10 out of 16 detectable amino acids are imported from the growth medium. Overall, uptake of glutamate, methionine, leucine, phenylalanine and isoleucine was the highest of all observed amino acids. Our simulations predict an incomplete degradation of leucine and tyrosine to organic acids, and in accordance with this, we detected the export of branched-chain and aromatic organic acids as well as amino acids, ammonium and trehalose into the culture supernatants. The branched-chain amino acids as well as phenylalanine and tyrosine are degraded to organic acids via oxidative Stickland reactions. Such reactions are known for prokaryotes capable of anaerobic growth, but so far have never been observed in an obligate aerobe. Also, 3-methyl-2-butenoate and 2-methyl-2-butenoate are for the first time found as products of modified Stickland reactions for the degradation of branched-chain amino acids. This work presents the first detailed description of branched-chain and aromatic amino acid catabolism in S. solfataricus.

Modeling metabolic networks including gene expression and uncertainties - Lindhorst, Henning; Lucia, Sergio; Findeisen, Rolf; Waldherr, Steffen (2017)
Constraint based methods, such as the Flux Balance Analysis, are widely used to model cellular growth processes without relying on extensive information on the regulatory features. The regulation is instead substituted by an optimization problem usually aiming at maximal biomass accumulation. A recent extension to these methods called the dynamic enzyme-cost Flux Balance Analysis (deFBA) is a fully dynamic modeling method allowing for the prediction of necessary enzyme levels under changing environmental conditions. However, this method was designed for deterministic settings in which all dynamics, parameters, etc. are exactly known. In this work, we present a theoretical framework extending the deFBA to handle uncertainties and provide a robust solution. We use the ideas from multi-stage nonlinear Model Predictive Control (MPC) and its feature to represent the evolution of uncertainties by an exponentially growing scenario tree. While this representation is able to construct a deterministic optimization problem in the presence of uncertainties, the computational cost also increases exponentially. We counter this by using a receding prediction horizon and reshape the standard deFBA to the short-time deFBA (sdeFBA). This leads us, along with further simplification of the scenario tree, to the robust deFBA (rdeFBA). This framework is capable of handling the uncertainties in the model itself as well as uncertainties experienced by the modeled system. We applied these algorithms to two case-studies: a minimal enzymatic nutrient uptake network, and the abstraction of the core metabolic process in bacteria.

Systems biology of the modified branched Entner-Doudoroff pathway in Sulfolobus solfataricus. - Figueiredo, A. S.; Kouril, T.; Esser, D.; Haferkamp, P.; Wieloch, P.; Schomburg, D.; Ruoff, P.; Siebers, B.; Schaber, J. (PLoS One, 2017)
Sulfolobus solfataricus is a thermoacidophilic Archaeon that thrives in terrestrial hot springs (solfatares) with optimal growth at 80 degrees C and pH 2-4. It catabolizes specific carbon sources, such as D-glucose, to pyruvate via the modified Entner-Doudoroff (ED) pathway. This pathway has two parallel branches, the semi-phosphorylative and the non-phosphorylative. However, the strategy of S.solfataricus to endure in such an extreme environment in terms of robustness and adaptation is not yet completely understood. Here, we present the first dynamic mathematical model of the ED pathway parameterized with quantitative experimental data. These data consist of enzyme activities of the branched pathway at 70 degrees C and 80 degrees C and of metabolomics data at the same temperatures for the wild type and for a metabolic engineered knockout of the semi-phosphorylative branch. We use the validated model to address two questions: 1. Is this system more robust to perturbations at its optimal growth temperature? 2. Is the ED robust to deletion and perturbations? We employed a systems biology approach to answer these questions and to gain further knowledge on the emergent properties of this biological system. Specifically, we applied deterministic and stochastic approaches to study the sensitivity and robustness of the system, respectively. The mathematical model we present here, shows that: 1. Steady state metabolite concentrations of the ED pathway are consistently more robust to stochastic internal perturbations at 80 degrees C than at 70 degrees C; 2. These metabolite concentrations are highly robust when faced with the knockout of either branch. Connected with this observation, these two branches show different properties at the level of metabolite production and flux control. These new results reveal how enzyme kinetics and metabolomics synergizes with mathematical modelling to unveil new systemic properties of the ED pathway in S.solfataricus in terms of its adaptation and robustness.
Keywords: Gene Knockout Techniques; *Metabolic Networks and Pathways; Metabolome; *Models, Biological; Monte Carlo Method; Pyruvates/metabolism; Reproducibility of Results; Stochastic Processes; Sulfolobus solfataricus/*metabolism; Systems Biology/*methods; Uncertainty

Miniaturized and automated adaptive laboratory evolution: Evolving Corynebacterium glutamicum towards an improved d-xylose utilization. - Radek, A.; Tenhaef, N.; Muller, M. F.; Brusseler, C.; Wiechert, W.; Marienhagen, J.; Polen, T.; Noack, S. (Bioresour Technol, 2017)
Adaptive Laboratory Evolution (ALE) is increasingly being used as a technique for untargeted strain optimization. This work aimed at developing an automated and miniaturized ALE approach based on repetitive batch cultivations in microtiter plates. The new method is applied to the recently published strain Corynebacterium glutamicum pEKEx3-xylXABCD(Cc), which is capable of utilizing d-xylose via the Weimberg (WMB) pathway. As a result, the significantly improved strain WMB2(evo) was obtained, showing a specific growth rate of 0.26h(-1) on d-xylose as sole carbon and energy source. WMB2(evo) grows stable during lab-scale bioreactor operation, demonstrating the high potential of this strain for future biorefinery applications. Genome sequencing of cell samples from two different ALE processes revealed potential key mutations, e.g. in the gene cg0196 (encoding for the transcriptional regulator IolR of the myo-inositol metabolism). These findings open up new perspectives for the rational engineering of C. glutamicum towards improved d-xylose utilization.
Keywords: *Bioreactors; *Corynebacterium glutamicum; Xylose

Linking circadian time to growth rate quantitatively via carbon metabolism - Chew, Yin Hoon; Seaton, Daniel; Mengin, Virginie; Flis, Anna; Mugford, Sam T.; Smith, Alison M.; Stitt, Mark; Millar, Andrew (2017)
Summary paragraph

Large-Scale Transposition Mutagenesis of Streptomyces coelicolor Identifies Hundreds of Genes Influencing Antibiotic Biosynthesis. - Xu, Z.; Wang, Y.; Chater, K. F.; Ou, H. Y.; Xu, H. H.; Deng, Z.; Tao, M. (Appl Environ Microbiol, 2017)
Gram-positive Streptomyces bacteria produce thousands of bioactive secondary metabolites, including antibiotics. To systematically investigate genes affecting secondary metabolism, we developed a hyperactive transposase-based Tn5 transposition system and employed it to mutagenize the model species Streptomyces coelicolor, leading to the identification of 51,443 transposition insertions. These insertions were distributed randomly along the chromosome except for some preferred regions associated with relatively low GC content in the chromosomal core. The base composition of the insertion site and its flanking sequences compiled from the 51,443 insertions implied a 19-bp expanded target site surrounding the insertion site, with a slight nucleic acid base preference in some positions, suggesting a relative randomness of Tn5 transposition targeting in the high-GC Streptomyces genome. From the mutagenesis library, 724 mutants involving 365 genes had altered levels of production of the tripyrrole antibiotic undecylprodigiosin (RED), including 17 genes in the RED biosynthetic gene cluster. Genetic complementation revealed that most of the insertions (more than two-thirds) were responsible for the changed antibiotic production. Genes associated with branched-chain amino acid biosynthesis, DNA metabolism, and protein modification affected RED production, and genes involved in signaling, stress, and transcriptional regulation were overrepresented. Some insertions caused dramatic changes in RED production, identifying future targets for strain improvement.IMPORTANCE High-GC Gram-positive streptomycetes and related actinomycetes have provided more than 100 clinical drugs used as antibiotics, immunosuppressants, and antitumor drugs. Their genomes harbor biosynthetic genes for many more unknown compounds with potential as future drugs. Here we developed a useful genome-wide mutagenesis tool based on the transposon Tn5 for the study of secondary metabolism and its regulation. Using Streptomyces coelicolor as a model strain, we found that chromosomal insertion was relatively random, except at some hot spots, though there was evidence of a slightly preferred 19-bp target site. We then used prodiginine production as a model to systematically survey genes affecting antibiotic biosynthesis, providing a global view of antibiotic regulation. The analysis revealed 348 genes that modulate antibiotic production, among which more than half act to reduce production. These might be valuable targets in future investigations of regulatory mechanisms, for strain improvement, and for the activation of silent biosynthetic gene clusters.
Keywords: Anti-Bacterial Agents/*biosynthesis; Base Composition/genetics; Base Sequence; DNA Transposable Elements/*genetics; Gene Expression Regulation, Bacterial; Gene Library; Mutagenesis, Insertional; Prodigiosin/*analogs & derivatives/biosynthesis; Secondary Metabolism/*genetics; Streptomyces coelicolor/*genetics; Transposases/*genetics

Photoreceptor effects on plant biomass, resource allocation, and metabolic state - Yang, Deyue; Seaton, Daniel D.; Krahmer, Johanna; Halliday, Karen J. (Proc Natl Acad Sci USA, 2016)
Plants sense the light environment through an ensemble of photoreceptors. Members of the phytochrome class of light receptors are known to play a critical role in seedling establishment, and are among the best-characterized plant signaling components. Phytochromes also regulate adult plant growth; however, our knowledge of this process is rather fragmented. This study demonstrates that phytochrome controls carbon allocation and biomass production in the developing plant. Phytochrome mutants have a reduced CO2 uptake, yet overaccumulate daytime sucrose and starch. This finding suggests that even though carbon fixation is impeded, the available carbon resources are not fully used for growth during the day. Supporting this notion, phytochrome depletion alters the proportion of day:night growth. In addition, phytochrome loss leads to sizeable reductions in overall growth, dry weight, total protein levels, and the expression of CELLULOSE SYNTHASE-LIKE genes. Because cellulose and protein are major constituents of plant biomass, our data point to an important role for phytochrome in regulating these fundamental components of plant productivity. We show that phytochrome loss impacts core metabolism, leading to elevated levels of tricarboxylic acid cycle intermediates, amino acids, sugar derivatives, and notably the stress metabolites proline and raffinose. Furthermore, the already growth-retarded phytochrome mutants are less responsive to growth-inhibiting abiotic stresses and have elevated expression of stress marker genes. This coordinated response appears to divert resources from energetically costly biomass production to improve resilience. In nature, this strategy may be activated in phytochrome-disabling, vegetation-dense habitats to enhance survival in potentially resource-limiting conditions.

Nutzung von Persistent Identifiern zur Umsetzung der FAIR-Prinzipien in Datenablageplattformen für die medizinische Forschung (2017)

Photoperiodic control of the Arabidopsis proteome reveals a translational coincidence mechanism - Seaton, Daniel; Graf, Alexander; Baerenfaller, Katja; Stitt, Mark; Millar, Andrew; Gruissem, Wilhelm
bioRxiv preprint 2017 Plants respond to seasonal cues such as the photoperiod, to adapt to current conditions and to prepare for environmental changes in the season to come. To assess photoperiodic responses at the protein level, we quantified the proteome of the model plant Arabidopsis thaliana by mass spectrometry across four photoperiods. This revealed coordinated changes of abundance in proteins of photosynthesis, primary and secondary metabolism, including pigment biosynthesis, consistent with higher metabolic activity in long photoperiods. Higher translation rates in the day time than the night likely contribute to these changes via rhythmic changes in RNA abundance. Photoperiodic control of protein levels might be greatest only if high translation rates coincide with high transcript levels in some photoperiods. We term this proposed mechanism ‘translational coincidence’, mathematically model its components, and demonstrate its effect on the Arabidopsis proteome. Datasets from a green alga and a cyanobacterium suggest that translational coincidence contributes to seasonal control of the proteome in many phototrophic organisms. This may explain why many transcripts but not their cognate proteins exhibit diurnal rhythms.

Photoperiod-dependent changes in the phase of core clock transcripts and global transcriptional outputs at dawn and dusk in Arabidopsis. - Flis, A.; Sulpice, R.; Seaton, D. D.; Ivakov, A. A.; Liput, M.; Abel, C.; Millar, A. J.; Stitt, M. (Plant Cell Environ, 2016)
Plants use the circadian clock to sense photoperiod length. Seasonal responses like flowering are triggered at a critical photoperiod when a light-sensitive clock output coincides with light or darkness. However, many metabolic processes, like starch turnover, and growth respond progressively to photoperiod duration. We first tested the photoperiod response of 10 core clock genes and two output genes. qRT-PCR analyses of transcript abundance under 6, 8, 12 and 18 h photoperiods revealed 1-4 h earlier peak times under short photoperiods and detailed changes like rising PRR7 expression before dawn. Clock models recapitulated most of these changes. We explored the consequences for global gene expression by performing transcript profiling in 4, 6, 8, 12 and 18 h photoperiods. There were major changes in transcript abundance at dawn, which were as large as those between dawn and dusk in a given photoperiod. Contributing factors included altered timing of the clock relative to dawn, light signalling and changes in carbon availability at night as a result of clock-dependent regulation of starch degradation. Their interaction facilitates coordinated transcriptional regulation of key processes like starch turnover, anthocyanin, flavonoid and glucosinolate biosynthesis and protein synthesis and underpins the response of metabolism and growth to photoperiod.
Keywords: Arabidopsis/*physiology; Arabidopsis Proteins/metabolism; Carbohydrate Metabolism; Circadian Clocks/*genetics; *Genes, Plant; Models, Biological; *Photoperiod; Principal Component Analysis; Protein Serine-Threonine Kinases/metabolism; Secondary Metabolism; Starch/biosynthesis; Sucrose/metabolism; Transcriptome

Global transcript levels respond to small changes of the carbon status during progressive exhaustion of carbohydrates in Arabidopsis rosettes. - Usadel, B.; Blasing, O. E.; Gibon, Y.; Retzlaff, K.; Hohne, M.; Gunther, M.; Stitt, M. (Plant Physiol, 2008)
The balance between the supply and utilization of carbon (C) changes continually. It has been proposed that plants respond in an acclimatory manner, modifying C utilization to minimize harmful periods of C depletion. This hypothesis predicts that signaling events are initiated by small changes in C status. We analyzed the global transcriptional response to a gradual depletion of C during the night and an extension of the night, where C becomes severely limiting from 4 h onward. The response was interpreted using published datasets for sugar, light, and circadian responses. Hundreds of C-responsive genes respond during the night and others very early in the extended night. Pathway analysis reveals that biosynthesis and cellular growth genes are repressed during the night and genes involved in catabolism are induced during the first hours of the extended night. The C response is amplified by an antagonistic interaction with the clock. Light signaling is attenuated during the 24-h light/dark cycle. A model was developed that uses the response of 22K genes during a circadian cycle and their responses to C and light to predict global transcriptional responses during diurnal cycles of wild-type and starchless pgm mutant plants and an extended night in wild-type plants. By identifying sets of genes that respond at different speeds and times during C depletion, our extended dataset and model aid the analysis of candidates for C signaling. This is illustrated for AKIN10 and four bZIP transcription factors, and sets of genes involved in trehalose signaling, protein turnover, and starch breakdown.
Keywords: Arabidopsis/genetics/*metabolism; *Carbohydrate Metabolism; Carbon/*metabolism; Gene Expression Profiling; RNA, Messenger/*genetics

Sugars and circadian regulation make major contributions to the global regulation of diurnal gene expression in Arabidopsis. - Blasing, O. E.; Gibon, Y.; Gunther, M.; Hohne, M.; Morcuende, R.; Osuna, D.; Thimm, O.; Usadel, B.; Scheible, W. R.; Stitt, M. (Plant Cell, 2005)
The diurnal cycle strongly influences many plant metabolic and physiological processes. Arabidopsis thaliana rosettes were harvested six times during 12-h-light/12-h-dark treatments to investigate changes in gene expression using ATH1 arrays. Diagnostic gene sets were identified from published or in-house expression profiles of the response to light, sugar, nitrogen, and water deficit in seedlings and 4 h of darkness or illumination at ambient or compensation point [CO(2)]. Many sugar-responsive genes showed large diurnal expression changes, whose timing matched that of the diurnal changes of sugars. A set of circadian-regulated genes also showed large diurnal changes in expression. Comparison of published results from a free-running cycle with the diurnal changes in Columbia-0 (Col-0) and the starchless phosphoglucomutase (pgm) mutant indicated that sugars modify the expression of up to half of the clock-regulated genes. Principle component analysis identified genes that make large contributions to diurnal changes and confirmed that sugar and circadian regulation are the major inputs in Col-0 but that sugars dominate the response in pgm. Most of the changes in pgm are triggered by low sugar levels during the night rather than high levels in the light, highlighting the importance of responses to low sugar in diurnal gene regulation. We identified a set of candidate regulatory genes that show robust responses to alterations in sugar levels and change markedly during the diurnal cycle.
Keywords: Arabidopsis/*genetics; Carbohydrates/*physiology; *Circadian Rhythm; Gene Expression Regulation, Plant/*physiology; Genes, Plant; Mutation; Nitrogen/physiology; RNA, Messenger/genetics

Stable Core Gut Microbiota across the Freshwater-to-Saltwater Transition for Farmed Atlantic Salmon - Rudi, Knut; Angell, Inga Leena; Pope, Phillip B.; Vik, Jon Olav; Sandve, Simen Rød; Snipen, Lars (Appl Environ Microbiol, 2018)
Gut microbiota associations through habitat transitions are fundamentally important yet poorly understood. One such habitat transition is the migration from freshwater to saltwater for anadromous fish, such as salmon. The aim of the current work was therefore to determine the freshwater-to-saltwater transition impact on the gut microbiota in farmed Atlantic salmon, with dietary interventions resembling freshwater and saltwater diets with respect to fatty acid composition. Using deep 16S rRNA gene sequencing and quantitative PCR, we found that the freshwater-to-saltwater transition had a major association with the microbiota composition and quantity, while diet did not show significant associations with the microbiota. In saltwater there was a 100-fold increase in bacterial quantity, with a relative increase of Firmicutes and a relative decrease of both Actinobacteria and Proteobacteria. Irrespective of an overall shift in microbiota composition from freshwater to saltwater, we identified three core clostridia and one Lactobacillus-affiliated phylotype with wide geographic distribution that were highly prevalent and co-occurring. Taken together, our results support the importance of the dominating bacteria in the salmon gut, with the freshwater microbiota being immature. Due to the low number of potentially host-associated bacterial species in the salmon gut, we believe that farmed salmon can represent an important model for future understanding of host-bacterium interactions in aquatic environments.

Dynamic proteomic profiling of a unicellular cyanobacterium Cyanothece ATCC51142 across light-dark diurnal cycles. - Aryal, U. K.; Stockel, J.; Krovvidi, R. K.; Gritsenko, M. A.; Monroe, M. E.; Moore, R. J.; Koppenaal, D. W.; Smith, R. D.; Pakrasi, H. B.; Jacobs, J. M. (BMC Syst Biol, 2011)
BACKGROUND: Unicellular cyanobacteria of the genus Cyanothece are recognized for their ability to execute nitrogen (N2)-fixation in the dark and photosynthesis in the light. An understanding of these mechanistic processes in an integrated systems context should provide insights into how Cyanothece might be optimized for specialized environments and/or industrial purposes. Systems-wide dynamic proteomic profiling with mass spectrometry (MS) analysis should reveal fundamental insights into the control and regulation of these functions. RESULTS: To expand upon the current knowledge of protein expression patterns in Cyanothece ATCC51142, we performed quantitative proteomic analysis using partial ("unsaturated") metabolic labeling and high mass accuracy LC-MS analysis. This dynamic proteomic profiling identified 721 actively synthesized proteins with significant temporal changes in expression throughout the light-dark cycles, of which 425 proteins matched with previously characterized cycling transcripts. The remaining 296 proteins contained a cluster of proteins uniquely involved in DNA replication and repair, protein degradation, tRNA synthesis and modification, transport and binding, and regulatory functions. Functional classification of labeled proteins suggested that proteins involved in respiration and glycogen metabolism showed increased expression in the dark cycle together with nitrogenase, suggesting that N2-fixation is mediated by higher respiration and glycogen metabolism. Results indicated that Cyanothece ATCC51142 might utilize alternative pathways for carbon (C) and nitrogen (N) acquisition, particularly, aspartic acid and glutamate as substrates of C and N, respectively. Utilization of phosphoketolase (PHK) pathway for the conversion of xylulose-5P to pyruvate and acetyl-P likely constitutes an alternative strategy to compensate higher ATP and NADPH demand. CONCLUSION: This study provides a deeper systems level insight into how Cyanothece ATCC51142 modulates cellular functions to accommodate photosynthesis and N2-fixation within the single cell.
Keywords: Bacterial Proteins/genetics/metabolism/*physiology; *Circadian Rhythm; Cyanothece/genetics/*metabolism; Darkness; Light; *Models, Biological; *Nitrogen Fixation; *Photosynthesis; Protein Interaction Maps; *Proteome; Proteomics; Stress, Physiological; Systems Biology; Transcriptome

Proteome turnover in the green alga Ostreococcus tauri by time course 15N metabolic labeling mass spectrometry. - Martin, S. F.; Munagapati, V. S.; Salvo-Chirnside, E.; Kerr, L. E.; Le Bihan, T. (J Proteome Res, 2012)
Protein synthesis and degradation determine the cellular levels of proteins, and their control hence enables organisms to respond to environmental change. Experimentally, these are little known proteome parameters; however, recently, SILAC-based mass spectrometry studies have begun to quantify turnover in the proteomes of cell lines, yeast, and animals. Here, we present a proteome-scale method to quantify turnover and calculate synthesis and degradation rate constants of individual proteins in autotrophic organisms such as algae and plants. The workflow is based on the automated analysis of partial stable isotope incorporation with (15)N. We applied it in a study of the unicellular pico-alga Ostreococcus tauri and observed high relative turnover in chloroplast-encoded ATPases (0.42-0.58% h(-1)), core photosystem II proteins (0.34-0.51% h(-1)), and RbcL (0.47% h(-1)), while nuclear-encoded RbcS2 is more stable (0.23% h(-1)). Mitochondrial targeted ATPases (0.14-0.16% h(-1)), photosystem antennae (0.09-0.14% h(-1)), and histones (0.07-0.1% h(-1)) were comparatively stable. The calculation of degradation and synthesis rate constants k(deg) and k(syn) confirms RbcL as the bulk contributor to overall protein turnover. This study performed over 144 h of incorporation reveals dynamics of protein complex subunits as well as isoforms targeted to different organelles.
Keywords: Algorithms; Amino Acid Sequence; Chlorophyta/*metabolism; Kinetics; Molecular Sequence Data; Nitrogen Isotopes; Peptide Fragments/chemistry; Plant Proteins/chemistry/*metabolism; Protein Biosynthesis; Protein Stability; Proteolysis; Proteome/chemistry/*metabolism; Staining and Labeling; Tandem Mass Spectrometry

SABIO-RK: an updated resource for manually curated biochemical reaction kinetics. - Wittig, U.; Rey, M.; Weidemann, A.; Kania, R.; Muller, W. (Nucleic Acids Res, 2018)
SABIO-RK (http://sabiork.h-its.org/) is a manually curated database containing data about biochemical reactions and their reaction kinetics. The data are primarily extracted from scientific literature and stored in a relational database. The content comprises both naturally occurring and alternatively measured biochemical reactions and is not restricted to any organism class. The data are made available to the public by a web-based search interface and by web services for programmatic access. In this update we describe major improvements and extensions of SABIO-RK since our last publication in the database issue of Nucleic Acid Research (2012). (i) The website has been completely revised and (ii) allows now also free text search for kinetics data. (iii) Additional interlinkages with other databases in our field have been established; this enables users to gain directly comprehensive knowledge about the properties of enzymes and kinetics beyond SABIO-RK. (iv) Vice versa, direct access to SABIO-RK data has been implemented in several systems biology tools and workflows. (v) On request of our experimental users, the data can be exported now additionally in spreadsheet formats. (vi) The newly established SABIO-RK Curation Service allows to respond to specific data requirements.
Keywords: Animals; *Biochemical Phenomena; Data Curation; *Databases, Chemical; Enzymes/metabolism; Humans; Internet; Kinetics; Metabolic Networks and Pathways; Search Engine; Signal Transduction; User-Computer Interface

Life-stage-associated remodelling of lipid metabolism regulation in Atlantic salmon. - Gillard, G.; Harvey, T. N.; Gjuvsland, A.; Jin, Y.; Thomassen, M.; Lien, S.; Leaver, M.; Torgersen, J. S.; Hvidsten, T. R.; Vik, J. O.; Sandve, S. R. (Mol Ecol, 2018)
Atlantic salmon migrates from rivers to sea to feed, grow and develop gonads before returning to spawn in freshwater. The transition to marine habitats is associated with dramatic changes in the environment, including water salinity, exposure to pathogens and shift in dietary lipid availability. Many changes in physiology and metabolism occur across this life-stage transition, but little is known about the molecular nature of these changes. Here, we use a long-term feeding experiment to study transcriptional regulation of lipid metabolism in Atlantic salmon gut and liver in both fresh- and saltwater. We find that lipid metabolism becomes significantly less plastic to differences in dietary lipid composition when salmon transitions to saltwater and experiences increased dietary lipid availability. Expression of genes in liver relating to lipogenesis and lipid transport decreases overall and becomes less responsive to diet, while genes for lipid uptake in gut become more highly expressed. Finally, analyses of evolutionary consequences of the salmonid-specific whole-genome duplication on lipid metabolism reveal several pathways with significantly different (p < .05) duplicate retention or duplicate regulatory conservation. We also find a limited number of cases where the whole-genome duplication has resulted in an increased gene dosage. In conclusion, we find variable and pathway-specific effects of the salmonid genome duplication on lipid metabolism genes. A clear life-stage-associated shift in lipid metabolism regulation is evident, and we hypothesize this to be, at least partly, driven by nondietary factors such as the preparatory remodelling of gene regulation and physiology prior to sea migration.
Keywords: Acclimatization; Animal Migration; Animals; Diet; Gene Duplication; Gene Expression Regulation, Developmental; Life Cycle Stages/genetics; *Lipid Metabolism; Liver/metabolism; Molecular Sequence Annotation; Salmo salar/genetics/growth & development/*metabolism; Transcriptome

Copy number profiling by array comparative genomic hybridization identifies frequently occurring BRCA2-like male breast cancer. - Biesma, H. D.; Schouten, P. C.; Lacle, M. M.; Sanders, J.; Brugman, W.; Kerkhoven, R.; Mandjes, I.; van der Groep, P.; van Diest, P. J.; Linn, S. C. (Genes Chromosomes Cancer, 2015)
Genomic aberrations can be used to subtype breast cancer. In this study, we investigated DNA copy number (CN) profiles of 69 cases of male breast cancer (MBC) by array comparative genomic hybridization (aCGH) to detect recurrent gains and losses in comparison with female breast cancers (FBC). Further, we classified these profiles as BRCA1-like, BRCA2-like or non-BRCA-like profiles using previous classifiers derived from FBC, and correlated these profiles with pathological characteristics. We observed large CN gains on chromosome arms 1q, 5p, 8q, 10p, 16p, 17q, and chromosomes 20 and X. Large losses were seen on chromosomes/chromosome arms 1p, 6p, 8p, 9, 11q, 13, 14q, 16q, 17p, and 22. The pattern of gains and losses in estrogen receptor positive (ER+) MBC was largely similar to ER+ FBC, except for gains on chromosome X in MBC, which were uncommon in FBC. Out of 69 MBC patients, 15 patients (22%) had a BRCA2-like profile, of which 2 (3%) were also BRCA1-like. One patient (1%) was only BRCA1-like; the remaining 53 (77%) patients were classified as non-BRCA-like. BRCA2-like cases were more often p53 accumulated than non-BRCA-like cases (P = 0.014). In conclusion, the pattern of gains and losses in ER+ MBC was largely similar to that of its ER+ FBC counterpart, except for gains on chromosome X in MBC, which are uncommon in FBC. A significant proportion of MBC has a BRCA2-like aCGH profile, pointing to a potentially hereditary nature, and indicating that they could benefit from a drug regimen targeting BRCA defects as in FBC.
Keywords: Adult; Aged; Aged, 80 and over; BRCA1 Protein/genetics; BRCA2 Protein/*genetics; Breast Neoplasms, Male/*classification/*genetics/pathology; *Chromosome Aberrations; Comparative Genomic Hybridization/methods; *DNA Copy Number Variations; Female; Humans; Male; Middle Aged; Neoplasm Grading; Tumor Suppressor Protein p53/metabolism

Gene expression profiling of primary male breast cancers reveals two unique subgroups and identifies N-acetyltransferase-1 (NAT1) as a novel prognostic biomarker. - Johansson, I.; Nilsson, C.; Berglund, P.; Lauss, M.; Ringner, M.; Olsson, H.; Luts, L.; Sim, E.; Thorstensson, S.; Fjallskog, M. L.; Hedenfalk, I. (Breast Cancer Res, 2012)
INTRODUCTION: Male breast cancer (MBC) is a rare and inadequately characterized disease. The aim of the present study was to characterize MBC tumors transcriptionally, to classify them into comprehensive subgroups, and to compare them with female breast cancer (FBC). METHODS: A total of 66 clinicopathologically well-annotated fresh frozen MBC tumors were analyzed using Illumina Human HT-12 bead arrays, and a tissue microarray with 220 MBC tumors was constructed for validation using immunohistochemistry. Two external gene expression datasets were used for comparison purposes: 37 MBCs and 359 FBCs. RESULTS: Using an unsupervised approach, we classified the MBC tumors into two subgroups, luminal M1 and luminal M2, respectively, with differences in tumor biological features and outcome, and which differed from the intrinsic subgroups described in FBC. The two subgroups were recapitulated in the external MBC dataset. Luminal M2 tumors were characterized by high expression of immune response genes and genes associated with estrogen receptor (ER) signaling. Luminal M1 tumors, on the other hand, despite being ER positive by immunohistochemistry showed a lower correlation to genes associated with ER signaling and displayed a more aggressive phenotype and worse prognosis. Validation of two of the most differentially expressed genes, class 1 human leukocyte antigen (HLA) and the metabolizing gene N-acetyltransferase-1 (NAT1), respectively, revealed significantly better survival associated with high expression of both markers (HLA, hazard ratio (HR) 3.6, P = 0.002; NAT1, HR 2.5, P = 0.033). Importantly, NAT1 remained significant in a multivariate analysis (HR 2.8, P = 0.040) and may thus be a novel prognostic marker in MBC. CONCLUSIONS: We have detected two unique and stable subgroups of MBC with differences in tumor biological features and outcome. They differ from the widely acknowledged intrinsic subgroups of FBC. As such, they may constitute two novel subgroups of breast cancer, occurring exclusively in men, and which may consequently require novel treatment approaches. Finally, we identified NAT1 as a possible prognostic biomarker for MBC, as suggested by NAT1 positivity corresponding to better outcome.
Keywords: Adult; Aged; Aged, 80 and over; Arylamine N-Acetyltransferase/genetics/*metabolism; Biomarkers, Tumor/genetics/*metabolism; Breast Neoplasms, Male/classification/diagnosis/*enzymology/mortality; Carcinoma, Ductal, Breast/classification/diagnosis/*enzymology/mortality; Carcinoma, Intraductal, Noninfiltrating/classification/diagnosis/*enzymology/mortality; Cluster Analysis; Female; Gene Expression Profiling; Humans; Isoenzymes/genetics/*metabolism; Kaplan-Meier Estimate; Male; Middle Aged; Multivariate Analysis; Oligonucleotide Array Sequence Analysis; Principal Component Analysis; Prognosis; Statistics, Nonparametric; Tissue Array Analysis; *Transcriptome; Young Adult

Suppression of indoleamine-2,3-dioxygenase 1 expression by promoter hypermethylation in ER-positive breast cancer. - Dewi, D. L.; Mohapatra, S. R.; Blanco Cabanes, S.; Adam, I.; Somarribas Patterson, L. F.; Berdel, B.; Kahloon, M.; Thurmann, L.; Loth, S.; Heilmann, K.; Weichenhan, D.; Mucke, O.; et al. (Oncoimmunology, 2017)
Kynurenine formation by tryptophan-catabolic indoleamine-2,3-dioxygenase 1 (IDO1) plays a key role in tumor immune evasion and inhibition of IDO1 is efficacious in preclinical models of breast cancer. As the response of breast cancer to immune checkpoint inhibitors may be limited, a better understanding of the expression of additional targetable immunomodulatory pathways is of importance. We therefore investigated the regulation of IDO1 expression in different breast cancer subtypes. We identified estrogen receptor alpha (ER) as a negative regulator of IDO1 expression. Serum kynurenine levels as well as tumoral IDO1 expression were lower in patients with ER-positive than ER-negative tumors and an inverse relationship between IDO1 and estrogen receptor mRNA was observed across 14 breast cancer data sets. Analysis of whole genome bisulfite sequencing, 450k, MassARRAY and pyrosequencing data revealed that the IDO1 promoter is hypermethylated in ER-positive compared with ER-negative breast cancer. Reduced induction of IDO1 was also observed in human ER-positive breast cancer cell lines. IDO1 induction was enhanced upon DNA demethylation in ER-positive but not in ER-negative cells and methylation of an IDO1 promoter construct reduced IDO1 expression, suggesting that enhanced methylation of the IDO1 promoter suppresses IDO1 in ER-positive breast cancer. The association of ER overexpression with epigenetic downregulation of IDO1 appears to be a particular feature of breast cancer as IDO1 was not suppressed by IDO1 promoter hypermethylation in the presence of high ER expression in cervical or endometrial cancer.

Model of tryptophan metabolism, readily scalable using tissue-specific gene expression data. - Stavrum, A. K.; Heiland, I.; Schuster, S.; Puntervoll, P.; Ziegler, M. (J Biol Chem, 2013)
Tryptophan is utilized in various metabolic routes including protein synthesis, serotonin, and melatonin synthesis and the kynurenine pathway. Perturbations in these pathways have been associated with neurodegenerative diseases and cancer. Here we present a comprehensive kinetic model of the complex network of human tryptophan metabolism based upon existing kinetic data for all enzymatic conversions and transporters. By integrating tissue-specific expression data, modeling tryptophan metabolism in liver and brain returned intermediate metabolite concentrations in the physiological range. Sensitivity and metabolic control analyses identified expected key enzymes to govern fluxes in the branches of the network. Combining tissue-specific models revealed a considerable impact of the kynurenine pathway in liver on the concentrations of neuroactive derivatives in the brain. Moreover, using expression data from a cancer study predicted metabolite changes that resembled the experimental observations. We conclude that the combination of the kinetic model with expression data represents a powerful diagnostic tool to predict alterations in tryptophan metabolism. The model is readily scalable to include more tissues, thereby enabling assessment of organismal tryptophan metabolism in health and disease.
Keywords: Humans; Kinetics; Kynurenine/metabolism; Liver/*enzymology/metabolism; Metabolic Networks and Pathways/*genetics; *Models, Theoretical; Organ Specificity; Transcriptome; Tryptophan/genetics/*metabolism

Schemes of flux control in a model of Saccharomyces cerevisiae glycolysis. - Pritchard, L.; Kell, D. B. (Eur J Biochem, 2002)
We used parameter scanning to emulate changes to the limiting rate for steps in a fitted model of glucose-derepressed yeast glycolysis. Three flux-control regimes were observed, two of which were under the dominant control of hexose transport, in accordance with various experimental studies and other model predictions. A third control regime in which phosphofructokinase exerted dominant glycolytic flux control was also found, but it appeared to be physiologically unreachable by this model, and all realistically obtainable flux control regimes featured hexose transport as a step involving high flux control.
Keywords: Adenosine Triphosphate/metabolism; Algorithms; Biological Transport; *Computer Simulation; Glucose/pharmacology; Glycogen/metabolism; *Glycolysis; Kinetics; *Models, Biological; Saccharomyces cerevisiae/drug effects/*metabolism; Saccharomyces cerevisiae Proteins/metabolism; Trehalose/metabolism

Morpheus: a user-friendly modeling environment for multiscale and multicellular systems biology. - Starruss, J.; de Back, W.; Brusch, L.; Deutsch, A. (Bioinformatics, 2014)
Morpheus is a modeling environment for the simulation and integration of cell-based models with ordinary differential equations and reaction-diffusion systems. It allows rapid development of multiscale models in biological terms and mathematical expressions rather than programming code. Its graphical user interface supports the entire workflow from model construction and simulation to visualization, archiving and batch processing.
Keywords: Models, Biological; Myxococcus xanthus/cytology; Software; Systems Biology/*methods

A Predictive 3D Multi-Scale Model of Biliary Fluid Dynamics in the Liver Lobule. - Meyer, K.; Ostrenko, O.; Bourantas, G.; Morales-Navarrete, H.; Porat-Shliom, N.; Segovia-Miranda, F.; Nonaka, H.; Ghaemi, A.; Verbavatz, J. M.; Brusch, L.; Sbalzarini, I.; Kalaidzidis, Y.; et al. (Cell Syst, 2017)
Bile, the central metabolic product of the liver, is transported by the bile canaliculi network. The impairment of bile flow in cholestatic liver diseases has urged a demand for insights into its regulation. Here, we developed a predictive 3D multi-scale model that simulates fluid dynamic properties successively from the subcellular to the tissue level. The model integrates the structure of the bile canalicular network in the mouse liver lobule, as determined by high-resolution confocal and serial block-face scanning electron microscopy, with measurements of bile transport by intravital microscopy. The combined experiment-theory approach revealed spatial heterogeneities of biliary geometry and hepatocyte transport activity. Based on this, our model predicts gradients of bile velocity and pressure in the liver lobule. Validation of the model predictions by pharmacological inhibition of Rho kinase demonstrated a requirement of canaliculi contractility for bile flow in vivo. Our model can be applied to functionally characterize liver diseases and quantitatively estimate biliary transport upon drug-induced liver injury.
Keywords: Animals; Bile/metabolism; Bile Canaliculi/*metabolism/*physiology; Biliary Tract/*diagnostic imaging/metabolism/physiology; Chemical and Drug Induced Liver Injury/metabolism; Cholestasis/metabolism; Computer Simulation; Forecasting; Hepatocytes/metabolism; Hydrodynamics; Liver/metabolism; Mice; Mice, Inbred C57BL

pSSAlib: The partial-propensity stochastic chemical network simulator - Ostrenko, Oleksandr; Incardona, Pietro; Ramaswamy, Rajesh; Brusch, Lutz; Sbalzarini, Ivo F. (PLoS Comput Biol, 2017)
Chemical reaction networks are ubiquitous in biology, and their dynamics is fundamentally stochastic. Here, we present the software library pSSAlib, which provides a complete and concise implementation of the most efficient partial-propensity methods for simulating exact stochastic chemical kinetics. pSSAlib can import models encoded in Systems Biology Markup Language, supports time delays in chemical reactions, and stochastic spatiotemporal reaction-diffusion systems. It also provides tools for statistical analysis of simulation results and supports multiple output formats. It has previously been used for studies of biochemical reaction pathways and to benchmark other stochastic simulation methods. Here, we describe pSSAlib in detail and apply it to a new model of the endocytic pathway in eukaryotic cells, leading to the discovery of a stochastic counterpart of the cut-out switch motif underlying early-to-late endosome conversion. pSSAlib is provided as a stand-alone command-line tool and as a developer API. We also provide a plug-in for the SBMLToolbox. The open-source code and pre-packaged installers are freely available from http://mosaic.mpi-cbg.de.

Characterization of the Weimberg Pathway in Caulobacter crescentus - Almqvist, Henrik; Jonsdottir Glaser, Sara; Tufvegren, Celina; Wasserstrom, Lisa; Liden, Gunnar (Fermentation, 2018)
Caulobacter crescentus is a gram-negative bacterium that can utilize xylose as a substrate using the Weimberg pathway, which converts xylose to α-ketoglutarate in five steps without carbon loss. This is an interesting pathway for heterologous expression in other organisms in order to enable xylose utilization in biorefinery processes. C. crescentus was grown on xylose, arabinose and glucose, and maximum specific growth rates determined for the three substrates were 0.11 h−1, 0.05 h−1, and 0.15 h−1 respectively. Growth was found to be significantly inhibited at sugar concentration of 20 g L−1, shown primarily by an increased lag phase. Enzyme activity assays showed that the Weimberg pathway was active in cells grown, not only on xylose but also on arabinose. No activity was found for growth on glucose. Furthermore, substantial amounts of α-ketoglutarate—up to a yield of 0.4 g g−1—was excreted during growth on xylose, but no other extracellular intermediates in the Weimberg pathway were detected during growth on xylose. Apparently, C. crescentus is not well adapted for efficient growth on high xylose levels, and responds by an extended lag phase and secretion of α-ketoglutarate.

Phytochrome B regulates resource allocation in Brassica rapa. - Arsovski, A. A.; Zemke, J. E.; Haagen, B. D.; Kim, S. H.; Nemhauser, J. L. (J Exp Bot, 2018)
Crop biomass and yield are tightly linked to how the light signaling network translates information about the environment into allocation of resources, including photosynthates. Once activated, the phytochrome (phy) class of photoreceptors signal and re-deploy carbon resources to alter growth, plant architecture, and reproductive timing. Most of the previous characterization of the light-modulated growth program has been performed in the reference plant Arabidopsis thaliana. Here, we use Brassica rapa as a crop model to test for conservation of the phytochrome-carbon network. In response to elevated levels of CO2, B. rapa seedlings showed increases in hypocotyl length, shoot and root fresh weight, and the number of lateral roots. All of these responses were dependent on nitrogen and polar auxin transport. In addition, we identified putative B. rapa orthologs of PhyB and isolated two nonsense alleles. BrphyB mutants had significantly decreased or absent CO2-stimulated growth responses. Mutant seedlings also showed misregulation of auxin-dependent genes and genes involved in chloroplast development. Adult mutant plants had reduced chlorophyll levels, photosynthetic rate, stomatal index, and seed yield. These findings support a recently proposed holistic role for phytochromes in regulating resource allocation, biomass production, and metabolic state in the developing plant.
Keywords: Brassica rapa/growth & development/*physiology; Carbon Dioxide/*metabolism; Phytochrome B/*metabolism; Plant Roots/growth & development/physiology; Plant Shoots/growth & development/physiology; Seedlings/growth & development/physiology

Phytochrome, Carbon Sensing, Metabolism, and Plant Growth Plasticity. - Krahmer, J.; Ganpudi, A.; Abbas, A.; Romanowski, A.; Halliday, K. J. (Plant Physiol, 2018)
Phytochrome signaling controls biomass accumulation, growth plasticity, and metabolism.
Keywords: Arabidopsis/growth & development/metabolism/radiation effects; Biomass; Carbon/*metabolism; Light; Photosynthesis/radiation effects; Phytochrome/*metabolism; Plant Development/*physiology/radiation effects; Plants/*metabolism/radiation effects; Signal Transduction/*physiology/radiation effects

Photosynthate partitioning to starch in Arabidopsis thaliana is insensitive to light intensity but sensitive to photoperiod due to a restriction on growth in the light in short photoperiods. - Mengin, V.; Pyl, E. T.; Alexandre Moraes, T.; Sulpice, R.; Krohn, N.; Encke, B.; Stitt, M. (Plant Cell Environ, 2017)
Photoperiod duration can be predicted from previous days, but irradiance fluctuates in an unpredictable manner. To investigate how allocation to starch responds to changes in these two environmental variables, Arabidopsis Col-0 was grown in a 6 h and a 12 h photoperiod at three different irradiances. The absolute rate of starch accumulation increased when photoperiod duration was shortened and when irradiance was increased. The proportion of photosynthate allocated to starch increased strongly when photoperiod duration was decreased but only slightly when irradiance was decreased. There was a small increase in the daytime level of sucrose and twofold increases in glucose, fructose and glucose 6-phosphate at a given irradiance in short photoperiods compared to long photoperiods. The rate of starch accumulation correlated strongly with sucrose and glucose levels in the light, irrespective of whether these sugars were responding to a change in photoperiod or irradiance. Whole plant carbon budget modelling revealed a selective restriction of growth in the light period in short photoperiods. It is proposed that photoperiod sensing, possibly related to the duration of the night, restricts growth in the light period in short photoperiods, increasing allocation to starch and providing more carbon reserves to support metabolism and growth in the long night.
Keywords: Arabidopsis/*growth & development/metabolism/*radiation effects; Cell Respiration/radiation effects; Circadian Rhythm/radiation effects; Darkness; *Light; Metabolome/radiation effects; *Photoperiod; Photosynthesis/*radiation effects; Starch/*metabolism; Sucrose/metabolism; Sugars/metabolism

Cell size and morphological properties of yeast Saccharomyces cerevisiae in relation to growth temperature - Zakhartsev, Maksim; Reuss, Matthias (2018)
Cell volume is an important parameter for modelling cellular processes. Temperature-induced variability of cellular size, volume, intracellular granularity, a fraction of budding cells of yeast Saccharomyces cerevisiae CEN.PK 113–7D (in anaerobic glucose unlimited batch cultures) were measured by flow cytometry and matched with the performance of the biomass growth (maximal specific growth rate (μmax), specific rate of glucose consumption, the rate of maintenance, biomass yield on glucose). The critical diameter of single cells was 7.94 μm and it is invariant at growth temperatures above 18.5°C. Below 18.5°C, it exponentially increases up to 10.2 μm. The size of the bud linearly depends on μmax, and it is between 50% at 5°C and 90% at 31°C of the averaged single cell. The intracellular granularity (side scatter channel (SSC)-index) negatively depends on μmax. There are two temperature regions (5–31°C vs. 33–40°C) where the relationship between SSC-index and various cellular parameters differ significantly. In supraoptimal temperature range (33–40°C), cells are less granulated perhaps due to a higher rate of the maintenance. There is temperature dependent passage through the checkpoints in the cell cycle which influences the μmax. The results point to the existence of two different morphological states of yeasts in these different temperature regions.

Entrainment of heterogeneous glycolytic oscillations in single cells - Gustavsson, Anna-Karin; Adiels, Caroline B.; Mehlig, Bernhard; Goksör, Mattias (Sci Rep, 2015)
Cell signaling, gene expression, and metabolism are affected by cell-cell heterogeneity and random changes in the environment. The effects of such fluctuations on cell signaling and gene expression have recently been studied intensively using single-cell experiments. In metabolism heterogeneity may be particularly important because it may affect synchronisation of metabolic oscillations, an important example of cell-cell communication. This synchronisation is notoriously difficult to describe theoretically as the example of glycolytic oscillations shows: neither is the mechanism of glycolytic synchronisation understood nor the role of cell-cell heterogeneity. To pin down the mechanism and to assess its robustness and universality we have experimentally investigated the entrainment of glycolytic oscillations in individual yeast cells by periodic external perturbations. We find that oscillatory cells synchronise through phase shifts and that the mechanism is insensitive to cell heterogeneity (robustness) and similar for different types of external perturbations (universality).

Allosteric regulation of phosphofructokinase controls the emergence of glycolytic oscillations in isolated yeast cells - Gustavsson, Anna-Karin; van Niekerk, Dawie; Adiels, Caroline B.; Kooi, Bob; Goksör, Mattias; Snoep, Jacky (FEBS J, 2014)

Multi-omics Reveals the Lifestyle of the Acidophilic, Mineral-Oxidizing Model Species Leptospirillum ferriphilum T - Christel, Stephan; Herold, Malte; Bellenberg, Soeren; El Hajjami, Mohamed; Buetti-Dinh, Antoine; Pivkin, Igor; Sand, Wolfgang; Wilmes, Paul; Poetsch, Ansgar; Dopson, Mark (Appl Environ Microbiol, 2018)
Leptospirillum ferriphilum plays a major role in acidic, metal rich environments where it represents one of the most prevalent iron oxidizers. These milieus include acid rock and mine drainage as well as biomining operations. Despite its perceived importance, no complete genome sequence of this model species' type strain is available, limiting the possibilities to investigate the strategies and adaptations Leptospirillum ferriphilumT applies to survive and compete in its niche. This study presents a complete, circular genome of Leptospirillum ferriphilumT DSM 14647 obtained by PacBio SMRT long read sequencing for use as a high quality reference. Analysis of the functionally annotated genome, mRNA transcripts, and protein concentrations revealed a previously undiscovered nitrogenase cluster for atmospheric nitrogen fixation and elucidated metabolic systems taking part in energy conservation, carbon fixation, pH homeostasis, heavy metal tolerance, oxidative stress response, chemotaxis and motility, quorum sensing, and biofilm formation. Additionally, mRNA transcript counts and protein concentrations were compared between cells grown in continuous culture using ferrous iron as substrate and bioleaching cultures containing chalcopyrite (CuFeS2). Leptospirillum ferriphilumT adaptations to growth on chalcopyrite included a possibly enhanced production of reducing power, reduced carbon dioxide fixation, as well as elevated RNA transcripts and proteins involved in heavy metal resistance, with special emphasis on copper efflux systems. Finally, expression and translation of genes responsible for chemotaxis and motility were enhanced.

Heterogeneity of glycolytic oscillatory behaviour in individual yeast cells - Gustavsson, Anna-Karin; van Niekerk, Dawie; Adiels, Caroline B.; Goksör, Mattias; Snoep, Jacky (2014)

Sustained glycolytic oscillations in individual isolated yeast cells - Gustavsson, Anna-Karin; van Niekerk, Dawie; Adiels, Caroline B.; du Preez, Franco B.; Goksör, Mattias; Snoep, Jacky (2012)

From steady-state to synchronized yeast glycolytic oscillations II: model validation. - du Preez, F. B.; van Niekerk, D. D.; Snoep, J. L. (FEBS J, 2012)
In an accompanying paper [du Preez et al., (2012) FEBS J279, 2810-2822], we adapt an existing kinetic model for steady-state yeast glycolysis to simulate limit-cycle oscillations. Here we validate the model by testing its capacity to simulate a wide range of experiments on dynamics of yeast glycolysis. In addition to its description of the oscillations of glycolytic intermediates in intact cells and the rapid synchronization observed when mixing out-of-phase oscillatory cell populations (see accompanying paper), the model was able to predict the Hopf bifurcation diagram with glucose as the bifurcation parameter (and one of the bifurcation points with cyanide as the bifurcation parameter), the glucose- and acetaldehyde-driven forced oscillations, glucose and acetaldehyde quenching, and cell-free extract oscillations (including complex oscillations and mixed-mode oscillations). Thus, the model was compliant, at least qualitatively, with the majority of available experimental data for glycolytic oscillations in yeast. To our knowledge, this is the first time that a model for yeast glycolysis has been tested against such a wide variety of independent data sets. DATABASE: The mathematical models described here have been submitted to the JWS Online Cellular Systems Modelling Database and can be accessed at http://jjj.biochem.sun.ac.za/database/dupreez/index.html.
Keywords: Acetaldehyde/metabolism; Adenosine Triphosphate/metabolism; Cell-Free System/physiology; Cyanides/pharmacology; Glucose/metabolism; *Glycolysis/drug effects; Kinetics; *Models, Biological; NAD/metabolism; Saccharomyces cerevisiae/drug effects/*metabolism; Systems Biology

From steady-state to synchronized yeast glycolytic oscillations I: model construction. - du Preez, F. B.; van Niekerk, D. D.; Kooi, B.; Rohwer, J. M.; Snoep, J. L. (FEBS J, 2012)
An existing detailed kinetic model for the steady-state behavior of yeast glycolysis was tested for its ability to simulate dynamic behavior. Using a small subset of experimental data, the original model was adapted by adjusting its parameter values in three optimization steps. Only small adaptations to the original model were required for realistic simulation of experimental data for limit-cycle oscillations. The greatest changes were required for parameter values for the phosphofructokinase reaction. The importance of ATP for the oscillatory mechanism and NAD(H) for inter-and intra-cellular communications and synchronization was evident in the optimization steps and simulation experiments. In an accompanying paper [du Preez F et al. (2012) FEBS J279, 2823-2836], we validate the model for a wide variety of experiments on oscillatory yeast cells. The results are important for re-use of detailed kinetic models in modular modeling approaches and for approaches such as that used in the Silicon Cell initiative. DATABASE: The mathematical models described here have been submitted to the JWS Online Cellular Systems Modelling Database and can be accessed at http://jjj.biochem.sun.ac.za/database/dupreez/index.html.
Keywords: Acetaldehyde/metabolism; Adenosine Triphosphatases/metabolism; Cell Communication/physiology; Computer Simulation; Databases, Factual; *Glycolysis; Kinetics; Metabolic Networks and Pathways; *Models, Biological; NAD/metabolism; Phosphofructokinases/metabolism; Saccharomyces cerevisiae/*metabolism; Systems Biology

Frequency doubling in the cyanobacterial circadian clock - Martins, Bruno MC; Das, Arijit K; Antunes, Liliana; Locke, James CW (Mol Syst Biol, 2016)
Organisms use circadian clocks to generate 24-h rhythms in gene expression. However, the clock can interact with other pathways to generate shorter period oscillations. It remains unclear how these different frequencies are generated. Here, we examine this problem by studying the coupling of the clock to the alternative sigma factor sigC in the cyanobacterium Synechococcus elongatus. Using single-cell microscopy, we find that psbAI, a key photosyn- thesis gene regulated by both sigC and the clock, is activated with two peaks of gene expression every circadian cycle under constant low light. This two-peak oscillation is dependent on sigC, without which psbAI rhythms revert to one oscillatory peak per day. We also observe two circadian peaks of elongation rate, which are dependent on sigC, suggesting a role for the frequency doubling in modulating growth. We propose that the two-peak rhythm in psbAI expression is generated by an incoherent feedforward loop between the clock, sigC and psbAI. Modelling and experiments suggest that this could be a general network motif to allow frequency doubling of outputs.

Biphasic response as a mechanism against mutant takeover in tissue homeostasis circuits - Karin, Omer; Alon, Uri (Mol Syst Biol, 2017)
Tissues use feedback circuits in which cells send signals to each other to control their growth and survival. We show that such feed- back circuits are inherently unstable to mutants that misread the signal level: Mutants have a growth advantage to take over the tissue, and cannot be eliminated by known cell-intrinsic mecha- nisms. To resolve this, we propose that tissues have biphasic responses in which the signal is toxic at both high and low levels, such as glucotoxicity of beta cells, excitotoxicity in neurons, and toxicity of growth factors to T cells. This gives most of these mutants a frequency-dependent selective disadvantage, which leads to their elimination. However, the biphasic mechanisms create a new unstable fixed point in the feedback circuit beyond which runaway processes can occur, leading to risk of diseases such as diabetes and neurodegenerative disease. Hence, glucotoxicity, which is a dangerous cause of diabetes, may have a protective anti- mutant effect. Biphasic responses in tissues may provide an evolu- tionary stable strategy that avoids invasion by commonly occurring mutants, but at the same time cause vulnerability to disease.

Hepatocytes contribute to residual glucose production in a mouse model for glycogen storage disease type Ia. - Hijmans, B. S.; Boss, A.; van Dijk, T. H.; Soty, M.; Wolters, H.; Mutel, E.; Groen, A. K.; Derks, T. G. J.; Mithieux, G.; Heerschap, A.; Reijngoud, D. J.; Rajas, F.; et al. (Hepatology, 2017)
It is a long-standing enigma how glycogen storage disease (GSD) type I patients retain a limited capacity for endogenous glucose production despite the loss of glucose-6-phosphatase activity. Insight into the source of residual endogenous glucose production is of clinical importance given the risk of sudden death in these patients, but so far contradictory mechanisms have been proposed. We investigated glucose-6-phosphatase-independent endogenous glucose production in hepatocytes isolated from a liver-specific GSD Ia mouse model (L-G6pc(-/-) mice) and performed real-time analysis of hepatic glucose fluxes and glycogen metabolism in L-G6pc(-/-) mice using state-of-the-art stable isotope methodologies. Here we show that G6pc-deficient hepatocytes are capable of producing glucose. In vivo analysis of hepatic glucose metabolism revealed that the hepatic glucokinase flux was decreased by 95% in L-G6pc(-/-) mice. It also showed increased glycogen phosphorylase flux in L-G6pc(-/-) mice, which is coupled to the release of free glucose through glycogen debranching. Although the ex vivo activities of debranching enzyme and lysosomal acid maltase, two major hepatic alpha-glucosidases, were unaltered in L-G6pc(-/-) mice, pharmacological inhibition of alpha-glucosidase activity almost completely abolished residual glucose production by G6pc-deficient hepatocytes. CONCLUSION: Our data indicate that hepatocytes contribute to residual glucose production in GSD Ia. We show that alpha-glucosidase activity, i.e. glycogen debranching and/or lysosomal glycogen breakdown, contributes to residual glucose production by GSD Ia hepatocytes. A strong reduction in hepatic GCK flux in L-G6pc-/- mice furthermore limits the phosphorylation of free glucose synthesized by G6pc-deficient hepatocytes, allowing the release of glucose into the circulation. The almost complete abrogation of GCK flux in G6pc-deficient liver also explains the contradictory reports on residual glucose production in GSD Ia patients. (Hepatology 2017;66:2042-2054).
Keywords: Animals; Disease Models, Animal; Galactose/metabolism; Glucose/*metabolism; Glucose-6-Phosphatase/genetics; Glycerol/metabolism; Glycogen Storage Disease Type I/*metabolism; Hepatocytes/*metabolism; Male; Mice; alpha-Glucosidases/metabolism

A systems study reveals concurrent activation of AMPK and mTOR by amino acids. - Dalle Pezze, P.; Ruf, S.; Sonntag, A. G.; Langelaar-Makkinje, M.; Hall, P.; Heberle, A. M.; Razquin Navas, P.; van Eunen, K.; Tolle, R. C.; Schwarz, J. J.; Wiese, H.; Warscheid, B.; et al. (Nat Commun, 2016)
Amino acids (aa) are not only building blocks for proteins, but also signalling molecules, with the mammalian target of rapamycin complex 1 (mTORC1) acting as a key mediator. However, little is known about whether aa, independently of mTORC1, activate other kinases of the mTOR signalling network. To delineate aa-stimulated mTOR network dynamics, we here combine a computational-experimental approach with text mining-enhanced quantitative proteomics. We report that AMP-activated protein kinase (AMPK), phosphatidylinositide 3-kinase (PI3K) and mTOR complex 2 (mTORC2) are acutely activated by aa-readdition in an mTORC1-independent manner. AMPK activation by aa is mediated by Ca(2+)/calmodulin-dependent protein kinase kinase beta (CaMKKbeta). In response, AMPK impinges on the autophagy regulators Unc-51-like kinase-1 (ULK1) and c-Jun. AMPK is widely recognized as an mTORC1 antagonist that is activated by starvation. We find that aa acutely activate AMPK concurrently with mTOR. We show that AMPK under aa sufficiency acts to sustain autophagy. This may be required to maintain protein homoeostasis and deliver metabolite intermediates for biosynthetic processes.
Keywords: AMP-Activated Protein Kinases/genetics/*metabolism; Amino Acids/*pharmacology; Autophagy-Related Protein-1 Homolog/genetics/metabolism; Calcium-Calmodulin-Dependent Protein Kinase Kinase/metabolism; Cell Line; Gene Expression Regulation/drug effects; Humans; Intracellular Signaling Peptides and Proteins/genetics/metabolism; Mechanistic Target of Rapamycin Complex 1/genetics/*metabolism; Mechanistic Target of Rapamycin Complex 2/genetics/*metabolism; Models, Biological; Phosphatidylinositol 3-Kinases/genetics/metabolism; Proto-Oncogene Proteins c-akt/genetics/metabolism; TOR Serine-Threonine Kinases/genetics/*metabolism

Translational Targeted Proteomics Profiling of Mitochondrial Energy Metabolic Pathways in Mouse and Human Samples. - Wolters, J. C.; Ciapaite, J.; van Eunen, K.; Niezen-Koning, K. E.; Matton, A.; Porte, R. J.; Horvatovich, P.; Bakker, B. M.; Bischoff, R.; Permentier, H. P. (J Proteome Res, 2016)
Absolute measurements of protein abundance are important in the understanding of biological processes and the precise computational modeling of biological pathways. We developed targeted LC-MS/MS assays in the selected reaction monitoring (SRM) mode to quantify over 50 mitochondrial proteins in a single run. The targeted proteins cover the tricarboxylic acid cycle, fatty acid beta-oxidation, oxidative phosphorylation, and the detoxification of reactive oxygen species. Assays used isotopically labeled concatemers as internal standards designed to target murine mitochondrial proteins and their human orthologues. Most assays were also suitable to quantify the corresponding protein orthologues in rats. After exclusion of peptides that did not pass the selection criteria, we arrived at SRM assays for 55 mouse, 52 human, and 51 rat proteins. These assays were optimized in isolated mitochondrial fractions from mouse and rat liver and cultured human fibroblasts and in total liver extracts from mouse, rat, and human. The developed proteomics approach is suitable for the quantification of proteins in the mitochondrial energy metabolic pathways in mice, rats, and humans as a basis for translational research. Initial data show that the assays have great potential for elucidating the adaptive response of human patients to mutations in mitochondrial proteins in a clinical setting.
Keywords: Animals; *Energy Metabolism; Fibroblasts/chemistry/metabolism; Humans; Liver/chemistry/metabolism; Metabolic Networks and Pathways; Mice; Mitochondria/*metabolism; Mitochondrial Proteins; Proteomics/*methods; Rats; Tandem Mass Spectrometry; Translational Research, Biomedical/*methods

Predicting strain engineering strategies using iKS1317: a genome‐scale metabolic model of Streptomyces coelicolor - Kumelj, Tjasa; Sulheim, Snorre; Wentzel, Alexander; Almaas, Eivind (Biotechnol. J., 2018)

NAD + Replenishment Improves Lifespan and Healthspan in Ataxia Telangiectasia Models via Mitophagy and DNA Repair - Fang, Evandro Fei; Kassahun, Henok; Croteau, Deborah L.; Scheibye-Knudsen, Morten; Marosi, Krisztina; Lu, Huiming; Shamanna, Raghavendra A.; Kalyanasundaram, Sumana; Bollineni, Ravi Chand; Wilson, Mark A.; Iser, Wendy B.; Wollman, Bradley N.; et al. (Cell Metabolism, 2016)
Ataxia telangiectasia (A-T) is a rare autosomal recessive disease characterized by progressive neurodegeneration and cerebellar ataxia. A-T is causally linked to defects in ATM, a master regulator of the response to and repair of DNA double-strand breaks. The molecular basis of cerebellar atrophy and neurodegeneration in A-T patients is unclear. Here we report and examine the significance of increased PARylation, low NAD+, and mitochondrial dysfunction in ATM-deficient neurons, mice, and worms. Treatments that replenish intracellular NAD+ reduce the severity of A-T neuropathology, normalize neuromuscular function, delay memory loss, and extend lifespan in both animal models. Mechanistically, treatments that increase intracellular NAD+ also stimulate neuronal DNA repair and improve mitochondrial quality via mitophagy. This work links two major theories on aging, DNA damage accumulation, and mitochondrial dysfunction through nuclear DNA damage-induced nuclear-mitochondrial signaling, and demonstrates that they are important pathophysiological determinants in premature aging of A-T, pointing to therapeutic interventions.

Rev1 contributes to proper mitochondrial function via the PARP-NAD+-SIRT1-PGC1α axis - Fakouri, Nima Borhan; Durhuus, Jon Ambæk; Regnell, Christine Elisabeth; Angleys, Maria; Desler, Claus; Hasan-Olive, Md Mahdi; Martín-Pardillos, Ana; Tsaalbi-Shtylik, Anastasia; Thomsen, Kirsten; Lauritzen, Martin; Bohr, Vilhelm A.; de Wind, Niels; et al. (Sci Rep, 2017)
Nucleic acids, which constitute the genetic material of all organisms, are continuously exposed to endogenous and exogenous damaging agents, representing a significant challenge to genome stability and genome integrity over the life of a cell or organism. Unrepaired DNA lesions, such as single- and double-stranded DNA breaks (SSBs and DSBs), and single-stranded gaps can block progression of the DNA replication fork, causing replicative stress and/or cell cycle arrest. However, translesion synthesis (TLS) DNA polymerases, such as Rev1, have the ability to bypass some DNA lesions, which can circumvent the process leading to replication fork arrest and minimize replicative stress. Here, we show that Rev1-deficiency in mouse embryo fibroblasts or mouse liver tissue is associated with replicative stress and mitochondrial dysfunction. In addition, Rev1-deficiency is associated with high poly(ADP) ribose polymerase 1 (PARP1) activity, low endogenous NAD+, low expression of SIRT1 and PGC1α and low adenosine monophosphate (AMP)-activated kinase (AMPK) activity. We conclude that replication stress via Rev1-deficiency contributes to metabolic stress caused by compromized mitochondrial function via the PARP-NAD+-SIRT1-PGC1α axis.

Draft genome sequence of the docosahexaenoic acid producing thraustochytrid Aurantiochytrium sp. T66. - Liu, B.; Ertesvag, H.; Aasen, I. M.; Vadstein, O.; Brautaset, T.; Heggeset, T. M. (Genom Data, 2016)
Thraustochytrids are unicellular, marine protists, and there is a growing industrial interest in these organisms, particularly because some species, including strains belonging to the genus Aurantiochytrium, accumulate high levels of docosahexaenoic acid (DHA). Here, we report the draft genome sequence of Aurantiochytrium sp. T66 (ATCC PRA-276), with a size of 43 Mbp, and 11,683 predicted protein-coding sequences. The data has been deposited at DDBJ/EMBL/Genbank under the accession LNGJ00000000. The genome sequence will contribute new insight into DHA biosynthesis and regulation, providing a basis for metabolic engineering of thraustochytrids.

Atlantic salmon raised with diets low in long-chain polyunsaturated n-3 fatty acids in freshwater have a Mycoplasma-dominated gut microbiota at sea - Jin, Yang; Angell, Inga Leena; Simen, Sandve; Snipen, Lars; Olsen, Y; Rudi, knut (Aquacult. Environ. Interact., 2019)
Factors affecting the establishment of the gut microbiota in animals living in marine environments remain largely unknown. In terrestrial animals, however, it is well established that the juvenile environment has a major impact on the gut microbiota later in life. Atlantic salmon Salmo salar is an anadromous fish important in aquaculture with a juvenile freshwater stage and an adult seawater stage. For wild salmon, there are major dietary changes with respect to availability of long-chain polyunsaturated n-3 fatty acids (LC-n-3 PUFA) with lower abundance in freshwater systems. The aim of our work was therefore to determine the effect of a juvenile freshwater diet with high LC-n-3 PUFA, as compared to a diet low in LC-n-3 PUFA (designed to increase the endogenous LC-n-3 PUFA production), on the transition to a seawater gut microbiota for Atlantic salmon. We found a juvenile freshwater microbiota high in Firmicutes for fish raised with low LC-n-3 PUFA, while the microbiota for fish given high LC-n-3 PUFA feed was high in Proteobacteria. One hundred days after transfer to a common sea cage, fish that were given low LC-n-3 PUFA diets in freshwater showed significantly higher (p = 0.02, Kruskal-Wallis) Mycoplasma content (90 ± 7%; mean ± SD) compared to fish raised on a high LC-n-3 PUFA diet in freshwater (25 ± 31% Mycoplasma). Shotgun metagenome sequencing from fish raised with a low LC-n-3 PUFA diet identified a salmon-associated Mycoplasma in sea, being distinct from currently known Mycoplasma. The genome sequence information indicated a mutualistic lifestyle of this bacterium. Mycoplasma has also previously been identified as dominant (>70%) in sea-living adult Atlantic salmon. Taken together, our results suggest that the juvenile freshwater diet influences the establishment of the gut microbiota in marine Atlantic salmon.

In situ esterification and extractive fermentation for butyl butyrate production with Clostridium tyrobutyricum. - Zhang, Z. T.; Taylor, S.; Wang, Y. (Biotechnol Bioeng, 2017)
Butyl butyrate (BB) is a valuable chemical that can be used as flavor, fragrance, extractant, and so on in various industries. Meanwhile, BB can also be used as a fuel source with excellent compatibility as gasoline, aviation kerosene, and diesel components. The conventional industrial production of BB is highly energy-consuming and generates various environmental pollutants. Recently, there have been tremendous interests in producing BB from renewable resources through biological routes. In this study, based on the fermentation using the hyper-butyrate producing strain Clostridium tyrobutyricum ATCC 25755, efficient BB production through in situ esterification was achieved by supplementation of lipase and butanol into the fermentation. Three commercially available lipases were assessed and the one from Candida sp. (recombinant, expressed in Aspergillus niger) was identified with highest catalytic activity for BB production. Various conditions that might affect BB production in the fermentation have been further evaluated, including the extractant type, enzyme loading, agitation, pH, and butanol supplementation strategy. Under the optimized conditions (5.0 g L(-1) of enzyme loading, pH at 5.5, butanol kept at 10.0 g L(-1) ), 34.7 g L(-1) BB was obtained with complete consumption of 50 g L(-1) glucose as the starting substrate. To our best knowledge, the BB production achieved in this study is the highest among the ever reported from the batch fermentation process. Our results demonstrated an excellent biological platform for renewable BB production from low-value carbon sources. Biotechnol. Bioeng. 2017;114: 1428-1437. (c) 2017 Wiley Periodicals, Inc.
Keywords: Batch Cell Culture Techniques/methods; Bioreactors/*microbiology; Butanols/*metabolism; Butyrates/chemistry/*isolation & purification/*metabolism; Clostridium tyrobutyricum/*physiology; Conservation of Natural Resources/methods; Esterification/physiology; Fermentation; Lipase/*metabolism; Liquid-Liquid Extraction/methods

Simultaneous Clostridial fermentation, lipase-catalyzed esterification, and ester extraction to enrich diesel with butyl butyrate. - van den Berg, C.; Heeres, A. S.; van der Wielen, L. A.; Straathof, A. J. (Biotechnol Bioeng, 2013)
The recovery of 1-butanol from fermentation broth is energy-intensive since typical concentrations in fermentation broth are below 20 g L(-1). To prevent butanol inhibition and high downstream processing costs, we aimed at producing butyl esters instead of 1-butanol. It is shown that it is possible to perform simultaneously clostridial fermentation, esterification of the formed butanol to butyl butyrate, and extraction of this ester by hexadecane. The very high partition coefficient of butyl butyrate pulls the esterification towards the product side even at fermentation pH and relatively low butanol concentrations. The hexadecane extractant is a model diesel compound and is nontoxic to the cells. If butyl butyrate enriched diesel can directly be used as car fuel, no product recovery is required. A proof-of-principle experiment for the one-pot bio-ester production from glucose led to 5 g L(-1) butyl butyrate in the hexadecane phase. The principle may be extended to a wide range of esters, especially to longer chain ones.
Keywords: *Biofuels; Bioreactors/microbiology; Butanols/metabolism; Butyrates/chemistry/*metabolism; Clostridium/*metabolism; Esterification; Fermentation; Gasoline; Glucose/metabolism; Lipase/*metabolism

Harmonizing semantic annotations for computational models in biology - Neal, Maxwell Lewis; König, Matthias; Nickerson, David; Mısırlı, Göksel; Kalbasi, Reza; Dräger, Andreas; Atalag, Koray; Chelliah, Vijayalakshmi; Cooling, Michael T; Cook, Daniel L; Crook, Sharon; de Alba, Miguel; et al. (Briefings in Bioinformatics, 2019)
Life science researchers use computational models to articulate and test hypotheses about the behavior of biological systems. Semantic annotation is a critical component for enhancing the interoperability and reusability of such models as well as for the integration of the data needed for model parameterization and validation. Encoded as machine-readable links to knowledge resource terms, semantic annotations describe the computational or biological meaning of what models and data represent. These annotations help researchers find and repurpose models, accelerate model composition and enable knowledge integration across model repositories and experimental data stores. However, realizing the potential benefits of semantic annotation requires the development of model annotation standards that adhere to a community-based annotation protocol. Without such standards, tool developers must account for a variety of annotation formats and approaches, a situation that can become prohibitively cumbersome and which can defeat the purpose of linking model elements to controlled knowledge resource terms. Currently, no consensus protocol for semantic annotation exists among the larger biological modeling community. Here, we report on the landscape of current annotation practices among the COmputational Modeling in BIology NEtwork community and provide a set of recommendations for building a consensus approach to semantic annotation.

Specifications of Standards in Systems and Synthetic Biology: Status and Developments in 2017 - Schreiber, Falk; Bader, Gary D.; Gleeson, Padraig; Golebiewski, Martin; Hucka, Mike; Keating, Sarah M.; Novère, Nicolas Le; Myers, Chris; Nickerson, David; Sommer, Björn; Waltemath, Dagmar (Journal of Integrative Bioinformatics, 2018)

The FAIR Guiding Principles for scientific data management and stewardship - Wilkinson, Mark D.; Dumontier, Michel; Aalbersberg, IJsbrand Jan; Appleton, Gabrielle; Axton, Myles; Baak, Arie; Blomberg, Niklas; Boiten, Jan-Willem; da Silva Santos, Luiz Bonino; Bourne, Philip E.; Bouwman, Jildau; Brookes, Anthony J.; et al. (Sci. Data, 2016)

Phosphoglycerate kinase acts as a futile cycle at high temperature. - Kouril, T.; Eicher, J. J.; Siebers, B.; Snoep, J. L. (Microbiology (Reading), 2017)
In (hyper)thermophilic organisms metabolic processes have to be adapted to function optimally at high temperature. We compared the gluconeogenic conversion of 3-phosphoglycerate via 1,3-bisphosphoglycerate to glyceraldehyde-3-phosphate at 30 degrees C and at 70 degrees C. At 30 degrees C it was possible to produce 1,3-bisphosphoglycerate from 3-phosphoglycerate with phosphoglycerate kinase, but at 70 degrees C, 1,3-bisphosphoglycerate was dephosphorylated rapidly to 3-phosphoglycerate, effectively turning the phosphoglycerate kinase into a futile cycle. When phosphoglycerate kinase was incubated together with glyceraldehyde 3-phosphate dehydrogenase it was possible to convert 3-phosphoglycerate to glyceraldehyde 3-phosphate, both at 30 degrees C and at 70 degrees C, however, at 70 degrees C only low concentrations of product were observed due to thermal instability of glyceraldehyde 3-phosphate. Thus, thermolabile intermediates challenge central metabolic reactions and require special adaptation strategies for life at high temperature.
Keywords: Enzyme Stability; Gluconeogenesis; Glyceraldehyde 3-Phosphate/*metabolism; Glyceraldehyde-3-Phosphate Dehydrogenases/chemistry/*metabolism; Glyceric Acids/metabolism; Half-Life; *Hot Temperature; Kinetics; Models, Statistical; Phosphoglycerate Kinase/chemistry/*metabolism; Recombinant Proteins/chemistry/metabolism; Saccharomyces cerevisiae/enzymology; Substrate Cycling/physiology; Sulfolobus solfataricus/*enzymology; Thermodynamics

The Carbon Switch at the Level of Pyruvate and Phosphoenolpyruvate in Sulfolobus solfataricus P2. - Haferkamp, P.; Tjaden, B.; Shen, L.; Brasen, C.; Kouril, T.; Siebers, B. (Front Microbiol, 2019)
Sulfolobus solfataricus P2 grows on different carbohydrates as well as alcohols, peptides and amino acids. Carbohydrates such as D-glucose or D-galactose are degraded via the modified, branched Entner-Doudoroff (ED) pathway whereas growth on peptides requires the Embden-Meyerhof-Parnas (EMP) pathway for gluconeogenesis. As for most hyperthermophilic Archaea an important control point is established at the level of triosephophate conversion, however, the regulation at the level of pyruvate/phosphoenolpyruvate conversion was not tackled so far. Here we describe the cloning, expression, purification and characterization of the pyruvate kinase (PK, SSO0981) and the phosphoenolpyruvate synthetase (PEPS, SSO0883) of Sul. solfataricus. The PK showed only catabolic activity [catalytic efficiency (PEP): 627.95 mM(-1)s(-1), 70 degrees C] with phosphoenolpyruvate as substrate and ADP as phosphate acceptor and was allosterically inhibited by ATP and isocitrate (K (i) 0.8 mM). The PEPS was reversible, however, exhibited preferred activity in the gluconeogenic direction [catalytic efficiency (pyruvate): 1.04 mM(-1)s(-1), 70 degrees C] and showed some inhibition by AMP and alpha-ketoglutarate. The gene SSO2829 annotated as PEPS/pyruvate:phosphate dikinase (PPDK) revealed neither PEPS nor PPDK activity. Our studies suggest that the energy charge of the cell as well as the availability of building blocks in the citric acid cycle and the carbon/nitrogen balance plays a major role in the Sul. solfataricus carbon switch. The comparison of regulatory features of well-studied hyperthermophilic Archaea reveals a close link and sophisticated coordination between the respective sugar kinases and the kinetic and regulatory properties of the enzymes at the level of PEP-pyruvate conversion.

Mechanistic model of temperature influence on flowering through whole-plant accumulation of FT - Kinmonth-Schultz, Hannah A; MacEwen, Melissa J; Seaton, Daniel; Millar, Andrew; Imaizumi, Takato; Kim, Soo-Hyung
BioRxiv preprint:

Subcellular Distribution of NAD+ between Cytosol and Mitochondria Determines the Metabolic Profile of Human Cells. - VanLinden, M. R.; Dolle, C.; Pettersen, I. K.; Kulikova, V. A.; Niere, M.; Agrimi, G.; Dyrstad, S. E.; Palmieri, F.; Nikiforov, A. A.; Tronstad, K. J.; Ziegler, M. (J Biol Chem, 2015)
The mitochondrial NAD pool is particularly important for the maintenance of vital cellular functions. Although at least in some fungi and plants, mitochondrial NAD is imported from the cytosol by carrier proteins, in mammals, the mechanism of how this organellar pool is generated has remained obscure. A transporter mediating NAD import into mammalian mitochondria has not been identified. In contrast, human recombinant NMNAT3 localizes to the mitochondrial matrix and is able to catalyze NAD(+) biosynthesis in vitro. However, whether the endogenous NMNAT3 protein is functionally effective at generating NAD(+) in mitochondria of intact human cells still remains to be demonstrated. To modulate mitochondrial NAD(+) content, we have expressed plant and yeast mitochondrial NAD(+) carriers in human cells and observed a profound increase in mitochondrial NAD(+). None of the closest human homologs of these carriers had any detectable effect on mitochondrial NAD(+) content. Surprisingly, constitutive redistribution of NAD(+) from the cytosol to the mitochondria by stable expression of the Arabidopsis thaliana mitochondrial NAD(+) transporter NDT2 in HEK293 cells resulted in dramatic growth retardation and a metabolic shift from oxidative phosphorylation to glycolysis, despite the elevated mitochondrial NAD(+) levels. These results suggest that a mitochondrial NAD(+) transporter, similar to the known one from A. thaliana, is likely absent and could even be harmful in human cells. We provide further support for the alternative possibility, namely intramitochondrial NAD(+) synthesis, by demonstrating the presence of endogenous NMNAT3 in the mitochondria of human cells.
Keywords: Amino Acid Sequence; Arabidopsis Proteins/chemistry/genetics/metabolism; Biological Transport; Carrier Proteins/chemistry/genetics/*metabolism; Cytosol/*metabolism; Glycolysis; HEK293 Cells; Humans; *Metabolome; Mitochondria/*metabolism; Mitochondrial Proteins; Molecular Sequence Data; NAD/*metabolism; Nicotinamide-Nucleotide Adenylyltransferase/chemistry/genetics/metabolism; Nucleotide Transport Proteins; Organic Cation Transport Proteins/chemistry/genetics/metabolism; Recombinant Proteins/chemistry/genetics/metabolism; Saccharomyces cerevisiae Proteins/chemistry/genetics/metabolism

Molecular basis of flowering under natural long-day conditions in Arabidopsis. - Song, Y. H.; Kubota, A.; Kwon, M. S.; Covington, M. F.; Lee, N.; Taagen, E. R.; Laboy Cintron, D.; Hwang, D. Y.; Akiyama, R.; Hodge, S. K.; Huang, H.; Nguyen, N. H.; et al. (Nat Plants, 2018)
Plants sense light and temperature changes to regulate flowering time. Here, we show that expression of the Arabidopsis florigen gene, FLOWERING LOCUS T (FT), peaks in the morning during spring, a different pattern than we observe in the laboratory. Providing our laboratory growth conditions with a red/far-red light ratio similar to open-field conditions and daily temperature oscillation is sufficient to mimic the FT expression and flowering time in natural long days. Under the adjusted growth conditions, key light signalling components, such as phytochrome A and EARLY FLOWERING 3, play important roles in morning FT expression. These conditions stabilize CONSTANS protein, a major FT activator, in the morning, which is probably a critical mechanism for photoperiodic flowering in nature. Refining the parameters of our standard growth conditions to more precisely mimic plant responses in nature can provide a powerful method for improving our understanding of seasonal response.
Keywords: Arabidopsis/*growth & development/metabolism; Arabidopsis Proteins/metabolism; DNA-Binding Proteins/metabolism; Flowers/*growth & development/metabolism; Gene Expression Regulation, Plant; Light; *Photoperiod; Phytochrome A/metabolism; Time Factors; Transcription Factors/metabolism

Circadian protein regulation in the green lineage I. A phospho-dawn anticipates light onset before proteins peak in daytime. - Noordally, Zeenat B.; Hindle, Matthew M.; Martin, Sarah F.; Seaton, Daniel; Simpson, Ian; Le Bihan, Thierry; Millar, Andrew
BioRxiv preprint, 4 April 2018. Abstract: Daily light-dark cycles (LD) drive dynamic regulation of plant and algal transcriptomes via photoreceptor pathways and 24-hour, circadian rhythms. Diel regulation of protein levels and modifications has been less studied. Ostreococcus tauri, the smallest free-living eukaryote, provides a minimal model proteome for the green lineage. Here, we compare transcriptome data under LD to the algal proteome and phosphoproteome, assayed using shotgun mass-spectrometry. Under 10% of 855 quantified proteins were rhythmic but two-thirds of 860 phosphoproteins showed rhythmic modification(s). Most rhythmic proteins peaked in the daytime. Model simulations showed that light-stimulated protein synthesis largely accounts for this distribution of protein peaks. Prompted by apparently dark-stable proteins, we sampled during prolonged dark adaptation, where stable RNAs and very limited change to the proteome suggested a quiescent, cellular “dark state”. In LD, acid-directed and proline-directed protein phosphorylation sites were regulated in antiphase. Strikingly, 39% of rhythmic phospho-sites reached peak levels just before dawn. This anticipatory phosphorylation is distinct from light-responsive translation but consistent with plant phosphoprotein profiles, suggesting that a clock-regulated phospho-dawn prepares green cells for daytime functions.

Human iPSC-derived RPE and retinal organoids reveal impaired alternative splicing of genes involved in pre-mRNA splicing in PRPF31 autosomal dominant retinitis pigmentosa - Buskin, Adriana; Zhu, Lili; Chichagova, Valeria; Basu, Basudha; Mozaffari-Jovin, Sina; Dolan, David; Droop, Alastair; Collin, Joseph; Bronstein, Revital; Mehrotra, Sudeep; Farkas, Michael; Hilgen, Gerrit; et al.
Mutations in pre-mRNA processing factors (PRPFs) cause 40% of autosomal dominant retinitis pigmentosa (RP), but it is unclear why mutations in ubiquitously expressed PRPFs cause retinal disease. To understand the molecular basis of this phenotype, we have generated RP type 11 (PRPF31-mutated) patient-specific retinal organoids and retinal pigment epithelium (RPE) from induced pluripotent stem cells (iPSC). Impaired alternative splicing of genes encoding pre-mRNA splicing proteins occurred in patient-specific retinal cells and Prpf31+/− mouse retinae, but not fibroblasts and iPSCs, providing mechanistic insights into retinal-specific phenotypes of PRPFs. RPE was the most affected, characterised by loss of apical-basal polarity, reduced trans-epithelial resistance, phagocytic capacity, microvilli, and cilia length and incidence. Disrupted cilia morphology was observed in patient-derived-photoreceptors that displayed progressive features associated with degeneration and cell stress. In situ gene-editing of a pathogenic mutation rescued key structural and functional phenotypes in RPE and photoreceptors, providing proof-of-concept for future therapeutic strategies.

Delivering on open data: Current practices in data sharing, and challenges ahead! - Oefelein, Timon (Septentrio Conference Series, 2018)

CRISPR/Cas9-mediated ablation of elovl2 in Atlantic salmon (Salmo salar L.) inhibits elongation of polyunsaturated fatty acids and induces Srebp-1 and target genes - Datsomor, Alex K.; Zic, Nikola; Li, Keshuai; Olsen, Rolf E.; Jin, Yang; Vik, Jon Olav; Edvardsen, Rolf B.; Grammes, Fabian; Wargelius, Anna; Winge, Per (Sci Rep, 2019)
Atlantic salmon can synthesize polyunsaturated fatty acids (PUFAs), such as eicosapentaenoic acid (20:5n-3), arachidonic acid (20:4n-6) and docosahexaenoic acid (22:6n-3) via activities of very long chain fatty acyl elongases (Elovls) and fatty acyl desaturases (Fads), albeit to a limited degree. Understanding molecular mechanisms of PUFA biosynthesis and regulation is a pre-requisite for sustainable use of vegetable oils in aquafeeds as current sources of fish oils are unable to meet increasing demands for omega-3 PUFAs. By generating CRISPR-mediated elovl2 partial knockout (KO), we have shown that elovl2 is crucial for multi-tissue synthesis of 22:6n-3 in vivo and that endogenously synthesized PUFAs are important for transcriptional regulation of lipogenic genes in Atlantic salmon. The elovl2-KOs showed reduced levels of 22:6n-3 and accumulation of 20:5n-3 and docosapentaenoic acid (22:5n-3) in the liver, brain and white muscle, suggesting inhibition of elongation. Additionally, elovl2-KO salmon showed accumulation of 20:4n-6 in brain and white muscle. The impaired synthesis of 22:6n-3 induced hepatic expression of sterol regulatory element binding protein-1 (srebp-1), fatty acid synthase-b, Δ6fad-a, Δ5fad and elovl5. Our study demonstrates key roles of elovl2 at two penultimate steps of PUFA synthesis in vivo and suggests Srebp-1 as a main regulator of endogenous PUFA synthesis in Atlantic salmon.

Living on the edge: substrate competition explains loss of robustness in mitochondrial fatty-acid oxidation disorders. - van Eunen, K.; Volker-Touw, C. M.; Gerding, A.; Bleeker, A.; Wolters, J. C.; van Rijt, W. J.; Martines, A. M.; Niezen-Koning, K. E.; Heiner, R. M.; Permentier, H.; Groen, A. K.; Reijngoud, D. J.; et al. (BMC Biol, 2016)
BACKGROUND: Defects in genes involved in mitochondrial fatty-acid oxidation (mFAO) reduce the ability of patients to cope with metabolic challenges. mFAO enzymes accept multiple substrates of different chain length, leading to molecular competition among the substrates. Here, we combined computational modeling with quantitative mouse and patient data to investigate whether substrate competition affects pathway robustness in mFAO disorders. RESULTS: First, we used comprehensive biochemical analyses of wild-type mice and mice deficient for medium-chain acyl-CoA dehydrogenase (MCAD) to parameterize a detailed computational model of mFAO. Model simulations predicted that MCAD deficiency would have no effect on the pathway flux at low concentrations of the mFAO substrate palmitoyl-CoA. However, high concentrations of palmitoyl-CoA would induce a decline in flux and an accumulation of intermediate metabolites. We proved computationally that the predicted overload behavior was due to substrate competition in the pathway. Second, to study the clinical relevance of this mechanism, we used patients' metabolite profiles and generated a humanized version of the computational model. While molecular competition did not affect the plasma metabolite profiles during MCAD deficiency, it was a key factor in explaining the characteristic acylcarnitine profiles of multiple acyl-CoA dehydrogenase deficient patients. The patient-specific computational models allowed us to predict the severity of the disease phenotype, providing a proof of principle for the systems medicine approach. CONCLUSION: We conclude that substrate competition is at the basis of the physiology seen in patients with mFAO disorders, a finding that may explain why these patients run a risk of a life-threatening metabolic catastrophe.
Keywords: Acyl-CoA Dehydrogenase/*deficiency/genetics/metabolism; Animals; Carnitine/analogs & derivatives/metabolism; Computational Biology; Computer Simulation; Disease Models, Animal; Fatty Acids/metabolism; Humans; Lipid Metabolism/*genetics; Lipid Metabolism, Inborn Errors/*genetics/metabolism; Male; Metabolic Networks and Pathways; Mice; Mice, Inbred C57BL; Mice, Knockout; Mitochondria/*metabolism; Oxidation-Reduction; Proteomics; Substrate Specificity

Aldolase-Catalyzed Asymmetric Synthesis of N-Heterocycles by Addition of Simple Aliphatic Nucleophiles to Aminoaldehydes - Roldán, Raquel; Hernández, Karel; Joglar, Jesús; Bujons, Jordi; Parella, Teodor; Fessner, Wolf Dieter; Clapés, Pere (Adv. Synth. Catal., 2019)
Nitrogen heterocycles are structural motifs found in many bioactive natural products and of utmost importance in pharmaceutical drug development. In this work, a stereoselective synthesis of functionalized N‐heterocycles was accomplished in two steps, comprising the biocatalytic aldol addition of ethanal and simple aliphatic ketones such as propanone, butanone, 3‐pentanone, cyclobutanone, and cyclopentanone to N‐Cbz‐protected aminoaldehydes using engineered variants of d‐fructose‐6‐phosphate aldolase from Escherichia coli (FSA) or 2‐deoxy‐d‐ribose‐5‐phosphate aldolase from Thermotoga maritima (DERATma) as catalysts. FSA catalyzed most of the additions of ketones while DERATma was restricted to ethanal and propanone. Subsequent treatment with hydrogen in the presence of palladium over charcoal, yielded low‐level oxygenated N‐heterocyclic derivatives of piperidine, pyrrolidine and N‐bicyclic structures bearing fused cyclobutane and cyclopentane rings, with stereoselectivities of 96–98 ee and 97:3 dr in isolated yields ranging from 35 to 79%.

Second-Generation Engineering of a Thermostable Transketolase (TK Gst ) for Aliphatic Aldehyde Acceptors with Either Improved or Reversed Stereoselectivity - Zhou, Chaoqiang; Saravanan, Thangavelu; Lorillière, Marion; Wei, Dongzhi; Charmantray, Franck; Hecquet, Laurence; Fessner, Wolf Dieter; Yi, Dong (ChemBioChem, 2017)
The transketolase from Geobacillus stearothermophilus (TKGst) is a thermostable enzyme with notable high activity and stability at elevated temperatures, but it accepts non‐α‐hydroxylated aldehydes only with low efficiency. Here we report a protein engineering study of TKGst based on double‐site saturation mutagenesis either at Leu191 or at Phe435 in combination with Asp470; these are the residues responsible for substrate binding in the active site. Screening of the mutagenesis libraries resulted in several positive variants with activity towards propanal up to 7.4 times higher than that of the wild type. Variants F435L/D470E and L191V/D470I exhibited improved (73 % ee, 3S) and inverted (74 % ee, 3R) stereoselectivity, respectively, for propanal. L191V, L382F/E, F435L, and D470/D470I were concluded to be positive mutations at Leu191, Leu382, Phe435, and Asp470 both for activity and for stereoselectivity improvement. These results should benefit further engineering of TKGst for various applications in asymmetric carboligation.

One‐Pot Cascade Synthesis of (3S)‐Hydroxyketones Catalyzed by Transketolase via Hydroxypyruvate Generated in Situ from d‐Serine by d‐Amino Acid Oxidase (Volume361, Issue11 Special Issue: Biocatalysis, Pages 2550-2558, 2019)
We described an efficient in situ generation of hydroxypyruvate from d‐serine catalyzed by a d‐amino acid oxidase from Rhodotorula gracilis. This strategy revealed an interesting alternative to the conventional chemical synthesis of hydroxypyruvate starting from toxic bromopyruvate or to the enzymatic transamination from l‐serine requiring an additional substrate as amino acceptor. Hydroxypyruvate thus produced was used as donor substrate of transketolases from Escherichia coli or from Geobacillus stearothermophilus catalyzing the stereoselective formation of a carbon−carbon bond. The enzymatic cascade reaction was performed in one‐pot in the presence of d‐serine and appropriate aldehydes for the synthesis of valuable (3S)‐hydroxyketones, which were obtained with high enantio‐ and diastereoselectivity and in good yield. The efficiency of the process was based on the irreversibility of both reactions allowing complete conversion of d‐serine and aldehydes.

Chemoenzymatic Hydroxymethylation of Carboxylic Acids by Tandem Stereodivergent Biocatalytic Aldol Reaction and Chemical Decarboxylation - Marín-Valls, Roser; Hernández, Karel; Bolte, Michael; Joglar, Jesús; Bujons, Jordi; Clapés, Pere (ACS Catal., 2019)
Chiral 2-substituted 3-hydroxycarboxylic acid derivatives are valuable building blocks for the preparation of naturally occurring and synthetic biologically active molecules. Current methodologies for the preparation of these compounds are still limited for large-scale production due to the high costs, limited microbial strains, low yields, difficult downstream processing, and limited range of structures. We report an effective chemoenzymatic method for the synthesis of enantiomerically pure 2 substituted 3 hydroxycarboxylic esters. The strategy comprises: i) a stereoselective aldol addition of 2 oxoacids to methanal catalyzed by two enantiocomplementary 2 oxoacid aldolases, ii) oxidative decarboxylation, and iii) esterification. Compounds with S-configuration were obtained in 69-80% isolated yields (94-99% ee), and the R enantiomers in 57-88% (88-95% ee), using a substrate concentration range of 0.1-1.0 M. The method developed offers a versatile alternative route to this important class of chiral building blocks, and highlights the exciting opportunities available for using natural enzymes with minimal active site modification.

Diastereoselective synthesis of vicinal amino alcohols - Karjalainen, Oskari K.; Koskinen, Ari M. P. (Org. Biomol. Chem., 2012)
The vicinal amino alcohol is a common motif in natural products and pharmaceuticals. Amino acidsconstitute a natural, inexpensive, and enantiopure choice of starting material for the synthesis of suchfunctionalities. However, the matters concerning diastereoselectivity are not obvious. This Perspectivetakes a look in thefield of diastereoselective synthesis of vicinal amino alcohols starting from amino acidsusing various methods. https://pubs.rsc.org/en/content/articlepdf/2012/ob/c2ob25357g

Contaminant accumulation and biological responses in Atlantic cod (Gadus morhua) caged at a capped waste disposal site in Kollevag, Western Norway. - Dale, K.; Muller, M. B.; Tairova, Z.; Khan, E. A.; Hatlen, K.; Grung, M.; Yadetie, F.; Lille-Langoy, R.; Blaser, N.; Skaug, H. J.; Lyche, J. L.; Arukwe, A.; et al. (Mar Environ Res, 2019)
The aim of this study was to assess whether fish in Kollevag, a sheltered bay on the western coast of Norway, previously utilized as a waste disposal site, could be affected by environmental contaminants leaking from the waste. Farmed, juvenile Atlantic cod (Gadus morhua) were caged for six weeks at three different locations in Kollevag bay and at one reference location. Sediments and cod samples (bile and liver) were analyzed for polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs), brominated flame retardants (BFRs), per-and polyfluoroalkyl substances (PFASs) and polycyclic aromatic hydrocarbon (PAH) metabolites, revealing a contamination gradient at the four stations. Furthermore, hepatosomatic index (HSI) and Fulton's condition factor (CF) were significantly lower in cod caged closest to the disposal site. Levels and activities of biomarker proteins, such as vitellogenin (Vtg), metallothionein (Mt), and biotransformation and oxidative stress enzymes, including cytochrome P450 1a and 3a (Cyp1a, Cyp3a), glutathione s-transferase (Gst) and catalase (Cat), were quantified in blood plasma and liver tissue. Hepatic Cat and Gst activities were significantly reduced in cod caged at the innermost stations in Kollevag, indicating modulation of oxidative stress responses. However, these results contrasted with reduced hepatic lipid peroxidation. Significant increases in transcript levels were observed for genes involved in lipid metabolism (fasn and acly) in cod liver, while transcript levels of ovarian steroidogenic enzyme genes such as p450scc, cyp19, 3beta-hsd and 20beta-hsd showed significant station-dependent increases. Cyp1a and Vtg protein levels were however not significantly altered in cod caged in Kollevag. Plasma levels of estradiol (E2) and testosterone (T) were determined by enzyme immunoassay (EIA) and showed elevated E2 levels, but only at the innermost station. We conclude that the bay of Kollevag did not fullfill adequate environmental condition based on environmental quality standards (EQSs) for chemicals in coastal waters. Following a six weeks caging period, environmental contaminants accumulated in cod tissues and effects were observed on biomarker responses, especially those involved in reproductive processes in cod ovary.
Keywords: Animals; Environmental Monitoring; Female; *Gadus morhua/physiology; Norway; Tissue Distribution; *Waste Disposal Facilities; *Water Pollutants, Chemical/pharmacokinetics

Modulation of Neuro-Dopamine Homeostasis in Juvenile Female Atlantic Cod ( Gadus morhua) Exposed to Polycyclic Aromatic Hydrocarbons and Perfluoroalkyl Substances. - Khan, E. A.; Bertotto, L. B.; Dale, K.; Lille-Langoy, R.; Yadetie, F.; Karlsen, O. A.; Goksoyr, A.; Schlenk, D.; Arukwe, A. (Environ Sci Technol, 2019)
The dopaminergic effect of PAH and PFAS mixtures, prepared according to environmentally relevant concentrations, has been studied in juvenile female Atlantic cod ( Gadus morhua). Benzo[a]pyrene, dibenzothiophene, fluorene, naphthalene, phenanthrene, and pyrene were used to prepare a PAH mixture, while PFNA, PFOA, PFOS, and PFTrA were used to prepare a PFAS mixture. Cod were injected intraperitoneally twice, with either a low (1x) or high (20x) dose of each compound mixture or their combinations. After 2 weeks of exposure, levels of plasma 17beta-estradiol (E2) were significantly elevated in high PAH/high PFAS treated group. Brain dopamine/metabolite ratios (DOPAC/dopamine and HVA+DOPAC/dopamine) changed with E2 plasma levels, except for high PAH/low PFAS and low PAH/high PFAS treated groups. On the transcript levels, th mRNA inversely correlated with dopamine/metabolite ratios and gnrh2 mRNA levels. Respective decreases and increases of drd1 and drd2a after exposure to the high PAH dose were observed. Specifically, high PFAS exposure decreased both drds, leading to high plasma E2 concentrations. Other studied end points suggest that these compounds, at different doses and combinations, have different toxicity threshold and modes of action. These effects indicate potential alterations in the feedback signaling processes within the dopaminergic pathway by these contaminant mixtures.
Keywords: Animals; Dopamine; Female; *Fluorocarbons; *Gadus morhua; Homeostasis; *Polycyclic Aromatic Hydrocarbons; *Water Pollutants, Chemical

Predicting Metabolism from Gene Expression in an Improved Whole-Genome Metabolic Network Model of Danio rerio. - van Steijn, L.; Verbeek, F. J.; Spaink, H. P.; Merks, R. M. H. (Zebrafish, 2019)
Zebrafish is a useful modeling organism for the study of vertebrate development, immune response, and metabolism. Metabolic studies can be aided by mathematical reconstructions of the metabolic network of zebrafish. These list the substrates and products of all biochemical reactions that occur in the zebrafish. Mathematical techniques such as flux-balance analysis then make it possible to predict the possible metabolic flux distributions that optimize, for example, the turnover of food into biomass. The only available genome-scale reconstruction of zebrafish metabolism is ZebraGEM. In this study, we present ZebraGEM 2.0, an updated and validated version of ZebraGEM. ZebraGEM 2.0 is extended with gene-protein-reaction associations (GPRs) that are required to integrate genetic data with the metabolic model. To demonstrate the use of these GPRs, we performed an in silico genetic screening for knockouts of metabolic genes and validated the results against published in vivo genetic knockout and knockdown screenings. Among the single knockout simulations, we identified 74 essential genes, whose knockout stopped growth completely. Among these, 11 genes are known have an abnormal knockout or knockdown phenotype in vivo (partial), and 41 have human homologs associated with metabolic diseases. We also added the oxidative phosphorylation pathway, which was unavailable in the published version of ZebraGEM. The updated model performs better than the original model on a predetermined list of metabolic functions. We also determined a minimal feed composition. The oxidative phosphorylation pathways were validated by comparing with published experiments in which key components of the oxidative phosphorylation pathway were pharmacologically inhibited. To test the utility of ZebraGEM2.0 for obtaining new results, we integrated gene expression data from control and Mycobacterium marinum-infected zebrafish larvae. The resulting model predicts impeded growth and altered histidine metabolism in the infected larvae.
Keywords: Animals; *Gene Expression; *Metabolic Networks and Pathways; Models, Genetic; Zebrafish/*genetics/*metabolism

Tryptophan metabolism as a common therapeutic target in cancer, neurodegeneration and beyond - Platten, Michael; Nollen, Ellen A. A.; Röhrig, Ute F.; Fallarino, Francesca; Opitz, Christiane (Nature Reviews Drug Discovery, 2019)
L-Tryptophan (Trp) metabolism through the kynurenine pathway (KP) is involved in the regulation of immunity, neuronal function and intestinal homeostasis. Imbalances in Trp metabolism in disorders ranging from cancer to neurodegenerative disease have stimulated interest in therapeutically targeting the KP, particularly the main rate-limiting enzymes indoleamine-2,3-dioxygenase 1 (IDO1), IDO2 and tryptophan-2,3-dioxygenase (TDO) as well as kynurenine monooxygenase (KMO). However, although small-molecule IDO1 inhibitors showed promise in early-stage cancer immunotherapy clinical trials, a phase III trial was negative. This Review summarizes the physiological and pathophysiological roles of Trp metabolism, highlighting the vast opportunities and challenges for drug development in multiple diseases. Full text of this paper is available here https://inrepo01.inet.dkfz-heidelberg.de/record/143705

Resistance Exercise Reduces Kynurenine Pathway Metabolites in Breast Cancer Patients Undergoing Radiotherapy - Zimmer, Philipp; Schmidt, Frank; Prentzell, Mirja Tamara; Berdel, Bianca; Wiskemann, Joachim; Kellner, Karl-Heinz; Debus, Jürgen; Ulrich, Cornelia; Opitz, Christiane; Steindorf, Karen (Front. Oncol., 2019)
Purpose: Evidence from preclinical studies and trials in healthy volunteers suggests that exercise may modulate the levels of tryptophan (TRP) metabolites along the kynurenine (KYN) pathway. As KYN and downstream KYN metabolites are known to promote cancer progression by inhibiting anti-tumor immune responses and by promoting the motility of cancer cells, we investigated if resistance exercise can also control the levels of KYN pathway metabolites in breast cancer patients undergoing radiotherapy (NCT01468766).

Developing A Virus-MicroRNA Interactome Using Cystoscope - Hill, Meredith; Mason, Dayna; Monteiro Marques, Tânia; Gama Carvalho, Margarida; Tran, Nham (MethodsX, 2019)
It is currently difficult to determine the effect of oncogenic viruses on the global function and regulation of pathways within mammalian cells. A thorough understanding of the molecular pathways and individual genes altered by oncogenic viruses is needed for the identification of targets that can be utilised for early diagnosis, prevention, and treatment methods. We detail a logical step-by-step guide to uncover viral-protein-miRNA interactions using publically available datasets and the network building program, Cytoscape. This method may be applied to identify specific pathways that are altered in viral infection, and contribute to the oncogenic transformation of cells. To demonstrate this, we constructed a gene regulatory interactome encompassing Human Papillomavirus Type 16 (HPV16) and its control of specific miRNAs. This approach can be broadly applied to understand and map the regulatory functions of other oncogenic viruses, and determine their role in altering the cellular environment in cancer.

Human papillomavirus 16 E6 modulates the expression of miR-496 in oropharyngeal cancer. - Sais, D.; Zhang, X.; Marques, T. M.; Rose, B.; Khoury, S.; Hill, M.; Deutsch, F.; Lyons, J. G.; Gama-Carvalho, M.; Tran, N. (Virology, 2018)
Human papillomavirus (HPV), notably type 16, is a risk factor for up to 75% of oropharyngeal squamous cell carcinomas (SCC). It has been demonstrated that small non-coding RNAs known as microRNAs play a vital role in the cellular transformation process. In this study, we used an LNA array to further investigate the impact of HPV16 on the expression of microRNAs in oropharyngeal (tonsillar) cancer. A number of miRNAs were found to be deregulated, with miR-496 showing a four-fold decrease. Over-expression of the high risk E6 oncoprotein down-regulated miR-496, impacting upon the post-transcriptional control of the transcription factor E2F2. These HPV specific miRNAs were integrated with the HPV16 interactome to identify possible mechanistic pathways. These analyses provide insights into novel molecular interactions between HPV16 and miRNAs in oropharyngeal cancers.
Keywords: Carcinoma, Squamous Cell/*pathology/virology; *Down-Regulation; E2F2 Transcription Factor/biosynthesis; Gene Regulatory Networks; *Host-Pathogen Interactions; Human papillomavirus 16/*growth & development; Humans; MicroRNAs/*biosynthesis; Oncogene Proteins, Viral/*metabolism; Oropharyngeal Neoplasms/*pathology/virology; Repressor Proteins/*metabolism

Searching the overlap between network modules with specific betweeness (S2B) and its application to cross-disease analysis - Garcia-Vaquero, Marina L.; Gama-Carvalho, Margarida; Rivas, Javier De Las; Pinto, Francisco R. (Sci Rep, 2018)
Discovering disease-associated genes (DG) is strategic for understanding pathological mechanisms. DGs form modules in protein interaction networks and diseases with common phenotypes share more DGs or have more closely interacting DGs. This prompted the development of Specific Betweenness (S2B) to find genes associated with two related diseases. S2B prioritizes genes frequently and specifically present in shortest paths linking two disease modules. Top S2B scores identified genes in the overlap of artificial network modules more than 80% of the times, even with incomplete or noisy knowledge. Applied to Amyotrophic Lateral Sclerosis and Spinal Muscular Atrophy, S2B candidates were enriched in biological processes previously associated with motor neuron degeneration. Some S2B candidates closely interacted in network cliques, suggesting common molecular mechanisms for the two diseases. S2B is a valuable tool for DG prediction, bringing new insights into pathological mechanisms. More generally, S2B can be applied to infer the overlap between other types of network modules, such as functional modules or context-specific subnetworks. An R package implementing S2B is publicly available at https://github.com/frpinto/S2B.

miRNA profiling of human naive CD4 T cells links miR-34c-5p to cell activation and HIV replication. - Amaral, A. J.; Andrade, J.; Foxall, R. B.; Matoso, P.; Matos, A. M.; Soares, R. S.; Rocha, C.; Ramos, C. G.; Tendeiro, R.; Serra-Caetano, A.; Guerra-Assuncao, J. A.; Santa-Marta, M.; et al. (EMBO J, 2017)
Cell activation is a vital step for T-cell memory/effector differentiation as well as for productive HIV infection. To identify novel regulators of this process, we used next-generation sequencing to profile changes in microRNA expression occurring in purified human naive CD4 T cells in response to TCR stimulation and/or HIV infection. Our results demonstrate, for the first time, the transcriptional up-regulation of miR-34c-5p in response to TCR stimulation in naive CD4 T cells. The induction of this miR was further consistently found to be reduced by both HIV-1 and HIV-2 infections. Overexpression of miR-34c-5p led to changes in the expression of several genes involved in TCR signaling and cell activation, confirming its role as a novel regulator of naive CD4 T-cell activation. We additionally show that miR-34c-5p promotes HIV-1 replication, suggesting that its down-regulation during HIV infection may be part of an anti-viral host response.
Keywords: CD4-Positive T-Lymphocytes/*immunology/virology; Gene Expression Profiling; HIV/immunology/*physiology; *Host-Pathogen Interactions; Humans; Immune Evasion; *Lymphocyte Activation; MicroRNAs/*analysis; Receptors, Antigen, T-Cell/*metabolism; *Virus Replication

Linking amyotrophic lateral sclerosis and spinal muscular atrophy through RNA-transcriptome homeostasis: a genomics perspective. - Gama-Carvalho, M.; L Garcia-Vaquero, M.; R Pinto, F.; Besse, F.; Weis, J.; Voigt, A.; Schulz, J. B.; De Las Rivas, J. (J Neurochem, 2017)
In this review, we present our most recent understanding of key biomolecular processes that underlie two motor neuron degenerative disorders, amyotrophic lateral sclerosis, and spinal muscular atrophy. We focus on the role of four multifunctional proteins involved in RNA metabolism (TDP-43, FUS, SMN, and Senataxin) that play a causal role in these diseases. Recent results have led to a novel scenario of intricate connections between these four proteins, bringing transcriptome homeostasis into the spotlight as a common theme in motor neuron degeneration. We review reported functional and physical interactions between these four proteins, highlighting their common association with nuclear bodies and small nuclear ribonucleoprotein particle biogenesis and function. We discuss how these interactions are turning out to be particularly relevant for the control of transcription and chromatin homeostasis, including the recent identification of an association between SMN and Senataxin required to ensure the resolution of DNA-RNA hybrid formation and proper termination by RNA polymerase II. These connections strongly support the existence of common pathways underlying the spinal muscular atrophy and amyotrophic lateral sclerosis phenotype. We also discuss the potential of genome-wide expression profiling, in particular RNA sequencing derived data, to contribute to unravelling the underlying mechanisms. We provide a review of publicly available datasets that have addressed both diseases using these approaches, and highlight the value of investing in cross-disease studies to promote our understanding of the pathways leading to neurodegeneration.
Keywords: Amyotrophic Lateral Sclerosis/diagnosis/*genetics; Animals; Databases, Genetic; Genomics/*methods; Homeostasis/*genetics; Humans; Muscular Atrophy, Spinal/diagnosis/*genetics; RNA/*genetics; Transcriptome/*genetics

A context-specific cardiac β-catenin and GATA4 interaction influences TCF7L2 occupancy and remodels chromatin driving disease progression in the adult heart - Iyer, Lavanya M; Nagarajan, Sankari; Woelfer, Monique; Schoger, Eric; Khadjeh, Sara; Zafiriou, Maria Patapia; Kari, Vijayalakshmi; Herting, Jonas; Pang, Sze Ting; Weber, Marc; Rathjens, Franziska S; Fischer, Ralf-Jörg; et al. (2018)
Chromatin remodelling precedes transcriptional and structural changes in heart failure. A body of work suggests roles for the developmental Wnt signalling pathway in cardiac remodelling. Hitherto, there is no evidence supporting a direct role of Wnt nuclear components in regulating chromatin landscapes in this process. We show that transcriptionally active, nuclear, phosphorylated(p)Ser675-β-catenin and TCF7L2 are upregulated in diseased murine and human cardiac ventricles. We report that inducible cardiomyocytes (CM)-specific pSer675-β-catenin accumulation mimics the disease situation by triggering TCF7L2 expression. This enhances active chromatin, characterized by increased H3K27ac and TCF7L2 occupancies to cardiac developmental and remodelling genes in vivo. Accordingly, transcriptomic analysis of β-catenin stabilized hearts shows a strong recapitulation of cardiac developmental processes like cell cycling and cytoskeletal remodelling. Mechanistically, TCF7L2 co-occupies distal genomic regions with cardiac transcription factors NKX2–5 and GATA4 in stabilized-β-catenin hearts. Validation assays revealed a previously unrecognized function of GATA4 as a cardiac repressor of the TCF7L2/β-catenin complex in vivo, thereby defining a transcriptional switch controlling disease progression. Conversely, preventing β-catenin activation post-pressure-overload results in a downregulation of these novel TCF7L2-targets and rescues cardiac function. Thus, we present a novel role for TCF7L2/β-catenin in CMs-specific chromatin modulation, which could be exploited for manipulating the ubiquitous Wnt pathway.

FAIRDOMHub: a repository and collaboration environment for sharing systems biology research. - Wolstencroft, K.; Krebs, O.; Snoep, J. L.; Stanford, N. J.; Bacall, F.; Golebiewski, M.; Kuzyakiv, R.; Nguyen, Q.; Owen, S.; Soiland-Reyes, S.; Straszewski, J.; van Niekerk, D. D.; et al. (Nucleic Acids Res, 2017)
The FAIRDOMHub is a repository for publishing FAIR (Findable, Accessible, Interoperable and Reusable) Data, Operating procedures and Models (https://fairdomhub.org/) for the Systems Biology community. It is a web-accessible repository for storing and sharing systems biology research assets. It enables researchers to organize, share and publish data, models and protocols, interlink them in the context of the systems biology investigations that produced them, and to interrogate them via API interfaces. By using the FAIRDOMHub, researchers can achieve more effective exchange with geographically distributed collaborators during projects, ensure results are sustained and preserved and generate reproducible publications that adhere to the FAIR guiding principles of data stewardship.
Keywords: Carbon/metabolism; Data Curation; *Databases, Factual; Information Dissemination; Metabolic Networks and Pathways; Research; Systems Biology/*methods

Cultivar-specific transcriptome and pan-transcriptome reconstruction of tetraploid potato - Petek, Marko; Zagorscak, Maja; Ramsak, Ziva; Sanders, Sheri; Tseng, Elizabeth; Zouine, Mohamed; Coll Rius, Anna; Gruden, Kristina
Background: Although the reference genome of Solanum tuberosum group Phureja double-monoploid (DM) clone is available, knowledge on the genetic diversity of the highly heterozygous tetraploid group Tuberosum, representing most cultivated varieties, remains largely unexplored. This lack of knowledge hinders further progress in potato research and its subsequent applications in breeding. Results: For the DM genome assembly, two only partially-overlapping gene models exist differing in a unique set of genes and intron/exon structure predictions. First step was to merge and manually curate the merged gene model, creating a union of genes in Phureja scaffold. We next compiled available RNA-Seq datasets (cca. 1.5 billion reads) for three tetraploid potato genotypes (cultivar Désirée, cultivar Rywal, and breeding clone PW363) with diverse breeding pedigrees. Short-read transcriptomes were assembled using CLC, Trinity, Velvet, and rnaSPAdes de novo assemblers using different settings to test for optimal outcome. In addition, for cultivar Rywal, PacBio Iso-Seq full-length transcriptome sequencing was also performed. Revised EvidentialGene redundancy-reducing pipeline was employed to produce accurate and complete cultivar-specific transcriptomes from assemblers output, as well as to attain the pan-transcriptome. Due to being the most diverse dataset in terms of tissues (stem, seedlings and roots) and experimental conditions, cv. Désirée was the most complete transcriptome (95.8% BUSCO completeness). For cv. Rywal and breeding clone PW363 data were available for leaf samples only and the resulting transcriptomes were less complete than cv. Désirée (89.8% and 89.3% BUSCO completeness, respectively). Cross comparison of these cultivar-specific transcriptomes and merged DM gene model suggests that the core potato transcriptome is comprised of 16,339 genes. The pan-transcriptome contains a total of 95,779 transcripts, of which 54,614 transcripts are not present in the Phureja genome. These represent the variants of the novel genes found in the potato pan-genome. Conclusions: Our analysis shows that the available gene model of double-monoploid potato from group Phureja is, to some degree, not complete. The generated transcriptomes and pan-transcriptome represent a valuable resource for potato gene variability exploration, high-throughput -omics analyses, and future breeding programmes.

The PI3K and MAPK/p38 pathways control stress granule assembly in a hierarchical manner - Heberle, Alexander; Razquin Navas, Patricia; Langelaar-Makkinje, Miriam; Kasack, Katharina; Sadik, Ahmed; Faessler, Erik; Hahn, Udo; Marx-Stoelting, Philip; Opitz, Christiane; Sers, Christine; Heiland, Ines; Schäuble, Sascha; et al. (Life Sci. Alliance, 2019)
All cells and organisms exhibit stress-coping mechanisms to ensure survival. Cytoplasmic protein-RNA assemblies termed stress granules are increasingly recognized to promote cellular survival under stress. Thus, they might represent tumor vulnerabilities that are currently poorly explored. The translationinhibitory eIF2α kinases are established as main drivers of stress granule assembly. Using a systems approach, we identify the translation enhancers PI3K and MAPK/p38 as pro-stressgranule- kinases. They act through the metabolic master regulator mammalian target of rapamycin complex 1 (mTORC1) to promote stress granule assembly.When highly active, PI3K is the main driver of stress granules; however, the impact of p38 becomes apparent as PI3K activity declines. PI3K and p38 thus act in a hierarchical manner to drive mTORC1 activity and stress granule assembly. Of note, this signaling hierarchy is also present in human breast cancer tissue. Importantly, only the recognition of the PI3K-p38 hierarchy under stress enabled the discovery of p38’s role in stress granule formation. In summary, we assign a new prosurvival function to the key oncogenic kinases PI3K and p38, as they hierarchically promote stress granule formation.

Know when your numbers are significant - Vaux, David L. (Nature, 2012)
Experimental biologists, their reviewers and their publishers must grasp basic statistics, urges David L. Vaux, or sloppy science will continue to grow.

Parallel DNA Polymerase Chain Reaction (PD-PCR) - bhardwaj, vikash; bhardwaj, Vikash; Krebs, Olga (Protocol Exchange, 2016)
This protocol describe an approach in which the first primer binds in a parallel complementary orientation to the single-stranded DNA, leading to synthesis in a parallel direction. Further reactions happened in a conventional way leading to the synthesis of PCR product having polarity opposite to the template used. Here in FAIRDOM we use this SOP as an example/template

Energy Conservation Associated with Ethanol Formation from H2 and CO2 in Clostridium autoethanogenum Involving Electron Bifurcation. - Mock, J.; Zheng, Y.; Mueller, A. P.; Ly, S.; Tran, L.; Segovia, S.; Nagaraju, S.; Kopke, M.; Durre, P.; Thauer, R. K. (J Bacteriol, 2015)
Most acetogens can reduce CO2 with H2 to acetic acid via the Wood-Ljungdahl pathway, in which the ATP required for formate activation is regenerated in the acetate kinase reaction. However, a few acetogens, such as Clostridium autoethanogenum, Clostridium ljungdahlii, and Clostridium ragsdalei, also form large amounts of ethanol from CO2 and H2. How these anaerobes with a growth pH optimum near 5 conserve energy has remained elusive. We investigated this question by determining the specific activities and cofactor specificities of all relevant oxidoreductases in cell extracts of H2/CO2-grown C. autoethanogenum. The activity studies were backed up by transcriptional and mutational analyses. Most notably, despite the presence of six hydrogenase systems of various types encoded in the genome, the cells appear to contain only one active hydrogenase. The active [FeFe]-hydrogenase is electron bifurcating, with ferredoxin and NADP as the two electron acceptors. Consistently, most of the other active oxidoreductases rely on either reduced ferredoxin and/or NADPH as the electron donor. An exception is ethanol dehydrogenase, which was found to be NAD specific. Methylenetetrahydrofolate reductase activity could only be demonstrated with artificial electron donors. Key to the understanding of this energy metabolism is the presence of membrane-associated reduced ferredoxin:NAD(+) oxidoreductase (Rnf), of electron-bifurcating and ferredoxin-dependent transhydrogenase (Nfn), and of acetaldehyde:ferredoxin oxidoreductase, which is present with very high specific activities in H2/CO2-grown cells. Based on these findings and on thermodynamic considerations, we propose metabolic schemes that allow, depending on the H2 partial pressure, the chemiosmotic synthesis of 0.14 to 1.5 mol ATP per mol ethanol synthesized from CO2 and H2. IMPORTANCE: Ethanol formation from syngas (H2, CO, and CO2) and from H2 and CO2 that is catalyzed by bacteria is presently a much-discussed process for sustainable production of biofuels. Although the process is already in use, its biochemistry is only incompletely understood. The most pertinent question is how the bacteria conserve energy for growth during ethanol formation from H2 and CO2, considering that acetyl coenzyme A (acetyl-CoA), is an intermediate. Can reduction of the activated acetic acid to ethanol with H2 be coupled with the phosphorylation of ADP? Evidence is presented that this is indeed possible, via both substrate-level phosphorylation and electron transport phosphorylation. In the case of substrate-level phosphorylation, acetyl-CoA reduction to ethanol proceeds via free acetic acid involving acetaldehyde:ferredoxin oxidoreductase (carboxylate reductase).
Keywords: Acetic Acid/chemistry/metabolism; Acetyl Coenzyme A/metabolism; Adenosine Diphosphate/metabolism; Bacterial Proteins/genetics/metabolism; Carbon Dioxide/*metabolism; Clostridium/classification/*metabolism; Electron Transport; Energy Metabolism/*physiology; Ethanol/*metabolism; Gene Expression Regulation, Bacterial/physiology; Gene Expression Regulation, Enzymologic/physiology; Hydrogen/*metabolism; Membrane Proteins; Oxidoreductases/genetics/metabolism; Phosphoproteins

RNA-Seq analysis of transcriptome responses in Atlantic cod (Gadus morhua) precision-cut liver slices exposed to benzo[a]pyrene and 17alpha-ethynylestradiol. - Yadetie, F.; Zhang, X.; Hanna, E. M.; Aranguren-Abadia, L.; Eide, M.; Blaser, N.; Brun, M.; Jonassen, I.; Goksoyr, A.; Karlsen, O. A. (Aquat Toxicol, 2018)
Polycyclic aromatic hydrocarbons such as benzo[a]pyrene (BaP) that activate the aryl hydrocarbon receptor (Ahr) pathway, and endocrine disruptors acting through the estrogen receptor pathway are among environmental pollutants of major concern. In this work, we exposed Atlantic cod (Gadus morhua) precision-cut liver slices (PCLS) to BaP (10 nM and 1000 nM), ethynylestradiol (EE2) (10 nM and 1000 nM), and equimolar mixtures of BaP and EE2 (10 nM and 1000 nM) for 48 h, and performed RNA-Seq based transcriptome mapping followed by systematic bioinformatics analyses. Our gene expression analysis showed that several genes were differentially expressed in response to BaP and EE2 treatments in PCLS. Strong up-regulation of genes coding for the cytochrome P450 1a (Cyp1a) enzyme and the Ahr repressor (Ahrrb) was observed in BaP treated PCLS. EE2 treatment of liver slices strongly up-regulated genes coding for precursors of vitellogenin (Vtg) and eggshell zona pellucida (Zp) proteins. As expected, pathway enrichment and network analysis showed that the Ahr and estrogen receptor pathways are among the top affected by BaP and EE2 treatments, respectively. Interestingly, two genes coding for fibroblast growth factor 3 (Fgf3) and fibroblast growth factor 4 (Fgf4) were up-regulated by EE2 in this study. To our knowledge, the fgf3 and fgf4 genes have not previously been described in relation to estrogen signaling in fish liver, and these results suggest the modulation of the FGF signaling pathway by estrogens in fish. The signature expression profiles of top differentially expressed genes in response to the single compound (BaP or EE2) treatment were generally maintained in the expression responses to the equimolar binary mixtures. However, in the mixture-treated groups, BaP appeared to have anti-estrogenic effects as observed by lower number of differentially expressed putative EE2 responsive genes. Our in-depth quantitative analysis of changes in liver transcriptome in response to BaP and EE2, using PCLS tissue culture provides further mechanistic insights into effects of the compounds. Moreover, the analyses demonstrate the usefulness of PCLS in cod for omics experiments.
Keywords: Animals; Benzo(a)pyrene/*toxicity; Cluster Analysis; Environmental Exposure/*analysis; Ethinyl Estradiol/*toxicity; Female; Gadus morhua/*genetics/metabolism; Gene Expression Profiling; Gene Regulatory Networks/drug effects; Liver/drug effects/*metabolism; Male; Molecular Sequence Annotation; RNA/metabolism; Sequence Analysis, RNA/*methods; Tissue Survival/drug effects; Transcriptome/*genetics; Water Pollutants, Chemical/toxicity

The clock gene circuit in Arabidopsis includes a repressilator with additional feedback loops. - Pokhilko, A.; Fernandez, A. P.; Edwards, K. D.; Southern, M. M.; Halliday, K. J.; Millar, A. J. (Mol Syst Biol, 2012)
Circadian clocks synchronise biological processes with the day/night cycle, using molecular mechanisms that include interlocked, transcriptional feedback loops. Recent experiments identified the evening complex (EC) as a repressor that can be essential for gene expression rhythms in plants. Integrating the EC components in this role significantly alters our mechanistic, mathematical model of the clock gene circuit. Negative autoregulation of the EC genes constitutes the clock's evening loop, replacing the hypothetical component Y. The EC explains our earlier conjecture that the morning gene Pseudo-Response Regulator 9 was repressed by an evening gene, previously identified with Timing Of CAB Expression1 (TOC1). Our computational analysis suggests that TOC1 is a repressor of the morning genes Late Elongated Hypocotyl and Circadian Clock Associated1 rather than an activator as first conceived. This removes the necessity for the unknown component X (or TOC1mod) from previous clock models. As well as matching timeseries and phase-response data, the model provides a new conceptual framework for the plant clock that includes a three-component repressilator circuit in its complex structure.
Keywords: Arabidopsis/*genetics; Arabidopsis Proteins/genetics/physiology; CLOCK Proteins/*genetics/physiology; Circadian Rhythm/genetics; Computational Biology; DNA-Binding Proteins/genetics; Feedback, Physiological/*physiology; Gene Expression Regulation, Plant/radiation effects; Gene Regulatory Networks/*physiology; Light; Models, Biological; Photoperiod; Plants, Genetically Modified; Repressor Proteins/*genetics; Transcription Factors/genetics/physiology; Ubiquitin-Protein Ligases

Rethinking Transcriptional Activation in the Arabidopsis Circadian Clock - Fogelmark, Karl; Troein, Carl (PLoS Comput Biol, 2014)

Disturbed hepatic carbohydrate management during high metabolic demand in medium-chain acyl-CoA dehydrogenase (MCAD)-deficient mice. - Herrema, H.; Derks, T. G.; van Dijk, T. H.; Bloks, V. W.; Gerding, A.; Havinga, R.; Tietge, U. J.; Muller, M.; Smit, G. P.; Kuipers, F.; Reijngoud, D. J. (Hepatology, 2008)
Medium-chain acyl-coenzyme A (CoA) dehydrogenase (MCAD) catalyzes crucial steps in mitochondrial fatty acid oxidation, a process that is of key relevance for maintenance of energy homeostasis, especially during high metabolic demand. To gain insight into the metabolic consequences of MCAD deficiency under these conditions, we compared hepatic carbohydrate metabolism in vivo in wild-type and MCAD(-/-) mice during fasting and during a lipopolysaccharide (LPS)-induced acute phase response (APR). MCAD(-/-) mice did not become more hypoglycemic on fasting or during the APR than wild-type mice did. Nevertheless, microarray analyses revealed increased hepatic peroxisome proliferator-activated receptor gamma coactivator-1alpha (Pgc-1alpha) and decreased peroxisome proliferator-activated receptor alpha (Ppar alpha) and pyruvate dehydrogenase kinase 4 (Pdk4) expression in MCAD(-/-) mice in both conditions, suggesting altered control of hepatic glucose metabolism. Quantitative flux measurements revealed that the de novo synthesis of glucose-6-phosphate (G6P) was not affected on fasting in MCAD(-/-) mice. During the APR, however, this flux was significantly decreased (-20%) in MCAD(-/-) mice compared with wild-type mice. Remarkably, newly formed G6P was preferentially directed toward glycogen in MCAD(-/-) mice under both conditions. Together with diminished de novo synthesis of G6P, this led to a decreased hepatic glucose output during the APR in MCAD(-/-) mice; de novo synthesis of G6P and hepatic glucose output were maintained in wild-type mice under both conditions. APR-associated hypoglycemia, which was observed in wild-type mice as well as MCAD(-/-) mice, was mainly due to enhanced peripheral glucose uptake. CONCLUSION: Our data demonstrate that MCAD deficiency in mice leads to specific changes in hepatic carbohydrate management on exposure to metabolic stress. This deficiency, however, does not lead to reduced de novo synthesis of G6P during fasting alone, which may be due to the existence of compensatory mechanisms or limited rate control of MCAD in murine mitochondrial fatty acid oxidation.
Keywords: Acyl-CoA Dehydrogenase/*genetics/*metabolism; Animals; Blood Glucose/metabolism; Carbohydrate Metabolism/*genetics/*physiology; Disease Models, Animal; Energy Metabolism/genetics/physiology; Fatty Acids; Gene Expression Regulation, Enzymologic; Glucose-6-Phosphate/metabolism; Glycogen/metabolism; Hypoglycemia/metabolism; Lipopolysaccharides/pharmacology; Liver/drug effects/*metabolism; Liver Diseases/*enzymology/genetics; Male; Mice; Mice, Knockout; Mitochondria, Liver

A combined experimental and modelling approach for the Weimberg pathway optimisation - Shen, Lu; Kohlhaas, Martha; Enoki, Junichi; Meier, Roland; Schönenberger, Bernhard; Wohlgemuth, Roland; Kourist, Robert; Niemeyer, Felix; van Niekerk, Dawie; Bräsen, Christopher; Niemeyer, Jochen; Snoep, Jacky; et al. (Nat Commun, 2020)
The oxidative Weimberg pathway for the five-step pentose degradation to α-ketoglutarate is a key route for sustainable bioconversion of lignocellulosic biomass to added-value products and biofuels. The oxidative pathway from Caulobacter crescentus has been employed in in-vivo metabolic engineering with intact cells and in in-vitro enzyme cascades. The performance of such engineering approaches is often hampered by systems complexity, caused by non-linear kinetics and allosteric regulatory mechanisms. Here we report an iterative approach to construct and validate a quantitative model for the Weimberg pathway. Two sensitive points in pathway performance have been identified as follows: (1) product inhibition of the dehydrogenases (particularly in the absence of an efficient NAD+ recycling mechanism) and (2) balancing the activities of the dehydratases. The resulting model is utilized to design enzyme cascades for optimized conversion and to analyse pathway performance in C. cresensus cell- free extracts.

11-Oxygenated androgen precursors are the preferred substrates for aldo-keto reductase 1C3 (AKR1C3): Implications for castration resistant prostate cancer - Barnard, Monique; Quanson, Jonathan L.; Mostaghel, Elahe; Pretorius, Elzette; Snoep, Jacky; Storbeck, Karl-Heinz (The Journal of Steroid Biochemistry and Molecular Biology, 2018)
The progression of castration resistant prostate cancer (CRPC) is driven by the intratumoral conversion of adrenal androgen precursors to potent androgens. The expression of aldo-keto reductase 1C3 (AKR1C3), which catalyses the reduction of weak androgens to more potent androgens, is significantly increased in CRPC tumours. The oxidation of androgens to their inactive form is catalysed by 17β-hydroxysteroid dehydrogenase type 2 (17βHSD2), but little attention is given to the expression levels of this enzyme. In this study, we show that the 11-oxygenated androgen precursors of adrenal origin are the preferred substrate for AKR1C3. In particular we show that the enzymatic efficiency of AKR1C3 is 8- and 24-fold greater for 11-ketoandrostenedione than for the classic substrates androstenedione and 5α-androstanedione, respectively. Using three independent experimental systems and a computational model we subsequently show that increased ratios of AKR1C3:17βHSD2 sig- nificantly favours the flux through the 11-oxygenated androgen pathway as compared to the classical or 5α- androstanedione pathways. Our findings reveal that the flux through the classical and 5α-androstanedione pathways are limited by the low catalytic efficiently of AKR1C3 towards classical androgens combined with the high catalytic efficiency of 17βHSD2, and that the expression of the oxidative enzyme therefore plays a vital role in determining the steady state concentration of active androgens. Using microarray data from prostate tissue we confirm that the AKR1C3:17βHSD2 ratio is significantly increased in patients undergoing androgen deprivation therapy as compared to benign tissue, and further increased in patients with CRPC. Taken together this study therefore demonstrates that the ratio of AKR1C3:17βHSD2 is more important than AKR1C3 expression alone in determining intratumoral androgen levels and that 11-oxygenated androgens may play a bigger role in CRPC than previously anticipated.

Design principles of ROS dynamic networks relevant to precision therapies for age-related diseases - Kolodkin, Alexey; Sharma, Raju Prasad; Colangelo, Anna Maria; Ignatenko, Andrew; Martorana, Francesca; Jennen, Danyel; Briede, Jacco J.; Brady, Nathan; Barberis, Matteo; Mondeel, Thierry D.G.A.; Papa, Michele; Kumar, Vikas; et al.
The eminently complex regulatory network protecting the cell against oxidative stress, surfaces in several disease maps, including that of Parkinson’s disease (PD). How this molecular networking achieves its various functionalities and how processes operating at the seconds-minutes time scale cause a disease at a time scale of multiple decennia is enigmatic.

GEMtractor: extracting views into genome-scale metabolic models - Scharm, Martin; Wolkenhauer, Olaf; Jalili, Mahdi; Salehzadeh-Yazdi, Ali (Bioinformatics, 2020)
SUMMARY:

Genome-scale Model Constrained by Proteomics Reveals Metabolic Changes in Streptomyces coelicolor M1152 Compared to M145 - Sulheim, Snorre; Kumelj, Tjasa; van Dissel, Dino; Salehzadeh-Yazdi, Ali; Du, Chao; van Wezel, Gilles P.; Nieselt, Kay; Almaas, Eivind; Wentzel, Alexander; Kerkhoven, Eduard (2019)
Streptomyces coelicolor M1152 is a widely used host strain for the heterologous production of novel small molecule natural products, genetically engineered for this purpose through e.g. deletion of four of its native biosynthetic gene clusters (BGCs) for improved precursor supply. Regardless of its potential, a systems understanding of its tight regulatory network and the effects of the significant genomic changes in M1152 is missing. In this study, we compare M1152 to its ancestor M145, thereby connecting observed phenotypic differences to changes on transcription and translation. Measured protein levels are connected to predicted metabolic fluxes, facilitated by an enzyme-constrained genome-scale model (GEM), that by itself is a consensus result of a community effort. This approach connects observed differences in growth rate and glucose consumption to changes in central carbon metabolism, accompanied by differential expression of important regulons. Results suggest that precursors supply is not limiting secondary metabolism, informing that alternative strategies will be beneficial for further development of S. coelicolor for heterologous production of novel compounds.

Transcriptome analysis suggests a compensatory role of the cofactors coenzyme A and NAD+ in medium-chain acyl-CoA dehydrogenase knockout mice - Martines, Anne-Claire M. F.; Gerding, Albert; Stolle, Sarah; Vieira-Lara, Marcel A.; Wolters, Justina C.; Jurdzinski, Angelika; Bongiovanni, Laura; de Bruin, Alain; van der Vlies, Pieter; van der Vries, Gerben; Bloks, Vincent W.; Derks, Terry G.J.; et al. (Scientific Reports, 2019)
Abstract During fasting, mitochondrial fatty-acid β-oxidation (mFAO) is essential for the generation of glucose by the liver. Children with a loss-of-function deficiency in the mFAO enzyme medium-chain acyl-Coenzyme A dehydrogenase (MCAD) are at serious risk of life-threatening low blood glucose levels during fasting in combination with intercurrent disease. However, a subset of these children remains asymptomatic throughout life. In MCAD-deficient (MCAD-KO) mice, glucose levels are similar to those of wild-type (WT) mice, even during fasting. We investigated if metabolic adaptations in the liver may underlie the robustness of this KO mouse. WT and KO mice were given a high- or low-fat diet and subsequently fasted. We analyzed histology, mitochondrial function, targeted mitochondrial proteomics, and transcriptome in liver tissue. Loss of MCAD led to a decreased capacity to oxidize octanoyl-CoA. This was not compensated for by altered protein levels of the short- and long-chain isoenzymes SCAD and LCAD. In the transcriptome, we identified subtle adaptations in the expression of genes encoding enzymes catalyzing CoA- and NAD(P)(H)-involving reactions and of genes involved in detoxification mechanisms. We discuss how these processes may contribute to robustness in MCAD-KO mice and potentially also in asymptomatic human subjects with a complete loss of MCAD activity.

A SARS-CoV-2-Human Protein-Protein Interaction Map Reveals Drug Targets and Potential Drug-Repurposing - Gordon, David E.; Jang, Gwendolyn M.; Bouhaddou, Mehdi; Xu, Jiewei; Obernier, Kirsten; O’Meara, Matthew J.; Guo, Jeffrey Z.; Swaney, Danielle L.; Tummino, Tia A.; Hüttenhain, Ruth; Kaake, Robyn M.; Richards, Alicia L.; et al. (2020)
An outbreak of the novel coronavirus SARS-CoV-2, the causative agent of COVID-19 respiratory disease, has infected over 290,000 people since the end of 2019, killed over 12,000, and caused worldwide social and economic disruption1,2. There are currently no antiviral drugs with proven efficacy nor are there vaccines for its prevention. Unfortunately, the scientific community has little knowledge of the molecular details of SARS-CoV-2 infection. To illuminate this, we cloned, tagged and expressed 26 of the 29 viral proteins in human cells and identified the human proteins physically associated with each using affinity-purification mass spectrometry (AP-MS), which identified 332 high confidence SARS-CoV-2-human protein-protein interactions (PPIs). Among these, we identify 67 druggable human proteins or host factors targeted by 69 existing FDA-approved drugs, drugs in clinical trials and/or preclinical compounds, that we are currently evaluating for efficacy in live SARS-CoV-2 infection assays. The identification of host dependency factors mediating virus infection may provide key insights into effective molecular targets for developing broadly acting antiviral therapeutics against SARS-CoV-2 and other deadly coronavirus strains.

SARS-CoV-2 receptor ACE2 and TMPRSS2 are predominantly expressed in a transient secretory cell type in subsegmental bronchial branches - Lukassen, Soeren; Chua, Robert Lorenz; Trefzer, Timo; Kahn, Nicolas C.; Schneider, Marc A.; Muley, Thomas; Winter, Hauke; Meister, Michael; Veith, Carmen; Boots, Agnes W.; Hennig, Bianca P.; Kreuter, Michael; et al. (2020)
The SARS-CoV-2 pandemic affecting the human respiratory system severely challenges public health and urgently demands for increasing our understanding of COVID-19 pathogenesis, especially host factors facilitating virus infection and replication. SARS-CoV-2 was reported to enter cells via binding to ACE2, followed by its priming by TMPRSS2. Here, we investigate ACE2 and TMPRSS2 expression levels and their distribution across cell types in lung tissue (twelve donors, 39,778 cells) and in cells derived from subsegmental bronchial branches (four donors, 17,521 cells) by single nuclei and single cell RNA sequencing, respectively. While TMPRSS2 is expressed in both tissues, in the subsegmental bronchial branches ACE2 is predominantly expressed in a transient secretory cell type. Interestingly, these transiently differentiating cells show an enrichment for pathways related to RHO GTPase function and viral processes suggesting increased vulnerability for SARS-CoV-2 infection. Our data provide a rich resource for future investigations of COVID-19 infection and pathogenesis.

LY6E impairs coronavirus fusion and confers immune control of viral disease - Pfaender, Stephanie; Mar, Katrina B.; Michailidis, Eleftherios; Kratzel, Annika; Hirt, Dagny; V’kovski, Philip; Fan, Wenchun; Ebert, Nadine; Stalder, Hanspeter; Kleine-Weber, Hannah; Hoffmann, Markus; Hoffmann, H. Heinrich; et al. (2020)
Zoonotic coronaviruses (CoVs) are significant threats to global health, as exemplified by the recent emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)1. Host immune responses to CoV are complex and regulated in part through antiviral interferons. However, the interferon-stimulated gene products that inhibit CoV are not well characterized2. Here, we show that interferon-inducible lymphocyte antigen 6 complex, locus E (LY6E) potently restricts cellular infection by multiple CoVs, including SARS-CoV, SARS-CoV-2, and Middle East respiratory syndrome coronavirus (MERS-CoV). Mechanistic studies revealed that LY6E inhibits CoV entry into cells by interfering with spike protein-mediated membrane fusion. Importantly, mice lacking Ly6e in hematopoietic cells were highly susceptible to murine CoV infection. Exacerbated viral pathogenesis in Ly6e knockout mice was accompanied by loss of hepatic and splenic immune cells and reduction in global antiviral gene pathways. Accordingly, we found that Ly6e directly protects primary B cells and dendritic cells from murine CoV infection. Our results demonstrate that LY6E is a critical antiviral immune effector that controls CoV infection and pathogenesis. These findings advance our understanding of immune-mediated control of CoV in vitro and in vivo, knowledge that could help inform strategies to combat infection by emerging CoV.

Structure, function and antigenicity of the SARS-CoV-2 spike glycoprotein - Walls, Alexandra C.; Park, Young-Jun; Tortorici, M. Alexandra; Wall, Abigail; McGuire, Andrew T.; Veesler, David (2020)
SUMMARY The recent emergence of a novel coronavirus associated with an ongoing outbreak of pneumonia (Covid-2019) resulted in infections of more than 72,000 people and claimed over 1,800 lives. Coronavirus spike (S) glycoprotein trimers promote entry into cells and are the main target of the humoral immune response. We show here that SARS-CoV-2 S mediates entry in VeroE6 cells and in BHK cells transiently transfected with human ACE2, establishing ACE2 as a functional receptor for this novel coronavirus. We further demonstrate that the receptor-binding domains of SARS-CoV-2 S and SARS-CoV S bind with similar affinities to human ACE2, which correlates with the efficient spread of SARS-CoV-2 among humans. We found that the SARS-CoV-2 S glycoprotein harbors a furin cleavage site at the boundary between the S 1 /S 2 subunits, which is processed during biogenesis and sets this virus apart from SARS-CoV and other SARS-related CoVs. We determined a cryo-electron microscopy structure of the SARS-CoV-2 S ectodomain trimer, demonstrating spontaneous opening of the receptor-binding domain, and providing a blueprint for the design of vaccines and inhibitors of viral entry. Finally, we demonstrate that SARS-CoV S murine polyclonal sera potently inhibited SARS-CoV-2 S-mediated entry into target cells, thereby indicating that cross-neutralizing antibodies targeting conserved S epitopes can be elicited upon vaccination.

The insert sequence in SARS-CoV-2 enhances spike protein cleavage by TMPRSS - Meng, Tong; Cao, Hao; Zhang, Hao; Kang, Zijian; Xu, Da; Gong, Haiyi; Wang, Jing; Li, Zifu; Cui, Xingang; Xu, Huji; Wei, Haifeng; Pan, Xiuwu; et al. (2020)
Abstract At the end of 2019, the SARS-CoV-2 induces an ongoing outbreak of pneumonia in China 1 , even more spread than SARS-CoV infection 2 . The entry of SARS-CoV into host cells mainly depends on the cell receptor (ACE2) recognition and spike protein cleavage-induced cell membrane fusion 3,4 . The spike protein of SARS-CoV-2 also binds to ACE2 with a similar affinity, whereas its spike protein cleavage remains unclear 5,6 . Here we show that an insertion sequence in the spike protein of SARS-CoV-2 enhances the cleavage efficiency, and besides pulmonary alveoli, intestinal and esophagus epithelium were also the target tissues of SARS-CoV-2. Compared with SARS-CoV, we found a SPRR insertion in the S1/S2 protease cleavage sites of SARS-CoV-2 spike protein increasing the cleavage efficiency by the protein sequence aligment and furin score calculation. Additionally, the insertion sequence facilitates the formation of an extended loop which was more suitable for protease recognition by the homology modeling and molicular docking. Furthermore, the single-cell transcriptomes identified that ACE2 and TMPRSSs are highly coexpressed in AT2 cells of lung, along with esophageal upper epithelial cells and absorptive enterocytes. Our results provide the bioinformatics evidence for the increased spike protein cleavage of SARS-CoV-2 and indicate its potential target cells.

The SARS-CoV-2 exerts a distinctive strategy for interacting with the ACE2 human receptor - Brielle, Esther S.; Schneidman-Duhovny, Dina; Linial, Michal (2020)
The COVID-19 disease has plagued over 110 countries and has resulted in over 4,000 deaths within 10 weeks. We compare the interaction between the human ACE2 receptor and the SARS-CoV-2 spike protein with that of other pathogenic coronaviruses using molecular dynamics simulations. SARS-CoV, SARS-CoV-2, and HCoV-NL63 recognize ACE2 as the natural receptor but present a distinct binding interface to ACE2 and a different network of residue-residue contacts. SARS-CoV and SARS-CoV-2 have comparable binding affinities achieved by balancing energetics and dynamics. The SARS-CoV-2–ACE2 complex contains a higher number of contacts, a larger interface area, and decreased interface residue fluctuations relative to SARS-CoV. These findings expose an exceptional evolutionary exploration exerted by coronaviruses toward host recognition. We postulate that the versatility of cell receptor binding strategies has immediate implications on therapeutic strategies.

The spike glycoprotein of the new coronavirus 2019-nCoV contains a furin-like cleavage site absent in CoV of the same clade - Coutard, B.; Valle, C.; de Lamballerie, X.; Canard, B.; Seidah, N.G.; Decroly, E. (Antiviral Research, 2020)
In 2019, a new coronavirus (2019-nCoV) infecting Humans has emerged in Wuhan, China. Its genome has been sequenced and the genomic information promptly released. Despite a high similarity with the genome sequence of SARS-CoV and SARS-like CoVs, we identiﬁed a peculiar furin-like cleavage site in the Spike protein of the 2019-nCoV, lacking in the other SARS-like CoVs. In this article, we discuss the possible functional consequences of this cleavage site in the viral cycle, pathogenicity and its potential implication in the development of antivirals.

SARS-CoV-2 Cell Entry Depends on ACE2 and TMPRSS2 and Is Blocked by a Clinically Proven Protease Inhibitor - Hoffmann, Markus; Kleine-Weber, Hannah; Schroeder, Simon; Krüger, Nadine; Herrler, Tanja; Erichsen, Sandra; Schiergens, Tobias S.; Herrler, Georg; Wu, Nai-Huei; Nitsche, Andreas; Müller, Marcel A.; Drosten, Christian; et al. (Cell, 2020)
The recent emergence of the novel, pathogenic SARS-coronavirus 2 (SARS-CoV-2) in China and its rapid national and international spread pose a global health emergency. Cell entry of coronaviruses depends on binding of the viral spike (S) proteins to cellular receptors and on S protein priming by host cell proteases. Unravelling which cellular factors are used by SARS-CoV-2 for entry might provide insights into viral transmission and reveal therapeutic targets. Here, we demonstrate that SARS-CoV-2 uses the SARS-CoV receptor ACE2 for entry and the serine protease TMPRSS2 for S protein priming. A TMPRSS2 inhibitor approved for clinical use blocked entry and might constitute a treatment option. Finally, we show that the sera from convalescent SARS patients cross-neutralized SARS-2S-driven entry. Our results reveal important commonalities between SARS-CoV-2 and SARS-CoV infection and identify a potential target for antiviral intervention.

Functional assessment of cell entry and receptor usage for SARS-CoV-2 and other lineage B betacoronaviruses - Letko, Michael; Marzi, Andrea; Munster, Vincent (Nature Microbiology, 2020)

SARS-CoV-2 invades host cells via a novel route: CD147-spike protein - Wang, Ke; Chen, Wei; Zhou, Yu-Sen; Lian, Jian-Qi; Zhang, Zheng; Du, Peng; Gong, Li; Zhang, Yang; Cui, Hong-Yong; Geng, Jie-Jie; Wang, Bin; Sun, Xiu-Xuan; et al. (2020)
Currently, COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been widely spread around the world; nevertheless, so far there exist no specific antiviral drugs for treatment of the disease, which poses great challenge to control and contain the virus. Here, we reported a research finding that SARS-CoV-2 invaded host cells via a novel route of CD147-spike protein (SP). SP bound to CD147, a receptor on the host cells, thereby mediating the viral invasion. Our further research confirmed this finding. First, in vitro antiviral tests indicated Meplazumab, an anti-CD147 humanized antibody, significantly inhibited the viruses from invading host cells, with an EC50 of 24.86 μg/mL and IC50 of 15.16 μg/mL. Second, we validated the interaction between CD147 and SP, with an affinity constant of 1.85×10-7M. Co-Immunoprecipitation and ELISA also confirmed the binding of the two proteins. Finally, the localization of CD147 and SP was observed in SARS-CoV-2 infected Vero E6 cells by immuno-electron microscope. Therefore, the discovery of the new route CD147-SP for SARS-CoV-2 invading host cells provides a critical target for development of specific antiviral drugs.

Cryo-EM structure of the 2019-nCoV spike in the prefusion conformation - Wrapp, Daniel; Wang, Nianshuang; Corbett, Kizzmekia S.; Goldsmith, Jory A.; Hsieh, Ching-Lin; Abiona, Olubukola; Graham, Barney S.; McLellan, Jason S. (Science, 2020)
The outbreak of a novel coronavirus (2019-nCoV) represents a pandemic threat that has been declared a public health emergency of international concern. The CoV spike (S) glycoprotein is a key target for vaccines, therapeutic antibodies, and diagnostics. To facilitate medical countermeasure development, we determined a 3.5-angstrom-resolution cryo–electron microscopy structure of the 2019-nCoV S trimer in the prefusion conformation. The predominant state of the trimer has one of the three receptor-binding domains (RBDs) rotated up in a receptor-accessible conformation. We also provide biophysical and structural evidence that the 2019-nCoV S protein binds angiotensin-converting enzyme 2 (ACE2) with higher affinity than does severe acute respiratory syndrome (SARS)-CoV S. Additionally, we tested several published SARS-CoV RBD-specific monoclonal antibodies and found that they do not have appreciable binding to 2019-nCoV S, suggesting that antibody cross-reactivity may be limited between the two RBDs. The structure of 2019-nCoV S should enable the rapid development and evaluation of medical countermeasures to address the ongoing public health crisis.

Mutations, Recombination and Insertion in the Evolution of 2019-nCoV - Wu, Aiping; Niu, Peihua; Wang, Lulan; Zhou, Hangyu; Zhao, Xiang; Wang, Wenling; Wang, Jingfeng; Ji, Chengyang; Ding, Xiao; Wang, Xianyue; Lu, Roujian; Gold, Sarah; et al. (2020)
Background: The 2019 novel coronavirus (2019-nCoV or SARS-CoV-2) has spread more rapidly than any other betacoronavirus including SARS-CoV and MERS-CoV. However, the mechanisms responsible for infection and molecular evolution of this virus 5 remained unclear. Methods: We collected and analyzed 120 genomic sequences of 2019-nCoV including 11 novel genomes from patients in China. Through comprehensive analysis of the available genome sequences of 2019-nCoV strains, we have tracked multiple inheritable SNPs and determined the evolution of 2019-nCoV relative to other 10 coronaviruses. Results: Systematic analysis of 120 genomic sequences of 2019-nCoV revealed cocirculation of two genetic subgroups with distinct SNPs markers, which can be used to trace the 2019-nCoV spreading pathways to different regions and countries. Although 2019-nCoV, human and bat SARS-CoV share high homologous in overall genome 15 structures, they evolved into two distinct groups with different receptor entry specificities through potential recombination in the receptor binding regions. In addition, 2019-nCoV has a unique four amino acid insertion between S1 and S2 domains of the spike protein, which created a potential furin or TMPRSS2 cleavage site. Conclusions: Our studies provided comprehensive insights into the evolution and 20

Severe acute respiratory syndrome-associated coronavirus 3a protein forms an ion channel and modulates virus release - Lu, W.; Zheng, B.-J.; Xu, K.; Schwarz, W.; Du, L.; Wong, C. K. L.; Chen, J.; Duan, S.; Deubel, V.; Sun, B. (Proceedings of the National Academy of Sciences, 2006)

A Novel Severe Acute Respiratory Syndrome Coronavirus Protein, U274, Is Transported to the Cell Surface and Undergoes Endocytosis - Tan, Y.-J.; Teng, E.; Shen, S.; Tan, T. H. P.; Goh, P.-Y.; Fielding, B. C.; Ooi, E.-E.; Tan, H.-C.; Lim, S. G.; Hong, W. (Journal of Virology, 2004)

Angiotensin-converting enzyme 2 protects from severe acute lung failure - Imai, Yumiko; Kuba, Keiji; Rao, Shuan; Huan, Yi; Guo, Feng; Guan, Bin; Yang, Peng; Sarao, Renu; Wada, Teiji; Leong-Poi, Howard; Crackower, Michael A.; Fukamizu, Akiyoshi; et al. (Nature, 2005)

The Severe Acute Respiratory Syndrome Coronavirus 3a Protein Up-Regulates Expression of Fibrinogen in Lung Epithelial Cells - Tan, Y.-J.; Tham, P.-Y.; Chan, D. Z. L.; Chou, C.-F.; Shen, S.; Fielding, B. C.; Tan, T. H. P.; Lim, S. G.; Hong, W. (Journal of Virology, 2005)

The discovery of angiotensin-converting enzyme 2 and its role in acute lung injury in mice: Discovery of ACE2 and its role in acute lung injury - Imai, Yumiko; Kuba, Keiji; Penninger, Josef M. (Experimental Physiology, 2008)

The ion channel activity of the SARS-coronavirus 3a protein is linked to its pro-apoptotic function - Chan, Chak-Ming; Tsoi, Ho; Chan, Wing-Man; Zhai, Shenyu; Wong, Ching-On; Yao, Xiaoqiang; Chan, Wood-Yee; Tsui, Stephen Kwok-Wing; Chan, Ho Yin Edwin (The International Journal of Biochemistry & Cell Biology, 2009)
The severe acute respiratory syndrome-coronavirus (SARS-CoV) caused an outbreak of atypical pneumonia in 2003. The SARS-CoV viral genome encodes several proteins which have no homology to proteins in any other coronaviruses, and a number of these proteins have been implicated in viral cytopathies. One such protein is 3a, which is also known as X1, ORF3 and U274. 3a expression is detected in both SARS-CoV infected cultured cells and patients. Among the different functions identiﬁed, 3a is a capable of inducing apoptosis. We previously showed that caspase pathways are involved in 3a-induced apoptosis. In this study, we attempted to ﬁnd out protein domains on 3a that are essential for its pro-apoptotic function. Protein sequence analysis reveals that 3a possesses three major protein signatures, the cysteine-rich, Yxx␾ and diacidic domains. We showed that 3a proteins carrying respective mutations in these protein domains exhibit reduced pro-apoptotic activities, indicating the importance of these domains on 3a’s pro-apoptotic function. It was previously reported that 3a possesses potassium ion channel activity. We further demonstrated that the blockade of 3a’s potassium channel activity abolished caspase-dependent apoptosis. This report provides the ﬁrst evidence that ion channel activity of 3a is required for its proapoptotic function. As ion channel activity has been reported to regulate apoptosis in different pathologic conditions, ﬁnding ways to modulate the ion channel activity may offer a new direction toward the inhibition of apoptosis triggered by SARS-CoV.

The SARS Coronavirus 3a Protein Causes Endoplasmic Reticulum Stress and Induces Ligand-Independent Downregulation of the Type 1 Interferon Receptor - Minakshi, Rinki; Padhan, Kartika; Rani, Manjusha; Khan, Nabab; Ahmad, Faizan; Jameel, Shahid (PLoS ONE, 2009)
The Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) is reported to cause apoptosis of infected cells and several of its proteins including the 3a accessory protein, are pro-apoptotic. Since the 3a protein localizes to the endoplasmic reticulum (ER)-Golgi compartment, its role in causing ER stress was investigated in transiently transfected cells. Cells expressing the 3a proteins showed ER stress based on activation of genes for the ER chaperones GRP78 and GRP94. Since ER stress can cause differential modulation of the unfolded protein response (UPR), which includes the inositol-requiring enzyme 1 (IRE-1), activating transcription factor 6 (ATF6) and PKR-like ER kinase (PERK) pathways, these were individually tested in 3a-expressing cells. Only the PERK pathway was found to be activated in 3a-expressing cells based on (1) increased phosphorylation of eukaryotic initiation factor 2 alpha (eIF2a) and inhibitory effects of a dominant-negative form of eIF2a on GRP78 promoter activity, (2) increased translation of activating transcription factor 4 (ATF4) mRNA, and (3) ATF4dependent activation of the C/EBP homologous protein (CHOP) gene promoter. Activation of PERK affects innate immunity by suppression of type 1 interferon (IFN) signaling. The 3a protein was found to induce serine phosphorylation within the IFN alpha-receptor subunit 1 (IFNAR1) degradation motif and to increase IFNAR1 ubiquitination. Confocal microscopic analysis showed increased translocation of IFNAR1 into the lysosomal compartment and flow cytometry showed reduced levels of IFNAR1 in 3a-expressing cells. These results provide further mechanistic details of the pro-apoptotic effects of the SARS-CoV 3a protein, and suggest a potential role for it in attenuating interferon responses and innate immunity.

Severe Acute Respiratory Syndrome Coronavirus Viroporin 3a Activates the NLRP3 Inflammasome - Chen, I-Yin; Moriyama, Miyu; Chang, Ming-Fu; Ichinohe, Takeshi (Frontiers in Microbiology, 2019)

Integrated network analysis reveals a novel role for the cell cycle in 2009 pandemic influenza virus-induced inflammation in macaque lungs - Shoemaker, Jason E; Fukuyama, Satoshi; Eisfeld, Amie J; Muramoto, Yukiko; Watanabe, Shinji; Watanabe, Tokiko; Matsuoka, Yukiko; Kitano, Hiroaki; Kawaoka, Yoshihiro (BMC Systems Biology, 2012)
Background: Annually, influenza A viruses circulate the world causing wide-spread sickness, economic loss, and death. One way to better defend against influenza virus-induced disease may be to develop novel host-based therapies, targeted at mitigating viral pathogenesis through the management of virus-dysregulated host functions. However, mechanisms that govern aberrant host responses to influenza virus infection remain incompletely understood. We previously showed that the pandemic H1N1 virus influenza A/California/04/2009 (H1N1; CA04) has enhanced pathogenicity in the lungs of cynomolgus macaques relative to a seasonal influenza virus isolate (A/Kawasaki/UTK-4/2009 (H1N1; KUTK4)). Results: Here, we used microarrays to identify host gene sequences that were highly differentially expressed (DE) in CA04-infected macaque lungs, and we employed a novel strategy – combining functional and pathway enrichment analyses, transcription factor binding site enrichment analysis and protein-protein interaction data – to create a CA04 differentially regulated host response network. This network describes enhanced viral RNA sensing, immune cell signaling and cell cycle arrest in CA04-infected lungs, and highlights a novel, putative role for the MYC-associated zinc finger (MAZ) transcription factor in regulating these processes. Conclusions: Our findings suggest that the enhanced pathology is the result of a prolonged immune response, despite successful virus clearance. Most interesting, we identify a mechanism which normally suppresses immune cell signaling and inflammation is ineffective in the pH1N1 virus infection; a dyregulatory event also associated with arthritis. This dysregulation offers several opportunities for developing strain-independent, immunomodulatory therapies to protect against future pandemics.

An Ultrasensitive Mechanism Regulates Influenza Virus-Induced Inflammation - Shoemaker, Jason E.; Fukuyama, Satoshi; Eisfeld, Amie J.; Zhao, Dongming; Kawakami, Eiryo; Sakabe, Saori; Maemura, Tadashi; Gorai, Takeo; Katsura, Hiroaki; Muramoto, Yukiko; Watanabe, Shinji; Watanabe, Tokiko; et al. (PLOS Pathogens, 2015)
Influenza viruses present major challenges to public health, evident by the 2009 influenza pandemic. Highly pathogenic influenza virus infections generally coincide with early, high levels of inflammatory cytokines that some studies have suggested may be regulated in a strain-dependent manner. However, a comprehensive characterization of the complex dynamics of the inflammatory response induced by virulent influenza strains is lacking. Here, we applied gene co-expression and nonlinear regression analysis to time-course, microarray data developed from influenza-infected mouse lung to create mathematical models of the host inflammatory response. We found that the dynamics of inflammation-associated gene expression are regulated by an ultrasensitive-like mechanism in which low levels of virus induce minimal gene expression but expression is strongly induced once a threshold virus titer is exceeded. Cytokine assays confirmed that the production of several key inflammatory cytokines, such as interleukin 6 and monocyte chemotactic protein 1, exhibit ultrasensitive behavior. A systematic exploration of the pathways regulating the inflammatoryassociated gene response suggests that the molecular origins of this ultrasensitive response mechanism lie within the branch of the Toll-like receptor pathway that regulates STAT1 phosphorylation. This study provides the first evidence of an ultrasensitive mechanism regulating influenza virus-induced inflammation in whole lungs and provides insight into how different virus strains can induce distinct temporal inflammation response profiles. The approach developed here should facilitate the construction of gene regulatory models of other infectious diseases.

The landscape of lung bronchoalveolar immune cells in COVID-19 revealed by single-cell RNA sequencing - Liao, Minfeng; Liu, Yang; Yuan, Jin; Wen, Yanling; Xu, Gang; Zhao, Juanjuan; Chen, Lin; Li, Jinxiu; Wang, Xin; Wang, Fuxiang; Liu, Lei; Zhang, Shuye; et al. (2020)
The novel coronavirus SARS-CoV-2, etiological agent of recently named Coronavirus infected disease (COVID-19) by WHO, has caused more than 2, 000 deaths worldwide since its emergency in Wuhan City, Hubei province, China, in December, 2019. The symptoms of COVID-19 varied from modest, mild to acute respiratory distress syndrome (ARDS), and the latter of which is generally associated with deregulated immune cytokine production; however, we currently know little as to the interplay between the extent of clinical symptoms and the compositions of lung immune microenvironment. Here, we comprehensively characterized the lung immune microenvironment with the bronchoalveolar lavage fluid (BALF) from 3 severe and 3 mild COVID-19 patients and 8 previously reported healthy lung controls through single-cell RNA sequence (scRNA-seq) combined with TCR-seq. Our data shows that monocyte-derived FCN1+ macrophages, whereas notFABP4+ alveolar macrophages that represent a predominant macrophage subset in BALF from patients with mild diseases, overwhelm in the severely damaged lungs from patients with ARDS. These cells are highly inflammatory and enormous chemokine producers implicated in cytokine storm. Furthermore, the formation of tissue resident, highly expanded clonal CD8+ T cells in the lung microenvironment of mild symptom patients suggests a robust adaptive immune response connected to a better control of COVID-19. This study first reported the cellular atlas of lung bronchoalveolar immune microenvironment in COVID-19 patients at the single-cell resolution, and unveiled the potential immune mechanisms underlying disease progression and protection in COVID-19.

Therapeutic Approaches for COVID-19 Based on the Dynamics of Interferon-mediated Immune Responses (2020)
As the outbreak of COVID-19 has accelerated, an urgent need for finding strategies to combat the virus is growing. Thus, gaining more knowledge on the pathogenicity mechanism of SARS-CoV2, the causing agent of COVID-19, and its interaction with the immune system is of utmost importance. Although this novel virus is not well known yet, its structural and genetic similarity with SARS-CoV as well as the comparable pattern of age-mortality relations suggest that the previous findings on SARS can be applicable for COVID-19. Therefore, a systems biology study was conducted to investigate the underlying mechanism for the differences in the age-specific mortality of SARS and the most important signaling pathways activated by the virus. The results were then validated through a literature review on COVID-19 and the other closely related viruses, SARS and MERS.

Breadth of concomitant immune responses prior to patient recovery: a case report of non-severe COVID-19 - Thevarajan, Irani; Nguyen, Thi H. O.; Koutsakos, Marios; Druce, Julian; Caly, Leon; van de Sandt, Carolien E.; Jia, Xiaoxiao; Nicholson, Suellen; Catton, Mike; Cowie, Benjamin; Tong, Steven Y. C.; Lewin, Sharon R.; et al. (Nature Medicine, 2020)

Evidence for gastrointestinal infection of SARS-CoV-2 - Xiao, Fei; Tang, Meiwen; Zheng, Xiaobin; Liu, Ye; Li, Xiaofeng; Shan, Hong (Gastroenterology, 2020)

Multiple organ infection and the pathogenesis of SARS - Gu, Jiang; Gong, Encong; Zhang, Bo; Zheng, Jie; Gao, Zifen; Zhong, Yanfeng; Zou, Wanzhong; Zhan, Jun; Wang, Shenglan; Xie, Zhigang; Zhuang, Hui; Wu, Bingquan; et al. (Journal of Experimental Medicine, 2005)
After >8,000 infections and >700 deaths worldwide, the pathogenesis of the new infectious disease, severe acute respiratory syndrome (SARS), remains poorly understood. We investigated 18 autopsies of patients who had suspected SARS; 8 cases were confirmed as SARS. We evaluated white blood cells from 22 confirmed SARS patients at various stages of the disease. T lymphocyte counts in 65 confirmed and 35 misdiagnosed SARS cases also were analyzed retrospectively. SARS viral particles and genomic sequence were detected in a large number of circulating lymphocytes, monocytes, and lymphoid tissues, as well as in the epithelial cells of the respiratory tract, the mucosa of the intestine, the epithelium of the renal distal tubules, the neurons of the brain, and macrophages in different organs. SARS virus seemed to be capable of infecting multiple cell types in several organs; immune cells and pulmonary epithelium were identified as the main sites of injury. A comprehensive theory of pathogenesis is proposed for SARS with immune and lung damage as key features.

Reinfection could not occur in SARS-CoV-2 infected rhesus macaques - Bao, Linlin; Deng, Wei; Gao, Hong; Xiao, Chong; Liu, Jiayi; Xue, Jing; Lv, Qi; Liu, Jiangning; Yu, Pin; Xu, Yanfeng; Qi, Feifei; Qu, Yajin; et al. (2020)
Abstract An outbreak of the Corona Virus Disease 2019 (COVID-19), caused by the severe acute respiratory syndrome CoV-2 (SARS-CoV-2), began in Wuhan and spread globally. Recently, it has been reported that discharged patients in China and elsewhere were testing positive after recovering. However, it remains unclear whether the convalescing patients have a risk of “relapse” or “reinfection”. The longitudinal tracking of re-exposure after the disappeared symptoms of the SARS-CoV-2-infected monkeys was performed in this study. We found that weight loss in some monkeys, viral replication mainly in nose, pharynx, lung and gut, as well as moderate interstitial pneumonia at 7 days post-infection (dpi) were clearly observed in rhesus monkeys after the primary infection. After the symptoms were alleviated and the specific antibody tested positively, the half of infected monkeys were rechallenged with the same dose of SARS-CoV-2 strain. Notably, neither viral loads in nasopharyngeal and anal swabs along timeline nor viral replication in all primary tissue compartments at 5 days post-reinfection (dpr) was found in re-exposed monkeys. Combined with the follow-up virologic, radiological and pathological findings, the monkeys with re-exposure showed no recurrence of COVID-19, similarly to the infected monkey without rechallenge. Taken together, our results indicated that the primary SARS-CoV-2 infection could protect from subsequent exposures, which have the reference of prognosis of the disease and vital implications for vaccine design.

Clinical characteristics of 2019 novel coronavirus infection in China - Guan, Wei-jie; Ni, Zheng-yi; Hu, Yu; Liang, Wen-hua; Ou, Chun-quan; He, Jian-xing; Liu, Lei; Shan, Hong; Lei, Chun-liang; Hui, David SC; Du, Bin; Li, Lan-juan; et al. (2020)
Background: Since December 2019, acute respiratory disease (ARD) due to 2019 novel coronavirus (2019-nCoV) emerged in Wuhan city and rapidly spread throughout China. We sought to delineate the clinical characteristics of these cases.

Clinical features of patients infected with 2019 novel coronavirus in Wuhan, China - Huang, Chaolin; Wang, Yeming; Li, Xingwang; Ren, Lili; Zhao, Jianping; Hu, Yi; Zhang, Li; Fan, Guohui; Xu, Jiuyang; Gu, Xiaoying; Cheng, Zhenshun; Yu, Ting; et al. (The Lancet, 2020)
Background A recent cluster of pneumonia cases in Wuhan, China, was caused by a novel betacoronavirus, the 2019 novel coronavirus (2019-nCoV). We report the epidemiological, clinical, laboratory, and radiological characteristics and treatment and clinical outcomes of these patients.

Eleven Faces of Coronavirus Disease 2019 - Dong, Xiang; Cao, Yi-yuan; Lu, Xiao-xia; Zhang, Jin-jin; Du, Hui; Yan, You-qin; Akdis, Cezmi A.; Gao, Ya-dong (Allergy, 2020)
Background and aims: The outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has recently spread worldwide and been declared a pandemic. We aim to describe here the various clinical presentations of this disease by examining eleven cases. Methods: Electronic medical records of 11 patients with COVID-19 were collected and demographics, clinical manifestations, outcomes, key laboratory results, and radiological images are discussed. Results: The clinical course of the eleven cases demonstrated the complexity of the COVID-19 profile with different clinical presentations. Clinical manifestations range from asymptomatic cases to patients with mild and severe symptoms, with or without pneumonia. Laboratory detection of the viral nucleic acid can yield false-negative results, and serological testing of virus specific IgG and IgM antibodies should be used as an alternative for diagnosis. Patients with common allergic diseases did not develop distinct symptoms and severe courses. Cases with a pre-existing condition of chronic obstructive pulmonary disease or complicated with a secondary bacterial pneumonia were more severe. Conclusion: All different clinical characteristics of COVID-19 should be taken into consideration to identify patients that need to be in strict quarantine for the efficient containment of the pandemic.

SARS-CoV-2 is sensitive to type I interferon pretreatment - Lokugamage, Kumari G.; Hage, Adam; Schindewolf, Craig; Rajsbaum, Ricardo; Menachery, Vineet D. (2020)
Abstract SARS-CoV-2, a novel coronavirus (CoV), has recently emerged causing an ongoing outbreak of viral pneumonia around the world. While genetically distinct from the original SARS-CoV, both group 2B CoVs share similar genome organization and origins to coronaviruses harbored in bats. Importantly, initial guidance has used insights from SARS-CoV infection to inform treatment and public health strategies. In this report, we evaluate type-I Interferon (IFN-I) sensitivity of SARS-CoV-2 relative to the original SARS-CoV. Our results indicate that while SARS-CoV-2 maintains similar viral replication kinetics to SARS-CoV in Vero cell, the novel CoV is much more sensitive to IFN-I pretreatment. Examining transcriptional factor activation and interferon stimulated gene (ISG) induction, SARS-CoV-2 in the context of type I IFN induces phosphorylation of STAT1 and increased ISG proteins. In contrast, the original SARS-CoV has no evidence for STAT1 phosphorylation or ISG protein increases even in the presence of type I IFN pretreatment. Finally, we examined homology between SARS-CoV and SARS-CoV-2 in viral proteins shown to be interferon antagonist. The absence of open reading frame (ORF) 3b and significant changes to ORF6 suggest the two key IFN antagonists may not maintain equivalent function in SARS-CoV-2. Together, the results identify key differences in susceptibility to the IFN-I response between SARS-CoV and SARS-CoV-2. that could help inform disease progression, treatment options, and animal model development. Importance With the ongoing outbreak of COVID-19 disease, differences between the SARS-CoV-2 and the original SARS-CoV could be leveraged to inform disease progression and eventual treatment options. In addition, these findings could have key implications for animal model development as well as further research into how SARS-CoV-2 modulates the type I IFN response early during infection. Article Summary SARS-CoV-2 has similar replication kinetics to SARS-CoV, but demonstrates significant sensitivity to type I interferon treatment.

COVID-19: combining antiviral and anti-inflammatory treatments - Stebbing, Justin; Phelan, Anne; Griffin, Ivan; Tucker, Catherine; Oechsle, Olly; Smith, Dan; Richardson, Peter (The Lancet Infectious Diseases, 2020)

Exploring diseases/traits and blood proteins causally related to expression of ACE2, the putative receptor of 2019-nCov: A Mendelian Randomization analysis - Rao, Shitao; Lau, Alexandria; So, Hon-Cheong (2020)
The novel coronavirus 2019-nCoV has caused major outbreaks in many parts of the world. A better understanding of the pathophysiology of COVID-19 is urgently needed. Clinically, it is important to identify who may be susceptible to infection and identify treatments for the disease.

Network Bioinformatics Analysis Provides Insight into Drug Repurposing for COVID-2019 - Li, Xu; Yu, Jinchao; Zhang, Zhiming; Ren, Jing; Peluffo, Alex E.; Zhang, Wen; Zhao, Yujie; Yan, Kaijing; Cohen, Daniel; Wang, Wenjia (2020)
The COVID-2019 disease caused by the SARS-CoV-2 virus (aka 2019-nCoV) has raised significant health concerns in China and worldwide. While novel drug discovery and vaccine studies are long, repurposing old drugs against the COVID-2019 epidemic can help identify treatments, with known preclinical, pharmacokinetic, pharmacodynamic, and toxicity profiles, which can rapidly enter Phase 3 or 4 or can be used directly in clinical settings. In this study, we presented a novel network based drug repurposing platform to identify potential drugs for the treatment of COVID-2019. We first analysed the genome sequence of SARS-CoV-2 and identified SARS as the closest disease, based on genome similarity between both causal viruses, followed by MERS and other human coronavirus diseases. Using our AutoSeed pipeline (text mining and database searches), we obtained 34 COVID-2019-related genes. Taking those genes as seeds, we automatically built a molecular network for which our module detection and drug prioritization algorithms identified 24 disease-related human pathways, five modules and finally suggested 78 drugs to repurpose. Following manual filtering based on clinical knowledge, we re-prioritized 30 potential repurposable drugs against COVID-2019 (including pseudoephedrine, andrographolide, chloroquine, abacavir, and thalidomide) . We hope that this data can provide critical insights into SARS-CoV-2 biology and help design rapid clinical trials of treatments against COVID-2019.

Emodin inhibits current through SARS-associated coronavirus 3a protein - Schwarz, Silvia; Wang, Kai; Yu, Wenjing; Sun, Bing; Schwarz, Wolfgang (Antiviral Research, 2011)
The open-reading-frame 3a of SARS coronavirus (SARS-CoV) had been demonstrated previously to form a cation-selective channel that may become expressed in the infected cell and is then involved in virus release. Drugs that inhibit the ion channel formed by the 3a protein can be expected to inhibit virus release, and would be a source for the development of novel therapeutic agents. Here we demonstrate that emodin can inhibit the 3a ion channel of coronavirus SARS-CoV and HCoV-OC43 as well as virus release from HCoV-OC43 with a K1/2 value of about 20 ␮M. We suggest that viral ion channels, in general, may be a good target for the development of antiviral agents.

Mechanisms and enzymes involved in SARS coronavirus genome expression - Thiel, Volker; Ivanov, Konstantin A.; Putics, Ákos; Hertzig, Tobias; Schelle, Barbara; Bayer, Sonja; Weißbrich, Benedikt; Snijder, Eric J.; Rabenau, Holger; Doerr, Hans Wilhelm; Gorbalenya, Alexander E.; Ziebuhr, John (Journal of General Virology, 2003)

Molecular immune pathogenesis and diagnosis of COVID-19 - Li, Xiaowei; Geng, Manman; Peng, Yizhao; Meng, Liesu; Lu, Shemin (Journal of Pharmaceutical Analysis, 2020)

The emergence of a novel coronavirus (SARS-CoV-2), their biology and therapeutic options - Khan, Suliman; Siddique, Rabeea; Shereen, Muhammad Adnan; Ali, Ashaq; Liu, Jianbo; Bai, Qian; Bashir, Nadia; Xue, Mengzhou (Journal of Clinical Microbiology, 2020)
The new decade of the 21 st century (2020) started with the emergence of novel coronavirus known as SARS-CoV-2 that caused an epidemic of coronavirus disease (COVID-19) in Wuhan, China. It is the third highly pathogenic and transmissible coronavirus after severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) emerged in humans. The source of origin, transmission to humans and mechanisms associated with the pathogenicity of SARS-CoV-2 are not clear yet, however, its resemblance with SARS-CoV and several other bat coronaviruses was recently confirmed through genome sequencing related studies. The development of therapeutic strategies is necessary in order to prevent further epidemics and cure infected people. In this Review, we summarize current information about the emergence, origin, diversity, and epidemiology of three pathogenic coronaviruses with a specific focus on the current outbreak in Wuhan, China. Furthermore, we discuss the clinical features and potential therapeutic options that may be effective against SARS-CoV-2.

A tug-of-war between severe acute respiratory syndrome coronavirus 2 and host antiviral defence: lessons from other pathogenic viruses - Fung, Sin-Yee; Yuen, Kit-San; Ye, Zi-Wei; Chan, Chi-Ping; Jin, Dong-Yan (Emerging Microbes & Infections, 2020)
World Health Organization has declared the ongoing outbreak of coronavirus disease 2019 (COVID-19) a Public Health Emergency of International Concern. The virus was named severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) by the International Committee on Taxonomy of Viruses. Human infection with SARS-CoV-2 leads to a wide range of clinical manifestations ranging from asymptomatic, mild, moderate to severe. The severe cases present with pneumonia, which can progress to acute respiratory distress syndrome. The outbreak provides an opportunity for real-time tracking of an animal coronavirus that has just crossed species barrier to infect humans. The outcome of SARS-CoV-2 infection is largely determined by virus-host interaction. Here, we review the discovery, zoonotic origin, animal hosts, transmissibility and pathogenicity of SARS-CoV-2 in relation to its interplay with host antiviral defense. A comparison with SARS-CoV, Middle East respiratory syndrome coronavirus, community-acquired human coronaviruses and other pathogenic viruses including human immunodeﬁciency viruses is made. We summarize current understanding of the induction of a proinﬂammatory cytokine storm by other highly pathogenic human coronaviruses, their adaptation to humans and their usurpation of the cell death programmes. Important questions concerning the interaction between SARS-CoV-2 and host antiviral defence, including asymptomatic and presymptomatic virus shedding, are also discussed.

Understanding SARS-CoV-2-Mediated Inflammatory Responses: From Mechanisms to Potential Therapeutic Tools - Fu, Yajing; Cheng, Yuanxiong; Wu, Yuntao (Virologica Sinica, 2020)
Currently there is no effective antiviral therapy for SARS-CoV-2 infection, which frequently leads to fatal inﬂammatory responses and acute lung injury. Here, we discuss the various mechanisms of SARS-CoV-mediated inﬂammation. We also assume that SARS-CoV-2 likely shares similar inﬂammatory responses. Potential therapeutic tools to reduce SARS-CoV-2 -induced inﬂammatory responses include various methods to block FcR activation. In the absence of a proven clinical FcR blocker, the use of intravenous immunoglobulin to block FcR activation may be a viable option for the urgent treatment of pulmonary inﬂammation to prevent severe lung injury. Such treatment may also be combined with systemic anti-inﬂammatory drugs or corticosteroids. However, these strategies, as proposed here, remain to be clinically tested for effectiveness.

Emerging coronaviruses: Genome structure, replication, and pathogenesis - Chen, Yu; Liu, Qianyun; Guo, Deyin (Journal of Medical Virology, 2020)
The recent emergence of a novel coronavirus (2019‐nCoV), which is causing an outbreak of unusual viral pneumonia in patients in Wuhan, a central city in China, is another warning of the risk of CoVs posed to public health. In this minireview, we provide a brief introduction of the general features of CoVs and describe diseases caused by different CoVs in humans and animals. This review will help understand the biology and potential risk of CoVs that exist in richness in wildlife such as bats.

Human Coronavirus: Host-Pathogen Interaction - Fung, To Sing; Liu, Ding Xiang (Annual Review of Microbiology, 2019)
Human coronavirus (HCoV) infection causes respiratory diseases with mild to severe outcomes. In the last 15 years, we have witnessed the emergence of two zoonotic, highly pathogenic HCoVs: severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV). Replication of HCoV is regulated by a diversity of host factors and induces drastic alterations in cellular structure and physiology. Activation of critical signaling pathways during HCoV infection modulates the induction of antiviral immune response and contributes to the pathogenesis of HCoV. Recent studies have begun to reveal some fundamental aspects of the intricate HCoV-host interaction in mechanistic detail. In this review, we summarize the current knowledge of host factors co-opted and signaling pathways activated during HCoV infection, with an emphasis on HCoV-infection-induced stress response, autophagy, apoptosis, and innate immunity. The cross talk among these pathways, as well as the modulatory strategies utilized by HCoV, is also discussed.

Incorporation of Spike and Membrane Glycoproteins into Coronavirus Virions - Ujike, Makoto; Taguchi, Fumihiro (Viruses, 2015)
The envelopes of coronaviruses (CoVs) contain primarily three proteins; the two major glycoproteins spike (S) and membrane (M), and envelope (E), a non-glycosylated protein. Unlike other enveloped viruses, CoVs bud and assemble at the endoplasmic reticulum (ER)-Golgi intermediate compartment (ERGIC). For efficient virion assembly, these proteins must be targeted to the budding site and to interact with each other or the ribonucleoprotein. Thus, the efficient incorporation of viral envelope proteins into CoV virions depends on protein trafficking and protein–protein interactions near the ERGIC. The goal of this review is to summarize recent findings on the mechanism of incorporation of the M and S glycoproteins into the CoV virion, focusing on protein trafficking and protein–protein interactions.

The Molecular Biology of Coronaviruses - Masters, Paul S. (Advances in Virus Research, 2006)

The Coronaviridae: An Introduction - Siddell, Stuart G. (The Coronaviridae, 1995)

To sense or not to sense viral RNA—essentials of coronavirus innate immune evasion - Kindler, Eveline; Thiel, Volker (Current Opinion in Microbiology, 2014)
An essential function of innate immunity is to distinguish self from non-self and receptors have evolved to specifically recognize viral components and initiate the expression of antiviral proteins to restrict viral replication. Coronaviruses are RNA viruses that replicate in the host cytoplasm and evade innate immune sensing in most cell types, either passively by hiding their viral signatures and limiting exposure to sensors or actively, by encoding viral antagonists to counteract the effects of interferons. Since many cytoplasmic viruses exploit similar mechanisms of innate immune evasion, mechanistic insight into the direct interplay between viral RNA, viral RNA-processing enzymes, cellular sensors and antiviral proteins will be highly relevant to develop novel antiviral targets and to restrict important animal and human infections.

Immune responses in influenza A virus and human coronavirus infections: an ongoing battle between the virus and host - Zheng, Jian; Perlman, Stanley (Current Opinion in Virology, 2018)
Respiratory viruses, especially influenza A viruses and coronaviruses such as MERS-CoV, represent continuing global threats to human health. Despite significant advances, much needs to be learned. Recent studies in virology and immunology have improved our understanding of the role of the immune system in protection and in the pathogenesis of these infections and of co-evolution of viruses and their hosts. These findings, together with sophisticated molecular structure analyses, omics tools and computer-based models, have helped delineate the interaction between respiratory viruses and the host immune system, which will facilitate the development of novel treatment strategies and vaccines with enhanced efficacy.

A molecular arms race between host innate antiviral response and emerging human coronaviruses - Wong, Lok-Yin Roy; Lui, Pak-Yin; Jin, Dong-Yan (Virologica Sinica, 2016)
Coronaviruses have been closely related with mankind for thousands of years. Communityacquired human coronaviruses have long been recognized to cause common cold. However, zoonotic coronaviruses are now becoming more a global concern with the discovery of highly pathogenic severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) coronaviruses causing severe respiratory diseases. Infections by these emerging human coronaviruses are characterized by less robust interferon production. Treatment of patients with recombinant interferon regimen promises beneficial outcomes, suggesting that compromised interferon expression might contribute at least partially to the severity of disease. The mechanisms by which coronaviruses evade host innate antiviral response are under intense investigations. This review focuses on the fierce arms race between host innate antiviral immunity and emerging human coronaviruses. Particularly, the host pathogen recognition receptors and the signal transduction pathways to mount an effective antiviral response against SARS and MERS coronavirus infection are discussed. On the other hand, the counter-measures evolved by SARS and MERS coronaviruses to circumvent host defense are also dissected. With a better understanding of the dynamic interaction between host and coronaviruses, it is hoped that insights on the pathogenesis of newly-identified highly pathogenic human coronaviruses and new strategies in antiviral development can be derived.

Pathogenic human coronavirus infections: causes and consequences of cytokine storm and immunopathology - Channappanavar, Rudragouda; Perlman, Stanley (Seminars in Immunopathology, 2017)
Human coronaviruses (hCoVs) can be divided into low pathogenic and highly pathogenic coronaviruses. The low pathogenic CoVs infect the upper respiratory tract and cause mild, cold-like respiratory illness. In contrast, highly pathogenic hCoVs such as severe acute respiratory syndrome CoV (SARS-CoV) and Middle East respiratory syndrome CoV (MERS-CoV) predominantly infect lower airways and cause fatal pneumonia. Severe pneumonia caused by pathogenic hCoVs is often associated with rapid virus replication, massive inflammatory cell infiltration and elevated pro-inflammatory cytokine/chemokine responses resulting in acute lung injury (ALI), and acute respiratory distress syndrome (ARDS). Recent studies in experimentally infected animal strongly suggest a crucial role for virus-induced immunopathological events in causing fatal pneumonia after hCoV infections. Here we review the current understanding of how a dysregulated immune response may cause lung immunopathology leading to deleterious clinical manifestations after pathogenic hCoV infections.

NLRP3 Inflammasome-A Key Player in Antiviral Responses - Zhao, Chunyuan; Zhao, Wei (Frontiers in Immunology, 2020)
The NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome is an oligomeric complex comprised of the NOD-like receptor NLRP3, the adaptor ASC, and caspase-1. This complex is crucial to the host’s defense against microbes as it promotes IL-1β and IL-18 secretion and induces pyroptosis. NLRP3 recognizes variety of pathogen-associated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPs) generated during viral replication that triggers the NLRP3 inflammasome-dependent antiviral immune responses and facilitates viral eradication. Meanwhile, several viruses have evolved elaborate strategies to evade the immune system by targeting the NLRP3 inflammasome. In this review, we will focus on the crosstalk between the NLRP3 inflammasome and viruses, provide an overview of viral infection-induced NLRP3 inflammasome activation, and the immune escape strategies of viruses through their modulation of the NLRP3 inflammasome activity.

Coronavirus infections and immune responses - Li, Geng; Fan, Yaohua; Lai, Yanni; Han, Tiantian; Li, Zonghui; Zhou, Peiwen; Pan, Pan; Wang, Wenbiao; Hu, Dingwen; Liu, Xiaohong; Zhang, Qiwei; Wu, Jianguo (Journal of Medical Virology, 2020)
Coronaviruses (CoVs) are by far the largest group of known positive-sense RNA viruses having an extensive range of natural hosts. In the past few decades, newly evolved Coronaviruses have posed a global threat to public health. The immune response is essential to control and eliminate CoV infections, however, maladjusted immune responses may result in immunopathology and impaired pulmonary gas exchange. Gaining a deeper understanding of the interaction between Coronaviruses and the innate immune systems of the hosts may shed light on the development and persistence of inflammation in the lungs and hopefully can reduce the risk of lung inflammation caused by CoVs. In this review, we provide an update on CoV infections and relevant diseases, particularly the host defense against CoV-induced inflammation of lung tissue, as well as the role of the innate immune system in the pathogenesis and clinical treatment.

Host Factors in Coronavirus Replication - de Wilde, Adriaan H.; Snijder, Eric J.; Kikkert, Marjolein; van Hemert, Martijn J. (Roles of Host Gene and Non-coding RNA Expression in Virus Infection, 2018)
Coronaviruses are pathogens with a serious impact on human and animal health. They mostly cause enteric or respiratory disease, which can be severe and life threatening, e.g., in the case of the zoonotic coronaviruses causing severe acute respiratory syndrome (SARS) and Middle East Respiratory Syndrome (MERS) in humans. Despite the economic and societal impact of such coronavirus infections, and the likelihood of future outbreaks of additional pathogenic coronaviruses, our options to prevent or treat coronavirus infections remain very limited. This highlights the importance of advancing our knowledge on the replication of these viruses and their interactions with the host. Compared to other +RNA viruses, coronaviruses have an exceptionally large genome and employ a complex genome expression strategy. Next to a role in basic virus replication or virus assembly, many of the coronavirus proteins expressed in the infected cell contribute to the coronavirus-host interplay. For example, by interacting with the host cell to create an optimal environment for coronavirus replication, by altering host gene expression or by counteracting the host’s antiviral defenses. These coronavirus–host interactions are key to viral pathogenesis and will ultimately determine the outcome of infection. Due to the complexity of the coronavirus proteome and replication cycle, our knowledge of host factors involved in coronavirus replication is still in an early stage compared to what is known for some other +RNA viruses. This review summarizes our current understanding of coronavirus–host interactions at the level of the infected cell, with special attention for the assembly and function of the viral RNA-synthesising machinery and the evasion of cellular innate immune responses.

Coronaviruses post-SARS: update on replication and pathogenesis - Perlman, Stanley; Netland, Jason (Nature Reviews Microbiology, 2009)

ORF8-Related Genetic Evidence for Chinese Horseshoe Bats as the Source of Human Severe Acute Respiratory Syndrome Coronavirus - Wu, Zhiqiang; Yang, Li; Ren, Xianwen; Zhang, Junpeng; Yang, Fan; Zhang, Shuyi; Jin, Qi (The Journal of Infectious Diseases, 2016)
Abstract. Several lineage B betacoronaviruses termed severe acute respiratory syndrome (SARS)–like CoVs (SL-CoVs) were identified from Rhinolophus bats in Chin

Genomic variance of the 2019-nCoV coronavirus - Ceraolo, Carmine; Giorgi, Federico M. (Journal of Medical Virology, 2020)
There is a rising global concern for the recently emerged novel coronavirus (2019-nCoV). Full genomic sequences have been released by the worldwide scientific community in the last few weeks to understand the evolutionary origin and molecular characteristics of this virus. Taking advantage of all the genomic information currently available, we constructed a phylogenetic tree including also representatives of other coronaviridae, such as Bat coronavirus (BCoV) and severe acute respiratory syndrome. We confirm high sequence similarity (>99%) between all sequenced 2019-nCoVs genomes available, with the closest BCoV sequence sharing 96.2% sequence identity, confirming the notion of a zoonotic origin of 2019-nCoV. Despite the low heterogeneity of the 2019-nCoV genomes, we could identify at least two hypervariable genomic hotspots, one of which is responsible for a Serine/Leucine variation in the viral ORF8-encoded protein. Finally, we perform a full proteomic comparison with other coronaviridae, identifying key aminoacidic differences to be considered for antiviral strategies deriving from previous anti-coronavirus approaches.

Severe Acute Respiratory Syndrome (SARS) Coronavirus ORF8 Protein Is Acquired from SARS-Related Coronavirus from Greater Horseshoe Bats through Recombination - Lau, Susanna K. P.; Feng, Yun; Chen, Honglin; Luk, Hayes K. H.; Yang, Wei-Hong; Li, Kenneth S. M.; Zhang, Yu-Zhen; Huang, Yi; Song, Zhi-Zhong; Chow, Wang-Ngai; Fan, Rachel Y. Y.; Ahmed, Syed Shakeel; et al. (Journal of Virology, 2015)
Despite the identification of horseshoe bats as the reservoir of severe acute respiratory syndrome (SARS)-related coronaviruses (SARSr-CoVs), the origin of SARS-CoV ORF8, which contains the 29-nucleotide signature deletion among human strains, remains obscure. Although two SARS-related Rhinolophus sinicus bat CoVs (SARSr-Rs-BatCoVs) previously detected in Chinese horseshoe bats (Rhinolophus sinicus) in Yunnan, RsSHC014 and Rs3367, possessed 95% genome identities to human and civet SARSr-CoVs, their ORF8 protein exhibited only 32.2 to 33% amino acid identities to that of human/civet SARSr-CoVs. To elucidate the origin of SARS-CoV ORF8, we sampled 348 bats of various species in Yunnan, among which diverse alphacoronaviruses and betacoronaviruses, including potentially novel CoVs, were identified, with some showing potential interspecies transmission. The genomes of two betacoronaviruses, SARSr-Rf-BatCoV YNLF_31C and YNLF_34C, from greater horseshoe bats (Rhinolophus ferrumequinum), possessed 93% nucleotide identities to human/civet SARSr-CoV genomes. Although these two betacoronaviruses displayed lower similarities than SARSr-Rs-BatCoV RsSHC014 and Rs3367 in S protein to civet SARSr-CoVs, their ORF8 proteins demonstrated exceptionally high (80.4 to 81.3%) amino acid identities to that of human/civet SARSr-CoVs, compared to SARSr-BatCoVs from other horseshoe bats (23.2 to 37.3%). Potential recombination events were identified around ORF8 between SARSr-Rf-BatCoVs and SARSr-Rs-BatCoVs, leading to the generation of civet SARSr-CoVs. The expression of ORF8 subgenomic mRNA suggested that the ORF8 protein may be functional in SARSr-Rf-BatCoVs. The high Ka/Ks ratio among human SARS-CoVs compared to that among SARSr-BatCoVs supported that ORF8 is under strong positive selection during animal-to-human transmission. Molecular clock analysis using ORF1ab showed that SARSr-Rf-BatCoV YNLF_31C and YNLF_34C diverged from civet/human SARSr-CoVs in approximately 1990. SARS-CoV ORF8 originated from SARSr-CoVs of greater horseshoe bats through recombination, which may be important for animal-to-human transmission., IMPORTANCE Although horseshoe bats are the primary reservoir of SARS-related coronaviruses (SARSr-CoVs), it is still unclear how these bat viruses have evolved to cross the species barrier to infect civets and humans. Most human SARS-CoV epidemic strains contain a signature 29-nucleotide deletion in ORF8, compared to civet SARSr-CoVs, suggesting that ORF8 may be important for interspecies transmission. However, the origin of SARS-CoV ORF8 remains obscure. In particular, SARSr-Rs-BatCoVs from Chinese horseshoe bats (Rhinolophus sinicus) exhibited <40% amino acid identities to human/civet SARS-CoV in the ORF8 protein. We detected diverse alphacoronaviruses and betacoronaviruses among various bat species in Yunnan, China, including two SARSr-Rf-BatCoVs from greater horseshoe bats that possessed ORF8 proteins with exceptionally high amino acid identities to that of human/civet SARSr-CoVs. We demonstrated recombination events around ORF8 between SARSr-Rf-BatCoVs and SARSr-Rs-BatCoVs, leading to the generation of civet SARSr-CoVs. Our findings offer insight into the evolutionary origin of SARS-CoV ORF8 protein, which was likely acquired from SARSr-CoVs of greater horseshoe bats through recombination.

Genomic characterization of the 2019 novel human-pathogenic coronavirus isolated from a patient with atypical pneumonia after visiting Wuhan - Chan, Jasper Fuk-Woo; Kok, Kin-Hang; Zhu, Zheng; Chu, Hin; To, Kelvin Kai-Wang; Yuan, Shuofeng; Yuen, Kwok-Yung (Emerging Microbes & Infections, 2020)
A mysterious outbreak of atypical pneumonia in late 2019 was traced to a seafood wholesale market in Wuhan of China. Within a few weeks, a novel coronavirus tentatively named as 2019 novel coronavirus (2019-nCoV) was announced by the World Health Organization. We performed bioinformatics analysis on a virus genome from a patient with 2019-nCoV infection and compared it with other related coronavirus genomes. Overall, the genome of 2019-nCoV has 89% nucleotide identity with bat SARS-like-CoVZXC21 and 82% with that of human SARS-CoV. The phylogenetic trees of their orf1a/b, Spike, Envelope, Membrane and Nucleoprotein also clustered closely with those of the bat, civet and human SARS coronaviruses. However, the external subdomain of Spike’s receptor binding domain of 2019-nCoV shares only 40% amino acid identity with other SARS-related coronaviruses. Remarkably, its orf3b encodes a completely novel short protein. Furthermore, its new orf8 likely encodes a secreted protein with an alpha-helix, following with a beta-sheet(s) containing six strands. Learning from the roles of civet in SARS and camel in MERS, hunting for the animal source of 2019-nCoV and its more ancestral virus would be important for understanding the origin and evolution of this novel lineage B betacoronavirus. These findings provide the basis for starting further studies on the pathogenesis, and optimizing the design of diagnostic, antiviral and vaccination strategies for this emerging infection.

Attenuation of replication by a 29 nucleotide deletion in SARS-coronavirus acquired during the early stages of human-to-human transmission - Muth, Doreen; Corman, Victor Max; Roth, Hanna; Binger, Tabea; Dijkman, Ronald; Gottula, Lina Theresa; Gloza-Rausch, Florian; Balboni, Andrea; Battilani, Mara; Rihtarič, Danijela; Toplak, Ivan; Ameneiros, Ramón Seage; et al. (Scientific Reports, 2018)
A 29 nucleotide deletion in open reading frame 8 (ORF8) is the most obvious genetic change in severe acute respiratory syndrome coronavirus (SARS-CoV) during its emergence in humans. In spite of intense study, it remains unclear whether the deletion actually reflects adaptation to humans. Here we engineered full, partially deleted (−29 nt), and fully deleted ORF8 into a SARS-CoV infectious cDNA clone, strain Frankfurt-1. Replication of the resulting viruses was compared in primate cell cultures as well as Rhinolophus bat cells made permissive for SARS-CoV replication by lentiviral transduction of the human angiotensin-converting enzyme 2 receptor. Cells from cotton rat, goat, and sheep provided control scenarios that represent host systems in which SARS-CoV is neither endemic nor epidemic. Independent of the cell system, the truncation of ORF8 (29 nt deletion) decreased replication up to 23-fold. The effect was independent of the type I interferon response. The 29 nt deletion in SARS-CoV is a deleterious mutation acquired along the initial human-to-human transmission chain. The resulting loss of fitness may be due to a founder effect, which has rarely been documented in processes of viral emergence. These results have important implications for the retrospective assessment of the threat posed by SARS.

COVID-19: Attacks the 1-Beta Chain of Hemoglobin and Captures the Porphyrin to Inhibit Human Heme Metabolism - Wenzhong, Liu; Hualan, Li (2020)
The novel coronavirus pneumonia (COVID-19) is an infectious acute respiratory infection caused by the novel coronavirus. The virus is a positive-strand RNA virus with high homology to bat coronavirus. In this study, conserved domain analysis, homology modeling, and molecular docking were used to compare the biological roles of certain proteins of the novel coronavirus. The results showed the ORF8 and surface glycoprotein could bind to the porphyrin, respectively. At the same time, orf1ab, ORF10, and ORF3a proteins could coordinate attack the heme on the 1-beta chain of hemoglobin to dissociate the iron to form the porphyrin. The attack will cause less and less hemoglobin that can carry oxygen and carbon dioxide. The lung cells have extremely intense poisoning and inflammatory due to the inability to exchange carbon dioxide and oxygen frequently, which eventually results in ground-glass-like lung images. The mechanism also interfered with the normal heme anabolic pathway of the human body, is expected to result in human disease. According to the validation analysis of these finds, chloroquine could prevent orf1ab, ORF3a, and ORF10 to attack the heme to form the porphyrin, and inhibit the binding of ORF8 and surface glycoproteins to porphyrins to a certain extent, effectively relieve the symptoms of respiratory distress. Favipiravir could inhibit the envelope protein and ORF7a protein bind to porphyrin, prevent the virus from entering host cells, and catching free porphyrins. Because the novel coronavirus is dependent on porphyrins, it may originate from an ancient virus. Therefore, this research is of high value to contemporary biological experiments, disease prevention, and clinical treatment.

Renin–Angiotensin–Aldosterone System Inhibitors in Patients with Covid-19 - Vaduganathan, Muthiah; Vardeny, Orly; Michel, Thomas; McMurray, John J.V.; Pfeffer, Marc A.; Solomon, Scott D. (New England Journal of Medicine, 2020)

Wild-type human coronaviruses prefer cell-surface TMPRSS2 to endosomal cathepsins for cell entry - Shirato, Kazuya; Kawase, Miyuki; Matsuyama, Shutoku (Virology, 2018)
Human coronaviruses (HCoVs) enter cells via two distinct pathways: the endosomal pathway using cathepsins to activate spike protein and the cell-surface or early endosome pathway using extracellular proteases such as transmembrane protease serine 2 (TMPRSS2). We previously reported that clinical isolates of HCoV-229E preferred cell-surface TMPRSS2 to endosomal cathepsin for cell entry, and that they acquired the ability to use cathepsin L by repeated passage in cultured cells and were then able to enter cells via the endosomal pathway. Here, we show that clinical isolates of HCoV-OC43 and -HKU1 preferred the cell-surface TMRRSS2 to endosomal cathepsins for cell entry, similar to HCoV-229E. In addition, the cell-culture-adapted HCoV-OC43 lost the ability to infect and replicate in air-liquid interface cultures of human bronchial tracheal epithelial cells. These results suggest that circulating HCoVs in the ﬁeld generally use cell-surface TMPRSS2 for cell entry, not endosomal cathepsins, in human airway epithelial cells.

Inhibition of SARS-CoV-2 (previously 2019-nCoV) infection by a highly potent pan-coronavirus fusion inhibitor targeting its spike protein that harbors a high capacity to mediate membrane fusion - Xia, Shuai; Liu, Meiqin; Wang, Chao; Xu, Wei; Lan, Qiaoshuai; Feng, Siliang; Qi, Feifei; Bao, Linlin; Du, Lanying; Liu, Shuwen; Qin, Chuan; Sun, Fei; et al. (Cell Research, 2020)

Structural Genomics of SARS-CoV-2 Indicates Evolutionary Conserved Functional Regions of Viral Proteins - Srinivasan, Suhas; Cui, Hongzhu; Gao, Ziyang; Liu, Ming; Lu, Senbao; Mkandawire, Winnie; Narykov, Oleksandr; Sun, Mo; Korkin, Dmitry (Viruses, 2020)
During its first two and a half months, the recently emerged 2019 novel coronavirus, SARS-CoV-2, has already infected over one-hundred thousand people worldwide and has taken more than four thousand lives. However, the swiftly spreading virus also caused an unprecedentedly rapid response from the research community facing the unknown health challenge of potentially enormous proportions. Unfortunately, the experimental research to understand the molecular mechanisms behind the viral infection and to design a vaccine or antivirals is costly and takes months to develop. To expedite the advancement of our knowledge, we leveraged data about the related coronaviruses that is readily available in public databases and integrated these data into a single computational pipeline. As a result, we provide comprehensive structural genomics and interactomics roadmaps of SARS-CoV-2 and use this information to infer the possible functional differences and similarities with the related SARS coronavirus. All data are made publicly available to the research community.

Principles of Virus Uncoating: Cues and the Snooker Ball - Yamauchi, Yohei; Greber, Urs F. (Traffic, 2016)
The architecture of a virus particle allows timely release of the viral genome in a host cell during entry. This critical step is known as viral uncoating. It is regulated by cues from receptors, enzymes and chemicals, and facilitated by factors that do not contact the virion directly. This review covers a wide range of cellular processes that enhance viral uncoating. The underlying mechanisms provide deep insights into cell biological and immunological processes of virus–host interactions and infections.

Targeting the Endocytic Pathway and Autophagy Process as a Novel Therapeutic Strategy in COVID-19 - Yang, Naidi; Shen, Han-Ming (International Journal of Biological Sciences, 2020)
Coronaviruses (CoVs) are a group of enveloped, single-stranded positive genomic RNA viruses and some of them are known to cause severe respiratory diseases in human, including Severe Acute Respiratory Syndrome (SARS), Middle East Respiratory Syndrome (MERS) and the ongoing coronavirus disease-19 (COVID-19). One key element in viral infection is the process of viral entry into the host cells. In the last two decades, there is increasing understanding on the importance of the endocytic pathway and the autophagy process in viral entry and replication. As a result, the endocytic pathway including endosome and lysosome has become important targets for development of therapeutic strategies in combating diseases caused by CoVs. In this mini-review, we will focus on the importance of the endocytic pathway as well as the autophagy process in viral infection of several pathogenic CoVs inclusive of SARS-CoV, MERS-CoV and the new CoV named as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and discuss the development of therapeutic agents by targeting these processes. Such knowledge will provide important clues for control of the ongoing epidemic of SARS-CoV-2 infection and treatment of COVID-19.

Clinical course and risk factors for mortality of adult inpatients with COVID-19 in Wuhan, China: a retrospective cohort study - Zhou, Fei; Yu, Ting; Du, Ronghui; Fan, Guohui; Liu, Ying; Liu, Zhibo; Xiang, Jie; Wang, Yeming; Song, Bin; Gu, Xiaoying; Guan, Lulu; Wei, Yuan; et al. (The Lancet, 2020)
Background Since December, 2019, Wuhan, China, has experienced an outbreak of coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Epidemiological and clinical characteristics of patients with COVID-19 have been reported but risk factors for mortality and a detailed clinical course of illness, including viral shedding, have not been well described.

Clinical Characteristics of Coronavirus Disease 2019 in China - Guan, Wei-jie; Ni, Zheng-yi; Hu, Yu; Liang, Wen-hua; Ou, Chun-quan; He, Jian-xing; Liu, Lei; Shan, Hong; Lei, Chun-liang; Hui, David S.C.; Du, Bin; Li, Lan-juan; et al. (New England Journal of Medicine, 2020)
BACKGROUND Since December 2019, when coronavirus disease 2019 (Covid-19) emerged in Wuhan city and rapidly spread throughout China, data have been needed on the clinical characteristics of the affected patients. METHODS We extracted data regarding 1099 patients with laboratory-confirmed Covid-19 from 552 hospitals in 30 provinces, autonomous regions, and municipalities in mainland China through January 29, 2020. The primary composite end point was admission to an intensive care unit (ICU), the use of mechanical ventilation, or death. The authors’ full names, academic degrees, and affiliations are listed in the Appendix. Address reprint requests to Dr. Zhong at the State Key Laboratory of Respiratory Disease, National Clinical Research Center for Respiratory Disease, Guangzhou Institute of Respiratory Health, First Affiliated Hospital of Guangzhou Medical University, 151 Yanjiang Rd., Guangzhou, Guangdong, China, or at nanshan@vip.163.com. RESULTS The median age of the patients was 47 years; 41.9% of the patients were female. The primary composite end point occurred in 67 patients (6.1%), including 5.0% who were admitted to the ICU, 2.3% who underwent invasive mechanical ventilation, and 1.4% who died. Only 1.9% of the patients had a history of direct contact with wildlife. Among nonresidents of Wuhan, 72.3% had contact with residents of Wuhan, including 31.3% who had visited the city. The most common symptoms were fever (43.8% on admission and 88.7% during hospitalization) and cough (67.8%). Diarrhea was uncommon (3.8%). The median incubation period was 4 days (interquartile range, 2 to 7). On admission, ground-glass opacity was the most common radiologic finding on chest computed tomography (CT) (56.4%). No radiographic or CT abnormality was found in 157 of 877 patients (17.9%) with nonsevere disease and in 5 of 173 patients (2.9%) with severe disease. Lymphocytopenia was present in 83.2% of the patients on admission. *A list of investigators in the China Medical Treatment Expert Group for Covid-19 study is provided in the Supplementary Appendix, available at NEJM.org. Drs. Guan, Ni, Yu Hu, W. Liang, Ou, He, L. Liu, Shan, Lei, Hui, Du, L. Li, Zeng, and Yuen contributed equally to this article. This article was published on February 28, 2020, and last updated on March 6, 2020, at NEJM.org. DOI: 10.1056/NEJMoa2002032 Copyright © 2020 Massachusetts Medical Society. CONCLUSIONS During the first 2 months of the current outbreak, Covid-19 spread rapidly throughout China and caused varying degrees of illness. Patients often presented without fever, and many did not have abnormal radiologic findings. (Funded by the National Health Commission of China and others.)

Cellular Immune Responses to Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) Infection in Senescent BALB/c Mice: CD4+ T Cells Are Important in Control of SARS-CoV Infection - Chen, J.; Lau, Y. F.; Lamirande, E. W.; Paddock, C. D.; Bartlett, J. H.; Zaki, S. R.; Subbarao, K. (Journal of Virology, 2010)

Dysregulated Type I Interferon and Inflammatory Monocyte-Macrophage Responses Cause Lethal Pneumonia in SARS-CoV-Infected Mice - Channappanavar, Rudragouda; Fehr, Anthony R.; Vijay, Rahul; Mack, Matthias; Zhao, Jincun; Meyerholz, David K.; Perlman, Stanley (Cell Host & Microbe, 2016)
Highly pathogenic human respiratory coronaviruses cause acute lethal disease characterized by exuberant inﬂammatory responses and lung damage. However, the factors leading to lung pathology are not well understood. Using mice infected with SARS (severe acute respiratory syndrome)-CoV, we show that robust virus replication accompanied by delayed type I interferon (IFN-I) signaling orchestrates inﬂammatory responses and lung immunopathology with diminished survival. IFN-I remains detectable until after virus titers peak, but early IFN-I administration ameliorates immunopathology. This delayed IFN-I signaling promotes the accumulation of pathogenic inﬂammatory monocytemacrophages (IMMs), resulting in elevated lung cytokine/chemokine levels, vascular leakage, and impaired virus-speciﬁc T cell responses. Genetic ablation of the IFN-ab receptor (IFNAR) or IMM depletion protects mice from lethal infection, without affecting viral load. These results demonstrate that IFN-I and IMM promote lethal SARS-CoV infection and identify IFN-I and IMMs as potential therapeutic targets in patients infected with pathogenic coronavirus and perhaps other respiratory viruses.

Reduction and Functional Exhaustion of T Cells in Patients with Coronavirus Disease 2019 (COVID-19) - Diao, Bo; Wang, Chenhui; Tan, Yingjun; Chen, Xiewan; Liu, Ying; Ning, Lifeng; Chen, Li; Li, Min; Liu, Yueping; Wang, Gang; Yuan, Zilin; Feng, Zeqing; et al. (2020)
BACKGROUND The outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has posed great threat to human health, which has been declared a public health emergency of international concern (PHEIC) by the WHO. T cells play a critical role in antiviral immunity but their numbers and functional state in COVID-19 patients remain largely unclear. METHODS We retrospectively reviewed the counts of total T cells, CD4+, CD8+ T cell subsets, and serum cytokine concentration from inpatient data of 522 patients with laboratory-confirmed COVID-19, admitted into two hospitals in Wuhan from December 2019 to January 2020, and 40 healthy controls, who came to the hospitals for routine physical examination. In addition, the expression of T cell exhaustion markers PD-1 and Tim-3 were measured by flow cytometry in the peripheral blood of 14 COVID-19 cases. RESULTS The number of total T cells, CD4+ and CD8+ T cells were dramatically reduced in COVID-19 patients, especially among elderly patients (≥60 years of age) and in patients requiring Intensive Care Unit (ICU) care. Counts of total T cells, CD8+T cells or CD4+T cells lower than 800/μL, 300/μL, or 400/μL, respectively, are negatively correlated with patient survival. Statistical analysis demonstrated that T cell numbers are negatively correlated to serum IL-6, IL-10 and TNF-α concentration, with patients in decline period showing reduced IL-6, IL-10 and TNF-α concentrations and restored T cell counts. Finally, T cells from COVID-19 patients have significantly higher levels of the exhausted marker PD-1 as compared to health controls. Moreover, increasing PD-1 and Tim-3 expression on T cells could be seen as patients progressed from prodromal to overtly symptomatic stages, further indicative of T cell exhaustion. CONCLUSIONS T cell counts are reduced significantly in COVID-19 patients, and the surviving T cells appear functionally exhausted. Non-ICU patients, with total T cells, CD8+T cells CD4+T cells counts lower than 800/μL, 300/μL, and 400/μL, respectively, may still require aggressive intervention even in the immediate absence of more severe symptoms due to a high risk for further deterioration in condition.

Clinical and immunologic features in severe and moderate Coronavirus Disease 2019 - Chen, Guang; Wu, Di; Guo, Wei; Cao, Yong; Huang, Da; Wang, Hongwu; Wang, Tao; Zhang, Xiaoyun; Chen, Huilong; Yu, Haijing; Zhang, Xiaoping; Zhang, Minxia; et al. (Journal of Clinical Investigation, 2020)

Network-based drug repurposing for novel coronavirus 2019-nCoV/SARS-CoV-2 - Zhou, Yadi; Hou, Yuan; Shen, Jiayu; Huang, Yin; Martin, William; Cheng, Feixiong (Cell Discovery, 2020)

Potent human neutralizing antibodies elicited by SARS-CoV-2 infection - Ju, Bin; Zhang, Qi; Ge, Xiangyang; Wang, Ruoke; Yu, Jiazhen; Shan, Sisi; Zhou, Bing; Song, Shuo; Tang, Xian; Yu, Jinfang; Ge, Jiwan; Lan, Jun; et al. (2020)
The pandemic caused by emerging coronavirus SARS-CoV-2 presents a serious global public health emergency in urgent need of prophylactic and therapeutic interventions. SARS CoV-2 cellular entry depends on binding between the viral Spike protein receptor-binding domain (RBD) and the angiotensin converting enzyme 2 (ACE2) target cell receptor. Here, we report on the isolation and characterization of 206 RBD-specific monoclonal antibodies (mAbs) derived from single B cells of eight SARS-CoV-2 infected individuals. These mAbs come from diverse families of antibody heavy and light chains without apparent enrichment for particular families in the repertoire. In samples from one patient selected for further analyses, we found coexistence of germline and germline divergent clones. Both clone types demonstrated impressive binding and neutralizing activity against pseudovirus and live SARS-CoV-2. However, the antibody neutralizing potency is determined by competition with ACE2 receptor for RBD binding. Surprisingly, none of the SARS CoV 2 antibodies nor the infected plasma cross-reacted with RBDs from either SARS CoV or MERS CoV although substantial plasma cross reactivity to the trimeric Spike proteins from SARS-CoV and MERS-CoV was found. These results suggest that antibody response to RBDs is viral species-specific while that cross-recognition target regions outside the RBD. The specificity and neutralizing characteristics of this plasma cross-reactivity requires further investigation. Nevertheless, the diverse and potent neutralizing antibodies identified here are promising candidates for prophylactic and therapeutic SARS-CoV-2 interventions.

Antibody responses to individual proteins of SARS coronavirus and their neutralization activities - Qiu, Maofeng; Shi, Yuling; Guo, Zhaobiao; Chen, Zeliang; He, Rongqiao; Chen, Runsheng; Zhou, Dongsheng; Dai, Erhei; Wang, Xiaoyi; Si, Bingyin; Song, Yajun; Li, Jingxiang; et al. (Microbes and Infection, 2005)
A novel coronavirus, the severe acute respiratory syndrome (SARS) coronavirus (SARS-CoV), was identified as the causative agent of SARS. The profile of specific antibodies to individual proteins of the virus is critical to the development of vaccine and diagnostic tools. In this study, 13 recombinant proteins associated with four structural proteins (S, E, M and N) and five putative uncharacterized proteins (3a, 3b, 6, 7a and 9b) of the SARS-CoV were prepared and used for screening and monitoring their specific IgG antibodies in SARS patient sera by protein microarray. Antibodies to proteins S, 3a, N and 9b were detected in the sera from convalescent-phase SARS patients, whereas those to proteins E, M, 3b, 6 and 7a were undetected. In the detectable specific antibodies, anti-S and anti-N were dominant and could persist in the sera of SARS patients until week 30. Among the rabbit antisera to recombinant proteins S3, N, 3a and 9b, only anti-S3 serum showed significant neutralizing activity to the SARS-CoV infection in Vero E6 cells. The results suggest (1) that anti-S and anti-N antibodies are diagnostic markers and in particular that S3 is immunogenic and therefore is a good candidate as a subunit vaccine antigen; and (2) that, from a virus structure viewpoint, the presence in some human sera of antibodies reacting with two recombinant polypeptides, 3a and 9b, supports the hypothesis that they are synthesized during the virus cycle.

Peptide-Based Membrane Fusion Inhibitors Targeting HCoV-229E Spike Protein HR1 and HR2 Domains - Xia, Shuai; Xu, Wei; Wang, Qian; Wang, Cong; Hua, Chen; Li, Weihua; Lu, Lu; Jiang, Shibo (International Journal of Molecular Sciences, 2018)
Human coronavirus 229E (HCoV-229E) infection in infants, elderly people, and immunocompromised patients can cause severe disease, thus calling for the development of effective and safe therapeutics to treat it. Here we reported the design, synthesis and characterization of two peptide-based membrane fusion inhibitors targeting HCoV-229E spike protein heptad repeat 1 (HR1) and heptad repeat 2 (HR2) domains, 229E-HR1P and 229E-HR2P, respectively. We found that 229E-HR1P and 229E-HR2P could interact to form a stable six-helix bundle and inhibit HCoV-229E spike protein-mediated cell-cell fusion with IC50 of 5.7 and 0.3 µM, respectively. 229E-HR2P effectively inhibited pseudotyped and live HCoV-229E infection with IC50 of 0.5 and 1.7 µM, respectively. In a mouse model, 229E-HR2P administered intranasally could widely distribute in the upper and lower respiratory tracts and maintain its fusion-inhibitory activity. Therefore, 229E-HR2P is a promising candidate for further development as an antiviral agent for the treatment and prevention of HCoV-229E infection.

SARS and MERS: recent insights into emerging coronaviruses - de Wit, Emmie; van Doremalen, Neeltje; Falzarano, Darryl; Munster, Vincent J. (Nature Reviews Microbiology, 2016)
The emergence of Middle East respiratory syndrome coronavirus (MERS-CoV) in 2012 marked the second introduction of a highly pathogenic coronavirus into the human population in the twenty-first century. The continuing introductions of MERS-CoV from dromedary camels, the subsequent travel-related viral spread, the unprecedented nosocomial outbreaks and the high case-fatality rates highlight the need for prophylactic and therapeutic measures. Scientific advancements since the 2002–2003 severe acute respiratory syndrome coronavirus (SARS-CoV) pandemic allowed for rapid progress in our understanding of the epidemiology and pathogenesis of MERS-CoV and the development of therapeutics. In this Review, we detail our present understanding of the transmission and pathogenesis of SARS-CoV and MERS-CoV, and discuss the current state of development of measures to combat emerging coronaviruses.

Furin, a potential therapeutic target for COVID-19 - Wu, Canrong; Yang, Yueying; Liu, Yang; Zhang, Peng; Wang, Yali; Li, Hua; Wang, Qiqi; Xu, Yang; Li, Mingxue; Zheng, Mengzhu; Chen, Lixia (2020)
A novel coronavirus (SARS-CoV-2) infectious disease has broken out in Wuhan, Hubei Province since December 2019, and spread rapidly from Wuhan to other areas, which has been listed as an international concerning public health emergency. We compared the Spike proteins from four sources, SARS-CoV-2, SARS-CoV, MERS-CoV and Bat-CoVRaTG13, and found that the SARS-CoV-2 virus sequence had redundant PRRA sequences. Through a series of analyses, we propose the reason why SARS-CoV-2is more infectious than other coronaviruses. And through structure based virtual ligand screening, we foundpotentialfurin inhibitors, which might be used in the treatment of new coronary pneumonia.

Repurposing Therapeutics for COVID-19: Supercomputer-Based Docking to the SARS-CoV-2 Viral Spike Protein and Viral Spike Protein-Human ACE2 Interface - Smith, Micholas; Smith, Jeremy C. (2020)

Quantitative analysis of amino acid metabolism in liver cancer links glutamate excretion to nucleotide synthesis - Nilsson, Avlant; Haanstra, Jurgen; Engqvist, Martin; Gerding, Albert; Bakker, Barbara; Klingmüller, Ursula; Teusink, Bas; Nielsen, Jens (Proceedings of the National Academy of Sciences, 2020)
Many cancer cells consume glutamine at high rates; counterintuitively, they simultaneously excrete glutamate, the first intermediate in glutamine metabolism. Glutamine consumption has been linked to replenishment of tricarboxylic acid cycle (TCA) intermediates and synthesis of adenosine triphosphate (ATP), but the reason for glutamate excretion is unclear. Here, we dynamically profile the uptake and excretion fluxes of a liver cancer cell line (HepG2) and use genome-scale metabolic modeling for in-depth analysis. We find that up to 30% of the glutamine is metabolized in the cytosol, primarily for nucleotide synthesis, producing cytosolic glutamate. We hypothesize that excreting glutamate helps the cell to increase the nucleotide synthesis rate to sustain growth. Indeed, we show experimentally that partial inhibition of glutamate excretion reduces cell growth. Our integrative approach thus links glutamine addiction to glutamate excretion in cancer and points toward potential drug targets.

The role of HPV RNA transcription, immune response-related gene expression and disruptive TP53 mutations in diagnostic and prognostic profiling of head and neck cancer. - Wichmann, G.; Rosolowski, M.; Krohn, K.; Kreuz, M.; Boehm, A.; Reiche, A.; Scharrer, U.; Halama, D.; Bertolini, J.; Bauer, U.; Holzinger, D.; Pawlita, M.; et al. (Int J Cancer, 2015)
Stratification of head and neck squamous cell carcinomas (HNSCC) based on HPV16 DNA and RNA status, gene expression patterns, and mutated candidate genes may facilitate patient treatment decision. We characterize head and neck squamous cell carcinomas (HNSCC) with different HPV16 DNA and RNA (E6*I) status from 290 consecutively recruited patients by gene expression profiling and targeted sequencing of 50 genes. We show that tumors with transcriptionally inactive HPV16 (DNA+ RNA-) are similar to HPV-negative (DNA-) tumors regarding gene expression and frequency of TP53 mutations (47%, 8/17 and 43%, 72/167, respectively). We also find that an immune response-related gene expression cluster is associated with lymph node metastasis, independent of HPV16 status and that disruptive TP53 mutations are associated with lymph node metastasis in HPV16 DNA- tumors. We validate each of these associations in another large data set. Four gene expression clusters which we identify differ moderately but significantly in overall survival. Our findings underscore the importance of measuring the HPV16 RNA (E6*I) and TP53-mutation status for patient stratification and identify associations of an immune response-related gene expression cluster and TP53 mutations with lymph node metastasis in HNSCC.
Keywords: Carcinoma, Squamous Cell/immunology/mortality/secondary/*virology; Gene Expression Regulation, Neoplastic/immunology; Gene Frequency; Head and Neck Neoplasms/immunology/mortality/pathology/*virology; Human papillomavirus 16/genetics/*immunology/metabolism; Humans; Immunity, Innate/genetics; Lymphatic Metastasis; Mutation; Papillomavirus Infections/*immunology/mortality/pathology; Prognosis; Proportional Hazards Models; RNA, Viral/*genetics/metabolism; Transcription, Genetic; Tumor Suppressor Protein p53/*genetics

Analysis of hospitalized COVID-19 patients in the Mount Sinai Health System using electronic medical records (EMR) reveals important prognostic factors for improved clinical outcomes - Wang, Zichen; Zheutlin, Amanda B; Kao, Yu-Han; Ayers, Kristin L; Gross, Susan J; Kovatch, Patricia; Nirenberg, Sharon; Charney, Alexander W; Nadkarni, Girish N; O'Reilly, Paul F; Just, Allan C; Horowitz, Carol R; et al. (2020)

Convergent in situ Generation of Both Transketolase Substrates via Transaminase and Aldolase Reactions for Sequential One‐Pot, Three‐Step Cascade Synthesis of Ketoses - Lorillière, Marion; Guérard‐Hélaine, Christine; Gefflaut, Thierry; Fessner, Wolf Dieter; Clapés, Pere; Charmantray, Franck; Hecquet, Laurence (ChemCatChem, 2019)

Functional characterization of GNAS mutations found in patients with pseudohypoparathyroidism type Ic defines a new subgroup of pseudohypoparathyroidism affecting selectively Gsα-receptor interaction - Thiele, Susanne; de Sanctis, Luisa; Werner, Ralf; Grötzinger, Joachim; Aydin, Cumhur; Jüppner, Harald; Bastepe, Murat; Hiort, Olaf (Human Mutation, 2011)

Analysis of Thermophysical Properties of Deep Eutectic Solvents by Data Integration - Xu, Xinmeng; Range, Jan; Gygli, Gudrun; Pleiss, Juergen (Journal of Chemical & Engineering Data, 2020)

Enhancement of Benzothiazoles as Pteridine Reductase-1 Inhibitors for the Treatment of Trypanosomatidic Infections. - Linciano, P.; Pozzi, C.; Iacono, L. D.; di Pisa, F.; Landi, G.; Bonucci, A.; Gul, S.; Kuzikov, M.; Ellinger, B.; Witt, G.; Santarem, N.; Baptista, C.; et al. (J Med Chem, 2019)
2-Amino-benzo[ d]thiazole was identified as a new scaffold for the development of improved pteridine reductase-1 (PTR1) inhibitors and anti-trypanosomatidic agents. Molecular docking and crystallography guided the design and synthesis of 42 new benzothiazoles. The compounds were assessed for Trypanosoma brucei and Leishmania major PTR1 inhibition and in vitro activity against T. brucei and amastigote Leishmania infantum. We identified several 2-amino-benzo[ d]thiazoles with improved enzymatic activity ( TbPTR1 IC(50) = 0.35 muM; LmPTR1 IC(50) = 1.9 muM) and low muM antiparasitic activity against T. brucei. The ten most active compounds against TbPTR1 were able to potentiate the antiparasitic activity of methotrexate when evaluated in combination against T. brucei, with a potentiating index between 1.2 and 2.7. The compound library was profiled for early ADME toxicity, and 2-amino- N-benzylbenzo[ d]thiazole-6-carboxamide (4c) was finally identified as a novel potent, safe, and selective anti-trypanocydal agent (EC(50) = 7.0 muM). Formulation of 4c with hydroxypropyl-beta-cyclodextrin yielded good oral bioavailability, encouraging progression to in vivo studies.
Keywords: Animals; Antiprotozoal Agents/*chemistry/metabolism/pharmacology/therapeutic use; Benzothiazoles/*chemistry/metabolism/pharmacology/therapeutic use; Binding Sites; Catalytic Domain; Crystallography, X-Ray; Drug Design; Enzyme Inhibitors/*chemistry/metabolism/pharmacology/therapeutic use; Half-Life; Leishmania major/drug effects/*enzymology; Mice; Mice, Inbred BALB C; Molecular Docking Simulation; Oxidoreductases/*antagonists & inhibitors/metabolism; Protozoan Proteins/*antagonists & inhibitors/metabolism; Structure-Activity Relationship; Trypanosoma brucei brucei/drug effects/*enzymology; Trypanosomiasis/drug therapy/pathology

Identification of a 2,4-diaminopyrimidine scaffold targeting Trypanosoma brucei pteridine reductase 1 from the LIBRA compound library screening campaign. - Linciano, P.; Cullia, G.; Borsari, C.; Santucci, M.; Ferrari, S.; Witt, G.; Gul, S.; Kuzikov, M.; Ellinger, B.; Santarem, N.; Cordeiro da Silva, A.; Conti, P.; et al. (Eur J Med Chem, 2020)
The LIBRA compound library is a collection of 522 non-commercial molecules contributed by various Italian academic laboratories. These compounds have been designed and synthesized during different medicinal chemistry programs and are hosted by the Italian Institute of Technology. We report the screening of the LIBRA compound library against Trypanosoma brucei and Leishmania major pteridine reductase 1, TbPTR1 and LmPTR1. Nine compounds were active against parasitic PTR1 and were selected for cell-based parasite screening, as single agents and in combination with methotrexate (MTX). The most interesting TbPTR1 inhibitor identified was 4-(benzyloxy)pyrimidine-2,6-diamine (LIB_66). Subsequently, six new LIB_66 derivatives were synthesized to explore its Structure-Activity-Relationship (SAR) and absorption, distribution, metabolism, excretion and toxicity (ADMET) properties. The results indicate that PTR1 has a preference to bind inhibitors, which resemble its biopterin/folic acid substrates, such as the 2,4-diaminopyrimidine derivatives.
Keywords: A549 Cells; Antimetabolites, Antineoplastic/pharmacology; Antineoplastic Agents/chemistry/*pharmacology; Cell Proliferation; Drug Synergism; Enzyme Inhibitors/chemistry/*pharmacology; High-Throughput Screening Assays/*methods; Humans; Macrophages/*drug effects; Methotrexate/pharmacology; Models, Molecular; Molecular Structure; Oxidoreductases/*antagonists & inhibitors; Pyrimidines/*chemistry; Structure-Activity Relationship; Trypanosoma brucei brucei/*enzymology

SAR Studies and Biological Characterization of a Chromen-4-one Derivative as an Anti-Trypanosoma brucei Agent. - Borsari, C.; Santarem, N.; Macedo, S.; Jimenez-Anton, M. D.; Torrado, J. J.; Olias-Molero, A. I.; Corral, M. J.; Tait, A.; Ferrari, S.; Costantino, L.; Luciani, R.; Ponterini, G.; et al. (ACS Med Chem Lett, 2019)
Chemical modulation of the flavonol 2-(benzo[d][1,3]dioxol-5-yl)-chromen-4-one (1), a promising anti-Trypanosomatid agent previously identified, was evaluated through a phenotypic screening approach. Herein, we have performed structure-activity relationship studies around hit compound 1. The pivaloyl derivative (13) showed significant anti-T. brucei activity (EC(50) = 1.1 muM) together with a selectivity index higher than 92. The early in vitro ADME-tox properties (cytotoxicity, mitochondrial toxicity, cytochrome P450 and hERG inhibition) were determined for compound 1 and its derivatives, and these led to the identification of some liabilities. The 1,3-benzodioxole moiety in the presented compounds confers better in vivo pharmacokinetic properties than those of classical flavonols. Further studies using different delivery systems could lead to an increase of compound blood levels.

Medicinal Chemistry of Neglected and Tropical Diseases - Jayaprakash, Venkatesan; Castagnolo, Daniele; Özkay, Yusuf (2019)

Structural Insights into the Development of Cycloguanil Derivatives as Trypanosoma brucei Pteridine-Reductase-1 Inhibitors. - Landi, G.; Linciano, P.; Borsari, C.; Bertolacini, C. P.; Moraes, C. B.; Cordeiro-da-Silva, A.; Gul, S.; Witt, G.; Kuzikov, M.; Costi, M. P.; Pozzi, C.; Mangani, S. (ACS Infect Dis, 2019)
Cycloguanil is a known dihydrofolate-reductase (DHFR) inhibitor, but there is no evidence of its activity on pteridine reductase (PTR), the main metabolic bypass to DHFR inhibition in trypanosomatid parasites. Here, we provide experimental evidence of cycloguanil as an inhibitor of Trypanosoma brucei PTR1 (TbPTR1). A small library of cycloguanil derivatives was developed, resulting in 1 and 2a having IC(50) values of 692 and 186 nM, respectively, toward TbPTR1. Structural analysis revealed that the increased potency of 1 and 2a is due to the combined contributions of hydrophobic interactions, H-bonds, and halogen bonds. Moreover, in vitro cell-growth-inhibition tests indicated that 2a is also effective on T. brucei. The simultaneous inhibition of DHFR and PTR1 activity in T. brucei is a promising new strategy for the treatment of human African trypanosomiasis. For this purpose, 1,6-dihydrotriazines represent new molecular tools to develop potent dual PTR and DHFR inhibitors.
Keywords: Enzyme Inhibitors/chemical synthesis/chemistry/pharmacology; Hydrophobic and Hydrophilic Interactions; Models, Molecular; Molecular Structure; Oxidoreductases/*antagonists & inhibitors/chemistry; Proguanil/*chemistry/pharmacology; Protozoan Proteins/antagonists & inhibitors/chemistry; Small Molecule Libraries/chemical synthesis/chemistry/pharmacology; Structure-Activity Relationship; Triazines/*chemical synthesis/chemistry/pharmacology; Trypanocidal Agents/*chemical synthesis/chemistry/pharmacology; Trypanosoma brucei brucei/drug effects/*enzymology

Accelerating Drug Discovery Efforts for Trypanosomatidic Infections Using an Integrated Transnational Academic Drug Discovery Platform. - Moraes, C. B.; Witt, G.; Kuzikov, M.; Ellinger, B.; Calogeropoulou, T.; Prousis, K. C.; Mangani, S.; Di Pisa, F.; Landi, G.; Iacono, L. D.; Pozzi, C.; Freitas-Junior, L. H.; et al. (SLAS Discov, 2019)
According to the World Health Organization, more than 1 billion people are at risk of or are affected by neglected tropical diseases. Examples of such diseases include trypanosomiasis, which causes sleeping sickness; leishmaniasis; and Chagas disease, all of which are prevalent in Africa, South America, and India. Our aim within the New Medicines for Trypanosomatidic Infections project was to use (1) synthetic and natural product libraries, (2) screening, and (3) a preclinical absorption, distribution, metabolism, and excretion-toxicity (ADME-Tox) profiling platform to identify compounds that can enter the trypanosomatidic drug discovery value chain. The synthetic compound libraries originated from multiple scaffolds with known antiparasitic activity and natural products from the Hypha Discovery MycoDiverse natural products library. Our focus was first to employ target-based screening to identify inhibitors of the protozoan Trypanosoma brucei pteridine reductase 1 ( TbPTR1) and second to use a Trypanosoma brucei phenotypic assay that made use of the T. brucei brucei parasite to identify compounds that inhibited cell growth and caused death. Some of the compounds underwent structure-activity relationship expansion and, when appropriate, were evaluated in a preclinical ADME-Tox assay panel. This preclinical platform has led to the identification of lead-like compounds as well as validated hits in the trypanosomatidic drug discovery value chain.
Keywords: Biological Products/chemistry; Drug Discovery/*methods; Humans; Structure-Activity Relationship; Trypanocidal Agents/*analysis/*pharmacology/therapeutic use; Trypanosomiasis/*drug therapy

Excited-state intramolecular proton transfer in a bioactive flavonoid provides fluorescence observables for recognizing its engagement with target proteins. - Vanossi, D.; Caselli, M.; Pavesi, G.; Borsari, C.; Linciano, P.; Costi, M. P.; Ponterini, G. (Photochem Photobiol Sci, 2019)
A benzothiophene-substituted chromenone with promising activity against Leishmania and Trypanosoma species exhibits peculiar fluorescence properties useful for identifying its complexes with target proteins in the microorganism proteomes. The emission spectra, anisotropy and time profiles of this flavonoid strongly change when moving from the free to the protein-bound forms. The same two types of emission are observed in organic solvents and their mixtures with water, with the relative band intensities depending on the solvent ability to establish hydrogen bonds with the solute. The regular emission prevails in protic solvents, while in aprotic solvents the anomalously red-shifted emission occurs from a zwitterionic tautomeric form, produced in the excited state by proton transfer within the intramolecularly H-bonded form. This interpretation finds support from an experimental and theoretical investigation of the conformational preferences of this compound in the ground and lowest excited state, with a focus on the relative twisting about the chromenone-benzothiophene interconnecting bond. An analysis of the absorption and emission spectra and of the photophysical properties of the two emitting tautomers highlights the relevance of the local microenvironment, particularly of the intra- and intermolecular hydrogen bonds in which this bioactive compound is involved, in determining both its steady-state and time-resolved fluorescence behaviour.
Keywords: *Density Functional Theory; Flavonoids/*chemistry/*pharmacology; *Fluorescence; Hydrogen Bonding; Leishmania/drug effects; Molecular Structure; Proteome/*antagonists & inhibitors/chemistry; *Protons; Protozoan Proteins/*antagonists & inhibitors/chemistry; Trypanosoma/drug effects

Scaffolds and Biological Targets Avenue to Fight Against Drug Resistance in Leishmaniasis - Borsari, Chiara; Quotadamo, Antonio; Ferrari, Stefania; Venturelli, Alberto; Cordeiro-da-Silva, Anabela; Santarem, Nuno; Costi, Maria Paola (Neglected Diseases: Extensive Space for Modern Drug Discovery, 2018)

Pharmacokinetics and disposition of miltefosine in healthy mice and hamsters experimentally infected with Leishmania infantum. - Jimenez-Anton, M. D.; Garcia-Calvo, E.; Gutierrez, C.; Escribano, M. D.; Kayali, N.; Luque-Garcia, J. L.; Olias-Molero, A. I.; Corral, M. J.; Costi, M. P.; Torrado, J. J.; Alunda, J. M. (Eur J Pharm Sci, 2018)
Miltefosine is the only currently available oral drug for treatment of leishmaniasis. However, information on the pharmacokinetics (PK) of miltefosine is relatively scarce in animals. PK parameters and disposition of the molecule was determined in healthy NMRI mice and Syrian hamsters infected and treated with different miltefosine doses and regimens. Long half-life of the molecule was confirmed and differential pattern of accumulation of the drug was observed in analyzed organs in mice and hamster. Long treatment schedules produced miltefosine levels over IC(50) value against L. infantum intracellular amastigotes for at least 24 days in spleen and liver of infected hamsters. The observed differential pattern of organ accumulation of the drug in mice and hamster supports the relevance of both species for translational research on chemotherapy of leishmaniasis.
Keywords: Animals; Antiprotozoal Agents/blood/*pharmacokinetics; Cricetinae; Female; Leishmania infantum; Leishmaniasis, Visceral/*metabolism; Male; Mice; Phosphorylcholine/*analogs & derivatives/blood/pharmacokinetics

Aryl thiosemicarbazones for the treatment of trypanosomatidic infections. - Linciano, P.; Moraes, C. B.; Alcantara, L. M.; Franco, C. H.; Pascoalino, B.; Freitas-Junior, L. H.; Macedo, S.; Santarem, N.; Cordeiro-da-Silva, A.; Gul, S.; Witt, G.; Kuzikov, M.; et al. (Eur J Med Chem, 2018)
Basing on a library of thiadiazole derivatives showing anti-trypanosomatidic activity, we have considered the thiadiazoles opened forms and reaction intermediates, thiosemicarbazones, as compounds of interest for phenotypic screening against Trypanosoma brucei (Tb), intracellular amastigote form of Leishmania infantum (Li) and Trypanosoma cruzi (Tc). Similar compounds have already shown interesting activity against the same organisms. The compounds were particularly effective against T. brucei and T. cruzi. Among the 28 synthesized compounds, the best one was (E)-2-(4-((3.4-dichlorobenzyl)oxy)benzylidene) hydrazinecarbothioamide (A14) yielding a comparable anti-parasitic activity against the three parasitic species (TbEC(50) = 2.31 muM, LiEC(50) = 6.14 muM, TcEC(50) = 1.31 muM) and a Selectivity Index higher than 10 with respect to human macrophages, therefore showing a pan-anti-trypanosomatidic activity. (E)-2-((3'.4'-dimethoxy-[1.1'-biphenyl]-3-yl)methyle ne) hydrazinecarbothioamide (A12) and (E)-2-(4-((3.4-dichlorobenzyl)oxy)benzylidene)hydrazine carbothioamide (A14) were able to potentiate the anti-parasitic activity of methotrexate (MTX) when evaluated in combination against T. brucei, yielding a 6-fold and 4-fold respectively Dose Reduction Index for MTX. The toxicity profile against four human cell lines and a panel of in vitro early-toxicity assays (comprising hERG, Aurora B, five cytochrome P450 isoforms and mitochondrial toxicity) demonstrated the low toxicity for the thosemicarbazones class in comparison with known drugs. The results confirmed thiosemicarbazones as a suitable chemical scaffold with potential for the development of properly decorated new anti-parasitic drugs.
Keywords: Antiprotozoal Agents/chemical synthesis/chemistry/*pharmacology; Chagas Disease/*drug therapy; Dose-Response Relationship, Drug; Humans; Macrophages/drug effects; Molecular Structure; Parasitic Sensitivity Tests; Structure-Activity Relationship; Thiosemicarbazones/chemical synthesis/chemistry/*pharmacology; Trypanosoma/*drug effects

Development of a Focused Library of Triazole-Linked Privileged-Structure-Based Conjugates Leading to the Discovery of Novel Phenotypic Hits against Protozoan Parasitic Infections. - Uliassi, E.; Piazzi, L.; Belluti, F.; Mazzanti, A.; Kaiser, M.; Brun, R.; Moraes, C. B.; Freitas-Junior, L. H.; Gul, S.; Kuzikov, M.; Ellinger, B.; Borsari, C.; et al. (ChemMedChem, 2018)
Protozoan infections caused by Plasmodium, Leishmania, and Trypanosoma spp. contribute significantly to the burden of infectious diseases worldwide, causing severe morbidity and mortality. The inadequacy of available treatments calls for cost- and time-effective drug discovery endeavors. To this end, we envisaged the triazole linkage of privileged structures as an effective drug design strategy to generate a focused library of high-quality compounds. The versatility of this approach was combined with the feasibility of a phenotypic assay, integrated with early ADME-tox profiling. Thus, an 18-membered library was efficiently assembled via Huisgen cycloaddition of phenothiazine, biphenyl, and phenylpiperazine scaffolds. The resulting 18 compounds were then tested against seven parasite strains, and counter-screened for selectivity against two mammalian cell lines. In parallel, hERG and cytochrome P450 (CYP) inhibition, and mitochondrial toxicity were assessed. Remarkably, 10-((1-(3-([1,1'-biphenyl]-3-yloxy)propyl)-1H-1,2,3-triazol-5-yl)methyl)-10H-phenothiazine (7) and 10-(3-(1-(3-([1,1'-biphenyl]-3-yloxy)propyl)-1H-1,2,3-triazol-4-yl)propyl)-10H-phenothiazine (12) showed respective IC(50) values of 1.8 and 1.9 mug mL(-1) against T. cruzi, together with optimal selectivity. In particular, compound 7 showed a promising ADME-tox profile. Thus, hit 7 might be progressed as an antichagasic lead.
Keywords: Animals; Antiprotozoal Agents/chemical synthesis/chemistry/*pharmacology/toxicity; Cell Line, Tumor; Cytochrome P-450 Enzyme Inhibitors/chemical synthesis/pharmacology/toxicity; ERG1 Potassium Channel/metabolism; Humans; Leishmania/drug effects; Molecular Structure; Parasitic Sensitivity Tests; Plasmodium falciparum/drug effects; Potassium Channel Blockers/chemical synthesis/pharmacology/toxicity; Rats; Small Molecule Libraries/chemical synthesis/chemistry/*pharmacology/toxicity; Triazoles/chemical synthesis/chemistry/*pharmacology/toxicity; Trypanosoma/drug effects

Methoxylated 2'-hydroxychalcones as antiparasitic hit compounds. - Borsari, C.; Santarem, N.; Torrado, J.; Olias, A. I.; Corral, M. J.; Baptista, C.; Gul, S.; Wolf, M.; Kuzikov, M.; Ellinger, B.; Witt, G.; Gribbon, P.; et al. (Eur J Med Chem, 2017)
Chalcones display a broad spectrum of pharmacological activities. Herein, a series of 2'-hydroxy methoxylated chalcones was synthesized and evaluated towards Trypanosoma brucei, Trypanosoma cruzi and Leishmania infantum. Among the synthesized library, compounds 1, 3, 4, 7 and 8 were the most potent and selective anti-T. brucei compounds (EC(50) = 1.3-4.2 muM, selectivity index >10-fold). Compound 4 showed the best early-tox and antiparasitic profile. The pharmacokinetic studies of compound 4 in BALB/c mice using hydroxypropil-beta-cyclodextrins formulation showed a 7.5 times increase in oral bioavailability.
Keywords: Animals; Antiparasitic Agents/*chemistry/pharmacokinetics/*pharmacology/toxicity; Cell Line, Tumor; Chalcones/*chemistry/pharmacokinetics/*pharmacology/toxicity; Cyclodextrins/chemistry; Drug Carriers/chemistry; Mice; Solubility; Trypanosomatina/drug effects

Molecular basis for covalent inhibition of glyceraldehyde-3-phosphate dehydrogenase by a 2-phenoxy-1,4-naphthoquinone small molecule. - Bruno, S.; Uliassi, E.; Zaffagnini, M.; Prati, F.; Bergamini, C.; Amorati, R.; Paredi, G.; Margiotta, M.; Conti, P.; Costi, M. P.; Kaiser, M.; Cavalli, A.; et al. (Chem Biol Drug Des, 2017)
Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) has recently gained attention as an antiprotozoan and anticancer drug target. We have previously identified 2-phenoxy-1,4-naphthoquinone as an inhibitor of both Trypanosoma brucei and human GAPDH. Herein, through multiple chemical, biochemical, and biological studies, and through the design of analogs, we confirmed the formation of a covalent adduct, we clarified the inhibition mechanism, and we demonstrated antitrypanosomal, antiplasmodial, and cytotoxic activities in cell cultures. The overall results lent support to the hypothesis that 2-phenoxy-1,4-naphthoquinone binds the GAPDH catalytic cysteine covalently through a phenolate displacement mechanism. By investigating the reactivity of 2-phenoxy-1,4-naphthoquinone and its analogs with four GAPDH homologs, we showed that the covalent inhibition is not preceded by the formation of a strong non-covalent complex. However, an up to fivefold difference in inactivation rates among homologs hinted at structural or electrostatic differences of their active sites that could be exploited to further design kinetically selective inhibitors. Moreover, we preliminarily showed that 2-phenoxy-1,4-naphthoquinone displays selectivity for GAPDHs over two other cysteine-dependent enzymes, supporting its suitability as a warhead starting fragment for the design of novel inhibitors.
Keywords: Antiprotozoal Agents/*chemistry/*pharmacology; Glyceraldehyde-3-Phosphate Dehydrogenases/*antagonists & inhibitors/metabolism; Humans; Malaria, Falciparum/drug therapy; Naphthoquinones/*chemistry/*pharmacology; Plasmodium falciparum/drug effects/*enzymology; Trypanocidal Agents/chemistry/pharmacology; Trypanosoma brucei brucei/drug effects/*enzymology

Chroman-4-One Derivatives Targeting Pteridine Reductase 1 and Showing Anti-Parasitic Activity. - Di Pisa, F.; Landi, G.; Dello Iacono, L.; Pozzi, C.; Borsari, C.; Ferrari, S.; Santucci, M.; Santarem, N.; Cordeiro-da-Silva, A.; Moraes, C. B.; Alcantara, L. M.; Fontana, V.; et al. (Molecules, 2017)
Flavonoids have previously been identified as antiparasitic agents and pteridine reductase 1 (PTR1) inhibitors. Herein, we focus our attention on the chroman-4-one scaffold. Three chroman-4-one analogues (1-3) of previously published chromen-4-one derivatives were synthesized and biologically evaluated against parasitic enzymes (Trypanosoma brucei PTR1-TbPTR1 and Leishmania major-LmPTR1) and parasites (Trypanosoma brucei and Leishmania infantum). A crystal structure of TbPTR1 in complex with compound 1 and the first crystal structures of LmPTR1-flavanone complexes (compounds 1 and 3) were solved. The inhibitory activity of the chroman-4-one and chromen-4-one derivatives was explained by comparison of observed and predicted binding modes of the compounds. Compound 1 showed activity both against the targeted enzymes and the parasites with a selectivity index greater than 7 and a low toxicity. Our results provide a basis for further scaffold optimization and structure-based drug design aimed at the identification of potent anti-trypanosomatidic compounds targeting multiple PTR1 variants.
Keywords: Antiparasitic Agents/chemical synthesis/*chemistry/*pharmacology; Binding Sites; Chromans/chemical synthesis/*chemistry/*pharmacology; Enzyme Activation/drug effects; Inhibitory Concentration 50; Leishmania major/drug effects/enzymology; Molecular Conformation; Molecular Docking Simulation; Molecular Dynamics Simulation; Molecular Structure; Oxidoreductases/*antagonists & inhibitors/chemistry; Protein Binding; Trypanosoma brucei brucei/drug effects/enzymology

In Silico Identification and In Vitro Evaluation of Natural Inhibitors of Leishmania major Pteridine Reductase I. - Herrmann, F. C.; Sivakumar, N.; Jose, J.; Costi, M. P.; Pozzi, C.; Schmidt, T. J. (Molecules, 2017)
In a continuation of our computational efforts to find new natural inhibitors of a variety of target enzymes from parasites causing neglected tropical diseases (NTDs), we now report on 15 natural products (NPs) that we have identified as inhibitors of Leishmania major pteridine reductase I (LmPTR1) through a combination of in silico and in vitro investigations. Pteridine reductase (PTR1) is an enzyme of the trypanosomatid parasites' peculiar folate metabolism, and has previously been validated as a drug target. Initially, pharmacophore queries were created based on four 3D structures of LmPTR1 using co-crystallized known inhibitors as templates. Each of the pharmacophore queries was used to virtually screen a database of 1100 commercially available natural products. The resulting hits were submitted to molecular docking analyses in the substrate binding site of the respective protein structures used for the pharmacophore design. This approach led to the in silico identification of a total of 18 NPs with predicted binding affinity to LmPTR1. These compounds were subsequently tested in vitro for inhibitory activity towards recombinant LmPTR1 in a spectrophotometric inhibition assay. Fifteen out of the 18 tested compounds (hit rate = 83%) showed significant inhibitory activity against LmPTR1 when tested at a concentration of 50 microM. The IC(50) values were determined for the six NPs that inhibited the target enzyme by more than 50% at 50 microM, with sophoraflavanone G being the most active compound tested (IC(50) = 19.2 microM). The NPs identified and evaluated in the present study may represent promising lead structures for the further rational drug design of more potent inhibitors against LmPTR1.
Keywords: Binding Sites; Biological Products/*chemistry/pharmacology; Enzyme Inhibitors/*chemistry/pharmacology; Leishmania major/drug effects/*enzymology; *Models, Molecular; Molecular Docking Simulation; Molecular Dynamics Simulation; Molecular Structure; Oxidoreductases/antagonists & inhibitors/*chemistry; Protein Binding; Structure-Activity Relationship

Exploiting the 2-Amino-1,3,4-thiadiazole Scaffold To Inhibit Trypanosoma brucei Pteridine Reductase in Support of Early-Stage Drug Discovery. - Linciano, P.; Dawson, A.; Pohner, I.; Costa, D. M.; Sa, M. S.; Cordeiro-da-Silva, A.; Luciani, R.; Gul, S.; Witt, G.; Ellinger, B.; Kuzikov, M.; Gribbon, P.; et al. (ACS Omega, 2017)
Pteridine reductase-1 (PTR1) is a promising drug target for the treatment of trypanosomiasis. We investigated the potential of a previously identified class of thiadiazole inhibitors of Leishmania major PTR1 for activity against Trypanosoma brucei (Tb). We solved crystal structures of several TbPTR1-inhibitor complexes to guide the structure-based design of new thiadiazole derivatives. Subsequent synthesis and enzyme- and cell-based assays confirm new, mid-micromolar inhibitors of TbPTR1 with low toxicity. In particular, compound 4m, a biphenyl-thiadiazole-2,5-diamine with IC(50) = 16 muM, was able to potentiate the antitrypanosomal activity of the dihydrofolate reductase inhibitor methotrexate (MTX) with a 4.1-fold decrease of the EC(50) value. In addition, the antiparasitic activity of the combination of 4m and MTX was reversed by addition of folic acid. By adopting an efficient hit discovery platform, we demonstrate, using the 2-amino-1,3,4-thiadiazole scaffold, how a promising tool for the development of anti-T. brucei agents can be obtained.

Comparative mapping of on-targets and off-targets for the discovery of anti-trypanosomatid folate pathway inhibitors. - Panecka-Hofman, J.; Pohner, I.; Spyrakis, F.; Zeppelin, T.; Di Pisa, F.; Dello Iacono, L.; Bonucci, A.; Quotadamo, A.; Venturelli, A.; Mangani, S.; Costi, M. P.; Wade, R. C. (Biochim Biophys Acta Gen Subj, 2017)
BACKGROUND: Multi-target approaches are necessary to properly analyze or modify the function of a biochemical pathway or a protein family. An example of such a problem is the repurposing of the known human anti-cancer drugs, antifolates, as selective anti-parasitic agents. This requires considering a set of experimentally validated protein targets in the folate pathway of major pathogenic trypanosomatid parasites and humans: (i) the primary parasite on-targets: pteridine reductase 1 (PTR1) (absent in humans) and bifunctional dihydrofolate reductase-thymidylate synthase (DHFR-TS), (ii) the primary off-targets: human DHFR and TS, and (iii) the secondary on-target: human folate receptor beta, a folate/antifolate transporter. METHODS: We computationally compared the structural, dynamic and physico-chemical properties of the targets. We based our analysis on available inhibitory activity and crystallographic data, including a crystal structure of the bifunctional T. cruzi DHFR-TS with tetrahydrofolate bound determined in this work. Due to the low sequence and structural similarity of the targets analyzed, we employed a mapping of binding pockets based on the known common ligands, folate and methotrexate. RESULTS: Our analysis provides a set of practical strategies for the design of selective trypanosomatid folate pathway inhibitors, which are supported by enzyme inhibition measurements and crystallographic structures. CONCLUSIONS: The ligand-based comparative computational mapping of protein binding pockets provides a basis for repurposing of anti-folates and the design of new anti-trypanosmatid agents. GENERAL SIGNIFICANCE: Apart from the target-based discovery of selective compounds, our approach may be also applied for protein engineering or analyzing evolutionary relationships in protein families.
Keywords: Binding Sites; Crystallography; *Drug Discovery; Folic Acid Antagonists/*pharmacology; Humans; Multienzyme Complexes/*antagonists & inhibitors/chemistry; Oxidoreductases/*antagonists & inhibitors/chemistry; Tetrahydrofolate Dehydrogenase/chemistry; Thymidylate Synthase/*antagonists & inhibitors/chemistry; Trypanocidal Agents/*pharmacology; Trypanosoma cruzi/drug effects/enzymology

The Future of Drug Development for Neglected Tropical Diseases: How the European Commission Can Continue to Make a Difference. - Pierce, R. J.; MacDougall, J.; Leurs, R.; Costi, M. P. (Trends Parasitol, 2017)
In this article, the four coordinators of neglected tropical disease (NTD) drug development projects funded under the European Commission (EC) Framework Programme 7 argue that the EC should reassess their funding strategy to cover the steps necessary to translate a lead compound into a drug candidate for testing in clinical trials, and suggest ways in which this might be achieved.
Keywords: Drug Discovery/economics/standards/*trends; European Union; Humans; *Neglected Diseases/drug therapy/economics; Public Health/economics/standards/*trends; *Tropical Medicine/economics

Crassiflorone derivatives that inhibit Trypanosoma brucei glyceraldehyde-3-phosphate dehydrogenase (TbGAPDH) and Trypanosoma cruzi trypanothione reductase (TcTR) and display trypanocidal activity. - Uliassi, E.; Fiorani, G.; Krauth-Siegel, R. L.; Bergamini, C.; Fato, R.; Bianchini, G.; Carlos Menendez, J.; Molina, M. T.; Lopez-Montero, E.; Falchi, F.; Cavalli, A.; Gul, S.; et al. (Eur J Med Chem, 2017)
Crassiflorone is a natural product with anti-mycobacterial and anti-gonorrhoeal properties, isolated from the stem bark of the African ebony tree Diospyros crassiflora. We noticed that its pentacyclic core possesses structural resemblance to the quinone-coumarin hybrid 3, which we reported to exhibit a dual-targeted inhibitory profile towards Trypanosoma brucei glyceraldehyde-3-phosphate dehydrogenase (TbGAPDH) and Trypanosoma cruzi trypanothione reductase (TcTR). Following this basic idea, we synthesized a small library of crassiflorone derivatives 15-23 and investigated their potential as anti-trypanosomatid agents. 19 is the only compound of the series showing a balanced dual profile at 10 muM (% inhibition(TbGAPDH) = 64% and % inhibition(TcTR) = 65%). In phenotypic assay, the most active compounds were 18 and 21, which at 5 muM inhibited Tb bloodstream-form growth by 29% and 38%, respectively. Notably, all the newly synthesized compounds at 10 muM did not affect viability and the status of mitochondria in human A549 and 786-O cell lines, respectively. However, further optimization that addresses metabolic liabilities including solubility, as well as cytochromes P450 (CYP1A2, CYP2C9, CYP2C19, and CYP2D6) inhibition, is required before this class of natural product-derived compounds can be further progressed.
Keywords: Cell Line, Tumor; Dose-Response Relationship, Drug; Glyceraldehyde-3-Phosphate Dehydrogenases/*antagonists & inhibitors/metabolism; Humans; Models, Molecular; Molecular Structure; NADH, NADPH Oxidoreductases/*antagonists & inhibitors/metabolism; Parasitic Sensitivity Tests; Quinones/chemical synthesis/chemistry/*pharmacology; Structure-Activity Relationship; Trypanocidal Agents/chemical synthesis/chemistry/*pharmacology; Trypanosoma brucei brucei/*drug effects/enzymology/growth & development; Trypanosoma cruzi/*drug effects/enzymology/growth & development

Profiling of Flavonol Derivatives for the Development of Antitrypanosomatidic Drugs. - Borsari, C.; Luciani, R.; Pozzi, C.; Poehner, I.; Henrich, S.; Trande, M.; Cordeiro-da-Silva, A.; Santarem, N.; Baptista, C.; Tait, A.; Di Pisa, F.; Dello Iacono, L.; et al. (J Med Chem, 2016)
Flavonoids represent a potential source of new antitrypanosomatidic leads. Starting from a library of natural products, we combined target-based screening on pteridine reductase 1 with phenotypic screening on Trypanosoma brucei for hit identification. Flavonols were identified as hits, and a library of 16 derivatives was synthesized. Twelve compounds showed EC50 values against T. brucei below 10 muM. Four X-ray crystal structures and docking studies explained the observed structure-activity relationships. Compound 2 (3,6-dihydroxy-2-(3-hydroxyphenyl)-4H-chromen-4-one) was selected for pharmacokinetic studies. Encapsulation of compound 2 in PLGA nanoparticles or cyclodextrins resulted in lower in vitro toxicity when compared to the free compound. Combination studies with methotrexate revealed that compound 13 (3-hydroxy-6-methoxy-2-(4-methoxyphenyl)-4H-chromen-4-one) has the highest synergistic effect at concentration of 1.3 muM, 11.7-fold dose reduction index and no toxicity toward host cells. Our results provide the basis for further chemical modifications aimed at identifying novel antitrypanosomatidic agents showing higher potency toward PTR1 and increased metabolic stability.
Keywords: Animals; Biological Products/chemical synthesis/chemistry/*pharmacology; Cell Line; Dose-Response Relationship, Drug; Flavonols/chemical synthesis/chemistry/*pharmacology; Humans; Macrophages/drug effects; Mice; Mice, Inbred BALB C; Models, Molecular; Molecular Structure; Parasitic Sensitivity Tests; Structure-Activity Relationship; Trypanocidal Agents/chemical synthesis/chemistry/*pharmacology; Trypanosoma brucei brucei/*drug effects

Current and Future Chemotherapy for Chagas Disease. - Gaspar, L.; Moraes, C. B.; Freitas-Junior, L. H.; Ferrari, S.; Costantino, L.; Costi, M. P.; Coron, R. P.; Smith, T. K.; Siqueira-Neto, J. L.; McKerrow, J. H.; Cordeiro-da-Silva, A. (Curr Med Chem, 2015)
Human American trypanosomiasis, commonly called Chagas disease, is one of the most neglected illnesses in the world and remains one of the most prevalent chronic infectious diseases of Latin America with thousands of new cases every year. The only treatments available have been introduced five decades ago. They have serious, undesirable side effects and disputed benefits in the chronic stage of the disease - a characteristic and debilitating cardiomyopathy and/or megavisceras. Several laboratories have therefore focused their efforts in finding better drugs. Although recent years have brought new clinical trials, these are few and lack diversity in terms of drug mechanism of action, thus resulting in a weak drug discovery pipeline. This fragility has been recently exposed by the failure of two candidates; posaconazole and E1224, to sterilely cure patients in phase 2 clinical trials. Such setbacks highlight the need for continuous, novel and high quality drug discovery and development efforts to discover better and safer treatments. In this article we will review past and current findings on drug discovery for Trypanosoma cruzi made by academic research groups, industry and other research organizations over the last half century. We also analyze the current research landscape that is now better placed than ever to deliver alternative treatments for Chagas disease in the near future.
Keywords: Antiprotozoal Agents/*therapeutic use; Chagas Disease/*drug therapy; Drug Discovery/*trends; Humans; Trypanosoma cruzi/physiology

The German Corona Consensus Dataset (GECCO): A standardized dataset for COVID-19 research - Sass, Julian; Bartschke, Alexander; Lehne, Moritz; Essenwanger, Andrea; Rinaldi, Eugenia; Rudolph, Stefanie; Heitmann, Kai Uwe; Vehreschild, Joerg Janne; von Kalle, Christof; Thun, Sylvia (2020)
Background: The current COVID-19 pandemic has led to a surge of research activity. While this research provides important insights, the multitude of studies results in an increasing segmentation of information. To ensure comparability across projects and institutions, standard datasets are needed. Here, we introduce the "German Corona Consensus Dataset" (GECCO), a uniform dataset that uses international terminologies and health IT standards to improve interoperability of COVID-19 data. Methods: Based on previous work (e.g., the ISARIC-WHO COVID-19 case report form) and in coordination with experts from university hospitals, professional associations and research initiatives, data elements relevant for COVID-19 research were collected, prioritized and consolidated into a compact core dataset. The dataset was mapped to international terminologies, and the Fast Healthcare Interoperability Resources (FHIR) standard was used to define interoperable, machine-readable data formats. Results: A core dataset consisting of 81 data elements with 281 response options was defined, including information about, for example, demography, anamnesis, symptoms, therapy, medications or laboratory values of COVID-19 patients. Data elements and response options were mapped to SNOMED CT, LOINC, UCUM, ICD-10-GM and ATC, and FHIR profiles for interoperable data exchange were defined. Conclusion: GECCO provides a compact, interoperable dataset that can help to make COVID-19 research data more comparable across studies and institutions. The dataset will be further refined in the future by adding domain-specific extension modules for more specialized use cases.

The first 10 years of the international coordination network for standards in systems and synthetic biology (COMBINE) - Waltemath, Dagmar; Golebiewski, Martin; Blinov, Michael; Gleeson, Padraig; Hermjakob, Henning; Hucka, Mike; Inau, Esther Thea; Keating, Sarah M; König, Matthias; Krebs, Olga; Malik-Sheriff, Rahuman S; Nickerson, David; et al. (Journal of Integrative Bioinformatics, 2020)
This paper presents a report on outcomes of the 10th Computational Modeling in Biology Network (COMBINE) meeting that was held in Heidelberg, Germany, in July of 2019. The annual event brings together researchers, biocurators and software engineers to present recent results and discuss future work in the area of standards for systems and synthetic biology. The COMBINE initiative coordinates the development of various community standards and formats for computational models in the life sciences. Over the past 10 years, COMBINE has brought together standard communities that have further developed and harmonized their standards for better interoperability of models and data. COMBINE 2019 was co-located with a stakeholder workshop of the European EU-STANDS4PM initiative that aims at harmonized data and model standardization for in silico models in the field of personalized medicine, as well as with the FAIRDOM PALs meeting to discuss findable, accessible, interoperable and reusable (FAIR) data sharing. This report briefly describes the work discussed in invited and contributed talks as well as during breakout sessions. It also highlights recent advancements in data, model, and annotation standardization efforts. Finally, this report concludes with some challenges and opportunities that this community will face during the next 10 years.

Specifications of standards in systems and synthetic biology: status and developments in 2020 - Schreiber, Falk; Sommer, Björn; Czauderna, Tobias; Golebiewski, Martin; Gorochowski, Thomas E.; Hucka, Mike; Keating, Sarah M.; König, Matthias; Myers, Chris; Nickerson, David; Waltemath, Dagmar (Journal of Integrative Bioinformatics, 2020)
This special issue of the Journal of Integrative Bioinformatics presents papers related to the 10th COMBINE meeting together with the annual update of COMBINE standards in systems and synthetic biology.

Data Management in Computational Systems Biology: Exploring Standards, Tools, Databases, and Packaging Best Practices. - Stanford, N. J.; Scharm, M.; Dobson, P. D.; Golebiewski, M.; Hucka, M.; Kothamachu, V. B.; Nickerson, D.; Owen, S.; Pahle, J.; Wittig, U.; Waltemath, D.; Goble, C.; et al. (Methods Mol Biol, 2019)
Computational systems biology involves integrating heterogeneous datasets in order to generate models. These models can assist with understanding and prediction of biological phenomena. Generating datasets and integrating them into models involves a wide range of scientific expertise. As a result these datasets are often collected by one set of researchers, and exchanged with others researchers for constructing the models. For this process to run smoothly the data and models must be FAIR-findable, accessible, interoperable, and reusable. In order for data and models to be FAIR they must be structured in consistent and predictable ways, and described sufficiently for other researchers to understand them. Furthermore, these data and models must be shared with other researchers, with appropriately controlled sharing permissions, before and after publication. In this chapter we explore the different data and model standards that assist with structuring, describing, and sharing. We also highlight the popular standards and sharing databases within computational systems biology.
Keywords: Computational Biology; Data Management/*methods; Databases, Factual; Systems Biology/*methods

Specifications of Standards in Systems and Synthetic Biology: Status and Developments in 2019 - Schreiber, Falk; Sommer, Björn; Bader, Gary D.; Gleeson, Padraig; Golebiewski, Martin; Hucka, Mike; Keating, Sarah M.; König, Matthias; Myers, Chris; Nickerson, David; Waltemath, Dagmar (Journal of Integrative Bioinformatics, 2019)
This special issue of the Journal of Integrative Bioinformatics presents an overview of COMBINE standards and their latest specifications. The standards cover representation formats for computational modeling in synthetic and systems biology and include BioPAX, CellML, NeuroML, SBML, SBGN, SBOL and SED-ML. The articles in this issue contain updated specifications of SBGN Process Description Level 1 Version 2, SBML Level 3 Core Version 2 Release 2, SBOL Version 2.3.0, and SBOL Visual Version 2.1.

Data Formats for Systems Biology and Quantitative Modeling - Golebiewski, Martin (Encyclopedia of Bioinformatics and Computational Biology, 2019)
Data standards support the reliable exchange of information, the interoperability of tools, and the reproducibility of scientific results. In systems biology standards are agreed ways of structuring, describing, and associating models and data, as well as their respective parts, graphical visualization, and information about applied experimental or computational methods. Such standards also assist with describing how constituent parts interact together, or are linked, and how they are embedded in their environmental and experimental context. Here the focus will be on standards for formatting models and their content, and on metadata checklists and ontologies that support modeling.

A brief history of COMBINE - Myers, Chris J.; Bader, Gary; Gleeson, Padraig; Golebiewski, Martin; Hucka, Mike; Le Novere, Nicolas; Nickerson, David; Schreiber, Falk; Waltemath, Dagmar (2017 Winter Simulation Conference (WSC), 2017)
Standards for data exchange are critical to the development of any field. They enable researchers and practitioners to transport information reliably, to apply a variety of tools to their problems, and to reproduce scientific results. Over the past two decades, a range of standards have been developed to facilitate the exchange and reuse of information in the domain of representation and modeling of biological systems. These standards are complementary, so the interactions between their developers increased over time. By the end of the last decade, the community of researchers decided that more interoperability is required between the standards, and that common development is needed to make better use of effort, time, and money devoted to this activity. The COmputational MOdeling in Biology NEtwork (COMBINE) was created to enable the sharing of resources, tools, and other infrastructure. This paper provides a brief history of this endeavor and the challenges that remain.

An explanatory model of temperature influence on flowering through whole-plant accumulation of FLOWERING LOCUS T in Arabidopsis thaliana - Kinmonth-Schultz, Hannah; MacEwen, Melissa J S; Seaton, Daniel; Millar, Andrew; Imaizumi, Takato; Kim, Soo-Hyung (in silico Plants, 2019)
We assessed mechanistic temperature influence on flowering by incorporating temperature-responsive flowering mechanisms across developmental age into an existing model. Temperature influences the leaf production rate as well as expression of FLOWERING LOCUS T (FT), a photoperiodic flowering regulator that is expressed in leaves. The Arabidopsis Framework Model incorporated temperature influence on leaf growth but ignored the consequences of leaf growth on and direct temperature influence of FT expression. We measured FT production in differently aged leaves and modified the model, adding mechanistic temperature influence on FT transcription, and causing whole-plant FT to accumulate with leaf growth. Our simulations suggest that in long days, the developmental stage (leaf number) at which the reproductive transition occurs is influenced by day length and temperature through FT, while temperature influences the rate of leaf production and the time (in days) the transition occurs. Further, we demonstrate that FT is mainly produced in the first 10 leaves in the Columbia (Col-0) accession, and that FT accumulation alone cannot explain flowering in conditions in which flowering is delayed. Our simulations supported our hypotheses that: (i) temperature regulation of FT, accumulated with leaf growth, is a component of thermal time, and (ii) incorporating mechanistic temperature regulation of FT can improve model predictions when temperatures change over time.

Advice from a systems-biology model of the corona epidemics - Westerhoff, Hans V.; Kolodkin, Alexey (npj Systems Biology and Applications, 2020)
Using standard systems biology methodologies a 14-compartment dynamic model was developed for the Corona virus epidemic. The model predicts that: (i) it will be impossible to limit lockdown intensity such that sufficient herd immunity develops for this epidemic to die down, (ii) the death toll from the SARS-CoV-2 virus decreases very strongly with increasing intensity of the lockdown, but (iii) the duration of the epidemic increases at first with that intensity and then decreases again, such that (iv) it may be best to begin with selecting a lockdown intensity beyond the intensity that leads to the maximum duration, (v) an intermittent lockdown strategy should also work and might be more acceptable socially and economically, (vi) an initially intensive but adaptive lockdown strategy should be most efficient, both in terms of its low number of casualties and shorter duration, (vii) such an adaptive lockdown strategy offers the advantage of being robust to unexpected imports of the virus, e.g. due to international travel, (viii) the eradication strategy may still be superior as it leads to even fewer deaths and a shorter period of economic downturn, but should have the adaptive strategy as backup in case of unexpected infection imports, (ix) earlier detection of infections is the most effective way in which the epidemic can be controlled, whilst waiting for vaccines.

Application of a simple quantum chemical approach to ligand fragment scoring for Trypanosoma brucei pteridine reductase 1 inhibition. - Jedwabny, W.; Panecka-Hofman, J.; Dyguda-Kazimierowicz, E.; Wade, R. C.; Sokalski, W. A. (J Comput Aided Mol Des, 2017)
There is a need for improved and generally applicable scoring functions for fragment-based approaches to ligand design. Here, we evaluate the performance of a computationally efficient model for inhibitory activity estimation, which is composed only of multipole electrostatic energy and dispersion energy terms that approximate long-range ab initio quantum mechanical interaction energies. We find that computed energies correlate well with inhibitory activity for a compound series with varying substituents targeting two subpockets of the binding site of Trypanosoma brucei pteridine reductase 1. For one subpocket, we find that the model is more predictive for inhibitory activity than the ab initio interaction energy calculated at the MP2 level. Furthermore, the model is found to outperform a commonly used empirical scoring method. Finally, we show that the results for the two subpockets can be combined, which suggests that this simple nonempirical scoring function could be applied in fragment-based drug design.
Keywords: Binding Sites; Drug Design; Humans; Ligands; *Models, Molecular; Molecular Structure; Oxidoreductases/*antagonists & inhibitors/chemistry; Protein Binding; Quantum Theory; Static Electricity; Structure-Activity Relationship; Trypanocidal Agents/*chemistry; Trypanosoma brucei brucei/*enzymology

TRAPP webserver: predicting protein binding site flexibility and detecting transient binding pockets. - Stank, A.; Kokh, D. B.; Horn, M.; Sizikova, E.; Neil, R.; Panecka, J.; Richter, S.; Wade, R. C. (Nucleic Acids Res, 2017)
The TRAnsient Pockets in Proteins (TRAPP) webserver provides an automated workflow that allows users to explore the dynamics of a protein binding site and to detect pockets or sub-pockets that may transiently open due to protein internal motion. These transient or cryptic sub-pockets may be of interest in the design and optimization of small molecular inhibitors for a protein target of interest. The TRAPP workflow consists of the following three modules: (i) TRAPP structure- generation of an ensemble of structures using one or more of four possible molecular simulation methods; (ii) TRAPP analysis-superposition and clustering of the binding site conformations either in an ensemble of structures generated in step (i) or in PDB structures or trajectories uploaded by the user; and (iii) TRAPP pocket-detection, analysis, and visualization of the binding pocket dynamics and characteristics, such as volume, solvent-exposed area or properties of surrounding residues. A standard sequence conservation score per residue or a differential score per residue, for comparing on- and off-targets, can be calculated and displayed on the binding pocket for an uploaded multiple sequence alignment file, and known protein sequence annotations can be displayed simultaneously. The TRAPP webserver is freely available at http://trapp.h-its.org.
Keywords: Amino Acid Sequence; Antiprotozoal Agents/chemical synthesis/*chemistry; Binding Sites; Drug Design; Folic Acid Antagonists/chemical synthesis/*chemistry; Humans; Internet; Ligands; Molecular Dynamics Simulation; Protein Binding; Protein Conformation, alpha-Helical; Protein Conformation, beta-Strand; Protein Interaction Domains and Motifs; Protozoan Proteins/antagonists & inhibitors/*chemistry; Sequence Alignment; *Software; Species Specificity; Tetrahydrofolate Dehydrogenase/*chemistry; Thermodynamics; Trypanosoma cruzi/*chemistry/enzymology

Solvent screening methodology for in situ ABE extractive fermentation - González-Peñas, H.; Lu-Chau, Thelmo; Moreira, Maria Teresa; Lema, J. M. (Applied Microbiology and Biotechnology, 2014)
Solvent screening for in situ liquid extraction of products from acetone-butanol-ethanol (ABE) fermentation was carried out, taking into account biological parameters (biocompatibility, bioavailability, and product yield) and ex-traction performance (partition coefficient and selectivity) determined in real fermentation broth. On the basis of different solvent characteristics obtained from literature, 16 compounds from different chemical families were selected and experimentally evaluated for their extraction capabilities in a real ABE fermentation broth system. From these compounds, nine potential solvents were also tested for their biocompatibility towards Clostridium acetobutylicum. Moreover, bioavailability and differences in substrate consumption and total n-butanol production with respect to solvent-free fermentations were quantified for each biocompatible solvent. Product yield was enhanced in the presence of organic solvents having higher affinity for butanol and butyric acid. Applying this methodology, it was found that the Guerbet alcohol 2-butyl-1-octanol presented the best extracting characteristics (the highest partition coefficient (6.76) and the third highest selectivity (644)), the highest butanol yield (27.4 %), and maintained biocompatibility with C. acetobutylicum.

Non-canonical signaling of the PTH receptor. - Vilardaga, J. P.; Gardella, T. J.; Wehbi, V. L.; Feinstein, T. N. (Trends Pharmacol Sci, 2012)
The classical model of arrestin-mediated desensitization of cell-surface G-protein-coupled receptors (GPCRs) is thought to be universal. However, this paradigm is incompatible with recent reports that the parathyroid hormone (PTH) receptor (PTHR), a crucial GPCR for bone and mineral ion metabolism, sustains G(S) activity and continues to generate cAMP for prolonged periods after ligand washout; during these periods the receptor is observed mainly in endosomes, associated with the bound ligand, G(S) and beta-arrestins. In this review we discuss possible molecular mechanisms underlying sustained signaling by the PTHR, including modes of signal generation and attenuation within endosomes, as well as the biological relevance of such non-canonical signaling.
Keywords: Animals; Arrestins/metabolism; Cyclic AMP/metabolism; Endosomes/metabolism; GTP-Binding Proteins/metabolism; Humans; Protein Conformation; Receptors, Parathyroid Hormone/*chemistry/metabolism; *Signal Transduction; beta-Arrestins

Winning the numbers game in enzyme evolution - fast screening methods for improved biotechnology proteins. - Sheludko, Y. V.; Fessner, W. D. (Curr Opin Struct Biol, 2020)
The booming demand for environmentally benign industrial processes relies on the ability to quickly find or engineer a biocatalyst suitable to ideal process conditions. Both metagenomic approaches and directed evolution involve the screening of huge libraries of protein variants, which can only be managed reasonably by flexible platforms for (ultra)high-throughput profiling against the desired criteria. Here, we review the most recent additions toward a growing toolbox of versatile assays using fluorescence, absorbance and mass spectrometry readouts. While conventional solution based high-throughput screening in microtiter plate formats is still important, the implementation of novel screening protocols for microfluidic cell or droplet sorting systems supports technological advances for ultra-high-frequency screening that now can dramatically reduce the timescale of engineering projects. We discuss practical issues of scope, scalability, sensitivity and stereoselectivity for the improvement of biotechnologically relevant enzymes from different classes.
Keywords: Animals; Biocatalysis; Biotechnology; *Directed Molecular Evolution; Enzyme Activation; Enzymes/*chemistry/genetics/metabolism; High-Throughput Screening Assays/methods; Humans; *Protein Engineering/methods; Protein Stability; Substrate Specificity

Biocatalytic Construction of Quaternary Centers by Aldol Addition of 3,3-Disubstituted 2-Oxoacid Derivatives to Aldehydes - Marín-Valls, Roser; Hernandez, Karel; Bolte, Michael; Parella, Teodor; Joglar, Jesús; Bujons, Jordi; Clapés, Pere (Journal of the American Chemical Society, 2020)
The congested nature of quaternary carbons hinders their preparation, most notably when stereocontrol is required. Here we report a biocatalytic method for the creation of quaternary carbon centers with broad substrate scope, leading to different compound classes bearing this structural feature. The key step comprises the aldol addition of 3,3-disubstituted 2-oxoacids to aldehydes catalyzed by metal dependent 3-methyl-2-oxobutanoate hydroxymethyltransferase from E. coli (KPHMT) and variants thereof. The 3,3,3-trisubstituted 2-oxoacids thus produced were converted into 2-oxolactones and 3-hydroxy acids and directly to ulosonic acid derivatives, all bearing gem-dialkyl, gem-cycloalkyl, and spirocyclic quaternary centers. In addition, some of these reactions use a single enantiomer from racemic nucleophiles to afford stereopure quaternary carbons. The notable substrate tolerance and stereocontrol of these enzymes are indicative of their potential for the synthesis of structurally intricate molecules.

Mutual Zonated Interactions of Wnt and Hh Signaling Are Orchestrating the Metabolism of the Adult Liver in Mice and Human. - Kolbe, E.; Aleithe, S.; Rennert, C.; Spormann, L.; Ott, F.; Meierhofer, D.; Gajowski, R.; Stopel, C.; Hoehme, S.; Kucken, M.; Brusch, L.; Seifert, M.; et al. (Cell Rep, 2019)
The Hedgehog (Hh) and Wnt/beta-Catenin (Wnt) cascades are morphogen pathways whose pronounced influence on adult liver metabolism has been identified in recent years. How both pathways communicate and control liver metabolic functions are largely unknown. Detecting core components of Wnt and Hh signaling and mathematical modeling showed that both pathways in healthy liver act largely complementary to each other in the pericentral (Wnt) and the periportal zone (Hh) and communicate mainly by mutual repression. The Wnt/Hh module inversely controls the spatiotemporal operation of various liver metabolic pathways, as revealed by transcriptome, proteome, and metabolome analyses. Shifting the balance to Wnt (activation) or Hh (inhibition) causes pericentralization and periportalization of liver functions, respectively. Thus, homeostasis of the Wnt/Hh module is essential for maintaining proper liver metabolism and to avoid the development of certain metabolic diseases. With caution due to minor species-specific differences, these conclusions may hold for human liver as well.
Keywords: Adult; Animals; Body Patterning/genetics; Female; Hedgehog Proteins/*metabolism; Humans; Liver/*metabolism; Male; Mice, Inbred C57BL; Mice, Knockout; Transcription, Genetic; Wnt Proteins/*metabolism; *Wnt Signaling Pathway/genetics

Bile canaliculi remodeling activates YAP via the actin cytoskeleton during liver regeneration. - Meyer, K.; Morales-Navarrete, H.; Seifert, S.; Wilsch-Braeuninger, M.; Dahmen, U.; Tanaka, E. M.; Brusch, L.; Kalaidzidis, Y.; Zerial, M. (Mol Syst Biol, 2020)
The mechanisms of organ size control remain poorly understood. A key question is how cells collectively sense the overall status of a tissue. We addressed this problem focusing on mouse liver regeneration. Using digital tissue reconstruction and quantitative image analysis, we found that the apical surface of hepatocytes forming the bile canalicular network expands concomitant with an increase in F-actin and phospho-myosin, to compensate an overload of bile acids. These changes are sensed by the Hippo transcriptional co-activator YAP, which localizes to apical F-actin-rich regions and translocates to the nucleus in dependence of the integrity of the actin cytoskeleton. This mechanism tolerates moderate bile acid fluctuations under tissue homeostasis, but activates YAP in response to sustained bile acid overload. Using an integrated biophysical-biochemical model of bile pressure and Hippo signaling, we explained this behavior by the existence of a mechano-sensory mechanism that activates YAP in a switch-like manner. We propose that the apical surface of hepatocytes acts as a self-regulatory mechano-sensory system that responds to critical levels of bile acids as readout of tissue status.
Keywords: Actin Cytoskeleton/*metabolism; Actins/metabolism; Adaptor Proteins, Signal Transducing/*metabolism; Animals; Bile Acids and Salts/*metabolism; Bile Canaliculi/*metabolism; Cell Cycle Proteins/*metabolism; Cell Nucleus/metabolism; Cells, Cultured; Hepatocytes/*cytology/metabolism; Liver Regeneration; Male; Mechanotransduction, Cellular; Mice; Myosins/metabolism; Organ Size; Protein Transport; Systems Biology; YAP-Signaling Proteins

ROS networks: designs, aging, Parkinson's disease and precision therapies. - N Kolodkin, A.; Sharma, R. P.; Colangelo, A. M.; Ignatenko, A.; Martorana, F.; Jennen, D.; Briede, J. J.; Brady, N.; Barberis, M.; Mondeel, T. D. G. A.; Papa, M.; Kumar, V.; et al. (NPJ Syst Biol Appl, 2020)
How the network around ROS protects against oxidative stress and Parkinson's disease (PD), and how processes at the minutes timescale cause disease and aging after decades, remains enigmatic. Challenging whether the ROS network is as complex as it seems, we built a fairly comprehensive version thereof which we disentangled into a hierarchy of only five simpler subnetworks each delivering one type of robustness. The comprehensive dynamic model described in vitro data sets from two independent laboratories. Notwithstanding its five-fold robustness, it exhibited a relatively sudden breakdown, after some 80 years of virtually steady performance: it predicted aging. PD-related conditions such as lack of DJ-1 protein or increased alpha-synuclein accelerated the collapse, while antioxidants or caffeine retarded it. Introducing a new concept (aging-time-control coefficient), we found that as many as 25 out of 57 molecular processes controlled aging. We identified new targets for "life-extending interventions": mitochondrial synthesis, KEAP1 degradation, and p62 metabolism.
Keywords: *Aging; Computational Biology; Humans; *Models, Biological; Molecular Targeted Therapy; Oxidative Stress; Parkinson Disease/*metabolism/physiopathology/*therapy; *Precision Medicine; Reactive Oxygen Species/*metabolism

Upcycling of hydrolyzed PET by microbial conversion to a fatty acid derivative - Welsing, Gina; Wolter, Birger; Hintzen, Henric M.T.; Tiso, Till; Blank, Lars (Methods in Enzymology, 2021)
The enzymatic degradation of polyethylene terephthalate (PET) results in a hydrolysate consisting almost exclusively of its two monomers, ethylene glycol and terephthalate. To biologically valorize the PET hydrolysate, microbial upcycling into high-value products is proposed. Fatty acid derivatives hydroxyalkanoyloxy alkanoates (HAAs) represent such valuable target molecules. HAAs exhibit surface-active properties and can be exploited in the catalytical conversion to drop-in biofuels as well as in the polymerization to bio-based poly(amide urethane). This chapter presents the genetic engineering methods of pseudomonads for the metabolization of PET monomers and the biosynthesis of HAAs with detailed protocols concerning product purification.

Identification of evolutionary and kinetic drivers of NAD-dependent signaling. - Bockwoldt, M.; Houry, D.; Niere, M.; Gossmann, T. I.; Reinartz, I.; Schug, A.; Ziegler, M.; Heiland, I. (Proc Natl Acad Sci U S A, 2019)
Nicotinamide adenine dinucleotide (NAD) provides an important link between metabolism and signal transduction and has emerged as central hub between bioenergetics and all major cellular events. NAD-dependent signaling (e.g., by sirtuins and poly-adenosine diphosphate [ADP] ribose polymerases [PARPs]) consumes considerable amounts of NAD. To maintain physiological functions, NAD consumption and biosynthesis need to be carefully balanced. Using extensive phylogenetic analyses, mathematical modeling of NAD metabolism, and experimental verification, we show that the diversification of NAD-dependent signaling in vertebrates depended on 3 critical evolutionary events: 1) the transition of NAD biosynthesis to exclusive usage of nicotinamide phosphoribosyltransferase (NamPT); 2) the occurrence of nicotinamide N-methyltransferase (NNMT), which diverts nicotinamide (Nam) from recycling into NAD, preventing Nam accumulation and inhibition of NAD-dependent signaling reactions; and 3) structural adaptation of NamPT, providing an unusually high affinity toward Nam, necessary to maintain NAD levels. Our results reveal an unexpected coevolution and kinetic interplay between NNMT and NamPT that enables extensive NAD signaling. This has implications for therapeutic strategies of NAD supplementation and the use of NNMT or NamPT inhibitors in disease treatment.
Keywords: Amino Acid Sequence; Animals; *Biological Evolution; Biosynthetic Pathways; HeLa Cells; Humans; Kinetics; NAD/*metabolism; Nicotinamide N-Methyltransferase; Nicotinamide Phosphoribosyltransferase/chemistry/metabolism; Phylogeny; *Signal Transduction; Substrate Specificity; Vertebrates/metabolism

IL4I1 Is a Metabolic Immune Checkpoint that Activates the AHR and Promotes Tumor Progression - Sadik, Ahmed; Somarribas Patterson, Luis F.; Öztürk, Selcen; Mohapatra, Soumya R.; Panitz, Verena; Secker, Philipp F.; Pfänder, Pauline; Loth, Stefanie; Salem, Heba; Prentzell, Mirja Tamara; Berdel, Bianca; Iskar, Murat; et al. (Cell, 2020)
Aryl hydrocarbon receptor (AHR) activation by tryptophan (Trp) catabolites enhances tumor malignancy and suppresses anti-tumor immunity. The context specificity of AHR target genes has so far impeded systematic investigation of AHR activity and its upstream enzymes across human cancers. A pan-tissue AHR signature, derived by natural language processing, revealed that across 32 tumor entities, interleukin-4-induced-1 (IL4I1) associates more frequently with AHR activity than IDO1 or TDO2, hitherto recognized as the main Trp-catabolic enzymes. IL4I1 activates the AHR through the generation of indole metabolites and kynurenic acid. It associates with reduced survival in glioma patients, promotes cancer cell motility, and suppresses adaptive immunity, thereby enhancing the progression of chronic lymphocytic leukemia (CLL) in mice. Immune checkpoint blockade (ICB) induces IDO1 and IL4I1. As IDO1 inhibitors do not block IL4I1, IL4I1 may explain the failure of clinical studies combining ICB with IDO1 inhibition. Taken together, IL4I1 blockade opens new avenues for cancer therapy.

Breaking the Interface: Efficient Extraction of Magnetic Beads from Nanoliter Droplets for Automated Sequential Immunoassays - Metzler, Lukas; Rehbein, Ulrike; Schönberg, Jan-Niklas; Brandstetter, Thomas; Thedieck, Kathrin; Rühe, Jürgen (Analytical Chemistry, 2020)
Droplet-based microfluidic systems offer a high potential for miniaturization and automation. Therefore, they are becoming an increasingly important tool in analytical chemistry, biosciences, and medicine. Heterogeneous assays commonly utilize magnetic beads as a solid phase. However, the sensitivity of state of the art microfluidic systems is limited by the high bead concentrations required for efficient extraction across the water–oil interface. Furthermore, current systems suffer from a lack of technical solutions for sequential measurements of multiple samples, limiting their throughput and capacity for automation. Taking advantage of the different wetting properties of hydrophilic and hydrophobic areas in the channels, we improve the extraction efficiency of magnetic beads from aqueous nanoliter-sized droplets by 2 orders of magnitude to the low μg/mL range. Furthermore, the introduction of a switchable magnetic trap enables repetitive capture and release of magnetic particles for sequential analysis of multiple samples, enhancing the throughput. In comparison to conventional ELISA-based sandwich immunoassays on microtiter plates, our microfluidic setup offers a 25–50-fold reduction of sample and reagent consumption with up to 50 technical replicates per sample. The enhanced sensitivity and throughput of this system open avenues for the development of automated detection of biomolecules at the nanoliter scale.

The therapeutic potential of targeting tryptophan catabolism in cancer. - Opitz, C. A.; Somarribas Patterson, L. F.; Mohapatra, S. R.; Dewi, D. L.; Sadik, A.; Platten, M.; Trump, S. (Br J Cancer, 2020)
Based on its effects on both tumour cell intrinsic malignant properties as well as anti-tumour immune responses, tryptophan catabolism has emerged as an important metabolic regulator of cancer progression. Three enzymes, indoleamine-2,3-dioxygenase 1 and 2 (IDO1/2) and tryptophan-2,3-dioxygenase (TDO2), catalyse the first step of the degradation of the essential amino acid tryptophan (Trp) to kynurenine (Kyn). The notion of inhibiting IDO1 using small-molecule inhibitors elicited high hopes of a positive impact in the field of immuno-oncology, by restoring anti-tumour immune responses and synergising with other immunotherapies such as immune checkpoint inhibition. However, clinical trials with IDO1 inhibitors have yielded disappointing results, hence raising many questions. This review will discuss strategies to target Trp-degrading enzymes and possible down-stream consequences of their inhibition. We aim to provide comprehensive background information on Trp catabolic enzymes as targets in immuno-oncology and their current state of development. Details of the clinical trials with IDO1 inhibitors, including patient stratification, possible effects of the inhibitors themselves, effects of pre-treatments and the therapies the inhibitors were combined with, are discussed and mechanisms proposed that might have compensated for IDO1 inhibition. Finally, alternative approaches are suggested to circumvent these problems.
Keywords: Animals; Enzyme Inhibitors/*therapeutic use; Humans; Immunotherapy/methods; Indoleamine-Pyrrole 2,3,-Dioxygenase/*antagonists & inhibitors/metabolism; Kynurenine/metabolism; Mice; Neoplasms/*drug therapy/*metabolism; Tryptophan/*metabolism; Tryptophan Oxygenase/*antagonists & inhibitors/metabolism

Protein misfolding is the molecular mechanism underlying MCADD identified in newborn screening. - Maier, E. M.; Gersting, S. W.; Kemter, K. F.; Jank, J. M.; Reindl, M.; Messing, D. D.; Truger, M. S.; Sommerhoff, C. P.; Muntau, A. C. (Hum Mol Genet, 2009)
Newborn screening (NBS) for medium-chain acyl-CoA dehydrogenase deficiency (MCADD) revealed a higher birth prevalence and genotypic variability than previously estimated, including numerous novel missense mutations in the ACADM gene. On average, these mutations are associated with milder biochemical phenotypes raising the question about their pathogenic relevance. In this study, we analyzed the impact of 10 ACADM mutations identified in NBS (A27V, Y42H, Y133H, R181C, R223G, D241G, K304E, R309K, I331T and R388S) on conformation, stability and enzyme kinetics of the corresponding proteins. Partial to total rescue of aggregation by co-overexpression of GroESL indicated protein misfolding. This was confirmed by accelerated thermal unfolding in all variants, as well as decreased proteolytic stability and accelerated thermal inactivation in most variants. Catalytic function varied from high residual activity to markedly decreased activity or substrate affinity. Mutations mapping to the beta-domain of the protein predisposed to severe destabilization. In silico structural analyses of the affected amino acid residues revealed involvement in functionally relevant networks. Taken together, our results substantiate the hypothesis of protein misfolding with loss-of-function being the common molecular basis in MCADD. Moreover, considerable structural alterations in all analyzed variants do not support the view that novel mutations found in NBS bear a lower risk of metabolic decompensation than that associated with mutations detected in clinically ascertained patients. Finally, the detailed insight into how ACADM missense mutations induce loss of MCAD function may provide guidance for risk assessment and counseling of patients, and in future may assist delineation of novel pharmacological strategies.
Keywords: Acyl-CoA Dehydrogenase/*chemistry/*deficiency/genetics; Amino Acid Substitution; Enzyme Stability; Female; Humans; Infant, Newborn; Kinetics; Lipid Metabolism, Inborn Errors/*enzymology/genetics; Male; Molecular Conformation; Molecular Sequence Data; Mutation, Missense; *Neonatal Screening; *Protein Folding

A Rapid Method for Selecting Non-Saccharomyces Strains with a Low Ethanol Yield - Zhu, Xiaolin; Navarro, Yurena; Mas, Albert; Torija-Martínez, María-Jesús; Beltran Casellas, Gemma (Microorganisms, 2020)
The alcohol content in wine has increased due to external factors in recent decades. In recent reports, some non-Saccharomyces yeast species have been confirmed to reduce ethanol during the alcoholic fermentation process. Thus, an efficient screening of non-Saccharomyces yeasts with low ethanol yield is required due to the broad diversity of these yeasts. In this study, we proposed a rapid method for selecting strains with a low ethanol yield from forty-five non-Saccharomyces yeasts belonging to eighteen species. Single fermentations were carried out for this rapid selection. Then, sequential fermentations in synthetic and natural must were conducted with the selected strains to confirm their capacity to reduce ethanol compared with that of Saccharomyces cerevisiae. The results showed that ten non-Saccharomyces strains were able to reduce the ethanol content, namely, Hanseniaspora uvarum (2), Issatchenkia terricola (1), Metschnikowia pulcherrima (2), Lachancea thermotolerans (1), Saccharomycodes ludwigii (1), Torulaspora delbrueckii (2), and Zygosaccharomyces bailii (1). Compared with S. cerevisiae, the ethanol reduction of the selected strains ranged from 0.29 to 1.39% (v/v). Sequential inoculations of M. pulcherrima (Mp51 and Mp FA) and S. cerevisiae reduced the highest concentration of ethanol by 1.17 to 1.39% (v/v) in synthetic or natural must. Second, sequential fermentations with Z. bailii (Zb43) and T. delbrueckii (Td Pt) performed in natural must yielded ethanol reductions of 1.02 and 0.84% (v/v), respectively.

Viability-PCR Allows Monitoring Yeast Population Dynamics in Mixed Fermentations Including Viable but Non-Culturable Yeasts - Navarro, Yurena; Torija-Martínez, María-Jesús; Mas, Albert; Beltran Casellas, Gemma (Foods, 2020)
The use of controlled mixed inocula of Saccharomyces cerevisiae and non-Saccharomyces yeasts is a common practice in winemaking, with Torulaspora delbrueckii, Lachancea thermotolerans and Metschnikowia pulcherrima being the most commonly used non-Saccharomyces species. Although S. cerevisiae is usually the dominant yeast at the end of mixed fermentations, some non-Saccharomyces species are also able to reach the late stages; such species may not grow in culture media, which is a status known as viable but non-culturable (VBNC). Thus, an accurate methodology to properly monitor viable yeast population dynamics during alcoholic fermentation is required to understand microbial interactions and the contribution of each species to the final product. Quantitative PCR (qPCR) has been found to be a good and sensitive method for determining the identity of the cell population, but it cannot distinguish the DNA from living and dead cells, which can overestimate the final population results. To address this shortcoming, viability dyes can be used to avoid the amplification and, therefore, the quantification of DNA from non-viable cells. In this study, we validated the use of PMAxx dye (an optimized version of propidium monoazide (PMA) dye) coupled with qPCR (PMAxx-qPCR), as a tool to monitor the viable population dynamics of the most common yeast species used in wine mixed fermentations (S. cerevisiae, T. delbrueckii, L. thermotolerans and M. pulcherrima), comparing the results with non-dyed qPCR and colony counting on differential medium. Our results showed that the PMAxx-qPCR assay used in this study is a reliable, specific and fast method for quantifying these four yeast species during the alcoholic fermentation process, being able to distinguish between living and dead yeast populations. Moreover, the entry into VBNC status was observed for the first time in L. thermotolerans and S. cerevisiae during alcoholic fermentation. Further studies are needed to unravel which compounds trigger this VBNC state during alcoholic fermentation in these species, which would help to better understand yeast interactions.

Nitrogen Preferences during Alcoholic Fermentation of Different Non-Saccharomyces Yeasts of Oenological Interest - Roca-Mesa, Helena; Sendra, Sonia; Mas, Albert; Beltran Casellas, Gemma; Torija-Martínez, María-Jesús (Microorganisms, 2020)
Non-Saccharomyces yeasts have long been considered spoilage microorganisms. Currently, oenological interest in those species is increasing, mostly due to their positive contribution to wine quality. In this work, the fermentative capacity and nitrogen consumption of several non-Saccharomyces wine yeast (Torulaspora delbrueckii, Lachancea thermotolerans, Starmerella bacillaris, Hanseniaspora uvarum, and Metschnikowia pulcherrima) were analyzed. For this purpose, synthetic must with three different nitrogen compositions was used: a mixture of amino acids and ammonium, only organic or inorganic nitrogen. The fermentation kinetics, nitrogen consumption, and yeast growth were measured over time. Our results showed that the good fermentative strains, T. delbrueckii and L. thermotolerans, had high similarities with Saccharomyces cerevisiae in terms of growth, fermentation profile, and nitrogen assimilation preferences, although L. thermotolerans presented an impaired behavior when only amino acids or ammonia were used, being strain-specific. M. pulcherrima was the non-Saccharomyces strain least affected by the nitrogen composition of the medium. The other two poor fermentative strains, H. uvarum and S. bacillaris, behaved similarly regarding amino acid uptake, which occurred earlier than that of the good fermentative species in the absence of ammonia. The results obtained in single non-Saccharomyces fermentations highlighted the importance of controlling nitrogen requirements of the wine yeasts, mainly in sequential fermentations, in order to manage a proper nitrogen supplementation, when needed.

Benchmark problems for dynamic modeling of intracellular processes - Hass, Helge; Loos, Carolin; Raimúndez-Álvarez, Elba; Timmer, Jens; Hasenauer, Jan; Kreutz, Clemens (Bioinformatics, 2019)

Testing the inferred transcription rates of a dynamic, gene network model in absolute units - Urquiza Garcia, Uriel; Millar, Andrew (2021)
The circadian clock coordinates plant physiology and development. Mathematical clock models have provided a rigorous framework to understand how the observed rhythms emerge from disparate, molecular processes. However, models of the plant clock have largely been built and tested against RNA timeseries data in arbitrary, relative units. This limits model transferability, refinement from biochemical data and applications in synthetic biology. Here, we incorporate absolute mass units into a detailed, gene circuit model of the clock in Arabidopsis thaliana. We re-interpret the established P2011 model, highlighting a transcriptional activator that overlaps the function of REVEILLE 8/LHY-CCA1-LIKE 5, and refactor dynamic equations for the Evening Complex. The U2020 model incorporates the repressive regulation of PRR genes, a key feature of the most detailed clock model F2014, without greatly increasing model complexity. We tested the experimental error distributions of qRT-PCR data calibrated for units of RNA transcripts/cell and of circadian period estimates, in order to link the models to data more appropriately. U2019 and U2020 models were constrained using these data types, recreating previously-described circadian behaviours with RNA metabolic processes in absolute units. To test their inferred rates, we estimated a distribution of observed, transcriptome-wide transcription rates (Plant Empirical Transcription Rates, PETR) in units of transcripts/cell/hour. The PETR distribution and the equivalent degradation rates indicated that the models’ predicted rates are biologically plausible, with individual exceptions. In addition to updated, explanatory models of the plant clock, this validation process represents an advance in biochemical realism for models of plant gene regulation.

Excision of mutagenic replication-blocking lesions suppresses cancer but promotes cytotoxicity and lethality in nitrosamine-exposed mice - Kay, Jennifer E.; Corrigan, Joshua J.; Armijo, Amanda L.; Nazari, Ilana S.; Kohale, Ishwar N.; Torous, Dorothea K.; Avlasevich, Svetlana L.; Croy, Robert G.; Wadduwage, Dushan N.; Carrasco, Sebastian E.; Dertinger, Stephen D.; White, Forest M.; et al. (Cell Reports, 2021)

Fermentative N-Methylanthranilate Production by Engineered Corynebacterium glutamicum - Walter, Tatjana; Al Medani, Nour; Burgardt, Arthur; cankar, Katarina; Ferrer, Lenny; Kerbs, Anastasia; Lee, Jin-Ho; Mindt, Melanie; Risse, Joe Max; Wendisch, Volker (Microorganisms, 2020)

Physiological Response of Corynebacterium glutamicum to Indole - Walter, Tatjana; Veldmann, Kareen H.; Götker, Susanne; Busche, Tobias; Rückert, Christian; Kashkooli, Arman Beyraghdar; Paulus, Jannik; cankar, Katarina; Wendisch, Volker (Microorganisms, 2020)

The chemical defensome of five model teleost fish - Eide, Marta; Zhang, Xiaokang; Karlsen, Odd André; Goldstone, Jared V.; Stegeman, John; Jonassen, Inge; Goksøyr, Anders (Scientific Reports, 2021)
How an organism copes with chemicals is largely determined by the genes and proteins that collectively function to defend against, detoxify and eliminate chemical stressors. This integrative network includes receptors and transcription factors, biotransformation enzymes, transporters, antioxidants, and metal- and heat-responsive genes, and is collectively known as the chemical defensome. Teleost fish is the largest group of vertebrate species and can provide valuable insights into the evolution and functional diversity of defensome genes. We have previously shown that the xenosensing pregnane x receptor (pxr, nr1i2) is lost in many teleost species, including Atlantic cod (Gadus morhua) and three-spined stickleback (Gasterosteus aculeatus), but it is not known if compensatory mechanisms or signaling pathways have evolved in its absence. In this study, we compared the genes comprising the chemical defensome of five fish species that span the teleosteii evolutionary branch often used as model species in toxicological studies and environmental monitoring programs: zebrafish (Danio rerio), medaka (Oryzias latipes), Atlantic killifish (Fundulus heteroclitus), Atlantic cod, and three-spined stickleback. Genome mining revealed evolved differences in the number and composition of defensome genes that can have implication for how these species sense and respond to environmental pollutants, but we did not observe any candidates of compensatory mechanisms or pathways in cod and stickleback in the absence of pxr. The results indicate that knowledge regarding the diversity and function of the defensome will be important for toxicological testing and risk assessment studies.

ReCodLiver0.9: Overcoming Challenges in Genome-Scale Metabolic Reconstruction of a Non-model Species - Hanna, Eileen Marie; Zhang, Xiaokang; Eide, Marta; Fallahi, Shirin; Furmanek, Tomasz; Yadetie, Fekadu; Zielinski, Tomasz; Goksøyr, Anders; Jonassen, Inge (Frontiers in Molecular Biosciences, 2020)
The availability of genome sequences, annotations, and knowledge of the biochemistry underlying metabolic transformations has led to the generation of metabolic network reconstructions for a wide range of organisms in bacteria, archaea, and eukaryotes. When modeled using mathematical representations, a reconstruction can simulate underlying genotype-phenotype relationships. Accordingly, genome-scale metabolic models (GEMs) can be used to predict the response of organisms to genetic and environmental variations. A bottom-up reconstruction procedure typically starts by generating a draft model from existing annotation data on a target organism. For model species, this part of the process can be straightforward, due to the abundant organism-specific biochemical data. However, the process becomes complicated for non-model less-annotated species. In this paper, we present a draft liver reconstruction, ReCodLiver0.9, of Atlantic cod (Gadus morhua), a non-model teleost fish, as a practicable guide for cases with comparably few resources. Although the reconstruction is considered a draft version, we show that it already has utility in elucidating metabolic response mechanisms to environmental toxicants by mapping gene expression data of exposure experiments to the resulting model.

Digitoxin metabolism by rat liver microsomes. - Schmoldt, A.; Benthe, H. F.; Haberland, G. (Biochem Pharmacol, 1975)
Keywords: Animals; Chromatography, Thin Layer; Digitoxigenin/metabolism; Digitoxin/*metabolism; Hydroxylation; In Vitro Techniques; Male; Microsomes, Liver/*metabolism; NADP/metabolism; Rats; Time Factors

Effects of Agricultural Pesticides in Aquafeeds on Wild Fish Feeding on Leftover Pellets Near Fish Farms - Olsvik, Pål A.; Larsen, Anett Kristin; Berntssen, Marc H. G.; Goksøyr, Anders; Karlsen, Odd André; Yadetie, Fekadu; Sanden, Monica; Kristensen, Torstein (Frontiers in Genetics, 2019)
Screening has revealed that modern-day feeds used in Atlantic salmon aquaculture might contain trace amounts of agricultural pesticides. To reach slaughter size, salmon are produced in open net pens in the sea. Uneaten feed pellets and undigested feces deposited beneath the net pens represent a source of contamination for marine organisms. To examine the impacts of long-term and continuous dietary exposure to an organophosphorus pesticide found in Atlantic salmon feed, we fed juvenile Atlantic cod (Gadus morhua), an abundant species around North Atlantic fish farms, three concentrations (0.5, 4.2, and 23.2 mg/kg) of chlorpyrifos-methyl (CPM) for 30 days. Endpoints included liver and bile bioaccumulation, liver transcriptomics and metabolomics, as well as plasma cholinesterase activity, cortisol, liver 7-ethoxyresor-ufin-O-deethylase activity, and hypoxia tolerance. The results show that Atlantic cod can accumulate relatively high levels of CPM in liver after continuous exposure, which is then metabolized and excreted via the bile. All three exposure concentrations lead to significant inhibition of plasma cholinesterase activity, the primary target of CPM. Transcriptomics profiling pointed to effects on cholesterol and steroid biosynthesis. Metabolite profiling revealed that CPM induced responses reflecting detoxification by glutathione-S-transferase, inhibition of monoacylglycerol lipase, potential inhibition of carboxylesterase, and increased demand for ATP, followed by secondary inflammatory responses. A gradual hypoxia challenge test showed that all groups of exposed fish were less tolerant to low oxygen saturation than the controls. In conclusion, this study suggests that wild fish continuously feeding on leftover pellets near fish farms over time may be vulnerable to organophosphorus pesticides.

Regulatory phosphorylation site tunes Phosphoglucomutase 1 as a metabolic valve to control mobilization of glycogen stores - Doello, Sofia; Neumann, Niels; Spät, Philipp; Maček, Boris; Forchhammer, Karl (2021)
Regulation of glycogen metabolism is of vital importance in organisms of all three kingdoms of life. Although the pathways involved in glycogen synthesis and degradation are well known, many regulatory aspects around the metabolism of this polysaccharide remain undeciphered. Here, we used the unicellular cyanobacterium Synechocystis as a model to investigate how glycogen metabolism is regulated in dormant nitrogen-starved cells, which entirely rely on glycogen catabolism to restore growth. We found that the activity of the enzymes involved in glycogen synthesis and degradation is tightly controlled at different levels via post-translational modifications. Phosphorylation of phosphoglucomutase 1 (Pgm1) on a peripheral residue (Ser63) regulates Pgm1 activity and controls the mobilization of the glycogen stores. Inhibition of Pgm1 activity via phosphorylation on Ser63 appears essential for survival of Synechocystis in the dormant state. Remarkably, this regulatory mechanism seems to be conserved from bacteria to humans. Moreover, phosphorylation of Pgm1 influences the formation of a metabolon, which includes Pgm1, oxidative pentose phosphate cycle protein (OpcA) and glucose-6-phosphate dehydrogenase (G6PDH). Analysis of the steady-state levels of the metabolic products of glycogen degradation together with protein-protein interaction studies revealed that the activity of G6PDH and the formation of this metabolon are under additional redox control, likely to ensure metabolic channeling of glucose-6-phosphate to the required pathways for each developmental stage.

Rethinking Transcriptional Activation in the Arabidopsis Circadian Clock - Fogelmark, Karl; Troein, Carl (PLoS Computational Biology, 2014)

Testing the inferred transcription rates of a dynamic, gene network model in absolute units (in silico Plants 2021) - Urquiza Garcia, Uriel; Millar, Andrew (in silico Plants, 2021)
The circadian clock coordinates plant physiology and development. Mathematical clock models have provided a rigorous framework to understand how the observed rhythms emerge from disparate, molecular processes. However, models of the plant clock have largely been built and tested against RNA timeseries data in arbitrary, relative units. This limits model transferability, refinement from biochemical data and applications in synthetic biology. Here, we incorporate absolute mass units into a detailed model of the clock gene network in Arabidopsis thaliana. We re-interpret the established P2011 model, highlighting a transcriptional activator that overlaps the function of REVEILLE 8/LHY-CCA1-LIKE 5. The U2020 model incorporates the repressive regulation of PRR genes, a key feature of the most detailed clock model KF2014, without greatly increasing model complexity. We tested the experimental error distributions of qRT-PCR data calibrated for units of RNA transcripts/cell and of circadian period estimates, in order to link the models to data more appropriately. U2019 and U2020 models were constrained using these data types, recreating previously-described circadian behaviours with RNA metabolic processes in absolute units. To test their inferred rates, we estimated a distribution of observed, transcriptome-wide transcription rates (Plant Empirical Transcription Rates, PETR) in units of transcripts/cell/hour. The PETR distribution and the equivalent degradation rates indicated that the models’ predicted rates are biologically plausible, with individual exceptions. In addition to updated clock models, FAIR data resources and a software environment in Docker, this validation process represents an advance in biochemical realism for models of plant gene regulation.

Conceptual and computational framework for logical modelling of biological networks deregulated in diseases. - Montagud, A.; Traynard, P.; Martignetti, L.; Bonnet, E.; Barillot, E.; Zinovyev, A.; Calzone, L. (Brief Bioinform, 2019)
Mathematical models can serve as a tool to formalize biological knowledge from diverse sources, to investigate biological questions in a formal way, to test experimental hypotheses, to predict the effect of perturbations and to identify underlying mechanisms. We present a pipeline of computational tools that performs a series of analyses to explore a logical model's properties. A logical model of initiation of the metastatic process in cancer is used as a transversal example. We start by analysing the structure of the interaction network constructed from the literature or existing databases. Next, we show how to translate this network into a mathematical object, specifically a logical model, and how robustness analyses can be applied to it. We explore the visualization of the stable states, defined as specific attractors of the model, and match them to cellular fates or biological read-outs. With the different tools we present here, we explain how to assign to each solution of the model a probability and how to identify genetic interactions using mutant phenotype probabilities. Finally, we connect the model to relevant experimental data: we present how some data analyses can direct the construction of the network, and how the solutions of a mathematical model can also be compared with experimental data, with a particular focus on high-throughput data in cancer biology. A step-by-step tutorial is provided as a Supplementary Material and all models, tools and scripts are provided on an accompanying website: https://github.com/sysbio-curie/Logical_modelling_pipeline.
Keywords: Computational Biology/methods; Computer Simulation; Databases, Factual; Disease; Epistasis, Genetic; Gene Regulatory Networks; Humans; Logistic Models; Mathematical Concepts; Metabolic Networks and Pathways; *Models, Biological; Mutation; Neoplasm Metastasis/genetics/pathology/physiopathology; *Signal Transduction; Software; Systems Biology/statistics & numerical data

PhysiBoSS: a multi-scale agent-based modelling framework integrating physical dimension and cell signalling - Letort, Gaelle; Montagud, Arnau; Stoll, Gautier; Heiland, Randy; Barillot, Emmanuel; Macklin, Paul; Zinovyev, Andrei; Calzone, Laurence (Bioinformatics, 2019)

Continuous time Boolean modeling for biological signaling: application of Gillespie algorithm. - Stoll, G.; Viara, E.; Barillot, E.; Calzone, L. (BMC Syst Biol, 2012)
Mathematical modeling is used as a Systems Biology tool to answer biological questions, and more precisely, to validate a network that describes biological observations and predict the effect of perturbations. This article presents an algorithm for modeling biological networks in a discrete framework with continuous time. BACKGROUND: There exist two major types of mathematical modeling approaches: (1) quantitative modeling, representing various chemical species concentrations by real numbers, mainly based on differential equations and chemical kinetics formalism; (2) and qualitative modeling, representing chemical species concentrations or activities by a finite set of discrete values. Both approaches answer particular (and often different) biological questions. Qualitative modeling approach permits a simple and less detailed description of the biological systems, efficiently describes stable state identification but remains inconvenient in describing the transient kinetics leading to these states. In this context, time is represented by discrete steps. Quantitative modeling, on the other hand, can describe more accurately the dynamical behavior of biological processes as it follows the evolution of concentration or activities of chemical species as a function of time, but requires an important amount of information on the parameters difficult to find in the literature. RESULTS: Here, we propose a modeling framework based on a qualitative approach that is intrinsically continuous in time. The algorithm presented in this article fills the gap between qualitative and quantitative modeling. It is based on continuous time Markov process applied on a Boolean state space. In order to describe the temporal evolution of the biological process we wish to model, we explicitly specify the transition rates for each node. For that purpose, we built a language that can be seen as a generalization of Boolean equations. Mathematically, this approach can be translated in a set of ordinary differential equations on probability distributions. We developed a C++ software, MaBoSS, that is able to simulate such a system by applying Kinetic Monte-Carlo (or Gillespie algorithm) on the Boolean state space. This software, parallelized and optimized, computes the temporal evolution of probability distributions and estimates stationary distributions. CONCLUSIONS: Applications of the Boolean Kinetic Monte-Carlo are demonstrated for three qualitative models: a toy model, a published model of p53/Mdm2 interaction and a published model of the mammalian cell cycle. Our approach allows to describe kinetic phenomena which were difficult to handle in the original models. In particular, transient effects are represented by time dependent probability distributions, interpretable in terms of cell populations.
Keywords: *Algorithms; Animals; Cell Cycle; Markov Chains; *Models, Biological; *Monte Carlo Method; Proto-Oncogene Proteins c-mdm2/metabolism; *Signal Transduction; Time Factors; Tumor Suppressor Protein p53/metabolism

MaBoSS 2.0: an environment for stochastic Boolean modeling. - Stoll, G.; Caron, B.; Viara, E.; Dugourd, A.; Zinovyev, A.; Naldi, A.; Kroemer, G.; Barillot, E.; Calzone, L. (Bioinformatics, 2017)
MOTIVATION: Modeling of signaling pathways is an important step towards the understanding and the treatment of diseases such as cancers, HIV or auto-immune diseases. MaBoSS is a software that allows to simulate populations of cells and to model stochastically the intracellular mechanisms that are deregulated in diseases. MaBoSS provides an output of a Boolean model in the form of time-dependent probabilities, for all biological entities (genes, proteins, phenotypes, etc.) of the model. RESULTS: We present a new version of MaBoSS (2.0), including an updated version of the core software and an environment. With this environment, the needs for modeling signaling pathways are facilitated, including model construction, visualization, simulations of mutations, drug treatments and sensitivity analyses. It offers a framework for automated production of theoretical predictions. AVAILABILITY AND IMPLEMENTATION: MaBoSS software can be found at https://maboss.curie.fr , including tutorials on existing models and examples of models. CONTACT: gautier.stoll@upmc.fr or laurence.calzone@curie.fr. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Computational Biology/*methods; *Computer Simulation; *Models, Biological; *Signal Transduction; *Software

Iterative community-driven development of a SARS-CoV-2 tissue simulator - Getz, Michael; Wang, Yafei; An, Gary; Asthana, Maansi; Becker, Andrew; Cockrell, Chase; Collier, Nicholson; Craig, Morgan; Davis, Courtney L.; Faeder, James R.; Ford Versypt, Ashlee N.; Mapder, Tarunendu; et al. (2020)

Automated inference of Boolean models from molecular interaction maps using CaSQ - Aghamiri, Sara Sadat; Singh, Vidisha; Naldi, Aurélien; Helikar, Tomáš; Soliman, Sylvain; Niarakis, Anna (Bioinformatics, 2020)

Quality control in scRNA-Seq can discriminate pacemaker cells: the mtRNA bias. - Galow, A. M.; Kussauer, S.; Wolfien, M.; Brunner, R. M.; Goldammer, T.; David, R.; Hoeflich, A. (Cell Mol Life Sci, 2021)
Single-cell RNA-sequencing (scRNA-seq) provides high-resolution insights into complex tissues. Cardiac tissue, however, poses a major challenge due to the delicate isolation process and the large size of mature cardiomyocytes. Regardless of the experimental technique, captured cells are often impaired and some capture sites may contain multiple or no cells at all. All this refers to "low quality" potentially leading to data misinterpretation. Common standard quality control parameters involve the number of detected genes, transcripts per cell, and the fraction of transcripts from mitochondrial genes. While cutoffs for transcripts and genes per cell are usually user-defined for each experiment or individually calculated, a fixed threshold of 5% mitochondrial transcripts is standard and often set as default in scRNA-seq software. However, this parameter is highly dependent on the tissue type. In the heart, mitochondrial transcripts comprise almost 30% of total mRNA due to high energy demands. Here, we demonstrate that a 5%-threshold not only causes an unacceptable exclusion of cardiomyocytes but also introduces a bias that particularly discriminates pacemaker cells. This effect is apparent for our in vitro generated induced-sinoatrial-bodies (iSABs; highly enriched physiologically functional pacemaker cells), and also evident in a public data set of cells isolated from embryonal murine sinoatrial node tissue (Goodyer William et al. in Circ Res 125:379-397, 2019). Taken together, we recommend omitting this filtering parameter for scRNA-seq in cardiovascular applications whenever possible.
Keywords: Animals; Cluster Analysis; Gene Expression Profiling/methods; Humans; Mice; Myocytes, Cardiac/physiology; Quality Control; RNA, Messenger/genetics; RNA, Mitochondrial/*genetics; RNA, Small Cytoplasmic/*genetics; Sequence Analysis, RNA; Single-Cell Analysis/*methods; Software; Exome Sequencing/methods

Virus structure and structure-based antivirals - Plavec, Zlatka; Poehner, Ina; Poso, Antti; Butcher, Sarah J (Current Opinion in Virology, 2021)
Structure-based antiviral developments in the past two years have been dominated by the structure determination and inhibition of SARS-CoV-2 proteins and new lead molecules for picornaviruses. The SARS-CoV-2 spike protein has been targeted successfully with antibodies, nanobodies, and receptor protein mimics effectively blocking receptor binding or fusion. The two most promising non-structural proteins sharing strong structural and functional conservation across virus families are the main protease and the RNA-dependent RNA polymerase, for which design and reuse of broad range inhibitors already approved for use has been an attractive avenue. For picornaviruses, the increasing recognition of the transient expansion of the capsid as a critical transition towards RNA release has been targeted through a newly identified, apparently widely conserved, druggable, interprotomer pocket preventing viral entry. We summarize some of the key papers in these areas and ponder the practical uses and contributions of molecular modeling alongside empirical structure determination.

Toward Reproducible Enzyme Modeling with Isothermal Titration Calorimetry - Ott, Felix; Rabe, Kersten S.; Niemeyer, Christof M.; Gygli, Gudrun (ACS Catalysis, 2021)
To apply enzymes in technical processes, a detailed understanding of the molecular mechanisms is required. Kinetic and thermodynamic parameters of enzyme catalysis are crucial to plan, model, and implement biocatalytic processes more efficiently. While the kinetic parameters, Km and kcat, are often accessible by optical methods, the determination of thermodynamic parameters requires more sophisticated methods. Isothermal titration calorimetry (ITC) allows the label-free and highly sensitive analysis of kinetic and thermodynamic parameters of individual steps in the catalytic cycle of an enzyme reaction. However, since ITC is susceptible to interferences due to denaturation or agglomeration of the enzymes, the homogeneity of the enzyme sample must always be considered, and this can be accomplished by means of dynamic light scattering (DLS) analysis. We here report on the use of an ITC-dependent work flow to determine both the kinetic and the thermodynamic data for a cofactor-dependent enzyme. Using a standardized approach with the implementation of sample quality control by DLS, we obtain high-quality data suitable for the advanced modeling of the enzyme reaction mechanism. Specifically, we investigated stereoselective reactions catalyzed by the NADPH-dependent ketoreductase Gre2p under different reaction conditions. The results revealed that this enzyme operates with an ordered sequential mechanism and is affected by substrate or product inhibition depending on the reaction buffer. Data reproducibility is ensured by specifying standard operating procedures, using programmed workflows for data analysis, and storing all data in a F.A.I.R. (findable, accessible, interoperable, and reusable) repository (https://doi.org/10.15490/fairdomhub.1.investigation.464.1). Our work highlights the utility for combined binding and kinetic studies for such complex multisubstrate reactions.

Simulation Foundry: Automated and F.A.I.R. Molecular Modeling - Gygli, Gudrun; Pleiss, Juergen (Journal of Chemical Information and Modeling, 2020)
The Simulation Foundry (SF) is a modular workflow for the automated creation of molecular modeling (MM) data. MM allows for the reliable prediction of the microscopic and macroscopic properties of multicomponent systems from first principles. The SF makes MM repeatable, replicable, and findable, accessible, interoperable, and reusable (F.A.I.R.). The SF uses a standardized data structure and file naming convention, allowing for replication on different supercomputers and re-entrancy. We focus on keeping the SF simple by basing it on scripting languages that are widely used by the MM community (bash, Python) and making it reusable and re-editable. The SF was developed to assist expert users in performing parameter studies of multicomponent systems by high throughput molecular dynamics simulations. The usability of the SF is demonstrated by simulations of thermophysical properties of binary mixtures. A standardized data exchange format enables the integration of simulated data with data from experiments. The SF also provides a complete documentation of how the results were obtained, thus assigning provenance. Increasing computational power facilitates the intensification of the simulation process and requires automation and modularity. The SF provides a community platform on which to integrate new methods and create data that is reproducible and transparent (https://fairdomhub.org/studies/639/snapshots/1, https://fairdomhub.org/studies/639/snapshots/2).

COVID19 Disease Map, a computational knowledge repository of virus-host interaction mechanisms. - Ostaszewski, M.; Niarakis, A.; Mazein, A.; Kuperstein, I.; Phair, R.; Orta-Resendiz, A.; Singh, V.; Aghamiri, S. S.; Acencio, M. L.; Glaab, E.; Ruepp, A.; Fobo, G.; et al. (Mol Syst Biol, 2021)
We need to effectively combine the knowledge from surging literature with complex datasets to propose mechanistic models of SARS-CoV-2 infection, improving data interpretation and predicting key targets of intervention. Here, we describe a large-scale community effort to build an open access, interoperable and computable repository of COVID-19 molecular mechanisms. The COVID-19 Disease Map (C19DMap) is a graphical, interactive representation of disease-relevant molecular mechanisms linking many knowledge sources. Notably, it is a computational resource for graph-based analyses and disease modelling. To this end, we established a framework of tools, platforms and guidelines necessary for a multifaceted community of biocurators, domain experts, bioinformaticians and computational biologists. The diagrams of the C19DMap, curated from the literature, are integrated with relevant interaction and text mining databases. We demonstrate the application of network analysis and modelling approaches by concrete examples to highlight new testable hypotheses. This framework helps to find signatures of SARS-CoV-2 predisposition, treatment response or prioritisation of drug candidates. Such an approach may help deal with new waves of COVID-19 or similar pandemics in the long-term perspective.
Keywords: Antiviral Agents/therapeutic use; COVID-19/genetics/*immunology/virology; Computational Biology/*methods; Computer Graphics; Cytokines/genetics/immunology; Data Mining/statistics & numerical data; *Databases, Factual; Gene Expression Regulation; Host Microbial Interactions/genetics/immunology; Humans; Immunity, Cellular/drug effects; Immunity, Humoral/drug effects; Immunity, Innate/drug effects; Lymphocytes/drug effects/immunology/virology; Metabolic Networks and Pathways/genetics/immunology; Myeloid Cells/drug effects/immunology/virology; Protein Interaction Mapping; SARS-CoV-2/drug effects/genetics/*immunology/pathogenicity; Signal Transduction; *Software; Transcription Factors/genetics/immunology; Viral Proteins/genetics/immunology; COVID-19 Drug Treatment

COVID19 Disease Map, a computational knowledge repository of virus–host interaction mechanisms - Ostaszewski, Marek; Niarakis, Anna; Mazein, Alexander; Kuperstein, Inna; Phair, Robert; Orta‐Resendiz, Aurelio; Singh, Vidisha; AGHAMIRI, Sara Sadat; Acencio, Marcio; Glaab, Enrico; Ruepp, Andreas; Fobo, Gisela; et al. (Molecular Systems Biology, 2021)

SARS‐CoV‐2–host proteome interactions for antiviral drug discovery - Liu, Xiaonan; Huuskonen, Sini; Laitinen, Tuomo; Redchuk, Taras; Bogacheva, Mariia; Salokas, Kari; Poehner, Ina; Öhman, Tiina; Tonduru, Arun Kumar; Hassinen, Antti; Gawriyski, Lisa; Keskitalo, Salla; et al. (Molecular Systems Biology, 2021)
Treatment options for COVID-19, caused by SARS-CoV-2, remain limited. Understanding viral pathogenesis at the molecular level is critical to develop effective therapy. Some recent studies have explored SARS-CoV-2–host interactomes and provided great resources for understanding viral replication. However, host proteins that functionally associate with SARS-CoV-2 are localized in the corresponding subnetwork within the comprehensive human interactome. Therefore, constructing a downstream network including all potential viral receptors, host cell proteases, and cofactors is necessary and should be used as an additional criterion for the validation of critical host machineries used for viral processing. This study applied both affinity purification mass spectrometry (AP-MS) and the complementary proximity-based labeling MS method (BioID-MS) on 29 viral ORFs and 18 host proteins with potential roles in viral replication to map the interactions relevant to viral processing. The analysis yields a list of 693 hub proteins sharing interactions with both viral baits and host baits and revealed their biological significance for SARS-CoV-2. Those hub proteins then served as a rational resource for drug repurposing via a virtual screening approach. The overall process resulted in the suggested repurposing of 59 compounds for 15 protein targets. Furthermore, antiviral effects of some candidate drugs were observed in vitro validation using image-based drug screen with infectious SARS-CoV-2. In addition, our results suggest that the antiviral activity of methotrexate could be associated with its inhibitory effect on specific protein-protein interactions.

Educational reconstruction of size-depended-properties in nanotechnology for teaching in tertiary education - Metaxas, Ioannis; Michailidi, Emily; Stavrou, Dimitris; Pavlidis, Ioannis (Chemistry Teacher International, 2021)
There is an overarching theme in Science Education to integrate in the school and university curriculum interdisciplinary state-of-art innovations. The field of Nanotechnology is such an example, because it combines the aforementioned interdisciplinarity and novelty with a well-documented educational value. Herein, a novel teaching approach concerning size-dependent properties at the nanoscale for chemistry and physics undergraduate students is proposed. The analysis of the scientific content and its following reconstruction for teaching purposes is based on the theoretical framework of the Model of Educational Reconstruction (MER). This analysis yielded two fundamental concepts and a series of activities that can be the main core of teaching Nanotechnology at a university level.

Rational engineering of Luminiphilus syltensis ( R )-selective amine transaminase for the acceptance of bulky substrates - Konia, Eleni; Chatzicharalampous, Konstantinos; Drakonaki, Athina; Muenke, Cornelia; Ermler, Ulrich; Tsiotis, Georgios; Pavlidis, Ioannis (Chemical Communications, 2021)
Despite the plethora of information on (S)-selective amine transaminases, the (R)-selective ones are still not well-studied; only a few structures are known to the day, and their substrate scope is limited, apart from a few stellar works on the field. Herein, Luminiphilus syltensis (R)-selective amine transaminase’s structure was elucidated to facilitate the engineering towards variants active on bulkier substrates. V37A variant led to increased activity towards 1-phenylpropylamine and to activity against 1-butylamine. On the contrary, S248 and T249 positions, located on the β-turn in P-pocket, seem crucial for maintaining enzyme’s activity.

Hypoxia Routes Tryptophan Homeostasis Towards Increased Tryptamine Production. - Mohapatra, S. R.; Sadik, A.; Sharma, S.; Poschet, G.; Gegner, H. M.; Lanz, T. V.; Lucarelli, P.; Klingmuller, U.; Platten, M.; Heiland, I.; Opitz, C. A. (Front Immunol, 2021)
The liver is the central hub for processing and maintaining homeostatic levels of dietary nutrients especially essential amino acids such as tryptophan (Trp). Trp is required not only to sustain protein synthesis but also as a precursor for the production of NAD, neurotransmitters and immunosuppressive metabolites. In light of these roles of Trp and its metabolic products, maintaining homeostatic levels of Trp is essential for health and well-being. The liver regulates global Trp supply by the immunosuppressive enzyme tryptophan-2,3-dioxygenase (TDO2), which degrades Trp down the kynurenine pathway (KP). In the current study, we show that isolated primary hepatocytes when exposed to hypoxic environments, extensively rewire their Trp metabolism by reducing constitutive Tdo2 expression and differentially regulating other Trp pathway enzymes and transporters. Mathematical modelling of Trp metabolism in liver cells under hypoxia predicted decreased flux through the KP while metabolic flux through the tryptamine branch significantly increased. In line, the model also revealed an increased accumulation of tryptamines under hypoxia, at the expense of kynurenines. Metabolic measurements in hypoxic hepatocytes confirmed the predicted reduction in KP metabolites as well as accumulation of tryptamine. Tdo2 expression in cultured primary hepatocytes was reduced upon hypoxia inducible factor (HIF) stabilisation by dimethyloxalylglycine (DMOG), demonstrating that HIFs are involved in the hypoxic downregulation of hepatic Tdo2. DMOG abrogated hepatic luciferase signals in Tdo2 reporter mice, indicating that HIF stability also recapitulates hypoxic rewiring of Trp metabolism in vivo. Also in WT mice HIF stabilization drove homeostatic Trp metabolism away from the KP towards enhanced tryptamine production, leading to enhanced levels of tryptamine in liver, serum and brain. As tryptamines are the most potent hallucinogens known, the observed upregulation of tryptamine in response to hypoxic exposure of hepatocytes may be involved in the generation of hallucinations occurring at high altitude. KP metabolites are known to activate the aryl hydrocarbon receptor (AHR). The AHR-activating properties of tryptamines may explain why immunosuppressive AHR activity is maintained under hypoxia despite downregulation of the KP. In summary our results identify hypoxia as an important factor controlling Trp metabolism in the liver with possible implications for immunosuppressive AHR activation and mental disturbances.
Keywords: Animals; Computational Biology/methods; Energy Metabolism; Gene Expression Profiling; Gene Expression Regulation; Hepatocytes/metabolism; *Homeostasis; Hypoxia/genetics/*metabolism; Indoleamine-Pyrrole 2,3,-Dioxygenase/genetics/metabolism; Liver/metabolism; Mice; Models, Biological; Oxygen/metabolism; Tryptamines/*metabolism; Tryptophan/*metabolism

Identification of evolutionary and kinetic drivers of NAD-dependent signaling - Bockwoldt, Mathias; Houry, Dorothee; Niere, Marc; Gossmann, Toni I.; Reinartz, Ines; Schug, Alexander; Ziegler, Mathias; Heiland, Ines (Proceedings of the National Academy of Sciences, 2019)

Welcome to the Family: Identification of the NAD(+) Transporter of Animal Mitochondria as Member of the Solute Carrier Family SLC25. - Ziegler, M.; Monne, M.; Nikiforov, A.; Agrimi, G.; Heiland, I.; Palmieri, F. (Biomolecules, 2021)
Subcellular compartmentation is a fundamental property of eukaryotic cells. Communication and metabolic and regulatory interconnectivity between organelles require that solutes can be transported across their surrounding membranes. Indeed, in mammals, there are hundreds of genes encoding solute carriers (SLCs) which mediate the selective transport of molecules such as nucleotides, amino acids, and sugars across biological membranes. Research over many years has identified the localization and preferred substrates of a large variety of SLCs. Of particular interest has been the SLC25 family, which includes carriers embedded in the inner membrane of mitochondria to secure the supply of these organelles with major metabolic intermediates and coenzymes. The substrate specificity of many of these carriers has been established in the past. However, the route by which animal mitochondria are supplied with NAD(+) had long remained obscure. Only just recently, the existence of a human mitochondrial NAD(+) carrier was firmly established. With the realization that SLC25A51 (or MCART1) represents the major mitochondrial NAD(+) carrier in mammals, a long-standing mystery in NAD(+) biology has been resolved. Here, we summarize the functional importance and structural features of this carrier as well as the key observations leading to its discovery.
Keywords: Biological Transport/genetics; Humans; Mitochondria/genetics/*metabolism; Mitochondrial Membrane Transport Proteins/genetics/*metabolism; NAD/genetics/*metabolism; Solute Carrier Proteins/genetics/*metabolism

Combining dictionary- and rule-based approximate entity linking with tuned BioBERT - Mobasher, Ghadeer; Mertová, Lukrécia; Ghosh, Sucheta; Krebs, Olga; Heinlein, Bettina; Müller, Wolfgang (2021)
Chemical named entity recognition (NER) is a significant step for many downstream applications like entity linking for the chemical text-mining pipeline. However, the identification of chemical entities in a biomedical text is a challenging task due to the diverse morphology of chemical entities and the different types of chemical nomenclature. In this work, we describe our approach that was submitted for BioCreative version 7 challenge Track 2, focusing on the ‘Chemical Identification’ task for identifying chemical entities and entity linking, using MeSH. For this purpose, we have applied a two-stage approach as follows (a) usage of fine-tuned BioBERT for identification of chemical entities (b) semantic approximate search in MeSH and PubChem databases for entity linking. There was some friction between the two approaches, as our rule-based approach did not harmonise optimally with partially recognized words forwarded by the BERT component. For our future work, we aim to resolve the issue of the artefacts arising from BERT tokenizers and develop joint learning of chemical named entity recognition and entity linking using pre-trained transformer-based models and compare their performance with our preliminary approach. Next, we will improve the efficiency of our approximate search in reference databases during entity linking. This task is non-trivial as it entails determining similarity scores of large sets of trees with respect to a query tree. Ideally, this will enable flexible parametrization and rule selection for the entity linking search.

A network-based approach reveals the dysregulated transcriptional regulation in non-alcoholic fatty liver disease. - Yang, H.; Arif, M.; Yuan, M.; Li, X.; Shong, K.; Turkez, H.; Nielsen, J.; Uhlen, M.; Boren, J.; Zhang, C.; Mardinoglu, A. (iScience, 2021)
Non-alcoholic fatty liver disease (NAFLD) is a leading cause of chronic liver disease worldwide. We performed network analysis to investigate the dysregulated biological processes in the disease progression and revealed the molecular mechanism underlying NAFLD. Based on network analysis, we identified a highly conserved disease-associated gene module across three different NAFLD cohorts and highlighted the predominant role of key transcriptional regulators associated with lipid and cholesterol metabolism. In addition, we revealed the detailed metabolic differences between heterogeneous NAFLD patients through integrative systems analysis of transcriptomic data and liver-specific genome-scale metabolic model. Furthermore, we identified transcription factors (TFs), including SREBF2, HNF4A, SREBF1, YY1, and KLF13, showing regulation of hepatic expression of genes in the NAFLD-associated modules and validated the TFs using data generated from a mouse NAFLD model. In conclusion, our integrative analysis facilitates the understanding of the regulatory mechanism of these perturbed TFs and their associated biological processes.

Genome-scale metabolic modelling of hepatocytes reveals serine deficiency in patients with non-alcoholic fatty liver disease. - Mardinoglu, A.; Agren, R.; Kampf, C.; Asplund, A.; Uhlen, M.; Nielsen, J. (Nat Commun, 2014)
Several liver disorders result from perturbations in the metabolism of hepatocytes, and their underlying mechanisms can be outlined through the use of genome-scale metabolic models (GEMs). Here we reconstruct a consensus GEM for hepatocytes, which we call iHepatocytes2322, that extends previous models by including an extensive description of lipid metabolism. We build iHepatocytes2322 using Human Metabolic Reaction 2.0 database and proteomics data in Human Protein Atlas, which experimentally validates the incorporated reactions. The reconstruction process enables improved annotation of the proteomics data using the network centric view of iHepatocytes2322. We then use iHepatocytes2322 to analyse transcriptomics data obtained from patients with non-alcoholic fatty liver disease. We show that blood concentrations of chondroitin and heparan sulphates are suitable for diagnosing non-alcoholic steatohepatitis and for the staging of non-alcoholic fatty liver disease. Furthermore, we observe serine deficiency in patients with NASH and identify PSPH, SHMT1 and BCAT1 as potential therapeutic targets for the treatment of non-alcoholic steatohepatitis.
Keywords: Adolescent; Adult; Aged; Biomarkers/blood; Chondroitin/blood; Databases, Genetic; Female; Genome/*genetics; Glycine Hydroxymethyltransferase; Heparitin Sulfate/blood; Hepatocytes/*metabolism/pathology; Humans; Lipid Metabolism/genetics; Male; Middle Aged; *Models, Biological; *Models, Genetic; Non-alcoholic Fatty Liver Disease/*genetics/*metabolism/pathology; Phosphoserine; Serine/*deficiency; Transaminases; Transcriptome; Young Adult

Bistability in fatty-acid oxidation resulting from substrate inhibition. - Abegaz, F.; Martines, A. M. F.; Vieira-Lara, M. A.; Rios-Morales, M.; Reijngoud, D. J.; Wit, E. C.; Bakker, B. M. (PLoS Comput Biol, 2021)
In this study we demonstrated through analytic considerations and numerical studies that the mitochondrial fatty-acid beta-oxidation can exhibit bistable-hysteresis behavior. In an experimentally validated computational model we identified a specific region in the parameter space in which two distinct stable and one unstable steady state could be attained with different fluxes. The two stable states were referred to as low-flux (disease) and high-flux (healthy) state. By a modular kinetic approach we traced the origin and causes of the bistability back to the distributive kinetics and the conservation of CoA, in particular in the last rounds of the beta-oxidation. We then extended the model to investigate various interventions that may confer health benefits by activating the pathway, including (i) activation of the last enzyme MCKAT via its endogenous regulator p46-SHC protein, (ii) addition of a thioesterase (an acyl-CoA hydrolysing enzyme) as a safety valve, and (iii) concomitant activation of a number of upstream and downstream enzymes by short-chain fatty-acids (SCFA), metabolites that are produced from nutritional fibers in the gut. A high concentration of SCFAs, thioesterase activity, and inhibition of the p46Shc protein led to a disappearance of the bistability, leaving only the high-flux state. A better understanding of the switch behavior of the mitochondrial fatty-acid oxidation process between a low- and a high-flux state may lead to dietary and pharmacological intervention in the treatment or prevention of obesity and or non-alcoholic fatty-liver disease.
Keywords: Acetyl-CoA C-Acyltransferase/antagonists & inhibitors/metabolism; Animals; Computational Biology; Computer Simulation; Enzyme Stability; Fatty Acids/chemistry/*metabolism; Humans; Kinetics; Metabolic Networks and Pathways; Mitochondria/metabolism; *Models, Biological; Non-alcoholic Fatty Liver Disease/etiology/metabolism; Obesity/etiology/metabolism

Effect of graphite oxide on the catalytic behavior of (S)-selective amine transaminases - Kaloudis, Nikolaos; Zygouri, Panagiota; Chalmpes, Nikolaos; Spyrou, Konstantinos; Gournis, Dimitrios; Pavlidis, Ioannis (Frontiers in Catalysis, 2021)
Graphite oxide (GO) has been used for the immobilization of several classes of enzymes, exhibiting very interesting properties as immobilization matrix. However, the effect the nanomaterial has on the enzyme cannot be predicted. Herein, the effect GO has on the catalytic behavior of several (S)-selective amine transaminases ((S)-ATAs) has been investigated. These enzymes were the focus of this work as they are homodimers with pyridoxal 5’-phosphate in their active site, significantly more complex systems than other enzymes previously studied. Addition of GO (up to 0.1 mg/mL) in the reaction medium leads to activation (up to 50% improved activity) for most enzymes studied, while they maintain their temperature profile (they perform better between 40-45ºC), and their stability. However, the effect is not universal and there are enzymes that are negatively influenced by the presence of the nanomaterial. More profound is the effect on the (S)-ATA from Chromobacterium violaceum which loses almost 50% of its activity in the presence of 0.1 mg/mL GO, while the stability was significantly decreased, losing its activity after 2 h incubation at 40°C, in the presence of 25 μg/mL GO. This negative effect seems to rise from minor secondary structure alterations; namely, a loss of α-helices and subsequent increase in random coil (~3% in the presence of 25 μg/mL GO). We hypothesize that the effect the GO has on (S)-ATAs is correlated to the surface chemistry of the enzymes; the less negatively-charged enzymes are deactivated from the interaction with GO. This insight will aid the rationalization of ATA immobilization onto carbon-based nanomaterials.

Natural isotope correction improves analysis of protein modification dynamics - Dietze, Jörn; van Pijkeren, Alienke; Egger, Anna-Sophia; Ziegler, Mathias; Kwiatkowski, Marcel; Heiland, Ines (Analytical and Bioanalytical Chemistry, 2021)
Abstract Stable isotope labelling in combination with high-resolution mass spectrometry approaches are increasingly used to analyze both metabolite and protein modification dynamics. To enable correct estimation of the resulting dynamics, it is critical to correct the measured values for naturally occurring stable isotopes, a process commonly called isotopologue correction or deconvolution. While the importance of isotopologue correction is well recognized in metabolomics, it has received far less attention in proteomics approaches. Although several tools exist that enable isotopologue correction of mass spectrometry data, the majority is tailored for the analysis of low molecular weight metabolites. We here present PICor which has been developed for isotopologue correction of complex isotope labelling experiments in proteomics or metabolomics and demonstrate the importance of appropriate correction for accurate determination of protein modifications dynamics, using histone acetylation as an example.

Partially non-homogeneous dynamic Bayesian networks based on Bayesian regression models with partitioned design matrices - Shafiee Kamalabad, Mahdi; Heberle, Alexander; Thedieck, Kathrin; Grzegorczyk, Marco (Bioinformatics, 2019)
Non-homogeneous dynamic Bayesian networks (NH-DBNs) are a popular modelling tool for learning cellular networks from time series data. In systems biology, time series are often measured under different experimental conditions, and not rarely only some network interaction parameters depend on the condition while the other parameters stay constant across conditions. For this situation, we propose a new partially NH-DBN, based on Bayesian hierarchical regression models with partitioned design matrices. With regard to our main application to semi-quantitative (immunoblot) timecourse data from mammalian target of rapamycin complex 1 (mTORC1) signalling, we also propose a Gaussian process-based method to solve the problem of non-equidistant time series measurements.

Black soldier fly larvae (BSFL) and their affinity for organic waste processing. - Siddiqui, S. A.; Ristow, B.; Rahayu, T.; Putra, N. S.; Widya Yuwono, N.; Nisa', K.; Mategeko, B.; Smetana, S.; Saki, M.; Nawaz, A.; Nagdalian, A. (Waste Manag, 2022)
There are two major problems that we are facing currently. Firstly, a growing human population continues to contribute to the increased food demand. Secondly, the volume of organic waste produced will threaten human health and the quality of the environment. Recently, there is an increasing number of efforts placed into farming insect biomass to produce alternative feed ingredients. Black soldier fly larvae (BSFL), Hermetia illucens have proven to convert organic waste into high-quality nutrients for pet foods, fish and poultry feeds, as well as residue fertilizer for soil amendment. However, better BSFL feed formulation and feeding approaches are necessary for yielding a higher nutrient content of the insect body, and if performed efficiently, whilst converting waste into higher value biomass. Lastly, this paper reveals that BSFL, in fact, thrives in various ranges of organic matter composition and with simple rearing systems.
Keywords: Agriculture; Animals; Biomass; *Diptera; Food; Larva

Gene Network Inference from Single-Cell Omics Data and Domain Knowledge for Constructing COVID-19-Specific ICAM1-Associated Pathways - Odaka, Mitsuhiro; Magnin, Morgan; Inoue, Katsumi (2022)
Abstract ICAM-1 is critical for interactions between cells. Previous studies have suggested that ICAM-1 triggers cell-to-cell transmission of HIV-1 or HTLV-1. SARS-CoV-2 shares several features with these viruses in interactions between cells, and SARS-CoV-2 cell-to-cell transmission is associated with COVID-19 severity. However, ICAM-1 and its associated pathways are not identified as essential factors in interactions between cells in COVID-19. For example, the current COVID-19 Disease Map has no entry for those pathways. Therefore, discovering unknown ICAM-1 pathways will be indispensable for clarifying the mechanism of COVID-19. This study builds ICAM1-associated pathways by gene network inference from single-cell omics data and multiple knowledge bases. First, data analyses extracted coexpressed genes with significant differences in expression levels with spurious correlations removed. Second, knowledge bases validate models. Finally, mapping the models onto existing pathways identifies new ICAM1-associated pathways. These pathways indicate that (1) upstream pathways include proteins in noncanonical NF-kappaB pathway and that (2) downstream pathways contain integrins and cytoskeleton or motor proteins for cell transformation. In this way, data-driven and knowledge-based approaches are integrated into gene network inference for ICAM1-associated pathway construction. The results can contribute to repairing and completing the COVID-19 Disease Map, thereby improving our understanding of the mechanisms of COVID-19.

The Arabidopsis Framework Model version 2 predicts the organism-level effects of circadian clock gene mis-regulation - Chew, Yin Hoon; Seaton, Daniel; Mengin, Virginie; Flis, Anna; Mugford, Sam T.; George, Gavin M.; Moulin, Michael; Hume, Alastair; Zeeman, Samuel C.; Fitzpatrick, Teresa B.; Smith, Alison M.; Stitt, Mark; et al. (2017)
Predicting a multicellular organism’s phenotype quantitatively from its genotype is challenging, as genetic effects must propagate across scales. Circadian clocks are intracellular regulators that control temporal gene expression patterns and hence metabolism, physiology and behaviour. Here we explain and predict canonical phenotypes of circadian timing in a multicellular, model organism. We used diverse metabolic and physiological data to combine and extend mathematical models of rhythmic gene expression, photoperiod-dependent flowering, elongation growth and starch metabolism within a Framework Model for the vegetative growth of Arabidopsis thaliana, sharing the model and data files in a structured, public resource. The calibrated model predicted the effect of altered circadian timing upon each particular phenotype in clock-mutant plants under standard laboratory conditions. Altered night-time metabolism of stored starch accounted for most of the decrease in whole-plant biomass, as previously proposed. Mobilisation of a secondary store of malate and fumarate was also mis-regulated, accounting for any remaining biomass defect. We test three candidate mechanisms for the accumulation of these organic acids. Our results link genotype through specific processes to higher-level phenotypes, formalising our understanding of a subtle, pleiotropic syndrome at the whole-organism level, and validating the systems approach to understand complex traits starting from intracellular circuits.

Rainbow Trout (Oncorhynchus Mykiss) Intestinal Epithelial Cells as a Model for Studying Gut Immune Function and Effects of Functional Feed Ingredients - Wang, Hao; Lei, Peng; Gamil, Amr Ahmed Abdelrahim; Lagos, Leidy; Yue, Yang; Schirmer, Kristin; Mydland, Liv Torunn; Overland, Margareth; Krogdahl, Åshild; Kortner, Trond M. (Frontiers in Immunology, 2019)
The objective of this study was to evaluate the suitability of the rainbow trout intestinal epithelial cell line (RTgutGC) as an in vitro model for studies of gut immune function and effects of functional feed ingredients. Effects of lipopolysaccharide (LPS) and three functional feed ingredients [nucleotides, mannanoligosaccharides (MOS), and beta-glucans] were evaluated in RTgutGC cells grown on conventional culture plates and transwell membranes. Permeation of fluorescently-labeled albumin, transepithelial electrical resistance (TEER), and tight junction protein expression confirmed the barrier function of the cells. Brush border membrane enzyme activities [leucine aminopeptidase (LAP) and maltase] were detected in the RTgutGC cells but activity levels were not modulated by any of the exposures. Immune related genes were expressed at comparable relative basal levels as these in rainbow trout distal intestine. LPS produced markedly elevated gene expression levels of the pro-inflammatory cytokines il1b, il6, il8, and tnfa but had no effect on ROS production. Immunostaining demonstrated increased F-actin contents after LPS exposure. Among the functional feed ingredients, MOS seemed to be the most potent modulator of RTgutGC immune and barrier function. MOS significantly increased albumin permeation and il1b, il6, il8, tnfa, and tgfb expression, but suppressed ROS production, cell proliferation and myd88 expression. Induced levels of il1b and il8 were also observed after treatment with nucleotides and beta-glucans. For barrier function related genes, all treatments up-regulated the expression of cldn3 and suppressed cdh1 levels. Beta-glucans increased TEER levels and F-actin content. Collectively, the present study has provided new information on how functional ingredients commonly applied in aquafeeds can affect intestinal epithelial function in fish. Our findings suggest that RTgutGC cells possess characteristic features of functional intestinal epithelial cells indicating a potential for use as an efficient in vitro model to evaluate effects of bioactive feed ingredients on gut immune and barrier functions and their underlying cellular mechanisms.

SALARECON connects the Atlantic salmon genome to growth and feed efficiency - Zakhartsev, Maksim; Rotnes, Filip; Gulla, Marie; Oyas, Ove; van Dam, Jesse; Suarez Diez, Maria; Grammes, Fabian; Hafthorsson, Robert; van Helvoirt, Wout; Koehorst, Jasper; Schaap, Peter; Jin, Yang; et al. (PLOS Computational Biology, 2022)
Atlantic salmon (Salmo salar) is the most valuable farmed fish globally and there is much interest in optimizing its genetics and rearing conditions for growth and feed efficiency. Marine feed ingredients must be replaced to meet global demand, with challenges for fish health and sustainability. Metabolic models can address this by connecting genomes to metabolism, which converts nutrients in the feed to energy and biomass, but such models are currently not available for major aquaculture species such as salmon. We present SALARECON, a model focusing on energy, amino acid, and nucleotide metabolism that links the Atlantic salmon genome to metabolic fluxes and growth. It performs well in standardized tests and captures expected metabolic (in)capabilities. We show that it can explain observed hypoxic growth in terms of metabolic fluxes and apply it to aquaculture by simulating growth with commercial feed ingredients. Predicted limiting amino acids and feed efficiencies agree with data, and the model suggests that marine feed efficiency can be achieved by supplementing a few amino acids to plant- and insect-based feeds. SALARECON is a high-quality model that makes it possible to simulate Atlantic salmon metabolism and growth. It can be used to explain Atlantic salmon physiology and address key challenges in aquaculture such as development of sustainable feeds.

Exercise-Induced Fitness Changes Correlate with Changes in Neural Specificity in Older Adults - Kleemeyer, Maike; Polk, Thad A.; Schaefer, Sabine; Bodammer, Nils C.; Brechtel, Lars; Lindenberger, Ulman (Frontiers in Human Neuroscience, 2017)
Neural specificity refers to the degree to which neural representations of different stimuli can be distinguished. Evidence suggests that neural specificity, operationally defined as stimulus-related differences in functional magnetic resonance imaging (fMRI) activation patterns, declines with advancing adult age, and that individual differences in neural specificity are associated with individual differences in fluid intelligence. A growing body of literature also suggests that regular physical activity may help preserve cognitive abilities in old age. Based on this literature, we hypothesized that exercise-induced improvements in fitness would be associated with greater neural specificity among older adults. A total of 52 adults aged 59–74 years were randomly assigned to one of two aerobic-fitness training regimens, which differed in intensity. Participants in both groups trained three times a week on stationary bicycles. In the low-intensity (LI) group, the resistance was kept constant at a low level (10 Watts). In the high-intensity (HI) group, the resistance depended on participants’ heart rate and therefore typically increased with increasing fitness. Before and after the 6-month training phase, participants took part in a functional MRI experiment in which they viewed pictures of faces and buildings. We used multivariate pattern analysis (MVPA) to estimate the distinctiveness of neural activation patterns in ventral visual cortex (VVC) evoked by face or building stimuli. Fitness was also assessed before and after training. In line with our hypothesis, training-induced changes in fitness were positively associated with changes in neural specificity. We conclude that physical activity may protect against age-related declines in neural specificity.

Health benefits of microalgae and their microbiomes - Krohn, Ines; Menanteau‐Ledouble, Simon; Hageskal, Gunhild; Astafyeva, Yekaterina; Jouannais, Pierre; Nielsen, Jeppe Lund; Pizzol, Massimo; Wentzel, Alexander; Streit, Wolfgang R. (Microbial Biotechnology, 2022)
Microalgae comprise a phylogenetically very diverse group of photosynthetic unicellular pro- and eukaryotic organisms growing in marine and other aquatic environments. While they are well explored for the generation of biofuels, their potential as a source of antimicrobial and prebiotic substances have recently received increasing interest. Within this framework, microalgae may offer solutions to the societal challenge we face, concerning the lack of antibiotics treating the growing level of antimicrobial resistant bacteria and fungi in clinical settings. While the vast majority of microalgae and their associated microbiota remain unstudied, they may be a fascinating and rewarding source for novel and more sustainable antimicrobials and alternative molecules and compounds. In this review, we present an overview of the current knowledge on health benefits of microalgae and their associated microbiota. Finally, we describe remaining issues and limitation, and suggest several promising research potentials that should be given attention.

Stochastic LCA Model of Upscaling the Production of Microalgal Compounds - Jouannais, Pierre; Hindersin, Stefan; Löhn, Sarah; Pizzol, Massimo (Environmental Science & Technology, 2022)

Microalgae and Bacteria Interaction—Evidence for Division of Diligence in the Alga Microbiota - Astafyeva, Yekaterina; Gurschke, Marno; Qi, Minyue; Bergmann, Lutgardis; Indenbirken, Daniela; de Grahl, Imke; Katzowitsch, Elena; Reumann, Sigrun; Hanelt, Dieter; Alawi, Malik; Streit, Wolfgang R.; Krohn, Ines (Microbiology Spectrum, 2022)

Diversity and Evolution of Clostridium beijerinckii and Complete Genome of the Type Strain DSM 791T - Sedlar, Karel; Nykrynova, Marketa; Bezdicek, Matej; Branska, Barbora; Lengerova, Martina; Patakova, Petra; Skutkova, Helena (Processes, 2021)
Clostridium beijerinckii is a relatively widely studied, yet non-model, bacterium. While 246 genome assemblies of its various strains are available currently, the diversity of the whole species has not been studied, and it has only been analyzed in part for a missing genome of the type strain. Here, we sequenced and assembled the complete genome of the type strain Clostridium beijerinckii DSM 791T, composed of a circular chromosome and a circular megaplasmid, and used it for a comparison with other genomes to evaluate diversity and capture the evolution of the whole species. We found that strains WB53 and HUN142 were misidentified and did not belong to the Clostridium beijerinckii species. Additionally, we filtered possibly misassembled genomes, and we used the remaining 237 high-quality genomes to define the pangenome of the whole species. By its functional annotation, we showed that the core genome contains genes responsible for basic metabolism, while the accessory genome has genes affecting final phenotype that may vary among different strains. We used the core genome to reconstruct the phylogeny of the species and showed its great diversity, which complicates the identification of particular strains, yet hides possibilities to reveal hitherto unreported phenotypic features and processes utilizable in biotechnology.

Digitoxin metabolism by rat liver microsomes. - Schmoldt, A.; Benthe, H. F.; Haberland, G. (Biochem Pharmacol, 1975)
Keywords: Animals; Chromatography, Thin Layer; Digitoxigenin/metabolism; Digitoxin/*metabolism; Hydroxylation; In Vitro Techniques; Male; Microsomes, Liver/*metabolism; NADP/metabolism; Rats; Time Factors

pISA-tree - a data management framework for life science research projects using a standardised directory tree - Petek, Marko; Zagorscak, Maja; Blejec, Andrej; Ramsak, Ziva; Coll, Anna; Baebler, Špela; Gruden, Kristina (2021)
Abstract

Fermentative Indole Production via Bacterial Tryptophan Synthase Alpha Subunit and Plant Indole-3-Glycerol Phosphate Lyase Enzymes - Ferrer, Lenny; Mindt, Melanie; Suarez Diez, Maria; Hentrich, Thomas; Zagorscak, Maja; Lee, Jin-Ho; Gruden, Kristina; Wendisch, Volker; cankar, Katarina (Journal of Agricultural and Food Chemistry, 2022)
Indole is produced in nature by diverse organisms and exhibits a characteristic odor described as animal, fecal, and floral. In addition, it contributes to the flavor in foods, and it is applied in the fragrance and flavor industry. In nature, indole is synthesized either from tryptophan by bacterial tryptophanases (TNAs) or from indole-3-glycerol phosphate (IGP) by plant indole-3-glycerol phosphate lyases (IGLs). While it is widely accepted that the tryptophan synthase α-subunit (TSA) has intrinsically low IGL activity in the absence of the tryptophan synthase β-subunit, in this study, we show that Corynebacterium glutamicum TSA functions as a bona fide IGL and can support fermentative indole production in strains providing IGP. By bioprospecting additional bacterial TSAs and plant IGLs that function as bona fide IGLs were identified. Capturing indole in an overlay enabled indole production to titers of about 0.7 g L-1 in fermentations using C. glutamicum strains expressing either the endogenous TSA gene or the IGL gene from wheat.

The Arabidopsis Framework Model version 2 predicts the organism-level effects of circadian clock gene mis-regulation - Chew, Yin Hoon; Seaton, Daniel; Mengin, Virginie; Flis, Anna; Mugford, Sam T; George, Gavin M; Moulin, Michael; Hume, Alastair; Zeeman, Samuel C; Fitzpatrick, Teresa B; Smith, Alison M; Stitt, Mark; et al. (in silico Plants, 2022)
Predicting a multicellular organism’s phenotype quantitatively from its genotype is challenging, as genetic effects must propagate across scales. Circadian clocks are intracellular regulators that control temporal gene expression patterns and hence metabolism, physiology and behaviour. Here we explain and predict canonical phenotypes of circadian timing in a multicellular, model organism. We used diverse metabolic and physiological data to combine and extend mathematical models of rhythmic gene expression, photoperiod-dependent flowering, elongation growth and starch metabolism within a Framework Model for the vegetative growth of Arabidopsis thaliana, sharing the model and data files in a structured, public resource. The calibrated model predicted the effect of altered circadian timing upon each particular phenotype in clock-mutant plants under standard laboratory conditions. Altered night-time metabolism of stored starch accounted for most of the decrease in whole-plant biomass, as previously proposed. Mobilization of a secondary store of malate and fumarate was also mis-regulated, accounting for any remaining biomass defect. The three candidate mechanisms tested did not explain this organic acid accumulation. Our results link genotype through specific processes to higher-level phenotypes, formalizing our understanding of a subtle, pleiotropic syndrome at the whole-organism level, and validating the systems approach to understand complex traits starting from intracellular circuits.

Periportal steatosis in mice affects distinct parameters of pericentral drug metabolism - Albadry, Mohamed; Höpfl, Sebastian; Ehteshamzad, Nadia; König, Matthias; Böttcher, Michael; Neumann, Jasna; Lupp, Amelie; Dirsch, Olaf; Radde, Nicole; Christ, Bruno; Christ, Madlen; Schwen, Lars Ole; et al. (Scientific Reports, 2022)
Abstract Little is known about the impact of morphological disorders in distinct zones on metabolic zonation. It was described recently that periportal fibrosis did affect the expression of CYP proteins, a set of pericentrally located drug-metabolizing enzymes. Here, we investigated whether periportal steatosis might have a similar effect. Periportal steatosis was induced in C57BL6/J mice by feeding a high-fat diet with low methionine/choline content for either two or four weeks. Steatosis severity was quantified using image analysis. Triglycerides and CYP activity were quantified in photometric or fluorometric assay. The distribution of CYP3A4, CYP1A2, CYP2D6, and CYP2E1 was visualized by immunohistochemistry. Pharmacokinetic parameters of test drugs were determined after injecting a drug cocktail (caffeine, codeine, and midazolam). The dietary model resulted in moderate to severe mixed steatosis confined to periportal and midzonal areas. Periportal steatosis did not affect the zonal distribution of CYP expression but the activity of selected CYPs was associated with steatosis severity. Caffeine elimination was accelerated by microvesicular steatosis, whereas midazolam elimination was delayed in macrovesicular steatosis. In summary, periportal steatosis affected parameters of pericentrally located drug metabolism. This observation calls for further investigations of the highly complex interrelationship between steatosis and drug metabolism and underlying signaling mechanisms.

Toward New Transmission-Blocking Combination Therapies: Pharmacokinetics of 10-Amino-Artemisinins and 11-Aza-Artemisinin and Comparison with Dihydroartemisinin and Artemether - Watson, Daniel J.; Laing, Lizahn; Gibhard, Liezl; Wong, Ho Ning; Haynes, Richard K.; Wiesner, Lubbe (Antimicrobial Agents and Chemotherapy, 2021)

Comparison of in vitro/in vivo blood distribution and pharmacokinetics of artemisinin, artemether and dihydroartemisinin in rats - Dai, Tianming; Jiang, Weifan; Guo, Yike; Xie, Yanxiang; Dai, Renke (Journal of Pharmaceutical and Biomedical Analysis, 2019)

A Phase 1, Placebo-controlled, Randomized, Single Ascending Dose Study and a Volunteer Infection Study to Characterize the Safety, Pharmacokinetics, and Antimalarial Activity of the Plasmodium Phosphatidylinositol 4-Kinase Inhibitor MMV390048 - McCarthy, James S; Donini, Cristina; Chalon, Stephan; Woodford, John; Marquart, Louise; Collins, Katharine A; Rozenberg, Felix D; Fidock, David A; Cherkaoui-Rbati, Mohammed H; Gobeau, Nathalie; Möhrle, Jörg J (Clinical Infectious Diseases, 2020)
Abstract

Review of the clinical pharmacokinetics of artesunate and its active metabolite dihydroartemisinin following intravenous, intramuscular, oral or rectal administration - Morris, Lorna; Duparc, Stephan; Borghini-Fuhrer, Isabelle; Jung, Kirsten; Shin, Chang-Sik; Fleckenstein, Lawrence (Malaria Journal, 2011)
Abstract Artesunate (AS) is a clinically versatile artemisinin derivative utilized for the treatment of mild to severe malaria infection. Given the therapeutic significance of AS and the necessity of appropriate AS dosing, substantial research has been performed investigating the pharmacokinetics of AS and its active metabolite dihydroartemisinin (DHA). In this article, a comprehensive review is presented of AS clinical pharmacokinetics following administration of AS by the intravenous (IV), intramuscular (IM), oral or rectal routes. Intravenous AS is associated with high initial AS concentrations which subsequently decline rapidly, with typical AS half-life estimates of less than 15 minutes. AS clearance and volume estimates average 2 - 3 L/kg/hr and 0.1 - 0.3 L/kg, respectively. DHA concentrations peak within 25 minutes post-dose, and DHA is eliminated with a half-life of 30 - 60 minutes. DHA clearance and volume average between 0.5 - 1.5 L/kg/hr and 0.5 - 1.0 L/kg, respectively. Compared to IV administration, IM administration produces lower peaks, longer half-life values, and higher volumes of distribution for AS, as well as delayed peaks for DHA; other parameters are generally similar due to the high bioavailability, assessed by exposure to DHA, associated with IM AS administration (> 86%). Similarly high bioavailability of DHA (> 80%) is associated with oral administration. Following oral AS, peak AS concentrations (Cmax) are achieved within one hour, and AS is eliminated with a half-life of 20 - 45 minutes. DHA Cmax values are observed within two hours post-dose; DHA half-life values average 0.5 - 1.5 hours. AUC values reported for AS are often substantially lower than those reported for DHA following oral AS administration. Rectal AS administration yields pharmacokinetic results similar to those obtained from oral administration, with the exceptions of delayed AS Cmax and longer AS half-life. Drug interaction studies conducted with oral AS suggest that AS does not appreciably alter the pharmacokinetics of atovaquone/proguanil, chlorproguanil/dapsone, or sulphadoxine/pyrimethamine, and mefloquine and pyronaridine do not alter the pharmacokinetics of DHA. Finally, there is evidence suggesting that the pharmacokinetics of AS and/or DHA following AS administration may be altered by pregnancy and by acute malaria infection, but further investigation would be required to define those alterations precisely.

Antimalarial efficacy of MMV390048, an inhibitor of Plasmodium phosphatidylinositol 4-kinase - Paquet, Tanya; Le Manach, Claire; Cabrera, Diego González; Younis, Yassir; Henrich, Philipp P.; Abraham, Tara S.; Lee, Marcus C. S.; Basak, Rajshekhar; Ghidelli-Disse, Sonja; Lafuente-Monasterio, María José; Bantscheff, Marcus; Ruecker, Andrea; et al. (Science Translational Medicine, 2017)

Pharmacokinetics of Artemisinin-Type Compounds - Navaratnam, Visweswaran; Mansor, Sharif Mahsufi; Sit, Nam-Weng; Grace, James; Li, Xiangcheng; Olliaro, Piero (Clinical Pharmacokinetics, 2000)

Safety, Tolerability, Pharmacokinetics, and Antimalarial Activity of the Novel Plasmodium Phosphatidylinositol 4-Kinase Inhibitor MMV390048 in Healthy Volunteers - Sinxadi, Phumla; Donini, Cristina; Johnstone, Hilary; Langdon, Grant; Wiesner, Lubbe; Allen, Elizabeth; Duparc, Stephan; Chalon, Stephan; McCarthy, James S.; Lorch, Ulrike; Chibale, Kelly; Möhrle, Jörg; et al. (Antimicrobial Agents and Chemotherapy, 2020)

Development of potent and selective FAAH inhibitors with improved drug-like properties as potential tools to treat neuroinflammatory conditions. - Papa, A.; Pasquini, S.; Galvani, F.; Cammarota, M.; Contri, C.; Carullo, G.; Gemma, S.; Ramunno, A.; Lamponi, S.; Gorelli, B.; Saponara, S.; Varani, K.; et al. (Eur J Med Chem, 2023)
The neuroprotective performance against neuroinflammation of the endocannabinoid system (ECS) can be remarkably improved by indirect stimulation mediated by the pharmacological inhibition of the key ECS catabolic enzyme fatty acid amide hydrolase (FAAH). Based on our previous works and aiming to discover new selective FAAH inhibitors , we herein reported a new series of carbamate-based FAAH inhibitors (4a-t) which showed improved drug disposition properties compared to the previously reported analogues 2a-b. The introduction of ionizable functions allowed us to obtain new FAAH inhibitors of nanomolar potency characterized by good water solubility and chemical stability at physiological pH. Interesting structure-activity relationships (SARs), deeply analyzed by molecular docking and molecular dynamic (MD) simulations, were obtained. All the newly developed inhibitors showed an excellent selectivity profile evaluated against monoacylglycerol lipase and cannabinoid receptors. The reversible mechanism of action was determined by a rapid dilution assay. Absence of toxicity was confirmed in mouse fibroblasts NIH3T3 (for compounds 4e, 4g, 4n-o, and 4s) and in human astrocytes cell line 1321N1 (for compounds 4e, 4n, and 4s). The absence of undesired cardiac effects was also confirmed for compound 4n. Selected analogues (compounds 4e, 4g, 4n, and 4s) were able to reduce oxidative stress in 1321N1 astrocytes and exhibited notable neuroprotective effects when tested in an ex vivo model of neuroinflammation.
Keywords: Mice; Animals; Humans; *Enzyme Inhibitors/chemistry; Molecular Docking Simulation; NIH 3T3 Cells; *Neuroinflammatory Diseases; Amidohydrolases/metabolism; Endocannabinoids/metabolism

4-Amino-1,8-naphthalimide–ferrocene conjugates as potential multi-targeted anticancer and fluorescent cellular imaging agents - Johnson, Alex D.; Buhagiar, Joseph A.; Magri, David (RSC Medicinal Chemistry, 2021)
Eight ferrocenyl 4-amino-1,8-naphthalimide logic gates for acidity and oxidisability are repurposed as anti-proliferation and cellular imaging agents against MCF-7 and K562 cancer cell lines.

The SZT2 Interactome Unravels New Functions of the KICSTOR Complex - Cattelani, Cecilia; Lesiak, Dominik; Liebscher, Gudrun; Singer, Isabel I.; Stasyk, Taras; Wallnöfer, Moritz H.; Heberle, Alexander; Corti, Corrado; Hess, Michael W.; Pfaller, Kristian; Kwiatkowski, Marcel; Pramstaller, Peter P.; et al. (Cells, 2021)
Seizure threshold 2 (SZT2) is a component of the KICSTOR complex which, under catabolic conditions, functions as a negative regulator in the amino acid-sensing branch of mTORC1. Mutations in this gene cause a severe neurodevelopmental and epileptic encephalopathy whose main symptoms include epilepsy, intellectual disability, and macrocephaly. As SZT2 remains one of the least characterized regulators of mTORC1, in this work we performed a systematic interactome analysis under catabolic and anabolic conditions. Besides numerous mTORC1 and AMPK signaling components, we identified clusters of proteins related to autophagy, ciliogenesis regulation, neurogenesis, and neurodegenerative processes. Moreover, analysis of SZT2 ablated cells revealed increased mTORC1 signaling activation that could be reversed by Rapamycin or Torin treatments. Strikingly, SZT2 KO cells also exhibited higher levels of autophagic components, independent of the physiological conditions tested. These results are consistent with our interactome data, in which we detected an enriched pool of selective autophagy receptors/regulators. Moreover, preliminary analyses indicated that SZT2 alters ciliogenesis. Overall, the data presented form the basis to comprehensively investigate the physiological functions of SZT2 that could explain major molecular events in the pathophysiology of developmental and epileptic encephalopathy in patients with SZT2 mutations.

Chemical identification and indexing in full-text articles: an overview of the NLM-Chem track at BioCreative VII - Leaman, Robert; Islamaj, Rezarta; Adams, Virginia; Alliheedi, Mohammed A; Almeida, Camila; Antunes, Rui; Bevan, Robert; Chang, Antje; Erdengasileng, Arslan; Hodgskiss, Matthew; Ida, Ryuki; Kim, Dong-Hyun; et al. (Database, 2023)
Abstract The BioCreative National Library of Medicine (NLM)-Chem track calls for a community effort to fine-tune automated recognition of chemical names in the biomedical literature. Chemicals are one of the most searched biomedical entities in PubMed, and—as highlighted during the coronavirus disease 2019 pandemic—their identification may significantly advance research in multiple biomedical subfields. While previous community challenges focused on identifying chemical names mentioned in titles and abstracts, the full text contains valuable additional detail. We, therefore, organized the BioCreative NLM-Chem track as a community effort to address automated chemical entity recognition in full-text articles. The track consisted of two tasks: (i) chemical identification and (ii) chemical indexing. The chemical identification task required predicting all chemicals mentioned in recently published full-text articles, both span [i.e. named entity recognition (NER)] and normalization (i.e. entity linking), using Medical Subject Headings (MeSH). The chemical indexing task required identifying which chemicals reflect topics for each article and should therefore appear in the listing of MeSH terms for the document in the MEDLINE article indexing. This manuscript summarizes the BioCreative NLM-Chem track and post-challenge experiments. We received a total of 85 submissions from 17 teams worldwide. The highest performance achieved for the chemical identification task was 0.8672 F-score (0.8759 precision and 0.8587 recall) for strict NER performance and 0.8136 F-score (0.8621 precision and 0.7702 recall) for strict normalization performance. The highest performance achieved for the chemical indexing task was 0.6073 F-score (0.7417 precision and 0.5141 recall). This community challenge demonstrated that (i) the current substantial achievements in deep learning technologies can be utilized to improve automated prediction accuracy further and (ii) the chemical indexing task is substantially more challenging. We look forward to further developing biomedical text–mining methods to respond to the rapid growth of biomedical literature. The NLM-Chem track dataset and other challenge materials are publicly available at https://ftp.ncbi.nlm.nih.gov/pub/lu/BC7-NLM-Chem-track/. Database URL https://ftp.ncbi.nlm.nih.gov/pub/lu/BC7-NLM-Chem-track/

Synthesis of Deoxysugars from Aliphatic α-Ketoacids and Aldoses Catalyzed by Thermostable Transketolase Variants from Geobacillus stearothermophilus - Hecquet, Laurence (2022)

Design, synthesis and biological evaluation of antiparasitic dinitroaniline-ether phospholipid hybrids - Roussaki, Marina; Magoulas, George E.; Fotopoulou, Theano; Santarem, Nuno; Barrias, Emile; Poehner, Ina; Luelmo, Sara; Afroudakis, Pantelis; Georgikopoulou, Kalliopi; Nevado, Paloma Tejera; Eick, Julia; Bifeld, Eugenia; et al. (Bioorganic Chemistry, 2023)
A series of nine novel ether phospholipid-dinitroaniline hybrids were synthesized in an effort to deliver more potent antiparasitic agents with improved safety profile compared to miltefosine. The compounds were evaluated for their in vitro antiparasitic activity against L. infantum, L.donovani, L. amazonensis, L. major and L. tropica promastigotes, L. infantum and L. donovani intracellular amastigotes, Trypanosoma brucei brucei and against different developmental stages of Trypanosoma cruzi. The nature of the oligomethylene spacer between the dinitroaniline moiety and the phosphate group, the length of the side chain substituent on the dinitroaniline and the choline or homocholine head group were found to affect both the activity and toxicity of the hybrids. The early ADMET profile of the derivatives did not reveal major liabilities. Hybrid 3, bearing an 11-carbon oligomethylene spacer, a butyl side chain and a choline head group, was the most potent analogue of the series. It exhibited a broad spectrum antiparasitic profile against the promastigotes of New and Old World Leishmania spp., against intracellular amastigotes of two L. infantum strains and L. donovani, against T. brucei and against T. cruzi Y strain epimastigotes, intracellular amastigotes and trypomastigotes. The early toxicity studies revealed that hybrid 3 showed a safe toxicological profile while its cytotoxicity concentration (CC50) against THP-1 macrophages being >100 μM. Computational analysis of binding sites and docking indicated that the interaction of hybrid 3 with trypanosomatid α-tubulin may contribute to its mechanism of action. Furthermore, compound 3 was found to interfere with the cell cycle in T. cruzi epimastigotes, while ultrastructural studies using SEM and TEM in T. cruzi showed that compound 3 affects cellular processes that result in changes in the Golgi complex, the mitochondria and the parasite’s plasma membrane. The snapshot pharmacokinetic studies showed low levels of 3 after 24 h following oral administration of 100 mg/Kg, while, its homocholine congener compound 9 presented a better pharmacokinetic profile.

Phosphofructokinase controls the acetaldehyde-induced phase shift in isolated yeast glycolytic oscillators - van Niekerk, Dawie; Gustavsson, Anna-Karin; Mojica-Benavides, Martin; Adiels, Caroline B.; Goksör, Mattias; Snoep, Jacky (Biochemical Journal, 2019)
Abstract The response of oscillatory systems to external perturbations is crucial for emergent properties such as synchronisation and phase locking and can be quantified in a phase response curve (PRC). In individual, oscillating yeast cells, we characterised experimentally the phase response of glycolytic oscillations for external acetaldehyde pulses and followed the transduction of the perturbation through the system. Subsequently, we analysed the control of the relevant system components in a detailed mechanistic model. The observed responses are interpreted in terms of the functional coupling and regulation in the reaction network. We find that our model quantitatively predicts the phase-dependent phase shift observed in the experimental data. The phase shift is in agreement with an adaptation leading to synchronisation with an external signal. Our model analysis establishes that phosphofructokinase plays a key role in the phase shift dynamics as shown in the PRC and adaptation time to external perturbations. Specific mechanism-based interventions, made possible through such analyses of detailed models, can improve upon standard trial and error methods, e.g. melatonin supplementation to overcome jet-lag, which are error-prone, specifically, since the effects are phase dependent and dose dependent. The models by Gustavsson and Goldbeter discussed in the text can be obtained from the JWS Online simulation database: (https://jjj.bio.vu.nl/models/gustavsson5 and https://jjj.bio.vu.nl/models/goldbeter1)

Inhibitor titrations reveal low control of glyceraldehyde 3-phosphate dehydrogenase and high control of hexokinase on glycolytic flux in an aggressive triple-negative breast cancer cell line - Kouril, Theresa; October, Craig; Hollocks, Stephanie; Odendaal, Christoff; van Niekerk, Dawie; Snoep, Jacky (Biosystems, 2023)

MIFlowCyt: The minimum information about a flow cytometry experiment - Lee, Jamie A.; Spidlen, Josef; Boyce, Keith; Cai, Jennifer; Crosbie, Nicholas; Dalphin, Mark; Furlong, Jeff; Gasparetto, Maura; Goldberg, Michael; Goralczyk, Elizabeth M.; Hyun, Bill; Jansen, Kirstin; et al. (Cytometry Part A, 2008)

WeLT: Improving Biomedical Fine-tuned Pre-trained Language Models with Cost-sensitive Learning - Mobasher, Ghadeer; Müller, Wolfgang; Krebs, Olga; Gertz, Michael (The 22nd Workshop on Biomedical Natural Language Processing and BioNLP Shared Tasks, 2023)

In vitro grafting of hepatic spheroids and organoids on a microfluidic vascular bed. - Bonanini, F.; Kurek, D.; Previdi, S.; Nicolas, A.; Hendriks, D.; de Ruiter, S.; Meyer, M.; Clapes Cabrer, M.; Dinkelberg, R.; Garcia, S. B.; Kramer, B.; Olivier, T.; et al. (Angiogenesis, 2022)
With recent progress in modeling liver organogenesis and regeneration, the lack of vasculature is becoming the bottleneck in progressing our ability to model human hepatic tissues in vitro. Here, we introduce a platform for routine grafting of liver and other tissues on an in vitro grown microvascular bed. The platform consists of 64 microfluidic chips patterned underneath a 384-well microtiter plate. Each chip allows the formation of a microvascular bed between two main lateral vessels by inducing angiogenesis. Chips consist of an open-top microfluidic chamber, which enables addition of a target tissue by manual or robotic pipetting. Upon grafting a liver microtissue, the microvascular bed undergoes anastomosis, resulting in a stable, perfusable vascular network. Interactions with vasculature were found in spheroids and organoids upon 7 days of co-culture with space of Disse-like architecture in between hepatocytes and endothelium. Veno-occlusive disease was induced by azathioprine exposure, leading to impeded perfusion of the vascularized spheroid. The platform holds the potential to replace animals with an in vitro alternative for routine grafting of spheroids, organoids, or (patient-derived) explants.
Keywords: Animals; Azathioprine; Coculture Techniques; Humans; Liver; *Microfluidics/methods; *Organoids

Development of a targeted hydrophilic interaction liquid chromatography-tandem mass spectrometry based lipidomics platform applied to a coronavirus disease severity study. - Zhang, Z.; Singh, M.; Kindt, A.; Wegrzyn, A. B.; Pearson, M. J.; Ali, A.; Harms, A. C.; Baker, P.; Hankemeier, T. (J Chromatogr A, 2023)
The importance of lipids seen in studies of metabolism, cancer, the recent COVID-19 pandemic and other diseases has brought the field of lipidomics to the forefront of clinical research. Quantitative and comprehensive analysis is required to understand biological interactions among lipid species. However, lipidomic analysis is often challenging due to the various compositional structures, diverse physicochemical properties, and wide dynamic range of concentrations of lipids in biological systems. To study the comprehensive lipidome, a hydrophilic interaction liquid chromatography-tandem mass spectrometry (HILIC-MS/MS)-based screening method with 1200 lipid features across 19 (sub)classes, including both nonpolar and polar lipids, has been developed. HILIC-MS/MS was selected due to its class separation property and fatty acyl chain level information. 3D models of class chromatographic retention behavior were established and evaluations of cross-class and within-class interferences were performed to avoid over-reporting these features. This targeted HILIC-MS/MS method was fully validated, with acceptable analytical parameters in terms of linearity, precision, reproducibility, and recovery. The accurate quantitation of 608 lipid species in the SRM 1950 NIST plasma was achieved using multi-internal standards per class and post-hoc correction, extending current databases by providing lipid concentrations resolved at fatty acyl chain level. The overall correlation coefficients (R(2)) of measured concentrations with values from literature range from 0.64 to 0.84. The applicability of the developed targeted lipidomics method was demonstrated by discovering 520 differential lipid features related to COVID-19 severity. This high coverage and targeted approach will aid in future investigations of the lipidome in various disease contexts.
Keywords: Humans; *Lipidomics; Tandem Mass Spectrometry; Pandemics; Reproducibility of Results; *COVID-19; Chromatography, Liquid; Patient Acuity; Lipids

Development of HILIC-MS/MS method for acyl-CoAs covering short- to long-chain species in a single analytical run - Singh, Madhulika; Kiyuna, Ligia Akemi; Odendaal, Christoff; Bakker, Barbara; HARMS, Amy; Hankemeier, Thomas (2023)
Acyl-CoAs play a significant role in numerous physiological and metabolic processes making it important to assess their concentration levels for evaluating metabolic health. Considering the important role of acyl-CoAs, it is crucial to develop an analytical method that can analyze these compounds. Due to the structural variations of acyl-CoAs, multiple analytical methods are often required for comprehensive analysis of these compounds, which increases complexity and the analysis time. In this study, we have developed a method using a zwitterionic HILIC column that enables the coverage of free CoA and short- to long-chain acyl-CoA species in one analytical run. Initially, we developed the method on a QTOF instrument for the identification of acyl-CoA species, optimizing their chromatography and retention times. Later, a targeted HILIC-MS/MS method was created in scheduled multiple reaction monitoring mode on a QTRAP instrument. The performance of the method was evaluated based on various parameters such as linearity, precision, recovery and matrix effect. This method was applied to identify the difference in acyl-CoA profiles in HepG2 cells cultured in different conditions. Our findings revealed an increase in levels of acetyl-CoA, medium- and long-chain acyl-CoA while a decrease in the profiles of free CoA in the starved state, indicating a clear alteration in the fatty acid oxidation process.

ReStoRunT: Simple Recording, Storing, Running and Tracing changes in Spreadsheets - Müller, Wolfgang; Mertová, Lukrécia (Datenbanksysteme für Business, Technologie und Web, 2023)
In addition to the ubiquitous big data, one key challenge indata processing and management in the life sciences is the diversity ofsmall data. Diverse pieces of small data have to be transformed intostandards-compliant data. Here, the challenge lies not in the difficulty ofsingle steps that need to be performed, but rather in the fact that manytransformation tasks are to be performed once or only a few times. Thislimits the time that can be put into automated approaches, which inturn severely limits the verifiability of such transformations.As much of the data to be processed is stored in spreadsheets, withinthis paper we justify and propose a lightweight recording-based solutionthat works on a wide variety of spreadsheet programs, from MicrosoftExcel to Google Docs.

Proteome Coverage after Simultaneous Proteo-Metabolome Liquid–Liquid Extraction - van Pijkeren, Alienke; Egger, Anna-Sophia; Hotze, Madlen; Zimmermann, Boris; Kipura, Tobias; Grander, Julia; Gollowitzer, André; Koeberle, Andreas; Bischoff, Rainer; Thedieck, Kathrin; Kwiatkowski, Marcel (Journal of Proteome Research, 2023)
Proteomics and metabolomics are essential in systems biology, and simultaneous proteo-metabolome liquid–liquid extraction (SPM-LLE) allows isolation of the metabolome and proteome from the same sample. Since the proteome is present as a pellet in SPM-LLE, it must be solubilized for quantitative proteomics. Solubilization and proteome extraction are critical factors in the information obtained at the proteome level. In this study, we investigated the performance of two surfactants (sodium deoxycholate (SDC), sodium dodecyl sulfate (SDS)) and urea in terms of proteome coverage and extraction efficiency of an interphase proteome pellet generated by methanol–chloroform based SPM-LLE. We also investigated how the performance differs when the proteome is extracted from the interphase pellet or by direct cell lysis. We quantified 12 lipids covering triglycerides and various phospholipid classes, and 25 polar metabolites covering central energy metabolism in chloroform and methanol extracts. Our study reveals that the proteome coverages between the two surfactants and urea for the SPM-LLE interphase pellet were similar, but the extraction efficiencies differed significantly. While SDS led to enrichment of basic proteins, which were mainly ribosomal and ribonuclear proteins, urea was the most efficient extraction agent for simultaneous proteo-metabolome analysis. The results of our study also show that the performance of surfactants for quantitative proteomics is better when the proteome is extracted through direct cell lysis rather than an interphase pellet. In contrast, the performance of urea for quantitative proteomics was significantly better when the proteome was extracted from an interphase pellet than by direct cell lysis. We demonstrated that urea is superior to surfactants for proteome extraction from SPM-LLE interphase pellets, with a particularly good performance for the extraction of proteins associated with metabolic pathways. Data are available via ProteomeXchange with identifier PXD027338 (https://proteomecentral.proteomexchange.org/cgi/GetDataset?ID=PXD027338)

Tryptophan stress activates EGFR-RAS-signaling to MTORC1 and p38/MAPK to sustain translation and AHR-dependent autophagy - Pfänder, Pauline; Hensen, Lucas; Navas, Patricia Razquin; Solvay, Marie; Prentzell, Mirja Tamara; Sadik, Ahmed; Heberle, Alexander; Seifert, Sophie; Regin, Leon; Bausbacher, Tobias; Egger, Anna-Sophia; Hotze, Madlen; et al. (2023)
Limited supply and catabolism restrict the essential amino acid tryptophan (Trp) in tumors. How tumors sustain translation under Trp stress remains unclear. Unlike other amino acids, Trp stress activates the EGFR, which enhances macropinocytosis and RAS signaling to the MTORC1 and p38/MAPK kinases, sustaining translation. The AHR forms part of the Trp stress proteome and promotes autophagy to sustain Trp levels, and ceramide biosynthesis. Thus, Trp restriction elicits pro-translation signals enabling adaptation to nutrient stress, placing Trp into a unique position in the amino acid-mediated stress response. Our findings challenge the current perception that Trp restriction inhibits MTORC1 and the AHR and explain how both cancer drivers remain active. A glioblastoma patient subgroup with enhanced MTORC1 and AHR displays an autophagy signature, highlighting the clinical relevance of MTORC1-AHR crosstalk. Regions of high Trp or high ceramides are mutually exclusive, supporting that low Trp activates the EGFR-MTORC1-AHR axis in glioblastoma tissue.

Tryptophan depletion sensitizes the AHR pathway by increasing AHR expression and GCN2/LAT1-mediated kynurenine uptake, and potentiates induction of regulatory T lymphocytes - Solvay, Marie; Holfelder, Pauline; Klaessens, Simon; Pilotte, Luc; Stroobant, Vincent; Lamy, Juliette; Naulaerts, Stefan; Spillier, Quentin; Frédérick, Raphaël; De Plaen, Etienne; Sers, Christine; Opitz, Christiane; et al. (Journal for ImmunoTherapy of Cancer, 2023)
Abstract Background Indoleamine 2,3-dioxygenase 1 (IDO1) and tryptophan-dioxygenase (TDO) are enzymes catabolizing the essential amino acid tryptophan into kynurenine. Expression of these enzymes is frequently observed in advanced-stage cancers and is associated with poor disease prognosis and immune suppression. Mechanistically, the respective roles of tryptophan shortage and kynurenine production in suppressing immunity remain unclear. Kynurenine was proposed as an endogenous ligand for the aryl hydrocarbon receptor (AHR), which can regulate inflammation and immunity. However, controversy remains regarding the role of AHR in IDO1/TDO-mediated immune suppression, as well as the involvement of kynurenine. In this study, we aimed to clarify the link between IDO1/TDO expression, AHR pathway activation and immune suppression.

The complex biology of aryl hydrocarbon receptor activation in cancer and beyond - Opitz, Christiane; Holfelder, Pauline; Prentzell, Mirja Tamara; Trump, Saskia (Biochemical Pharmacology, 2023)

Finding new edges: systems approaches to MTOR signaling. - Heberle, A. M.; Rehbein, U.; Rodriguez Peiris, M.; Thedieck, K. (Biochem Soc Trans, 2021)
Cells have evolved highly intertwined kinase networks to finely tune cellular homeostasis to the environment. The network converging on the mechanistic target of rapamycin (MTOR) kinase constitutes a central hub that integrates metabolic signals and adapts cellular metabolism and functions to nutritional changes and stress. Feedforward and feedback loops, crosstalks and a plethora of modulators finely balance MTOR-driven anabolic and catabolic processes. This complexity renders it difficult - if not impossible - to intuitively decipher signaling dynamics and network topology. Over the last two decades, systems approaches have emerged as powerful tools to simulate signaling network dynamics and responses. In this review, we discuss the contribution of systems studies to the discovery of novel edges and modulators in the MTOR network in healthy cells and in disease.
Keywords: Animals; Gene Regulatory Networks/physiology; Homeostasis/physiology; Humans; Protein Interaction Maps/physiology; Signal Transduction/physiology; Systems Integration; TOR Serine-Threonine Kinases/metabolism/*physiology

Cardiac PI3K p110alpha attenuation delays aging and extends lifespan. - Abdellatif, M.; Eisenberg, T.; Heberle, A. M.; Thedieck, K.; Kroemer, G.; Sedej, S. (Cell Stress, 2022)
Phosphoinositide 3-kinase (PI3K) is a key component of the insulin signaling pathway that controls cellular me-tabolism and growth. Loss-of-function mutations in PI3K signaling and other downstream effectors of the insulin signaling pathway extend the lifespan of various model organisms. However, the pro-longevity effect appears to be sex-specific and young mice with reduced PI3K signaling have increased risk of cardiac disease. Hence, it remains elusive as to whether PI3K inhibition is a valid strategy to delay aging and extend healthspan in humans. We recently demonstrated that reduced PI3K activity in cardiomyocytes delays cardiac growth, causing subnormal contractility and cardiopulmonary functional capacity, as well as increased risk of mortality at young age. In stark contrast, in aged mice, experi-mental attenuation of PI3K signaling reduced the age-dependent decline in cardiac function and extended maximal lifespan, suggesting a biphasic effect of PI3K on cardiac health and survival. The cardiac anti-aging effects of reduced PI3K activity coincided with enhanced oxida-tive phosphorylation and required increased autophagic flux. In humans, explanted failing hearts showed in-creased PI3K signaling, as indicated by increased phos-phorylation of the serine/threonine-protein kinase AKT. Hence, late-life cardiac-specific targeting of PI3K might have a therapeutic potential in cardiac aging and related diseases.

Systematic transcriptional analysis of human cell lines for gene expression landscape and tumor representation - Jin, Han; Zhang, Cheng; Zwahlen, Martin; von Feilitzen, Kalle; Karlsson, Max; Shi, Mengnan; Yuan, Meng; Song, Xiya; Li, Xiangyu; Yang, Hong; Turkez, Hasan; Fagerberg, Linn; et al. (Nature Communications, 2023)
Abstract Cell lines are valuable resources as model for human biology and translational medicine. It is thus important to explore the concordance between the expression in various cell lines vis-à-vis human native and disease tissues. In this study, we investigate the expression of all human protein-coding genes in more than 1,000 human cell lines representing 27 cancer types by a genome-wide transcriptomics analysis. The cell line gene expression is compared with the corresponding profiles in various tissues, organs, single-cell types and cancers. Here, we present the expression for each cell line and give guidance for the most appropriate cell line for a given experimental study. In addition, we explore the cancer-related pathway and cytokine activity of the cell lines to aid human biology studies and drug development projects. All data are presented in an open access cell line section of the Human Protein Atlas to facilitate the exploration of all human protein-coding genes across these cell lines.

Fine-Tuning Cardiac Insulin-Like Growth Factor 1 Receptor Signaling to Promote Health and Longevity. - Abdellatif, M.; Trummer-Herbst, V.; Heberle, A. M.; Humnig, A.; Pendl, T.; Durand, S.; Cerrato, G.; Hofer, S. J.; Islam, M.; Voglhuber, J.; Ramos Pittol, J. M.; Kepp, O.; et al. (Circulation, 2022)
BACKGROUND: The insulin-like growth factor 1 (IGF1) pathway is a key regulator of cellular metabolism and aging. Although its inhibition promotes longevity across species, the effect of attenuated IGF1 signaling on cardiac aging remains controversial. METHODS: We performed a lifelong study to assess cardiac health and lifespan in 2 cardiomyocyte-specific transgenic mouse models with enhanced versus reduced IGF1 receptor (IGF1R) signaling. Male mice with human IGF1R overexpression or dominant negative phosphoinositide 3-kinase mutation were examined at different life stages by echocardiography, invasive hemodynamics, and treadmill coupled to indirect calorimetry. In vitro assays included cardiac histology, mitochondrial respiration, ATP synthesis, autophagic flux, and targeted metabolome profiling, and immunoblots of key IGF1R downstream targets in mouse and human explanted failing and nonfailing hearts, as well. RESULTS: Young mice with increased IGF1R signaling exhibited superior cardiac function that progressively declined with aging in an accelerated fashion compared with wild-type animals, resulting in heart failure and a reduced lifespan. In contrast, mice with low cardiac IGF1R signaling exhibited inferior cardiac function early in life, but superior cardiac performance during aging, and increased maximum lifespan, as well. Mechanistically, the late-life detrimental effects of IGF1R activation correlated with suppressed autophagic flux and impaired oxidative phosphorylation in the heart. Low IGF1R activity consistently improved myocardial bioenergetics and function of the aging heart in an autophagy-dependent manner. In humans, failing hearts, but not those with compensated hypertrophy, displayed exaggerated IGF1R expression and signaling activity. CONCLUSIONS: Our findings indicate that the relationship between IGF1R signaling and cardiac health is not linear, but rather biphasic. Hence, pharmacological inhibitors of the IGF1 pathway, albeit unsuitable for young individuals, might be worth considering in older adults.
Keywords: Aged; Animals; Health Promotion; Humans; *Insulin-Like Growth Factor I/metabolism; *Longevity; Male; Mice; Myocytes, Cardiac/metabolism; Phosphatidylinositol 3-Kinases/metabolism; Receptor, IGF Type 1/genetics/metabolism

Identification of evolutionary and kinetic drivers of NAD-dependent signaling - Bockwoldt, Mathias; Houry, Dorothee; Niere, Marc; Gossmann, Toni I.; Reinartz, Ines; Schug, Alexander; Ziegler, Mathias; Heiland, Ines (Proceedings of the National Academy of Sciences, 2019)
Nicotinamide adenine dinucleotide (NAD) provides an important link between metabolism and signal transduction and has emerged as central hub between bioenergetics and all major cellular events. NAD-dependent signaling (e.g., by sirtuins and poly–adenosine diphosphate [ADP] ribose polymerases [PARPs]) consumes considerable amounts of NAD. To maintain physiological functions, NAD consumption and biosynthesis need to be carefully balanced. Using extensive phylogenetic analyses, mathematical modeling of NAD metabolism, and experimental verification, we show that the diversification of NAD-dependent signaling in vertebrates depended on 3 critical evolutionary events: 1) the transition of NAD biosynthesis to exclusive usage of nicotinamide phosphoribosyltransferase (NamPT); 2) the occurrence of nicotinamide N-methyltransferase (NNMT), which diverts nicotinamide (Nam) from recycling into NAD, preventing Nam accumulation and inhibition of NAD-dependent signaling reactions; and 3) structural adaptation of NamPT, providing an unusually high affinity toward Nam, necessary to maintain NAD levels. Our results reveal an unexpected coevolution and kinetic interplay between NNMT and NamPT that enables extensive NAD signaling. This has implications for therapeutic strategies of NAD supplementation and the use of NNMT or NamPT inhibitors in disease treatment.

AnthraxKP: a knowledge graph-based, Anthrax Knowledge Portal mined from biomedical literature. - Feng, B.; Gao, J. (Database (Oxford), 2022)
Anthrax is a zoonotic infectious disease caused by Bacillus anthracis (anthrax bacterium) that affects not only domestic and wild animals worldwide but also human health. As the study develops in-depth, a large quantity of related biomedical publications emerge. Acquiring knowledge from the literature is essential for gaining insight into anthrax etiology, diagnosis, treatment and research. In this study, we used a set of text mining tools to identify nearly 14 000 entities of 29 categories, such as genes, diseases, chemicals, species, vaccines and proteins, from nearly 8000 anthrax biomedical literature and extracted 281 categories of association relationships among the entities. We curated Anthrax-related Entities Dictionary and Anthrax Ontology. We formed Anthrax Knowledge Graph (AnthraxKG) containing more than 6000 nodes, 6000 edges and 32 000 properties. An interactive visualized Anthrax Knowledge Portal(AnthraxKP) was also developed based on AnthraxKG by using Web technology. AnthraxKP in this study provides rich and authentic relevant knowledge in many forms, which can help researchers carry out research more efficiently. Database URL: AnthraxKP is permitted users to query and download data at http://139.224.212.120:18095/.
Keywords: Animals; *Anthrax; Data Mining; Databases, Factual; Knowledge Bases; Pattern Recognition, Automated

Hepatic ChREBP orchestrates intrahepatic carbohydrate metabolism to limit hepatic glucose 6-phosphate and glycogen accumulation in a mouse model for acute Glycogen Storage Disease type Ib - Alagere Krishnamurthy, Kishore; Rutten, M.G.S.; Hoogerland, J.A.; van Dijk, T.H.; Bos, T.; Koehorst, M.; de Vries, M.P.; Kloosterhuis, N.J.; Havinga, H.; Schomakers, B.V.; van Weeghel, M.; Wolters, J.C.; et al. (Molecular Metabolism, 2024)
Carbohydrate Response Element Binding Protein (ChREBP) is a glucose 6-phosphate (G6P)-sensitive transcription factor that acts as a metabolic switch to maintain intracellular glucose and phosphate homeostasis. Hepatic ChREBP is well-known for its regulatory role in glycolysis, the pentose phosphate pathway, and de novo lipogenesis. The physiological role of ChREBP in hepatic glycogen metabolism and blood glucose regulation has not been assessed in detail, and ChREBP's contribution to carbohydrate flux adaptations in hepatic Glycogen Storage Disease type 1 (GSD I) requires further investigation.

Personalised modelling of clinical heterogeneity between medium-chain acyl-CoA dehydrogenase patients. - Odendaal, C.; Jager, E. A.; Martines, A. M. F.; Vieira-Lara, M. A.; Huijkman, N. C. A.; Kiyuna, L. A.; Gerding, A.; Wolters, J. C.; Heiner-Fokkema, R.; van Eunen, K.; Derks, T. G. J.; Bakker, B. M. (BMC Biol, 2023)
BACKGROUND: Monogenetic inborn errors of metabolism cause a wide phenotypic heterogeneity that may even differ between family members carrying the same genetic variant. Computational modelling of metabolic networks may identify putative sources of this inter-patient heterogeneity. Here, we mainly focus on medium-chain acyl-CoA dehydrogenase deficiency (MCADD), the most common inborn error of the mitochondrial fatty acid oxidation (mFAO). It is an enigma why some MCADD patients-if untreated-are at risk to develop severe metabolic decompensations, whereas others remain asymptomatic throughout life. We hypothesised that an ability to maintain an increased free mitochondrial CoA (CoASH) and pathway flux might distinguish asymptomatic from symptomatic patients. RESULTS: We built and experimentally validated, for the first time, a kinetic model of the human liver mFAO. Metabolites were partitioned according to their water solubility between the bulk aqueous matrix and the inner membrane. Enzymes are also either membrane-bound or in the matrix. This metabolite partitioning is a novel model attribute and improved predictions. MCADD substantially reduced pathway flux and CoASH, the latter due to the sequestration of CoA as medium-chain acyl-CoA esters. Analysis of urine from MCADD patients obtained during a metabolic decompensation showed an accumulation of medium- and short-chain acylcarnitines, just like the acyl-CoA pool in the MCADD model. The model suggested some rescues that increased flux and CoASH, notably increasing short-chain acyl-CoA dehydrogenase (SCAD) levels. Proteome analysis of MCADD patient-derived fibroblasts indeed revealed elevated levels of SCAD in a patient with a clinically asymptomatic state. This is a rescue for MCADD that has not been explored before. Personalised models based on these proteomics data confirmed an increased pathway flux and CoASH in the model of an asymptomatic patient compared to those of symptomatic MCADD patients. CONCLUSIONS: We present a detailed, validated kinetic model of mFAO in human liver, with solubility-dependent metabolite partitioning. Personalised modelling of individual patients provides a novel explanation for phenotypic heterogeneity among MCADD patients. Further development of personalised metabolic models is a promising direction to improve individualised risk assessment, management and monitoring for inborn errors of metabolism.
Keywords: Humans; Acyl-CoA Dehydrogenase/genetics; *Lipid Metabolism; Coenzyme A; *Lipid Metabolism, Inborn Errors/genetics

Hepatocytes reprogram liver macrophages involving control of TGF-beta activation, influencing liver regeneration and injury. - Wolf, S. D.; Ehlting, C.; Muller-Dott, S.; Poschmann, G.; Petzsch, P.; Lautwein, T.; Wang, S.; Helm, B.; Schilling, M.; Saez-Rodriguez, J.; Vucur, M.; Stuhler, K.; et al. (Hepatol Commun, 2023)
BACKGROUND: Macrophages play an important role in maintaining liver homeostasis and regeneration. However, it is not clear to what extent the different macrophage populations of the liver differ in terms of their activation state and which other liver cell populations may play a role in regulating the same. METHODS: Reverse transcription PCR, flow cytometry, transcriptome, proteome, secretome, single cell analysis, and immunohistochemical methods were used to study changes in gene expression as well as the activation state of macrophages in vitro and in vivo under homeostatic conditions and after partial hepatectomy. RESULTS: We show that F4/80+/CD11bhi/CD14hi macrophages of the liver are recruited in a C-C motif chemokine receptor (CCR2)-dependent manner and exhibit an activation state that differs substantially from that of the other liver macrophage populations, which can be distinguished on the basis of CD11b and CD14 expressions. Thereby, primary hepatocytes are capable of creating an environment in vitro that elicits the same specific activation state in bone marrow-derived macrophages as observed in F4/80+/CD11bhi/CD14hi liver macrophages in vivo. Subsequent analyses, including studies in mice with a myeloid cell-specific deletion of the TGF-beta type II receptor, suggest that the availability of activated TGF-beta and its downregulation by a hepatocyte-conditioned milieu are critical. Reduction of TGF-betaRII-mediated signal transduction in myeloid cells leads to upregulation of IL-6, IL-10, and SIGLEC1 expression, a hallmark of the activation state of F4/80+/CD11bhi/CD14hi macrophages, and enhances liver regeneration. CONCLUSIONS: The availability of activated TGF-beta determines the activation state of specific macrophage populations in the liver, and the observed rapid transient activation of TGF-beta may represent an important regulatory mechanism in the early phase of liver regeneration in this context.
Keywords: Animals; Mice; Gene Expression; Hepatocytes/metabolism; *Liver Regeneration; Macrophages/metabolism; *Transforming Growth Factor beta/metabolism